Solutions to problems in Cellular biophysics, vol. 2 - electrical properties - Weiss, Thomas Fischer (1996)

Molecular and Cellular Biophysics (Pure and Applied Physics) - Tuszynski, Jack A (2007)
Molecular and Cellular Biophysics (Pure and Applied Physics)

Cellular Biophysics. Electrical properties - Weiss, Thomas Fisher (Cellular Biophysics. Electrical properties, 1996)
Cellular Biophysics is a quantitatively oriented basic physiology text for seniorundergraduate and graduate students in bioengineering, biophysics, physiology, and neuroscienceprograms. It will also serve as a major reference work for biophysicists.Developed from the author'snotes for a course that he has taught at MIT for many years, these books provide a clear and logicalexplanation of the foundations of cell biophysics, teaching transport and the electrical propertiesof cells from a combined biological, physical, and engineering viewpoint.Each volume containsintroductory chapters that motivate the material and present it in a broad historical context.Important experimental results and methods are described. Theories are derived almost always fromfirst principles so that students develop an understanding of not only the predictions of the theorybut also its limitations. Theoretical results are compared carefully with experimental findings andnew results appear throughout. There are many time-tested exercises and problems as well asextensive lists of references.The volume on transport is unique in that no other text on thisimportant topic develops it clearly and systematically at the student level. It explains all theprincipal mechanisms by which matter is transported across cellular membranes and describes thehomeostatic mechanisms that allow cells to maintain their concentrations of solutes, their volume,and the potential across the membrane. Chapters are organized by individual transport mechanisms --diffusion, osmosis, coupled solute and solvent transport, carrier-mediated transport, and iontransport (both passive and active). A final chapter discusses the interplay of all these mechanismsin cellular homeostasis.

Perspectives on the agrochemical industry and agrochemical discovery - Sparks, Thomas C.; Lorsbach, Beth A. (Pest Management Science, 2017)
Agrochemicals have been critical to the production of food and fiber, as well as the control of vectors of disease. The need for the discovery and development of new agrochemicals continues unabated due to the loss of existing products through the development of resistance, the desire for products with more favorable environmental and toxicological profiles, shifting pest spectra, and changing agricultural needs and practices. As presented in the associated analysis of the agrochemical industry, the rising costs and complexities of agrochemical discovery have, in part, led to increasing consolidation, especially in the USA and Europe. However, as demonstrated by the present analysis, the discovery of new agrochemicals continues in spite of the challenges. © 2016 Society of Chemical Industry.
Keywords: agrochemical discovery; agrochemical industry; fungicide; herbicide; insecticide; pesticide discovery; resistance to pesticides

Propesticides and their use as agrochemicals - Jeschke, Peter (Pest Management Science, 2016)
The synthesis of propesticides is an important concept in design of modern agrochemicals with optimal efficacy, environmental safety, user friendliness and economic variability. Based on increasing knowledge of the biochemistry and genetics of major pest insects, weeds and agricultural pathogens, the search for selectivity has become an ever more important part of pesticide development and can be achieved by appropriate structural modifications of the active ingredient. Propesticides affect the absorption, distribution, metabolism and excretion parameters, which can lead to biological superiority of these modified active ingredients over their non-derivatised analogues. Various selected commercial propesticides testify to the successful utilisation of this concept in the design of agrochemicals. This review describes comprehensively the successful utilisation of propesticides and their role in syntheses of modern agrochemicals, exemplified by selected commercial products coming from different agrochemical areas.
Keywords: Active metabolites; Profungicides; Proherbicides; Proinsecticides; Propesticides; Prosafeners, mode of action

Evaluation of motor changes and toxicity of insecticides Fipronil and imidacloprid in Africanized Honey bees (Hymenoptera: Apidae) - Lunardi, J. S.; Zaluski, R.; Orsi, R. O. (Sociobiology, 2017)
Honey bees are important pollinators and are essential in beekeeping. Honey bees get exposed to systemic pesticides while foraging in contaminated fields, and it is important to know the toxicity (LD50) and evaluate the impacts of bees' exposure to these molecules. Fipronil and imidacloprid are systemic pesticides widely used in Brazil and other countries. The objective of this study was to determine the LD50 (24 hours) and evaluate motor changes in Africanized honey bee foragers exposed to lethal and sublethal doses of fipronil and imidacloprid. To determine the LD50, foraging honey bees were exposed by ingestion and contact to five doses of fipronil (Regent 800WG°) and imidacloprid (Appalus 200SC°) insecticides. After 24 hours of exposure, the number of dead bees was counted, and the results were subjected to probit analysis. The motor activity of bees exposed by ingestion or contact to LD50 and sublethal doses (1/500th of the LD50) of both pesticides was assessed 4 hours after exposure using a behavioral observation box. The ingestion and contact with LD50 of fipronil were 0.0528±0.0090 and 0.0054±0.0041 μg/bee, respectively; the ingestion and contact with LD50 of imidacloprid were 0.0809±0.0135 and 0.0626±0.0080 μg/bee, respectively. Bees exposed to lethal and sublethal doses of both insecticides experienced significant motor alterations compared to the control, except for exposure to sublethal doses of fipronil by contact. Fipronil and imidacloprid are highly toxic and promote motor changes in bees. Thus, it is important to establish management methods to reduce pollinators' exposure to these pesticides.
Keywords: Apis mellifera; Beekeeping; Behavior; Pollinators; Systemic pesticides; Toxicology

The impact of four widely used neonicotinoid insecticides on Tetragonisca angustula (Latreille) (Hymenoptera: Apidae) - Jacob, Cynthia Renata de Oliveira; Zanardi, Odimar Zanuzo; Malaquias, José Bruno; Souza Silva, Carina Aparecida; Yamamoto, Pedro Takao (Chemosphere, 2019)
Application of neonicotinoid insecticides on crops can reduce the pollination services and population levels of the stingless bee Tetragonisca angustula (Latreille) (Hymenoptera: Apidae) in Neotropical agroecosystems. However, the impact of these insecticides on this bee has not been fully investigated. This study assessed the susceptibility levels of T. angustula to four neonicotinoid insecticides (acetamiprid, imidacloprid, thiacloprid and thiamethoxam), widely used to manage pests on different crops, and their effects on locomotion of the bee. Neonicotinoids with the cyano radical caused lower bee mortality (assessed by mean lethal concentration, LC50), while those compounds with the nitro radical were highly harmful to T. angustula. Locomotion activity was strongly impaired in bees treated with thiacloprid and imidacloprid, while acetamiprid did not affect the locomotion activity, which was similar to the control. Application of thiamethoxam caused hyperactivity, as observed by increases of ∼4.5 and 5.0-fold in mean speed and distance traveled, respectively. These results suggest that applications of neonicotinoid insecticides can negatively affect the pollination activity of T. angustula. These results can also help to develop strategies to conserve these pollinators in agroecosystems.
Keywords: Acute toxicity; Stingless bee; Susceptibility; Walking behavior

Assessment of acute sublethal effects of clothianidin on motor function of honeybee workers using video-tracking analysis - Alkassab, Abdulrahim T.; Kirchner, Wolfgang H. (Ecotoxicology and Environmental Safety, 2018)
Sublethal impacts of pesticides on the locomotor activity might occur to different degrees and could escape visual observation. Therefore, our objective is the utilization of video-tracking to quantify how the acute oral exposure to different doses (0.1–2 ng/bee) of the neonicotinoid “clothianidin” influences the locomotor activity of honeybees in a time course experiment. The total distance moved, resting time as well as the duration and frequency of bouts of laying upside down are measured. Our results show that bees exposed to acute sublethal doses of clothianidin exhibit a significant increase in the total distance moved after 30 and 60 min of the treatment at the highest dose (2 ng/bee). Nevertheless, a reduction of the total distance is observed at this dose 90 min post-treatment compared to the distance of the same group after 30 min, where the treated bees show an arched abdomen and start to lose their postural control. The treated bees with 1 ng clothianidin show a significant increase in total distance moved over the experimental period. Moreover, a reduction in the resting time and increase of the duration and frequency of bouts of laying upside down at these doses are found. Furthermore, significant effects on the tested parameters are observed at the dose (0.5 ng/bee) first at 60 min post-treatment compared to untreated bees. The lowest dose (0.1 ng/bee) has non-significant effects on the motor activity of honeybees compared to untreated bees over the experimental period.
Keywords: Clothianidin; Honeybee; Locomotor activity; Sublethal; Tracking

The Neonicotinoid Imidacloprid Impairs Learning, Locomotor Activity Levels, and Sucrose Solution Consumption in Bumblebees (Bombus terrestris) - Paus-Knudsen, Julie Sørlie; Sveinsson, Henrik Andersen; Grung, Merete; Borgå, Katrine; Nielsen, Anders (Environmental Toxicology and Chemistry, 2023)
Bumblebees carry out the complex task of foraging to provide for their colonies. They also conduct pollination, an ecosystem service of high importance to both wild plants and entomophilous crops. Insecticides can alter different aspects of bumblebee foraging behavior, including the motivation to leave the hive, finding the right flowers, handling flowers, and the ability to return to the colony. In the present study, we assessed how the neonicotinoid imidacloprid affects bumblebees' foraging behavior after exposure to four different treatment levels, including field-realistic concentrations (0 [control], 1, 10, and 100 μg/L), through sucrose solution over 9 days. We observed the behavior of several free-flying bumblebees simultaneously foraging on artificial flowers in a flight arena to register the bees' complex behavior postexposure. To conduct a detailed assessment of how insecticides affect bumblebee locomotor behavior, we used video cameras and analyzed the recordings using computer vision. We found that imidacloprid impaired learning and locomotor activity level when the bumblebees foraged on artificial flowers. We also found that imidacloprid exposure reduced sucrose solution intake and storage. By using automated analyses of video recordings of bumblebee behavior, we identified sublethal effects of imidacloprid exposure at field-realistic doses. Specifically, we observed negative impacts on consumption of sucrose solution as well as on learning and locomotor activity level. Our results highlight the need for more multimodal approaches when assessing the sublethal effects of insecticides and plant protection products in general. Environ Toxicol Chem 2023;42:1337–1345. © 2023 SETAC.
Keywords: Behavior; Bumblebees; Imidacloprid; Movement; Object detection; Pesticides; Plant protection products; Pollinator

Toxicity and motor changes in africanized honey bees (Apis mellifera l.) exposed to fipronil and imidacloprid - Bovi, Thaís S.; Zaluski, Rodrigo; Orsi, Ricardo de Oliveira (Anais da Academia Brasileira de Ciencias, 2018)
This study evaluated the in vitro toxicity and motor activity changes in African-derived adult honey bees (Apis mellifera L.) exposed to lethal or sublethal doses of the insecticides fipronil and imidacloprid. Mortality of bees was assessed to determine the ingestion and contact lethal dose for 24 h using probit analysis. Motor activities in bees exposed to lethal (LD50) and sublethal doses (1/500thof the lethal dose) of both insecticides were evaluated in a behavioral observation box at 1 and 4 h. Ingestion and contact lethal doses of fipronil were 0.2316 ± 0.0626 and 0.0080 ± 0.0021 mg/bee, respectively. Ingestion and contact lethal doses of imidacloprid were 0.1079 ± 0.0375 and 0.0308 ± 0.0218 mg/bee, respectively. Motor function of bees exposed to lethal doses of fipronil and imidacloprid was impaired; exposure to sublethal doses of fipronil but not imidacloprid impaired motor function. The insecticides evaluated in this study were highly toxic to African-derived A. mellifera and caused impaired motor function in these pollinators.
Keywords: Contamination; Environment; Neonicotinoids; Pesticides; Phenylpyrazoles; Pollinators

The effects of field-realistic doses of imidacloprid on Melipona quadrifasciata (Apidae: Meliponini) workers - Brito, Pedro; Elias, Marcos; Silva-Neto, Carlos; Sujii, Edison; Silva, Daniela; Gonçalves, Bruno; Franceschinelli, & Edivani
The presence of Brazilian native bees can improve tomato production by increasing pollination effectiveness. However, the extensive use of pesticides in tomato cultures may be harmful to bees. Imidacloprid-based insecticides are used in tomato plantations because of its high efficiency against tomato pests. This study investigated the effects of oral intake of field-realistic concentrations of imidacloprid by M. quadrifasciata workers, a stingless native bee from Brazil and effective pollinators of tomato crops. The oral intake of sucrose syrup added with 10, 35, or 70 ppb of imidacloprid did not increase the mortality rate when compared with the control group. However, we observed a reduction in the workers' motility and food consumption. We also treated M. quadrifasciata workers with sucrose syrup mixed with an imidacloprid-based insecticide (Evidence 700 WG®, Bayer), with the final concentration of 250 ppb of imidacloprid. This treatment did not cause visible alterations of the intestine absorptive cells of the bees' midgut and did not increase DNA damage. Therefore, the observed reduction of food consumption and locomotion behavior of M. quadrifasciata workers may contribute to the global effort to understand the contribution of neonicotinoids on bees' population decline process.
Keywords: Comet assay; Electron microscopy; Insecticide; Neonicotinoids; Pollinators; Stingless bees

Sublethal exposure to neonicotinoids and related side effects on insect pollinators: honeybees, bumblebees, and solitary bees - Alkassab, Abdulrahim T.; Kirchner, Wolfgang H. (Journal of Plant Diseases and Protection, 2017)
Nowadays, there are increasing concerns about the bioavailability of neonicotinoids in the environment and possible exposure of nontarget organisms to these insecticides, their residues having been detected at different concentrations in many matrices, i.e., pollen, nectar, soil, water. Regarding the risk assessment process, there are still some information gaps about the exposure pathways and the possibility of various sublethal effects on insect pollinators. Recently, a clear rapprochement between the sublethal effects of different endpoints under laboratory conditions and field-realistic exposure level has been demonstrated. Here, we attempt to draw general portrayal about the current debate of the exposure to neonicotinoids and their impacts on pollinators. Depending on our extracted data from the published literature, we show that the lowest observed effect concentration under realistic field conditions in the most cases is higher than under laboratory conditions, which indicate that further long-term field research is required with consideration that our good understanding of the pollinators’ responses to sublethal exposure should be taken into account in the future experimental design in order to establish vigorous conclusions. We review currently available information in the published literature, presenting the reports about detected residues in relation to multiple ways of exposure and their potential consequences on insect pollinators and community dynamics. Nevertheless, we attempt to classify the sublethal effects depending on the different biological levels from genes to population. Moreover, we consider the field-realistic exposure level and critically analyze the laboratory as well as field studies to specify their physiological and behavioral effects. Additionally, synergistic effects of different factors, including exposure to neonicotinoids and their hazards on bees, will find special attention.
Keywords: Bees; Neonicotinoids; Risk assessment; Sublethal effects

The Neonicotinoid Insecticide Imidacloprid Disrupts Bumblebee Foraging Rhythms and Sleep - Tasman, Kiah; Rands, Sean A.; Hodge, James J.L. (iScience, 2020)
Neonicotinoids have been implicated in the large declines observed in insects such as bumblebees, an important group of pollinators. Neonicotinoids are agonists of nicotinic acetylcholine receptors that are found throughout the insect central nervous system and are the main mediators of synaptic neurotransmission. These receptors are important for the function of the insect central clock and circadian rhythms. The clock allows pollinators to coincide their activity with the availability of floral resources and favorable flight temperatures, as well as impact learning, navigation, and communication. Here we show that exposure to the field-relevant concentration of 10 μg/L imidacloprid caused a reduction in bumblebee foraging activity, locomotion, and foraging rhythmicity. Foragers showed an increase in daytime sleep and an increase in the proportion of activity occurring at night. This could reduce foraging and pollination opportunities, reducing the ability of the colony to grow and reproduce, endangering bee populations and crop yields.
Keywords: Animal Physiology; Behavioral Neuroscience; Biological Sciences; Ecology; Zoology

:00:46 AM All use subject to JSTOR Terms and Conditions - mellifera Author, Apis; Michelsen, Axel; Kirchner, Wolfgang H; Lindauer, Martin (Behavioral Ecology and Sociobiology, 1986)
JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Springer is collaborating with JSTOR to digitize, preserve and extend access to Behavioral Ecology and Sociobiology. Summary. Sound and vibrational signals exchanged by honeybees during the performance of wagging dances were simultaneously recorded by means of a microphone and a laser vibrometer. Previous descriptions of the 280-Hz sounds emitted by the dancing bee were confirmed, and no vibra-tional (substrate-borne) component could be detected. In contrast, the 320-Hz "begging sig-nals" (emitted by bees following a dancer and used as a request for food samples from the dancer) do vibrate the comb with peak-peak displacement amplitudes up to 1.5 Itm. Artificially-generated comb vibrations of sufficient amplitude cause bees standing on the comb to "freeze". The threshold for obtaining a detectable freezing response was measured for frequencies between 100 Hz and 3 kHz. At 320 Hz it is just below the amplitude of the natural begging signals. Thus it seems likely that these signals are received by the bees as vibrations of the comb. The propagation velocity of waves, damping, and mechanical input impedance of honeybee combs were studied. These results, combined with the observed amplitudes of the begging signals, support the assumption that the begging signals are generated with the flight muscles. The begging signal propagates as a bending wave. The attenuation of the begging signal with distance is relatively small, so the amplitude of the signal probably needs to be carefully adjusted in order to restrict the range of the communication.

On the importance of the sound emitted by honey bee hives - Terenzi, Alessandro; Cecchi, Stefania; Spinsante, Susanna (Veterinary Sciences, 2020)
Recent years have seen a worsening in the decline of honey bees (Apis mellifera L.) colonies. This phenomenon has sparked a great amount of attention regarding the need for intense bee hive monitoring, in order to identify possible causes, and design corresponding countermeasures. Honey bees have a key role in pollination services of both cultivated and spontaneous flora, and the increase in bee mortality could lead to an ecological and economical damage. Despite many smart monitoring systems for honey bees and bee hives, relying on different sensors and measured quantities, have been proposed over the years, the most promising ones are based on sound analysis. Sounds are used by the bees to communicate within the hive, and their analysis can reveal useful information to understand the colony health status and to detect sudden variations, just by using a simple microphone and an acquisition system. The work here presented aims to provide a review of the most interesting approaches proposed over the years for honey bees sound analysis and the type of knowledge about bees that can be extracted from sounds.
Keywords: Bee hive monitoring; Queen bee detection; Real-time monitoring; Sound analysis; Sound measurement; Swarming detection

UC San Diego UC San Diego Previously Published Works Title The complex world of honey bee vibrational signaling: A response to Permalink https://escholarship.org/uc/item/6r23s4mj Publication Date - Bell, Heather; Kietzman, Parry; Nieh, James (2017)

Honey bee workers generate low-frequency vibrations that are reliable indicators of their activity level - Hrncir, Michael; Maia-Silva, Camila; Farina, Walter M. (Journal of Comparative Physiology A: Neuroethology, Sensory, Neural, and Behavioral Physiology, 2019)
In social insects, the tuning of activity levels among different worker task groups, which constitutes a fundamental basis of colony organization, relies on the exchange of reliable information on the activity level of individuals. The underlying stimuli, however, have remained largely unexplored so far. In the present study, we describe low-frequency thoracic vibrations generated by honey bee workers (Apis mellifera) within the colony, whose velocity amplitudes and main frequency components significantly increased with the level of an individual’s activity. The characteristics of these vibrations segregated three main activity level-groups: foragers, active hive bees, and inactive hive bees. Nectar foragers, moreover, modulated their low-frequency vibrations during trophallactic food unloading to nestmates according to the quality of the collected food. Owing to their clear association with the activity level of an individual and their potential perceptibility during direct contacts, these low-frequency thoracic vibrations are candidate stimuli for providing unambiguous local information on the motivational status of honey bee workers.
Keywords: Apis mellifera; Mechanical cues; Motivational state; Social insects; Vibratory communication

The neonicotinoid pesticide, imidacloprid, affects Bombus impatiens (bumblebee) sonication behavior when consumed at doses below the LD50 - Switzer, Callin M.; Combes, Stacey A. (Ecotoxicology, 2016)
We investigated changes in sonication (or buzz-pollination) behavior of Bombus impatiens bumblebees, after consumption of the neonicotinoid pesticide, imidacloprid. We measured sonication frequency, sonication length, and flight (wing beat) frequency of marked bees collecting pollen from Solanum lycopsersicum (tomato), and then randomly assigned bees to consume 0, 0.0515, 0.515, or 5.15 ng of imidacloprid. We recorded the number of bees in each treatment group that resumed sonication behavior after consuming imidacloprid, and re-measured sonication and flight behavior for these bees. We did not find evidence that consuming 0.0515 ng imidacloprid affected the sonication length, sonication frequency, or flight frequency for bees that sonicated after consuming imidacloprid; we were unable to test changes in these variables for bees that consumed 0.515 or 5.15 ng because we did not observe enough of these bees sonicating after treatment. We performed Cox proportional hazard regression to determine whether consuming imidacloprid affected the probability of engaging in further sonication behavior on S. lycopersicum and found that bumblebees who consumed 0.515 or 5.15 ng of imidacloprid were significantly less likely to sonicate after treatment than bees who consumed no imidacloprid. At the end of the experiment, we classified bees as dead or alive; our data suggest a trend of increasing mortality with higher doses of imidacloprid. Our results show that even modest doses of imidacloprid can significantly affect the likelihood of bumblebees engaging in sonication, a behavior critical for the pollination of a variety of crops and other plants.
Keywords: Buzz pollination; Native bees; Pollination; Solanum; Tomato; Vibration

Bee declines driven by combined Stress from parasites, pesticides, and lack of flowers - Goulson, Dave; Nicholls, Elizabeth; Botías, Cristina; Rotheray, Ellen L. (Science, 2015)
Bees are subject to numerous pressures in the modern world. The abundance and diversity of flowers has declined; bees are chronically exposed to cocktails of agrochemicals, and they are simultaneously exposed to novel parasites accidentally spread by humans. Climate change is likely to exacerbate these problems in the future. Stressors do not act in isolation; for example, pesticide exposure can impair both detoxification mechanisms and immune responses, rendering bees more susceptible to parasites. It seems certain that chronic exposure to multiple interacting stressors is driving honey bee colony losses and declines of wild pollinators, but such interactions are not addressed by current regulatory procedures, and studying these interactions experimentally poses a major challenge. In the meantime, taking steps to reduce stress on bees would seem prudent; incorporating flower-rich habitat into farmland, reducing pesticide use through adopting more sustainable farming methods, and enforcing effective quarantine measures on bee movements are all practical measures that should be adopted. Effective monitoring of wild pollinator populations is urgently needed to inform management strategies into the future.

Agrochemicals interact synergistically to increase bee mortality - Siviter, Harry; Bailes, Emily J.; Martin, Callum D.; Oliver, Thomas R.; Koricheva, Julia; Leadbeater, Ellouise; Brown, Mark J.F. (Nature, 2021)
Global concern over widely documented declines in pollinators1–3 has led to the identification of anthropogenic stressors that, individually, are detrimental to bee populations4–7. Synergistic interactions between these stressors could substantially amplify the environmental effect of these stressors and could therefore have important implications for policy decisions that aim to improve the health of pollinators3,8,9. Here, to quantitatively assess the scale of this threat, we conducted a meta-analysis of 356 interaction effect sizes from 90 studies in which bees were exposed to combinations of agrochemicals, nutritional stressors and/or parasites. We found an overall synergistic effect between multiple stressors on bee mortality. Subgroup analysis of bee mortality revealed strong evidence for synergy when bees were exposed to multiple agrochemicals at field-realistic levels, but interactions were not greater than additive expectations when bees were exposed to parasites and/or nutritional stressors. All interactive effects on proxies of fitness, behaviour, parasite load and immune responses were either additive or antagonistic; therefore, the potential mechanisms that drive the observed synergistic interactions for bee mortality remain unclear. Environmental risk assessment schemes that assume additive effects of the risk of agrochemical exposure may underestimate the interactive effect of anthropogenic stressors on bee mortality and will fail to protect the pollinators that provide a key ecosystem service that underpins sustainable agriculture.

Bees and pesticides: the research impact and scientometrics relations - Abati, Raiza; Sampaio, Amanda Roberta; Mendes, Rodrigo; Maciel, Antunes; Colombo, Fernanda Caroline; Libardoni, Gabriela; Battisti, Lucas; Lozano, Everton Ricardi; De, Nédia; Ghisi, Castilhos; Martins Costa-Maia, Fabiana; Potrich, Michele (2021)
Bees are fundamental insects in agroecosystems, mainly due to pollination. However, its decline has been observed in recent years, and the contamination by pesticides is suspected to be responsible. This relationship is the objective of our research, which is the first scientometric study on this subject. The data were obtained from the Web of Science database (1231) and were analyzed using Microsoft Office Excel and CiteSpace. The results point to a significant increase in pesticide and bee reseach in the last 15 years in the most influential scientific journals. The USA and France have the largest number of publications and a moderade relationship between this trait and GDP (gross domestic product) was observed (r = 0.80; r 2 = 0.60). There is no correlation between the use of pesticides and studies of the effects on pollinators and the use of pesticides and the countries' GDP. In general, studies have shown the negative effects of the contamination by pesticides on bees; however, most publications are with bees of the Apis genus, and therefore it is necessary to explore the action of pesticides on bumble bees and wild bees, as well furthur as studies are needed regarding the sublethal effects of these products on bees as the number of molecules used in the management of agricultural crops is vast.
Keywords: Pollination. Environmental. Honey bee. Toxicity. Insecticide. CiteSpace

Acute oral exposure to imidacloprid induces apoptosis and autophagy in the midgut of honey bee Apis mellifera workers - Carneiro, Lenise Silva; Martinez, Luis Carlos; Oliveira, André Henrique de; Cossolin, Jamile Fernanda Silva; Resende, Matheus Tudor Cândido Santos de; Gonçalves, Wagner Gonzanga; Medeiros-Santana, Luanda; Serrão, José Eduardo (Science of the Total Environment, 2022)
The honey bee Apis mellifera is an important pollinator that increases the yield and quality of crops. In recent years, honey bee populations have declined in some parts of the world, which has been associated with several causes, including pesticides used in agriculture. Neonicotinoids are neurotoxic insecticides widely used in the world with systemic action mode contaminating nectar and pollen that may be consumed by bees. This study evaluated the side effects of imidacloprid in the midgut of A. mellifera after acute oral exposure. Toxicity, histopathology, cytotoxicity, and expression of autophagy-related gene atg1 were evaluated in honey bee workers orally exposed to imidacloprid. The estimated imidacloprid LC50 was 1.44 mg L−1. The midgut epithelium of bees fed on imidacloprid LC50 has the occurrence of cytoplasm vacuoles, enlarged intercellular spaces, disorganization of the striated border, and nuclear pyknosis, with an organ injury index that increases with time exposure. The midgut digestive cells of treated bees have apical protrusions, damaged mitochondria, and autophagosomes that were characterized for content with organelle debris and high expression of atg1. These features indicate the occurrence of high cell death in the midgut of workers exposed to imidacloprid, which may affect the digestibility the physiology of the insect.
Keywords: Apoptosis; Autophagy; Bee; Imidacloprid; Midgut

A new design for honey bee hoarding cages for laboratory experiments - Köhler, Angela; Nicolson, Susan W.; Pirk, Christian W.W. (Journal of Apicultural Research, 2013)
Keywords: Apis mellifera scutellata; Feeders; Group size; Honeycomb; Polycarbonate cage

A new design of bee cage for laboratory experiments: nutritional assessment of supplemental diets in honey bees (Apis mellifera) - Yang, Kai Chieh; Peng, Zhi Wei; Lin, Chun Hsien; Wu, Ming Cheng (Apidologie, 2021)
We designed a cage that can maintain adult bees for 21 days with about 90% survival rate, in addition to facilitating the changing of sucrose syrup and beebread, and collection of live and dead bees without disturbing or releasing bees. The consumption rates of bee pollen diet and sucrose syrup for groups of 50–200 honey bees were recorded for 21 days after emergence. The bees consumed the bee pollen diet mainly at the age of 1–9 days. Regular consumption of sucrose syrup was observed among all bee groups throughout the 21 days. Furthermore, the nutritional responses of nurse bees—specifically, the expressions of major royal jelly protein 1 (mrjp1) in the head and vitellogenin (vg) in the abdomen—upon the provision of five single-supplemental diets were evaluated. We aimed to improve the usability of bee cages by elucidating the food consumption of bees and the relationship between nutritional gene expression and the ingestion of each single-protein diet.
Keywords: Bee cage; Bee pollen substitutes; Major royal jelly protein 1; Vitellogenin

Standard methods for maintaining adult Apis mellifera in cages under in vitro laboratory conditions - Williams, Geoffrey R.; Alaux, Cédric; Costa, Cecilia; Csáki, Támas; Doublet, Vincent; Eisenhardt, Dorothea; Fries, Ingemar; Kuhn, Rolf; McMahon, Dino P.; Medrzycki, Piotr; Murray, Tomás E.; Natsopoulou, Myrsini E.; et al. (Journal of Apicultural Research, 2013)
Adult honey bees are maintained in vitro in laboratory cages for a variety of purposes. For example, researchers may wish to perform experiments on honey bees caged individually or in groups to study aspects of parasitology, toxicology, or physiology under highly controlled conditions, or they may cage whole frames to obtain newly emerged workers of known age cohorts. Regardless of purpose, researchers must manage a number of variables, ranging from selection of study subjects (e.g. honey bee subspecies) to experimental environment (e.g. temperature and relative humidity). Although decisions made by researchers may not necessarily jeopardize the scientific rigour of an experiment, they may profoundly affect results, and may make comparisons with similar, but independent, studies difficult. Focusing primarily on workers, we provide recommendations for maintaining adults under in vitro laboratory conditions, whilst acknowledging gaps in our understanding that require further attention. We specifically describe how to properly obtain honey bees, and how to choose appropriate cages, incubator conditions, and food to obtain biologically relevant and comparable experimental results. Additionally, we provide broad recommendations for experimental design and statistical analyses of data that arises from experiments using caged honey bees. The ultimate goal of this, and of all COLOSS BEEBOOK papers, is not to stifle science with restrictions, but rather to provide researchers with the appropriate tools to generate comparable data that will build upon our current understanding of honey bees Copyright © IBRA 2013.
Keywords: Apis mellifera; BEEBOOK; COLOSS; Cage; Colony losses; Hoarding; Honey bee; In vitro; Laboratory; Nosema; Toxicology

OECD GUIDELINES FOR THE TESTING OF CHEMICALS Honeybees, Acute Oral Toxicity Test (1998)

PROPOSAL FOR A NEW GUIDELINE FOR (2016)

OCDE guideline for the testing of chemicals honey bee (Apis mellifera) - OCDE (2017)

Improved protocols for testing agrochemicals in bees Deliverable D3.2 CREA-AA, 2 MLU, 3 RHUL, 4 EMU, 5 INRA, 6 UM, 7 SLU and 8 UBERN PoshBee Pan-european assessment, monitoring, and mitigation of stressors on the health of bees - Medrzycki, Piotr; Hellström, Sara; Straw, Edward; Linguadoca, Alberto; Jürison, Margret; Alaux, Cedric; Barascou, Lena; Brown, Mark; Costa, Cecilia; De La Rúa, Pilar; Rodrigues De Miranda, Joachim; Di Prisco, Gennaro; et al. (2021)

Proposal of a new OECD guideline for the testing of chemicals

Towards precision nutrition: A novel concept linking phytochemicals, immune response and honey bee health - Negri, Pedro; Villalobos, Ethel; Szawarski, Nicolás; Damiani, Natalia; Gende, Liesel; Garrido, Melisa; Maggi, Matías; Quintana, Silvina; Lamattina, Lorenzo; Eguaras, Martin (Insects, 2019)
The high annual losses of managed honey bees (Apis mellifera) has attracted intensive attention, and scientists have dedicated much effort trying to identify the stresses affecting bees. There are, however, no simple answers; rather, research suggests multifactorial effects. Several works have been reported highlighting the relationship between bees’ immunosuppression and the effects of malnutrition, parasites, pathogens, agrochemical and beekeeping pesticides exposure, forage dearth and cold stress. Here we analyze a possible connection between immunity-related signaling pathways that could be involved in the response to the stress resulted from Varroa-virus association and cold stress during winter. The analysis was made understanding the honey bee as a superorganism, where individuals are integrated and interacting within the colony, going from social to individual immune responses. We propose the term “Precision Nutrition” as a way to think and study bees’ nutrition in the search for key molecules which would be able to strengthen colonies’ responses to any or all of those stresses combined.
Keywords: Apis mellifera; Cold stress; Immunity; Nutrition; Signaling pathways; Varroa

Context-Dependent Effect of Dietary Phytochemicals on Honey Bees Exposed to a Pesticide, Thiamethoxam - Seshadri, Arathi; Bernklau, Elisa (Journal of Insect Science, 2021)
Honey bees continue to face challenges relating to the degradation of natural flowering habitats that limit their access to diverse floral resources. While it is known that nectar and pollen provide macronutrients, flowers also contain secondary metabolites (phytochemicals) that impart benefits including increased longevity, improved gut microbiome abundance, and pathogen tolerance. Our study aims to understand the role of phytochemicals in pesticide tolerance when worker bees were fed with sublethal doses (1 ppb and 10 ppb) of thiamethoxam (TMX), a neonicotinoid, in 20% (w/v) sugar solution supplemented with 25 ppm of phytochemicals - caffeine, kaempferol, gallic acid, or p-coumaric acid, previously shown to have beneficial impacts on bee health. The effect of phytochemical supplementation during pesticide exposure was context-dependent. With 1 ppb TMX, phytochemical supplementation increased longevity but at 10 ppb TMX, longevity was reduced suggesting a negative synergistic effect. Phytochemicals mixed with 1 ppb TMX increased mortality in bees of the forager-age group but with 10 ppb TMX, mortality of the inhive-age group increased, implying the possibility of accumulation effect in lower sublethal doses. Given that the phytochemical composition of pollen and nectar varies between plant species, we suggest that the negative impacts of agrochemicals on honey bees could vary based on the phytochemicals in pollen and nectar of that crop, and hence the effects may vary across crops. Analyzing the phytochemical composition for individual crops may be a necessary first step prior to determining the appropriate dosage of agrochemicals so that harm to bees Apis mellifera L. is minimized while crop pests are effectively controlled.
Keywords: honey bee; phytochemical; plant-pollinator interaction; pollinator; synergism; thiamethoxam

Dietary phytochemicals alter hypopharyngeal gland size in honey bee (Apis mellifera L.) workers - Niño, Elina L.; Yokota, Seiji; Stacy, William H.O.; Arathi, H. S. (Heliyon, 2022)
Honey bees are the most efficient pollinators of several important fruits, nuts and vegetables and are indispensable for the profitable production of these crops. Health and performance of honey bee colonies have been declining for decades due to a combination of factors including poor nutrition, agrochemicals, pests and diseases. Bees depend on a diversity of plants for nutrition as pollen is the predominant protein and lipid source, and nectar, the source of carbohydrates for larval development. Additionally, pollen and nectar also contain small amounts of plant secondary metabolites or phytochemicals that are primarily plant defense compounds. Bees have coevolved to benefit from these compounds as seen by the improved longevity, pathogen tolerance and gut microbiome abundance in worker bees whose diets were supplemented with select phytochemicals. Here we investigate the impact of four phytochemicals, known to benefit bees, – caffeine, kaempferol, gallic acid and p-coumaric acid, on hypopharyngeal gland (HPG) size of nurse bees. Newly emerged bees were provided with 25 ppm of each of the four phytochemicals in 20% (w/v) sucrose solution and the size of HPGs were measured after a 10 d period. Bees that received p-coumaric acid or kaempferol showed a significant increase in HPG size. A significant decrease in HPG size was seen in bees receiving caffeine or gallic acid. The implication of our findings on worker bee ontogeny, transitioning from nurses to foragers and relevance to foraging related competencies are discussed. It is critical that bees have access to phytochemicals to ensure colony health and performance. Such access could be through natural habitats that provide a diversity of pollen and nectar sources or through dietary supplements for bee colonies.
Keywords: Caffeine; Gallic acid; Honey bees; Hypopharyngeal glands (HPG); Kaempferol; Phytochemicals; p-coumaric acid

Impacts of dietary phytochemicals in the presence and absence of pesticides on longevity of honey bees (Apis mellifera) - Liao, Ling Hsiu; Wu, Wen Yen; Berenbaum, May R. (Insects, 2017)
Because certain flavonols and phenolic acids are found in pollen and nectar of most angiosperms, they are routinely ingested by Apis mellifera, the western honey bee. The flavonol quercetin and the phenolic acid p-coumaric acid are known to upregulate detoxification enzymes in adult bees; their presence or absence in the diet may thus affect the toxicity of ingested pesticides. We conducted a series of longevity assays with one-day-old adult workers to test if dietary phytochemicals enhance longevity and pesticide tolerance. One-day-old bees were maintained on sugar syrup with or without casein (a phytochemical-free protein source) in the presence or absence of quercetin and p-coumaric acid as well as in the presence or absence of two pyrethroid insecticides, bifenthrin and β-cyfluthrin. Dietary quercetin (hazard ratio, HR = 0.82), p-coumaric acid (HR = 0.91) and casein (HR = 0.74) were associated with extended lifespan and the two pyrethroid insecticides, 4 ppm bifenthrin (HR = 9.17) and 0.5 ppm (β -cyfluthrin (HR = 1.34), reduced lifespan. Dietary quercetin enhanced tolerance of both pyrethroids; p-coumaric acid had a similar effect trend, although of reduced magnitude. Casein in the diet appears to eliminate the life-prolonging effect of p-coumaric acid in the absence of quercetin. Collectively, these assays demonstrate that dietary phytochemicals influence honey bee longevity and pesticide stress; substituting sugar syrups for honey or yeast/soy flour patties may thus have hitherto unrecognized impacts on adult bee health.
Keywords: Bifenthrin; Detoxification; Lifespan; Nutrition; P-coumaric acid; Quercetin; β-cyfluthrin

Dietary supplementation with phytochemicals improves diversity and abundance of honey bee gut microbiota - Geldert, C.; Abdo, Z.; Stewart, J. E.; Arathi, H. S. (Journal of Applied Microbiology, 2021)
Aim: Determine the impact of beneficial phytochemicals on diversity and abundance of the gut microbiome in the honey bee (Apis mellifera). Methods and Results: Eight-day-old honey bee workers were fed 25 ppm of phytochemical (caffeine, gallic acid, p-coumaric acid or kaempferol) in 20% sucrose. Guts of bees collected at 3 and 6 days were excised and subjected to next-generation sequencing for bacterial 16S and fungal ITS regions. Although phytochemical supplementation fostered gut microbial diversity and abundance, the patterns differed between phytochemicals and there was a temporal stabilization of the bacterial community. While bacterial and fungal communities responded differently, all phytochemical treatments displayed increased abundance of the most represented bacterial genera, Snodgrassella sp. and Lactobacillus sp. Conclusions: Phytochemical supplementation improves gut microbial diversity and abundance, reiterating the need for diverse habitats that provide bees with access to pollen and nectar rich in these micronutrients. Diverse gut microbiota can provide a strong line of defense for bees against biotic stressors while improving worker bee lifespan. Significance and Impact of the Study: This is the first report on the impact of phytochemical supplementation on gut microbiota in honey bees and these findings have implications for strategic hive management through standardization of effective phytochemical and probiotic feed supplements.
Keywords: Apis mellifera; genomics; gut microbiota; honey bee; next-generation sequencing; nutrition; phytochemicals; plant–pollinator interactions

Metabolomics unveils the influence of dietary phytochemicals on residual pesticide concentrations in honey bees - Ardalani, Hamidreza; Vidkjær, Nanna Hjort; Kryger, Per; Fiehn, Oliver; Fomsgaard, Inge S. (Environment International, 2021)
The losses of honey bee colonies and declines of other insect pollinators have been associated with negative effects of pesticides. Honey bees as well as other pollinators are nectar and pollen foragers and thus are exposed to an extensive range of phytochemicals. Understanding the synergistic, additive, and antagonistic effects of plant secondary metabolites and pesticides in honey bees may help to protect honey bee colonies against agrochemicals. In this study, we used untargeted metabolomics to investigate the impact of dietary phytochemical composition on the residual concentration of three pesticides: imidacloprid, tau-fluvalinate and tebuconazole in exposed honey bees. Honey bees were given different diets based on pollen or nectar from four plants: Reseda odorata, Borago officinalis, Phacelia tanacetifolia, and Trifolium repens for two days. Thereafter, they were orally exposed to 10 ng/bee imidacloprid or contact-exposed to 0.9 μg/bee tau-fluvalinate or 5 μg/bee tebuconazole. After 1 h of oral exposure or 24 h of contact exposure, the honey bees were anaesthetised with CO2, sacrificed by freezing, extracted with a validated QuEChERS method, and residual pesticide concentrations were determined by LC-QTRAP-MS/MS. The phytochemical composition in the given diets were profiled with an UHPLC-Q Exactive-MS/MS. The results revealed that the dietary phytochemical composition has a noteworthy influence on the concentration of residual pesticides in honey bees. The correlation coefficient analysis demonstrated that flavonoids have a reducing effect on the residual concentration of imidacloprid and tau-fluvalinate in honey bees. The results also highlighted that exposure to imidacloprid impaired the metabolism of sugars in honey bees. Exploiting flavonoid-rich plants may protect honey bees against pesticides and hold promise as forage plants in future beekeeping.
Keywords: Flavonoid; Honey bee; Imidacloprid; Metabolomics; Neonicotinoid; Pesticide

Dietary quercetin impacts the concentration of pesticides in honey bees - Ardalani, Hamidreza; Vidkjær, Nanna Hjort; Laursen, Bente B.; Kryger, Per; Fomsgaard, Inge S. (Chemosphere, 2021)
Honey bees are important pollinators and are subject to numerous stressors, such as changing floral resources, parasites, and agrochemical exposure. Pesticide exposure has been linked to the decline in the global honey bee population. We have limited knowledge of the metabolic pathways and synergistic effects of xenobiotics in bees. Quercetin is one of the most abundant phytochemicals in plants and is therefore abundant in the honey bee diet. Quercetin can upregulate the detoxification system in honey bees; however, it is still unknown to what extent quercetin ingestion can reduce the content of absorbed pesticides. In this study, we investigated the effect of dietary quercetin on the contents of three pesticides in honey bees: imidacloprid (insecticide), tebuconazole (fungicide), and tau-fluvalinate (insecticide and acaricide). Bees were divided into two main groups and fed either quercetin-sucrose paste or only sucrose for 72 h. Thereafter, they were orally exposed to ∼10 ng/bee imidacloprid or contact-exposed to ∼0.9 μg/bee tau-fluvalinate or ∼5.2 μg/bee tebuconazole. After 1 h of oral exposure or 24 h of contact exposure, the bees were anaesthetised with CO2, sacrificed by freezing, and extracted with a validated QuEChERS method. Subsequently, the concentrations of the three pesticides and quercetin in the bees were determined with a triple quadrupole tandem mass spectrometer coupled to an HPLC system. No significant effect on the concentration of tebuconazole or tau-fluvalinate was observed in bees fed quercetin. Intake of quercetin led to a reduction in the concentration of imidacloprid in honey bees. Quercetin-rich plants may be exploited in future beekeeping.
Keywords: Honey bee; Imidacloprid; Neonicotinoid; Pesticide; Quercetin

Chemical Control of Invasive Weed View project Drug Delivery and Cosmetics Lab View project - Gulzar, Asim; Shah, Ali; Fatima, Marium; Tariq, Muhammad (2016)
The user has requested enhancement of the downloaded file.

A method to quantify and analyze the foraging activity of honey bees: Relevance to the sublethal effects induced by systemic insecticides - Colin, M. E.; Bonmatin, J. M.; Moineau, I.; Gaimon, C.; Brun, S.; Vermandere, J. P. (Archives of Environmental Contamination and Toxicology, 2004)
The assessment of agropharmaceuticals' side effects requires more realistic simulations of field conditions than those deduced from the dose-lethality relation obtained under laboratory conditions. Because the presence of sublethal doses or concentrations may also alter the behavior of foraging insects, we attempted to devise a quantifiable and accurate protocol for evidencing various alterations in free-flying bees. Such a protocol was illustrated by testing new classes of systemic insecticides. The protocol focused on video recording to quantify the foraging activity of small colonies of honey bees confined in insect-proof tunnels. The basis of the protocol was not the colony itself but the change in each colony on a specific day and between days. First, the paradigms of attendance at a safe feeding source were established by observing 8 control colonies at different times of the season during 5 days after the necessary forager training was accomplished. Second, on three different colonies we considered the paradigms on the control day before contamination and during 4 days after the feeding source was contaminated. During the same period, one more colony was exclusively fed with safe food to serve as control. Two plant-systemic insecticides were tested at contamination levels 70 times lower than the 50% of the lethal concentration. Imidacloprid, at 6 μg/kg, clearly induced a decrease in the proportion of active bees. Fipronil, at 2 μg/kg, induced an additional decrease in attendance at the feeder. Such levels are still higher than the corresponding lowest observable effect concentration (LOEC). Our protocol, which provided intermediate conditions between field and laboratory conditions, allowed the quantification, with an enhanced level of sensitivity, of sublethal effects on foraging bees.

Melatonin enhances the antioxidant capacity to rescue the honey bee Apis mellifera from the ecotoxicological effects caused by environmental imidacloprid - Li, Zhi; Duan, Jiaxin; Chen, Lanchun; Wang, Yuedi; Qin, Qiqian; Dang, Xiaoqun; Zhou, Zeyang (Ecotoxicology and Environmental Safety, 2022)
Imidacloprid severely poisons the nontarget insect honey bee Apis mellifera. Few treatments are available to mitigate the adverse effects of imidacloprid. The primary concern is that the molecular understanding of imidacloprid toxicity is not comprehensive enough. Oxidative stress is the primary pathophysiological mechanism by which pesticides cause high mortality. Our pilot study found for the first time that imidacloprid stimulates bee brains to secrete melatonin, a free radical scavenger. However, the molecular basis for imidacloprid toxicity and the role of melatonin in coping with imidacloprid have not been systematically investigated in bees. This study administered an environmental dose of imidacloprid (36 ng/bee) orally to A. mellifera. The detoxification gene cytochrome P450 CYP4G11 was significantly induced. However, potent cytotoxicity of imidacloprid suppressed the expression of the antioxidants catalase (CAT) and thioredoxin reductase (TrxR), and the activity of guaiacol peroxidase (GPX), superoxide dismutase (SOD), and reduced glutathione (GSH) was not induced. The levels of reactive oxygen species (ROS) and the lipid peroxidation marker malondialdehyde (MDA) were increased. The expression of the apoptotic genes cysteinyl aspartate specific proteinase (Caspase-3) and apoptosis inducing factor (AIF) increased, and the apoptotic features of midgut cells were prominently apparent. These results suggest that imidacloprid disrupts the bee antioxidant system, causing severe oxidative stress and tissue damage and ultimately leading to apoptosis. Significantly, however, imidacloprid exposure also stimulated bee brains to continuously secrete melatonin. Further preadministration of exogenous melatonin (200 ng/bee) orally to bees significantly reversed and enhanced the activity of the imidacloprid-suppressed antioxidants CAT, SOD, and GSH, which allowed imidacloprid-induced ROS accumulation to be effectively alleviated. The MDA content, apoptotic genes Caspase-3 and AIF, and detoxification gene CYPG411 expression were restored to normalization; midgut cell damage, apoptosis, and mortality were significantly reduced. These findings strongly suggest that melatonin enhanced bee antioxidant capacity, thus attenuating oxidative stress and apoptosis to confer imidacloprid tolerance to honey bees. Melatonin secretion may be a defense mechanism to mitigate imidacloprid toxicity.
Keywords: Antioxidant; Apis mellifera; Imidacloprid; Melatonin; Oxidative stress

Relevance of wild and managed bees for human well-being - Klein, Alexandra Maria; Boreux, Virginie; Fornoff, Felix; Mupepele, Anne Christine; Pufal, Gesine (Current Opinion in Insect Science, 2018)
Wild and managed bees provide pollination services to both crops and wild plants, and a variety of other services from which humans benefit. We summarize the most important and recent findings on bees as providers of provisioning, regulating and cultural ecosystem services. With comprehensive literature searches, we first identified ten important bee species for global pollination of crops, which include wild and managed honey bees, bumble bees, orchard-, cucumber- and longhorn bees. We second summarized bee-dependent ecosystem services to show how bees substantially contribute to food security, medical resources, soil formation or spiritual practices, highlighting their wide range of benefits for human well-being and to identify future research needs.

Impacts of honeybee density on crop yield: A meta-analysis - Rollin, Orianne; Garibaldi, Lucas A. (Journal of Applied Ecology, 2019)
There is increasing recognition that pollination deficits are limiting crop yields world-wide. However, management strategies for optimal insect pollination are still unclear for most crops. Current management focuses on providing high densities of honeybees, but recommended densities are highly variable, even within single crops and cultivars. We performed an extensive literature search to record honeybee densities (colony density and/or flower visitation rates) and crop productivity (fruit set, seed set, fruit weight and/or yield). Effect sizes were represented as the difference in crop productivity between the two most extreme levels of honeybee densities. Out of 795 reviewed studies, only 22 analysed the effect of at least two levels of honeybee densities on crop productivity (reporting 60 resulting effect sizes in total). Moreover, few recommendations for crop pollination management are based on results from controlled experimental designs, and with comparable methodology. We found that both colony density and visitation rates increased all the productivity variables. However, effects were nonlinear for visitation rates, suggesting that there is an optimum (mean of 8–10 visits per flower) beyond which more honeybees are not beneficial (and can even be detrimental) for crop productivity. Effect sizes for visitation rates were greater than that for colony densities, suggesting that visitation rates are a more direct measure of the pollination process. Data on the relation between colony density and visitation rates are lacking. Interestingly, effect sizes for visitation rates were greater for crops with separate sexes than those with hermaphroditic flowers; therefore, the benefits of honeybee pollination vary according to the crop biology. Synthesis and applications. Current practices for crop pollination assume that more honeybees are always better for crop yield, even if the effect of this management on crop production still unclear. In contrast, our analyses suggest that there is an optimum for honeybee densities. Despite the importance of honeybees and pollinator-dependent crops world-wide, there is a lack of studies designed for finding such an optimal level of crop pollination. Our analyses further suggest that visitation rates could be used as a proxy to guide management recommendations such as colony density and spatial arrangement.
Keywords: crop yield; fruit set; fruit weight; honeybee colony density; pollination; seed set; visitation rate

Pesticide mixtures detected in crop and non-target wild plant pollen and nectar - Zioga, Elena; White, Blánaid; Stout, Jane C. (Science of the Total Environment, 2023)
Cultivation of mass flowering entomophilous crops benefits from the presence of managed and wild pollinators, who visit flowers to forage on pollen and nectar. However, management of these crops typically includes application of pesticides, the presence of which may pose a hazard for pollinators foraging in an agricultural environment. To determine the levels of potential exposure to pesticides, their presence and concentration in pollen and nectar need assessing, both within and beyond the target crop plants. We selected ten pesticide compounds and one metabolite and analysed their occurrence in a crop (Brassica napus) and a wild plant (Rubus fruticosus agg.), which was flowering in field edges. Nectar and pollen from both plants were collected from five spring and five winter sown B. napus fields in Ireland, and were tested for pesticide residues, using QuEChERS and Liquid Chromatography tandem mass spectrometry (LC-MS/MS). Pesticide residues were detected in plant pollen and nectar of both plants. Most detections were from fields with no recorded application of the respective compounds in that year, but higher concentrations were observed in recently treated fields. Overall, more residues were detected in B. napus pollen and nectar than in the wild plant, and B. napus pollen had the highest mean concentration of residues. All matrices were contaminated with at least three compounds, and the most frequently detected compounds were fungicides. The most common compound mixture was comprised of the fungicides azoxystrobin, boscalid, and the neonicotinoid insecticide clothianidin, which was not recently applied on the fields. Our results indicate that persistent compounds like the neonicotinoids, should be continuously monitored for their presence and fate in the field environment. The toxicological evaluation of the compound mixtures identified in the present study should be performed, to determine their impacts on foraging insects that may be exposed to them.
Keywords: Bees; Environmental contamination; Fungicides; Herbicides; Insecticides; Neonicotinoids

Effects of neonicotinoids and fipronil on non-target invertebrates - Pisa, L. W.; Amaral-Rogers, V.; Belzunces, L. P.; Bonmatin, J. M.; Downs, C. A.; Goulson, D.; Kreutzweiser, D. P.; Krupke, C.; Liess, M.; Mcfield, M.; Morrissey, C. A.; Noome, D. A.; et al. (Environmental Science and Pollution Research, 2014)
We assessed the state of knowledge regarding the effects of large-scale pollution with neonicotinoid insecticides and fipronil on non-target invertebrate species of terrestrial, freshwater and marine environments. A large section of the assessment is dedicated to the state of knowledge on sublethal effects on honeybees (Apis mellifera) because this important pollinator is the most studied non-target invertebrate species. Lepidoptera (butterflies and moths), Lumbricidae (earthworms), Apoidae sensu lato (bumblebees, solitary bees) and the section “other invertebrates” review available studies on the other terrestrial species. The sections on freshwater and marine species are rather short as little is known so far about the impact of neonicotinoid insecticides and fipronil on the diverse invertebrate fauna of these widely exposed habitats. For terrestrial and aquatic invertebrate species, the known effects of neonicotinoid pesticides and fipronil are described ranging from organismal toxicology and behavioural effects to population-level effects. For earthworms, freshwater and marine species, the relation of findings to regulatory risk assessment is described. Neonicotinoid insecticides exhibit very high toxicity to a wide range of invertebrates, particularly insects, and field-realistic exposure is likely to result in both lethal and a broad range of important sublethal impacts. There is a major knowledge gap regarding impacts on the grand majority of invertebrates, many of which perform essential roles enabling healthy ecosystem functioning. The data on the few non-target species on which field tests have been performed are limited by major flaws in the outdated test protocols. Despite large knowledge gaps and uncertainties, enough knowledge exists to conclude that existing levels of pollution with neonicotinoids and fipronil resulting from presently authorized uses frequently exceed the lowest observed adverse effect concentrations and are thus likely to have large-scale and wide ranging negative biological and ecological impacts on a wide range of non-target invertebrates in terrestrial, aquatic, marine and benthic habitats.
Keywords: Butterflies; Earthworms; Fipronil; Freshwater habitat; Honeybee; Invertebrates; Marine habitat; Neonicotinoids; Non-target species; Pesticides

Neonicotinoid insecticides negatively affect performance measures of non-target terrestrial arthropods: a meta-analysis - Main, Anson R.; Webb, Elisabeth B.; Goyne, Keith W.; Mengel, Doreen (Ecological Applications, 2018)
Neonicotinoid insecticides are currently the fastest-growing and most widely used insecticide class worldwide. Valued for their versatility in application, these insecticides may cause deleterious effects in a range of non-target (beneficial) arthropods. However, it remains unclear whether strong patterns exist in terms of their major effects, if broad measures of arthropod performance are negatively affected, or whether different functional groups are equally vulnerable. Here, we present a meta-analysis of 372 observations from 44 field and laboratory studies that describe neonicotinoid effects on 14 arthropod orders across five broad performance measures: abundance, behavior, condition, reproductive success, and survival. Across studies, neonicotinoids negatively affected all performance metrics evaluated; however, magnitude of the effects varied. Arthropod behavior and survival were the most negatively affected and abundance was the least negatively affected. Effects on arthropod functional groups were inconsistent. Pollinator condition, reproductive success, and survival were significantly lower in neonicotinoid treatments compared to untreated controls; whereas, neonicotinoid effects on detritivores were not significant. Although magnitude of arthropod response to neonicotinoids varied among performance measures and functional groups, we documented a consistent negative relationship between exposure to neonicotinoid insecticides in published studies and beneficial arthropod performance.
Keywords: abundance; behavior; beneficial insects; condition; meta-analysis; neonicotinoids; non-target; reproductive success; survival; terrestrial

RISK ASSESSMENT OF THE NEONICOTINOID INSECTICIDE ACETAMIPRID ON TWO NON-TARGET SPECIES, DAPHNIA MAGNA STRAUS, 1820 (CRUSTACEA, CLADOCERA) AND PLEA MINUTISSIMA LEACH, 1817 (INSECTA, HETEROPTERA) - Gacem, H.; Bendali-Saoudi, F.; Serradj, N.; Houmani, M.; Soltani, N. (Applied Ecology and Environmental Research, 2023)
Aquatic organisms are used to assess the health of aquatic systems. Extensive use of pesticides in agricultural and public health programs causes many environmental problems and toxic effects on aquatic animals especially against non-target organisms such as non-target organisms for mosquito larvae Plea minutissima Leach, 1817 and cladoceran biofilter and biomarker Daphnia magna Straus, 1820. These biological models were selected for their importance in the food chain and in the maintenance of homeostasis. Rustile is a multi-purpose toxic insecticide, manufactured by SARL DEKACHIM, consisting of 20% of the active ingredient Acetamipride. The lethal doses used for the insecticide in the treatment of these two non-target groups were LC50 = 1.45 ml/l and LC90 = 1.90 ml/l. The superiority of Culex pipiens larvae was recorded during three days of treatment. Both types showed a variable response to the tested product depending on doses and exposure times. Toxicity assays clearly showed a variable sensitivity of the two treated species recorded at high rates. The maximum values recorded were 86% and 97% for LC50 and LC90, respectively. It was found that rusty pesticides affect the two non-target tested species. The most sensitive species to this pesticide was Daphnia magna.
Keywords: Heteropter; Rustile; crustasia; ecotoxicity; insect

Current knowledge of detoxification mechanisms of xenobiotic in honey bees - Gong, Youhui; Diao, Qingyun (Ecotoxicology, 2017)
The western honey bee Apis mellifera is the most important managed pollinator species in the world. Multiple factors have been implicated as potential causes or factors contributing to colony collapse disorder, including honey bee pathogens and nutritional deficiencies as well as exposure to pesticides. Honey bees’ genome is characterized by a paucity of genes associated with detoxification, which makes them vulnerable to specific pesticides, especially to combinations of pesticides in real field environments. Many studies have investigated the mechanisms involved in detoxification of xenobiotics/pesticides in honey bees, from primal enzyme assays or toxicity bioassays to characterization of transcript gene expression and protein expression in response to xenobiotics/insecticides by using a global transcriptomic or proteomic approach, and even to functional characterizations. The global transcriptomic and proteomic approach allowed us to learn that detoxification mechanisms in honey bees involve multiple genes and pathways along with changes in energy metabolism and cellular stress response. P450 genes, is highly implicated in the direct detoxification of xenobiotics/insecticides in honey bees and their expression can be regulated by honey/pollen constitutes, resulting in the tolerance of honey bees to other xenobiotics or insecticides. P450s is also a key detoxification enzyme that mediate synergism interaction between acaricides/insecticides and fungicides through inhibition P450 activity by fungicides or competition for detoxification enzymes between acaricides. With the wide use of insecticides in agriculture, understanding the detoxification mechanism of insecticides in honey bees and how honeybees fight with the xenobiotis or insecticides to survive in the changing environment will finally benefit honeybees’ management.
Keywords: Detoxification genes; Function; Honeybee health management; Metabolism pathways; Nutrition; P450 genes

The health crisis in managed honey bees (Apis mellifera). Which factors are involved in this phenomenon? - Neov, Boyko; Shumkova, Rositsa; Palova, Nadezhda; Hristov, Peter
The Western honey bee, Apis mellifera plays a crucial role as a pollinator worldwide. Except the wide number of commercial crops, honey bees pollinate many wild plants, some of which are threatened with extinction and are valuable genetic resource. Although during the last few years honey bee populations are steady and increasing in numbers with some fluctuation, there are a number of threats responsible for honey bee health and survival. As key factors for this are pointing out poor nutrition, sublethal insecticide exposure, and biotic stressors, including diseases and parasites. The decline of honey bee populations negatively affects not only many commercial crop and flowering plants, but also reduces honey bee products such as honey, bee pollen, propolis, bee venom, royal jelly and beeswax etc., many of them with significant role in human health benefits. Many hypotheses have been put forward in an attempt to explain these losses, but so far no indisputable factor has been identified responsible as the main driver of bee decline. Thus, it is necessary to urgently take measures to protect and preserve the honey bee by identifying and neutralizing the most significant causes leading to this phenomenon. Conservation methods are in place to protect A. mellifera and honey bee populations in a large part of the world. However, the survey also reveals the disparity in resources and information dedicated between honey bees and all other pollinators.
Keywords: Apis mellifera; Biotic and abiotic stressors; Honey bee population decline

Bee nutrition and artificial food - Agarwal, Rajkumar; Bansal, Astha; Saini, Amarjeet Singh; Raj, Ashish; Kumar, Ashish; Saini, Singh; Gharde, S K (~ 1635 ~ The Pharma Innovation Journal, 2023)
Bee nutrition is vital for the survival and wellness of bee colonies. Bees need a balanced diet of carbohydrates, proteins, vitamins, and minerals to perform their vital functions such as pollination and honey production. Still, the accessibility of natural food sources for bees, such as nectar and pollen, has been declining due to habitat loss, fungicide use, and climate change. The use of artificial food has raised concerns among experimenters and beekeepers about its potential long-term goods on bee health and behaviour. Some examinations suggest that bees fed on artificial food may have reduced immune function, changed inside microbiome, and behavioural changes, similar as dropped rustling and reduced colony growth. Thus, its essential to balance the use of artificial food with efforts to conserve natural territories and promote sustainable farming practices that support bee populations.
Keywords: Honey bee nutrition; artificial food; colony; pollen substitute; pollen supplement

The flavonoid rutin protects the bumble bee Bombus impatiens against cognitive impairment by imidacloprid and fipronil - Riveros, Andre J.; Gronenberg, Wulfila (Journal of Experimental Biology, 2022)
The ongoing decline of bee populations and its impact on food security demands integrating multiple strategies. Sublethal impairments associated with exposure to insecticides, affecting the individual and the colony levels, have led to insecticide moratoria and bans. However, legislation alone is not sufficient and remains a temporary solution to an evolving market of insecticides. Here, we asked whether bees can be prophylactically protected against sublethal cognitive effects of two major neurotoxic insecticides, imidacloprid and fipronil, with different mechanisms of action. We evaluated the protective effect of the prophylactic administration of the flavonoid rutin, a secondary plant metabolite, present in nectar and pollen, and known for its neuroprotective properties. Following controlled or ad libitum administration of rutin, foragers of the North American bumble bee Bombus impatiens received oral administration of the insecticides at sublethal realistic dosages. Learning acquisition, memory retention and decision speed were evaluated using olfactory absolute conditioning of the proboscis extension response. We show that the insecticides primarily impair acquisition but not retention or speed of the conditioned proboscis extension response. We further show that the administration of the flavonoid rutin successfully protects the bees against impairments produced by acute and chronic administration of insecticides. Our results suggest a new avenue for the protection of bees against sublethal cognitive effects of insecticides.
Keywords: Bee decline; Flavonol; Neonicotinoid; Pollinator

Biphasic concentration-dependent interaction between imidacloprid and dietary phytochemicals in honey bees (Apis mellifera) - Wong, Michael J.; Liao, Ling Hsiu; Berenbaum, May R. (PLoS ONE, 2018)
Background The presence of the neonicotinoid imidacloprid in nectar, honey, pollen, beebread and beeswax has been implicated in declines worldwide in the health of the western honey bee Apis mellifera. Certain phytochemicals, including quercetin and p-coumaric acid, are ubiquitous in the honey bee diet and are known to upregulate cytochrome P450 genes encoding enzymes that detoxify insecticides. Thus, the possibility exists that these dietary phytochemicals interact with ingested imidacloprid to ameliorate toxicity by enhancing its detoxification. Approach Quercetin and p-coumaric acid were incorporated in a phytochemical-free artificial diet individually and together along with imidacloprid at a range of field-realistic concentrations. In acute toxicity bioassays, honey bee 24-and 48-hour imidacloprid LC50 values were determined in the presence of the phytochemicals. Additionally, chronic toxicity bioassays were conducted using varying concentrations of imidacloprid in diets with the phytochemicals to test impacts of phytochemicals on longevity. Results In acute toxicity bioassays, the phytochemicals had no effect on imidacloprid LC50 values. In chronic toxicity longevity bioassays, phytochemicals enhanced honey bee survival at low imidacloprid concentrations (15 and 45 ppb) but had a negative effect at higher concentrations (105 ppb and 135 ppb). p-Coumaric acid alone increased honey bee longevity at concentrations of 15 and 45 ppb imidacloprid (hazard ratio (HR): 0.83 and 0.70, respectively). Quercetin alone and in combination with p-coumaric acid similarly enhanced longevity at 45 ppb imidacloprid (HR:0.81 and HR:0.77, respectively). However, p-coumaric acid in combination with 105 ppb imidacloprid and quercetin in combination with 135 ppb imidacloprid increased honey bee HR by approximately 30% (HR:1.33 and HR:1.30, respectively). Conclusions The biphasic concentration-dependent response of honey bees to imidacloprid in the presence of two ubiquitous dietary phytochemicals indicates that there are limits to the protective effects of the natural diet of honey bees against neonicotinoids based on their own inherent toxicity.

In vitro antioxidant properties of rutin - Yang, Jianxiong; Guo, Juan; Yuan, Jiangfeng (LWT, 2008)
Much work has been carried out in recent years on the beneficial effect of phenolic compounds which act as natural antioxidants and help to neutralize free radicals. We analysed the antioxidant activity of the rutin (quercetin-3-rhamnosyl glucoside) using different assays including: total antioxidant activity and reducing power, hydroxyl radical scavenging assay, superoxide radical scavenging assay, 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging assay and lipid peroxidation assay which uses egg yolk as the lipid-rich source. Total antioxidant capacity was determined by the assay based on the decrease in absorbance of β-carotene by the sample. Rutin exhibited strong DPPH radical scavenging activity. At the concentration of 0.05 mg/ml, ascorbic acid (Vc), butylated hydroxytoluene (BHT) and rutin showed 92.8%, 58.8%, and 90.4% inhibition, respectively. In addition, rutin had effective inhibition of lipid peroxidation. Those various antioxidant activities were compared to standard antioxidants such as BHT and Vc. © 2007 Swiss Society of Food Science and Technology.
Keywords: Antioxidant activity; DPPH; Hydroxyl radical; In vitro; Rutin

A comparative study of rutin and rutin glycoside: Antioxidant activity, anti-inflammatory effect, effect on platelet aggregation and blood coagulation - Choi, Sung Sook; Park, Hye Ryung; Lee, Kyung Ae (Antioxidants, 2021)
The effects of rutin and rutin glycoside with different solubility were compared on an-tioxidant activity and anti-inflammatory effects in vitro and the effects on platelet aggregation and blood coagulation in vitro and in vivo. Rutin glycoside (consisting of rutin mono-glucoside and rutin di-glucoside) was prepared via enzymatic transglycosylation from rutin. Rutin glycoside showed a higher effect than rutin on radical scavenging activity in antioxidant assays. Rutin showed a higher toxicity than rutin glycoside in murine macrophage RAW264.7 cells. They had similar effects on the levels of nitric oxide (NO), prostaglandin E (PGE) 2 and pro-inflammatory cytokines (such as tumor necrosis factor (TNF)-α, and interleukin (IL)-6) in the cells. Both rutin and rutin glycosides similarly reduced the rate of platelet aggregation compared to controls in vitro. They also similarly delayed prothrombin time (PT) and activated partial thromboplastin time (APTT) in an in vitro blood coagulation test. The effect of repeated administration of rutin and rutin glycoside was evaluated in vivo using SD rats. The platelet aggregation rate of rutin and the rutin glycoside administered group was significantly decreased compared to that of the control group. On the other hand, PT and APTT of rutin and rutin glycoside group were not significantly delayed in vivo blood coagulation test. In conclusion, rutin and rutin glycoside showed differences in antioxidant activities in vitro, while they were similar in the reduction of NO, PGE2, TNF-α and IL-6 in vitro. Rutin and rutin glycoside also showed similar platelet aggregation rates, and blood coagulation both in vitro and in vivo condition. Comparing in vitro and in vivo, rutin and rutin glycoside were effective on platelet aggregation both in vitro and in vivo, but only in vitro on blood coagulation.
Keywords: Anti-inflammatory; Antioxidant; Blood coagulation; In vitro; In vivo; Platelet aggregation; Rutin; Rutin glycoside; Solubility; Transglycosylation

Impact of sublethal concentrations of flonicamid on key demographic parameters and feeding behavior of Schizaphis graminum - Gul, Hina; ul Haq, Ihsan; Ullah, Farman; Khan, Shanza; Yaseen, Aqsa; Shah, Said Hussain; Tariq, Kaleem; Güncan, Ali; Desneux, Nicolas; Liu, Xiaoxia (Ecotoxicology, 2023)

Lethal and sublethal effects of synthetic and bioinsecticides toward the invasive ambrosia beetle Xylosandrus compactus - Gugliuzzo, Antonio; Giuliano, Gaetano; Rizzo, Roberto; Tropea Garzia, Giovanna; Biondi, Antonio (Pest Management Science, 2023)
BACKGROUND: Exotic ambrosia beetles are emerging widespread pests of several wild and managed trees and shrubs. Xylosandrus compactus (Eichhoff) is one of the most invasive species causing damage to a broad range of host plants. Little information is available on its control, including the impact of insecticides. Bioassays were conducted to evaluate the potential of four bioinsecticides and seven synthetic insecticides in controlling X. compactus. Beetle mortality and sublethal effects on tunneling, cultivation of the mutualist fungus and reproduction were assessed. RESULTS: Concentration–mortality curves were determined for all tested insecticides. Lambda-cyhalothrin was the most toxic insecticide, showing the lowest estimated 90% and 50% lethal concentrations (LC90 and LC50), followed by deltamethrin and thiamethoxam. Acetamiprid caused the highest levels of mortality and brood size reduction under extended laboratory conditions. Moreover, acetamiprid, thiamethoxam and lambda-cyhalothrin caused the greatest mortality and, together with deltamethrin, strongly affected progeny occurrence inside infested galleries and beetle brood size. Among the bioinsecticides, pyrethrins significantly affected beetle survival under laboratory conditions, but not brood size in extended laboratory bioassays. Some of the tested insecticides had significant lethal and sublethal effects only when beetles were exposed to fresher residues, highlighting differences in toxicity persistence. CONCLUSION: This study provides first baseline toxicity data for synthetic insecticides and bioinsecticides with different modes of action and origin toward X. compactus, and the first evidence that several insecticides can cause multiple sublethal effects on this pest. These findings can help in building suitable integrated pest management packages against this pest. © 2023 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: Xyleborini; biopesticides; integrated pest management; invasive species; neonicotinoids; pyrethroids

Sugar content of diet does not buffer against chronic oral imidacloprid exposure in the alfalfa leafcutting bee (Hymenoptera: Megachilidae) - Cecala, Jacob M.; Baronia, Danelle Angeline; Wilson Rankin, Erin E. (Journal of Economic Entomology, 2020)
Bees are economically critical pollinators, but are declining broadly due to several stressors, including nontarget exposure to insecticides and deficiencies in nutrition. Understanding the simultaneous impact of stressors, particularly interactions between them, is critical to effectively conserving bees. Although behavioral effects of pesticides like neonicotinoids have received some attention in solitary bees, our understanding of how they are modulated by diet quality is limited. Furthermore, scarce data exist on what concentrations of orally ingested neonicotinoids elicit mortality in solitary bees. In a controlled exposure laboratory experiment, we investigated how diet quality, as sugar concentration, and chronic oral exposure to imidacloprid affect adult alfalfa leafcutting bees, Megachile rotundata (Fabricius). We provided individuals ad libitum with either 20 or 50% (m/m) sucrose syrups containing either 0, 30, or 300 ppb imidacloprid (measuring 0, 27, and 209 ppb via an ELISA assay). Over 5 wk, we tracked behavior and survivorship of individuals. Imidacloprid decreased survivorship in a dose-dependent fashion, but sucrose content did not affect survivorship, even in bees not fed imidacloprid. In the high imidacloprid treatment, 45% of bees were observed in a motionless supine position while still alive, with this effect appearing to be buffered against by the higher sucrose diet. Our results suggest that diets higher in sugar concentration may prevent an intermediate stage of poisoning, but do not ultimately extend longevity. In devising risk assessments for bees, it is important to consider that interactions between stressors may occur in the stages leading up to death even if survivorship is unaffected.
Keywords: behavior; neonicotinoids; nutrition; pesticides; solitary bees

Biotic and abiotic stresses on honeybee health - Lin, Zheguang; Shen, Siyi; Wang, Kang; Ting, J. I. (Integrative Zoology, 2023)
Honeybees are the most critical pollinators providing key ecosystem services that underpin crop production and sustainable agriculture. Amidst a backdrop of rapid global change, this eusocial insect encounters a succession of stressors during nesting, foraging, and pollination. Ectoparasitic mites, together with vectored viruses, have been recognized as central biotic threats to honeybee health, while the spread of invasive giant hornets and small hive beetles also increasingly threatens colonies worldwide. Cocktails of agrochemicals, including acaricides used for mite treatment, and other pollutants of the environment have been widely documented to affect bee health in various ways. Additionally, expanding urbanization, climate change, and agricultural intensification often result in the destruction or fragmentation of flower-rich bee habitats. The anthropogenic pressures exerted by beekeeping management practices affect the natural selection and evolution of honeybees, and colony translocations facilitate alien species invasion and disease transmission. In this review, the multiple biotic and abiotic threats and their interactions that potentially undermine bee colony health are discussed, while taking into consideration the sensitivity, large foraging area, dense network among related nestmates, and social behaviors of honeybees.
Keywords: Apis; abiotic stressor; biotic stressor; colony losses; interaction effect; pollinator decline

Using the Honey Bee (Apis mellifera L.) Cell Line AmE-711 to Evaluate Insecticide Toxicity - Goblirsch, Michael; Adamczyk, John J. (Environmental Toxicology and Chemistry, 2023)
One of the main contributors to poor productivity and elevated mortality of honey bee colonies globally is insecticide exposure. Whole-organism and colony-level studies have demonstrated the effects of insecticides on many aspects of honey bee biology and have also shown their interactions with pathogens. However, there is a need for in vitro studies using cell lines to provide greater illumination of the effects of insecticides on honey bee cellular and molecular processes. We used a continuous cell line established from honey bee embryonic tissues (AmE-711) in assays that enabled assessment of cell viability in response to insecticide exposure. We exposed AmE-711 cells to four formulations, each containing a different insecticide. Treatment of cells with the insecticides resulted in a concentration-dependent reduction in viability after a 24-h exposure, whereas long-term exposure (120 h) to sublethal concentrations had limited effects on viability. The 24-h exposure data allowed us to predict the half-maximal lethal concentration (LC50) for each insecticide using a four-parameter logistical model. We then exposed cells for 12 h to the predicted LC50 and observed changes in morphology that would indicate stress and death. Reverse transcription–quantitative polymerase chain reaction analysis corroborated changes in morphology: expression of a cellular stress response gene, 410087a, increased after an 18-h exposure to the predicted LC50. Demonstration of the effects of insecticides through use of AmE-711 provides a foundation for additional research addressing issues specific to honey bee toxicology and complements whole-organism and colony-level approaches. Moreover, advances in the use of AmE-711 in high-throughput screening and in-depth analysis of cell regulatory networks will promote the discovery of novel control agents with decreased negative impacts on honey bees. Environ Toxicol Chem 2023;42:88–99. Published 2022. This article is a U.S. Government work and is in the public domain in the USA. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.
Keywords: cytotoxicity; heat shock proteins; honey bee cell culture; l(2)efl 410087a; nontarget organism; sublethal doses

Semi-Lethal Doses of Neonicotinoid Imidacloprid Adjust the Wing-Flapping Frequency and Flight Ability Of Apis Mellifera

Residual effect of imidacloprid and beta-cyfluthrin on Africanized Apis mellifera L. (Hymenoptera: Apidae) workers - Abati, Raiza; Libardoni, Gabriela; Osowski, Gabriela; de Souza Vismara, Edgar; Costa-Maia, Fabiana Martins; Lozano, Everton Ricardi; Adami, Paulo Fernando; Potrich, Michele (Apidologie, 2023)
Canola has a long period of flowering in the winter season and this, associated with the lack of other flowers and the use of insecticides to control insect pests, means it may have a great impact on bee populations, such as Apis mellifera L. (Hymenoptera: Apidae). In this context, the use of insecticides with lower residuals and less harmful effects to bees is fundamental. Thus, the objective of the current work was to evaluate, in a laboratory bioassay, the residual toxicity and effect of imidacloprid, beta-cyfluthrin, and a mixture of both, when applied on canola in the field, on Africanized A. mellifera workers. Three commercial products were applied, formulated with imidacloprid, beta-cyfluthrin, and beta-cyfluthrin + imidacloprid. Each plot received one of the three treatments, in the concentration recommended by the manufacturer, at intervals between 14 and 0 days prior to conducting the bioassays. On the day of the bioassay, the bees were exposed to the plant material containing the treatments for a period of two hours, and were transferred to PVC cages, containing food and water. Mortality assessments were then performed at pre-established intervals until a 96 h post-exposure. Residuals on canola leaves of all tested products caused a significant reduction of honeybee worker longevity, which was less accentuated when the interval after treatment application increased. Safer pest management strategies are needed to ensure the preservation of bees.
Keywords: Brassica napus; honey bee; insecticide; neonicotinoid; pollinator; pyrethroid

Chronic exposure to imidacloprid or thiamethoxam neonicotinoid causes oxidative damages and alters carotenoid-retinoid levels in caged honey bees (Apis mellifera) - Gauthier, Maxime; Aras, Philippe; Paquin, Joanne; Boily, Monique (Scientific Reports, 2018)
Over the last decade, the persistent dwindling of the populations of honey bees has become a growing concern. While this phenomenon is partly attributed to neonicotinoids (NEOCs), chronic exposures to these insecticides at environmentally-relevant concentrations are needed to fully estimate their implications. In this study, honey bees were orally exposed for 10 days to low field-realistic concentrations of NEOCs known for their effects on the cholinergic system (imidacloprid – IMI or thiamethoxam – THM). Selected biomarkers were measured such as acetylcholinesterase (AChE) activity, lipid peroxidation (LPO), α-tocopherol as well as several forms of vitamin A (retinoids) and carotenoids. Bees exposed to IMI showed lower levels of two carotenoids (α-carotene and α-cryptoxanthin) and α-tocopherol. The THM exposure increased the oxidized vitamin A metabolites in bees conjointly with the LPO. These results could be the consequence of a pro-oxidant effect of NEOCs and were observed at levels where no effects were recorded for AChE activity. This study reveals that exposure to low levels of NEOCs alters the carotenoid-retinoid system in honey bees. This would merit further investigation as these compounds are important in various aspects of bees’ health. Overall, this study contributes to the development of biomonitoring tools for the health of bees and other pollinators.

Imidacloprid and clothianidin insecticides individual and mixture effects on fish Labeorohita plasma electrolytes and gill Na + /K + ATPase activities - Sadaya Kumar, Gajula; Das Vanamala, Vanita (Journal of Survey in Fisheries Sciences, 2023)
Neonicotinoids are a new class of insecticides that are widely used around the world owing to their efficacy and insect selectivity. Imidacloprid and clothianidin are major neonicotinoids which are frequently found in the aquatic environment, especially in streams. The present investigation evaluated the individual and combined toxicity of imidacloprid and clothianidin in the freshwater fish Labeorohita. The fish were intoxicated with imidacloprid (66.6 mg/L), clothianidin (30 mg/L) and their combination mixture (IMI: 33.3 and CLO: 15.0 mg/L) for 42 days. The plasma electrolytes such as Na + , K + andCl-andgills Na + /K + ATPase were evaluated. The plasma electrolytes (Na + , K + andCl-) and gill Na + /K + ATPase activities were significantly inhibited throughout the exposure period. The maximum inhibition was noted on the 28 th day of intoxication and is more in the mixture than the individual.
Keywords: Clothianidin; Electrolytes; Imidacloprid; Na + /K + ATPase; Neonicotinoids

Sub-lethal doses of imidacloprid alter food selection in the invasive garden ant Lasius neglectus - Frizzi, Filippo; Balzani, Paride; Masoni, Alberto; Frasconi Wendt, Clara; Marconi, Matilde; Rossi, Asia; Santini, Giacomo (Environmental Science and Pollution Research, 2023)
Despite several restrictions to their use, neonicotinoid insecticides are still widely employed worldwide. Residual sub-lethal amounts of these chemicals can have detrimental effects on the behavior of non-target insects. Toxic effects on economically important species such as bees have been widely documented, but less is known about their toxic action on other social insects, such as ants. In this study, we assessed the effect of different sub-lethal doses of the neonicotinoid imidacloprid on the ability of colonies of the invasive ant Lasius neglectus to select the most profitable resource. We used Y-shaped mazes having an imidacloprid-polluted or an unpolluted sucrose solution on the two branches. Two sucrose (0.1 M, 0.5 M) and two imidacloprid (1 μg/ml, 10 μg/ml) concentrations were used. In parallel, we evaluated the marking activity of foragers who fed on the same solutions. We found that the 0.1 M sugar solution polluted with 1 μg/ml imidacloprid was significantly more frequently selected in binary choices experiments than the unpolluted resource. Moreover, the ingestion of the same combination of sugar and imidacloprid significantly increased the marking rate of foragers. The higher concentration of the pollutant had lower effects, probably because of the hormesis phenomenon. Results suggest that the lower sub-lethal dose of imidacloprid can lead ants to select again the polluted resource. This “active” selection of the pollutant may magnify the negative effects on the colonies. Due to their ecological role, any impairment of ant survival or behavior may have detrimental cascade effects on the whole ecosystem.
Keywords: Ants; Binary choice; Invasive species; Neonicotinoids; Resource selection; Symmetry breaking

The protective effects of rutin on the liver, kidneys, and heart by counteracting organ toxicity caused by synthetic and natural compounds - Rahmani, Sohrab; Naraki, Karim; Roohbakhsh, Ali; Hayes, A. Wallace; Karimi, Gholamreza (Food Science and Nutrition, 2023)
Rutin is a flavonoid present in many plant species. Because of its antioxidant, anti-inflammatory, and antiapoptotic properties, rutin is of interest for its potential protective effects against toxic agents. The hepatoprotective, renoprotective, and cardioprotective effects of rutin are reviewed. The antioxidant effects of rutin are elicited by enhancing antioxidant enzymes such as GST, GGT, CAT, GPx, SOD, and GR, activating the Nrf2/HO-1 pathway, elevating GSH content, and the reduction in MDA. The anti-inflammatory effects of rutin are mediated by the inhibition of IL-1β, IL-6, TGF-β1, COX-2, iNOS, TLR4, and XO. Rutin exerted its antiapoptotic effects by inhibition of free radicals, caspase-3/-7/-9, hsp70, HMGB1, and p53, and the elevation of the antiapoptotic protein Bcl-2. Rutin has potential therapeutic effectiveness against several toxicants, and its beneficial effects are more than likely mediated by its antioxidant, anti-inflammatory, and/or antiapoptotic property.
Keywords: apoptosis; flavonoid; oxidative stress; rutin

Rutin ameliorates gout via reducing XOD activity, inhibiting ROS production and NLRP3 inflammasome activation in quail - Wu, Hao; Wang, Yu; Huang, Jingjian; Li, Yaolei; Lin, Zhijian; Zhang, Bing (Biomedicine and Pharmacotherapy, 2023)
Gout is a metabolic disease affected by monosodium urate (MSU) deposition, which is directly related to hyperuricemia. Recent reports on the prevalence and incidence of gout have been widely circulated worldwide. Currently, the anti-gout drugs in clinical practice are mainly small-molecule synthetic drugs, and the effectiveness and safety are limited. Reducing uric acid and inhibiting inflammation are the focused areas of drug research and development on gout. Rutin, a natural flavonoid, has been reported to alleviate inflammation in various diseases. However, whether rutin exerts protective effects on gout remains to be elucidated. This study used quails without urate oxidase as experimental animals to induce endogenous gout models through a high purine diet. We confirmed that quail in the model group developed gout symptoms at 30 days of the experiment. And the targets of uric acid metabolism, oxidative stress level, and NLRP3 inflammasome were dysregulated in quails. Rutin treatment improves gout and reduces inflammatory expression in quail. We further confirmed that rutin treatment reduced XOD activity and uric acid levels in quail. And rutin inhibited ROS production, restored oxidative stress balance, inhibited NLRP3 inflammasome activation, and exerted anti-inflammatory effects. We extracted and identified the fibroblast-like synoviocytes (FLS) for the first time. The results showed that rutin could reduce ROS production and NLRP3 inflammasome activation of FLS after uric acid stimulation. In conclusion, our findings underscore that rutin may be a gout protective agent by reducing XOD activity, inhibiting ROS production and NLRP3 inflammasome activation. Meanwhile, this study also provides an available animal model for the research drugs of gout.
Keywords: Gout; NLRP3 inflammasome; ROS; Rutin; Uric Acid; XOD

Physiological and Behavioral Changes in Honey Bees (Apis mellifera) Induced by Nosema ceranae Infection - Goblirsch, Mike; Huang, Zachary Y.; Spivak, Marla (PLoS ONE, 2013)
Persistent exposure to mite pests, poor nutrition, pesticides, and pathogens threaten honey bee survival. In healthy colonies, the interaction of the yolk precursor protein, vitellogenin (Vg), and endocrine factor, juvenile hormone (JH), functions as a pacemaker driving the sequence of behaviors that workers perform throughout their lives. Young bees perform nursing duties within the hive and have high Vg and low JH; as older bees transition to foraging, this trend reverses. Pathogens and parasites can alter this regulatory network. For example, infection with the microsporidian, Nosema apis, has been shown to advance behavioral maturation in workers. We investigated the effects of infection with a recent honey bee pathogen on physiological factors underlying the division of labor in workers. Bees infected with N. ceranae were nearly twice as likely to engage in precocious foraging and lived 9 days less, on average, compared to controls. We also show that Vg transcript was low, while JH titer spiked, in infected nurse-aged bees in cages. This pattern of expression is atypical and the reverse of what would be expected for healthy, non-infected bees. Disruption of the basic underpinnings of temporal polyethism due to infection may be a contributing factor to recent high colony mortality, as workers may lose flexibility in their response to colony demands. © 2013 Goblirsch et al.

Caffeine Consumption Helps Honey Bees Fight a Bacterial Pathogen - Motta, Erick V. S.; Arnott, Ryan L. W.; Moran, Nancy A. (Microbiology Spectrum, 2023)
The consumption of caffeine is a remarkable feature of the human diet. Common drinks, such as coffee and tea, contain caffeine as a stimulant. Caffeine has long been used as a stimulant by humans. Although this secondary metabolite is produced by some plants as a mechanism of defense against herbivores, beneficial or detrimental effects of such consumption are usually associated with dose. The Western honey bee, Apis mellifera , can also be exposed to caffeine when foraging at Coffea and Citrus plants, and low doses as are found in the nectar of these plants seem to boost memory learning and ameliorate parasite infection in bees. In this study, we investigated the effects of caffeine consumption on the gut microbiota of honey bees and on susceptibility to bacterial infection. We performed in vivo experiments in which honey bees, deprived of or colonized with their native microbiota, were exposed to nectar-relevant concentrations of caffeine for a week, then challenged with the bacterial pathogen Serratia marcescens . We found that caffeine consumption did not impact the gut microbiota or survival rates of honey bees. Moreover, microbiota-colonized bees exposed to caffeine were more resistant to infection and exhibited increased survival rates compared to microbiota-colonized or microbiota-deprived bees only exposed to the pathogen. Our findings point to an additional benefit of caffeine consumption in honey bee health by protecting against bacterial infections. IMPORTANCE The consumption of caffeine is a remarkable feature of the human diet. Common drinks, such as coffee and tea, contain caffeine as a stimulant. Interestingly, honey bees also seem to like caffeine. They are usually attracted to the low concentrations of caffeine found in nectar and pollen of Coffea plants, and consumption improves learning and memory retention, as well as protects against viruses and fungal parasites. In this study, we expanded these findings by demonstrating that caffeine can improve survival rates of honey bees infected with Serratia marcescens , a bacterial pathogen known to cause sepsis in animals. However, this beneficial effect was only observed when bees were colonized with their native gut microbiota, and caffeine seemed not to directly affect the gut microbiota or survival rates of bees. Our findings suggest a potential synergism between caffeine and gut microbial communities in protection against bacterial pathogens.

Hugh-D.-Young-Roger-A.-Freedman-A.-Lewis-Ford-University-Physics-with-Modern-Physics-with-MasteringPhysics®-13th-Edition-Addison-Wesley-2011

Standard methods for toxicology research in Apis mellifera - Medrzycki, Piotr; Giffard, Hervé; Aupinel, Pierrick; Belzunces, Luc P.; Chauzat, Marie Pierre; Claßen, Christian; Colin, Marc E.; Dupont, Thierry; Girolami, Vincenzo; Johnson, Reed; Conte, Yves Le; Lückmann, Johannes; et al. (Journal of Apicultural Research, 2013)
Modern agriculture often involves the use of pesticides to protect crops. These substances are harmful to target organisms (pests and pathogens). Nevertheless, they can also damage non-target animals, such as pollinators and entomophagous arthropods. It is obvious that the undesirable side effects of pesticides on the environment should be reduced to a minimum. Western honey bees (Apis mellifera) are very important organisms from an agricultural perspective and are vulnerable to pesticide-induced impacts. They contribute actively to the pollination of cultivated crops and wild vegetation, making food production possible. Of course, since Apis mellifera occupies the same ecological niche as many other species of pollinators, the loss of honey bees caused by environmental pollutants suggests that other insects may experience a similar outcome. Because pesticides can harm honey bees and other pollinators, it is important to register pesticides that are as selective as possible. In this manuscript, we describe a selection of methods used for studying pesticide toxicity/selectiveness towards Apis mellifera. These methods may be used in risk assessment schemes and in scientific research aimed to explain acute and chronic effects of any target compound on Apis mellifera. © IBRA 2013.
Keywords: Apis mellifera; BEEBOOK; COLOSS; Exposure; Field; Honey bee; Laboratory; Lethal; Pesticide; Residue; Semifield; Sublethal

Abnormal Foraging Behavior Induced by Sublethal Dosage of Imidacloprid in the Honey Bee (Hymenoptera: Apidae) - Yang, E C; Chuang, Y C; Chen, Y L; Chang, L H (APICULTURE AND SOCIAL INSECTS J. Econ. Entomol, 2008)
Although sublethal dosages of insecticide to nontarget insects have never been an important issue, they are attracting more and more attention lately. It has been demonstrated that low dosages of the neonicotinoid insecticide imidacloprid may affect honey bee, Apis mellifera L., behavior. In this article, the foraging behavior of the honey bee workers was investigated to show the effects of imidacloprid. By measuring the time interval between two visits at the same feeding site, we found that the normal foraging interval of honey bee workers was within 300 s. However, these honey bee workers delayed their return visit for 300 s when they were treated orally with sugar water containing imidacloprid. This time delay in their return visit is concentration-dependent, and the lowest effective concentration was found to be 50 g/liter. When bees were treated with an imidacloprid concentration higher than 1,200 g/liter, they showed abnormalities in revisiting the feeding site. Some of them went missing, and some were present again at the feeding site the next day. Returning bees also showed delay in their return trips. Our results demonstrated that sublethal dosages of imidacloprid were able to affect foraging behavior of honey bees.
Keywords: foraging behavior; honey bee; imidacloprid; sublethal dosage

Rutin attenuates inflammatory responses induced by lipopolysaccharide in an in vitro mouse muscle cell (C2C12) model - Liu, Shangxi; Adewole, Deborah; Yu, Li; Sid, Victoria; Wang, Blake; Karmin, O.; Yang, Chengbo (Poultry Science, 2019)
White striping (WS) and woody breast (WB) are 2 of the major myopathies in the modern poultry industry. Even though the exact etiology for WS and WB is still unknown, differentially expressed genes in broiler breast muscle affected by WS and WB indicate that oxidative stress and inflammation could be involved in their occurrences. Therefore, it is very important to identify natural compounds with antioxidative stress and anti-inflammation properties that can reduce the occurrences of WS and WB in broiler chickens. Rutin is a polyphenol antioxidant that has been reported to be present in several plant extracts. In the current study, we established an in vitro inflammation model by using mouse muscle cells (C2C12) and evaluated the effects of rutin on lipopolysaccharide (LPS)-induced inflammatory responses in the muscle cells. Interleukin 6 (IL-6) secretion was measured by enzyme-linked immunosorbent assay. The mRNA abundance of cytokines and inducible nitric oxide synthase (iNOS) was measured by real-time PCR. Nuclear factor kappa B (NF-κB) activation was detected by electrophoretic mobility shift assay. The results showed that LPS (25 ng/ml) stimulation quickly activated NF-κB and induced significant IL-6 expression on both mRNA and protein levels (P < 0.05) in cells when compared with control cells without the LPS treatment. The rutin treatment decreased IL-6 mRNA abundance induced by LPS in a dose-dependent manner (P < 0.05). LPS-induced tumor necrosis factor-alpha and iNOS gene expression was significantly attenuated by 100 μM of rutin (P < 0.05). Moreover, LPS induced reactive oxygen species (ROS) production, and NF-κB activation was significantly blocked by 100 μM of rutin. These results suggest that rutin can attenuate LPS-induced inflammation in muscle cells and supplementation of rutin or rutin-containing plant extracts may present a promising approach to control WS and WB in broiler chickens.
Keywords: Broiler chickens; Inflammation; LPS; Muscle cells; Myopathies

Rutin as a potent antioxidant: Implications for neurodegenerative disorders - Enogieru, Adaze Bijou; Haylett, William; Hiss, Donavon Charles; Bardien, Soraya; Ekpo, Okobi Eko (Oxidative Medicine and Cellular Longevity, 2018)
A wide range of neurodegenerative diseases (NDs), including Alzheimer's disease, Parkinson's disease, Huntington's disease, and prion diseases, share common mechanisms such as neuronal loss, apoptosis, mitochondrial dysfunction, oxidative stress, and inflammation. Intervention strategies using plant-derived bioactive compounds have been offered as a form of treatment for these debilitating conditions, as there are currently no remedies to prevent, reverse, or halt the progression of neuronal loss. Rutin, a glycoside of the flavonoid quercetin, is found in many plants and fruits, especially buckwheat, apricots, cherries, grapes, grapefruit, plums, and oranges. Pharmacological studies have reported the beneficial effects of rutin in many disease conditions, and its therapeutic potential in several models of NDs has created considerable excitement. Here, we have summarized the current knowledge on the neuroprotective mechanisms of rutin in various experimental models of NDs. The mechanisms of action reviewed in this article include reduction of proinflammatory cytokines, improved antioxidant enzyme activities, activation of the mitogen-activated protein kinase cascade, downregulation of mRNA expression of PD-linked and proapoptotic genes, upregulation of the ion transport and antiapoptotic genes, and restoration of the activities of mitochondrial complex enzymes. Taken together, these findings suggest that rutin may be a promising neuroprotective compound for the treatment of NDs.

Neuroprotective Effects of Rutin and Quercetin Flavonoids in Glaucium corniculatum Methanol and Water Extracts - Koçancı, Fatma Gonca; Aslim, Belma (International Journal of Secondary Metabolite, 2017)
Neurodegenerative diseases (NDs) are characterized by loss of neurons. NDs are associated with development of inflammation. Existing drugs against NDs only delay the progression; however, they do not provide a cure. The studies for the treatment of NDs focused on to discover natural products that have the potential of anti-inhibition and anti-radical properties. The Papaveraceae family members are important for the synthesis of pharmaceutically compounds such as flavonoids which act like anti-inflammatory drugs. In this study, methanol and water extracts of Glaucium corniculatum, a member of the Papaveraceae family, were analysed for flavonoid compounds. The effects of extracts on neuronal PC12 cells viability was determined. The anti-inflammatory effects of extracts were assessed by measuring the levels of IL-6 and IL-10 cytokines on hydrogen peroxide (H2O2)-stimulated PC12 cells. As a result of our studies, Rutin and Quercetin flavonoids have been found to be as major. The amount of Rutin was higher in methanol (45 μg/ml) than water (41 μg/ml). Quercetin was better extracted with methanol (12 μg/ml) than water (10 μg/ml). None of the tested extracts were cytotoxic even to PC12 cells. Both extracts showed an anti-inflammatory effect in a dose dependent manner. The water extract showed the maximum anti-inflammatory effect, with IL-6 secretion decreased 79 fold according to the H2O2 treated group and IL-10 secretion increased to 87 fold according to the control group. This study is an evidence that the Rutin and Quercetin flavonoids detected in G. corniculatum methanol and water extracts have a neuroprotective effect through anti-inflammation.

Protective effect of secondary plant metabolites from Ipomoea aquatica Forsk. against carbofuran induced damages - Datta, Sanjukta; Sinha, Mahuya; Das, Dipesh; Ghosh, Santinath; Dhar, Pubali (Indian Journal of Experimental Biology, 2013)
Plausible interactions between food contaminants and natural constituents in vivo and protective effect of polyphenols present in I. aquatica against carbofuran toxicity in Charles Foster rats were evaluated. Determinations based on antioxidant enzyme activities showed significant alterations in glutathione, glutathione peroxidase, superoxide dismutase and catalase in tissues (liver and brain) and plasma of pesticide treated group while polyphenolic extracts from I. aquatica (IAE) attenuated their activities when given alongwith carbofuran. IAE decreased enhanced lipid peroxidation levels in plasma and erythrocyte membrane and cholesterol levels in brain and plasma. IAE also minimized histopathological degenerative changes produced by carbofuran. While single cell gel electrophoresis showed that secondary metabolites in leafy vegetables produced a combinatorial effect with pesticide at cellular level, DNA fragmentation level in bone marrow cells showed a decline in the IAE treated rats. Food safety adversely affected by various chemical contaminants can be retained by plant polyphenols and secondary plant constituents that can be found together in bolus. Therefore, the present study gives an insight into the protective role of naturally found polyphenols against pesticide toxicity.
Keywords: Antioxidant enzymes; Carbofuran; Flavonoids; Lipid peroxidation; Oxidative stress

Protective Effects of Rutin Against Deltamethrin-Induced Hepatotoxicity and Nephrotoxicity in Rats via Regulation of Oxidative Stress, Inammation and Apoptosis - Küçükler, Sefa; Kandemir, Fatih Mehmet; Özdemir, Selçuk; Çomaklı, Selim; Caglayan, Cuneyt (2021)
Deltamethrin (DLM) is a type-II pyrethroid synthetic insecticide that is extensively used for controlling mosquitoes, ies, pests, insects worldwide. Oxidative stress is one of the DLM toxicity mechanisms. This study was carried out to evaluate the likelihood protective effects of rutin (RUT), a natural antioxidant, against DLM-induced liver and kidney toxicities in rats. Hepatotoxicity and nephrotoxicity were evaluated after the rats were treated orally with DLM (1.28 mg/kg b.w.) alone or with RUT (25 and 50 mg/kg b.w.) for 30 days. DLM administration caused an increase in lipid peroxidation level and a decrease in activities of SOD, CAT, and GPx and GSH levels in the both tissues. DLM also increased serum ALT, AST, ALP, urea, and creatinine levels, while reduced nephrine levels in rats. In addition, DLM increased the activation of inammatory and apoptotic pathways by decreasing Bcl-2 and increasing TNF-α, NF-κB, IL-1β, p38α MAPK, COX-2, iNOS, beclin-1, Bax, and caspase-3 protein levels and/or activities. Furthermore, DLM increased mRNA expression levels of PARP-1, VEGF and immunohistochemical expressions of c-fos in the tissues. RUT treatment signicantly improved all examined parameters and restored the liver and kidney histopathological and immunohistochemical alterations. These ndings demonstrate that RUT could be used to ameliorate hepatotoxicity and nephrotoxicity associated with oxidative stress, inammation, and apoptosis in DLM-induced rats.
Keywords: Apoptosis; Deltamethrin; Hepatotoxicity; Nephrotoxicity; Oxidative stress; Rutin

Protective effects of rutin against deltamethrin-induced hepatotoxicity and nephrotoxicity in rats via regulation of oxidative stress, inflammation, and apoptosis - Küçükler, Sefa; Fatih, &; Kandemir, Mehmet; Özdemir, Selçuk; Çomaklı, Selim; Caglayan, Cuneyt
Deltamethrin is a type-II pyrethroid synthetic insecticide that is extensively used for controlling mosquitoes, flies, pests, and insects worldwide. This study was carried out to evaluate the likelihood protective effects of rutin, a natural antioxidant, against deltamethrin-induced liver and kidney toxicities in rats. Hepatotoxicity and nephrotoxicity were evaluated after the rats were treated orally with deltamethrin (1.28 mg/kg b.w.) alone or with rutin (25 and 50 mg/kg b.w.) for 30 days. Deltamethrin administration caused an increase in lipid peroxidation level and a decrease in activities of SOD, CAT, GPx, and GSH levels in the both tissues. Deltamethrin also increased serum ALT, AST, ALP, urea, and creatinine levels, while reduced nephrine levels in rats. In addition, deltamethrin increased the activation of inflammatory and apoptotic pathways by decreasing Bcl-2 and increasing TNF-α, NF-κB, IL-1β, p38α MAPK, COX-2, iNOS, beclin-1, Bax, and caspase-3 protein levels and/or activities. Furthermore, deltamethrin increased mRNA expression levels of PARP-1, VEGF, and immunohistochemical expressions of c-fos in the tissues. Rutin treatment significantly improved all examined parameters and restored the liver and kidney histopath-ological and immunohistochemical alterations. These findings demonstrate that rutin could be used to ameliorate hepatotoxicity and nephrotoxicity associated with oxidative stress, inflammation, and apoptosis in deltamethrin-induced rats.
Keywords: Apoptosis; Deltamethrin; Hepatotoxicity; Nephrotoxicity; Oxidative stress; Rutin

Ion channels as insecticide targets - ffrench-Constant, Richard H.; Williamson, Martin S.; Davies, T. G.Emyr; Bass, Chris (Journal of Neurogenetics, 2016)
Ion channels remain the primary target of most of the small molecule insecticides. This review examines how the subunit composition of heterologously expressed receptors determines their insecticide-specific pharmacology and how the pharmacology of expressed receptors differs from those found in the insect nervous system. We find that the insecticide-specific pharmacology of some receptors, like that containing subunits of the Rdl encoded GABA receptor, can be reconstituted with very few of the naturally occurring subunits expressed. In contrast, workers have struggled even to express functional insect nicotinic acetylcholine receptors (nAChRs), and work has therefore often relied upon the expression of vertebrate receptor subunits in their place. We also examine the extent to which insecticide-resistance-associated mutations, such as those in the para encoded voltage-gated sodium channel, can reveal details of insecticide-binding sites and mode of action. In particular, we examine whether mutations are present in the insecticide-binding site and/or at sites that allosterically affect the drug preferred conformation of the receptor. We also discuss the ryanodine receptor as a target for the recently developed diamides. Finally, we examine the lethality of the genes encoding these receptor subunits and discuss how this might determine the degree of conservation of the resistance-associated mutations found.
Keywords: Drosophila; Insecticide resistance; ion channels

DISCREPANCY BETWEEN ACUTE AND CHRONIC TOXICITY INDUCED BY IMIDACLOPRID AND ITS METABOLITES IN APIS MELLIFERA - Verine Suchail, Sé; Guez, David; Belzunces, Luc P (Environmental Toxicology and Chemistry, 2001)
Imidacloprid is a systemic nitroguanidine insecticide that belongs to the neonicotinoid family. As an agonist of the acetylcholine receptor, it attacks the insect nervous system and is extremely effective against various sucking and mining pests. Oral acute and chronic toxicity of imidacloprid and its main metabolites (5-hydroxyimidacloprid, 4,5-dihydroxyimidacloprid, desnitroimidacloprid, 6-chloronicotinic acid, olefin, and urea derivative) were investigated in Apis mellifera. Acute intoxication by imidacloprid or its metabolites resulted in the rapid appearance of neurotoxicity symptoms, such as hyperresponsiveness, hyper-activity, and trembling and led to hyporesponsiveness and hypoactivity. For acute toxicity tests, bees were treated with doses of toxic compounds ranging from 1 to 1,000 ng/bee (10-10,000 g/kg). Acute toxicity (LD50) values of imidacloprid were about 60 ng/bee (600 g/kg) at 48 h and about 40 ng/bee (400 g/kg) at 72 and 96 h. Out of the six imidacloprid metabolites tested, only two (5-hydroxyimidacloprid and olefin) exhibited a toxicity close to that of imidacloprid. Olefin LD50 values were lower than those of imidacloprid. The 5-hydroxyimidacloprid showed a lower toxicity than imidacloprid with a LD50 four to six times higher than that of imidacloprid. Urea also appeared as a compound of nonnegligible toxicity by eliciting close to 40% mortality at 1,000 ng/bee (10,000 g/kg). However, no significant toxicity was observed with 4,5-dihydroxyimidacloprid, 6-chloronicotinic acid, and desnitroimidacloprid in the range of doses tested. To test chronic toxicity, worker bees were fed sucrose solutions containing 0.1, 1, and 10 g/L of imidacloprid and its metabolites for 10 d. Fifty percent mortality was reached at approximately 8 d. Hence, considering that sucrose syrup was consumed at the mean rate of 12 l/d and per bee, after an 8-d period the cumulated doses were approximately 0.01, 0.

Metabolism of imidacloprid in Apis mellifera - Suchail, Séverine; Debrauwer, Laurent; Belzunces, Luc P. (Pest Management Science, 2004)
Biotransformation of imidacloprid and the appearance of olefin and 5-hydroxyimidacloprid metabolites in the honeybee were studied by HPLC-MS/MS analysis. Honeybees were treated orally with imidacloprid at 20 and 50 μg kg-1 bee. Imidacloprid was metabolised relatively quickly and thoroughly. Twenty minutes after the beginning of imidacloprid ingestion, the sum of the residues from the three compounds amounted to only 70% of the actual given dose. Imidacloprid, 5-hydroxyimidacloprid and olefin represented, respectively, 50%, 9% and 8% of the actual ingested dose. Six and 24h, respectively, after ingestion of imidacloprid at 20 and 50 μg kg -1 bee, imidacloprid could no longer be detected in the honeybee. Imidacloprid had a half-life ranging between 4.5 and 5h and was rapidly metabolised into 5-hydroxyimidacloprid and olefin. Except 5-hydroxyimidacloprid in the 20 μg kg-1 treatment, these two metabolites presented a peak value 4h after ingestion of the 20 and 50 μg kg-1 doses. This time fully coincided with the appearance of mortality induced by imidacloprid after acute oral intoxication. These results suggested that the immediate neurotoxicity symptoms are due to the action of imidacloprid, whereas 5-hydroxyimidacloprid and/or olefin are involved in honeybee mortality. In addition, it was likely that the 30% of residues undetected 20min after intoxication were imidacloprid metabolites, although not 5-hydroxyimidacloprid or olefin. Thus, 5-hydroxyirnidacloprid and olefin could not be the major metabolites in the worker bees. © 2003 Society of Chemical Industry.
Keywords: Honeybee; Imidacloprid; LC-MS/MS; Metabolisation; Metabolite

Effects of Sinusoidal Vibrations on the Motion Response of Honeybees - Stefanec, Martin; Oberreiter, Hannes; Becher, Matthias A.; Haase, Gundolf; Schmickl, Thomas (Frontiers in Physics, 2021)
Vibratory signals play a major role in the organization of honeybee colonies. Due to the seemingly chaotic nature of the mechano-acoustic landscape within the hive, it is difficult to understand the exact meaning of specific substrate-borne signals. Artificially generated vibrational substrate stimuli not only allow precise frequency and amplitude control for studying the effects of specific stimuli, but could also provide an interface for human-animal interaction for bee-keeping-relevant colony interventions. We present a simple method for analyzing motion activity of honeybees and show that specifically generated vibrational signals can be used to alter honeybee behavior. Certain frequency-amplitude combinations can induce a significant decrease and other signals might trigger an increase in honeybees’ motion activity. Our results demonstrate how different subtle local modulatory signals on the comb can influence individual bees in the local vicinity of the emitter. Our findings could fundamentally impact our general understanding of a major communication pathway in honeybee colonies. This pathway is based on mechanic signal emission and mechanic proprio-reception of honeybees in the bee colony. It is a candidate to be a technologically accessible gateway into the self-regulated system of the colony and thus may offer a novel information transmission interface between humans and honeybees for the next generation of “smart beehives” in future beekeeping.
Keywords: behavior; freezing responds; honeybees; modulatory signals; substrate-born communication

Bioinsecticidal effect of the flavonoids pinocembrin and quercetin against Spodoptera frugiperda - Diaz Napal, Georgina N.; Palacios, Sara M. (Journal of Pest Science, 2015)
Flavonoids function in many aspects of plant–insect interactions, but the responses of insects to these compounds vary greatly. In this study, we determined the effects of two widely distributed flavonoids, pinocembrin and quercetin, on the feeding behavior, survival, and development of the fall armyworm Spodoptera frugiperda J.E. (Smith) (Lepidoptera: Noctuidae). In a choice test, S. frugiperda larvae strongly rejected leaves treated with pinocembrin at concentrations of 10, 50, or 100 μg/cm2. Larvae fed normally on leaves treated with quercetin at 10 and 50 μg/cm2, but showed 57 % deterrence when fed on leaves treated with 100 μg/cm2 quercetin. At concentrations of 0.01–1 µg/cm2, pinocembrin and quercetin functioned as phagostimulants for S. frugiperda. In a multiple-choice experiment, S. frugiperda larvae preferred to consume untreated leaves or those treated with 0.1 µg/cm2 pinocembrin, but rejected leaves treated with 5–50 µg/cm2 pinocembrin. In a no-choice feeding experiment, larvae fed on leaves treated with 5 and 50 μg/cm2 pinocembrin consumed less than those fed on leaves treated with 0.1 and 1 μg/cm2 pinocembrin or untreated leaves. Pinocembrin at 1–50 μg/cm2 negatively affected larval weight and survival, thus showing a toxic effect. In contrast, leaf consumption and larval weight were not significantly affected by quercetin at 0.1, 1, 5, and 50 μg/cm2, and mortality rates only slightly increased. Because of its dual activity, pinocembrin could be used for insect control in a stimulo-deterrent diversionary strategy: the same compound could promote both stimulate (low doses) and deter insect activity (high doses).
Keywords: Antifeedant; Flavonoids; Lepidoptera; Noctuidae; Pinocembrin; Quercetin

In Vitro Insecticidal Effect of Commercial Fatty Acids, β-Sitosterol, and Rutin against the Sugarcane Aphid, Melanaphis sacchari Zehntner (Hemiptera: Aphididae) - Aguilar-Marcelino, Liliana; Pineda-Alegría, Jesús Antonio; Salinas-Sánchez, David Osvaldo; Hernández-Velázquez, Víctor Manuel; Silva-Aguayo, Gonzalo Iván; Navarro-Tito, Napoleón; Sotelo-Leyva, César (Journal of Food Protection, 2022)
The sugarcane aphid, Melanaphis sacchari Zehntner (Hemiptera: Aphididae), is the main pest of sorghum, Sorghum bicolor L. Moench (Poaceae), in Mexico. To control this insect, farmers currently use synthetic chemical insecticides, which are toxic to humans and biodiversity. However, natural products are a promising potential source of safer alternative means to control different agricultural pests. The main objective of this study was to evaluate the insecticidal effect of contact by fumigation of pure molecules of four commercial fatty acids (palmitic, stearic, pentadecanoic, and linoleic acids), the phytosterol b-sitosterol, and the flavonoid rutin. The results showed that fatty acids were the most effective against M. sacchari; the highest mortality rate (85%) was produced by linoleic acid and the mean lethal concentration was 1,181 ppm, followed by stearic and palmitic acids with 74 and 63% mortality, respectively, at a concentration of 2,500 ppm at 72 h. The positive control, imidacloprid, had 100% mortality in 24 h and the Tween 20, negative control, exhibited 4% mortality in 72 h. Our results show that commercial fatty acids are effective against adults of M. sacchari and can be considered an environmentally friendly alternative to the frequent use of synthetic chemical insecticides.
Keywords: Aphids; Mortality; Pest; Pure compounds

Efeito do flavonoide rutina na biologia de Spodoptera frugiperda (Lepidoptera: Noctuidae) - Silva, Talita Roberta Ferreira Borges; Almeida, André Cirilo de Sousa; Moura, Tony de Lima; da Silva, Anderson Rodrigo; Freitas, Silvia de Sousa; Jesus, Flávio Gonçalves (Acta Scientiarum - Agronomy, 2016)
The fall armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is a major pest of maize crops in Brazil. The effects of plant metabolites on the biology and behavior of insects is little studied. The aim of the study was to evaluate the activity of rutin on the biology of the S. frugiperda by using artificial diets containing rutin. The study evaluated four treatments: regular diet (control group) and diets containing 1.0, 2.0 and 3.0 mg g-1 of rutin. The following biological variables parameters of the larvae were evaluated daily: development time (days), larval and pupal weight (g) and viability (%), adult longevity and total life cycle (days). A completely randomized experimental design was used with 25 replication. The rutin flavonoid negatively affected the biology of S. frugiperda by prolonging the larval development time, reducing the weight of larvae and pupae and decreasing the viability of the pupae. The addition of different concentrations of rutin prolonged the S. frugiperda life cycle. The use of plant with insecticidal activity has the potential with strategy in IPM.
Keywords: Fall armyworm; Flavonoid; Insecticide platnt; Secondary metabolite

Biopesticide synergy when combining plant flavonoids and entomopathogenic baculovirus - Hay, William T.; Behle, Robert W.; Berhow, Mark A.; Miller, Andie C.; Selling, Gordon W. (Scientific Reports, 2020)
Four crop plants known to be hosts for the lepidopteran Trichoplusia ni (soybean, green bean, cotton, and cabbage) were treated with the biopesticide AfMNPV baculovirus in a dosage response assay. Treated soybean had, on average, a 6-fold increase in virus activity compared with the other crops. Leaf trichomes on soybeans were not found to be responsible for the observed increase of insecticidal activity. Three flavonoid compounds (daidzein, genistein, and kaempferol) were uniquely found only in the soybean crop, and were not detected in cotton, cabbage, or green bean plant matter. The individual flavonoid compounds did not cause T ni. mortality in no-virus assays when incorporated into artificial insect diet. The combination of the three flavonoid compounds at leaf level concentrations significantly increased baculovirus activity in diet incorporation assays. When the daidzein, genistein, and kaempferol were added to artificial diet, at 3.5–6.5 × leaf level concentrations, virus activity increased 1.5, 2.3, and 4.2-fold for each respective flavonoid. The soybean flavonoid compounds were found to synergistically improve baculovirus activity against T. ni.

Phenotypic and Transcriptomic Response of the Grasshopper Oedaleus asiaticus (Orthoptera: Acrididae) to Toxic Rutin - Huang, Xunbing; Lv, Shenjin; Zhang, Zehua; Chang, Babar Hussain (Frontiers in Physiology, 2020)
Rutin, a widely distributed phytochemical flavonoid, can be used to control insect pests. In this study, we studied the growth performance of the grasshopper Oedaleus asiaticus Bey-Bienko given xenobiotic rutin using feeding experiments and transcriptomic analysis. O. asiaticus had reduced body size, lower survival rate, and reduced growth performance when fed with xenobiotic rutin. Rutin-fed nymphs had large variation in gene expression profiles, with a total of 308 genes significantly upregulated and 287 genes downregulated. The upregulated genes were significantly enriched in stress resistance-, immune-, and detoxification-related biological processes and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Downregulated genes mainly involved cuticle biosynthesis and nutrition metabolism-related pathways. The quantitative real-time PCR (qRT-PCR) analysis of 15 candidate genes also produced results consistent with the transcriptome data. These results suggested that grasshoppers’ capacity for biosynthesis and nutrition metabolism decreased, and stress resistance and metabolized capacity to toxic substances were significantly induced when O. asiaticus was fed on xenobiotic rutin. Rutin, as a phytotoxin, had detrimental effects and induced changes in gene expression profiles for O. asiaticus. This study can provide a molecular basis and offer future opportunities for the development of rutin-related insecticides and their application to grasshopper control.
Keywords: biopesticides; grasshopper; phenotype; rutin; transcriptomics

Larvicidal and repellent potential of Ageratum houstonianum against Culex pipiens - Hadidy, Doaa El; El Sayed, Abeer M.; Tantawy, Mona El; Alfy, Taha El; Farag, Shaimaa M.; Haleem, Doaa R.Abdel (Scientific Reports, 2022)
Mosquitoes are unquestionably the most medic arthropod vectors of disease. Culex pipiens, usually defined as a common house mosquito, is a well-known carrier of several virus diseases. Crude ethanol extracts of different organs of Agratum houstonianum are tested with Culex pipiens Linnaeus (Diptera: Culicidae) to determine their larvicidal, antifeedant, and repellency effects. Alongside biochemical analysis, the activity of the AChE, ATPase, CarE, and CYP-450 is detected in the total hemolymph of the C. pipiens larvae to examine the enzymatic action on the way to explain their neurotoxic effect and mode of action. Through HPLC and GC–MS analysis of the phytochemical profile of A. houstonianum aerial parts is identified. The larvicidal activity of aerial parts; flower (AF), leaf (AL), and stem (AS) of A. houstonianum extracts are evaluated against the 3rd instar larvae of C. pipiens at 24-, 48- and 72-post-treatment. A. houstonianium AF, AL, and AS extracts influenced the mortality of larvae with LC50 values 259.79, 266.85, and 306.86 ppm, respectively after 24 h of application. The potency of AF and AL extracts was 1.69- and 1.25-folds than that of AS extract, respectively. A high repellency percentage was obtained by AF extract 89.10% at a dose of 3.60 mg/cm2. A. houstonianium AF prevailed inhibition on acetylcholinesterase and decrease in carboxylesterase activity. Moreover, a significant increase in the ATPase levels and a decrease in cytochrome P-450 monooxegenase activity (− 36.60%) are detected. HPLC analysis prevailed chlorogenic and rosmarinic acid as the major phenolic acids in AL and AF, respectively. GC–MS analysis of A. houstonianum results in the identification of phytol as the major makeup. Precocene I and II were detected in AF. Linoleic, linolenic, and oleic acid were detected in comparable amounts in the studied organs. Overall, results suggest that the A. houstonianum flower extract (AF) exhibits significant repellent, antifeedant, and larvicidal activities.

Flavonoids: An overview - Panche, A. N.; Diwan, A. D.; Chandra, S. R. (Journal of Nutritional Science, 2016)
Flavonoids, a group of natural substances with variable phenolic structures, are found in fruits, vegetables, grains, bark, roots, stems, flowers, tea and wine. These natural products are well known for their beneficial effects on health and efforts are being made to isolate the ingredients so called flavonoids. Flavonoids are now considered as an indispensable component in a variety of nutraceutical, pharmaceutical, medicinal and cosmetic applications. This is attributed to their anti-oxidative, anti-inflammatory, anti-mutagenic and anti-carcinogenic properties coupled with their capacity to modulate key cellular enzyme function. Research on flavonoids received an added impulse with the discovery of the low cardiovascular mortality rate and also prevention of CHD. Information on the working mechanisms of flavonoids is still not understood properly. However, it has widely been known for centuries that derivatives of plant origin possess a broad spectrum of biological activity. Current trends of research and development activities on flavonoids relate to isolation, identification, characterisation and functions of flavonoids and finally their applications on health benefits. Molecular docking and knowledge of bioinformatics are also being used to predict potential applications and manufacturing by industry. In the present review, attempts have been made to discuss the current trends of research and development on flavonoids, working mechanisms of flavonoids, flavonoid functions and applications, prediction of flavonoids as potential drugs in preventing chronic diseases and future research directions.

Rutin and gallic acid regulates mitochondrial functions via the sirt1 pathway in c2c12 myotubes - Chang, Wei Tang; Huang, Shih Chien; Cheng, Hsin Lin; Chen, Shiuan Chih; Hsu, Chin Lin (Antioxidants, 2021)
Mitochondria are highly dynamic organelles, balancing synthesis and degradation in response to increases in mitochondrial turnover (i.e., biogenesis, fusion, fission, and mitophagy) and function. The aim of this study was to investigate the role of polyphenols in the regulation of mito-chondrial functions and dynamics in C2C12 myotubes and their molecular mechanisms. Our results indicate that gallic acid and rutin are the most potential polyphenol compounds in response to 15 phenolic acids and 5 flavonoids. Gallic acid and rutin were associated with a significantly greater mitochondrial DNA (cytochrome b and COX-II), mitochondrial enzymatic activities (including citrate synthase and cytochrome c oxidase), and intracellular ATP levels in C2C12 myotubes. Moreover, gallic acid and rutin significantly increased the gene expressions of mitochondrial turnover in C2C12 myotubes. Our findings indicated that gallic acid and rutin may have a beneficial effect on mitochondrial dynamics via regulation of the SIRT1-associated pathway in C2C12 myotubes.
Keywords: C2C12 myotubes; Gallic acid; Mitochondria; Rutin; Sirtuin-1

Phenolic acids: Natural versatile molecules with promising therapeutic applications - Kumar, Naresh; Goel, Nidhi (Biotechnology Reports, 2019)
Plant phenolics are considered to be a vital human dietary component and exhibit a tremendous antioxidant activity as well as other health benefits. Epidemiology evidence indicates that a diet rich in antioxidant fruits and vegetables significantly reduces the risk of many oxidative stress related diseases viz. cancers, diabetes and cardiovascular. The number and position of hydroxyl group in a particular phenolic compound leads to the variation in their antioxidant potential. Polyphenols are the main source of dietary antioxidants, and are effortlessly absorbed in the intestine. Phenolic acids, a sub class of plant phenolics, possess phenol moiety and resonance stabilized structure which causes the H-atom donation results in antioxidant property through radical scavenging mechanism. Other mode such as radical quenching via electron donation and singlet oxygen quenching are also known for the antioxidant activity of phenolic acids. Furthermore, phenolic acids are found ubiquitously and well documented for other health protective effects like antimicrobial, anticancer, anti-inflammatory, anti-mutagenic etc. The contribution emphasize on the phenolic acids potential in drug discovery. In addition their occurrence, biosynthesis, metabolism and health effects are discussed in detail.
Keywords: Antioxidant; Biomedical applications; Natural medicine; Phenolic acids; Phytochemical

Effects of Dietary Rutin Supplementation on the Intestinal Morphology, Antioxidant Capacity, Immunity, and Microbiota of Aged Laying Hens - Li, Hengzhi; Gu, Yunfeng; Jin, Rui; He, Qingfen; Zhou, Yanmin (Antioxidants, 2022)
This research investigated the effects of dietary rutin supplementation on the intestinal morphology, antioxidant capacity, immunity, and microbiota of aged laying hens. The results showed that 500 mg/kg rutin supplementation increased the villus height of jejunum (P < 0.05). Rutin affected the immune system of the ileum and the jejunum. In the jejunum, a diet with 500 mg/kg rutin supplementation enhanced secretory immunoglobulin A (sIgA) and reduced tumor necrosis factor- (Formula presented.) (TNF- (Formula presented.)) levels (P < 0.05). A diet with 1000 mg/kg rutin supplementation increased jejunal sIgA, immunologlobulin M (IgM), and interleukin-4 (IL-4) levels while decreasing interleukin-1 (Formula presented.) (IL-1 (Formula presented.)), TNF- (Formula presented.), and interferon- (Formula presented.) (IFN- (Formula presented.)) levels (P < 0.05). Meanwhile, a diet with 500 mg/kg rutin increased sIgA, immunologlobulin G (IgG), IgM, and interleukin-10 (IL-10) levels and reduced TNF- (Formula presented.) and IFN- (Formula presented.) levels in the ileum (P < 0.05). In the ileum, a diet with 1000 mg/kg rutin supplementation raised sIgA, IgG, IgM, IL-4, and IL-10 levels while decreasing IL-1 (Formula presented.), TNF- (Formula presented.), and IFN- (Formula presented.) levels (P < 0.05). At the family level, a diet with 500 mg/kg rutin supplementation raised the relative abundance of Monoglobaceae and decreased the relative abundance of Eubacteriaceae (P < 0.05) compared to the control group. In the 1000 mg/kg rutin group, the relative abundance of Lactobacillaceae and Unclassified Coriobacteriale was considerably lower and the relative abundance of Monoglobaceae was higher than the control group (P < 0.05). This study showed that a diet with rutin supplementation can improve the intestinal health of aged laying hens, and the mechanism is related to improving the intestinal morphology and intestinal immune status, and regulating the intestinal microbes.
Keywords: aged laying hens; antioxidant capacity; immunity; intestinal morphology; microbiota; rutin

Conversion of Rutin, a Prevalent Dietary Flavonol, by the Human Gut Microbiota - Riva, Alessandra; Kolimár, Ditta; Spittler, Andreas; Wisgrill, Lukas; Herbold, Craig W.; Abrankó, László; Berry, David (Frontiers in Microbiology, 2020)
The gut microbiota plays a pivotal role in the conversion of dietary flavonoids, which can affect their bioavailability and bioactivity and thereby their health-promoting properties. The ability of flavonoids to metabolically-activate the microbiota has, however, not been systematically evaluated. In the present study, we used a fluorescence-based single-cell activity measure [biorthogonal non-canonical ammino acid-tagging (BONCAT)] combined with fluorescence activated cell sorting (FACS) to determine which microorganisms are metabolically-active after amendment of the flavonoid rutin. We performed anaerobic incubations of human fecal microbiota amended with rutin and in the presence of the cellular activity marker L-azidohomoalanine (AHA) to detect metabolically-active cells. We found that 7.3% of cells in the gut microbiota were active after a 6 h incubation and 26.9% after 24 h. We then sorted BONCAT-positive cells and observed an enrichment of Lachnospiraceae (Lachnoclostridium and Eisenbergiella), Enterobacteriaceae, Tannerellaceae, and Erysipelotrichaceae species in the rutin-responsive fraction of the microbiota. There was marked inter-individual variability in the appearance of rutin conversion products after incubation with rutin. Consistent with this, there was substantial variability in the abundance of rutin-responsive microbiota among different individuals. Specifically, we observed that Enterobacteriaceae were associated with conversion of rutin into quercetin-3-glucoside (Q-glc) and Lachnospiraceae were associated with quercetin (Q) production. This suggests that individual microbiotas differ in their ability to metabolize rutin and utilize different conversion pathways.
Keywords: dietary bioactives; fluorescence activated cell sorting; gut microbiota; inter-individual variability; rutin; rutin metabolism

Influence of diet on the gut microbiome and implications for human health - Singh, Rasnik K.; Chang, Hsin Wen; Yan, Di; Lee, Kristina M.; Ucmak, Derya; Wong, Kirsten; Abrouk, Michael; Farahnik, Benjamin; Nakamura, Mio; Zhu, Tian Hao; Bhutani, Tina; Liao, Wilson (Journal of Translational Medicine, 2017)
Recent studies have suggested that the intestinal microbiome plays an important role in modulating risk of several chronic diseases, including inflammatory bowel disease, obesity, type 2 diabetes, cardiovascular disease, and cancer. At the same time, it is now understood that diet plays a significant role in shaping the microbiome, with experiments showing that dietary alterations can induce large, temporary microbial shifts within 24 h. Given this association, there may be significant therapeutic utility in altering microbial composition through diet. This review systematically evaluates current data regarding the effects of several common dietary components on intestinal microbiota. We show that consumption of particular types of food produces predictable shifts in existing host bacterial genera. Furthermore, the identity of these bacteria affects host immune and metabolic parameters, with broad implications for human health. Familiarity with these associations will be of tremendous use to the practitioner as well as the patient.
Keywords: Diet; Health; Metabolism; Microbiome; Microbiota; Nutrition

Rutin alleviates colon lesions and regulates gut microbiota in diabetic mice - Cai, Cifeng; Cheng, Wenwen; Shi, Tiantian; Liao, Yueling; Zhou, Meiliang; Liao, Zhiyong (Scientific Reports, 2023)
Diabetes is a common metabolic disorder that has become a major health problem worldwide. In this study, we investigated the role of rutin in attenuating diabetes and preventing diabetes-related colon lesions in mice potentially through regulation of gut microbiota. The rutin from tartary buckwheat as analyzed by HPLC was administered intragastrically to diabetic mice, and then the biochemical parameters, overall community structure and composition of gut microbiota in diabetic mice were assayed. The results showed that rutin lowered serum glucose and improved serum total cholesterol, low-density lipoprotein, high-density lipoprotein, triglyceride concentrations, tumor necrosis factor-α, interleukin-6, and serum insulin in diabetic mice. Notably, rutin obviously alleviated colon lesions in diabetic mice. Moreover, rutin also significantly regulated gut microbiota dysbiosis and enriched beneficial microbiota, such as Akkermansia (p < 0.05). Rutin selectively increased short-chain fatty acid producing bacteria, such as Alistipes (p < 0.05) and Roseburia (p < 0.05), and decreased the abundance of diabetes-related gut microbiota, such as Escherichia (p < 0.05) and Mucispirillum (p < 0.05). Our data suggested that rutin exerted an antidiabetic effect and alleviated colon lesions in diabetic mice possibly by regulating gut microbiota dysbiosis, which might be a potential mechanism through which rutin alleviates diabetes-related symptoms.

Protective effects of dietary flavonoids against pesticide-induced toxicity: A review - Zeng, Xiangquan; Du, Zhenjiao; Ding, Xiaomeng; Jiang, Weibo (Trends in Food Science and Technology, 2021)
Background: Pesticide exposure is closely associated with the incidence of various severe diseases in humans, including immune dysfunctions, respiratory problems and neurobehavioral disorders. Although several drugs are utilized for the treatment of pesticide intoxication in patients, the side effects have limited their use. It has been demonstrated that generation of oxidative stress is a main mechanism involved in pesticide-induced toxicity. Naturally, there is an increasing interest in screening safe antioxidants and evaluating their potentials of reducing oxidative stress induced by pesticides. Flavonoids are members of the polyphenol family and possess strong antioxidant properties. Based on the results of previous studies, a series of dietary flavonoids exhibit protective effects against pesticide-induced toxicity both in vitro and in vivo. Scope and approach: This paper mainly focused on the preventive roles of quercetin, naringin, naringenin, (+)-catechin, (−)-epicatechin, (−)-epigallocatechin-3-gallate, hesperidin, rutin, apigenin, luteolin and taxifolin against pesticide-induced toxicity in cell and animal models. The possible mechanisms for the protection of these flavonoids from pesticide-induced toxicity were critically reviewed as well. Key findings and conclusions: Dietary flavonoids could protect cells and animals from pesticide toxicity through their antioxidant, anti-inflammatory, anti-apoptotic, anti-mutagenic, anti-stress properties, effects on improving organ functions, activating the immune system, promoting the xenobiotic excretion from the body, modulating the levels of neurotransmitters and hormones as well as regulating lipid and energy metabolisms. In addition, we introduced the issues that need to be resolved in future investigations and pointed out current challenges of developing flavonoids into therapeutic agents for pesticide intoxication.
Keywords: Flavonoids; Oxidative stress; Pesticides; Possible mechanisms; Protective effects; Toxicity

Honey bee (Apis mellifera) colony strength and its effects on pollination and yield in highbush blueberries (Vaccinium corymbosum) - Grant, Kennedy Judith; DeVetter, Lisa; Melathopoulos, Andony (PeerJ, 2021)
Many pollination studies with honey bees have examined the effect of colony density on crop yield and yet overlook the effect of variation in the population size of these colonies. High colony density in northern highbush blueberry has been met with concerns from beekeepers who feel higher densities will intensify outbreaks of European foulbrood (EFB, Melissococcus plutonius, Truper and dé Clari), a honey bee brood disease. The purpose of this study was to confirm the prevalence of EFB in colonies pollinating blueberries and to determine whether field-level variation in the population of adult workers in colonies explained variation in blueberry fruit set and/or yield. We addressed these objectives over the course of two production seasons at 13 commercial blueberry fields in Oregon, USA, stocked with identical densities of 10 colonies/ha. We confirmed that all colonies had negligible symptoms of EFB at the start of blueberry pollination, but 53% of colonies in 2019 and 41% in 2020 had symptoms immediately following the pollination season. We also validated a method for rapidly assessing adult honey bee colony populations, namely by counting the rate of foragers returning to colonies, and it was found to be strongly correlated to true internal adult bee population independent of year and ambient temperature at the time of evaluation. Using returning forager counts, we determined there was considerable variation in the average population of colonies at each field, ranging from an estimated 10,300 to 30,700 adult worker bees per colony. While average colony strength did not predict variation in fruit set, it was related to variation in yield, independent of year. Our linear model of flight count (as a proxy for colony strength) predicts estimated yield increases of up to 25,000 kg/ha of blueberries could be achieved by colonies stronger than the recommended six frame minimum, suggesting that higher pollination benefits could be achieved without increasing hive density if stronger colonies are promoted.
Keywords: Cluster count; Crop pollination; European foulbrood; Floral visitation; Pollination; Stocking rate

Importance of pollinators in changing landscapes for world crops - Klein, Alexandra Maria; Vaissière, Bernard E.; Cane, James H.; Steffan-Dewenter, Ingolf; Cunningham, Saul A.; Kremen, Claire; Tscharntke, Teja (Proceedings of the Royal Society B: Biological Sciences, 2007)
The extent of our reliance on animal pollination for world crop production for human food has not previously been evaluated and the previous estimates for countries or continents have seldom used primary data. In this review, we expand the previous estimates using novel primary data from 200 countries and found that fruit, vegetable or seed production from 87 of the leading global food crops is dependent upon animal pollination, while 28 crops do not rely upon animal pollination. However, global production volumes give a contrasting perspective, since 60% of global production comes from crops that do not depend on animal pollination, 35% from crops that depend on pollinators, and 5% are unevaluated. Using all crops traded on the world market and setting aside crops that are solely passively self-pollinated, wind-pollinated or parthenocarpic, we then evaluated the level of dependence on animal-mediated pollination for crops that are directly consumed by humans. We found that pollinators are essential for 13 crops, production is highly pollinator dependent for 30, moderately for 27, slightly for 21, unimportant for 7, and is of unknown significance for the remaining 9. We further evaluated whether local and landscape-wide management for natural pollination services could help to sustain crop diversity and production. Case studies for nine crops on four continents revealed that agricultural intensification jeopardizes wild bee communities and their stabilizing effect on pollination services at the landscape scale. © 2006 The Royal Society.
Keywords: Agriculture; Biodiversity; Conservation; Pollination; Spatial ecology; Wild bees

Toward the protection of bees and pollination under global change: present and future perspectives in a challenging applied science - Decourtye, Axel; Alaux, Cédric; Le Conte, Yves; Henry, Mickaël (Current Opinion in Insect Science, 2019)
Over the past 30 years (1987–2016), bibliometric data have shown a drastic change in the scientific investigation of threats to bee populations. Bee research efforts committed to studying bioagressors of honeybees (mainly Varroa sp.) were predominant, but now appear to be shifting from bioagressors to global change in the published literature. This rise of global change science reveals prevailing topics, for current and future years: climate change, landscape alteration, agricultural intensification and invasive species. We argue that with increased investment in applied research and development, the scientific, beekeeping and agricultural communities will be able to find management strategies for productive agrosystems and enhanced resilience of pollination and beekeeping. This implies the need for restoring and improving food resources and shelters of bees by ecological intensification of diversified farming systems, and also reconciling sustainable beekeeping with wild pollinator conservation.

Supplementary honey bee (Apis mellifera L.) pollination enhances fruit growth rate and fruit yield in Paeonia ostii (family: Paeoniaceae) - Zhang, Kaiyue; Li, Yuying; Sun, Kaili; Bao, Junyi; He, Chunling; Hou, Xiaogai (PLoS ONE, 2022)
Insufficient pollination leads to low and unstable production of oil tree peony. Supplementary managed honeybees (Apis mellifera L.) in agricultural ecosystems is a common practice for addressing the problem. At this study site (N 34°38030@ and E 112°39043@, with an altitude of 125.5 m), we set up four pollination areas (low-density bee pollination group (LDBP), highdensity bee pollination group (HDBP), blank control group (CK1) and field control group (CK2)) to examine the pollination effectiveness of different densities of honeybee supplementation on oil tree peony (Paeonia ostii). Our work demonstrated that bee-pollination increased fruit size and growth rate. On average, bee-pollinated (LDBP) plants produced 63.16% more number of seeds per plant, showed also 53.47% more weight of seeds per plant than those in CK2. Also, seeds of LDBP contained, on average, 26.15% more oil content than CK2. Kernel percent and seed oil fatty acid content, however, were unaffected (F = 1.759, p = 0.074). Compared with LDBP, weight of seeds per plant and oil content with HDBP decreased by 21.89% and 2.63%, respectively. Following the same trend, compared with LDBP, HDBP slowed fruit growth and reduced fruit size. Our results showed that insufficient pollination limits fruit set in oil tree peony, while supplementary reasonable bee density in the field for pollination is an important strategy to maximize fruit yield.

Bumble bee ecophysiology: integrating the changing environment and the organism - Woodard, S. Hollis (Current Opinion in Insect Science, 2017)
Bumble bees are among the most ecologically and economically important pollinators worldwide, yet many of their populations are being threatened by a suite of interrelated, human-mediated environmental changes. Here, I discuss recent progress in our understanding of bumble bee ecophysiology, including advances related to thermal biology in light of global warming; nutritional biology in the context of declining food resources; and the capacity for bumble bees to exhibit physiological plasticity or adaptations to novel or extreme environments, with reference to their evolutionary history and current biogeography.

Operative temperature analysis of the honey bee Apis mellifera - Stupski, Stanley D.; Schilder, Rudolf J. (Journal of Experimental Biology, 2021)
A key challenge for linking experiments of organisms performed in a laboratory environment to their performance in more complex environments is to determine thermal differences between a laboratory and the energetically complex terrestrial ecosystem. Studies performed in the laboratory do not account for many factors that contribute to the realized temperature of an organism in its natural environment. This can lead to modelling approaches that use experimentally derived data to erroneously link the air temperature in a laboratory to air temperatures in energetically heterogenous ecosystems. Traditional solutions to this classic problem assume that animals in an isotropic, isothermal chamber behave either as pure heterothermic ectotherms (body temperature=chamber temperature) or homeothermic endotherms (body temperature is entirely independent of chamber temperature). This approach may not be appropriate for endothermic insects which exist as an intermediate between strongly thermoregulating endotherms and purely thermoconforming species. Here, we use a heat budget modelling approach for the honey bee Apis mellifera to demonstrate that the unique physiology of endothermic insects may challenge many assumptions of traditional biophysical modelling approaches. We then demonstrate under modelled field-realistic scenarios that an experiment performed in a laboratory has the potential to both overestimate and underestimate the temperature of foraging bees when only air temperature is considered.
Keywords: Dynamic energy budget; Heat budget modelling; Heat transfer; Thermal ecology

Effects of some insecticides on longevity of the foragers honey bee worker of local honey bee race Apis mellifera jemenatica - Musleh Aljedani, Dalal; Almehmadi, Roqaya Mohammed (Electronic physician, 2015)
Abstract Background: In many cases, myocardial infarction leads to arrhythmia. Since antioxidant agents have an important protective role in heart disease, these compounds in medicinal plants are used in traditional medicine. Lemon balm extract, compared to other plants of the lamiaceae family, has been proven to have significant amounts of antioxidant compounds. The aim of this study was to assess the effect of the hydroalcoholic extract of lemon balm (Melissa officinalis L.) on CaCl2-induced arrhythmias in rats. Methods: This research is an experimental study; male adult Sprague Dawley rats that weighed 200-250 g were divided randomly into three groups, i.e., 1) control (normal saline, 1 ml/kg/day), 2) extract (100 mg/kg), and 3) extract (200 mg/kg). The normal saline and the extracts were gavaged for 14 consecutive days. After anesthesia, lead II electrocardiograms were recorded for calculating the rats’ heart rates (HRs). Arrhythmia was induced by intravenous injection of CaCl2 solution (140 mg/kg), and the percentages of incidence of ventricular tachycardia (VT), ventricular fibrillation (VF), and ventricular premature beats (VPB) were recorded. The results were analyzed by using Fisher’s exact test and one-way ANOVA. P-values less than 0.05 were considered as significant level. Results: Heart rates and percentages of incidence of VPB, VT, and VF were reduced significantly in extract groups (with the highest activity at 200 mg/kg) in comparison with the control group. Conclusion: Melissa officinalis was considered to be an antiarrhythmic agent because it reduced the percentage of incidence of VPB, VT, and VF in the groups that received it. The results indicated that Melissa officinalis had a protective effect on the heart. Keywords: arrhythmia, Melissa officinalis, chronotropic effect, rats

Sublethal effects of kaolin and the biopesticides Prestop-Mix and BotaniGard on metabolic rate, water loss and longevity in bumble bees (Bombus terrestris) - Karise, Reet; Muljar, Riin; Smagghe, Guy; Kaart, Tanel; Kuusik, Aare; Dreyersdorff, Gerit; Williams, Ingrid H.; Mänd, Marika (Journal of Pest Science, 2016)
Kaolin is an inert material with a broad range of applications, e.g. as an insecticide and as a filling substance in the formulation of biopesticides. Hence, bees that dispense biopesticides to the field in the context of entomovectoring are exposed to elevated risks because of side-effects of those products. Here, we investigated with use of bumble bee workers of Bombus terrestris L. the lethal and sublethal effects of (i) pure kaolin, (ii) the biofungicide Prestop-Mix containing the parasitic fungus Gliocladium catenulatum and kaolin and (iii) the bioinsecticide BotaniGard containing the entomopathogenic fungus Beauveria bassiana and compared with wheat flour powder that we considered safe for bumble bees. As the most important result, treatment with kaolin increased the cuticular water loss and reduced the survival of treated bumble bees, while Prestop-Mix had no negative effect on longevity. BotaniGard caused mortality in the bumble bees because of the entomopathogenic spores it contained. In conclusion, our data indicated that substances used as ‘inert materials’ and in biocontrol agents which are used in IPM and organic farming systems may bring higher risks to bumble bees used in entomovector technology.
Keywords: Biocontrol agent; Bombus terrestris; Inert material; Kaolin; Metabolic rate; Survival; Water loss

The behavioral regulation of thirst, water collection and water storage in honey bee colonies - Ostwald, Madeleine M.; Smith, Michael L.; Seeley, Thomas D. (Journal of Experimental Biology, 2016)
This study investigated how a honey bee colony develops and quenches its collective thirst when it experiences hyperthermia of its broodnest. We found that a colony must strongly boost its water intake because evaporative cooling is critical to relieving broodnest hyperthermia, and that it must rapidly boost its water intake because a colony maintains only a small water reserve. We also clarified how a colony's water collectors know when to spring into action - by sensing either more frequent requests for fluid or greater personal thirst, or both. Finally, we found that the behavioral flexibility of a colony's water collectors enables them not only to satisfy their colony's current water needs but also to buffer their colony against future extreme water stresses by storing water in their crops and in their combs.
Keywords: Apis mellifera; Nest thermoregulation; Social physiology; Social thirst; Water collectors; Water homeostasis

Tolerance of two honey bee races to various temperature and relative humidity gradients - Abou-Shaara, Hossam F; Al-Ghamdi, Ahmad A; Mohamed, Abdelsalam A (Environmental and Experimental Biology, 2012)
here are various factors that can have an efect on honey bee colonies. Temperature and relative humidity, in particularly, have special importance for honey bee colonies. Relatively few studies have been conducted on the efects of temperature and relative humidity on honey bee races. Here, the efects of diferent levels of temperature and relative humidity on survival, tolerance and body water loss were investigated on two races, one adapted to harsh conditions (Yemeni honey bees) and the other adapted to normal conditions (Carniolan honey bees). Results showed that temperature had higher efect than relative humidity on workers survival and Yemeni honey bees were more tolerant to elevated temperature than Carniolan honey bees. Moreover, rates of body water loss for the two races were high under elevated temperature and low humidity conditions. In general, the response of the two races in the studied treatments was somewhat similar. However, under extreme conditions at elevated temperature or low humidity, Yemeni honey bees showed higher tolerance than Carniolan honey bees.
Keywords: Apis mellifera carnica; Apis mellifera jemenitica; honey bees; humidity; relative humidity; survival Abbreviations: RH; temperature; tolerance

Water homeostasis in bees, with the emphasis on sociality - Nicolson, Susan W. (Journal of Experimental Biology, 2009)
Avenues of water gain and loss in bees are examined here at two levels of organisation: the individual and the colony. Compared with the majority of terrestrial insects, bees have a high water turnover. This is due to their nectar diet and, in larger species, substantial metabolic water production during flight, counteracted by high evaporative and excretory losses. Water fluxes at the colony level can also be very high. When incoming nectar is dilute, honeybees need to remove large volumes of water by evaporation. On the other hand, water is not stored in the nest and must be collected for evaporative cooling and for feeding the brood. Water regulation has many similarities at individual and colony levels. In particular, manipulation of nectar or water on the tongue is extensively used by bees to increase evaporation for either food-concentrating or cooling purposes.
Keywords: Bubbling; Evaporation; Nectar; Water collection

The interaction between a parasite and sub-optimal temperatures contributes to honey bee decline

The organizational impact of chronic heat: diffuse brood comb and decreased carbohydrate stores in honey bee colonies - Weinberg, Isaac P.; Wetzel, Jaya P.; Kuchar, Eleanor P.; Kaplan, Abigail T.; Graham, Rebecca S.; Zuckerman, Jonah E.; Starks, Philip T. (Frontiers in Ecology and Evolution, 2023)
Insect pollinators are vital to the stability of a broad range of both natural and anthropogenic ecosystems and add billions of dollars to the economy each year. Honey bees are perhaps the best studied insect pollinator due to their economic and cultural importance. Of particular interest to researchers are the wide variety of mechanisms honey bees use for thermoregulation, such as fanning cool air currents around the hive and careful selection of insulated nest sites. These behaviors help honey bees remain active through both winter freezes and summer heatwaves, and may allow honey bees to deal with the ongoing climate crisis more readily than other insect species. Surprisingly, little is known about how honey bee colonies manage chronic heat stress. Here we provide a review of honey bee conservation behavior as it pertains to thermoregulation, and then present a novel behavior displayed in honey bees—the alteration of comb arrangement in response to 6 weeks of increased hive temperature. We found that while overall quantities of brood remained stable between treatments, brood were distributed more diffusely throughout heated hives. We also found that heated hives contained significantly less honey and nectar stores than control hives, likely indicating an increase in energy expenditure. Our results support previous findings that temperature gradients play a role in how honey bees arrange their comb contents, and improves our understanding of how honey bees modify their behavior to survive extreme environmental challenges.
Keywords: climate change; conservation behavior; honey bees; insect architecture; thermoregulation

Sublethal effects of herbicides clethodim, haloxyfop-P-methyl, and their mixture on honey bee health - Mohamed, Ibrahim A.; Omar, Eslam M.; Tawfik, Amer I.; Amro, Abdulraouf M.A.; Al Naggar, Yahya (Apidologie, 2023)
Herbicides are the most frequently used pesticides, accounting for more than 60% of all pesticides used in agriculture around the world. Clethodim (CTD) (Vixtol Super® 24% EC), haloxyfop-p-methyl (HFM) (Gallant Super® 10.8% EC), and their mixture (CTD (15%) + HFM (7.5%) (Fine® 22.5% EC) are among the most commonly used post-emergence graminicides in Egypt and worldwide. However, little data on their toxicological effects on honey bees (Apis mellifera L.) is known. In this study, the lethal and sublethal effects of CTD or HFM and their mixture were assessed in the laboratory on foragers and nurse honey bee workers, respectively. In the acute toxicity test, HFM was more toxic to forager workers (LC50 = 0.95 mg a.i./ml) after 96 h of oral exposure, followed by CTD then the mixture which was the least toxic one. In a chronic toxicity test, newly emerged bees were fed sugar syrup that was herbicide-free (control) or sugar syrup that contained a sublethal concentration of HFM (0.2 mg/ml; 1/5 of 96 h-LC50) or CTD (0.6 mg/ml; 1/5 96 h-LC50) or the mixture (0.2 mg/ml; 1/15 96 h-LC50) for 20 days. CTD significantly reduced bee survival and dry body weight compared to non-exposed control bees and bees exposed to HFM or the mixture. Chronic sublethal exposure to these herbicides also caused a considerable reduction in hypopharyngeal glan (HPG) acini volume, severe morphologic alterations, and a deleterious impact on hemocyte account and differentiation. This is the first study of its kind to indicate that herbicides that inhibit acetyl-CoA-carboxylase (ACCase) have a negative impact on honey bee health at sublethal levels.
Keywords: hemolymph; herbicides; honey bees; hypopharyngeal glands; sublethal concentrations

Honey bee foraging and pesticide exposure in a desert urban agroecosystem - Zhang, Ge; Kersten, Miranda; Owen, Amy; Skidmore, Amanda (Ecotoxicology and Environmental Safety, 2023)
The negative impacts of industrial farming on honey bee health have been widely recognized regarding pesticide use and natural foraging habitat loss. An assessment of suitability of urban farms regarding honey bee health is necessary for sustainable development of agriculture and apiculture in urban settings. Urban farms that adopt organic farming practices with restrictions on synthetic pesticide use and conservation of natural habitat can potentially create an environment to mitigate these environmental stressors on honey bees. In this experiment, bee-collected pollen was taken from honey bee colonies that were located on five organically managed urban farms located in Albuquerque, New Mexico, to evaluate pesticide exposure and forage use. We also explored the influence of hive equipment on honey bee health in a high desert climate. We found that honey bees on organic urban farms were not stressed by pesticides with limited pesticide types detected (2 out of 187), low residue levels (< 20 µg/kg) and low toxicity (either no, or low toxicity with LD50 at 1,450,300 µg/kg). Honey bees had access to diverse forage resources based on pollen barcoding data. When comparing hive equipment between 10-frame, 8-frame Langstroth and top bar hives, it was determined that 8-frame hives could significantly enhance honey bee health including colony survival and weight growth, comb construction and brood production. Our results suggest that organic urban farms are appropriate locations for securing honey bee health and food safety in a desert climate; while, the selection of hive equipment should be considered when mitigating environmental stress to colonies.
Keywords: Apis mellifera; Beekeeping; Natural habitat; Organic; Pollen; Urban farm

Effects of fungicides propiconazole and Trichoderma spp. on the mortality and the physiological status of larvae and adult worker honey bees (Apis mellifera L.) - Banan, Arezoo; Homayoonzadeh, Mohammad; Torabi, Ehssan; Ghasemi, Vahid; Shahbazi, Samira; Talebi, Khalil (Journal of Apicultural Research, 2023)
Exposure to pesticides may affect the survival and normal physiological functions of the honey bee (Apis mellifera L.). The fungicide propiconazole (PRO) and the biofungicide Trichoderma are widely used in agroecosystems, and their effects on the physiology of the honey bee have been largely neglected in risk assessment procedures. We investigated the mortality and variations in physiological biomarkers of honey bee larvae and newly emerged workers exposed to PRO and Trichoderma. Exceeding the field-recommended concentrations of Trichoderma decreased the survival of newly emerged bee workers significantly through oral exposure. PRO, however, showed no significant lethal effects. Contact or oral exposure to field-realistic concentrations of PRO and Trichoderma profoundly altered the activities of detoxification, antioxidative, and digestive enzymes along with energy reserve concentrations of honey bee larvae and adult workers. Integrated biological index (IBRv2) values suggested potential risks of PRO and Trichoderma to honey bees by impairing the physiological status of larvae and newly emerged workers.
Keywords: Honey bee; IBRv2; Trichoderma; physiological biomarkers; propiconazole

Pesticide residues in honey bee (Apis mellifera) pollen collected in two ornamental plant nurseries in Connecticut: Implications for bee health and risk assessment - Hester, K.P.; Stoner, K.A.; Eitzer, B.D.; Koethe, R.W.; Lehmann, D.M. (Environmental Pollution, 2023)

Potential Risk of Residues From Neonicotinoid-Treated Sugar Beet Flowering Weeds to Honey Bees (Apis mellifera L.) - Odemer, Richard; Friedrich, Elsa; Illies, Ingrid; Berg, Stefan; Pistorius, Jens; Bischoff, Gabriela (Environmental Toxicology and Chemistry, 2023)
In 2018 the European Union (EU) banned the three neonicotinoid insecticides imidacloprid, clothianidin (CLO), and thiamethoxam (TMX), but they can still be used if an EU Member State issues an emergency approval. Such an approval went into effect in 2021 for TMX-coated sugar beet seeds in Germany. Usually, this crop is harvested before flowering without exposing non-target organisms to the active ingredient or its metabolites. In addition to the approval, strict mitigation measures were imposed by the EU and the German federal states. One of the measures was to monitor the drilling of sugar beet and its impact on the environment. Hence we took residue samples from different bee and plant matrices and at different dates to fully map beet growth in the German states of Lower Saxony, Bavaria, and Baden-Württemberg. A total of four treated and three untreated plots were surveyed, resulting in 189 samples. Residue data were evaluated using the US Environmental Protection Agency BeeREX model to assess acute and chronic risk to honey bees from the samples, because oral toxicity data are widely available for both TMX and CLO. Within treated plots, we found no residues either in pools of nectar and honey crop samples (n = 24) or dead bee samples (n = 21). Although 13% of beebread and pollen samples and 88% of weed and sugar beet shoot samples were positive, the BeeREX model found no evidence of acute or chronic risk. We also detected neonicotinoid residues in the nesting material of the solitary bee Osmia bicornis, probably from contaminated soil of a treated plot. All control plots were free of residues. Currently, there are insufficient data on wild bee species to allow for an individual risk assessment. In terms of the future use of these highly potent insecticides, therefore, it must be ensured that all regulatory requirements are complied with to mitigate any unintentional exposure. Environ Toxicol Chem 2023;42:1167–1177. © 2023 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.
Keywords: BeeREX model; Clothianidin; Flowering weeds; Honey bee risk assessment; Neonicotinoid; Pollen nectar residues; Risk quotient; Thiamethoxam; Treated sugar beet

Non‐neonicotinoid pesticides impact bumblebee activity and pollen provisioning - O'Reilly, Alison D.; Stanley, Dara A. (Journal of Applied Ecology, 2023)

Semi-Lethal Doses of Neonicotinoid Imidacloprid Adjust the Wing-Flapping Frequency and Flight Abi

Sensitivity to imidacloprid insecticide varies among some social and solitary bee species of agricultural value - Sampson, Blair; Gregorc, Aleš; Alburaki, Mohamed; Werle, Christopher; Karim, Shahid; Adamczyk, John; Knight, Patricia (PLoS ONE, 2023)
Pollinator health risks from long-lasting neonicotinoid insecticides like imidacloprid has primarily focused on commercially managed, cavity-nesting bees in the genera Apis, Bombus, and Osmia. We expand these assessments to include 12 species of native and non-native crop pollinators of differing levels of body size, sociality, and floral specialization. Bees were collected throughout 2016 and 2017 from flowering blueberry, squash, pumpkin, sunflower and okra in south Mississippi, USA. Within 30-60 minutes of capture, bees were installed in bioassay cages made from transparent plastic cups and dark amber jars. Bees were fed via dental wicks saturated with 27% (1.25 M) sugar syrup containing a realistic range of sublethal concentrations of imidacloprid (0, 5, 20, or 100 ppb) that are often found in nectar. Bees displayed no visible tremors or convulsions except for a small sweat bee, Halictus ligatus, and only at 100ppb syrup. Imidacloprid shortened the captive longevities of the solitary bees. Tolerant bee species lived ∼10 to 12 days in the bioassays and included two social and one solitary species: Halictus ligatus, Apis mellifera and Ptilothrix bombiformis (rose mallow bees), respectively. No other bee species tolerated imidacloprid as well as honey bees did, which exhibited no appreciable mortality and only modest paralysis across concentration. In contrast, native bees either lived shorter lives, experienced longer paralysis, or endured both. Overall, longevity decreased with concentration linearly for social bees and non-linearly for solitary species. The percentage of a bee's captive lifespan spent paralyzed increased logarithmically with concentration for all species, although bumble bees suffered longest. Of greatest concern was comparable debilitation of agriculturally valuable solitary bees at both low and high sublethal rates of imidacloprid.

Sublethal exposure to imidacloprid in commercial Apis mellifera colonies in early spring: performance of honey bees and insecticide transference between in-hive products - Michlig, Melina Paola; Pacini, Adriana Cecilia; Merke, Julieta; Orellano, Emanuel Matías; Brasca, Romina; Repetti, María Rosa (Apidologie, 2023)
Honey bees have an important role in ecosystems as pollinators. However, in recent years, bee populations have declined, with habitat destruction, pesticide use, and climate change contributing to the decline. One of the most important risk factors is the use of neurotoxic pesticides, such as neonicotinoids. The aim of this work was to study the effects of imidacloprid in commercial Apis mellifera L. colonies artificially fed with syrups spiked with this insecticide and its possible transfer among in-hive products such as honey and larvae. For this purpose, 30 colonies were placed in the same apiary; once a week for 7 weeks in early spring, each colony was fed with 0.5 L of syrup with the following doses of imidacloprid: 0, 15, 30, 120, and 240 µg kg−1. The colony strength was evaluated by monitoring: the number of adult bees and brood combs, queenlessness, unhealthy colonies (by detection of Nosema spp. spores and European foulbrood), as well as pollen and honey storage. Worker bees, larvae, honey, and beeswax were sampled to evaluate imidacloprid transfer within the hive. Trends in the persistence of the compound showed that up to 60% of the parent (not metabolized) was stored in honey, and the absence of residues in the larvae suggests that they were not exposed. Another result showed a certain impact in the honey reserves and honey yield with a reduction of this resource in the colonies exposed to imidacloprid.
Keywords: Apis mellifera L; Colony strength; Imidacloprid; Residues; Sublethal doses

Effect of belt expert (Flubendiamide + Thiacloprid), Imidacloprid, Thiamethoxam seed treatment and economic impact on fall armyworm (Spodoptera frugiperda) infestation on Maize in Nigeria - Utono, Iliyasu Mohammed; Adamu, Rabiu Salisu (Cogent Food and Agriculture, 2023)
Fall Armyworm (FAW) Spodoptera frugiperda infestation in Nigeria has reduced the yield of maize by over 40%, especially where control measures are not implemented adequately or effectively. The concealed feeding behavior of the larvae in the leaf whorl makes its control with insecticide difficult, especially for older larvae as a high volume of insecticide will be required to reach the hidden larvae. This can increase the potential of pest exposure to insecticide, selection pressure and consequent development of resistance. One of the new control strategies being developed for this pest is the use of new insecticides of a different mode of action; Belt Expert (Flubendiamide + Thiacloprid) applied at a threshold of 20% (11,000 plant samples/ha) infestation. Flubendiamide + Thiacloprid gave yields similar to conventional insecticides (Emamectin Benzoate and Lambda-cyhalothrin + Chlorantraniliprole) which were better than the untreated. Another approach is the use of seed treatments (Imidacloprid, Thiamethoxam, Apron plus) followed by 2 foliar sprays with Ampligo (Lambda-cyhalothrin + Chlorantraniliprole) at 2, 4, 6 and 8 weeks after planting (WAP). Treatment with imidacloprid or thiamethoxam seed treatment flowed with foliar application of Ampligo at 4WAP significantly had the lowest larval count and highest percentage maize grain yield with a significant yield increase of >15% over the untreated. The use of insecticide with a different mode of action in the targeted pest density and a seed management-based approach may be significant in the management of pest resistance. Future works should focus on integrating some of these approaches in the management of FAW in Nigeria.
Keywords: Invasive; Maize; Management; Sustainable; Yield increase; fall armyworm

Efficacy of Imidacloprid Seed Treatments against Four Wheat Aphids under Laboratory and Field Conditions - Zhang, Zhi; Li, Yaping; Li, Xiangrui; Zhu, Xun; Zhang, Yunhui (Plants, 2023)
Imidacloprid seed treatments are effective at reducing the cohorts of many insect pests on crops such as cotton, corn, and cereals. The effects of imidacloprid seed treatments depend on the aphid species. In China, there are four wheat aphid species—Sitobion avenae (Fabricius), Rhopalosiphum padi (Linnaeus), Schizaphis graminum (Rondani), and Metopolophium dirhodum (Walker)—and for a given region, these four aphid species differ in dominance with changes in cultivation practices and climate. Therefore, it is necessary to evaluate the effects of imidacloprid seed treatments on the four different aphid species. In experiments in the laboratory, imidacloprid seed treatments significantly reduced the survival rates of S. avenae, R. padi, and S. graminum to 57.33 ± 2.86%, 12.67 ± 1.92%, and 20.66 ± 2.33%, respectively, but for M. dirhodum, there was no significant difference between the control (96.33 ± 1.08%) and the treatment (97.00 ± 0.98%). The fecundities of the four aphid species were much reduced, especially for R. padi when feeding on treated wheat plants. For the field survey, only three aphid species were considered because the density of S. graminum was too low to be analyzed. The effects of imidacloprid seed treatment on the three aphid species in the field were consistent with the laboratory results. Imidacloprid seed treatment reduced the population sizes of S. avenae and R. padi at rates of 70.30 ± 3.15% and 87.62 ± 2.28%, respectively, for the whole wheat season in the field. For M. dirhodum, imidacloprid seed treatments were less effective, and the densities of M. dirhodum increased on four sample days. From this study, we confirmed that the effect of imidacloprid seed treatment varied with the composition of aphid species, being especially less effective for M. dirhodum.
Keywords: Metopolophium dirhodum (Walker); Rhopalosiphum padi (Linnaeus); Schizaphis graminum (Rondani); Sitobion avenae (Fabricius); imidacloprid seed treatment; wheat aphid

Sublethal effects of imidacloprid and clothianidin on the biological traits of predatory lacewing Chrysopa pallens (Rambur) (Neuroptera: Chrysopidae) - Su, Yue; Ren, Xiangliang; Hu, Hongyan; Song, Xianpeng; Ma, Xiaoyan; Wang, Dan; Yao, Yongsheng; Ma, Yan; Cui, Jinjie (Crop Protection, 2023)
Imidacloprid and clothianidin are widely used insecticides for controlling piercing-sucking pests. However, their effects on non-targets insects are a major concern. Here, we evaluated the effects of sublethal concentrations of imidacloprid and clothianidin on Chrysopa pallens (Rambur) (Neuroptera: Chrysopidae), an important pest predator on many crops. Our data showed that imidacloprid and clothianidin at LD10 (0.71 and 1.42 ng active ingredient [a.i.] per insect, respectively) and LD30 (1.31 and 2.49 ng a.i. per insect, respectively) significantly increased the duration of the second instar larval stage of C. pallens. However, the duration of the third instar was prolonged only by clothianidin at LD30. At LD10, imidacloprid and clothianidin significantly increased the length of pupal stage. In addition, imidacloprid at LD30 significantly prolonged the mean generation time (T). Our results showed that imidacloprid and clothianidin prolong C. pallens developmental but had limited effects on population growth parameters. These results are expected to guide the development of integrated pest management strategies.
Keywords: Biological control; Integrated pest management; Risk assessment; Two-sex life table

Behavioral and physiological response of the passerine bird Agelaioides badius to seeds coated with imidacloprid - Poliserpi, Maria Belen; Noya Abad, Tatiana; De Gerónimo, Eduardo; Aparicio, Virginia; Brodeur, Julie Celine (Environmental Science and Pollution Research, 2023)
Neonicotinoids are globally used insecticides, and there are increasing evidence on their negative effects on birds. This study is aimed at characterizing the behavioral and physiological effects of the neonicotinoid imidacloprid (IMI) in a songbird. Adults of Agelaioides badius were exposed for 7 days to non-treated peeled millet and to peeled millet treated with nominal concentrations of 75 (IMI1) and 450 (IMI2) mg IMI/kg seed. On days 2 and 6 of the trial, the behavior of each bird was evaluated for 9 min by measuring the time spent on the floor, the perch, or the feeder. Daily millet consumption, initial and final body weight, and physiological, hematological, genotoxic, and biochemical parameters at the end of exposure were also measured. Activity was greatest on the floor, followed by the perch and the feeder. On the second day, birds exposed to IMI1and IMI2 remained mostly on the perch and the feeder, respectively. On the sixth day, a transition occurred to sectors of greater activity, consistent with the disappearance of the intoxication signs: birds from IMI1 and IMI2 increased their time on the floor and the perch, respectively. Control birds always remained most of the time on the floor. IMI2 birds significantly decreased their feed intake by 31% the first 3 days, compared to the other groups, and significantly decreased their body weight at the end of the exposure. From the set of hematological, genotoxic, and biochemical parameters, treated birds exhibited an alteration of glutathione-S-transferase activity (GST) in breast muscle; the minimal effects observed are probably related to the IMI administration regime. These results highlight that the consumption of less than 10% of the bird daily diet as IMI-treated seeds trigger effects at multiple levels that can impair bird survival.
Keywords: Agriculture; Behavior; Biomarkers; Bird; Insecticides; Neonicotinoids; Pesticides; Seeds

Effects and potential resistance induced by imidacloprid and clothianidin insecticides in the German cockroach (Blatella germanica L.) - Konkala, Anand; Kanthala, Sampath; Reddy Narra, Madhusudan (2023)
Neonicotinoid pesticides have occupied one-third of the world's insecticidal market in the last two decades. Their mimicking effects of imidacloprid and clothianidin on the target-neurotransmission system (AChE) and digestive oxidative and antioxidant enzymes have been evaluated in Blatella germanica. The cockroach brain's AChE activity decreased through the exposure period. The P450 monooxygenase enzyme, which is involved in a xenobiotic breakdown in endogenous metabolism and has adapted to toxic chemicals, has increased over time. This phenomenon indicates that the P450 enzyme is coupled with insecticides through the detoxication process. The elevated SOD, CAT and LPO levels indicate an increase in the scavenging activity of free radicals to overcome the IMI and CLO-caused oxidative alterations. Increasing GST was conjugated with decreasing GSH in phase II bio-transformation reactions, resulting in a defence against the stress of intoxication. Besides, IMI and CLO instigated elevated oxidative stress, as proved by elevated hydrolytic lysosomal enzyme phosphatases (ALP and ACP) and lactate dehydrogenase activities evident that the cockroach counteracted to overcome the insecticidal stress. The present investigation elucidates the fact that resistance performance against the effects of imidacloprid and clothianidin baits, indicating the potential involvement of cytochrome P450 monooxygenase, antioxidants, and a slight participation of esterase, has activated the detoxication system to metabolise endogenous insecticide architecture. Because of its chemical structure, clothianidin causes severe intoxication and less detoxication than imidacloprid.
Keywords: Blattella germanica; Clothianidin; Imidacloprid; Neonicotinoids; P450 monooxygenase; Resistance

Functional response of an egg parasitoid, Trichogramma chilonis Ishii to sublethal imidacloprid exposure - Ray, Aishwarya; Gadratagi, Basana Gowda; Budhlakoti, Neeraj; Rana, Dhanendra Kumar; Adak, Totan; Govindharaj, Guru Pirasanna Pandi; Patil, Naveenkumar Basavanagouda; Mahendiran, Annamalai; Rath, Prakash Chandra (Pest Management Science, 2023)
BACKGROUND: The effectiveness of a biological control agent depends on how well it can control pests and how compatible it is with pesticides. Therefore, we reported the multigenerational effect of a commonly used insecticide, imidacloprid, on the functional response of a widely acclaimed egg parasitoid, Trichogramma chilonis Ishii, to different densities of the host Corcyra cephalonica Stainton eggs. The study investigated the outcomes of the median lethal concentration (LC50) and sublethal concentrations (LC5, LC30), along with control treatments for five continuous generations (F1 to F5). RESULTS: The results showed that the F5 generation of LC30, both of the F1 and F5 generations of LC50, and the control all had a Type II functional response. A Type I functional response was exhibited for the F1 generation of LC30 and both generations of LC5. The attack rate on host eggs treated with LC5 and LC30 did not change (decrease) with the shift in the type of functional response as compared to the control. A significant increase in the searching efficiency (a) was observed in the later generation (F5) under the exposure of LC5 and LC30 imidacloprid concentrations. A lower handling time (Th) in both generations of the LC5 followed by LC30 treated individuals was observed when compared with the control and LC50 treatments. The per capita parasitization efficiency (1/Th) and the rate of parasitization per handling time (a/Th) were also considerably higher in both the generations of LC5 and LC30 than in the control and LC50, thereby implying positive effects of imidacloprid on the parasitization potential of T. chilonis. CONCLUSION: Altogether, these multigenerational outcomes on the functional response of T. chilonis could be leveraged to control the intractable lepidopteran pests under the mild exposure of imidacloprid in integrated pest management (IPM) programs as well as in the mass rearing of the parasitoid, T. chilonis. © 2023 Society of Chemical Industry.
Keywords: biological control; biological traits; eco-toxicology; hormesis; host/parasitoid interaction; insecticide stress

The interaction of nicotinic acetylcholine receptor subunits Ldα3, Ldα8 and Ldβ1 with neonicotinoids in Colorado potato beetle, Leptinotarsa decemlineata - Shi, Chengcheng; Tian, Yitong; Wang, Yaqi; Guo, Wenchao; Jiang, Weihua (Pesticide Biochemistry and Physiology, 2023)

Effects of imidacloprid-induced hormesis on the development and reproduction of the rose-grain aphid Metopolophium dirhodum (Hemiptera: Aphididae) - Li, Xinan; Li, Yaping; Zhu, Xun; Li, Xiangrui; Cheng, Dengfa; Zhang, Yunhui (Frontiers in Physiology, 2023)
Field populations of insect pests are affected by sub-lethal doses of insecticides, leading to hormesis. Imidacloprid is a neonicotinoid insecticide widely used to control various sucking insect pests, including aphids. In this study, the effects of sub-lethal concentrations of imidacloprid on the life table traits of the rose-grain aphid Metopolophium dirhodum (Walker) were evaluated on parental and first filial generations. The results showed that sub-lethal concentrations of imidacloprid significantly reduced the fecundity, adult longevity, and reproductive period of M. dirhodum in parental generation (F0). However, the imidacloprid-induced hormetic effects on development and reproduction were detected in the F1 generation. These hormetic effects were indicated by significantly higher adult longevity, fecundity, survival rate, intrinsic and finite rates of increase, and net reproductive rate of first filial generation (F1) of M. dirhodum. Our finding indicated that the application of sub-lethal concentrations of imidacloprid inhibited parental generation (F0), but it significantly stimulated the population growth of filial generation (F1) in the M. dirhodum. The results support the inclusion of insecticides in integrated pest management programs for managing wheat aphids.
Keywords: Metopolophium dirhodum; fecundity; hormesis; imidacloprid; longevity

Controlled expression of nicotinic acetylcholine receptor-encoding genes in insects uncovers distinct mechanisms of action of the neonicotinoid insecticide dinotefuran - Ozoe, Yoshihisa; Matsubara, Yoshiki; Tanaka, Yuji; Yoshioka, Yasuhide; Ozoe, Fumiyo; Shiotsuki, Takahiro; Nomura, Kazuki; Nakao, Toshifumi; Banba, Shinichi (Pesticide Biochemistry and Physiology, 2023)
Dinotefuran, a neonicotinoid, is a unique insecticide owing to its structure and action. We took two approaches that employed insects with controlled expression of nicotinic acetylcholine receptor (nAChR)-encoding genes to gain insight into the uniqueness of dinotefuran. First, we examined the insecticidal activity of dinotefuran and imidacloprid against brown planthoppers (Nilaparvata lugens), in which the expression of eight (of 13) individual subunit-encoding genes was specifically reduced using RNA interference. Knockdown of the tested gene, except one, resulted in a decrease in sensitivity to imidacloprid, whereas the sensitivity of N. lugens to dinotefuran decreased only when two of the eight genes were knocked down. These findings imply that a major dinotefuran-targeted nAChR subtype may contain specific subunits although imidacloprid acts on a broad range of receptor subtypes. Next, we examined the effects of knockout of Drosophila α1 subunit-encoding gene (Dα1) on the insecticidal effects of dinotefuran and imidacloprid. Dα1-deficient flies (Dα1KO) demonstrated the same sensitivity to dinotefuran as control flies, but a decreased sensitivity to imidacloprid. This difference was attributed to a reduction in imidacloprid-binding sites in Dα1KO flies, whereas the binding of dinotefuran remained unchanged. RNA sequencing analysis indicated that Dα2 expression was specifically enhanced in Dα1KO flies. These findings suggest that changes in Dα1 and Dα2 expression contribute to the differences in the insecticidal activity of dinotefuran and imidacloprid in Dα1KO flies. Overall, our findings suggest that dinotefuran acts on distinct nAChR subtypes.
Keywords: Dinotefuran; Imidacloprid; Neonicotinoid; Nicotinic acetylcholine receptor

A quantitative micro-tomographic gut atlas of the lepidopteran model insect Manduca sexta - Windfelder, Anton G.; Steinbart, Jessica; Flögel, Ulrich; Scherberich, Jan; Kampschulte, Marian; Krombach, Gabriele A.; Vilcinskas, Andreas (iScience, 2023)
The tobacco hornworm is used extensively as a model system for ecotoxicology, immunology and gut physiology. Here, we established a micro-computed tomography approach based on the oral application of the clinical contrast agent iodixanol, allowing for a high-resolution quantitative analysis of the Manduca sexta gut. This technique permitted the identification of previously unknown and understudied structures, such as the crop or gastric ceca, and revealed the underlying complexity of the hindgut folding pattern, which is involved in fecal pellet formation. The acquired data enabled the volume rendering of all gut parts, the reliable calculation of their volumes, and the virtual endoscopy of the entire alimentary tract. It can provide information for accurate orientation in histology uses, enable quantitative anatomical phenotyping in three dimensions, and allow the calculation of locally effective midgut concentrations of applied chemicals. This atlas will provide critical insights into the evolution of the alimentary tract in lepidopterans.
Keywords: Imaging anatomy; Methodology in biological sciences; Model organism

Individual and combined treatments with imidacloprid and spinosad disrupt survival, life-history traits, and nutritional physiology of Spodoptera littoralis - Shaurub, El Sayed H.; Tawfik, Amer I.; El-Sayed, Asmaa M. (International Journal of Tropical Insect Science, 2023)
The Egyptian cotton leafworm Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) is a pervasive agricultural polyphagous insect pest. Because of the negative side-effects of conventional pesticides used in agricultural fields, safer alternatives for insect pest management are required. We evaluated here susceptibility, biological features, and nutritional indices of S. littoralis after treatment of 4th-instar larvae with the neonicotinoid imidacloprid and the spinosyn spinosad separately or in combination. Larvae were fed for three successive days on treated leaves of castor-bean Ricinus communis using leaf-dip technique (treatment period). In addition, in case of nutritional indices study, treated leaves were replaced by fresh untreated leaves for two successive days (recovery period). Spinosad was more toxic than imidacloprid, and their combination revealed additive effects based on the co-toxicity factor. Individual and combined treatments significantly decreased pupation rate, adult emergence rate, pupal weight, number of eggs laid per female, egg-hatch, and female longevity, compared to those of controls. Pupal and adult malformations were recorded. During the treatment period, nutritional indices were insecticide- and time-dependent. On the 2nd day of recovery, all nutritional indices of treated larvae were not significantly different, compared to those of controls. The results presented herein may help in developing more effective crop protection methodologies within integrated pest management of this insect.
Keywords: Biological features; Egyptian cotton leafworm; Neonicotinoids; Nutritional indices; Spinosyns; Toxicity

Protective effect of rutin against thiram-induced cytotoxicity and oxidative damage in human erythrocytes - Salam, Samreen; Arif, Amin; Sharma, Monika; Mahmood, Riaz (Pesticide Biochemistry and Physiology, 2023)
Thiram is a fungicide that is used to prevent fungal diseases in seeds and crops and also as an animal repellent. The pro-oxidant activity of thiram is well established. Rutin is a flavonoid glycoside present in many fruits and plants and has several beneficial properties, including antioxidant effects. We have previously shown that thiram causes oxidative damage in human erythrocytes. The present study was designed to evaluate the protective effect of rutin against thiram-induced damage in human erythrocytes. Treatment of erythrocytes with 0.5 mM thiram for 4 h increased the level of oxidative stress markers, decreased antioxidant power and lowered the activity of antioxidant and membrane bound enzymes. It also enhanced the generation of reactive oxygen and nitrogen species (ROS and RNS) and altered the morphology of erythrocytes. However, prior treatment of erythrocytes with rutin (0.5, 1 and 2 mM) for 2 h, followed by 4 h incubation with 0.5 mM thiram, led to a decrease in the level of oxidative stress markers in a rutin concentration-dependent manner. A significant restoration in the antioxidant power and activity of antioxidant enzymes was observed upon the treatment of erythrocytes with 1 and 2 mM rutin. Pre-incubation with rutin lowered the generation of ROS and RNS which will reduce oxidative damage in erythrocytes. The thiram-induced changes in cell morphology and activity of membrane-bound enzymes were also attenuated by rutin. These results suggest that rutin can be used to mitigate thiram-induced oxidative damage in human erythrocytes.
Keywords: Antioxidant; Human erythrocytes; Oxidative stress; Rutin; Thiram

The antioxidant/anti‐inflammatory protective effects of rutin against ethanol‐induced testicular perturbation in rats: Involvement of the immunosuppressive indoleamine 2,3‐dioxygenase - Ebokaiwe, Azubuike Peter; Obasi, Doris Olachi; Osawe, Sharon Oluchi; Njoku, Rex Clovis C. (Basic & Clinical Pharmacology & Toxicology, 2023)

Synthesis, characterization, antioxidant activity of Quercetin, Rutin and Quercetin-Rutin incorporated β-cyclodextrin inclusion complexes and determination of their activity in NIH-3T3, MDA-MB-231 and A549 cell lines - Alper Öztürk, A.; Başaran, Ebru; Şenel, Behiye; Demirel, Müzeyyen; Sarıca, Şenay (Journal of Molecular Structure, 2023)
Quercetin (Q) and rutin (R) are plant-originated polyphenolic flavonoids with considerably strong antioxidant and anticancer activity. Despite their potentials, low water solubility, stability problems and oral bioavailability limit their therapeutic use. The specific purpose of our study was to formulate inclusion complexes of Q and R with β-cyclodextrin (β-CD) to improve the solubility and also antioxidant activity of the flavonoids. Therefore 12 different complexes were prepared by both evaporation and lyophilization methods with 1:1 molar ratio in ethanol:water (1:1, v/v) solvent system. The characteristics of the complexes were also evaluated by yield%, zeta potential (ZP), entrapment efficiency (EE), 1H NMR, XRD, FT-IR, DSC analyses. In vitro dissolution studies were performed in comparison with pure substances. Antioxidant activity studies were carried out with DPPH tests. Cytotoxic evaluations of complexes were conducted with MTT tests on NIH 3T3, MDA-MB-231 and A549 cell lines. 1H- NMR analyses revealed the complex formation considering the shifts of the protons of the APIs as well as β-CD. ZP values were ranged between -21.20±0.56 mV and -7.10±0.62 mV. The aqueous solubility of Q and R were increased ∼29 fold and ∼35 fold, respectively. According to the MTT analyses results it has been shown that the flavonoids loaded complexes were particularly effective in MDA-MB-231 cells and 50% cell inhibition was observed even at 5 µM. The results of the analyses have demonstrated that the formation of inclusion complexes resulted in enhanced water solubility and cytotoxicity which will enhance their potential use in pharmaceutical applications.
Keywords: Antioxidant activity; Cytotoxicity; Inclusion complex; Quercetin; Rutin; β-cyclodextrin

Natural antioxidants inhibit oxidative stress-induced changes in the morphology and motility of cells - Xiang, Xiong; Kwame, Amakye William; Qing, Yinglu; Li, Shan; Wang, Min; Ren, Jiaoyan (Food Bioscience, 2023)
Effect of antioxidants in oxidative stress-induced cell damage has been extensively studied, but its effects on cell macroscopic phenomena have rarely been explored. Cell morphology and motility are two interrelated cellular processes reflecting cellular function phenotype, and the real-time imaging technology is key for the study of these processes. In this study, we used two known antioxidants, pyrroloquinoline quinone (PQQ) and rutin, to explore the antioxidant effects on cell morphology and motility in rotenone-damaged NIH3T3 cells, as well as roles in their antioxidant function based on Cytation 7 Cell Imaging Multi-Mode Reader. First, NIH-3T3 cells were pretreated with PQQ and rutin for 4 h and then rotenone was used to induce oxidative damage. It was found that PQQ (2 μM) and rutin (300 μM) had similar protective effects on the proliferation activity of rotenone-damaged cells. Subsequently, the morphology and motility of the treated cells were quantified. Results showed that both PQQ and rutin could significantly inhibit morphological changes including cell shape index and cell surface of the damaged cells, however PQQ had a stronger effect on cell motility under the specific experimental concentrations. Using principal component analysis (PCA), we further demonstrated that the quantified cell morphology and motility were consistent with the cell proliferation activity. Consequently, quantification of cell morphology and motility as evaluation indices may serve as potential reference values for the evaluation of biological activity of antioxidants.
Keywords: Antioxidants; Cell morphology; Cell motility; Cytation 7 cell imaging multi-mode reader; Single cell tracing

Impacts of Imidacloprid and Flupyradifurone Insecticides on the Gut Microbiota of Bombus terrestris - Zhang, Qingchao; Wang, Qinglin; Zhai, Yifan; Zheng, Hao; Wang, Xiaofei (Agriculture (Switzerland), 2022)
Bumblebees are important pollinators for crops and wild flowering plants. Various pesticides have threatened the abundance and diversity of bumblebees. In addition to direct sublethal effects, pesticides may alter the gut microbial communities of bees. Imidacloprid and flupyradifurone insecticides both bind to the nicotinic acetylcholine receptor. However, the latter was assumed to be harmless for honeybees and can even be applied to flowering crops. In this study, we assessed the impacts of these two pesticides on queenless microcolonies and the gut microbiota of Bombus terrestris. We found that 10 µg/L imidacloprid significantly impeded syrup consumption, and post-poned the egg-laying period, larvae, and pupae development. It decreased the relative abundance of the bumblebee-specific symbionts, Apibacter and Lactobacillus Firm-5. On the contrary, 10 µg/L flupyradifurone did not reduce syrup consumption, block larvae and pupae development in bumble-bees. Although no significant phenotypes were observed, PICRUST revealed that flupyradifurone suppressed pathways, involving carbohydrate metabolism, nucleotide metabolism, translation, and membrane transport. Our findings suggest the appropriate use of this new pesticide may be consid-ered safe for bumblebees, but the underlying mechanism warrants further investigation.
Keywords: B. terrestris; Flupyradifurone; Gut microbiota; Imidacloprid; Microcolony

Toxicity of the Pesticides Imidacloprid, Difenoconazole and Glyphosate Alone and in Binary and Ternary Mixtures to Winter Honey Bees: Effects on Survival and Antioxidative Defenses - Pal, Elisa; Almasri, Hanine; Paris, Laurianne; Diogon, Marie; Pioz, Maryline; Cousin, Marianne; Sené, Déborah; Tchamitchian, Sylvie; Tavares, Daiana Antonia; Delbac, Frédéric; Blot, Nicolas; Brunet, Jean Luc; et al. (Toxics, 2022)
To explain losses of bees that could occur after the winter season, we studied the effects of the insecticide imidacloprid, the herbicide glyphosate and the fungicide difenoconazole, alone and in binary and ternary mixtures, on winter honey bees orally exposed to food containing these pesticides at concentrations of 0, 0.01, 0.1, 1 and 10 µg/L. Attention was focused on bee survival, food consumption and oxidative stress. The effects on oxidative stress were assessed by deter-mining the activity of enzymes involved in antioxidant defenses (superoxide dismutase, catalase, glutathione-S-transferase, glutathione reductase, glutathione peroxidase and glucose-6-phosphate dehydrogenase) in the head, abdomen and midgut; oxidative damage reflected by both lipid per-oxidation and protein carbonylation was also evaluated. In general, no significant effect on food consumption was observed. Pesticide mixtures were more toxic than individual substances, and the highest mortalities were induced at intermediate doses of 0.1 and 1 µg/L. The toxicity was not always linked to the exposure level and the number of substances in the mixtures. Mixtures did not systematically induce synergistic effects, as antagonism, subadditivity and additivity were also observed. The tested pesticides, alone and in mixtures, triggered important, systemic oxidative stress that could largely explain pesticide toxicity to honey bees.
Keywords: honey bees; oxidative stress; pesticide mixtures; physiological alterations

Pesticides and reduced-risk insecticides, native bees and pantropical stingless bees: Pitfalls and perspectives - Barbosa, Wagner F.; Smagghe, Guy; Guedes, Raul Narciso C. (Pest Management Science, 2015)
Although invertebrates generally have a low public profile, the honey bee, Apis mellifera L., is a flagship species whose popularity likely derives from the products it provides and its perceived ecological services. Therefore, the raging debate regarding honey bee decline has surpassed the realm of beekeepers, academia, industry and regulatory agencies and now also encompasses non-governmental agencies, media, fiction writers and the general public. The early interest and concern about honey bee colony collapse disorder (CCD) soon shifted to the bigger issue of pollinator decline, with a focus on the potential involvement of pesticides in such a phenomenon. Pesticides were previously recognised as the potential culprits of the reported declines, particularly the neonicotinoid insecticides owing to their widespread and peculiar use in agriculture. However, the evidence for the potential pivotal role of these neonicotinoids in honey bee decline remains a matter of debate, with an increased recognition of the multifactorial nature of the problem and the lack of a direct association between the noted decline and neonicotinoid use. The focus on the decline of honey bee populations subsequently spread to other species, and bumblebees became another matter of concern, particularly in Europe and the United States. Other bee species, ones that are particularly important in other regions of the world, remain the object of little concern (unjustifiably so). Furthermore, the continuous focus on neonicotinoids is also in need of revision, as the current evidence suggests that a broad spectrum of compounds deserve attention. Here we address both shortcomings.
Keywords: Bioinsecticides; Biorational insecticides; Insecticidal stress; Meliponini; Wild pollinators

Honey bee losses and pesticides threat: an Asian perspective - Pervez, Mahnoor; Manzoor, Farkhanda (Journal of Apicultural Research, 2022)
In Asian countries, the agriculture sector is an important domain. Honey bees (Apis mellifera, L.) play an important role in the agricultural sector by pollinating the vast range of edible fruits and grain crops. The value of A. mellifera as the most valuable pollinating insect has long been recognized throughout the temperate and tropical zones of Asia. The worldwide value of pollinators is €153 billion (217 billion US dollars). Pollinators enhanced seed production, fruit setting, and yield. The main challenge faced throughout the world due to honey bee losses is starvation. It leads to a food security crisis. Both biotic and abiotic factors float bee survival challenges. Pesticides inevitably harm vital pollinators and cause lethal and sublethal toxicity. In Asia, excessive usage of pesticides is a great threat to pollinators. It disrupts molecular and physiological functions, behavior, and cognitive activities. Dealing with all constraints in an integrated way will be a profoundly vital necessity. Altering excessive chemical-intensive agriculture systems into an ecological farming system is a current requirement for food security. People should have awareness of sustainable pollination services through managing beekeeping practices.
Keywords: Asia; Honey bee; pesticides; pollinator losses

Evaluating the Impact of Commonly Used Pesticides on Honeybees (Apis mellifera) in North Gonder of Amhara Region, Ethiopia - Abay, Zewdie; Bezabeh, Amssalu; Gela, Alemayehu; Tassew, Asaminew (Journal of Toxicology, 2023)
Global honeybee losses and colony decline are becoming continuous threat to the apicultural industry, as well as, for food security and environmental stability. Although the putative causes are still unclear, extensive exposure of bees to pesticides could be the possible factor for worldwide colony losses. This study was aimed at evaluating the impact of nine commonly used pesticide incidents on adult worker honeybees (A. mellifera) under the laboratory condition, in North Gonder of Amhara region, Ethiopia. Feeding test, contact test, and fumigation tests were carried out for each pesticide following the standard procedures, and each pesticide toxicity was compared to the standard toxic chemical, dimethoate 40% EC (positive control), and to 50% honey solution (negative control). The results revealed that all the tested pesticides caused significant deaths of the experimental bees (P<0.05) in all the tests when compared to the negative control. Diazinon 60% EC, endosulfan 35% EC, and malathion 50% EC were appeared highly toxic causing 100% mortality of bees, while chlorsulfuron 75% WG killed 90% of the experimental bees as tested via feeding. On the other hand, agro-2, 4-D and its mixture with glycel 41% EC are moderately toxic, and mancozeb 80% WP and glycel 41% EC were slightly toxic to honeybees as compared to the positive control (dimethoate 40% EC). Suddenly, diazinon 60% EC and malathion 50% EC triggered 100% mortality of bees, while endosulfan 35% EC and chlorsulfuron 75% WG caused 63.63% and 90.82% of bee mortality, respectively, when evaluated via contact test. The fumigation test also showed that chlorsulfuron 75% WG, diazinon 60% EC, and endosulfan 35% EC caused 100%, 86.7%, and 65.6% mortality rate of bees. Our result also highlighted that tested LD50 of all pesticide incidents were significantly lower than the manufacturer-based LD50. This shows that local honeybees A. m. jemenetica are extremely sensitive to commonly used agricultural pesticides, which may affect the colony level due to the intensive application of these pesticides in Ethiopia.

Negative effects of pesticides on wild bee communities can be buffered by landscape context - Park, Mia G.; Blitzer, E. J.; Gibbs, Jason; Losey, John E.; Danforth, Bryan N. (Proceedings of the Royal Society B: Biological Sciences, 2015)
Wild bee communities provide underappreciated but critical agricultural pollination services. Given predicted global shortages in pollination services, managing agroecosystems to support thriving wild bee communities is, therefore, central to ensuring sustainable food production. Benefits of natural (including semi-natural) habitat for wild bee abundance and diversity on farms are well documented. By contrast, few studies have examined toxicity of pesticides on wild bees, let alone effects of farm-level pesticide exposure on entire bee communities. Whether beneficial natural areas could mediate effects of harmful pesticides on wild bees is also unknown. Here, we assess the effect of conventional pesticide use on the wild bee community visiting apple (Malus domestica) within a gradient of percentage natural area in the landscape. Wild bee community abundance and species richness decreased linearly with increasing pesticide use in orchards one year after application; however, pesticide effects on wild beeswere buffered by increasing proportion of natural habitat in the surrounding landscape. A significant contribution of fungicides to observed pesticide effects suggests deleterious properties of a class of pesticides that was, until recently, considered benign to bees. Our results demonstrate extended benefits of natural areas for wild pollinators and highlight the importance of considering the landscape context when weighing up the costs of pest management on crop pollination services.
Keywords: Agroecosystem; Apple; Native bees; Orchards; Pest management

Field populations of native Indian honey bees from pesticide intensive agricultural landscape show signs of impaired olfaction - Chakrabarti, Priyadarshini; Rana, Santanu; Bandopadhyay, Sreejata; Naik, Dattatraya G.; Sarkar, Sagartirtha; Basu, Parthiba (Scientific Reports, 2015)
Little information is available regarding the adverse effects of pesticides on natural honey bee populations. This study highlights the detrimental effects of pesticides on honey bee olfaction through behavioural studies, scanning electron microscopic imaging of antennal sensillae and confocal microscopic studies of honey bee brains for calcium ions on Apis cerana, a native Indian honey bee species. There was a significant decrease in proboscis extension response and biologically active free calcium ions and adverse changes in antennal sensillae in pesticide exposed field honey bee populations compared to morphometrically similar honey bees sampled from low/no pesticide sites. Controlled laboratory experiments corroborated these findings. This study reports for the first time the changes in antennal sensillae, expression of Calpain 1(an important calcium binding protein) and resting state free calcium in brains of honey bees exposed to pesticide stress.

Pesticide exposure of wild bees and honey bees foraging from field border flowers in intensively managed agriculture areas - Ward, Laura T.; Hladik, Michelle L.; Guzman, Aidee; Winsemius, Sara; Bautista, Ariana; Kremen, Claire; Mills, Nicholas J. (Science of the Total Environment, 2022)
Bees are critical for food crop pollination, yet their populations are declining as agricultural practices intensify. Pollinator-attractive field border plantings (e.g. hedgerows and forb strips) can increase bee diversity and abundance in agricultural areas; however, recent studies suggest these plants may contain pesticides. Pesticide exposure for wild bees remains largely unknown; however, this information is needed to inform agricultural practices and pesticide regulations meant to protect bees. It is important to determine whether border plantings that attract and support pollinators may also deliver pesticides to them. In this study, we collected various samples for pesticide residue analysis, including: multiple species of wild bees, honey bees, flowers from four types of bee-attractive field border plants, and soil. Silicone bands were also utilized as passive aerial samplers of pesticide residues. The five pesticides detected most frequently across all samples were the insecticide bifenthrin, the herbicides thiobencarb, metolaclor, and propanil, and the fungicide fluopyram. We detected the greatest number of parent pesticides in bands (24), followed by soil (21). Pesticides were also detected in field border plant flowers (16), which do not receive direct pesticide applications, and included many products which were not applied to adjacent field crops. Pesticide concentrations were lower in bees than in flowers but higher in bees than in soils. Pesticide residue per bee (ng/bee) increased with increasing wild bee size, though pesticide concentration (ng/g) did not increase. While honey bees and wild bees contained a similar number and concentration of pesticides overall, pesticide mixtures varied by bee type, and included some mixtures known to cause sublethal effects. The results from this study highlight the benefits of measuring more sample types to capture the total exposome of bees, including a greater range of bee species, as well as the need to consider exposure to pesticides at the landscape level.
Keywords: Bees; Exposure; Fungicide; Hedgerows; Herbicide; Insecticide

Acute exposure to sublethal doses of neonicotinoid insecticides increases heat tolerance in honey bees - Gonzalez, Victor H.; Hranitz, John M.; McGonigle, Mercedes B.; Manweiler, Rachel E.; Smith, Deborah R.; Barthell, John F. (PLoS ONE, 2022)
The European honey bee, Apis mellifera L., is the single most valuable managed pollinator in the world. Poor colony health or unusually high colony losses of managed honey bees result from a myriad of stressors, which are more harmful in combination. Climate change is expected to accentuate the effects of these stressors, but the physiological and behavioral responses of honey bees to elevated temperatures while under simultaneous influence of one or more stressors remain largely unknown. Here we test the hypothesis that exposure to acute, sublethal doses of neonicotinoid insecticides reduce thermal tolerance in honey bees. We administered to bees oral doses of imidacloprid and acetamiprid at 1/5, 1/20, and 1/100 of LD50 and measured their heat tolerance 4 h post-feeding, using both dynamic and static protocols. Contrary to our expectations, acute exposure to sublethal doses of both insecticides resulted in higher thermal tolerance and greater survival rates of bees. Bees that ingested the higher doses of insecticides displayed a critical thermal maximum from 2 ̊C to 5 ̊C greater than that of the control group, and 67%–87% reduction in mortality. Our study suggests a resilience of honey bees to high temperatures when other stressors are present, which is consistent with studies in other insects. We discuss the implications of these results and hypothesize that this compensatory effect is likely due to induction of heat shock proteins by the insecticides, which provides temporary protection from elevated temperatures.

Missing Nurse Bees—Early Transcriptomic Switch From Nurse Bee to Forager Induced by Sublethal Imidacloprid - Chen, Yun Ru; Tzeng, David T.W.; Ting, Chieh; Hsu, Pei Shou; Wu, Tzu Hsien; Zhong, Silin; Yang, En Cheng (Frontiers in Genetics, 2021)
The environmental residue/sublethal doses of neonicotinoid insecticides are believed to generate a negative impact on pollinators, including honey bees. Here we report our recent investigation on how imidacloprid, one of the major neonicotinoids, affects worker bees by profiling the transcriptomes of various ages of bees exposed to different doses of imidacloprid during the larval stage. The results show that imidacloprid treatments during the larval stage severely altered the gene expression profiles and may induce precocious foraging. Differential expression of foraging regulators was found in 14-day-old treated adults. A high transcriptome similarity between larvae-treated 14-day-old adults and 20-day-old controls was also observed, and the similarity was positively correlated with the dose of imidacloprid. One parts per billion (ppb) of imidacloprid was sufficient to generate a long-term impact on the bee’s gene expression as severe as with 50 ppb imidacloprid. The disappearance of nurse bees may be driven not only by the hive member constitution but also by the neonicotinoid-induced precocious foraging behavior.
Keywords: honey bee; imidacloprid; precocious foraging; sublethal dosage; transcriptome

OECD (2017)

A new design of bee cage for laboratory experiments: nutritional assessment of supplemental diets in honey bees (Apis mellifera) A new design of bee cage for laboratory experiments: nutritional assessment of supplemental diets in honey bees (Apis mellifera ) - Yang, Kai-Chieh; Peng, Zhi-Wei; Lin, Chun-Hsien; Wu, Ming-Cheng (Apidologie, 2021)
A new design of bee cage for laboratory experiments: nutritional assessment of supplemental diets in honey bees (Apis mellifera). Abstract-We designed a cage that can maintain adult bees for 21 days with about 90% survival rate, in addition to facilitating the changing of sucrose syrup and beebread, and collection of live and dead bees without disturbing or releasing bees. The consumption rates of bee pollen diet and sucrose syrup for groups of 50-200 honey bees were recorded for 21 days after emergence. The bees consumed the bee pollen diet mainly at the age of 1-9 days. Regular consumption of sucrose syrup was observed among all bee groups throughout the 21 days. Furthermore, the nutritional responses of nurse bees-specifically, the expressions of major royal jelly protein 1 (mrjp1) in the head and vitellogenin (vg) in the abdomen-upon the provision of five single-supplemental diets were evaluated. We aimed to improve the usability of bee cages by elucidating the food consumption of bees and the relationship between nutritional gene expression and the ingestion of each single-protein diet. Bee cage / Bee pollen substitutes / Major royal jelly protein 1 / Vitellogenin

Evaluation of cage designs and feeding regimes for honey bee (Hymenoptera: Apidae) laboratory experiments - Huang, Shao Kang; Csaki, Tamas; Doublet, Vincent; Dussaubat, Claudia; Evans, Jay D.; Gajda, Anna M.; Gregorc, Alex; Hamilton, Michele C.; Kamler, Martin; Lecocq, Antoine; Muz, Mustafa N.; Neumann, Peter; et al. (Journal of Economic Entomology, 2014)
The aim of this study was to improve cage systems for maintaining adult honey bee (Apis mellifera L.) workers under in vitro laboratory conditions. To achieve this goal, we experimentally evaluated the impact of different cages, developed by scientists of the international research network COLOSS (Prevention of honey bee COlony LOSSes), on the physiology and survival of honey bees. We identified three cages that promoted good survival of honey bees. The bees from cages that exhibited greater survival had relatively lower titers of deformed wing virus, suggesting that deformed wing virus is a significant marker reflecting stress level and health status of the host. We also determined that a leakand drip-proof feeder was an integral part of a cage system and a feeder modified from a 20-ml plastic syringe displayed the best result in providing steady food supply to bees. Finally,wealso demonstrated that the addition of protein to the bees' diet could significantly increase the level of vitellogenin gene expression and improve bees' survival. This international collaborative study represents a critical step toward improvement of cage designs and feeding regimes for honey bee laboratory experiments. © 2014 Entomological Society of America.
Keywords: Apis mellifera; COLOSS; Cage; Honey bee; Laboratory testing

Pesticide occurrence and water quality assessment from an agriculturally influenced Latin-American tropical region - Ramírez-Morales, Didier; Pérez-Villanueva, Marta E.; Chin-Pampillo, Juan S.; Aguilar-Mora, Paula; Arias-Mora, Víctor; Masís-Mora, Mario (Chemosphere, 2021)
A monitoring study was carried out in three agriculturally influenced microcatchments in Costa Rica during 2012–2014, for pesticides and water quality parameters. A total of 42 pesticides were analyzed, detecting the following in water samples: two herbicides (oxyfluorfen, diuron), four insecticides (carbofuran, chlorpyrifos, oxamyl, ethion), and two fungicides (thiabendazole, carbendazim); while in sediment samples only the insecticides, chlorpyrifos and cypermethrin were found. Water quality was also assessed by the Canadian Council of Ministers of the Environment Water Quality Index and the National Sanitation Water Quality Index, the first one classified most of the sampling point as marginal and poor quality while the second one classified most of them as good quality, the most affected parameters were nitrate, phosphorous, suspended solids and organic matter content. The results suggest that the water quality in the microcatchments seems to be affected by the nearby agricultural and urban activities in the region.
Keywords: Ecotoxicology; Environmental risk; Physicochemical analysis; Sediment; Surface water monitoring; Water quality index

Legacy and emerging pollutants in Latin America: A critical review of occurrence and levels in environmental and food samples - Souza, Marília Cristina Oliveira; Rocha, Bruno Alves; Adeyemi, Joseph A.; Nadal, Martí; Domingo, José Luis; Barbosa, Fernando (Science of the Total Environment, 2022)
The increase and indiscriminate use of personal care products, food products, fertilizers, pesticides, and health products, among others, have resulted/are resulting in extensive environmental contamination. Most of these products contain traces of widespread chemicals, usually known as emerging pollutants (EPs) or pollutants of emerging concern (PEC). The Latin American (LA) region comprises 20 countries with different social and cultural aspects, with 81 % of the population living in urban areas. The LA region has some countries on the top list of users/consumers of EPs, from pesticides and fertilizers to personal care products. However, there is a gap in information related to the distribution of EPs in the environment of this region, with very few existing review texts exploring this issue. Therefore, this present paper advances this approach. An exhaustive literature review, with the selection of 176 documents, provided unique up-to-date information on the presence/distribution of 17 classes of legacy or emerging pollutants in different food and environmental matrices (soil, sediment, water, and air). The study shows that the wide distribution and recorded levels of these pollutants in the continental environment are potential risks to human health, mainly through food and drinking water ingestion. Polycyclic aromatic hydrocarbons are pollutants of deep public concern since they show carcinogenic properties. Several classes of pollutants, like endocrine disruptors, have caused harmful effects on humans and the environment. Besides that, pharmaceutical products and pesticides are compounds of high consumption worldwide, being environmental contamination a real and ongoing possibility. Finally, gaps and future research needs are deeply pointed out.
Keywords: Emerging countries; Environmental pollutants; Environmental risks; Exposure sources; Health risks; Human exposure

A review of spline function procedures in R - Perperoglou, Aris; Sauerbrei, Willi; Abrahamowicz, Michal; Schmid, Matthias (BMC Medical Research Methodology, 2019)
Background: With progress on both the theoretical and the computational fronts the use of spline modelling has become an established tool in statistical regression analysis. An important issue in spline modelling is the availability of user friendly, well documented software packages. Following the idea of the STRengthening Analytical Thinking for Observational Studies initiative to provide users with guidance documents on the application of statistical methods in observational research, the aim of this article is to provide an overview of the most widely used spline-based techniques and their implementation in R. Methods: In this work, we focus on the R Language for Statistical Computing which has become a hugely popular statistics software. We identified a set of packages that include functions for spline modelling within a regression framework. Using simulated and real data we provide an introduction to spline modelling and an overview of the most popular spline functions. Results: We present a series of simple scenarios of univariate data, where different basis functions are used to identify the correct functional form of an independent variable. Even in simple data, using routines from different packages would lead to different results. Conclusions: This work illustrate challenges that an analyst faces when working with data. Most differences can be attributed to the choice of hyper-parameters rather than the basis used. In fact an experienced user will know how to obtain a reasonable outcome, regardless of the type of spline used. However, many analysts do not have sufficient knowledge to use these powerful tools adequately and will need more guidance.
Keywords: Functional form of continuous covariates; Multivariable modelling

Differential physiological effects of neonicotinoid insecticides on honey bees: A comparison between Apis mellifera and Apis cerana - Li, Zhiguo; Li, Meng; He, Jingfang; Zhao, Xiaomeng; Chaimanee, Veeranan; Huang, Wei Fone; Nie, Hongyi; Zhao, Yazhou; Su, Songkun (Pesticide Biochemistry and Physiology, 2017)
Acute toxicities (LD50s) of imidacloprid and clothianidin to Apis mellifera and A. cerana were investigated. Changing patterns of immune-related gene expressions and the activities of four enzymes between the two bee species were compared and analyzed after exposure to sublethal doses of insecticides. Results indicated that A. cerana was more sensitive to imidacloprid and clothianidin than A. mellifera. The acute oral LD50 values of imidacloprid and clothianidin for A. mellifera were 8.6 and 2.0 ng/bee, respectively, whereas the corresponding values for A. cerana were 2.7 and 0.5 ng/bee. The two bee species possessed distinct abilities to mount innate immune response against neonicotinoids. After 48 h of imidacloprid treatment, carboxylesterase (CCE), prophenol oxidase (PPO), and acetylcholinesterase (AChE) activities were significantly downregulated in A. mellifera but were upregulated in A. cerana. Glutathione-S-transferase (GST) activity was significantly elevated in A. mellifera at 48 h after exposure to imidacloprid, but no significant change was observed in A. cerana. AChE was downregulated in both bee species at three different time points during clothianidin exposure, and GST activities were upregulated in both species exposed to clothianidin. Different patterns of immune-related gene expression and enzymatic activities implied distinct detoxification and immune responses of A. cerana and A. mellifera to imidacloprid and clothianidin.
Keywords: Apis cerana; Apis mellifera; Clothianidin; Detoxification; Imidacloprid; Immunity

Guideline for the testing of chemical honey bee (Apis mellifera) - OCDE 245 (2017)

ENVIRONMENT DIRECTORATE JOINT MEETING OF THE CHEMICALS COMMITTEE AND THE WORKING PARTY ON CHEMICALS, PESTICIDES AND BIOTECHNOLOGY Cancels & replaces the same document of Guidance Document on Honey Bee (Apis mellifera) Larval Toxicity Test, Repeated Exposure Series on Testing and Assessment No. 239 (2021)
Following several questions raised after publication, the OECD would like to clarify that the validity criteria mentioned in paragraph 7 «across all replicates» should be understood as the average value across all replicates, a replicate being defined as the number of larvae originating from the same colony. JT03479290 OFDE This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Honey bees as bioindicators of changing global agricultural landscapes - Quigley, Tyler P.; Amdam, Gro V.; Harwood, Gyan H. (Current Opinion in Insect Science, 2019)
There is a growing need to understand relationships between agricultural intensification and global change. Monitoring solutions, however, often do not include pollinator communities that are of importance to ecosystem integrity. Here, we put forth the honey bee as an economical and broadly available bioindicator that can be used to assess and track changes in the quality of agricultural ecosystems. We detail a variety of simple, low-cost procedures that can be deployed within honey bee hives to gain generalizable information about ecosystem quality at multiple scales, and discuss the potential of the honey bee system in both environmental and ecological bioindication.

What Is Biophysics? Where Physics and Biology Meet — Caltech Magazine

Biophysics and systems biology - Noble, Denis (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2010)
Biophysics at the systems level, as distinct from molecular biophysics, acquired its most famous paradigm in the work of Hodgkin and Huxley, who integrated their equations for the nerve impulse in 1952. Their approach has since been extended to other organs of the body, notably including the heart. The modern field of computational biology has expanded rapidly during the first decade of the twenty-first century and, through its contribution to what is now called systems biology, it is set to revise many of the fundamental principles of biology, including the relations between genotypes and phenotypes. Evolutionary theory, in particular, will require re-assessment. To succeed in this, computational and systems biology will need to develop the theoretical framework required to deal with multilevel interactions. While computational power is necessary, and is forthcoming, it is not sufficient. We will also require mathematical insight, perhaps of a nature we have not yet identified. This article is therefore also a challenge to mathematicians to develop such insights. © 2010 The Royal Society.
Keywords: Cell biophysics; Computational biology; Mathematical biology; Systems biology

Grand challenges in biophysics - Alsteens, David (Frontiers in Biophysics, 2023)

What does physics have to offer biology? (2011)

Availability of Using Honeybees as Bioindicators of Pesticide Exposure in the Vicinity of Agricultural Environments in Taiwan - Hung, Chien Che; Yiin, Lih Ming (Toxics, 2023)
While pollinating, honeybees are subject to exposure to a variety of pesticides; with their characteristics of certain foraging distances, they could serve as bioindicators of pesticide exposure in a neighborhood. We conducted a study to assess availability by collecting and analyzing bee samples from 15 apiaries located in East Taiwan and dust samples from the adjacent environment, and by finding relations between both samples. Seventeen pesticides were selected for the analysis using gas or liquid chromatography coupled with mass spectrometry, and eight (three insecticides, two herbicides, and three fungicides) were more frequently detected from bee or dust samples; the levels of these pesticides were mostly under 1000 ng/g. Significant correlation results (r ≅ 0.8) between residue concentrations in bees and in dust suggest that honeybees could be a good bioindicator for exposure to herbicides and fungicides within certain ranges. The pesticide contents of sick/dead bees were much higher than those of healthy counterparts regarding any pesticide type, with the mean total concentrations of 635 ng/g and 176 ng/g, respectively. We conclude that honeybees could be used as bioindicators of pesticide exposure; sick/dead bees could serve as a warning sign of the severity of pesticide pollution.
Keywords: bee; bioindicator; dust; exposure; fungicide; herbicide; honey; insecticide; pesticide

A meta-analysis comparing the sensitivity of bees to pesticides - Arena, Maria; Sgolastra, Fabio (Ecotoxicology, 2014)
The honey bee Apis mellifera, the test species used in the current environmental risk assessment procedure, is generally considered as extremely sensitive to pesticides when compared to other bee species, although a quantitative approach for comparing the difference in sensitivity among bees has not yet been reported. A systematic review of the relevant literature on the topic followed by a meta-analysis has been performed. Both the contact and oral acute LD50 and the chronic LC50 reported in laboratory studies for as many substances as possible have been extracted from the papers in order to compare the sensitivity to pesticides of honey bees and other bee species (Apiformes). The sensitivity ratio R between the endpoint for the species a (A. mellifera) and the species s (bees other than A. mellifera) was calculated for a total of 150 case studies including 19 bee species. A ratio higher than 1 indicated that the species s was more sensitive to pesticides than honey bees. The meta-analysis showed a high variability of sensitivity among bee species (R from 0.001 to 2085.7), however, in approximately 95 % of the cases the sensitivity ratio was below 10. The effect of pesticides in domestic and wild bees is dependent on the intrinsic sensitivity of single bee species as well as their specific life cycle, nesting activity and foraging behaviour. Current data indicates a need for more comparative information between honey bees and non-Apis bees as well as separate pesticide risk assessment procedures for non-Apis bees. © 2014 Springer Science+Business Media.
Keywords: Apiformes; Apis mellifera; Comparative ecotoxicology; Environmental risk assessment; Pollinators; Toxicity

Sensitivity analyses for simulating pesticide impacts on honey bee 1 colonies 2 - Carmen Kuan, A; DeGrandi-Hoffman, Gloria; Curry, Robert; Garber, Kristina V; Snyder, Marcia N; Wolfe, Kurt L; Thomas Purucker, S (2018)
6 3 Crystal River Consulting, Tucson, AZ, stratpilot@gmail.com; 7 4 US EPA, Office of Pesticide Programs, Arlington, VA, garber.kristina@epa.gov, 8 kanarek.andrew@epa.gov; 9 5 US EPA, Office of Research and Development, Corvallis, OR, snyder.marcia@epa.gov; 10 6 US EPA, Office of Research and Development, Athens, GA, wolfe.kurt@epa.gov, 11 purucker.tom@epa.gov 12 13 We employ Monte Carlo simulation and sensitivity analysis techniques to describe the 14 population dynamics of pesticide exposure to a honey bee colony using the 15 VarroaPop+Pesticide model. Simulations are performed of hive population trajectories with and 16 without pesticide exposure to determine the effects of weather, queen strength, foraging activity, 17 colony resources, and Varroa populations on colony growth and survival. The daily resolution of 18 the model allows us to conditionally identify sensitivity metrics. Simulations indicate queen 19 strength and forager lifespan are consistent, critical inputs for colony dynamics in both the 20 control and exposed conditions. Adult contact toxicity, application rate and nectar load become 21 critical parameters for colony dynamics within exposed simulations. Daily sensitivity analysis 22 also reveals that the relative importance of these parameters fluctuates throughout the 23 simulation period according to the status of other inputs. 24
Keywords: colony population model; honey bee; pesticides; pollinator; sensitivity analysis

Erratum: Aversive conditioning in honey bees (Apis mellifera anatolica): A comparison of drones and workers (The Journal of Experimental Biology 216 (4124-4134)) - Dinges, Christopher W.; Avalos, Arian; Abramson, Charles I.; Arthur Craig, David Philip; Austin, Zoe M.; Varnon, Christopher A.; Nur Dal, Fatima; Giray, Tugrul; Wells, Harrington (Journal of Experimental Biology, 2013)

Effects of aversive conditioning on expression of physiological stress in honey bees (Apis mellifera) - Black, Timothy E.; Fofah, Ova; Dinges, Christopher W.; Ortiz-Alvarado, Carlos A.; Avalos, Arian; Ortiz-Alvarado, Yarira; Abramson, Charles I. (Neurobiology of Learning and Memory, 2021)
Stress is defined as any deviation from an organism's baseline physiological levels. Therefore, introduction of new stimuli and information, such as in learning, can be defined as a stressor. A large body of research exists examining the role that stress plays in learning, but virtually none addresses whether or not learning itself is a measurable cause of stress. The current study used a wide variety of learning centric stress responses. Researchers examined changes in expression of ten stress and learning related genes in various physiological systems in domesticated honey bees (Apis mellifera) as a result of exposure to an aversive conditioning task. Gene expression was examined using quantitative real-time polymerase chain reaction following the learning task. Results indicate that learning affects expression of some stress related genes.
Keywords: Aversive conditioning; Gene Expression; Honey bees; Learning; Stress; qPCR

Metabolic cost of freeze-thaw and source of CO2production in the freeze-tolerant cricket Gryllus veletis - Smith, Adam; Turnbull, Kurtis F.; Moulton, Julian H.; Sinclair, Brent J. (Journal of Experimental Biology, 2021)
Freeze-tolerant insects can survive the conversion of a substantial portion of their body water to ice. While the process of freezing induces active responses from some organisms, these responses appear absent from freeze-tolerant insects. Recovery from freezing likely requires energy expenditure to repair tissues and re-establish homeostasis, which should be evident as elevations in metabolic rate after thaw. We measured carbon dioxide (CO2) production in the spring field cricket (Gryllus veletis) as a proxy for metabolic rate during cooling, freezing and thawing and compared the metabolic costs associated with recovery from freezing and chilling. We hypothesized that freezing does not induce active responses, but that recovery from freeze-thaw is metabolically costly. We observed a burst of CO2 release at the onset of freezing in all crickets that froze, including those killed by either cyanide or an insecticide (thiacloprid), implying that the source of this CO2 was neither aerobic metabolism nor a coordinated nervous system response. These results suggest that freezing does not induce active responses from G. veletis, but may liberate buffered CO2 from hemolymph. There was a transient 'overshoot' in CO2 release during the first hour of recovery, and elevated metabolic rate at 24, 48 and 72 h, in crickets that had been frozen compared with crickets that had been chilled (but not frozen). Thus, recovery from freeze-thaw and the repair of freeze-induced damage appears metabolically costly in G. veletis, and this cost persists for several days after thawing.
Keywords: CTmin; Hemolymph; Metabolic rate; Respiratory quotient; Spiracles; TCO2

Chilled, starved or frozen: insect mitochondrial adaptations to overcome the cold - Lebenzon, Jacqueline E.; Overgaard, Johannes; Jørgensen, Lisa Bjerregaard (Current Opinion in Insect Science, 2023)
Physiological adaptations to tackle cold exposure are crucial for insects living in temperate and arctic environments and here we review how cold adaptation is manifested in terms of mitochondrial function. Cold challenges are diverse, and different insect species have evolved metabolic and mitochondrial adaptations to i) energize homeostatic regulation at low temperatures ii) stretch energy reserves during prolonged cold exposure, and iii) preserve the structural organization of organelles following extracellular freezing. While the literature is still sparse, our review suggests that cold-adapted insects preserve ATP production at low temperatures by maintaining preferred mitochondrial substrate oxidation, which is otherwise challenged in cold-sensitive species. Chronic cold exposure and metabolic depression during dormancy are linked to reduced mitochondrial metabolism and may involve mitochondrial degradation. Finally, adaptation to extracellular freezing could be associated with the superior structural integrity of the mitochondrial inner membrane following freezing which is linked to cellular and organismal survival.

Hyperkalaemia, not apoptosis, accurately predicts insect chilling injury: Hyperkalaemia and apoptosis in the cold - Carrington, Jessica; Andersen, Mads Kuhlmann; Brzezinski, Kaylen; MacMillan, Heath A. (Proceedings of the Royal Society B: Biological Sciences, 2020)
There is a growing appreciation that insect distribution and abundance are associated with the limits of thermal tolerance, but the physiology underlying thermal tolerance remains poorly understood. Many insects, like the migratory locust (Locusta migratoria), suffer a loss of ion and water balance leading to hyperkalaemia (high extracellular [K +[) in the cold that indirectly causes cell death. Cells can die in several ways under stress, and how they die is of critical importance to identifying and understanding the nature of thermal adaptation. Whether apoptotic or necrotic cell death pathways are responsible for low-temperature injury is unclear. Here, we use a caspase-3 specific assay to indirectly quantify apoptotic cell death in three locust tissues (muscle, nerves and midgut) following prolonged chilling and recovery from an injury-inducing cold exposure. Furthermore, we obtain matching measurements of injury, extracellular [K +[ and muscle caspase-3 activity in individual locusts to gain further insight into the mechanistic nature of chilling injury. We found a significant increase in muscle caspase-3 activity, but no such increase was observed in either nervous or gut tissue from the same animals, suggesting that chill injury primarily relates to muscle cell death. Levels of chilling injury measured at the whole animal level, however, were strongly correlated with the degree of haemolymph hyperkalaemia, and not apoptosis. These results support the notion that cold-induced ion balance disruption triggers cell death but also that apoptosis is not the main form of cell damage driving low-temperature injury.
Keywords: cold tolerance; ionoregulatory collapse; neuromuscular system; programmed cell death; thermal limits; thermal performance

Insect resilience: unraveling responses and adaptations to cold temperatures - Ullah, Farman; Abbas, Arzlan; Gul, Hina; Güncan, Ali; Hafeez, Muhammad; Gadratagi, Basana Gowda; Cicero, Lizette; Ramirez-Romero, Ricardo; Desneux, Nicolas; Li, Zhihong (Journal of Pest Science, 2024)
Insects are vital arthropods that significantly impact various ecosystems. Their successful colonization of diverse habitats spanning from cold to warm environments is made possible by numerous adaptations shaped by environmental selection. This comprehensive review delves into the spectrum of physiological adaptations exhibited by insects to thrive in diverse environments, with a particular emphasis on the connection between these adaptations and the challenges posed by cold temperatures. Focusing on both long-term and short-term strategies, the review highlights the key protective mechanisms that insects employ to cope and thrive in cold temperatures. To withstand these constraints, insects have developed four main strategies: freeze tolerance, freeze avoidance, cryoprotective dehydration, and vitrification. These adaptive responses involve crucial physiological and biochemical changes that enable insects to withstand low temperatures. Specifically, insects exhibit cold tolerance through a range of molecular adaptive strategies, which encompass alterations in the expression of specific target genes, the synthesis of ice core formers, and the production of polyol cryoprotectants. Despite these remarkable results, there is still a lack of in-depth knowledge about the major factors contributing to successful overwintering of insects and their ability to withstand extremely low temperatures. To address these gaps, technological advances and genome sequencing of model organisms are critical to uncover the molecular mechanisms in insect responses to low temperatures. The knowledge gained from these advances provides valuable information about insect cold tolerance strategies and paves the way for a better understanding of their ecological importance and potential applications in conservation and ecological management.
Keywords: Abiotic constraints; Climate change; Cold tolerance; Environment; Physiological adaptations; Protective mechanisms

Supercooling points of freeze-avoiding bumble bees vary with caste and queen life stage - Keaveny, Ellen C.; Waybright, Sarah A.; Rusch, Travis W.; Dillon, Michael E. (Journal of Thermal Biology, 2022)
Bumble bees thrive in cold climates including high latitude and high altitude regions around the world, yet cold tolerance strategies are largely unknown for most species. To determine bumble bee cold tolerance strategy, we exposed bumble bees to a range of low temperatures and measured survival 72 h post-exposure. All bees that froze died within 72 h while only one bee died without freezing, suggesting that bumble bees are generally freeze-avoiding insects and may be slightly chill susceptible. We then assessed whether temperatures that cause internal ice formation (supercooling points, SCP) varied among bumble bee castes (drones, workers, and queens), or across queen life stages, collection elevation, species, or season. Males froze at significantly lower temperatures than workers or queens. Queens in pre-overwintering or overwintering states froze at significantly lower temperatures than queens stimulated to initiate ovary development by CO2 narcosis (i.e., “spring” queens). We also tested whether the presence of water (i.e., wet or dry) or ramping rate affected SCP. As expected, queens inoculated with water froze at significantly higher temperatures than dry queens. SCP tended to be lower, but not significantly so, at faster ramping rates (0.5 °C/min vs 0.25 °C/min). We also found no differences in SCP between queen bumble bees collected in spring and fall, between queens collected at two sites differing in elevation by 1100 m, or between three field-caught bumble bee species. Bumble bees appear to have relatively high, invariable SCPs, likely making them highly susceptible to freezing across all seasons. As bumble bees are not freeze-tolerant and appear to lack the ability to prevent freezing at temperatures much below 0 °C, they may rely on season- and caste-specific micro-habitat selection to thrive in cold climates.
Keywords: Bombus; Chill susceptible; Cold tolerance; Freeze avoidant; Overwintering

Body mass and sex, not local climate, drive differences in chill coma recovery times in common garden reared bumble bees - Oyen, K. Jeannet; Jardine, Laura E.; Parsons, Zachary M.; Herndon, James D.; Strange, James P.; Lozier, Jeffrey D.; Dillon, Michael E. (Journal of Comparative Physiology B: Biochemical, Systemic, and Environmental Physiology, 2021)
The time required to recover from cold exposure (chill coma recovery time) may represent an important metric of performance and has been linked to geographic distributions of diverse species. Chill coma recovery time (CCRT) has rarely been measured in bumble bees (genus Bombus) but may provide insights regarding recent changes in their distributions. We measured CCRT of Bombus vosnesenskii workers reared in common garden laboratory conditions from queens collected across altitude and latitude in the Western United States. We also compared CCRTs of male and female bumble bees because males are often overlooked in studies of bumble bee ecology and physiology and may differ in their ability to respond to cold temperatures. We found no relationship between CCRT and local climate at the queen collection sites, but CCRT varied significantly with sex and body mass. Because differences in the ability to recover from cold temperatures have been shown in wild-caught Bombus, we predict that variability in CCRT may be strongly influenced by plasticity.
Keywords: Allometry; Bombus vosnesenskii; CCRT; Cold tolerance; Thermal ecology

Winter packings in honey bees (Apis cerana) to reduce winter mortality in Kashmir Himalayas - Ahmad, Muneer; And Kashmir, Jammu; Correspondence, India (Journal of Applied Entomologist, 2023)
Bees provide a range of ecosystem services that contribute to the wellbeing of people whilst maintaining the planet's life support systems by pollination services. It is very important to save this creature by caring its health. A colony of honey bees (Apis cerana) does not hibernate in winter. The bees form cluster, clinging tightly together on the combs of hive. They employ fairly sophisticated thermal management strategies to prepare the nest and protect the colony from freezing. However, the precise nature of the cluster, its response to external temperature and ability to survive extreme cold for extended periods in chilly winter in Kashmir was studied in this programme. the activity of honey bees in harsh winter in Kashmir valley especially the 40 days which starts from 20 th December to January 30 th which cause winter mortality in bees. Colony winter mortality varied considerably in different regions of the state. Survey conducted during2015-2020 revealed that 72.55 percent farmers used gunny bags as packing material while as 26.93 percent use rice straw. Our study shows highest 80.00percent survivability of bees with using packing combination of Paper Rice straw gunny bags. The economics of migratory and non-migratory honey bees were worked out in our study programme.
Keywords: Apis cerana; health; honey bees; winter packings

Effects of developmental state on low-temperature physiology of the alfalfa leafcutting bee, Megachile rotundata - Bennett, Meghan M.; Debardlabon, Korie M.; Rinehart, Joseph P.; Yocum, George D.; Greenlee, Kendra J. (Bulletin of Entomological Research, 2023)
The success of agriculture relies on healthy bees to pollinate crops. Commercially managed pollinators are often kept under temperature-controlled conditions to better control development and optimize field performance. One such pollinator, the alfalfa leafcutting bee, Megachile rotundata, is the most widely used solitary bee in agriculture. Problematically, very little is known about the thermal physiology of M. rotundata or the consequences of artificial thermal regimes used in commercial management practices. Therefore, we took a broad look at the thermal performance of M. rotundata across development and the effects of commonly used commercial thermal regimes on adult bee physiology. After the termination of diapause, we hypothesized thermal sensitivity would vary across pupal metamorphosis. Our data show that bees in the post-diapause quiescent stage were more tolerant of low temperatures compared to bees in active development. We found that commercial practices applied during development decrease the likelihood of a bee recovering from another bout of thermal stress in adulthood, thereby decreasing their resilience. Lastly, commercial regimes applied during development affected the number of days to adult emergence, but the time of day that adults emerged was unaffected. Our data demonstrate the complex interactions between bee development and thermal regimes used in management. This knowledge can help improve the commercial management of these bees by optimizing the thermal regimes used and the timing of their application to alleviate negative downstream effects on adult performance.
Keywords: CT min; Megachile; solitary bee; survival; thermal stress

Effect of cold narcosis on foraging behavior of European honey bees (Apis mellifera ligustica) tracked using a radio-frequency identification (RFID) system - Okubo, Satoru; Yoshiyama, Mikio; Nikkeshi, Aoi; Morimoto, Nobuo; Kimura, Kiyoshi (Journal of Apicultural Research, 2020)
Radio-frequency identification (RFID) is both a commonly used method and a promising tool for investigating the foraging activities of bees. To prevent loss of electronic tags from individual bees, they must be immobilized long enough for adhesives to dry, but because narcosis can negatively affect bee health and behaviors, a very brief narcosis period is recommended. The present study assessed the impact of 30 min of cold narcosis, compared with carbon dioxide or no narcosis, on foraging activities using RFID monitoring. From each of three hives, 8 to 10 bees were placed in each of three narcosis treatments (n = 85), then tagged and monitored for homing success, activity after returning to the hive, and duration of flights outside the hive. Bees showed no significant differences in homing success and flight duration between cold narcosis treatment and the control (no narcosis), whereas bees narcotized by carbon dioxide showed significantly lower homing success and shorter flight duration than control bees. We conclude that for observing bee foraging behaviors using RFID systems, the effects of cold narcosis on ice for 30 min on foraging behaviors are acceptable, and cold narcosis is more practical for tagging many bees at once than physical immobilization using plunger cages.
Keywords: anesthesia; carbon dioxide narcosis; chill-coma; ice chilling; ultra-high-frequency tag

Cold stress induces specific antioxidant responses in honey bee brood - Mucci, Claudio Andoni; Ramirez, Leonor; Giffoni, Rocío Soledad; Lamattina, Lorenzo (Apidologie, 2021)
Multiple harmful factors cause chronic sub-lethal stress in managed honey bee colonies. In weak colonies, worker bees may not efficiently maintain the optimum temperature (33–36°C) in peripheral brood development areas. A short period at 25°C induces physiological adjustments and increases the mortality in honey bee brood reared in vitro. Molecular damage due to oxidative imbalance can be one of the main causes of mortality when organisms are under stress. Here, we demonstrate that in vitro rearing honey bee brood exposed 3 days at sub-optimal temperature (25°C) does not lead to H2O2 accumulation and oxidative protein damage. Cold-stressed honey bee brood showed increased levels of both total antioxidant status (TAS) and expression of peroxiredoxins PRX1 and PRX4, but not of catalase activity. Results indicate that specific antioxidant defenses induced in honey bee brood under moderated cold stress are enough to keep H2O2 levels under control and avoid major protein damages. It is concluded that the increase of mortality in cold-stressed brood are due to multifactor’s, beyond uncontrolled oxidative injuries.
Keywords: antioxidant responses; cold stress; honey bee brood; oxidative damage

The honey bee (Apis mellifera L., 1758) and the seasonal adaptation of productions. Highlights on summer to winter transition and back to summer metabolic activity. A review - Knoll, Stephane; Pinna, Walter; Varcasia, Antonio; Scala, Antonio; Cappai, Maria Grazia (Livestock Science, 2020)
Beekeeping plays a key role within animal productions since millennia. Honey bee colonies consist mainly out of worker bees which, besides based on their behavioural roles, are divided according to seasonal appearance. In this manner, a distinction is made between classical summer bees and long lived winter or “diutinus” bees. Seasonal transition into their winter form allows honey bee colonies to survive harsh winter conditions through in-hive thermoregulation and by initiating brood rearing for the new cycle. Vitellogenin, the main bee nutritional storage molecule, is central in winter bee physiology and accounts for the typical features associated with diutinus bees (high hemolymph and fat body lipid and protein contents, hypertrophied hypopharyngeal glands and longevity). Overall, transition into the winter bee state can be explained by extension of the mechanisms regulating juvenile hormone metabolism and worker bee age based division of labour, namely; changes in bee nutrient stores, brood microclimate and colony age demography. Furthermore, substantial evidence has been produced indicating the arrival of winter bees to be strongly correlated to decreasing brood rearing activity in fall. Subsequently, factors regulating the brood rearing pattern of honey bees can be considered key triggers in the appearance of winter bees. In this way, the arrival of winter bees is mainly linked to plummeting pollen supplies in fall. The effect of other triggers have either been categorised as lesser, indirect or their involvement remains unclear. The current knowledge regarding the functionality of the seasonal transition of honey bee colonies has led to the description of an elegant system controlled by a multitude of internal and external factors. Regardless, certain aspects of this phenomenon still remain unknown and especially the transition back from winter to summer bees still represents an open question.
Keywords: Fat body; Hypopharyngeal glands; Juvenile hormone; Overwintering. vitellogenin; Winter bees

Metabolic effects of anesthetics (cold, CO2, and isoflurane) and captivity conditions in isolated honey bee (Apis mellifera) foragers under different ambient temperatures - Gooley, Zuyi C.; Gooley, Aaron C. (Journal of Apicultural Research, 2023)
Acclimation and anesthesia are necessary steps when manipulating live honey bees, Apis mellifera, in laboratory. Although cold and carbon dioxide exposure are commonly used to temporarily immobilize honey bees, they are known to influence the bees’ physiology and behavior in various ways. We investigated the effect of captivity conditions and anesthesia methods on the non-flight metabolic rate in honey bee foragers under different ambient temperatures (25, 30, or 35 °C) by using flow-through respirometry. Honey bees experienced a significant drop in metabolic rate as they acclimate to captivity at normal laboratory temperature (25 °C), but did not show much change at higher temperatures. We found that cold and carbon dioxide exposure greatly affected honey bees’ metabolic rates during and after recovery from the anesthesia regardless of the ambient temperatures. Compared to these traditional anesthesia methods, isoflurane at the dose tested is an alternative anesthetic with a) less effect on honey bees’ metabolic rate, b) an adjustable recovery time that depends on ambient temperature, and c) visible sign of life displayed by anesthetized honey bees.
Keywords: anesthesia; captivity; honey bees; metabolic rate; temperature

Fast weight recovery, metabolic rate adjustment and gene-expression regulation define responses of cold-stressed honey bee brood - Ramirez, Leonor; Luna, Facundo; Mucci, Claudio Andoni; Lamattina, Lorenzo (Journal of Insect Physiology, 2021)
In temperate climates, low ambient temperatures in late winter and in spring can result in cold stress conditions in brood areas of weakened honey bee colonies, leading to increased levels of developmental interruptions and death of the brood. Very little is known about the physiological and molecular mechanisms that regulate honey bee brood responses to acute cold-stress. Here, we hypothesized that central regulatory pathways mediated by insulin/insulin-like peptide signalling (IIS) and adipokinetic hormone (AKH) are linked to metabolic changes in cold-stressed honey bee brood. A. mellifera brood reared at suboptimal temperatures showed diminished growth rate and arrested development progress. Notably, cold-stressed brood rapidly recovers the growth in the first 24 h after returning at control rearing temperature, sustained by the induction of compensatory mechanisms. We determined fast changes in the expression of components of IIS and AKH pathways in cold-stressed brood supporting their participation in metabolic events, growth and stress responses. We also showed that metabolic rate keeps high in brood exposed to stress suggesting a role in energy supply for growth and cell repair. Additionally, transcript levels of the uncoupling protein MUP2 were elevated in cold-stressed brood, which could indicate that this protein acts in the heat generation through mitochondrial decoupling mechanisms and/or in the ROS attenuation. Physiological, metabolic and molecular mechanisms that shape the responses to cold-stress in honey bee brood are addressed and discussed.
Keywords: Adipokinetic hormone; Cold stress; Compensatory growth; Honey bee brood; Insulin/insulin-like peptide signalling; Metabolic adjustments

Impact of low temperatures on the immune system of honeybees - Butolo, N. P.; Azevedo, P.; Alencar, L. D.; Malaspina, O.; Nocelli, R. C.F. (Journal of Thermal Biology, 2021)
Changes in temperature resulting from climate change can impact the distribution and survival of species, including bees, where temperature may also affect their immune system. Evaluation of immune system activity is often performed by the total count of circulating hemocytes in the hemolymph. However, there are few studies on bees examining the relationship between the amount of circulating hemocytes and temperature. This study evaluated changes of circulating hemocytes in Apis mellifera hemolymph at different temperatures and development stages. Total hemocytes of bees were determined at - 8, 16, 24, and 32 °C - and at different development stages - in vivo larvae, in vitro larvae, newly emerged, and forager bees. A. mellifera larvae had a greater number of circulating hemocytes compared to the other development stages (newly emerged and foragers). Additionally, temperature was an important factor explaining variation of circulating hemocytes in the hemolymph, according to principal component analyses (PCA), as the number of circulating hemocytes was greater at higher temperatures. Therefore, extreme events arising from climate change, such as variation in temperature, can directly impact the immune system of bees, both individually and at the colony level, threatening the distribution and survival of several species.
Keywords: Africanized Apis mellifera; Climate changes; Defense cells; Global thermal variation; Innate immune system; Total hemocyte count

Tissue-specific transcriptional patterns underlie seasonal phenotypes in honey bees (Apis mellifera) - Bresnahan, Sean T.; Döke, Mehmet A.; Giray, Tugrul; Grozinger, Christina M. (Molecular Ecology, 2022)
Faced with adverse conditions, such as winter in temperate regions or hot and dry conditions in tropical regions, many insect species enter a state of diapause, a period of dormancy associated with a reduction or arrest of physical activity, development and reproduction. Changes in common physiological pathways underlie diapause phenotypes in different insect species. However, most transcriptomic studies of diapause have not simultaneously evaluated and compared expression patterns in different tissues. Honey bees (Apis mellifera) represent a unique model system to study the mechanisms underpinning diapause-related phenotypes. In winter, honey bees exhibit a classic diapause phenotype, with reduced metabolic activity, increased physiological nutritional resources and altered hormonal profiles. However, winter bees actively heat their colony by vibrating their wing muscles; thus, this tissue is not quiescent. Here, we evaluated the transcriptional profiles of flight muscle tissue and fat body tissue (involved in nutrient storage, metabolism and immune function) of winter bees. We also evaluated two behavioural phenotypes of summer bees: nurses, which exhibit high nutritional stores and low flight activity, and foragers, which exhibit low nutritional stores and high flight activity. We found winter bees and nurses have similar fat body transcriptional profiles, whereas winter bees and foragers have similar flight muscle transcriptional profiles. Additionally, differentially expressed genes were enriched in diapause-related gene ontology terms. Thus, honey bees exhibit tissue-specific transcriptional profiles associated with seasonal phenotypes, laying the groundwork for future studies evaluating the mechanisms, evolution and consequences of this tissue-specific regulation.

Thermal stress induces tissue damage and a broad shift in regenerative signaling pathways in the honey bee digestive tract - Bach, Dunay M.; Holzman, Miriam A.; Wague, Fatoumata; Miranda, J. J.L.; Lopatkin, Allison J.; Mansfield, Jennifer H.; Snow, Jonathan W. (Journal of Experimental Biology, 2021)
Honey bee colonies in the USA have suffered from increased die-off in the last few years with a complex set of interacting stresses playing a key role. With changing climate, an increase in the frequency of severe weather events, such as heat waves, is anticipated. Understanding how these changes may contribute to stress in honey bees is crucial. Individual honey bees appear to have a high capacity to endure thermal stress. One reason for this high-level endurance is likely their robust heat shock response (HSR), which contributes to thermotolerance at the cellular level. However, less is known about other mechanisms of thermotolerance, especially those operating at the tissue level. To elucidate other determinants of resilience in this species, we used thermal stress coupled with RNAseq and identified broad transcriptional remodeling of a number of key signaling pathways in the honey bee, including those pathways known to be involved in digestive tract regeneration in the fruit fly such as the Hippo and JAK/STAT pathways. We also observed cell death and shedding of epithelial cells, which likely leads to induction of this regenerative transcriptional program. We found that thermal stress affects many of these pathways in other tissues, suggesting a shared program of damage response. This study provides important foundational characterization of the tissue damage response program in this key pollinating species. In addition, our data suggest that a robust regeneration program may also be a critical contributor to thermotolerance at the tissue level, a possibility which warrants further exploration in this and other species.
Keywords: Apis mellifera; Heat shock response; Hippo pathway; JAK/STAT pathway; Proteostasis; Regeneration; Thermotolerance

Erratum: The neonicotinoid imidacloprid impairs honey bee aversive learning of simulated predation (Journal of Experimental Biology(2015)218(3199-3205)Doi: 10.1242/jeb.127472) - Zhang, Erica; Nieh, James C. (Journal of Experimental Biology, 2020)
The concentration of imidacloprid is erroneously given as of 1.5 μg per bee day-1 in the Abstract; this should be 1.5 ng per bee day-1, as correctly stated in Results. Both the online full-text and PDF versions have been updated. The authors apologise to readers for this error.

Visual learning in tethered bees modifies flight orientation and is impaired by epinastine - Kobayashi, Norihiro; Hasegawa, Yuji; Okada, Ryuichi; Sakura, Midori (Journal of Comparative Physiology A: Neuroethology, Sensory, Neural, and Behavioral Physiology, 2023)
Visual-orientation learning of a tethered flying bee was investigated using a flight simulator and a novel protocol in which orientation preference toward trained visual targets was assessed in tests performed before and after appetitive conditioning. Either a blue or a green rectangle (conditioned stimulus, CS) was associated with 30% sucrose solution (unconditioned stimulus, US), whereas the other rectangle was not paired with US. Bees were tested in a closed-looped flight simulator 5 min after ten pairings of the US and CS. Conditioned bees were preferentially oriented to the CS after such training. This increase in preference for CS was maintained for 24 h, indicating the presence of long-term memory. Because the total orienting time was not altered by conditioning, conditioning did not enhance orientation activity itself but increased the relative time for orientation to CS. When 0.4 or 4 mM epinastine (an antagonist of octopamine receptors) was injected into the bee’s head 30 min prior to the experiment, both short- and long-term memory formation were significantly impaired, suggesting that octopamine, which is crucial for appetitive olfactory learning in insects, is also involved in visual orientation learning.
Keywords: Color discrimination; Flight simulator; Honey bee; Octopamine; Visual learning

Involvement of octopamine in conditioned visual ight orientation in honeybees - Kobayashi, Norihiro; Hasegawa, Yuji; Okada, Ryuichi; Sakura, Midori (2022)
Visual orientation learning of a tethered ying bee was investigated using a ight simulator with a novel protocol using which orientation preference tests were performed before and after classical conditioning was applied. Either a blue or a green rectangle (conditioned stimulus, CS) was associated with 30% sucrose solution (unconditioned stimulus, US), whereas the other was not paired with US. Bees were tested in a closed-looped ight simulator 5 min after ten pairing presentations of US and CS. Conditioned bees preferentially oriented to the CS compared to the other color. This increase in the preference for CS was maintained for 24 h, indicating that long-term memory was established by this procedure. Because the total ight time was not altered by the conditioning, conditioning did not enhance orientation activity itself but increased the relative time for orientation to CS. When 0.4 or 4 mM epinastine (an antagonist of the octopamine receptor) was injected into the bee's head 30 min prior to the experiment, both short-and long-term memory formation were signicantly impaired, strongly suggesting that octopamine, which is crucial for appetitive olfactory learning in insects, is also involved in visual orientation learning.
Keywords: color discrimination; honeybee; ight simulator; octopamine; visual learning

Comparing the appetitive learning performance of six european honeybee subspecies in a common apiary - Scheiner, Ricarda; Lim, Kayun; Meixner, Marina D.; Gabel, Martin S. (Insects, 2021)
The Western honeybee (Apis mellifera L.) is one of the most widespread insects with numerous subspecies in its native range. How far adaptation to local habitats has affected the cognitive skills of the different subspecies is an intriguing question that we investigate in this study. Naturally mated queens of the following five subspecies from different parts of Europe were transferred to Southern Germany: A. m. iberiensis from Portugal, A. m. mellifera from Belgium, A. m. macedonica from Greece, A. m. ligustica from Italy, and A. m. ruttneri from Malta. We also included the local subspecies A. m. carnica in our study. New colonies were built up in a common apiary where the respective queens were introduced. Worker offspring from the different subspecies were compared in classical olfactory learning performance using the proboscis extension response. Prior to conditioning, we measured individual sucrose responsiveness to investigate whether possible differences in learning performances were due to differential responsiveness to the sugar water reward. Most subspecies did not differ in their appetitive learning performance. However, foragers of the Iberian honeybee, A. m. iberiensis, performed significantly more poorly, despite having a similar sucrose responsiveness. We discuss possible causes for the poor performance of the Iberian honeybees, which may have been shaped by adaptation to the local habitat.
Keywords: Adaptation; Apis mellifera; Genetic diversity; Olfactory learning; Proboscis extension response; Sucrose responsiveness

Low-Level Fluvalinate Treatment in the Larval Stage Induces Impaired Olfactory Associative Behavior of Honey Bee Workers in the Field - Ko, Chong Yu; Nai, Yu Shin; Lo, Wei; Chen, Chun Ting; Chen, Yue Wen (Insects, 2022)
Fluvalinate is a widely used insecticide for varroa mite control in apiculture. While most beekeepers have ignored the effects of low levels of fluvalinate on bees, this study aims to demonstrate its effects at very low concentrations. We first used fluvalinate doses ranging from 0.4 to 400 ng/larva to monitor the capping, pupation, and emergence rates of larval bees. Second, we used the honey bees’ proboscis extension reflex reaction to test the learning ability of adult bees that were exposed to fluvalinate doses from 0.004 to 4 ng/larva in the larval stage. The brood-capped rate of larvae decreased dramatically when the dose was increased to 40 ng/larva. Although no significant effect was observed on brood-capping, pupation, and eclosion rates with a dose of 4 ng/larva, we found that the olfactory associative behavior of adult bees was impaired when they were treated with sublethal doses from 0.004 to 4 ng/larva in the larval stage. These findings suggest that a sublethal dose of fluvalinate given to larvae affects the subsequent associative ability of adult honey bee workers. Thus, a very low dose may affect the survival conditions of the entire colony.
Keywords: Fluvalinate; Honey bee; Proboscis extension reflex; Sublethal dosage

Associative Learning of Quantitative Mechanosensory Stimuli in Honeybees - Strelevitz, Heather; Tiraboschi, Ettore; Haase, Albrecht (Insects, 2024)
The proboscis extension response (PER) has been widely used to evaluate honeybees’ (Apis mellifera) learning and memory abilities, typically by using odors and visual cues for the conditioned stimuli. Here we asked whether honeybees could learn to distinguish between different magnitudes of the same type of stimulus, given as two speeds of air flux. By taking advantage of a novel automated system for administering PER experiments, we determined that the bees were highly successful when the lower air flux was rewarded and less successful when the higher flux was rewarded. Importantly, since our method includes AI-assisted analysis, we were able to consider subthreshold responses at a high temporal resolution; this analysis revealed patterns of rapid generalization and slowly acquired discrimination between the rewarded and unrewarded stimuli, as well as indications that the high air flux may have been mildly aversive. The learning curve for these mechanosensory stimuli, at least when the lower flux is rewarded, more closely mimics prior data from olfactory PER studies rather than visual ones, possibly in agreement with recent findings that the insect olfactory system is also sensitive to mechanosensory information. This work demonstrates a new modality to be used in PER experiments and lays the foundation for deeper exploration of honeybee cognitive processes when posed with complex learning challenges.
Keywords: automation; decision making; honeybee; learning; mechanosensation; proboscis extension

The thermal model of winter aggregation of bees - Oskin, S. V.; Tsokur, D. S.; Sultanov, G. A.; Kudryavtseva, A. A. (IOP Conference Series: Earth and Environmental Science, 2020)
For successful competition of the Russian beekeepers in the world honey market it is necessary to concentrate their attention on production of separate grades of this product. The most expensive honey is produced in spring and therefore it is necessary that the bees were successful in winter. The use of electric heating of bee hives does not always have a positive effect on the safety of bees in winter. In this regard, it is necessary to study more carefully the complex biological formation - winter bee hives. There were the basic equations for determining the physical parameters of the bee family in winter, including the energy characteristic. The established equations were included in the mathematical models describing the parameters of the microclimate. Mathematical processing of the obtained thermophysical model was carried out in the Comsol software product, which confirmed the validity of the use of the main functional dependencies and allowed to see the critical zones of the hive in temperature and humidity. Despite the large temperature changes outside the hive, it is maintained a fairly stable positive temperature at the level of +25C to + 32C inside. Such temperatures are not dangerous for bees. The images of temperature fields obtained in the course of mathematical processing confirm the assumptions that the lowest temperatures are in the lower part of the hive, and the higher ones are in the upper part. The results of the simulation will be used to determine the optimal power supply to electric heaters and to the place of their installation.

Thermal limits of Africanized honey bees are influenced by temperature ramping rate but not by other experimental conditions - Gonzalez, Victor H.; Oyen, Kennan; Ávila, Omar; Ospina, Rodulfo (Journal of Thermal Biology, 2022)
Interest in assessing the critical thermal limits of bees is rapidly increasing, as these physiological traits are good predictors of bees' potential responses to extreme temperature changes, which is relevant in the context of global climate change. However, estimates of thermal limits may be influenced by several factors and published studies differ in experimental methods and conditions, such as the rate of temperature change (ramping rate) and feeding status, which might yield inaccurate predictions and limit comparisons across taxa and regions. Using Africanized honey bees as a model organism, we assessed the effect of ramping rate (0.25, 0.5, 0.75, 1.0 and 1.5 °C min−1) and length of starvation (recently fed vs. fasted for 6, 12, and 18 h) on foragers’ lower (CTMin) and upper (CTMax) thermal limits, as well as the effect of cold stress on CTMax. In addition, we evaluated the two approaches currently used to assess CTMax with a water bath: floating or submerging the testing vials in the bath. We found that critical thermal limits were influenced by ramping rates but not by the other assessed experimental conditions. On average, at ramping rates faster than 0.5 °C min−1, bees displayed a CTMin 1.1–2.6 °C lower and a CTMax 5.3–6.9 °C higher than those of the slowest ramping rate. We discuss the implications of these results and provide suggestions for future thermal studies on bees.
Keywords: Bees; Critical thermal maximum; Critical thermal minimum; Pollinators; Ramping rate; Tropics

Honey bee (Apis mellifera) size determines colony heat transfer when brood covering or distributed - Mitchell, Derek Morville (International Journal of Biometeorology, 2022)
Heat transfer is key to the survival of honey bee colonies (Apis mellifera L.) in the wide range of hot (e.g. sub-Saharan) and cool climates (e.g. maritime-temperate) in which they have evolved and adapted. Here, a validated computational fluid dynamics, conjugate heat transfer model was used to determine the heat transfer of honey bee colonies in simulated standard wooden hives, complete with combs and brood, for a broad range of honey bee sizes, from slender lowland African A.m. scutellata, to broader (larger diameter) Northern European A.m. mellifera, across the whole range of brood covering honey bee densities, as well as when evenly distributed throughout the hive. It shows that under cooling stress, brood covering, broad subspecies need less than a third of the number of bees per unit of brood area for thermal insulation compared to slender subspecies. Also, when distributed evenly around the nest, broad subspecies lose less brood heat than when brood covering. These simulations demonstrate that honey bee girth has climate-based evolutionary advantages directly for the colony as well as via the survival of the individual. In addition, it shows that non-clustering behavioural patterns of passive honey bees can make significant, subspecies distinctive changes to nest heat loss and therefore honey production and climate change survival.
Keywords: Acclimation; CFD; Climate change; Heat transfer; Thermofluids

Effect of floral locations on physicochemical and thermal honey bee properties - Uzochukwu Asoiro, Felix; Imologie Simeon, Meshack; Eberechukwu Azuka, Chinenye
The effects of floral location on the physicochemical and thermal parameters of honey bee samples from Enugu North senatorial zone were evaluated. For physicochemical properties, a 14×5×10 completely randomized design (CRD) with a total of 700 observations (14 physicochemical properties as responses × 5 levels of floral location as treatment × 10 replications) was conducted. For thermal properties, a 3×5×10 CRD with a total of 150 observations (3 thermal properties as responses × 5 levels of floral location as treatment × 10 replications) was also conducted. Floral location had significant effects (P ≤ 0.05) on viscosity, electrical conductivity, sugar content, free acidity, ash content, moisture content, density, pH, colour, thermal heat conductivity and thermal heat diffusivity except, fructose/glucose (F/G) ratio and specific heat capacity. Viscosity of honey decreased as temperature increased with samples from Igbo-Eze South more viscose than those from other floral locations. Fructose had the highest mean value (35.26 g/100g), followed by glucose (31.92 g/100g) and sucrose (1.47 g/100g). All samples were generally acidic and of very high quality standard as Udenu, Igbo-Eze South and Nsukka honeys were adjudged extra white in colour while Igbo-Eze North and Igbo-Etiti were white honey. Values for thermal heat conductivity and thermal heat diffusivity were 0.44 W m-1o C-1 and 3.51 m 2 s-1 ; 0.43 W m-1o C-1 and 3.84 m 2 s-1 ; 0.44 W m-1o C-1 and 2.43 m 2 s-1 ; 0.44 W m-1o C-1 and 2.84 m 2 s-1 ; and 0.45 W m-1o C-1 and 2.69 m 2 s-1 for Igbo-Eze North, Udenu, Igbo-Eze South, Igbo-Etiti and Nsukka respectively. Honey is a promising food rich in essential minerals. Knowledge of its physicochemical and thermal properties is inevitable to facilitate its postharvest processing.
Keywords: density; electrical conductivity; free acidity; fructose; moisture content; thermal heat diffusivity; viscosity

A thermal performance curve perspective explains decades of disagreements over how air temperature affects the flight metabolism of honey bees - Glass, Jordan R.; Harrison, Jon F. (Journal of Experimental Biology, 2024)
While multiple studies have shown that honey bees and some other flying insects lower their flight metabolic rates when flying at high air temperatures, critics have suggested such patterns result from poor experimental methods as, theoretically, air temperature should not appreciably affect aerodynamic force requirements. Here, we show that apparently contradictory studies can be reconciled by considering the thermal performance curve of flight muscle.We show that prior studies that found no effects of air temperature on flight metabolism of honey bees achieved flight muscle temperatures that were near or on equal, opposite sides of the thermal performance curve. Honey bees vary their wing kinematics and metabolic heat production to thermoregulate, and how air temperature affects the flight metabolic rate of honey bees is predictable using a non-linear thermal performance perspective of honey bee flight muscle.
Keywords: Apis mellifera; Flight muscle temperature; Metabolic rate; Thermoregulation; Wing kinematics

Impacts of Different Winter Storage Conditions on the Physiology of Diutinus Honey Bees (Hymenoptera: Apidae) - Hopkins, Brandon K.; Chakrabarti, Priyadarshini; Lucas, Hannah M.; Sagili, Ramesh R.; Sheppard, Walter S. (Journal of Economic Entomology, 2021)
Global decline in insect pollinators, especially bees, have resulted in extensive research into understanding the various causative factors and formulating mitigative strategies. For commercial beekeepers in the United States, overwintering honey bee colony losses are significant, requiring tactics to overwinter bees in conditions designed to minimize such losses. This is especially important as overwintered honey bees are responsible for colony expansion each spring, and overwintered bees must survive in sufficient numbers to nurse the spring brood and forage until the new 'replacement' workers become fully functional. In this study, we examined the physiology of overwintered (diutinus) bees following various overwintering storage conditions. Important physiological markers, i.e., head proteins and abdominal lipid contents were higher in honey bees that overwintered in controlled indoor storage facilities, compared with bees held outdoors through the winter months. Our findings provide new insights into the physiology of honey bees overwintered in indoor and outdoor environments and have implications for improved beekeeping management.
Keywords: abdominal lipid content; head protein content; honey bee overwintering; honey bee physiology; indoor storage

The mushroom body development and learning ability of adult honeybees are influenced by cold exposure during their early pupal stage - Zhu, Chenyu; Li, Han; Xu, Xinjian; Zhou, Shujing; Zhou, Bingfeng; Li, Xiang; Xu, Hongzhi; Tian, Yuanmingyue; Wang, Yanxin; Chu, Yu; Zhang, Xianlan; Zhu, Xiangjie (Frontiers in Physiology, 2023)
The honeybees are the most important pollinator in the production of crops and fresh produce. Temperature affects the survival of honeybees, and determines the quality of their development, which is of great significance for beekeeping production. Yet, little was known about how does low temperature stress during development stage cause bee death and any sub-lethal effect on subsequent. Early pupal stage is the most sensitive stage to low temperature in pupal stage. In this study, early pupal broods were exposed to 20°C for 12, 16, 24, and 48 h, followed by incubation at 35°C until emergence. We found that 48 h of low temperature duration cause 70% of individual bees to die. Although the mortality at 12 and 16 h seems not very high, the association learning ability of the surviving individuals was greatly affected. The brain slices of honeybees showed that low temperature treatment could cause the brain development of honeybees to almost stop. Gene expression profiles between low temperature treatment groups (T24, T48) and the control revealed that 1,267 and 1,174 genes were differentially expressed respectively. Functional enrichment analysis of differentially expressed genes showed that the differential expression of Map3k9, Dhrs4, and Sod-2 genes on MAPK and peroxisome signaling pathway caused oxidative damage to the honeybee head. On the FoxO signal pathway, InsR and FoxO were upregulated, and JNK, Akt, and Bsk were downregulated; and on the insect hormone synthesis signal pathway, Phm and Spo genes were downregulated. Therefore, we speculate that low temperature stress affects hormone regulation. It was detected that the pathways related to the nervous system were Cholinergic synapse, Dopaminergic synapse, GABAergic synapse, Glutamatergic synapse, Serotonergic synapse, Neurotrophin signaling pathway, and Synaptic vesicle cycle. This implies that the synaptic development of honeybees is quite possibly greatly affected by low temperature stress. Understanding how low temperature stress affects the physiology of bee brain development and how it affects bee behavior provide a theoretical foundation for a deeper comprehension of the temperature adaptation mechanism that underlies the “stenothermic” development of social insects, and help to improve honeybee management strategies to ensure the healthy of colony.
Keywords: Apis mellifera; association learning; cold-temperature stress; development; pupae stage

Neonicotinoid Pesticides Are More Toxic to Honey Bees at Lower Temperatures: Implications for Overwintering Bees - Saleem, Muhammad Shoaib; Huang, Zachary Y.; Milbrath, Meghan O. (Frontiers in Ecology and Evolution, 2020)
The honey bee (Apis mellifera) is an important pollinator as well as an important test model for pesticide effects on other insect pollinators. Honey bees have been experiencing high mortality in both the United States and worldwide. Pesticide exposure has been identified as one of the many stressors causing this mortality. Effects of various pesticides have been measured for multiple responses such as learning, memory performance, feeding activity, and thermoregulation. These studies were conducted at many different temperatures (11–35°C); however, few studies compared toxicity of the same pesticide to bees at different temperatures. It is possible that the same pesticide might show different toxicity to honey bees at different temperatures. To reveal such potential interactions, we administered low doses of two neonicotinoid insecticides (imidacloprid and thiamethoxam) at three different temperature scenarios (35°C, 24°C, and a varying temperature) and determined the effects on honey bee survivorship. We discovered that honey bees are much more sensitive to the neonicotinoid pesticides imidacloprid and thiamethoxam at a constant 24°C or at a varying temperature (night at 13°C and day at 24°C) compared to bees at 35°C. These results suggest that honey bee colonies during winter time will be more sensitive to pesticides. Doses of neonicotinoids that are safe to colonies during summer might kill them during the winter time.
Keywords: Apis mellifera; neonicotinoids; overwintering bees; pesticide toxicity; temperature

Economic evaluation of the honey yield from four forest tree species and the future prospect of the forest beekeeping in Sudan - Elzaki, Elsamoal; Tian, Gang (Agroforestry Systems, 2020)
The present study is an investigation into beekeeping activity values as land use types practiced in Sudanese forests. The main objectives of the study are to estimate honey yield produced per unit area from four tree species, namely: Acacia seyal, A. nilotica, Ziziphus spina-Christi and Eucalyptus spp. Furthermore, the study aims at estimating its economic value and financial return (US$/hectare) using Return On Investment (ROI) as a decision criterion. In addition, the study aims at identifying the obstacles and constraints which this activity faces. The data were collected through interviews with 96 beekeepers in six selected production areas and a survey of market-related data. A structured questionnaire was used, and a descriptive and comparative analysis carried out. The results indicated that the average annual yield of honey/bee hives is 13 kg, ranging between 10 and 16 kg, and A. seyal showed the highest productivity. Furthermore, the results showed that 15 bee colonies/hectare is more suitable with a return rate of 780 US$/hectare annual income. This result indicates that the productivity of honey yield from forest trees has a considerable economic value and financial return. Thus, these results could be a great incentive to encourage local communities to integrate forest management.
Keywords: Forest beekeeping; Forest management; Forest value; Honey yield

Evaluation of the Pollination Ecosystem Service of the Honey Bee (Apis mellifera) Based on a Beekeeping Model in Hungary - Feketéné Ferenczi, Aliz; Szűcs, Isván; Bauerné Gáthy, Andrea (Sustainability (Switzerland), 2023)
Apiaries must be ecologically and economically sustainable to provide pollination as a unique ecosystem service. Pollination as an ecosystem service is economically, socially, and environmentally irreplaceable. Therefore, it is essential to improve the profitability of beekeeping activities, which are mainly carried out in rural areas. With this in mind, the main objective of this article is to assess pollination as one of the ecosystem services provided by bees, based on the specificities of Hungarian honey production. The authors’ analysis is based on a Hungarian apiary with 300 colonies active in migratory beekeeping. The model farm produces a wide variety of honey thanks to its migratory beekeeping, visiting several bee pastures during the beekeeping season. This paper presents an approach to quantify the ecosystem services provided by honey bees (Apis mellifera) using two economic valuation methods (productivity change and surrogate market goods) belonging to the family of cost-based valuation. The results of the monetary valuation of the ecosystem services provided by bees can provide a starting point for further research to help decision-makers and farmers to calculate a fair “pollination fee” for beekeepers, which will significantly help beekeepers to maintain beekeeping, an important and beneficial activity for all of us.
Keywords: ecosystem services; honey bees; productivity changed method; replacement goods/services method; sustainability

Bee pollination: From an ecological and economical perspective - Saha, Samrat; Munshi, Sahin Aktar; Laskar, Nripendra (2023)
About 70% of our food crops depend on the pollination service provided by different insect pollinators amongst which wild and hive bees are the key pollinators. Insect pollination accounts for over 153 billion euro to agricultural production annually. Pollination also improves yield and market value of the food commodity. A section of people from our society depend on the activities related to bee pollination service to earn a livelihood. Bee pollination and beekeeping are significant contributors to a country's GDP. It also conserves several wild flowers by helping them in reproduction. However, due to the action of various stressors such as chemical advancement in agricultural production, the diversity of different bees is in a threatening position. Though technological advancement brings some alternatives of bee pollination, but that can't meet the requirements up to a satisfactory level. With the decline in bee diversity our food production is also in an alarming stage. Keeping this in view, everyone needs to come forward to protect the pollinators for a promising future.
Keywords: Bee pollination; Crop production; Decline; Economy

Overview of bee pollination and its economic value for crop production - Khalifa, Shaden A.M.; Elshafiey, Esraa H.; Shetaia, Aya A.; El-Wahed, Aida A.Abd; Algethami, Ahmed F.; Musharraf, Syed G.; Alajmi, Mohamed F.; Zhao, Chao; Masry, Saad H.D.; Abdel-Daim, Mohamed M.; Halabi, Mohammed F.; Kai, Guoyin; et al. (Insects, 2021)
Pollination plays a significant role in the agriculture sector and serves as a basic pillar for crop production. Plants depend on vectors to move pollen, which can include water, wind, and animal pollinators like bats, moths, hoverflies, birds, bees, butterflies, wasps, thrips, and beetles. Cultivated plants are typically pollinated by animals. Animal-based pollination contributes to 30% of global food production, and bee-pollinated crops contribute to approximately one-third of the total human dietary supply. Bees are considered significant pollinators due to their effectiveness and wide availability. Bee pollination provides excellent value to crop quality and quantity, improv-ing global economic and dietary outcomes. This review highlights the role played by bee pollina-tion, which influences the economy, and enlists the different types of bees and other insects associated with pollination.
Keywords: Bee visitation; Bees pollination; Challenges; Crop production; Economic; Impact

Voltage-gated ion channels in central neurons of Helicoverpa armigera as potential targets for cycloxaprid: a cis-configuration neonicotinoid insecticide - Liu, Xiao; Chen, Man; Ma, Zheng; Yang, Yongchuan; Li, Yangxingzi; Li-Byarlay, Hongmei; He, Bingjun (Applied Entomology and Zoology, 2023)
Cycloxaprid is a novel cis-neonicotinoid, mainly acting on the nicotinic acetylcholine receptor; however, it is not clear whether cycloxaprid can act on voltage-gated ion channels. In this study, the effects of cycloxaprid on the sodium, calcium and potassium channels in central neurons acutely dissociated from Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) were investigated by the whole-cell patch clamp technique. With the application of cycloxaprid, the half voltage (V0.5) of activation and inactivation of sodium channels exhibited an obvious hyperpolarizing shift around 4–16 mV and 4–14 mV, respectively. The window currents of sodium channels increased by 35.04–88.89%. The time course of recovery from inactivation was also significantly prolonged by 0.25–0.43 ms. The V0.5 of activation and inactivation of calcium channels exhibited a marked hyperpolarizing shift around 6–9 mV and 13–19 mV, respectively. The window currents of calcium channels increased by 13.82–28.97%. The time course of recovery from inactivation for calcium channels was prolonged by 0.76–16.85 ms, although not significantly. Comparatively, the peak currents and the V0.5 of activation of potassium channels showed no significant change. These results indicate that sodium and calcium channels of H. armigera are potential target sites of cycloxaprid.
Keywords: Cycloxaprid; Helicoverpa armigera; Voltage-gated calcium channel; Voltage-gated potassium channel; Voltage-gated sodium channel

Chloronicotinyl insecticide imidacloprid: Agricultural relevance, pitfalls and emerging opportunities - Motaung, Thabiso E. (Crop Protection, 2020)
Imidacloprid quickly gained popularity as the first commercial neonicotinoid following the invention of neonicotinoids by Bayer in 1985. Its relationship with agriculture is linked to protection of field crops against a range of insect pests. Beyond this, imidacloprid applications – foliar spraying, soil and seed treatment – have become intertwined with the negative impacts on ecosystem services, including killing of non-target organisms with great economic value such as pollinators, honey providers and beneficial insects which assist farmers with natural pest control. Because early plant growth (e.g. tissue, organ and seedling phase) forms an important part of a plant's life history, the current review draws attention to applying imidacloprid in priming or selection of physiologically important traits. And it reasons that neonicotinoid(imidacloprid)-driven priming/selection is enriched with the potential to integrate robust responses in, and for, plants to better deal with future hostile encounters from early life. Further discussed are some of the metabolites and synthetic compounds that are analogous to imidacloprid. Such compounds appear to greatly influence plant biochemical processes, and thus reflect the potential for imidacloprid to select traits important to safeguard plants against environmental stresses.
Keywords: Crop protection; Neonicotinoids; Pests; Priming

Ligand-gated ion channels as targets of neuroactive insecticides - Ihara, Makoto (Bioscience, Biotechnology and Biochemistry, 2022)
The Cys-loop superfamily of ligand-gated ion channels (Cys-loop receptors) is one of the most ubiquitous ion channel families in vertebrates and invertebrates. Despite their ubiquity, they are targeted by several classes of pesticides, including neonicotinoids, phenylpyrazols, and macrolides such as ivermectins. The current commercialized compounds have high target site selectivity, which contributes to the safety of insecticide use. Structural analyses have accelerated progress in this field; notably, the X-ray crystal structures of acetylcholine binding protein and glutamate-gated Cl channels revealed the details of the molecular interactions between insecticides and their targets. Recently, the functional expression of the insect nicotinic acetylcholine receptor (nAChR) has been described, and detailed evaluations using the insect nAChR have emerged. This review discusses the basic concepts and the current insights into the molecular mechanisms of neuroactive insecticides targeting the ligand-gated ion channels, particularly Cys-loop receptors, and presents insights into target-based selectivity, resistance, and future drug design.
Keywords: Cys-loop superfamily of ligand gated ion channel; ligand-gated ion channels (LGIC); neonicotinoids; neuroactive insecticides; nicotinic acetylcholine receptor (nAChR)

Mode of action of neonicotinoid insecticides imidacloprid and thiacloprid to the cockroach pameα7 nicotinic acetylcholine receptor - Cartereau, Alison; Taillebois, Emiliane; Le Questel, Jean Yves; Thany, Steeve H. (International Journal of Molecular Sciences, 2021)
The functional expression of the cockroach Pameα7 nicotinic acetylcholine receptor sub-unit has been previously studied, and was found to be able to form a homomeric receptor when expressed in Xenopus laevis oocytes. In this study, we found that the neonicotinoid insecticide im-idacloprid is unable to activate the cockroach Pameα7 receptor, although thiacloprid induces low inward currents, suggesting that it is a partial agonist. In addition, the co-application or 5 min pre-treatment with 10 µM imidacloprid increased nicotine current amplitudes, while the co-application or 5 min pretreatment with 10 µM thiacloprid decreased nicotine-evoked current amplitudes by 54% and 28%, respectively. This suggesting that these two representatives of neonicotinoid insecticides bind differently to the cockroach Pameα7 receptor. Interestingly, the docking models demon-strate that the orientation and interactions of the two insecticides in the cockroach Pameα7 nAChR binding pocket are very similar. Electrophysiological results have provided evidence to suggest that imidacloprid and thiacloprid could act as modulators of the cockroach Pameα7 receptors.
Keywords: Acetylcholine; Binding studies; Imidacloprid; Molecular modeling; Neonicotinoids; Nicotinic receptors; Thiacloprid

Recent progress in the structural study of ion channels as insecticide targets - Hadiatullah, Hadiatullah; Zhang, Yongliang; Samurkas, Arthur; Xie, Yunxuan; Sundarraj, Rajamanikandan; Zuilhof, Han; Qiao, Jianjun; Yuchi, Zhiguang (Insect Science, 2022)
Ion channels, many expressed in insect neural and muscular systems, have drawn huge attention as primary targets of insecticides. With the recent technical breakthroughs in structural biology, especially in cryo-electron microscopy (cryo-EM), many new high-resolution structures of ion channel targets, apo or in complex with insecticides, have been solved, shedding light on the molecular mechanism of action of the insecticides and resistance mutations. These structures also provide accurate templates for structure-based insecticide screening and rational design. This review summarizes the recent progress in the structural studies of 5 ion channel families: the ryanodine receptor (RyR), the nicotinic acetylcholine receptor (nAChR), the voltage-gated sodium channel (VGSC), the transient receptor potential (TRP) channel, and the ligand-gated chloride channel (LGCC). We address the selectivity of the channel-targeting insecticides by examining the conservation of key coordinating residues revealed by the structures. The possible resistance mechanisms are proposed based on the locations of the identified resistance mutations on the 3D structures of the target channels and their impacts on the binding of insecticides. Finally, we discuss how to develop “green” insecticides with a novel mode of action based on these high-resolution structures to overcome the resistance.
Keywords: cryo-electron microscopy structure; crystal structure; insecticide; ion channel; resistance

Imidacloprid biodegradation using novel bacteria Tepidibacillus decaturensis strain ST1 in batch and in situ microcosm study - Tiwari, Sonam; Tripathi, Pranjal; Mohan, Devendra; Singh, Ram Sharan (Environmental Science and Pollution Research, 2023)
Imidacloprid is one of the frequently used insecticides. Indiscriminate use of imidacloprid makes it perilous to non-target organisms as well as the environment, including soil and water sources, thus, making its elimination from the environment an irresistible concern. Bioremediation is a technique that uses the degrading capabilities of bacteria to create an economical and reliable method of pesticide abatement. In an attempt to solve the problem arising due to imidacloprid contamination, bacterial strains possessing the ability to degrade imidacloprid were isolated from contaminated agricultural soil samples in the present study. Imidacloprid-degrading isolate, identified as Tepidibacillus decaturensis strain ST1, could effectively degrade imidacloprid in liquid media, slurry, and soil microcosms. The microcosm studies using the isolate resulted in the degradation of around 77.5% and 85% of imidacloprid (200 ppm) in sterile and unsterile soils within 45 days. In addition to biodegradation, sorption of insecticide by the plants and natural reduction of insecticide over time has also been reported. The degradation in soil follows first-order kinetics. Hydrazinecarboxamide and hydroxyurea were identified as metabolites on conducting GC–MS analysis of the degraded samples.
Keywords: Biodegradation; Imidacloprid; Indigenous bacteria; Microcosm; Self-degradation; Slurry

Using Ochrobactrum thiophenivorans and Sphingomonas melonis for bioremediation of Imidacloprid - Erguven, Gokhan Onder; Demirci, Ulas (Environmental Technology and Innovation, 2021)
To solve the environmental problems of the pesticides, bioremediation methods are commonly useful for their environment friendly properties. These methods are more cheap, useful and have more advantages for remediate receiving environments In this study, imidacloprid which is one of the selective insecticide in all over the world is chosenfor bioremediation studies with two soil bacteria. The imidacloprid used in the Mediterranean climate for cotton, pistachios, tomatoes, peppers and eggplant cultivation. The bioremediation of this insecticide was investigated via the performance of O.thiophenivorans and S. melonis in agitated culture media. The agricultural soil used for the isolation of these two bacteria was taken from the cotton cultivated agricultural area in Adana province in Turkey. For this purpose, the isolated and enriched bacteria were added to the recommended insecticide concentrations, and the Imidacloprid active material, Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD5), Total Organic Carbon (TOC), pH and dissolved oxygen (DO) parameters were determined for two weeks on each day of the study. O. thiophenivorens and S. melonis bioremediate the Imidacloprid insecticide with high efficiency (over 90%). According to these results, it is understood that these bacteria can be preferred in the bioremediation of receiving environments that are contaminated with such pesticides and can be useful for scientists to handle the opposite effects of such persistent organic pollutants and COD, BOD5 and TOC parameters can easily give opinions about decreasing of pesticides like the active materials
Keywords: Active material; Bioremediation; Imidacloprid; Ochrobactrum thiophenivorans; Sphingomonas melonis

Evaluating imidacloprid exposure among grape field male workers using biological and environmental assessment tools: An exploratory study - López-Gálvez, Nicolás; Wagoner, Rietta; Canales, Robert A.; de Zapien, Jill; Calafat, Antonia M.; Ospina, Maria; Rosales, Cecilia; Beamer, Paloma (International Journal of Hygiene and Environmental Health, 2020)
Imidacloprid is a neonicotinoid insecticide commonly injected through agricultural drip irrigation systems to reduce the population of vine mealybugs (P. ficus) in grape farms. There is a growing concern of potential human health effects of imidacloprid, however, there is limited information on the exposure to imidacloprid in farm workers. Imidacloprid exposure was evaluated in this exploratory study of 20 male migrant grape workers sampled five days after imidacloprid was injected in the irrigation system during winter and summer seasons. We administered a questionnaire on work activities, exposure characteristics, and socio-demographics and collected personal air, hand wipe, and spot urine samples. Heat exposure was also assessed. Spearman's correlation coefficients and Wilcoxon rank-sum tests were utilized to evaluate associations and differences in imidacloprid exposures with socio-demographic, occupational, and environmental characteristics. All participants had less than a high school education and about half identified an Indigenous language as their primary language. Although not detected in air samples, imidacloprid was detected in 85% of the hand wipes (median: 0.26: 0.41 μg/wipe, range: 0.05–7.10 μg/wipe). The majority of participants (75%) had detectable urinary concentrations of imidacloprid (median: 0.11 μg/g creatinine, range: 0.05–3.90 μg/g of creatinine), and nearly all (95%) had detectable urinary concentrations of 5-hydroxy-Imidacloprid (5-OH-IMI), a metabolite of imidacloprid (median: 1.28 μg/g creatinine, range: 0.20–27.89 μg/g creatinine). There was a significant correlation (p < 0.001) between imidacloprid in hand wipes and urinary imidacloprid and 5-OH-IMI (rs: 0.67 for imidacloprid and 0.80 for 5-OH-IMI). Hand temperature was significantly and positively correlated (p < 0.05) with imidacloprid concentration on hand wipes (rs: 0.70), and urinary biomarkers (rs: 0.68 for imidacloprid, and 0.60 for 5-OH-IMI) suggesting that working in high temperatures may influence the exposure and absorption of imidacloprid. Thus, research on farm workers would benefit in the future by evaluating imidacloprid exposure in relation to heat stress and other occupational factors.
Keywords: Farm workers; Imidacloprid; Neonicotinoids; Occupational health; Pesticide exposure

Metabolic disturbance in lettuce (Lactuca sativa) plants triggered by imidacloprid and fenvalerate - Zhang, Yuxue; Huang, Lin; Liu, Lijuan; Cao, Xiaochuang; Sun, Chengliang; Lin, Xianyong (Science of the Total Environment, 2022)
Intensive and indiscriminate use of insecticides in agroecosystems causes phytotoxic disturbances in non-target crops. However, the mechanisms by which plants reprogram cellular metabolites to resist and tolerate such agrochemicals remain unclear. Here, the interaction between lettuce plants with imidacloprid and fenvalerate was investigated by the complementary use of physiological and metabolomic analyses. Neither imidacloprid nor fenvalerate induced overt phytotoxicity in lettuce seedlings. The plant biomass, chlorophyll fluorescence, lipid peroxidation, and membrane integrity were not significantly affected by the selected insecticides. Flavonoid content decreased by 25% in lettuce leaves under fenvalerate exposure, whereas polyphenol and flavonoid contents were not significantly altered by imidacloprid. Although the content of most of the nutrient element in the leaves remained the same following pesticide treatment, iron content decreased by 28.1% under imidacloprid exposure but increased by 22.8% under fenvalerate exposure. Metabolomic analysis revealed that the selected insecticides induced extensive metabolic reprogramming in lettuce roots and shoots. Imidacloprid dramatically increased the metabolism of several amino acids (arginine, cysteine, homoserine, and 4-hydroxyisoleucine), whereas markedly decreased the metabolism of various carbohydrates (glucose, raffinose, maltotetraose, maltopentaose, and stachyose). Fenvalerate did not significantly alter amino acid metabolism but decreased carbohydrate metabolism. Additionally, the relative abundance of most organic acids and polyphenolic compounds decreased significantly after pesticide exposure. These results suggest that plants might program their primary and secondary metabolism to resist and tolerate insecticides. The findings of this study provide important information on how neonicotinoid and pyrethroid insecticides affect the health and physiological state of plants, which are ultimately associated with crop yield and quality.
Keywords: Insecticides; Lettuce; Metabolomics; Physiology; Phytotoxicity

Biodegradation of imidacloprid: Molecular and kinetic analysis - Gautam, Pallavi; Kumar Dubey, Suresh (Bioresource Technology, 2022)
Imidacloprid (C9H10ClN5O2) is the most widely used insecticide. Its persistence and toxic nature have caused a detrimental effect on living biota. Thus its removal from the contaminated environment has become imperative. The present study aimed to isolate bacterial species from pesticide-contaminated sites and assess their potential for biodegradation of imidacloprid. The 16S rRNA analysis revealed the genetic relatedness of isolates to Sphingobacterium sp., Agrobacterium sp., Pseudomonas sp., and Bacillus sp. Batch biodegradation studies showed that Sphingobacterium sp. and Agrobacterium sp. were the most promising isolates as they degraded 81.0% and 84.9%, respectively, of imidacloprid at the concentration of 95 mg/L via co-metabolism. Kinetic study (Vmax/Ks ratio) also suggested the high degradation efficiency of these isolates. Imidacloprid-guanidine (C9H11ClN4) was identified as the metabolite. This report highlights the potential of bacteria for imidacloprid degradation and could be utilized for the formulation of strategies for the remediation of imidacloprid contaminated environments.
Keywords: Biodegradation; Imidacloprid; Imidacloprid-guanidine; Kinetics

Aquaporin expression in the alimentary canal of the honey bee Apis mellifera L. (Hymenoptera: Apidae) and functional characterization of Am_Eglp 1 - de Souza, Débora Linhares Lino; Serrão, Jose Eduardo; Hansen, Immo Alex (PLoS ONE, 2020)
Aquaporins (AQP) are a family of plasma membrane proteins responsible for water transport through cell membranes. They are differentially expressed in different parts of the alimentary canal of insects where they regulate water transport. These proteins have been studied in detail in some insects, but few data are available for aquaporins of the honey bee, Apis mellifera. We used quantitative PCR to study the expression of six putative aquaporin genes in forager honey bees. We found differential expression of all putative AQP genes in crop, midgut, ileum, rectum and Malpighian tubules. We found the entomoglyceroporin Am_Eglp 1 expressed at extremely high levels in the midgut. We performed a functional characterization of Am_Eglp 1 using heterologous expression in Xenopus laevis oocyte followed by water uptake assays. Our results confirmed that the Am_Eglp 1 gene encodes a functional water transporter. This study shows that all putative honey bee aquaporin genes have complex expression patterns in the digestive and excretory organs of honey bee workers. Our results suggest that Am_Eglp 1 is the principal water transporter in the midgut of A. mellifera workers.

Honey as a Functional Food for Apis mellifera - Berenbaum, May R; Calla, Bernarda (Annual Review of Entomology Annu. Rev. Entomol. 2021, 2021)
Although nectar is consumed, primarily as a supplemental food, by a broad range of insects spanning at least five orders, it is processed and stored by only a small number of species, most of which are bees and wasps in the superfamily Apoidea. Within this group, Apis mellifera has evolved remarkable adaptations facilitating nectar processing and storage; in doing so, this species utilizes the end product, honey, for diverse functions with few if any equivalents in other phytophagous insects. Honey and its phytochemi-cal constituents, some of which likely derive from propolis, have functional significance in protecting honey bees against microbial pathogens, toxins, and cold stress, as well as in regulating development and adult longevity. The distinctive properties of A. mellifera honey appear to have arisen in multiple ways, including genome modification; partnerships with microbial symbionts; and evolution of specialized behaviors, including foraging for substances other than nectar. That honey making by A. mellifera involves incorporation of exogenous material other than nectar, as well as endoge-nous products such as antimicrobial peptides and royal jelly, suggests that regarding honey as little more than a source of carbohydrates for bees is a concept in need of revision. 185
Keywords: alpha-glucosidases; antioxidants; detoxification; flavonoids; immunity; invertase; phenolics

Characterization of Gromphadorhina coquereliana hemolymph under cold stress - Lubawy, Jan; Słocińska, Małgorzata (Scientific Reports, 2020)
Low temperatures in nature occur together with desiccation conditions, causing changes in metabolic pathways and cellular dehydration, affecting hemolymph volume, water content and ion homeostasis. Although some research has been conducted on the effect of low temperature on Gromphadorhina coquereliana, showing that it can survive exposures to cold or even freezing, no one has studied the effect of cold on the hemolymph volume and the immune response of this cockroach. Here, we investigated the effect of low temperature (4 °C) on the abovementioned parameters, hemocyte morphology and total number. Cold stress affected hemocytes and the immune response, but not hemolymph volume. After stress, the number of circulating hemocytes decreased by 44.7%, but the ratio of apoptotic cells did not differ significantly between stressed and control individuals: 8.06% and 7.18%, respectively. The number of phagocyting hemocytes decreased by 16.66%, the hemocyte morphology drastically changed, and the F-actin cytoskeleton differed substantially in cold-stressed insects compared to control insects. Moreover, the surface area of the cells increased from 393.69 µm2 in the control to 458.38 µm2 in cold-treated animals. Together, our results show the links between cold stress and the cellular immune response, which probably results in the survival capability of this species.

Dying of thirst: Osmoregulation by a hawkmoth pollinator in response to variability in ambient humidity and nectar availability § - Dahake, Ajinkya; Persaud, Steven; Jones, Marnesha N; Goyret, Joaquin; Davidowitz, Goggy; Raguso, Robert A
Climate-induced alterations in flowering phenology can lead to a temporal mismatch between pollinators and the availability of floral resources. Such asynchrony may be especially impactful in desert ecosystems, where flowering time and pollinator emergence are particularly sensitive to rainfall. To investigate the osmoregulation of a desert-living hawkmoth pollinator Manduca sexta, we sampled hemolymph osmolality of over 1000 lab-grown moths held at 20%, 50%, and 80% ambient humidity. Under starvation, the hemolymph osmolality of moths remained within a healthy range from days 1-3, regardless of ambient humidity. However, osmolality levels increase steeply from a baseline of 360-370 mmol/kg to 550 mmol/kg after 4-5 days in low and intermediate humidity and after 5 days in high humidity. Starved moths exposed to low humidity conditions died within 5 days, whereas those in high humidity conditions lived twice as long. Moths fed either synthetic Datura wrightii nectar, synthetic Agave palmeri nectar, or water, maintained osmolality within a healthy baseline range of 350-400 mmol/kg. The same was true for moths that fed on authentic floral nectars. However, moths consumed higher amounts of synthetic nectar, likely due to the non-sugar nectar constituents in the authentic nectar. Finally, simulating a 4-day mismatch between pollinator emergence and nectar availability, we found that a single nectar meal can osmotically rescue moths in dry ambient conditions. Our findings indicate that hemolymph osmolality provides a rapid and accurate biomarker for assessing both the health and relative hydration state of insect pollinators.
Keywords: Agave; Datura; Sonoran Desert; climate change; desiccation; humidity; moths; osmolality; plant-pollinator mismatch

Rutin (Bioflavonoid) as cell signaling pathway modulator: Prospects in treatment and chemoprevention - Pandey, Pratibha; Khan, Fahad; Qari, Huda A.; Oves, Mohammad (Pharmaceuticals, 2021)
Cancer is a complex ailment orchestrated by numerous intrinsic and extrinsic pathways. Recent research has displayed a deep interest in developing plant-based cancer therapeutics for better management of the disease and limited side effects. A wide range of plant-derived compounds have been reported for their anticancer potential in the quest of finding an effective therapeutic approach. Rutin (vitamin P) is a low-molecular weight flavonoid glycoside (polyphenolic com-pound), abundantly present in various vegetables, fruits (especially berries and citrus fruits), and medicinal herbs. Numerous studies have delineated several pharmacological properties of rutin such as its antiprotozoal, antibacterial, anti-inflammatory, antitumor, antiviral, antiallergic, vasoactive, cytoprotective, antispasmodic, hypolipidemic, antihypertensive, and antiplatelet properties. Specifi-cally, rutin-mediated anticancerous activities have been reported in several cancerous cell lines, but the most common scientific evidence, encompassing several molecular processes and interactions, including apoptosis pathway regulation, aberrant cell signaling pathways, and oncogenic genes, has not been thoroughly studied. In this direction, we attempted to project rutin-mediated oncogenic pathway regulation in various carcinomas. Additionally, we also incorporated advanced research that has uncovered the notable potential of rutin in the modulation of several key cellular functions via interaction with mRNAs, with major emphasis on elucidating direct miRNA targets of rutin as well as the process needed to transform these approaches for developing novel therapeutic interventions for the treatment of several cancers.
Keywords: Cancer; Cell signaling pathways; MiRNA; Rutin; Therapeutic potential

Quercetin and rutin as modifiers of aphid probing behavior - Stec, Katarzyna; Kordan, Bożena; Gabryś, Beata (Molecules, 2021)
Rutin and its aglycone quercetin occur in the fruits, leaves, seeds, and grains of many plant species and are involved in plant herbivore interactions. We studied the effect of the ex-ogenous application of rutin and quercetin on the probing behavior (=stylet penetration activities in plant tissues) of Acyrthosiphon pisum on Pisum sativum, Myzus persicae on Brassica rapa ssp. pekinensis, and Rhopalosiphum padi on Avena sativa using the electrical penetration graph technique (EPG = electropenetrography). The reaction of aphids to quercetin and rutin and the potency of the effect depended on aphid species, the flavonol, and flavonol concentration. Quercetin promoted probing activities of A. pisum within non-phloem and phloem tissues, which was demonstrated in the longer duration of probes and a trend toward longer duration of sap ingestion, respectively. M. persicae reached phloem in a shorter time on quercetin-treated B. rapa than on the control. Rutin caused a delay in reaching sieve elements by A. pisum and deterred probing activities of M. persicae within non-phloem tissues. Probing of R. padi was not affected by quercetin or rutin. The potency of behavioral effects increased as the applied concentrations of flavonols increased. The prospects of using quercetin and rutin in plant protection are discussed.
Keywords: Antifeedants; Bird cherry-oat aphid; Flavonoids; Pea aphid; Peach-potato aphid; Stylet penetration

Health benefits and limitations of rutin - A natural flavonoid with high nutraceutical value - Semwal, Ravindra; Joshi, Sunil Kumar; Semwal, Ruchi Badoni; Semwal, Deepak Kumar (Phytochemistry Letters, 2021)
Rutin, a plant-derived natural flavonoid, is considered among the top therapeutically active phytochemicals and one of the major bioactive constituents of a variety of natural foods and brews like buckwheat flour, apples, citrus fruits, tea and red wine. The present work aimed to review the advantages and limitations of rutin based on available literature. Considering its potential role in many health problems, this molecule was critically reviewed for its therapeutical uses and pharmacokinetic properties with the main emphasis on the current advances. Moreover, some solutions to improve the pharmacokinetic profile of rutin are also suggested for its clinical use in the near future. The information on its research outcome was collected online from different authentic scientific databases like Scopus and Google Scholar. Its protective role against heart-related problems, diabetes, inflammation and different microbial infections is evident from earlier research. However, some drawbacks like poor solubility and low bioavailability make its clinical use limited. As a result, various studies on the development of novel drug delivery systems have been conducted in recent years to improve its pharmacokinetic profile and found that the new formulated systems have not only improved pharmacokinetics but also increased the efficacy of rutin. Hence, this molecule can be used clinically after improving its pharmacokinetic properties and revalidating its safety profile in further research.
Keywords: Antioxidant activity; Drug delivery; Flavonoid; Natural products; Nutraceutical; Rutin

Therapeutic benefits of rutin and its nanoformulations - Negahdari, Ramin; Bohlouli, Sepideh; Sharifi, Simin; Maleki Dizaj, Solmaz; Rahbar Saadat, Yalda; Khezri, Khadijeh; Jafari, Samira; Ahmadian, Elham; Gorbani Jahandizi, Negar; Raeesi, Safa (Phytotherapy Research, 2021)
Background: Rutin as a natural flavonoid compound has revealed an extensive range of therapeutic potentials. Purpose: The current paper is focused on the numerous studies on rutin nanoformulations regarding its broad spectrum of therapeutic potentials. Study and methods: A review was conducted in electronic databases (PubMed) to identify relevant published literature in English. No restrictions on publication date were imposed. Results: The literature search provided 7,078 results for rutin. Among them, 25 papers were related to the potential biological activities of rutin nanoformulations. Polymeric nanoparticles were the most studied nanoformulations for rutin (14 titles) and lipid nanoparticles (5 titles) were in second place. The reviewed literature showed that rutin has been used as an antimicrobial, antifungal, and anti-allergic agent. Improving the bioavailability of rutin using novel drug-delivery methods will help the investigators to use its useful effects in the treatment of various chronic human diseases. Conclusion: It can be concluded that the preparation of rutin nanomaterials for the various therapeutic objects confirmed the enhanced aqueous solubility as well as enhanced efficacy compared to conventional delivery of rutin. However, more investigations should be conducted to confirm the improved bioavailability of the rutin nanoformulations.
Keywords: antimicrobial; antioxidant; flavonoids; nanoformulation; rutin

Dietary supplementation of rutin and rutin-rich buckwheat elevates endogenous glucagon-like peptide 1 levels to facilitate glycemic control in type 2 diabetic mice - Lee, Lin Chien; Hou, Yu Chang; Hsieh, Ying Ying; Chen, Yu Hsin; Shen, Yuh Chiang; Lee, I. Jung; Monica Shih, Meng Chun; Hou, Wen Chi; Liu, Hui Kang (Journal of Functional Foods, 2021)
Rutin and rutin-rich buckwheat are commonly used as alternative medicines due to their wide range of health benefits. The present study aims to investigate their anti-diabetes effects and the association with glucagon-like peptide 1 (GLP-1) levels. A murine model of type 2 diabetes (T2D), induced by a high-fat diet combined with streptozocin injection, was utilized. T2D mice were fed 3% buckwheat, 10% buckwheat, or 0.1% rutin as part of their diet for 4 weeks. Dipeptidyl peptidase-4 assays, secretin tumor cell line (STC-1) cells, and GLP-1 receptor-knockout mice were employed for mechanistic studies. Dietary consumption of 10% buckwheat and 0.1% rutin provided beneficial outcomes including lowering blood glucose levels and HbA1c, enhancing HOMA-B%, improving glucose tolerance and pyruvate tolerance. Serum GLP-1, ghrelin, leptin, and adiponectin levels were also increased at the end of the treatment. Increased GLP-1 levels and the improvement of β-cell function were closely associated with the blood glucose-lowering effects observed. Hypoglycemic effects of buckwheat and rutin supplement were abolished in diabetic GLP-1 receptor knockout mice. In conclusion, rutin and related herbal materials are expected to provide health benefits due to their ability to modulate endogenous GLP-1 levels in T2D mice.
Keywords: Dipeptidyl peptidase-4; GLP-1-receptor-knockout mice; Glucagon-like peptide 1; Rutin; Tartary buckwheat; Type 2 diabetes

Rutin ameliorates inflammation and improves metabolic function: A comprehensive analysis of scientific literature - Muvhulawa, Ndivhuwo; Dludla, Phiwayinkosi V.; Ziqubu, Khanyisani; Mthembu, Sinenhlanhla X.H.; Mthiyane, Fikile; Nkambule, Bongani B.; Mazibuko-Mbeje, Sithandiwe E. (Pharmacological Research, 2022)
Chronic inflammation remains an essential complication in the pathogenesis and aggravation of metabolic diseases. There is a growing interest in the use of medicinal plants or food-derived bioactive compounds for their antioxidant and anti-inflammatory properties to improve metabolic function. For example, rutin, a flavonol derivative of quercetin that is found in several medicinal plants and food sources has displayed therapeutic benefits against diverse metabolic diseases. Here, we searched the major electronic databases and search engines such as PubMed/MEDLINE, Scopus and Google Scholar to systematically extract and critically discuss evidence reporting on the impact of rutin against metabolic diseases by affecting inflammation. In fact, available preclinical evidence suggests that rutin, through its strong antioxidant properties, can effectively ameliorate inflammation by reducing the levels of pro-inflammatory markers such as tumor necrosis factor-α, interleukin (IL)-6, cyclooxygenase-2, IL-1β, as well as blocking nuclear factor kappa B (NF-κB)/mitogen-activated protein kinase (MAPK) activation to improve metabolic function. Notably, although clinical data on the impact of rutin on inflammation is limited, food-derived sources rich in this flavonol such as Fagopyrum tataricum, Coffea arabica and Aspalathus linearis (rooibos) have shown promise in improving metabolic function, in part by reducing markers of oxidative stress and inflammation. However, additional studies are still required to confirm the therapeutic properties of rutin in a clinical setting, including the enhancement of it low bioavailability profile.
Keywords: Cardiovascular diseases; Flavonoids; Inflammation; Metabolic diseases; Rutin; Therapeutic targets

Effects of residual doses of neonicotinoid (imidacloprid) on metabolic rate of queen honey bees Apis mellifera (Hymenoptera: Apidae) - Vergara-Amado, Jonathan; Manzi, Catalina; Franco, Lida Marcela; Contecha, Sebastian C.; Marquez, Silvia Juliana; Solano-Iguaran, Jaiber J.; Haro, Ronie E.; Silva, Andrea X. (Apidologie, 2020)
Bees are key regulators in the maintenance of global biodiversity and food security. Overwhelming evidence has shown elevated colony losses for honey bees and a decrease in the abundance of other pollinators. Insecticides of the neonicotinoid type have been associated with these losses, but few studies have explored how residual exposure doses affect the queen’s energy metabolism. Here, we studied how a residual dose of neonicotinoid (imidacloprid), combined with reproductive status (virgin and inseminated) affects honey bee queen’s metabolism. We conducted the same experiment in two geographical locations (Chile and Colombia) and found a strong reduction of standard metabolic rate (SMR) in insecticide-treated queens (Chilean queen bees 11.3% reduction in watt output; Colombian queen bees 11.7% reduction in watt output). No effects were found when comparing reproductive condition on SMR. We will highlight the possible consequences of a weak honey bee queen’s performance on colony stability.
Keywords: Chile; Colombia; honey bee races; insecticide; respirometry

Physiological and biochemical response of the solitary bee Osmia bicornis exposed to three insecticide-based agrochemicals - Mokkapati, Jaya Sravanthi; Bednarska, Agnieszka J.; Laskowski, Ryszard (Ecotoxicology and Environmental Safety, 2022)
The physiological and biochemical stress induced by pesticides need to be addressed in economically and ecologically important non-Apis solitary bees, particularly at lower than field-applied concentrations. Thus, the aim of the present study was to analyse the physiological and biochemical changes in female adult Osmia bicornis bees upon continuous oral exposure to three insecticide-based agrochemicals – i.e. Dursban 480 EC (active ingredient - a.i. chlorpyrifos), Sherpa 100 EC (a.i. cypermethrin), and Mospilan 20 SP (a.i. acetamiprid), in a toxicokinetic manner (feeding with either insecticide-contaminated food or uncontaminated food (controls) for 8 d in the contamination phase followed by 8 d of decontamination (i.e. feeding with uncontaminated food)). All three tested agrochemicals altered the energetic budget of bees by the deprivation of energy derived from lipids and carbohydrates (but not proteins) and/or a decrease in respiration based metabolic rate (energy consumption) compared to the controls. The activities of acetylcholinesterase and glutathione-S-transferase enzymes were not altered by insecticides at tested concentrations. These results show that chronic exposure to at least some pesticides even at relatively low concentrations may cause severe physiological disruptions that could potentially be damaging for the solitary bees.
Keywords: Acetylcholinesterase; Energy reserves; Glutathione S-transferase; Pesticides; Pollinators; Respiration

The impact of early-life exposure to three agrochemicals on survival, behavior, and gut microbiota of stingless bees (Partamona helleri) - Botina, Lorena Lisbetd; Barbosa, Wagner Faria; Acosta, João Paulo Lima; Bernardes, Rodrigo Cupertino; Cortes, Johana Elizabeth Quintero; Pylro, Victor Satler; Mendonça, Adriana Corrêa; Barbosa, Renata Cristina; Lima, Maria Augusta Pereira; Martins, Gustavo Ferreira (Environmental Science and Pollution Research, 2023)
Over the last few decades, agrochemicals have been partially associated with a global reduction in bees’ population. Toxicological assessment is therefore crucial for understanding the overall agrochemical risks to stingless bees. Therefore, the lethal and sublethal effects of agrochemicals commonly used in crops (copper sulfate, glyphosate, and spinosad) on the behavior and gut microbiota of the stingless bee, Partamona helleri, were assessed using chronic exposure during the larval stage. When used at the field-recommended rates, both copper sulfate (200 µg of active ingredient/bee; a.i µg bee−1) and spinosad (8.16 a.i µg bee−1) caused a decrease in bee survival, while glyphosate (148 a.i µg bee−1) did not show any significant effects. No significant adverse effects on bee development were observed in any treatment with CuSO4 or glyphosate, but spinosad (0.08 or 0.03 a.i µg bee −1) increased the number of deformed bees and reduced their body mass. Agrochemicals changed the behavior of bees and composition of the gut microbiota of adult bees, and metals such as copper accumulated in the bees’ bodies. The response of bees to agrochemicals depends on the class or dose of the ingested compound. In vitro rearing of stingless bees’ larvae is a useful tool to elucidate the sublethal effects of agrochemicals.
Keywords: Agrochemicals; Gut symbionts; Larval exposure; Native bees; Toxicological assessment; Walking behavior

The development of the solitary bee Osmia bicornis is affected by some insecticide agrochemicals at environmentally relevant concentrations - Mokkapati, Jaya Sravanthi; Bednarska, Agnieszka J.; Laskowski, Ryszard (Science of the Total Environment, 2021)
Solitary bees provide essential pollination services for many arable crops, but are prone to global decline. Agricultural intensification, which is connected with pesticide usage, is among major threats to bees and, thus, to the food security and ecosystem stability. As it may not be possible to cease pesticide usage currently because of the growing demand for food, it is crucial to understand the pesticide toxicities to bees for better protection of pollinator populations. The majority of studies have focused on social bees, and those on solitary bees studied effects of adult exposure, whereas these bees are also likely to be exposed as larvae via the consumption of contaminated pollen. Here, the effects of three commonly used insecticide-based plant protection products on the development of the solitary bee, Osmia bicornis (red mason bee), were studied by exposing larvae to insecticide-contaminated multifloral pollen. The tested insecticides were: Dursban480EC, containing the organophosphate chlorpyrifos (CHP), Sherpa100EC, containing the pyrethroid cypermethrin (CYP), and Mospilan20SP with the neonicotinoid acetamiprid (ACT). When compared to the control larvae fed with uncontaminated-pollen, both CHP and CYP significantly reduced the O. bicornis larval survival and their body mass at all tested concentrations. In contrast, ACT did not affect either larval survival or body mass, but the length of larval stage to cocoon formation was significantly shortened compared to controls. None of studied insecticides affected the mass of cocooned individuals. However, at least 80% of individuals exposed to any of the tested insecticides died before reaching the adult stage, whereas 43% of the controls emerged successfully after overwintering. Although no clear monotonic dose-response relationships were found, our study showed that at least some insecticide formulations affect the development of O. bicornis even at concentrations actually found in pollen in the field, indicating an urgent need for revising current pesticide usage recommendations.
Keywords: Ecological risk assessment; Ecotoxicology; Pesticide; Red mason bee; Toxicity

OECD GUIDELINES FOR THE TESTING OF CHEMICALS Honeybees, Acute Oral Toxicity Test (1998)

OECD GUIDELINES FOR THE TESTING OF CHEMICALS Honeybees, Acute Contact Toxicity Test (1998)

[Title] - DER WAL Leon, Van

ENVIRONMENT DIRECTORATE JOINT MEETING OF THE CHEMICALS COMMITTEE AND THE WORKING PARTY ON CHEMICALS, PESTICIDES AND BIOTECHNOLOGY Cancels & replaces the same document of Guidance Document on Honey Bee (Apis mellifera) Larval Toxicity Test, Repeated Exposure Series on Testing and Assessment No. 239 (2021)
Following several questions raised after publication, the OECD would like to clarify that the validity criteria mentioned in paragraph 7 «across all replicates» should be understood as the average value across all replicates, a replicate being defined as the number of larvae originating from the same colony. JT03479290 OFDE This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Bee pollination services and the burden of biogeography - Tierney, Simon M.; Bernauer, Olivia M.; King, Lachlan; Spooner-Hart, Robert; Cook, James M. (Proceedings of the Royal Society B: Biological Sciences, 2023)
Native bees augment pollination services in the Northern Hemisphere, especially cultivated apple crops, yet Southern Hemisphere contexts are poorly known. We observed the foraging behaviour of 69 354 invertebrate flower visitors in Australian orchards (two regions, 3 years) to assess the efficacy of pollination service (P eff). Native stingless bees and introduced honey bees were the most abundant visitors and most efficacious pollinators (Tetragonula P eff = 6.16; Apis P eff = 13.02), with Tetragonula becoming important service providers above 22°C. However, visits by tree-nesting stingless bees decreased with distance from native forest (less than 200 m) and their tropical/subtropical distribution precludes pollination service in other major Australian apple-producing regions. More broadly distributed native allodapine and halictine bees transferred the most pollen per-visit, but their low abundances reduce efficacies (Exoneura P eff = 0.03; Lasioglossum P eff = 0.06), resulting in a general dependence on honey bees. This reliance is a burden of biogeography, since key Northern Hemisphere pollinators of apple (Andrena, Apis, Bombus, Osmia) do not naturally occur in Australasia - where there is only 15% generic overlap with Central Asian bees sympatric with wild apple distributions (cf. Palaearctic 66% and Nearctic 46% generic overlaps). The historical biogeography of bees therefore drives an extreme dependence on one introduced species for apple pollination in Australia.
Keywords: apple; biogeography; efficacy; foraging behaviour; native bees; pollination service

Pollination service provided by honey bees to buzz-pollinated crops in the Neotropics - Rocha, Franklin H.; Peraza, Daniel N.; Medina, Salvador; Quezada-Euán, José Javier G. (PLoS ONE, 2023)
Generalist honey bees grant significant pollination services worldwide. Although honey bees can provide compensatory pollination services, their service to buzz-pollinated crops, compared to specialized pollinators, is not clear. In this study, we assessed the contribution of Africanized honey bees (AHB) and native sonicating bees (NBZ) to the pollination of eggplant (Solanum melongena) and annatto (Bixa orellana) in Yucatan, Mexico, one of the largest producers of these crops in the Americas and a region with one of the largest densities of honey bees in the world. We first compared the relative frequency and abundance of both bee types on flowers of both crops. Secondly, we controlled access to flowers to compare the number and weight of fruit and number of seed produced after single visits of AHB and native bees. For a better assessment of pollination services, we evaluated the productivity of individual flowers multiply visited by AHB. The results were compared against treatments using pollinator-excluded flowers and flowers that were supplied with additional pollen, which allowed an overall measure of pollination service provision (PSP). Our results showed that AHB were the predominant flower visitors in both crops and that were poorly efficient on individual visits. Notably, fruit quantity and seed number increased concomitantly with the number of AHB visits per flower on eggplant, but not on annatto. Estimation of PSP revealed no pollination deficit on eggplant but that a deficit existed on the pollination services to annatto. We found that AHB numerical predominance compensates their poor individual performance and can complement the services of native bees on eggplant, but not on annatto. We discuss possible explanations and implications of these results for buzz-pollinated crops in the neotropics an area with little assessment of pollination services and a high density of honey bees.

Economics of Pollination - Baylis, Kathy; Lichtenberg, Elinor M; Lichtenberg, Erik (2021)
Many food crops rely on pollination by animals. Historically, wind and wild organisms provided pollination as an ecosystem service that varied across agroecological zones, cropping systems, and time. The value of these pollination services is likely substantial but has not been estimated reliably. More recently, pollination services in major crop-producing regions have been provided through organized markets, primarily the rental of honey bees. The sustainability of commercially provided pollination services is being challenged by parasites, diseases, pesticide exposures, poor nutrition, and Colony Collapse Disorder. Economic analyses indicate that honey bee rental markets have been able to adjust to those challenges, at least to date. Understanding the future sustainability of rental markets requires greater knowledge of the contributions of wild pollinators, optimal management of pollination services from wild and managed organisms, and the value of pollination services provided by wild and managed organisms. 335
Keywords: Colony Collapse Disorder; JEL codes: Q15; Q57 Keywords pollination; ecosystem services; honey bees

Crop pollination services: Complementary resource use by social vs solitary bees facing crops with contrasting flower supply - Bänsch, Svenja; Tscharntke, Teja; Gabriel, Doreen; Westphal, Catrin (Journal of Applied Ecology, 2021)
Many farmers are facing high economic risks if pollinator declines continue or temporal and spatial variation in wild bee communities cause reduced pollination services. Co-flowering crops might compete for pollinators, while they also might facilitate the delivery of pollination services. This rarely studied topic is of particular interest with respect to the foraging decisions of bees from different functional groups and when more sparsely and mass-flowering crops are in bloom at the same time. The abundance of honey bees, bumble bees and solitary bees in strawberry fields was quantified with transect walks along a gradient of oilseed rape (OSR) availability (product of OSR land cover and temporally changing OSR flower cover). We established a pollination experiment with pollination treatments (open-, wind- and self-pollination) to study the effects of insect pollination on strawberry fruit weight and quality. Changes in OSR availability exhibited contrasting effects on social versus solitary bees in strawberry fields. Bumble bees and honey bees were less abundant in strawberry fields when OSR availability was high, whereas solitary bees were facilitated. With more strawberry flowers, we found more bees in general. When flowers were open-pollinated, they resulted in heavier fruits with better commercial grades compared to wind- and self-pollinated flowers. A higher bee abundance enhanced the strawberry fruit weight and quality but depended on flower order and variety. Synthesis and applications. Sparsely flowering crops may compete with mass-flowering crops for social bee pollinators, while solitary pollinators in the field might be evenly facilitated. To ensure best fruit weight and quality, it can be beneficial to support bee abundance in the field. While some social and solitary bee species can be managed for pollination services, wild bees, in particular solitary species, should be conserved and promoted for stable crop pollination services in dynamic agricultural landscapes.
Keywords: competition; facilitation; flowering phenology; foraging behaviour; fruit quality; mass-flowering crops; oilseed rape; strawberry

Honeybees are far too insufficient to supply optimum pollination services in agricultural systems worldwide - Mashilingi, Shibonage K.; Zhang, Hong; Garibaldi, Lucas A.; An, Jiandong (Agriculture, Ecosystems and Environment, 2022)
Evidence of a decline in wild pollinators is increasing across global and local habitats. However, with regional variation, the number of managed pollinators has increased globally. Whether these managed pollinators can sufficiently meet the agricultural pollination demand given wild pollinator declines remains unclear. Data on 49 honeybee-pollinated crops cultivated worldwide and stocked honeybee colonies were analysed to assess the pollination demand and pollination service capacity between 1989 and 2019. We found a rapidly increasing demand for honeybee pollination but a decreasing pollination service capacity of honeybee colonies. Globally, the demand for honeybee pollination rose approximately 2.3 times higher than the stocked number of honeybee colonies in 2019, growing 1.78% annually, almost 2 times faster than honeybee colonies (0.95%). On average, the pollination service capacity, growth rates of demands for honeybee colony stocks and honeybee pollination, and diversity of honeybee-pollinated crops varied regionally. Nevertheless, fluctuation of the honeybee-pollination demand increased with increased fluctuation of crop diversification. Oil crops accounted for over 70% of the world's honeybee-pollination demand in 2019, with soybean and rapeseed accounting for 39% and 16%, respectively. This was the case in less diversified countries, where a few crops dominated the demand for honeybee pollination, including American countries such as Argentina, Brazil, and the USA, compared to more diversified countries such as China, India, and Japan in Asia. Our study shows that managed pollinators are far too insufficient to adequately supply the agricultural pollination demand worldwide. This emphasises the importance of ongoing calls for protecting pollinators and the integrated management of honeybees and wild pollinator assemblages for a sustainable food-secure future world.
Keywords: Crop diversification; Honeybee; Pollination demand; Pollination service capacity

Factors associated with honey bee colony losses: A mini‐review - Hristov, Peter; Shumkova, Rositsa; Palova, Nadezhda; Neov, Boyko (Veterinary Sciences, 2020)
The Western honey bee (Apis mellifera L., Hymenoptera: Apidae) is a species of crucial economic, agricultural and environmental importance. In the last ten years, some regions of the world have suffered from a significant reduction of honey bee colonies. In fact, honey bee losses are not an unusual phenomenon, but in many countries worldwide there has been a notable decrease in honey bee colonies. The cases in the USA, in many European countries, and in the Middle East have received considerable attention, mostly due to the absence of an easily identifiable cause. It has been difficult to determine the main factors leading to colony losses because of honey bees’ diverse social behavior. Moreover, in their daily routine, they make contact with many agents of the environment and are exposed to a plethora of human activities and their consequences. Nevertheless, various factors have been considered to be contributing to honey bee losses, and recent investigations have established some of the most important ones, in particular, pests and diseases, bee management, including bee keeping practices and breeding, the change in climatic conditions, agricultural practices, and the use of pesticides. The global picture highlights the ectoparasitic mite Varroa destructor as a major factor in colony loss. Last but not least, microsporidian parasites, mainly Nosema ceranae, also contribute to the problem. Thus, it is obvious that there are many factors affecting honey bee colony losses globally. Increased monitoring and scientific research should throw new light on the factors involved in recent honey bee colony losses. The present review focuses on the main factors which have been found to have an impact on the increase in honey bee colony losses.
Keywords: Colony collapse disorder; Honey bee losses; Negative pressures; Nosematosis; Varroa destructor; Viral diseases

Challenges to sustaining beekeeping livelihoods in Ghana - Jeil, Emmanuel Bintaayi; Abass, Kabila; Segbefia, Alexander Yao (GeoJournal, 2022)
Although making a living within the beekeeping value chain can be wobbly due to some challenges, this aspect has often been ignored in academic circles. Discussions of challenges to livelihoods that draw on beekeeping have focused largely on beehive management but paid little attention to related issues that engage broader contexts of the beekeeping value chain. This paper, therefore, examines challenges to beekeeping livelihoods among actors within Ghana’s beekeeping value chain. The study is a cross-sectional study employing a mixed-method and a triangulation of individual interviews and focus group discussions. To examine the different challenges to the beekeeping value chain, we purposively sampled 106 beekeepers, six hive product retailers and two key informants from Ghana’s Ministry of Food and Agriculture. The findings revealed that bee abscondment, pest and predators, lack of finance, and bush (wild) fires were some of the challenges to the sustainability of livelihoods of beekeepers. However, participants ranked lack of finance to expand operations as the major challenge to beekeeping livelihoods. Institutional support from Non-Governmental Organisations and financial institutions in the form of credit and education is a critical requirement for making livelihoods hinged on beekeeping secure and sustainable.
Keywords: Beekeeping; Challenges; Ghana; Livelihoods sustainability

Honey bee pathogenesis posing threat to its global population: a short review - Parveen, Nagma; Miglani, Rashi; Kumar, Ankit; Dewali, Seeta; Kumar, Kulbhushan; Sharma, Netrapal; Bisht, Satpal Singh (Proceedings of the Indian National Science Academy, 2022)
Pollination and ecosystem sustainability are the two chief varieties of services provided by honey bees and they play a paramount role in the functioning of an ecosystem and human lives. Apis cerana, Apis mellifera, Apis florea and Apis dorsata are the main species of honey bees found all over the world. Honey, beeswax, royal jelly and propolis are the core products produced by honey bees. This review aims to emphasize and bring together the facts and ground realities leading to the decline of the honey bee population. The declining population of bees is a serious threat to ecosystem services therefore researchers around the world are consequently interested in understanding the causes and concerns. The reasons responsible for the fall in the honey bee population were bacteria, viruses, parasites and other invaders, including certain chemicals, toxic substances, improper nutrition and dirty farming practices. Conservation and management strategies are much needed to counter the decline of these important insects in the interest of global ecosystem services and commercial benefits.
Keywords: Chemical toxicity; Ecosystem services; Honey bee; Pathogens; Population decline

Pesticide–virus interactions in honey bees: Challenges and opportunities for understanding drivers of bee declines - Harwood, Gyan P.; Dolezal, Adam G. (Viruses, 2020)
Honey bees are key agricultural pollinators, but beekeepers continually suffer high annual colony losses owing to a number of environmental stressors, including inadequate nutrition, pressures from parasites and pathogens, and exposure to a wide variety of pesticides. In this review, we examine how two such stressors, pesticides and viruses, may interact in additive or synergistic ways to affect honey bee health. Despite what appears to be a straightforward comparison, there is a dearth of studies examining this issue likely owing to the complexity of such interactions. Such complexities include the wide array of pesticide chemical classes with different modes of actions, the coupling of many bee viruses with ectoparasitic Varroa mites, and the intricate social structure of honey bee colonies. Together, these issues pose a challenge to researchers examining the effects pesticide-virus interactions at both the individual and colony level.
Keywords: Honey bee virus; Insecticide–virus synergism; Pesticide resistance; Toxicology; Virus tolerance/resistance

Overview of the testing and assessment of effects of microbial pesticides on bees: strengths, challenges and perspectives - Borges, Shannon; Alkassab, Abdulrahim T.; Collison, Elizabeth; Hinarejos, Silvia; Jones, Ben; McVey, Emily; Roessink, Ivo; Steeger, Thomas; Sultan, Maryam; Wassenberg, Jacoba (Apidologie, 2021)
Currently, there is a growing interest in developing biopesticides and increasing their share in the plant protection market as sustainable tools in integrated pest management (IPM). Therefore, it is important that regulatory requirements are consistent and thorough in consideration of biopesticides’ unique properties. While microbial pesticides generally have a lower risk profile, they present special challenges in non-target organism testing and risk assessment since, in contrast to chemical pesticides, their modes of action include infectivity and pathogenicity rather than toxicity alone. For this reason, non-target organism testing guidelines designed for conventional chemical pesticides are not necessarily directly applicable to microbial pesticides. Many stakeholders have recognised the need for improvements in the guidance available for testing microbial pesticides with honey bees, particularly given the increasing interest in development and registration of microbial pesticides and concerns over risks to pollinators. This paper provides an overview of the challenges with testing and assessment of the effects of microbial pesticides on honey bees (Apis mellifera), which have served as a surrogate for both Apis and non-Apis bees, and provides a foundation toward developing improved testing methods.
Keywords: Apis mellifera; biological control; biopesticides; pathogenicity; toxicity

Possible side effects of sugar supplementary nutrition on honey bee health - Frizzera, Davide; Del Fabbro, Simone; Ortis, Giacomo; Zanni, Virginia; Bortolomeazzi, Renzo; Nazzi, Francesco; Annoscia, Desiderato (Apidologie, 2020)
Food shortage, along with biotic stressors, contributes to winter honey bee colony losses. In autumn, to support honey bee colonies and prepare them for the winter season, beekeepers can supply homemade syrups which could contain compounds with possible negative side effects. In this study, we investigated the toxicity of one of those compounds (e.g., hydroxymethylfurfural, HMF) at doses consistent with literature data both to healthy bees and bees challenged with their most important parasite (i.e., Varroa destructor). To strengthen available data on HMF concentration in sugar syrups, we also investigated HMF formation in homemade 2:1 inverted sugar syrup, considering, in particular, the influence of temperature or boiling time on different homemade sugar syrups according to their acidity. Finally, we studied the effects of the acidity of sugar syrups on honeybee survival, and tested whether or not sucrose inversion through acidification is really necessary. We show that doses of HMF similar to those reported as sublethal in the literature appear to be non-toxic even to mite infested bees. However, the amount of HMF that can be found in homemade syrups, which increases with temperature and acidity, can be much higher and can cause significant bee mortality. Moreover, we highlighted the detrimental effect of syrups acidity on honeybee survival, suggesting that the addition of lemon or any other acidifying substance to invert the sucrose could be harmful and not necessary. Our results suggest a responsible approach to homemade colony nutrition.
Keywords: honey bee; hydroxymethylfurfural; nutrition; sugar syrup acidity

World Honey Bee Health: The Global Distribution of Western Honey Bee ( Apis mellifera L.) Pests and Pathogens - Boncristiani, Humberto; Ellis, James D.; Bustamante, Tomas; Graham, Jason; Jack, Cameron; Kimmel, Chase B.; Mortensen, Ashley; Schmehl, Daniel R. (Bee World, 2021)
Western honey bees, Apis mellifera L., (hereafter “honey bee”) are among the most widespread organisms in the world, as their association with humans has led to their dispersal from their native ra...

Review on effects of some insecticides on honey bee health - Zhao, Hang; Li, Guilin; Cui, Xuepei; Wang, Hongfang; Liu, Zhenguo; Yang, Yuewei; Xu, Baohua (Pesticide Biochemistry and Physiology, 2022)
Insecticides, one of the main agrochemicals, are useful for controlling pests; however, the indiscriminate use of insecticides has led to negative effects on nontarget insects, especially honey bees, which are essential for pollination services. Different classes of insecticides, such as neonicotinoids, pyrethroids, chlorantraniliprole, spinosad, flupyradifurone and sulfoxaflor, not only negatively affect honey bee growth and development but also decrease their foraging activity and pollination services by influencing their olfactory sensation, memory, navigation back to the nest, flight ability, and dance circuits. Honey bees resist the harmful effects of insecticides by coordinating the expression of genes related to immunity, metabolism, and detoxification pathways. To our knowledge, more research has been conducted on the effects of neonicotinoids on honey bee health than those of other insecticides. In this review, we summarize the current knowledge regarding the effects of some insecticides, especially neonicotinoids, on honey bee health. Possible strategies to increase the positive impacts of insecticides on agriculture and reduce their negative effects on honey bees are also discussed.
Keywords: Adverse effects; Agrochemicals; Health; Honey bees; Neonicotinoids

Parasites and pesticides act antagonistically on honey bee health - Bird, Gwendolyn; Wilson, Alan E.; Williams, Geoffrey R.; Hardy, Nate B. (Journal of Applied Ecology, 2021)
Pesticides and parasites have each been linked to increased mortality in western honey bees (Apis mellifera). Currently, it is uncertain if one makes the other worse; several studies have tested for potential synergistic stressor effects, but results have been mixed. Here, we use a hierarchical meta-analysis of 63 experiments from 26 studies to gain a clearer view of the combined effects of parasites and pesticides on honey bee health. We found that combined pesticide–parasite treatments do tend to be deadlier than uncombined treatments but are significantly less deadly than predicted additive or multiplicative effects. In other words, combined treatment effects are not synergistic, but antagonistic. Much of the previous uncertainty about the combined effects of pesticides and parasites on honey bee health can be attributed to a bias in the previous research against stressor antagonism; many researchers have excluded the possibility of antagonism a priori. Synthesis and applications. Meta-analysis shows that when honey bees are stressed by a combination of pesticides and parasites, the combined stress effect is antagonistic, that is, less than the sum of its parts. A better understanding of the mechanisms underlying this antagonism could prove critical for effective management of honey bee health.
Keywords: colony loss; honey bee; interaction; meta-analysis; parasite; pesticide; stress; synergy

Acute and chronic ingestion of polyethylene (PE) microplastics has mild effects on honey bee health and cognition - Balzani, Paride; Galeotti, Giorgia; Scheggi, Sara; Masoni, Alberto; Santini, Giacomo; Baracchi, David (Environmental Pollution, 2022)
The massive use of plastic has contributed to huge quantities of hazardous refuse at a global scale and represents one of the most prominent issues of the Anthropocene. Microplastics (MPs) have been detected in almost all environments and pose a potential threat to a variety of plant and animal species. Many studies have reported a variety of effects, from negligible to detrimental, of MPs to aquatic organisms. Conversely, much less is known about their effect on terrestrial biota, and particularly on animal behavior and cognition. We assessed the oral toxicity of polyethylene (PE) MPs at three different concentrations (0.5, 5, and 50 mg L−1), and at different timescales (1 day and 7 days of exposure) and tested for their effects on survival, food intake, sucrose responsiveness, habituation to sucrose and appetitive olfactory learning and memory in the honey bee Apis mellifera. We found that workers were not completely unaffected by acute and prolonged ingestion of this polymer. A significant effect of PE on bee mortality was found for the highest concentration but not for lower ones. PE affected feeding behavior in a concentration-dependent manner, with bees consuming more food than controls when exposed to low concentration PE. Regarding our behavioral and cognitive experiments, the high concentration PE was found to affect only bees’ ability to respond consistently to sucrose but not sucrose sensitivity, habituation to sucrose or learning and memory abilities, even for prolonged exposure to PE. While these last results may look somewhat encouraging, we discussed why caution is warranted before ruling out the possibility that PE particles at environmental concentrations are harmful to honey bees.
Keywords: Apis mellifera; Learning and memory; Microplastics; Pollinators; Pollution; Stressors

Environmental exposures associated with honey bee health - Mayack, Christopher; Macherone, Anthony; Zaki, Asal Ghaffari; Filiztekin, Elif; Özkazanç, Burcu; Koperly, Yasameen; Schick, Sassicaia J.; Eppley, Elizabeth J.; Deb, Moniher; Ambiel, Nicholas; Schafsnitz, Alexis M.; Broadrup, Robert L. (Chemosphere, 2022)
Bee health is declining on a global scale, yet the exact causes and their interactions responsible for the decline remain unknown. To more objectively study bee health, recently biomarkers have been proposed as an essential tool, because they can be rapidly quantified and standardized, serving as a comparable measure across bee species and varying environments. Here, we used a systems biology approach to draw associations between endogenous and exogenous chemical profiles, with pesticide exposure, or the abundance of the 21 most common honey bee diseases. From the analysis we identified chemical biomarkers for both pesticide exposure and bee diseases along with the mechanistic biological pathways that may influence disease onset and progression. We found a total of 2352 chemical features, from 30 different hives, sampled from seven different locations. Of these, a total of 1088 significant associations were found that could serve as chemical biomarker profiles for predicting both pesticide exposure and the presence of diseases in a bee colony. In almost all cases we found novel external environmental exposures within the top seven associations with bee diseases and pesticide exposures, with the majority having previously unknown connections to bee health. We highlight the exposure-outcome paradigm and its ability to identify previously uncategorized interactions from different environmental exposures associated with bee diseases, pesticides, mechanisms, and potential synergistic interactions of these that are responsible for honey bee health decline.
Keywords: Bee pathogens; Colony collapse; Exposomics; Pesticides; Systems biology; Xenobiotics

Land use changes associated with declining honey bee health across temperate North America - Richardson, Rodney T.; Conflitti, Ida M.; Labuschagne, Renata S.; Hoover, Shelley E.; Currie, Rob W.; Giovenazzo, Pierre; Guarna, M. Marta; Pernal, Stephen F.; Foster, Leonard J.; Zayed, Amro (Environmental Research Letters, 2023)
Urbanization and agricultural intensification continue to reshape landscapes, altering the habitat available to wildlife and threatening species of both economic and conservation concern. The honey bee, Apis mellifera, is a pollinator of economic importance to North American agriculture yet managed colonies are burdened by poor health and high annual mortality. Understanding the factors influencing this species is critical for improving colony health and supporting crop production. We used a nationwide cohort of 638 managed Canadian colonies to study the dominant drivers of colony health and overwintering mortality. We found that fall colony weight—a major predictor of overwintering survival—was strongly associated with landscape composition. Among four broadly defined land cover types, we discovered that urban and forested land covers were the least valuable sources of habitat for colonies, as inferred from fall colony weight measurements. Agricultural land appeared to provide habitat quality of slightly greater value, while herbaceous land cover was most strongly positively associated with fall colony weight. Herbaceous land cover also exhibited an associational effect size which was strongly statistically distinguishable from those of urban and forested land. Our research indicates that recent and ongoing land-use changes exacerbate modern apicultural challenges, and suggests variation in nutrition or floral resource availability plays a major role in modulating honey bee health. Our work highlights the need for additional research investigating whether land use change-associated alterations in floral resource availability increase the potential for resource competition between pollinator species.
Keywords: land cover; land use change; landscape ecology; pollination; pollinator conservation

Foraging of honey bees in agricultural landscapes with changing patterns of flower resources - Bänsch, Svenja; Tscharntke, Teja; Ratnieks, Francis L.W.; Härtel, Stephan; Westphal, Catrin (Agriculture, Ecosystems and Environment, 2020)
The demand for crop pollination is increasing and honey bees are frequently used, in particular as wild pollinators are in decline. Temporal and spatial variation of flower resources affects foraging decisions of wild and honey bees. To optimise crop pollination management a better understanding of potential competition for pollinators in mass- and minor-flowering crops is needed. We combined waggle dance decoding, pollen load analysis and field surveys to identify the habitat preferences and pollen use of honey bees in response to spatio-temporal changes in resource availability. Observation hives were placed on the edge of eleven fields of blooming strawberries (mean 2.24 ha) located in landscapes with different amounts of oilseed rape (OSR), semi-natural habitats (SNH) and apple trees in Germany. In addition, we surveyed honey bees and wild bees in strawberry fields. Honey bee dances more often indicated strawberry, OSR fields and SNH than expected given their landscape-wide areas. Honey bees collected on average 7.9 % strawberry, 49.0 % OSR, 30.2 % Pyrus type (e.g. apple) and 12.9 % other pollen types. The mean honey bee foraging distance was 740 m, and decreased with OSR availability. In the observation hives, dances for strawberry fields were not directly affected by OSR availability or SNH land cover. But large amounts of OSR reduced overall honey bee and bumble bee abundance in strawberry fields, while solitary bees were unaffected. Bumble bees were most abundant in strawberry fields (54.1%) and together with solitary bees (19.7%) they represented about 75.0% of the observed bees. Minor-flowering strawberry fields represent a preferred resource for honey bees, especially for small colonies as indicated by decoding of waggle dances. However, the availability of more attractive OSR and local strawberry flower cover moderates the abundance of social bees (honey bees and bumble bees) in strawberry fields while other wild bees were less affected. Hence, we conclude that wild bee conservation plays a major role for strawberry pollination. If pollination services by solitary bees are limited, small honey bee hives can be used scrupulously to supplement pollination services in strawberries.
Keywords: Competition; Ecosystem service; Foraging behaviour; Oilseed rape; Pollination; Strawberriess; Waggle dance

Agroecosystem landscape diversity shapes wild bee communities independent of managed honey bee presence - St. Clair, Ashley L.; Zhang, Ge; Dolezal, Adam G.; O'Neal, Matthew E.; Toth, Amy L. (Agriculture, Ecosystems and Environment, 2022)
Large scale agricultural production can lead to a reduction in availability of habitat used by wild bees for nesting and forage and has been implicated in worldwide bee population declines. There is growing concern that further declines in wild bee populations will occur because of continued transformations of natural or seminatural landscapes into crop monocultures. Managed honey bees, often used for pollination services in agricultural systems, can compete with wild bees and are hypothesized to negatively affect their communities. Although the response of wild bees to both agriculture and honey bees (i.e., apiculture) has been studied, the relative importance of each and their potential interactions on wild bee communities are not well understood. To forecast the extent to which landscape simplification can affect wild bees and to better understand whether honey bee presence in an already disturbed landscape might further exacerbate declines, we conducted a replicated, longitudinal assessment of wild bee community richness and richness of functional guilds (e.g., floral specificity and nesting preference) in an intensively farmed region of the United States where much of the landscape is devoted to monoculture annual crop (maize and soybean) production and managed honey bee colonies co-occur. The presence of a small apiary (4 colonies) had no immediate effect on wild bee richness, suggesting honey beekeeping may not always negatively impact wild bees. Rather, landscape composition analysis showed strong responses of wild bees to land use, with communities being less speciose in landscapes with high proportions of crop production. The availability of woodland and grassland habitat, especially at the local scale (<800 m), was associated with the greatest increase in bee richness especially for rarer aboveground nesting and floral specialist species. These data suggest large scale monocultures have a greater impact on bee communities than the presence of small apiaries. The results of this research provide important information on possible solutions in agroecosystem management to support increased bee diversity where annual crop production and apiculture are practiced. Namely, mitigation of wild bee declines in such agroecosystems may benefit more from the re-integration of landscape biodiversity, with priority on the re-introduction of perennial vegetation, like that found in woodland and grassland habitats, than the restriction of honey bee apiculture. Data Availability: Data will be archived through Iowa State Universities digital data repository.
Keywords: Agriculture; Apis mellifera; Competition; Guilds; Native bee; Soybean; Spatial scales

Honey bee colony performance affected by crop diversity and farmland structure: a modeling framework - Horn, Juliane; Becher, Matthias A.; Johst, Karin; Kennedy, Peter J.; Osborne, Juliet L.; Radchuk, Viktoriia; Grimm, Volker (Ecological Applications, 2021)
Forage availability has been suggested as one driver of the observed decline in honey bees. However, little is known about the effects of its spatiotemporal variation on colony success. We present a modeling framework for assessing honey bee colony viability in cropping systems. Based on two real farmland structures, we developed a landscape generator to design cropping systems varying in crop species identity, diversity, and relative abundance. The landscape scenarios generated were evaluated using the existing honey bee colony model BEEHAVE, which links foraging to in-hive dynamics. We thereby explored how different cropping systems determine spatiotemporal forage availability and, in turn, honey bee colony viability (e.g., time to extinction, TTE) and resilience (indicated by, e.g., brood mortality). To assess overall colony viability, we developed metrics, PH and PP, which quantified how much nectar and pollen provided by a cropping system per year was converted into a colony's adult worker population. Both crop species identity and diversity determined the temporal continuity in nectar and pollen supply and thus colony viability. Overall farmland structure and relative crop abundance were less important, but details mattered. For monocultures and for four-crop species systems composed of cereals, oilseed rape, maize, and sunflower, PH and PP were below the viability threshold. Such cropping systems showed frequent, badly timed, and prolonged forage gaps leading to detrimental cascading effects on life stages and in-hive work force, which critically reduced colony resilience. Four-crop systems composed of rye-grass–dandelion pasture, trefoil–grass pasture, sunflower, and phacelia ensured continuous nectar and pollen supply resulting in TTE > 5 yr, and PH (269.5 kg) and PP (108 kg) being above viability thresholds for 5 yr. Overall, trefoil–grass pasture, oilseed rape, buckwheat, and phacelia improved the temporal continuity in forage supply and colony's viability. Our results are hypothetical as they are obtained from simplified landscape settings, but they nevertheless match empirical observations, in particular the viability threshold. Our framework can be used to assess the effects of cropping systems on honey bee viability and to develop land-use strategies that help maintain pollination services by avoiding prolonged and badly timed forage gaps.
Keywords: Apis mellifera; BEEHAVE; colony viability; crop diversity; cropping system; decline; forage availability; forage gaps; honey bees; landscape generator; modeling

Land conversion and pesticide use degrade forage areas for honey bees in America's beekeeping epicenter - Dixon, Dan J.; Zheng, Haochi; Otto, Clint R.V. (PLoS ONE, 2021)
A diverse range of threats have been associated with managed-bee declines globally. Recent increases of two known threats, land-use change and pesticide use, have resulted from agricultural expansion and intensification notably in the top honey-producing state in the United States: North Dakota. This study investigated the dual threat from land conversion and pesticide use surrounding -14,000 registered apiaries in North Dakota from 2001 to 2014. We estimated the annual total insecticide use (kg) on major crops within 1.6 km of apiary sites. Of the eight insecticides quantified, six showed significant increasing trends over the time period. Specifically, applications of the newly established neonicotinoids Chlothianidin, Imidacloprid and Thiamethoxam, increased annually by 1329 kg, 686 kg, 795 kg, respectively. Also, the use of Chlorpyrifos, which was well-established in the state by 2001 and is highly toxic to honey bees, increased by -8,800 kg annually from 6,500 kg in 2001 to 115,000 kg in 2014 on corn, soybeans and wheat. We further evaluated the relative quality changes of natural/semi-natural land covers surrounding apiaries in 2006, 2010 and 2014, a period of significant increases in cropland area. In areas surrounding apiaries, we observed changes in multiple indices of forage quality that reflect the deteriorating landscape surrounding registered apiary sites due to land-use change and pesticide-use increases. Overall, our results suggest that the application of foliar-applied insecticides, including pyrethroids and one organophosphate, increased surrounding apiaries when the use of neonicotinoid seed treatments surged and the area for producing corn and soybeans expanded. Spatially, these threats were most pronounced in southeastern North Dakota, a region hosting a high density of apiary sites that has recently experienced corn and soybean expansion. Our results highlight the value of natural and semi-natural land covers as sources of pollinator forage and refugia for bees against pesticide exposure. Our study provides insights for targeting conservation efforts to improve forage quality benefiting managed pollinators.

Diversified Farming in a Monoculture Landscape: Effects on Honey Bee Health and Wild Bee Communities - St Clair, Ashley L.; St Clair, Ashley L.; Zhang, Ge; Dolezal, Adam G.; O'Neal, Matthew E.; Toth, Amy L.; Toth, Amy L. (Environmental Entomology, 2020)
In the last century, a global transformation of Earth's surface has occurred due to human activity with extensive agriculture replacing natural ecosystems. Concomitant declines in wild and managed bees are occurring, largely due to a lack of floral resources and inadequate nutrition, caused by conversion to monoculture-based farming. Diversified fruit and vegetable farms may provide an enhanced variety of resources through crops and weedy plants, which have potential to sustain human and bee nutrition. We hypothesized fruit and vegetable farms can enhance honey bee (Hymenoptera: Apidae, Apis mellifera Linnaeus) colony growth and nutritional state over a soybean monoculture, as well as support a more diverse wild bee community. We tracked honey bee colony growth, nutritional state, and wild bee abundance, richness, and diversity in both farm types. Honey bees kept at diversified farms had increased colony weight and preoverwintering nutritional state. Regardless of colony location, precipitous declines in colony weight occurred during autumn and thus colonies were not completely buffered from the stressors of living in a matrix dominated with monocultures. Contrary to our hypothesis, wild bee diversity was greater in soybean, specifically in August, a time when fields are in bloom. These differences were largely driven by four common bee species that performed well in soybean. Overall, these results suggest fruit and vegetable farms provide some benefits for honey bees; however, they do not benefit wild bee communities. Thus, incorporation of natural habitat, rather than diversified farming, in these landscapes, may be a better choice for wild bee conservation efforts.
Keywords: Apis mellifera; diversified farming; honey bee; wild bee

Foraging behaviour and preference of pollen sources by honey bee (Apis mellifera) relative to protein contents - Ghosh, Sampat; Jeon, Hyejin; Jung, Chuleui (Journal of Ecology and Environment, 2020)
Background: Pollen is an important source of protein and lipids for many animals including honey bees. In order to understand the foraging behaviour of honey bee colonies and preference among the available floral resources, pollen collections from three experimental healthy colonies of honey bees were analysed in the month of June. Results: The amount of pollen collections were related to the colony's need which was indicated by the number of larval and adult bees present in the hive. Interesting was the sequence of pollen collection from different floral sources. All honey bee colonies collected pollens from Trifolium repens first, then Erigeron annus and the third choice was Coreopsis drummondii and Oenothera biennis flowers. Total protein content of Trifolium pollen was the highest (20.0 g/100 g DM), and the others were in the range of 8.9-11.4 g/100 g DM. Conclusion: The results indicated that the first criteria for honey bee foraging preference of pollens would be the nutritional contents of protein and the resource availability of the lesser nutritious floral sources. This information can help pollinator protection programmes of habitat manipulation using flowering plants for nectar and pollen sources.
Keywords: Amino acid; Coreopsis; Erigeron; Nutrition; Oenothera; Trifolium

Nutritional Quality and Safety of Complementary Foods Developed from Blends of Staple Grains and Honey Bee Larvae (Apis mellifera) - Mekuria, Shewangzaw Addisu; Kinyuru, John N.; Mokua, Beatrice Kiage; Tenagashaw, Mesfin Wogayehu (International Journal of Food Science, 2021)
Complementary foods must be adequate to satisfy the nutritional needs of the growing child together with breastfeeding. This study was aimed at evaluating the nutritional composition, microbial safety, and sensory quality of extruded complementary foods developed from blends of staple grains and insect bee larva (Apis mellifera). Teff, maize, soybean, and bee larva samples were milled to flour and blended before extrusion as follows: ComF01 (57% maize, 29% teff, and 14% soybean) and ComF02 (58% maize, 29% teff, and 13% bee larvae) using NutriSurvey software (version, 2007). Nutrient composition, microbial, and sensory analyses of developed flour blends were conducted using standard methods. The proximate composition of moisture, fat, fiber, carbohydrate, and energy was significantly different between the developed and commercial wean-mix foods. ComF02 recorded the highest fat content (14.3 g/100 g), energy (427.18 kcal/100 g), and vitamins A (706 μg/100 g), B3 (8.2 mg/100 g), and B9 (86.7 mg/100 g) while ComF01 had the highest protein content (12.56 g/100 g). Iron (40.94 mg/100 g) and calcium (68.20 mg/100 g) were the minerals with the highest content in ComF02. Both ComF01 and ComF02 met the recommended dietary allowance of nutrients for infants aged 6-12 months. Overall, the present study showed that bee larvae can be used to develop complementary foods that are nutritionally adequate, microbiologically safe, and sensory acceptable meeting the dietary allowance of infants at an acceptable level compared to conventional cereal-based foods.

A Sweeter Pill to Swallow: A Review of Honey Bees and Honey as a Source of Probiotic and Prebiotic Products - Mustar, Suraiami; Ibrahim, Nurliayana (Foods, 2022)
Honey bees and honey, have been the subject of study for decades due to their importance in improving health. At times, some of the probiotics may be transferred to the honey stored in the honeycomb. Consumers may benefit from consuming live-probiotics honey, which can aid in suppressing the reproduction of pathogens in their digestive system. Prebiotics, on the other hand, are mainly carbohydrates that promote the growth of native microflora probiotics in the digestive tract to maintain a healthy environment and improve the gut performance of the host. Therefore, this narrative review aims to present and analyze ten years’ worth of information on the probiotic and prebiotic potential of honey bees and honey since not many review articles were found discussing this topic. Results showed that not many studies have been performed on the probiotic and prebiotic aspects of honey bees and honey. If further research is conducted, isolated probiotics from the bee’s gut combined with honey’s prebiotic properties can be manipulated as potential sources of probiotics and prebiotics for human and animal benefits since they appear to be interrelated and function in symbiosis.
Keywords: honey; honey bee; lactic acid bacteria; oligosaccharides; prebiotic; probiotic

Honeybee nutrition and pollen substitutes: A review - Paray, Bilal Ahamad; Kumari, Indu; Hajam, Younis Ahmad; Sharma, Bharti; Kumar, Rajesh; Albeshr, Mohammed Fahad; Farah, Mohammad Abul; Khan, Javed Masood (Saudi Journal of Biological Sciences, 2021)
Like other invertebrates, honey bees too are poikilothermic animals; they cannot regulate their body temperature and they have to undergo a period of inactivation when atmospheric temperature is un-tolerable. During this period, their nutritional requirements and metabolic activities are minimized due to highly restricted foraging activities. The egg-laying by queen and rearing of unsealed and sealed brood are decreased, however their extent is governed by the quantum of stored food available. The problems of deleterious influence of adverse weather conditions and non-availability of bee flora all round the year, in a particular locality, have been realized by the researchers/beekeepers and migration concept has been developed to solve this problem. But again, migration itself is not an easy task. The provision of artificial feeding as an alternate of migration. Scientists all over the world have formulated different artificial food recepies for bees on the basis of nutrient composition of honey and pollen, acceptability, palatability, digestibility and affordability of ingredients. This may help to maintain all colony parameters enough to derive maximum advantage of forthcoming floral rich season. However, a standard balanced diet for commercial beekeeping that is accepted worldwide is still awaited.
Keywords: Apis mellifera; Commercial beekeeping; Diet; Honeybee; India; Nectar; Pollen

Polyphenols as food supplement improved food consumption and longevity of honey bees (Apis mellifera) intoxicated by pesticide thiacloprid - Hýbl, Marian; Mráz, Petr; Šipoš, Jan; Hoštičková, Irena; Bohatá, Andrea; Čurn, Vladislav; Kopec, Tomáš (Insects, 2021)
Malnutrition is one of the main problems related to the global mass collapse of honey bee colonies, because in honey bees, malnutrition is associated with deterioration of the immune system and increased pesticide susceptibility. Another important cause of mass bee colonies losses is the use of pesticides. Therefore, the goal of this study was to verify the influence of polyphenols on longevity, food consumption, and cytochrome P450 gene expression in worker bees intoxicated by thiacloprid. The tests were carried out in vitro under artificial conditions (caged bees). A conclusively lower mortality rate and, in parallel, a higher average food intake, were observed in intoxicated bees treated using a mixture of phenolic acids and flavonoids compared to untreated intoxicated bees. This was probably caused by increased detoxification capacity caused by increased expression level of genes encoding the cytochrome P450 enzyme in the bees. Therefore, the addition of polyphenols into bee nutrition is probably able to positively affect the detoxification capacity of bees, which is often reduced by the impact of malnutrition resulting from degradation of the environment and common beekeeping management.
Keywords: Cage experiments; Cytochrome P450; Detoxification; Food intake; Mortality rate

Chemical composition of bee bread (perga), a functional food: A review - Ćirić, Jelena; Haneklaus, Nils; Rajić, Sara; Baltić, Tatjana; Lazić, Ivana Branković; Đorđević, Vesna (Journal of Trace Elements and Minerals, 2022)
ABSTRACT Background Bee bread can be defined as a popular bee product (behind honey, propolis, beewax, bee pollen, royal jelly and apitoxin), a natural substance, a mixture of bee pollen, honey and lactic acid bacteria that is the result of lactic acid bacteria (LAB) fermentation of bee pollen collected by bees from the natural environment, and is the protein basis of food in the beehive. Results Primarily, honey bees use bee bread for brood growing (nutrition), but humans use bee bread in folk medicine and apitherapy, but also as a functional food, according to the bread's powerful healing properties and content of different molecules (bioactive, antibacterial, antifungal, antiviral, etc.). The biological properties of bee bread depend on its chemical composition, the melliferous plants in the region, geographical area, season, climatic conditions, etc. Conclusion According to its chemical and nutritional properties, bee bread is more valuable (higher biological value, faster digestibility and better chemical composition if compared to bee pollen) than bee pollen. Bee bread contains about 250 different substances, such as proteins, macro- and microelements, lipids, free amino acids, fatty acids (linoleic, linolenic and arachidonic), flavonoids, phenolic compounds, vitamins, and enzymes. Many different scientific articles have been published in international journals with focus on the chemical composition of honey, bee pollen and propolis. This paper contributes to the knowledge of the chemical composition, nutritional value and bioactivity of bee bread.

Food wanting is mediated by transient activation of dopaminergic signaling in the honey bee brain - Huang, Jingnan; Zhang, Zhaonan; Feng, Wangjiang; Zhao, Yuanhong; Aldanondo, Anna; Gabriela de Brito Sanchez, Maria; Paoli, Marco; Rolland, Angele; Li, Zhiguo; Nie, Hongyi; Lin, Yan; Zhang, Shaowu; et al.
The biological bases of wanting have been characterized in mammals, but whether an equivalent wanting system exists in insects remains unknown. In this study, we focused on honey bees, which perform intensive foraging activities to satisfy colony needs, and sought to determine whether foragers leave the hive driven by specific expectations about reward and whether they recollect these expectations during their waggle dances. We monitored foraging and dance behavior and simultaneously quantified and interfered with biogenic amine signaling in the bee brain. We show that a dopamine-dependent wanting system is activated transiently in the bee brain by increased appetite and individual recollection of profitable food sources, both en route to the goal and during waggle dances. Our results show that insects share with mammals common neural mechanisms for encoding wanting of stimuli with positive hedonic value.

Pollen diet—properties and impact on a bee colony - Bryś, Maciej Sylwester; Skowronek, Patrycja; Strachecka, Aneta (Insects, 2021)
Diet is an important factor in the proper development of the individual and the entire colony. A pollen diet affects honey bees in a number of ways. It can stimulate the number and type of hemocytes, the total number of proteins, carbohydrates and lipids, affect the histology of the middle intestine, and ensure the correct ontogenesis of the larvae. Moreover, selected single-flower diets can stimulate the development of the pharyngeal glands that produce royal jelly, thus conditioning the development of secretory immunity. Selected single-species pollen may also increase the phenol oxidase concentration, which contributes to the humoral response. A honey bee diet based on multi-flower pollen is more desirable than a mono-flower diet, but must be properly balanced.
Keywords: Apis mellifera; Monofloral diet; Multifloral diet; Nutrition pollen

Improving pollen substitutes to maintain development and hemolymph parameters of honey bees (Apis mellifera L.) during pollen dearth periods - Omar, Eslam M.; Amro, Abdulraouf M. (Journal of Apicultural Research, 2023)
To enhance the performance of honey bee colonies and to improve the physiological characteristics of honey bee workers in late winter and early spring (dearth period) in Assiut region, Upper Egypt—three pollen substitutes rich in protein and available in the local market were used and compared with bee bread as a control. The pollen substitutes were administrated at 7-day intervals for 15 wk, from December 2018 to March 2019. The rate of food consumption, sealed brood areas, bee population size, and characteristics of hemolymph of honey bee individuals were measured. Stored bee bread was the best protein source for developing honey bee colonies, continued with date syrup, recording the highest sealed brood areas compared with the rest of the diets. All hemolymph parameters under substitute feeding conditions were less than those determined under control conditions (bee bread), and the numbers of spring bees were more than those of winter bees. Total soluble solids (TSS), total hemolymph count (THC), differential hemolymph count (DHC), and hemolymph protein concentration (HPC) differed significantly among the experimental treatments with a significant superiority of date syrup (diet 3) over the others. It can be concluded that the date syrup was more suitable for honey bee colonies which was more favorable than traditional pollen substitute and improved physiological status of honey bee individuals during pollen scarcity periods. So under Upper Egypt conditions, pollen substitute feeding especially date syrup during the winter-early spring period under pollen scarcity helped honey bee colonies to be developed in the early spring seasons.
Keywords: Apis mellifera L; Hemolymph; Honey bee; Pollen substitutes; Winter feeding

The effect of pollen monodiets on fat body morphology parameters and energy substrate levels in the fat body and hemolymph of Apis mellifera L. workers - Bryś, Maciej Sylwester; Staniec, Bernard; Strachecka, Aneta (Scientific Reports, 2024)
Human activities associated with large-scale farms and the monocultures expose honey bees to one type of food. Moreover, there is an ongoing decline of plant species producing pollen and nectar in Europe. A poorly balanced diet affects a number of processes occurring in a bee’s body. The fat body and hemolymph are the tissues that participate in all of them. Therefore, the aim of our study was to determine the effect of hazel, pine, rapeseed, buckwheat, phacelia and goldenrod pollen on the morphological parameters of fat body trophocytes, the diameters of cell nuclei in oenocytes and the concentrations of compounds involved in energy metabolism (glucose, glycogen, triglycerides and protein). In the cage tests, the bees were fed from the first day of life with sugar candy (control group) or candy with a 10% addition of one of the 6 pollen types. Hemolymph and fat body from various locations were collected from 1-, 7- and 14-day-old workers. Pollen produced by plant species such as hazel and pine increased glucose concentrations in the bee tissues, especially in the hemolymph. It can therefore be concluded that they are valuable sources of energy (in the form of simple carbohydrates) which are quickly used by bees. Pollen from plants blooming in the summer and autumn increased the concentrations of proteins, glycogen and triglycerides in the fat body, especially that from the third tergite. The accumulation of these compounds was associated with an increased the length and width of trophocytes as well as with enhanced metabolic activity, which was evidenced in the increasing diameter of oenocyte cell nuclei. It seems a balanced multi-pollen diet is more valuable for bees, but it is important to understand the effects of the particular pollen types in the context of a mono-diet. In the future, this will make it possible to produce mixtures that can ensure homeostasis in the apian body.
Keywords: Biochemical pathway; Biomarkers; Cell metabolism; Diets; Honeybee; Nutrition

Effect of amino acid enriched diets on hemolymph amino acid composition in honey bees - Tafi, Elena; Sagona, Simona; Meucci, Valentina; Bortolotti, Laura; Galloni, Marta; Bogo, Gherardo; Gatta, Domenico; Casini, Lucia; Barberis, Marta; Nepi, Massimo; Felicioli, Antonio (Archives of Insect Biochemistry and Physiology, 2024)
Amino acids (AAs) are an abundant class of nectar solutes, and they are involved in the nectar attractiveness to flower visitors. Among the various AAs, proline is the most abundant proteogenic AA, and γ-amino butyric acid (GABA) and β-alanine are the two most abundant non-proteogenic AAs. These three AAs are known to affect insect physiology, being involved in flight metabolism and neurotransmission. The aim of this study was to investigate the effects of artificial diets enriched with either β-alanine, GABA, or proline on consumption, survival, and hemolymph composition in honey bees belonging to two different ages and with different metabolism (i.e., newly emerged and foragers). Differences in feed intake among diets were not observed, while a diet enriched with β-alanine improved the survival rate of newly emerged honey bees compared to the control group. Variations in the hemolymph AA concentrations occurred only in newly emerged honey bees, according to the diet and the time of hemolymph sampling. A greater susceptibility of young honey bees to enriched diets than older honey bees was observed. The variations in the concentrations of hemolymph AAs reflect either the accumulation of dietary AAs or the existence of metabolic pathways that may lead to the conversion of dietary AAs into different ones. This investigation could be an initial contribution to studying the complex dynamics that regulate hemolymph AA composition and its effect on honey bee physiology.
Keywords: Apis mellifera; GABA; artificial diets; feed intake; proline; β-alanine

Anthropogenic influence on seasonal and spatial variation in bioelements and non-essential elements in honeybees and their hemolymph - Ilijević, Konstantin; Vujanović, Dragana; Orčić, Snežana; Purać, Jelena; Kojić, Danijela; Zarić, Nenad; Gržetić, Ivan; Blagojević, Duško P.; Čelić, Tatjana V. (Comparative Biochemistry and Physiology Part - C: Toxicology and Pharmacology, 2021)
Honeybee colony losses have been a focus of research in the last years, due to the importance of managed honeybee colonies for economy and ecology. Different unfavorable conditions from the outside environment have a strong impact on the hive health. The majority of losses occur mainly during winter and the exact reason is not completely understood. Only a small number of studies are dealing with content of bioelements, their function and influence on honeybee physiology. The aim of the present study was to determine seasonal and spatial variations in content of bioelements and non-essential elements, in hemolymph and whole body of honeybees originating from three regions with different degrees of urbanization and industrialization. Concentrations of 16 elements were compared: macroelements (Ca, K, Mg, Na), microelements (Cu, Fe, Mn, Zn) and non-essential elements (Al, Ba, Cd, Co, Cr, Ni, Pb, Sr) in samples collected from 3 different environments: Golija (rural region), Belgrade (urban region) and Zajača (industrial region). Content of bioelements and non-essential elements in honeybees was under noticeable influence of the surrounding environment, season and degree of honeybee activity. Hemolymph was proven to be helpful in differentiating air pollution from other sources of honeybee exposure. The results of our study demonstrated that bees can be successfully used as biomonitors since we have observed statistically significant differences among observed locations, but unless compared locations are exposed to excessively different pollution pressures, it is essential that all bees should be collected at the same season.
Keywords: Apis mellifera; Environmental pollution; Hemolymph; ICP-OES; Metals

Metabolomic analysis of honey bees (Apis mellifera) response to carbendazim based on UPLC-MS - Chen, Heng; Wang, Kang; Ji, Wenna; Xu, Hao; Liu, Yibing; Wang, Shuang; Wang, Zhi; Gao, Fuchao; Lin, Zheguang; Ji, Ting (Pesticide Biochemistry and Physiology, 2021)
Pesticides are one of the main causes of colony losses globally, posing a huge threat to the beekeeping industry. The fungicide carbendazim is commonly used on many crops worldwide, but the effects of fungicides on honey bees have received less attention than those of insecticides. Previous studies have shown that sublethal doses of carbendazim hinder growth and development and may destabilize and impede the development of honey bee colonies. The metabolome closely reflects brain activity at the functional level, allowing the effects of compounds such as fungicides to be investigated. Here, we established a model of carbendazim-treated honey bees, Apis mellifera, and used metabolomic approaches to better understand the effect of carbendazim on bee metabolic profiles. The results showed that 112 metabolites were significantly affected in carbendazim-treated bees compared to the control. Metabolites associated with energy and amino acid metabolism showed high abundance and were enriched for a wide range of pathways. In addition, the down-regulation of Aflatoxin B1exo-8,9-epoxide-GSH and glycerol diphosphate showed that carbenazim may affect the detoxification and immune system of honey bees. These results provide new insights into the interaction between fungicides and honey bees.
Keywords: Carbendazim; Fungicide; Honey bee; Metabolomics

The bee hemolymph metabolome: A window into the impact of viruses on bumble bees - Wang, Luoluo; Van Meulebroek, Lieven; Vanhaecke, Lynn; Smagghe, Guy; Meeus, Ivan (Viruses, 2021)
State-of-the-art virus detection technology has advanced a lot, yet technology to evaluate the impacts of viruses on bee physiology and health is basically lacking. However, such technology is sorely needed to understand how multi-host viruses can impact the composition of the bee com-munity. Here, we evaluated the potential of hemolymph metabolites as biomarkers to identify the viral infection status in bees. A metabolomics strategy based on ultra-high-performance liquid chro-matography coupled to high-resolution mass spectrometry was implemented. First, we constructed a predictive model for standardized bumble bees, in which non-infected bees were metabolically differentiated from an overt Israeli acute paralysis virus (IAPV) infection (R2 Y = 0.993; Q2 = 0.906), as well as a covert slow bee paralysis virus (SBPV) infection (R2 Y = 0.999; Q2 = 0.875). Second, two sets of potential biomarkers were identified, being descriptors for the metabolomic changes in the bee’s hemolymph following viral infection. Third, the biomarker sets were evaluated in a new dataset only containing wild bees and successfully discriminated virus infection versus non-virus infection with an AUC of 0.985. We concluded that screening hemolymph metabolite markers can underpin physiological changes linked to virus infection dynamics, opening promising avenues to identify, monitor, and predict the effects of virus infection in a bee community within a specific environment.
Keywords: Biomarker; Bom-bus terrestris; Israeli acute paralysis virus; Metabolomics; Slow bee paralysis virus

Honey Bee Vitellogenin and Zn2+-Binding 1 Where Honey Bee Vitellogenin may Bind Zn 2+-Ions - Leipart, Vilde; Enger, Øyvind; Turcu, Diana Cornelia; Dobrovolska, Olena; Drabløs, Finn; Halskau, Øyvind; Amdam, Gro V
The protein Vitellogenin (Vg) plays a central role in lipid transportation in most egg-laying animals. High Vg levels correlate with stress resistance and lifespan potential in honey bees (Apis mellifera). Vg is the primary circulating zinc-carrying protein in honey bees. Zinc is an essential metal ion in numerous biological processes, including the function and structure of many proteins. Measurements of Zn 2+ suggest a variable number of ions per Vg molecule in different animal species, but the molecular implications of zinc-binding by this protein are not well understood. We used inductively coupled plasma mass spectrometry (ICP-MS) to determine that, on average, each honey bee Vg molecule binds 3 Zn 2+-ions. Our full-length protein structure and sequence analysis revealed seven potential zinc-binding sites. These are. CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted January 28, 2022. ; https://doi.org/10.1101/2022.01.28.478200 doi: bioRxiv preprint Honey Bee Vitellogenin and Zn2+-Binding 2 located in the β-barrel and α-helical subdomains of the N-terminal domain, the lipid binding site, and the cysteine-rich C-terminal region of unknown function. Interestingly, two potential zinc-binding sites in the β-barrel can support a proposed role for this structure in DNA-binding. Overall, our findings illustrate the capacity of honey bee Vg to bind zinc at several functional regions, indicating that Zn 2+-ions are important for many of the activities of this protein. In addition to being potentially relevant for other egg-laying species, these insights provide a platform for studies of metal ions in bee health, which is of global interest due to recent declines in pollinator numbers.
Keywords: Honey bees; insect immunity; protein structure analysis; vitellogenin; zinc-binding

Unraveling the Bombus terrestris Hemolymph, an Indicator of the Immune Response to Microbial Infections, through Complementary Mass Spectrometry Approaches - Bournonville, Lorène; Askri, Dalel; Arafah, Karim; Voisin, Sébastien N.; Bocquet, Michel; Bulet, Philippe (International Journal of Molecular Sciences, 2023)
Pollinators, including Bombus terrestris, are crucial for maintaining biodiversity in ecosystems and for agriculture. Deciphering their immune response under stress conditions is a key issue for protecting these populations. To assess this metric, we analyzed the B. terrestris hemolymph as an indicator of their immune status. Hemolymph analysis was carried out using mass spectrometry, MALDI molecular mass fingerprinting was used for its effectiveness in assessing the immune status, and high-resolution mass spectrometry was used to measure the impact of experimental bacterial infections on the “hemoproteome”. By infecting with three different types of bacteria, we observed that B. terrestris reacts in a specific way to bacterial attacks. Indeed, bacteria impact survival and stimulate an immune response in infected individuals, visible through changes in the molecular composition of their hemolymph. The characterization and label-free quantification of proteins involved in specific signaling pathways in bumble bees by bottom-up proteomics revealed differences in protein expression between the non-experimentally infected and the infected bees. Our results highlight the alteration of pathways involved in immune and defense reactions, stress, and energetic metabolism. Lastly, we developed molecular signatures reflecting the health status of B. terrestris to pave the way for diagnosis/prognosis tools in response to environmental stress.
Keywords: Bombus terrestris; bee health; bumble bee; immune response; molecular mass fingerprints; pathogens; proteomics

Resolving the zinc binding capacity of honey bee vitellogenin and locating its putative binding sites - Leipart, Vilde; Enger, Øyvind; Turcu, Diana Cornelia; Dobrovolska, Olena; Drabløs, Finn; Halskau, Øyvind; Amdam, Gro V. (Insect Molecular Biology, 2022)
The protein vitellogenin (Vg) plays a central role in lipid transportation in most egg-laying animals. High Vg levels correlate with stress resistance and lifespan potential in honey bees (Apis mellifera). Vg is the primary circulating zinc-carrying protein in honey bees. Zinc is an essential metal ion in numerous biological processes, including the function and structure of many proteins. Measurements of Zn2+ suggest a variable number of ions per Vg molecule in different animal species, but the molecular implications of zinc-binding by this protein are not well-understood. We used inductively coupled plasma mass spectrometry to determine that, on average, each honey bee Vg molecule binds 3 Zn2+-ions. Our full-length protein structure and sequence analysis revealed seven potential zinc-binding sites. These are located in the β-barrel and α-helical subdomains of the N-terminal domain, the lipid binding site, and the cysteine-rich C-terminal region of unknown function. Interestingly, two potential zinc-binding sites in the β-barrel can support a proposed role for this structure in DNA-binding. Overall, our findings suggest that honey bee Vg bind zinc at several functional regions, indicating that Zn2+-ions are important for many of the activities of this protein. In addition to being potentially relevant for other egg-laying species, these insights provide a platform for studies of metal ions in bee health, which is of global interest due to recent declines in pollinator numbers.
Keywords: honey bees; insect immunity; protein structure analysis; vitellogenin; zinc-binding

Physiological and immunological status of adult honeybees (Apis mellifera) fed sugar syrup supplemented with pentadecapeptide bpc 157 - Gajger, Ivana Tlak; Smodiš Šker, Maja Ivana; Šoštaric, Petra; Šuran, Jelena; Sikiric, Predrag; Vlainic, Josipa (Biology, 2021)
Various factors contribute to a decline in diversity and number of bees. Here, an integrated approach in experimental BPC 157 therapy was implemented, combining laboratory-controlled and field study results. The aim of a study was to assess the effects of BPC 157 additional feeding of newly emerged worker honeybees on few biochemical and immunological parameters in hemolymph (glucose, trehalose, lipids, proteins, vitellogenin, glucose-oxidase (GOX)), and hypopharyngeal gland (HPG), in laboratory-controlled conditions. Additionally, to examine the physiological status of protein digestion, the enzymatic activity of leucine aminopeptidase (LAP) in the mid-guts of worker honeybees was analyzed. It was found that individual honeybees, in hoarding cages, following BPC 157 administration through carbohydrate food, showed positive physiological changes when compared to the control groups. Those results were complemented by strong and visible LAP activity, particularly noticeable in the apical parts of the epithelial cells in the mid-guts of young worker honeybees originated from treated hives, suggesting a link between alternative oral therapy with BPC 157 and honeybees’ immunity.
Keywords: Apis mellifera; Hemolymph; Honeybee colonies; Laboratory-controlled conditions; Pentadecapeptide BPC 157; Physiology and immunology parameters

From consumption to excretion: Lithium concentrations in honey bees (Apis mellifera) after lithium chloride application and time-dependent effects on Varroa destructor - Rein, Carolin; Grünke, Markus; Traynor, Kirsten; Rosenkranz, Peter (Pest Management Science, 2024)
BACKGROUND: Owing to its systemic mode-of-action and ease of application, lithium chloride (LiCl) is an ideal varroacide for the control of Varroa destructor infestations in honey bee colonies. To better understand how LiCl functions within a colony, we screened different parts of honey bee anatomy for lithium accumulation. We wanted to elucidate the time-dependent effects of LiCl on V. destructor and its metabolism within honey bees when they were fed continuous LiCl treatments, as well as evaluate potential adverse effects such as accumulation in the hypopharyngeal glands of nurse bees, which could negatively impact queens and larvae. RESULTS: Cage experiments reveal rapid acaricidal onset, with >95% mite mortality within 48 h of treatment. Bee hemolymph analysis supports these observations, showing a rapid increase in lithium concentration within 12 h of treatment, followed by stabilization at a constant level. Lithium accumulates in the rectum of caged bees (≤475.5 mg kg−1 after 7 days of feeding 50 mm LiCl), reflecting the bees' metabolic and excretion process. Despite concerns about potential accumulation in hypopharyngeal glands, low lithium levels of only 0.52 mg kg−1 suggest minimal risk to the queen and 1st- and 2nd-instar larvae. Cessation of LiCl treatment results in a rapid decline in mite mortality in the first 5 days, which increases again thereafter, resulting in mite mortality of 77–90% after 10 days. CONCLUSION: These findings help optimize LiCl application in colonies to achieve high Varroa mortality without unwanted adverse effects and provide important baseline data for future registration. © 2024 The Author(s). Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: Varroa destructor; hemolymph; hypopharyngeal gland; lithium chloride; metabolism

Effects of Varroa destructor on Hemolymph Sugars and Secondary Infections in Honeybees (Apis mellifera) - Cournoyer, Antoine; Plamondon, Laurence; Bau-Gaudreault, Liza; Deschamps, Annie; Dubreuil, Pascal; Benoit-Biancamano, Marie Odile (Applied Sciences (Switzerland), 2022)
Featured Application: Featured Application: Diagnostic techniques have been adapted to better understand the health status of honeybees exposed to Varroa destructor over time. These techniques and the results presented herein could help beekeepers to prevent winter losses and to better manage the beehives exposed to life-threatening diseases. The concept of comparative medicine, which has a great importance in veterinary medicine, is put forward in this project. The European honeybee contributes to the agriculture by its pollination; however, the overwintering loss rate over the last decades is worrisome. Varroa destructor is considered one of the most important causes of bee colony declines. This project aims to correlate the infestation by varroa to the hemolymph sugar concentrations and bacterial and viral coinfections. Six highly infested and six control hives were compared over time. Pooled hemolymph samples from honeybees were collected for sugar concentration measurements using a previously validated portable glucometer. The hemolymph samples were submitted for bacteriology. Multiplex RT-PCR analysis was performed on honeybees for six viruses: DWV-A, DWV-B, BQCV, ABPV, KBV, and IAPV. There was also no predominance of pathogenic bacteria. In September, sugar concentrations in hemolymph were significantly lower in highly infested hives than in control hives. Infested hives showed markedly higher viral loads except for ABPV. DWV-A and BQCV viral loads from highly infested hives were significantly higher in September compared to July. A continued and severe exposure to varroa leads to increased viral charges and decreased sugar concentrations, suggesting alterations in immunity, metabolism, and reserve mobilization. These parameters contribute to the weakening and mortality of the colonies.
Keywords: ABPV; BQCV; DWV; IAPV; KBV; disease; hemolymph; honeybee; pathogen; sugar

Analytical validation of a portable human Accu-Chek glucometer in honeybee hemolymph - Cournoyer, Antoine; Deschamps, Annie; Bau-Gaudreault, Liza; Dubreuil, Pascal; Benoit-Biancamano, Marie Odile (Journal of Veterinary Diagnostic Investigation, 2022)
Glucose and trehalose are the main energy sources used by honeybees (Apis mellifera) for daily activities. However, there is no validated point-of-care method to reliably measure both sugars. We performed an analytical validation of a portable human glucometer (Accu-Chek; Roche) for glucose measurement in honeybee hemolymph compared to a reference method (GluCH, UniCel DxC 600; Beckman Coulter). We used 30 pooled hemolymph samples collected from the antennae of anesthetized honeybees and diluted 1:4 in 0.9% saline. We evaluated dilution linearity, spike recovery, and inter- and intra-assay imprecision. Glucose concentration was measured over time (2 h, 4 h, 8 h, 12 h, 1 d, 2 d, 3 d, 7 d, 21 d, 28 d) at various storage temperature (25°C, 4°C, −20°C, −80°C). The trehalose concentration was measured indirectly by trehalase hydrolyzation. Glucose concentrations measured by both instruments had a strong correlation (0.985, p < 0.0001) and a bias of −7.33 mmol/L (±1.96SD: 13.70 to −28.36), with linear agreement at <20 mmol/L (physiologic value: 100 mmol/L). The accuracy of the glucometer decreased at >20 mmol/L. Recovery of 115–130% of diluted spikes indicated good specificity. Inter- and intra-assay imprecision were 2.50% and 2.21%, respectively. Glucose concentrations fluctuated in stored samples dependent on time and temperature; however, glucose concentrations were constant with storage at −80°C for ≥28 d. The Accu-Chek glucometer is an adequate instrument to measure honeybee glucose concentration in hemolymph diluted with 0.9% NaCl, with good accuracy and precision at <20 mmol/L. Hemolymph storage at −80°C is suitable for long-term conservation of glucose.
Keywords: Apis mellifera; glucometer; glucose; hemolymph; honeybees; trehalase; trehalose

Conversión de proteína de los suplementos en proteína de la hemolinfa y los cuerpos grasos en abejas obreras de la miel (Apis mellifera L) - Barragán, Sergio; Basualdo, Marina; Rodríguez, Edgardo M. (Journal of Apicultural Research, 2015)
Adequate supplementation or replacement of pollen is necessary for maintaining healthy honey bee colonies during periods with limited pollen. Different supplemental protein diets could be metabolized in different ways by bees. We compared how protein supplements elaborated with free amino acids, with a soy-based diet, and with pollen, influence protein stores within individual honey bees. Caged bees were fed with one of three diets, and measurements were made based on protein content of hemolymph and fat bodies. The results show that these diets were metabolized in different way by bees. Bees fed with the free amino acid diet had significantly more proteins in hemolymph than bees fed with soya patty and pollen as they aged. The major amount of protein transported into the hemolymph by 27-day-old bees fed with free amino acid diet promoted the development of wax glands, and probably, it was the cause of a reduced storage of protein in fat bodies. Overall, our results suggest a connection between diets and physiological condition of honey bees.
Keywords: fat body; hemolymph; honey bees; nutrition; protein; supplements

Glyphosate induces immune dysregulation in honey bees - Motta, Erick V.S.; Powell, J. Elijah; Moran, Nancy A. (Animal Microbiome, 2022)
Background: Similar to many other animals, the honey bee Apis mellifera relies on a beneficial gut microbiota for regulation of immune homeostasis. Honey bees exposed to agrochemicals, such as the herbicide glyphosate or antibiotics, usually exhibit dysbiosis and increased susceptibility to bacterial infection. Considering the relevance of the microbiota–immunity axis for host health, we hypothesized that glyphosate exposure could potentially affect other components of the honey bee physiology, such as the immune system. Results: In this study, we investigated whether glyphosate, besides affecting the gut microbiota, could compromise two components of honey bee innate immunity: the expression of genes encoding antimicrobial peptides (humoral immunity) and the melanization pathway (cellular immunity). We also compared the effects of glyphosate on the bee immune system with those of tylosin, an antibiotic commonly used in beekeeping. We found that both glyphosate and tylosin decreased the expression of some antimicrobial peptides, such as apidaecin, defensin and hymenoptaecin, in exposed honey bees, but only glyphosate was able to inhibit melanization in the bee hemolymph. Conclusions: Exposure of honey bees to glyphosate or tylosin can reduce the abundance of beneficial gut bacteria and lead to immune dysregulation.
Keywords: Cellular immunity; Glyphosate; Honey bees; Humoral immunity; Microbiome; Tylosin

Immunity and physiological changes in adult honey bees (Apis mellifera) infected with Nosema ceranae: The natural colony environment - Lourenço, Anete P.; Guidugli-Lazzarini, Karina R.; de Freitas, Nayara H.A.; Message, Dejair; Bitondi, Márcia M.G.; Simões, Zilá L.P.; Teixeira, Érica W. (Journal of Insect Physiology, 2021)
Nosema ceranae is a microsporidium that infects Apis mellifera, causing diverse physiological and behavioral alterations. Given the existence of individual and social mechanisms to reduce infection and fungal spread in the colony, bees may respond differently to infection depending on their rearing conditions. In this study, we investigated the effect of N. ceranae in honey bee foragers naturally infected with different fungal loads in a tropical region. In addition, we explored the effects of N. ceranae artificially infected young bees placed in a healthy colony under field conditions. Honey bees naturally infected with higher loads of N. ceranae showed downregulation of genes from Toll and IMD immune pathways and antimicrobial peptide (AMP) genes, but hemolymph total protein amount and Vitellogenin (Vg) titers were not affected. Artificially infected bees spread N. ceranae to the controls in the colony, but fungal loads were generally lower than those observed in cages, probably because of social immunity. Although no significant changes in mRNA levels of AMP-encoding were observed, N. ceranae artificially infected bees showed downregulation of miR-989 (an immune-related microRNA), lower vitellogenin gene expression, and decreased hemolymph Vg titers. Our results demonstrate for the first time that natural infection by N. ceranae suppresses the immune system of honey bee foragers in the field. This parasite is detrimental to the immune system of young and old bees, and disease spread, mitigation and containment will depend on the colony environment.
Keywords: Antimicrobial peptides; IMD; Infection intensity; Toll; Vitellogenin; miRNA

Propolis extract and chitosan improve health of nosema ceranae infected giant honey bees, apis dorsata fabricius, 1793 - Naree, Sanchai; Ponkit, Rujira; Chotiaroonrat, Evada; Mayack, Christopher L.; Suwannapong, Guntima (Pathogens, 2021)
Nosema ceranae is a large contributing factor to the most recent decline in honey bee health worldwide. Developing new alternative treatments against N. ceranae is particularly pressing because there are few treatment options available and therefore the risk of increased antibiotic resistance is quite high. Recently, natural products have demonstrated to be a promising avenue for finding new effective treatments against N. ceranae. We evaluated the effects of propolis extract of stingless bee, Tetrigona apicalis and chito-oligosaccharide (COS) on giant honey bees, Apis dorsata, experimentally infected with N. ceranae to determine if these treatments could improve the health of the infected individuals. Newly emerged Nosema-free bees were individually inoculated with 106N. ceranae spores per bee. We fed infected and control bees the following treatments consisting of 0%, 50%, propolis extracts, 0 ppm and 0.5 ppm COS in honey solution (w/v). Propolis extracts and COS caused a significant increase in trehalose levels in hemolymph, protein contents, survival rates and acini diameters of the hypopharyngeal glands in infected bees. Our results suggest that propolis and COS could improve the health of infected bees. Further research is needed to determine the underlying mechanisms responsible for the improved health of the infected bees.
Keywords: Apis dorsata; Chito-oligosaccharide; Nosema ceranae; Propolis

A novel method for the detection and diagnosis of virus infections in honey bees - Huang, Shaokang; Li, Jianghong; Zhang, Yi; Li, Zhiguo; Evans, Jay D.; Rose, Robyn; Gilligan, Todd M.; LeBrun, Anne; He, Nan; Zheng, Teng; Zhang, Tiyin; Hamilton, Michele; et al. (Journal of Virological Methods, 2021)
In terms of infectious diseases caused by a variety of microorganisms, the ability to promptly and accurately identify the causative agents is the first step on the path to all types of effective management of such infections. Among the various factors that are affecting global bee health, viruses have often been linked to honey bee colony losses and they pose a serious threat to the fraction of agriculture that depends on the service of pollinators. Over the past few decades, PCR-based molecular methods have provided powerful tools for rapid, specific, and sensitive detection and the quantification of difficult-to-grow pathogenic microorganisms such as viruses in honey bees. However, PCR-based methods require nucleic acid extraction and purification, which can be quite laborious and time-consuming and they involve the use of organic solvents and chaotropic agents like phenol and chloroform which are volatile and highly toxic. In response, we developed a novel and non-sacrificial method for detecting viral infections in honey bees. As little as 1 μl of hemolymph was collected from adult workers, larvae, and queens of bee colonies by puncturing the soft inter-tergal integument between the second and third dorsal tergum with a fine glass capillary. The hemolymph was then diluted and subjected to RT-PCR analysis directly. The puncture wound caused by the glass capillary was found to heal automatically and rapidly without any trouble and the lifespan of the experimental workers remained unaffected. Using this method, we detected multiple viruses including Deformed wing virus (DWV), Black queen cell virus (BQCV), and Sacbrood virus (SBV) in infected bees. Furthermore, expressed transcripts that indicate the induction of innate immune response to the virus infections were also detected in the hemolymph of infected bees. The simplicity and cost-effectiveness of this innovative approach will allow it to be a valuable, time-saving, safer, and more environmentally friendly contribution to bee disease management programs.
Keywords: Detection; Diagnosis; Hemolymph; Honey bee; Immune peptides; Lifespan; Viruses

Ecosystem Services of Honey Bees; Regulating, Provisioning and Cultural Functions - Aryal, Sunil; Ghosh, Sampat; Jung, Chuleui (Journal of Apiculture, 2020)
Ecosystem services are often undervalued, largely because it remains outside of the market econo my, we do not require monetary paying for these services. However, without this ecosystem service, not only human but also the ecology and environment in totality will be imbalanced. In this paper, we attempt to understand the roles of honey bee in the context of human well-being. We represent services of honey bee on the basis of functionality i.e. regulating, provisioning and cultural functions. The paper strongly advocates that human must fully appreciate ecosystem service, otherwise it may threaten human livelihood.

The Honey Bee Apis mellifera: An Insect at the Interface between Human and Ecosystem Health - Papa, Giulia; Maier, Roberto; Durazzo, Alessandra; Lucarini, Massimo; Karabagias, Ioannis K.; Plutino, Manuela; Bianchetto, Elisa; Aromolo, Rita; Pignatti, Giuseppe; Ambrogio, Andrea; Pellecchia, Marco; Negri, Ilaria (Biology, 2022)
The concept of ecosystem services is widely understood as the services and benefits thatecosystems provide to humans, and they have been categorised into provisioning, regulating, supporting, and cultural services. This article aims to provide an updated overview of the benefits that the honey bee Apis mellifera provides to humans as well as ecosystems. We revised the role of honey bees as pollinators in natural ecosystems to preserve and restore the local biodiversity of wild plants; in agro-ecosystems, this species is widely used to enhance crop yield and quality, meeting the increasing food demand. Beekeeping activity provides humans not only with high-quality food but also with substances used as raw materials and in pharmaceuticals, and in polluted areas, bees convey valuable information on the environmental presence of pollutants and their impact on human and ecosystem health. Finally, the role of the honey bee in symbolic tradition, mysticism, and the cultural values of the bee habitats are also presented. Overall, we suggest that the symbolic value of the honey bee is the most important role played by this insect species, as it may help revitalise and strengthen the intimate and reciprocal relationship between humans and the natural world, avoiding the inaccuracy of considering the ecosystems as mere providers of services to humans.
Keywords: Agro-ecosystems; Apis mellifera; Bee products; Biodiversity; Cultural services; Ecosystem services; Honey bee; Provisioning services; Regulating services

A geographic approach for determining honey bee conservation areas for sustainable ecosystem services - Sari, Fatih; Kandemir, Irfan (Arabian Journal of Geosciences, 2022)
In recent years, ecosystems have been threatened by human-related factors to meet the growing demand for food. Natural areas are rapidly degraded by urbanization and being converted to human-dominated land use. Since honey bees have a key role in ecosystems due to their pollination role in both agricultural crops and natural plants, the dynamics of ecosystems and beekeeping activities are strongly affected by this conversion. Recent research has revealed that the decline of plant and pollinator species has been mentioned as a global threat that is closely related to ecosystem conversion and land use change. Thus, honey bee decline is being frequently mentioned within the context of bee conservation and sustaining ecosystem services to ensure productivity. In this study, a geographical approach has been introduced to decide on honey bee conservation areas, as honey bees are being threatened by land use change, pesticides, and natural disasters. All the reasons causing honey bee decline and even colony loss have been spatially integrated, and susceptible areas which are highly prone to natural hazards and pesticide usage have been determined. The results revealed that 164,650 km2 are being threatened by the conversion of natural areas into fruit orchards due to the citrus production demand and that approximately 5000 km2 of natural areas have been transformed into agricultural lands. Mersin, Adana, and Hatay provinces were specified as highly prone to bee decline, and the bee conservation requirement was mostly revealed in these provinces. Our results show that a 22,567.45 km2 area must be specified as bee conservation areas to minimize the bee decline in Turkey.

DEGRADATION OF HONEY BEES AND ENVIRONMENTAL POLLUTION : A REVIEW - Shaher, Kameela Ward; Manjy, Mohammed Shakir (2020)
Environmental pollution is the inappropriate transformation of all or most of our ocean as a result of human and natural activities through its direct and indirect effects of changes in energy methods, radiation levels, physical and chemical composition, abundance of organisms, and the degradation of honey bees as a result of environmental pollutants from pesticides which are of particular importance in the agricultural field. The need to increase the amount of food to the need to increase the size and equipment of agricultural production and the presence of large fields for one crop increased the problems of pests, requiring more pesticide treatments that led to the disappearance of many solitary bees and pollinators Therefore, the importance of bees as a pollinator for flowers because of the possibility of increasing numbers easily and transported to farms, bees come into contact with pesticides during his visit. Since air, water and soil contain heavy metals as a result of various industries and produced by car exhaust and burning garbage and others, as well as radiation emitted by electric power towers and mobile phone towers, some of which carry electric charges affect bees and the behavior of bees and affect the navigational capacity of bees. He used bees and their products as an indicator of environmental pollution with heavy elements, pesticides, radiation and antibiotics because of its behavioral and synthetic characteristics that enable it to deal with all components of the environment and when returned be loaded with these pollutants, which have an impact on the immune system as a result of residues in bee products, including honey and the deterioration of honey bees It is a serious environmental phenomenon that leads to losses in the production of many strategic crops as well as large losses in the number of honey bee hives.
Keywords: Apis mellifera L; Environmental pollution; Honey bees

The impact of habitat loss on pollination services for a threatened dune endemic plant - Mendes, Sara Beatriz; Timóteo, Sérgio; Loureiro, João; Castro, Sílvia (Oecologia, 2022)
Habitat loss is currently a major threat to biodiversity, affecting species interactions, such as plant–pollinator interactions. This is particularly important in self-incompatible plants relying on pollinators to reproduce and sustain their populations. Here, we evaluated how habitat loss affects the pollination system, plant individual–pollinator species interaction network, and plant reproductive fitness of the self-incompatible Jasione maritima var. sabularia, a threatened taxon from dune systems. This plant is a pollinator generalist, visited by 108 species from distinct taxonomic groups. Results suggest that increasing habitat loss led to a significant decline in pollinator richness, increased pollen limitation, and a decrease in reproductive fitness of J. maritima var. sabularia. Visitation rate per individual did not significantly change with available area, indicating that the quality of pollen differed across populations. The topology of the network between J. maritima var. sabularia individuals and its pollinator species did not change, which may be attributed to the stability in the core of pollinator species. This suggests that the lower fitness of plants with increasing habitat degradation may be explained not only by the lower richness of peripheral pollinators but also by the genetic structure of the plant populations, as there is a possible higher transference of less quality pollen by pollinators, ultimately compromising the persistence of plant populations. Our study highlights the need of future studies to integrate the fine details provided by individual-level networks, which will increase our understanding of the pattern of species interactions and its consequences for the fitness of threatened plant populations.
Keywords: Individual-based networks; Pollen limitation; Reproductive fitness; Self-incompatible plant; Threatened species

Pollinators of the Great Plains: Disturbances, Stressors, Management, and Research Needs - Hanberry, Brice B.; DeBano, Sandra J.; Kaye, Thomas N.; Rowland, Mary M.; Hartway, Cynthia R.; Shorrock, Donna (Rangeland Ecology and Management, 2021)
Recent global declines of pollinator populations have highlighted the importance of pollinators, which are undervalued despite essential contributions to ecosystem services. To identify critical knowledge gaps about pollinators, we describe the state of knowledge about responses of pollinators and their foraging and nesting resources to historical natural disturbances and new stressors in Great Plains grasslands and riparian ecosystems. In addition, we also provide information about pollinator management and research needs to guide efforts to sustain pollinators and by extension, flowering vegetation, and other ecosystem services of grasslands. Although pollinator responses varied, pollinator specialists of disturbance-sensitive plants tended to decline in response to disturbance. Management with grazing and fire overall may benefit pollinators of grasslands, depending on many factors; however, we recommend habitat and population monitoring to assess outcomes of these disturbances on small, isolated pollinator populations. The influences and interactions of drought and increasingly variable weather patterns, pesticides, and domesticated bees on pollinators are complex and understudied. Nonetheless, habitat management and restoration can reduce effects of stressors and augment floral and nesting resources for pollinators. Research needs include expanding information about 1) the distribution, abundance, trends, and intraregional variability of most pollinator species; 2) floral and nesting resources critical to support pollinators; 3) implications of different rangeland management approaches; 4) effects of missing and reestablished resources in altered and restored vegetation; and 5) disentangling the relative influence of interacting disturbances and stressors on pollinator declines. Despite limited research in the Great Plains on many of these topics, consideration of pollinator populations and their habitat needs in management plans is critical now to reduce future pollinator declines and promote recovery.
Keywords: Great Plains; climate; fire; grazing; herbivory; pesticides; pollinators

Forest and connectivity loss simplify tropical pollination networks - Ferreira, Patrícia Alves; Boscolo, Danilo; Lopes, Luciano Elsinor; Carvalheiro, Luísa G.; Biesmeijer, Jacobus C.; da Rocha, Pedro Luís Bernardo; Viana, Blandina Felipe (Oecologia, 2020)
Mutualistic interactions between plants and pollinators play an essential role in the organization and persistence of biodiversity. The structure of interaction networks mediates the resilience of local communities and ecosystem functioning to environmental changes. Hence, network structure conservation may be more critical for maintaining biodiversity and ecological services than the preservation of isolated species in changing landscapes. Here, we intensively surveyed seven 36 km2 landscapes to empirically investigate the effects of forest loss and landscape configuration on the structure of plant–pollinator networks in understory vegetation of Brazilian Atlantic Forest. Our results indicate that forest loss and isolation affect the structure of the plant–pollinator networks, which were smaller in deforested landscapes, and less specialized as patch isolation increased. Lower nestedness and degree of specialization (Hʹ2) indicated that the remaining plant and bee species tend to be generalists, and many of the expected specialized interactions in the network were already lost. Because generalist species generate a cohesive interaction core in these networks, these simplified networks might be resistant to loss of peripheral species, but may be susceptible to the extinction of the most generalist species. We suggest that such a network pattern is an outcome of landscapes with a few remaining isolated patches of natural habitat. Our results add a new perspective to studies of plant–pollinator networks in fragmented landscapes, showing that those interaction networks might also be used to indicate how changes in natural habitat affect biodiversity and biotic interactions.
Keywords: Bees; Brazilian Atlantic Forest; Fragmented landscapes; Interaction networks; Mutualistic web

Foraging Behaviour of Apis mellifera scutellata and Hypotrigona gribodoi Bees in Monoculture and Polyculture Vegetable Gardens - Tarakini, Gugulethu; Chemura, Abel; Tarakini, Tawanda; Mashavakure, Nilton; Musundire, Robert (Proceedings of the Zoological Society, 2021)
This study aimed to evaluate the influence of crop type, cropping systems and weather elements on foraging behaviour of pollinators, which is imperative for designing pollinator friendly agricultural systems. Generalised linear models were used to assess foraging time and visitation frequency of the honey bee Apis mellifera scutellata and the stingless bee Hypotrigona gribodoi across monocultures and polyculture systems of butternut, dry bean and mustard at two garden sites in Zvimba district, Zimbabwe. A total of 120 bee visitations across the crops and 103.4 min of foraging bouts were recorded. The honey bee had longer foraging bouts periods in monoculture system, but there were no differences in the stingless bee. Across the two bee species, mustard had the longest foraging bouts, and least in dry beans. Foraging time generally decreased with increasing temperatures, but the decreases in polyculture systems were less severe for the honey bee. Only the honey bee foraging time was shorter in the presence of competitors. We therefore conclude that there are possible negative impacts of projected increases in temperature due to global warming and agricultural intensification on foraging behaviour of important pollinators such as bees.
Keywords: Foraging activities; Monocultures; Pollinators; Polycultures; Temperature

From a free gift of nature to a precarious commodity: Bees, pollination services, and industrial agriculture - Ellis, Rebecca A.; Weis, Tony; Suryanarayanan, Sainath; Beilin, Kata (Journal of Agrarian Change, 2020)
The growing crisis of bee health has shone a spotlight on the problems facing pollinator populations in many parts of the world, the worrying implications for agriculture and ecosystems, and some of the risks of pesticides. Although this attention is important and can open a range of critical vistas, the threats to bees, other pollinators, and the future of pollination are too often framed in narrow ways. The goal of this paper is to provide a systematic way of thinking about the crisis of bee populations by examining the changing dynamics of pollination within industrial agriculture, drawing heavily on transformations in the United States and Canada. We set out a case for understanding pollination as a biophysical barrier to industrial organization and the rise of pollination services as a response that temporarily fixes (or overrides) this barrier, while containing an internal set of contradictions and overrides. We argue that these dialectic relations are continually generating further problems and hope that this lens can help inform critical education, outreach, and movement building with respect to the urgent problems of bee and pollinator health. In particular, we stress the need to connect growing bee-related advocacy with struggles to confront industrial capitalist agriculture.
Keywords: beekeeping; bees; industrial agriculture; political ecology; pollination

How protection of honey bees can help and hinder bee conservation - Iwasaki, Jay M.; Hogendoorn, Katja (Current Opinion in Insect Science, 2021)
Pollinators are globally recognised for their role in ecosystem function and reports of pollinator declines are a source of public and academic concern. However, pollinator decline is often erroneously interpreted as if crop pollination services are under threat, which can lead to misguided efforts to protect introduced and/or widespread crop pollinating species that are not in decline, without addressing the needs of other imperilled species. The honey bee (Apis mellifera L.) in particular has widespread recognition for its role as an integral agricultural pollinator and is the focus of many pollinator campaigns. However, we argue outside of their native range that honey bees are inappropriate as umbrella or flagship species for the conservation of pollinators.

Global trends in the number and diversity of managed pollinator species - Osterman, Julia; Aizen, Marcelo A.; Biesmeijer, Jacobus C.; Bosch, Jordi; Howlett, Brad G.; Inouye, David W.; Jung, Chuleui; Martins, Dino J.; Medel, Rodrigo; Pauw, Anton; Seymour, Colleen L.; Paxton, Robert J. (Agriculture, Ecosystems and Environment, 2021)
Cultivation of pollinator-dependent crops has expanded globally, increasing our reliance on insect pollination. This essential ecosystem service is provided by a wide range of managed and wild pollinators whose abundance and diversity are thought to be in decline, threatening sustainable food production. The Western honey bee (Apis mellifera) is amongst the best-monitored insects but the state of other managed pollinators is less well known. Here, we review the status and trends of all managed pollinators based on publicly accessible databases and the published literature. We found that, on a global scale, the number of managed A. mellifera colonies has increased by 85% since 1961, driven mainly by Asia. This contrasts with high reported colony overwinter mortality, especially in North America (average 26% since 2007) and Europe (average 16% since 2007). Increasing agricultural dependency on pollinators as well as threats associated with managing non-native pollinators have likely spurred interest in the management of alternative species for pollination, including bumble bees, stingless bees, solitary bees, and flies that have higher efficiency in pollinating specific crops. We identify 66 insect species that have been, or are considered to have the potential to be, managed for crop pollination, including seven bumble bee species and subspecies currently commercially produced mainly for the pollination of greenhouse-grown tomatoes and two species that are trap-nested in New Zealand. Other managed pollinators currently in use include eight solitary bee species (mainly for pollination services in orchards or alfalfa fields) and three fly species (mainly used in enclosures and for seed production). Additional species in each taxonomic category are under consideration for pollinator management. Examples include 15 stingless bee species that are able to buzz-pollinate, will fly in enclosures, and some of which have a history of management for honey production; their use for pollination is not yet established. To ensure sustainable, integrated pollination management in agricultural landscapes, the risks, as well as the benefits of novel managed pollinator species must be considered. We, therefore, urge the prioritization of biodiversity-friendly measures maintaining native pollinator species diversity to provide ecosystem resilience to future environmental changes.
Keywords: Apis; Bombus; Crop pollination; Meliponini; Overwinter mortality; Risk

E V O L U T I O N A R Y B I O L O G Y Gene reuse facilitates rapid radiation and independent adaptation to diverse habitats in the Asian honeybee - Ji, Yongkun; Li, Xingan; Ji, Ting; Tang, Junbo; Qiu, Lifei; Hu, Jiahui; Dong, Jiangxing; Luo, Shiqi; Liu, Shanlin; Frandsen, Paul B; Zhou, Xuguo; Parey, Sajad H; et al. (Sci. Adv, 2020)
Animals with recent shared ancestry frequently adapt in parallel to new but similar habitats, a process often underlined by repeated selection of the same genes. Yet, in contrast, few examples have demonstrated the significance of gene reuse in colonization of multiple disparate habitats. By analyzing 343 genomes of the widespread Asian honeybee, Apis cerana, we showed that multiple peripheral subspecies radiated from a central ancestral population and adapted independently to diverse habitats. We found strong evidence of gene reuse in the Leucokinin receptor (Lkr), which was repeatedly selected in almost all peripheral subspecies. Differential expression and RNA interference knockdown revealed the role of Lkr in influencing foraging labor division, suggesting that Lkr facilitates collective tendency for pollen/nectar collection as an adaptation to floral changes. Our results suggest that honeybees may accommodate diverse floral shifts during rapid radiation through fine-tuning individual foraging tendency, a seemingly complex process accomplished by gene reuse.

Significance of apoidea as main pollinators. ecological and economic impact and implications for human nutrition - Hristov, Peter; Neov, Boyko; Shumkova, Rositsa; Palova, Nadezhda (Diversity, 2020)
Wild and managed bees provide pollination services to crops and wild plants, as well as a variety of other services beneficial to humans. Honey bees are the most economically valuable pollinator worldwide. It has been calculated that 9.5% of the total economic value of agricultural production comes from insect pollination, thus amounting to just under USD 200 billion globally. More than 100 important crops depend on pollination by honey bees. The latter pollinate not only a wide number of commercial crops but also many wild plants, some of which are threatened by extinction and constitute a valuable genetic resource. Moreover, as pollinators, honey bees play a significant role in every aspect of the ecosystem by facilitating the growth of trees, flowers, and other plants that serve as food and shelter for many large and small creatures. In this paper, we describe how the reduction in honey bee populations affects various economic sectors, as well as human health.
Keywords: Apis mellifera; Honey bee products; Human nutrition; Medicinal impact

The economic value of the ecosystem services of beekeeping in the czech republic - Vrabcová, Pavla; Hájek, Miroslav (Sustainability (Switzerland), 2020)
Beekeeping is an important part of the bioeconomy. Throughout its existence, it has been one of the fields of human endeavour that contributes to sustainability. It has significant benefits for society, both economically and environmentally. Most (90%) of honeybees’ benefit to humankind lies in their pollination capacity, and only 10% lies in bee products (honey, propolis, wax, etc.). The research presented was carried out in the conditions of the Czech Republic in the first half of 2020 through a questionnaire survey within a Google Form, which was aimed at beekeepers. The aim of this paper is, based on a questionnaire survey, to evaluate ecosystem services of beekeeping from the perspective of beekeepers, including the valuation of selected types of ecosystem services. The results show that in the Czech Republic, the most common reason for beekeeping is as a hobby (34.18%). As expected, the demand for pollination is very low compared to other countries (11.6%). From the point of view of the benefits of ecosystem services, the questionnaire survey showed that the most important benefit is the pollination of cultivated and other plants (54.7%) and honeybee products (24.8%). The value of all selected ecosystem services totals 3,646,368 CZK. The results show that state support is needed, which should address the negative demographic development of beekeepers and thus ensure the production of ecosystem services.
Keywords: Apiary products; Apiculture; Bioeconomy strategy; Ecosystem services; Honeybees; Pollination

An economic approach to assess the annual stock in beekeeping farms: The honey bee colony inventory tool - Vercelli, Monica; Croce, Luca; Mancuso, Teresina (Sustainability (Switzerland), 2020)
For beekeepers, the beehive stock represents a fundamental means of ensuring the continuity of their activity, whether they are professionals or hobbyists. The evaluation of this asset for economic purposes requires knowledge of the rhythms and adaptations of honey bee colonies during the annual seasons. As in any breeding activity, it is necessary to establish the numerical and economic size of the species bred. Beekeepers are interested in this evaluation to monitor beehive stock. For keeping economic accounts of stock, a specific tool has been developed and proposed, here called the ‘Honey Bee Colony Inventory (HBCI)’. The HBCI can be used as either a final or preventive scheme to assess the numbers of honey bee colonies and nuclei, and the mortality rate, in order to calculate the monetary value. This tool allows the strength of honey bee colony stocks to be monitored, including fluctuations throughout the year, and will prove useful for determining solutions to maintain or increase how long stocks last. Data can be registered in countries such as Italy where the veterinary authorities request data on the stock owned and its variations. Due to widespread Varroa mite infestations, in recent years, beekeepers have experimented with a range of different biotechniques that have included queen caging as well as drone and total brood removal. To verify its effectiveness for gathering honey bee colony data, the HBCI was used in nine beekeeping farms applying different biotechniques to control Varroa mites: Chemical treatment, total brood removal, queen caging and old queen replacement by royal cell insertion. The results are compared and discussed. Out of the nine farms, seven showed negative monetary value according to the HBCI, as expected, due to multiple factors such as the unfavorable climate trend of 2017 in the studied area. The positive aspect is that the application of this tool will allow farmers to monitor, manage and maintain their beehive stocks.
Keywords: Apis mellifera; Beehive stock; Beekeeping; Colony inventory; Economic assessment; Honey bee; Varroa destructor

REVIEW ON HONEYBEE : MIRACLE AGENT OF POLLINATION - Chauhan, Tamana; Sarkar, Shimpy; Singh, Arshdeep (PLANT ARCHIVES, 2021)
Revista electrònica.

Bee pollination: From an ecological and economical perspective - Saha, Samrat; Munshi, Sahin Aktar; Laskar, Nripendra (2023)
About 70% of our food crops depend on the pollination service provided by different insect pollinators amongst which wild and hive bees are the key pollinators. Insect pollination accounts for over 153 billion euro to agricultural production annually. Pollination also improves yield and market value of the food commodity. A section of people from our society depend on the activities related to bee pollination service to earn a livelihood. Bee pollination and beekeeping are significant contributors to a country's GDP. It also conserves several wild flowers by helping them in reproduction. However, due to the action of various stressors such as chemical advancement in agricultural production, the diversity of different bees is in a threatening position. Though technological advancement brings some alternatives of bee pollination, but that can't meet the requirements up to a satisfactory level. With the decline in bee diversity our food production is also in an alarming stage. Keeping this in view, everyone needs to come forward to protect the pollinators for a promising future.
Keywords: Bee pollination; Crop production; Decline; Economy

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - Siviter, H.; Fisher, A.; Baer, B.; Brown, M. J.F.; Camargo, I. F.; Cole, J.; Le Conte, Y.; Dorin, B.; Evans, J. D.; Farina, W.; Fine, J.; Fischer, L. R.; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Targeted crop pollination by training honey bees: advances and perspectives - Farina, Walter M.; Arenas, Andrés; Estravis-Barcala, M. Cecilia; Palottini, Florencia (Frontiers in Bee Science, 2023)
As pollinator-dependent crops continue to expand globally, management strategies are needed to meet the current demand for pollination services. Improving the efficiency of pollinators depends on knowledge about crop plant biology as well as pollinator behavior. In this sense, we will review the scope and challenges of implementing a targeted pollination strategy based on the behavioral individual and social plasticity of the honey bee Apis mellifera. Here we summarize current knowledge on the bees´ ability to perceive, learn and generalize floral odors, the bias of their foraging preferences after in-hive experiences and the transfer of food source information within the social context of the colony, all aspects that impact on foraging decisions and can be used to direct pollinators to target crops. We focused on describing how key olfactory cues that mimic crop floral scents are acquired in the hive and propagate among colony mates to guide foraging to specific crops. Knowledge gaps, including volatiles variability between flowers of the same or different crop varieties, alternative managed pollinators, and potential impact on food industry are discussed.

Bee pollen and bee bread nutritional potential: Chemical composition and macronutrient digestibility under in vitro gastrointestinal system - Aylanc, Volkan; Falcão, Soraia I.; Vilas-Boas, Miguel (Food Chemistry, 2023)
Bee pollen (BP) and bee bread (BB) have been often investigated as potential functional foods. Both bee products are generally characterized by their high nutritional content, with BB being referred as more digestible than BP, however, there is a lack of scientific studies proving this claim. Here, we present a comparative evaluation of the macronutrient digestibility of BP and BB after applying a simulated in vitro gastrointestinal digestive system, together with the evaluation of its nutritional value and chemical composition. The digestibility scores for protein content were calculated on average as 69% and 76% for BP and BB, respectively, whereas digestibility scores for soluble sugars varied depending on bee product and sugar type. The results demonstrated that the nutritional values of both bee products changed depending on their botanical origin but BB is more accessible in the intestinal lumen, especially regarding protein.
Keywords: Amino acids; Bee bread; Bee pollen; Digestibility degree; Fatty acids; Nutritional composition

Honey bee (Apis mellifera) gut microbiota promotes host endogenous detoxification capability via regulation of P450 gene expression in the digestive tract - Wu, Yuqi; Zheng, Yufei; Chen, Yanan; Wang, Shuai; Chen, Yanping; Hu, Fuliang; Zheng, Huoqing (Microbial Biotechnology, 2020)
There is growing number of studies demonstrating a close relationship between insect gut microbiota and insecticide resistance. However, the contribution of the honey bee gut microbiota to host detoxification ability has yet to be investigated. In order to address this question, we compared the expression of cytochrome P450s (P450s) genes between gut microbiota deficient (GD) workers and conventional gut community (CV) workers and compared the mortality rates and the pesticide residue levels of GD and CV workers treated with thiacloprid or tau-fluvalinate. Our results showed that gut microbiota promotes the expression of P450 enzymes in the midgut, and the mortality rate and pesticide residue levels of GD workers are significantly higher than those of CV workers. Further comparisons between tetracycline-treated workers and untreated workers demonstrated that antibiotic-induced gut dysbiosis leads to attenuated expression of P450s in the midgut. The co-treatment of antibiotics and pesticides leads to reduced survival rate and a significantly higher amount of pesticide residues in honey bees. Taken together, our results demonstrated that honey bee gut symbiont could contribute to bee health through the modification of the host xenobiotics detoxification pathways and revealed a potential negative impact of antibiotics to honey bee detoxification ability and health.

Microbiota and Its Importance in Honey Bees - Borum, Ayşe Ebru (Bee Studies- Apiculture Research Institute, 2021)
In recent years, research on human and animal health has emerged as a very important microbiota and microbiome. Microbiota; has important functions in metabolism, immune system, growth and development.

Pollen reinforces learning in honey bee pollen foragers but not in nectar foragers - Nery, Denise; Moreno, Emilia; Arenas, Andrés (Journal of Experimental Biology, 2020)
Searching for reward motivates and drives behaviour. In honey bees Apis mellifera, specialized pollen foragers are attracted to and learn odours with pollen. However, the role of pollen as a reward remains poorly understood. Unlike nectar, pollen is not ingested during collection. We hypothesized that pollen (but not nectar) foragers could learn pollen by sole antennal or tarsal stimulation. Then, we tested how pairing of pollen (either hand- or bee-collected) and a neutral odour during a pre-conditioning affects performance of both pollen and nectar foragers during the classical conditioning of the proboscis extension response. Secondly, we tested whether nectar and pollen foragers perceive the simultaneous presentation of pollen (on the tarsi) and sugar (on the antennae) as a better reinforcement than sucrose alone. Finally, we searched for differences in learning of the pollen and nectar foragers when they were prevented from ingesting the reward during the conditioning. Differences in pollen-reinforced learning correlate with division of labour between pollen and nectar foragers. Results show that pollen foragers performed better than nectar foragers during the conditioning phase after being preconditioned with pollen. Pollen foragers also performed better than nectar foragers in both the acquisition and extinction phases of the conditioning, when reinforced with the dual reward. Consistently, pollen foragers showed improved abilities to learn cues reinforced without sugar ingestion. We discussed that differences in how pollen and nectar foragers respond to a cue associated with pollen greatly contribute to the physiological mechanism that underlies foraging specialization in the honeybee.
Keywords: Foraging division of labour; Olfactory memory; Pollen pre-conditioning; Pollen reinforcement; Pre-ingestive reward

Apple pollination is ensured by wild bees when honey bees are drawn away from orchards by a mass co-flowering crop, oilseed rape - Osterman, Julia; Theodorou, Panagiotis; Radzevičiūtė, Rita; Schnitker, Pascal; Paxton, Robert J. (Agriculture, Ecosystems and Environment, 2021)
Over the past two decades, the cultivated area of oilseed rape (Brassica napus L. or OSR), a mass-flowering crop, has markedly increased in Europe in response to bioenergy demands. As well as representing a major shift in floral composition across the landscape, mass-flowering OSR may alter pollination services to other simultaneously blooming crops, either decreasing pollination via competition for pollinators or facilitating it via pollinator spill-over. Apple (Malus domestica Borkh.) is an economically important, obligately insect-pollinated fruit crop that co-flowers with OSR. Using twelve independent apple orchards varying in the percentage of OSR in the surrounding landscape, we investigated the effect of OSR on pollinators and pollination of co-blooming apple. We collected bees with pan traps and quantified flower visitors during transect walks in both crops and we experimentally measured pollination service provision to apple as fruit and seed set. We confirm that apples are highly dependent on animal pollination and report pollination limitation in our apple orchards. Honey bees were the numerically dominant visitors of apple flowers observed during transect walks. Though their numbers dropped with an increasing percentage of OSR in the landscape, the number of bumble bees visiting apple flowers remained stable and those of other wild bees rose. The pan trapped Shannon diversity of bees remained constant. We could not detect an effect of OSR in the landscape on apple fruit set or seed set, both of which remained stable. Local wild bee populations might compensate for the loss of honey bees in the provision of pollination services in apple, providing especially effective pollination. Our results underscore not only the dominant role of bees in apple pollination but also the importance of wild bee conservation for providing pollination insurance and stability of apple crop yields under changing agricultural policies and cropping practices.
Keywords: Competition; Ecosystem service; Landscape; Mass flowering crop; Spillover

Honey sample collection methods influence pollen composition in determining true nectar-foraging bee plants - Layek, Ujjwal; Mondal, Rajib; Karmakar, Prakash (Acta Botanica Brasilica, 2020)
This study investigated the suitability of honey sample collection methods for determining the botanical origin of honey through palynological analysis. We used three methods to collect honey samples in three different modes viz. extracted honey using a honey extractor, squeezed honey and pipetted honey (collected by micropipette/dropper from honey cells only) during 2017 to 2019 in West Bengal, India. We considered two native honey bee species (Apis dorsata and Apis florea) and one introduced bee species (Apis mellifera). Pollen composition differed significantly, both quantitatively and qualitatively, among the honey samples of the different methods. The number of pollen grains in extracted honey and squeezed honey was significantly higher than that of pipetted honey. Furthermore, some pollen types of nectar deficient, but polleniferous plants (viz. Capparis zeylanica, Echinochloa frumentacea, Papaver somniferum, Poaceae type, Nelumbo nucifera, Solanum melongena, and Solanum sisymbriifolium), were also present in extracted and squeezed honeys. We concluded that some pollen grains present in extracted and squeezed honey samples came from stored pollen loads or bee bread in the hive. Hence, the pollen spectrum for pipetted honey samples was more accurate in depicting the bees foraging on nectariferous plants.
Keywords: Extracted honey; Nectariferous plant; Pipetted honey; Pollen spectrum; Squeezed honey

Plant protection product residues in plant pollen and nectar: A review of current knowledge - Zioga, Elena; Kelly, Ruth; White, Blánaid; Stout, Jane C. (Environmental Research, 2020)
Exposure to Plant Protection Products, PPPs, (fungicides, herbicides and insecticides) is a significant stressor for bees and other pollinators, and has recently been the focus of intensive debate and research. Specifically, exposure through contaminated pollen and nectar is considered pivotal, as it presents the highest risk of PPP exposure across all bee species. However, the actual risk that multiple PPP residues might pose to non-target species is difficult to assess due to the lack of clear evidence of their actual concentrations. To consolidate the existing knowledge of field-realistic residues detected in pollen and nectar directly collected from plants, we performed a systematic literature review of studies over the past 50 years (1968–2018). We found that pollen was the matrix most frequently evaluated and, of the compounds investigated, the majority were detected in pollen samples. Although the overall most studied category of PPPs were the neonicotinoid insecticides, the compounds with the highest median concentrations of residues in pollen were: the broad spectrum carbamate carbofuran (1400 ng/g), the fungicide and nematicide iprodione (524 ng/g), and the organophosphate insecticide dimethoate (500 ng/g). In nectar, the highest median concentration of PPP residues detected were dimethoate (1595 ng/g), chlorothalonil (76 ng/g), and the insecticide phorate (53.5 ng/g). Strong positive correlation was observed between neonicotinoid residues in pollen and nectar of cultivated plant species. The maximum concentrations of several compounds detected in nectar and pollen were estimated to exceed the LD50s for honey bees, bumble bees and four solitary bee species, by several orders of magnitude. However, there is a paucity of information for the biggest part of the world and there is an urgent need to expand the range of compounds evaluated in PPP studies.
Keywords: Bees; Exposure hazard; PPPs; Pesticide residues; Risk assessment

‘Honey pot’ rural enterprise hubs as micro-clusters: Exploring their role in creativity-led rural development - Merrell, Ian; Rowe, Frances; Cowie, Paul; Gkartzios, Menelaos (Local Economy, 2021)
Rural enterprise hubs are physical infrastructures designed to help rural businesses access tangible and intangible benefits. They generally operate within two main business models: ‘Honey Pots’ (i.e. targeting business-to-customer tenants) and ‘Hives’ (i.e. targeting business‐to‐business tenants). This paper focuses on the former type, Honey Pot hubs, which are best suited to tenants who sell their products/services directly to the general public, such as some creative sectors, retail and tourism. Honey Pot hubs are designed to cater to such needs by attracting footfall to the space, providing cafes and facilities for the general public and hosting events. This paper explores how these Honey Pot hubs contribute to rural and regional development, through the creative practices of their tenants. The paper draws on qualitative interviews with Honey Pot managers and tenants in remote rural locations of the North East of England. The findings are useful for Hub practitioners, policy makers and rural creative businesses who want to develop similar initiatives in their locales.
Keywords: Rural development; creative industries; enterprise hub; honey pot; micro-cluster

Direct economic impact assessment of winter honeybee colony losses in three european countries - Popovska Stojanov, Despina; Dimitrov, Lazo; Danihlík, Jiří; Uzunov, Aleksandar; Golubovski, Miroljub; Andonov, Sreten; Brodschneider, Robert (Agriculture (Switzerland), 2021)
Honeybees are of great importance because of their role in pollination as well as for hive products. The population of managed colonies fluctuates over time, and recent monitoring reports show different levels of colony losses in many regions and countries. The cause of this kind of loss is a combination of various factors, such as the parasitic mite Varroa destructor, viruses, pesticides, management practices, climate change, and other stress factors. Having in mind that the economic aspect of honeybee colony losses has not been estimated, a pioneer effort was made for developing a methodology that estimates the economic impact of honeybee colony losses. Winter loss data was based on 2993 answers of the COLOSS standard questionnaire survey of honeybee winter colony losses for 2016/2017. In addition, market and financial data were used for each country. In a comparative analysis, an assessment on the economic impact of colony losses in Austria, Czechia, and Macedonia was made. The estimation considered the value of the colonies and the potential production losses of the lost colonies and of surviving but weak colonies. The direct economic impact of winter honeybee colony losses in 2016/2017 in Austria was estimated to be about 32 Mio €; in Czechia, 21 Mio €; and in Macedonia, 3 Mio €. Economic impact reflects the different value levels in the three countries, national colony populations, and the magnitude of colony losses. This study also suggests that economic losses are much higher than the subsidies, which underlines the economic importance of honeybees for the agricultural sector.
Keywords: Apis mellifera; Colony losses; Economic assessment; Methodology

Protein profiling of hemolymph in Haemaphysalis flava ticks - Liu, Lei; Yan, Fen; Zhang, Lu; Wu, Zhi feng; Duan, De yong; Cheng, Tian yin (Parasites and Vectors, 2022)
Background: Tick hemolymph bathes internal organs, acts as an exchange medium for nutrients and cellular metabolites, and offers protection against pathogens. Hemolymph is abundant in proteins. However, there has been limited integrated protein analysis in tick hemolymph thus far. Moreover, there are difficulties in differentiating tick-derived proteins from the host source. The aim of this study was to profile the tick/host protein components in the hemolymph of Haemaphysalis flava. Methods: Hemolymph from adult engorged H. flava females was collected by leg amputation from the Erinaceus europaeus host. Hemolymph proteins were extracted by a filter-aided sample preparation protocol, digested by trypsin, and assayed by liquid chromatography–tandem mass spectrometry (LC–MS/MS). MS raw data were searched against the UniProt Erinaceidae database and H. flava protein database for host- and tick-derived protein identification. Protein abundance was further quantified by intensity-based absolute quantification (iBAQ). Results: Proteins extracted from hemolymph unevenly varied in size with intense bands between 100 and 130 kDa. In total, 312 proteins were identified in the present study. Therein 40 proteins were identified to be host-derived proteins, of which 18 were high-confidence proteins. Top 10 abundant host-derived proteins included hemoglobin subunit-α and subunit-β, albumin, serotransferrin-like, ubiquitin-like, haptoglobin, α-1-antitrypsin-like protein, histone H2B, apolipoprotein A-I, and C3-β. In contrast, 169 were high-confidence tick-derived proteins. These proteins were classified into six categories based on reported functions in ticks, i.e., enzymes, enzyme inhibitors, transporters, immune-related proteins, muscle proteins, and heat shock proteins. The abundance of Vg, microplusin and α-2-macroglobulin was the highest among tick-derived proteins as indicated by iBAQ. Conclusions: Numerous tick- and host-derived proteins were identified in hemolymph. The protein profile of H. flava hemolymph revealed a sophisticated protein system in the physiological processes of anticoagulation, digestion of blood meal, and innate immunity. More investigations are needed to characterize tick-derived proteins in hemolymph. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Cystatin; Enzyme; Enzyme inhibitors; Hemolymph; Microplusin; Serpin; Tick; Vitellogenin

The Insect Circulatory System: Structure, Function, and Evolution - Hillyer, Julián F; Pass, Günther (2019)
Although the insect circulatory system is involved in a multitude of vital physiological processes, it has gone grossly understudied. This review highlights this critical physiological system by detailing the structure and function of the circulatory organs, including the dorsal heart and the accessory pulsatile organs that supply hemolymph to the appendages. It also emphasizes how the circulatory system develops and ages and how, by means of reflex bleeding and functional integration with the immune system, it supports mechanisms for defense against predators and microbial invaders, respectively. Beyond that, this review details evolutionary trends and novelties associated with this system, as well as the ways in which this system also plays critical roles in thermoregulation and tracheal ventilation in high-performance fliers. Finally, this review highlights how novel discoveries could be harnessed for the control of vector-borne diseases and for translational medicine, and it details principal knowledge gaps that necessitate further investigation.
Keywords: defense; dorsal vessel; heart; hemocoel; hemolymph; pressure

Complex hemolymph circulation patterns in grasshopper wings - Salcedo, Mary K.; Jun, Brian H.; Socha, John J.; Pierce, Naomi E.; Vlachos, Pavlos P.; Combes, Stacey A. (Communications Biology, 2023)
An insect’s living systems—circulation, respiration, and a branching nervous system—extend from the body into the wing. Wing hemolymph circulation is critical for hydrating tissues and supplying nutrients to living systems such as sensory organs across the wing. Despite the critical role of hemolymph circulation in maintaining healthy wing function, wings are often considered “lifeless” cuticle, and flows remain largely unquantified. High-speed fluorescent microscopy and particle tracking of hemolymph in the wings and body of the grasshopper Schistocerca americana revealed dynamic flow in every vein of the fore- and hindwings. The global system forms a circuit, but local flow behavior is complex, exhibiting three distinct types: pulsatile, aperiodic, and “leaky” flow. Thoracic wing hearts pull hemolymph from the wing at slower frequencies than the dorsal vessel; however, the velocity of returning hemolymph (in the hindwing) is faster than in that of the dorsal vessel. To characterize the wing’s internal flow mechanics, we mapped dimensionless flow parameters across the wings, revealing viscous flow regimes. Wings sustain ecologically important insect behaviors such as pollination and migration. Analysis of the wing circulatory system provides a template for future studies investigating the critical hemodynamics necessary to sustaining wing health and insect flight.

Subcellular Biochemistry 94 Vertebrate and Invertebrate Respiratory Proteins, Lipoproteins and other Body Fluid Proteins - Hoeger, Ulrich; Robin, J; Editors, Harris

Sugar, amino acid and inorganic ion profiling of the honeydew from different hemipteran species feeding on Abies alba and Picea abies - Shaaban, Basel; Seeburger, Victoria; Schroeder, Annette; Lohaus, Gertrud (PLoS ONE, 2020)
Several hemipteran species feed on the phloem sap of plants and produce large amounts of honeydew that is collected by bees to produce honeydew honey. Therefore, it is important to know whether it is predominantly the hemipteran species or the host plant to influence the honeydew composition. This is particularly relevant for those botanical and zoological species from which the majority of honeydew honey originates. To investigate this issue, honeydew from two Cinara species located on Abies alba as well as from two Cinara and two Physokermes species located on Picea abies were collected. Phloem exudates of the host plants were also analyzed. Honeydew of all species contained different proportions of hexoses, sucrose, melezitose, erlose, and further di- and trisaccharides, whereas the phloem exudates of the host trees contained no trisaccharides. Moreover, the proportions of sugars differed significantly between hemipteran species feeding on the same tree species. Sucrose hydrolysis and oligosaccharide formation was shown in whole-body homogenates of aphids. The type of the produced oligosaccharides in the aphid-extracts correlated with the oligosaccharide composition in the honeydew of the different aphid species. The total contents of amino acids and inorganic ions in the honeydew were much lower than the sugar content. Glutamine and glutamate were predominant amino acids in the honeydew of all six hemipteran species and also in the phloem exudates of both tree species. Potassium was the dominant inorganic ion in all honeydew samples and also in the phloem exudate. Statistical analyses reveal that the sugar composition of honeydew is determined more by the hemipteran species than by the host plant. Consequently, it can be assumed that the sugar composition of honeydew honey is also more influenced by the hemipteran species than by the host tree.

The chemistry of an insect ear: ionic composition of a liquid-filled ear and haemolymphs of Neotropical katydids - Sarria-S, Fabio A.; Montealegre-Z, Fernando; Gonzalez-Rodriguez, Jose (Journal of the Royal Society Interface, 2023)
The purpose of this study is to examine and to compare the ionic composition of the haemolymph and the ear fluid of seven species of katydids (Orthoptera: Tettigoniidae) with the aim of providing from a biochemical perspective a preliminary assessment for an insect liquid contained in the auditory organ of katydids with a hearing mechanism reminiscent of that found in vertebrates. A multi-element trace analysis by inductively coupled plasma optical-emission spectrometry was run for 16 elements for the ear liquid of seven species and the haemolymph of six of them. Based on the obtained results, it can be recognized that the ionic composition is variable among the studied insects, but sodium (Na +), potassium (K +), calcium (Ca 2+) and magnesium (Mg 2+) are the most prominent of the dissolved inorganic cations. However, the ion concentrations between the two fluids are considerably different and the absence or low concentration of Ca 2+ is a noticeable feature in the inner ear liquid. A potential relationship between the male courtship song peak frequency and the total ion (Na +, K +, Mg 2+ and Ca 2+) concentration of the inner ear liquid is also reported.
Keywords: cochlea; hearing; inductively coupled plasma optical-emission spectrometry; inorganic ions; tympanal organ

Fat body—multifunctional insect tissue - Skowronek, Patrycja; Wójcik, Łukasz; Strachecka, Aneta (Insects, 2021)
The biodiversity of useful organisms, e.g., insects, decreases due to many environmental factors and increasing anthropopressure. Multifunctional tissues, such as the fat body, are key el-ements in the proper functioning of invertebrate organisms and resistance factors. The fat body is the center of metabolism, integrating signals, controlling molting and metamorphosis, and synthe-sizing hormones that control the functioning of the whole body and the synthesis of immune system proteins. In fat body cells, lipids, carbohydrates and proteins are the substrates and products of many pathways that can be used for energy production, accumulate as reserves, and mobi-lize at the appropriate stage of life (diapause, metamorphosis, flight), determining the survival of an individual. The fat body is the main tissue responsible for innate and acquired humoral im-munity. The tissue produces bactericidal proteins and polypeptides, i.e., lysozyme. The fat body is also important in the early stages of an insect’s life due to the production of vitellogenin, the yolk protein needed for the development of oocytes. Although a lot of information is available on its structure and biochemistry, the fat body is an interesting research topic on which much is still to be discovered.
Keywords: Humoral immunity; Insect immunology; Insect metabolism; Metamorphosis; Trophocytes

The Dielectric Properties of Worker Bee Homogenate in a High Frequency Electric Field - Szychta, Leszek; Jankowski-Mihułowicz, Piotr; Szychta, Elżbieta; Olszewski, Krzysztof; Putynkowski, Grzegorz; Barczak, Tadeusz; Wasilewski, Piotr (Energies, 2022)
Biological tissues, including insect tissues, are among lossy dielectric materials. The permittivity properties of these materials are described by loss factor (Formula presented.) and loss tangent tgδ. The dielectric properties of the worker honeybee body homogenate are tested in the range of high frequencies from 1 MHz to 6 GHz. The homogenate is produced by mixing whole worker honeybees and tested with an epsilometer from Compass Technology and a Copper Mountain Technologies vector circuit analyser VNA. Due to their consistency, the homogenate samples are placed inside polyurethane sachets. The measured permittivity relates to two components of a sample: homogenate and polyurethane. For five samples, two extremes were specified for the permittivity, loss factor (Formula presented.), and the loss tangent tgδ, for the frequency range 20 ÷ 80 MHz and 3 GHz. Four techniques of testing permittivity in biological tissues were used to determine the dielectric properties of the homogenate. A calculation model was developed featuring a minimum measurement error of the loss factor (Formula presented.) and the loss tangent tgδ. The power absorbed per unit volume is described for the whole frequency range.
Keywords: dielectric permittivity; high frequency electric field; honeybees; radio and microwave measurements

Strategies of Invertebrate Osmoregulation: An Evolutionary Blueprint for Transmuting into Fresh Water from the Sea - Mcnamara, John Campbell; Freire, Carolina Arruda (Integrative and Comparative Biology, 2022)
Earlymarine invertebrates like the Branchiopoda began their sojourn into dilutemedia some 500 million years ago in the Middle Cambrian. Others like the Mollusca, Annelida, and many crustacean taxa have followed, accompanying major marine transgressions and regressions, shifting landmasses, orogenies, and glaciations. In adapting to these events and new habitats, such invertebrates acquired novel physiological abilities that attenuate the ion loss and water gain that constitute severe challenges to life in dilute media. Among these taxon-specific adaptations, selected from the subcellular to organismal levels of organization, and constituting a feasible evolutionary blueprint for invading freshwater, are reduced body permeability and surface (S) to volume (V) ratios, lowered osmotic concentrations, increased osmotic gradients, increased surface areas of interface epithelia, relocation of membrane proteins in ion-transporting cells, and augmented transport enzyme abundance, activity, and affinity. We examine these adaptations in taxa that have penetrated into freshwater, revealing diversified modifications, a consequence of distinct body plans, morpho-physiological resources, and occupation routes. Contingent on life history and reproductive strategy, numerous patterns of osmotic regulation have emerged, including intracellular isosmotic regulation in weak hyper-regulators and well-developed anisosmotic extracellular regulation in strong hyper-regulators, likely reflecting inertial adaptations to early life in an estuarine environment. In this review, we address osmoregulation in those freshwater invertebrate lineages that have successfully invaded this biotope. Our analyses show that across 66 freshwater invertebrate species from six phyla/classes that have transmuted into freshwater from the sea, hemolymph osmolalities decrease logarithmically with increasing S:V ratios. The arthropods have the highest osmolalities, from 300 to 650 mOsmoles/kg H2O in the Decapoda with 220-320 mOsmoles/kg H2O in the Insecta; osmolalities in the Annelida range from 150 to 200 mOsmoles/kg H2O, and the Mollusca showing the lowest osmolalities at 40-120 mOsmoles/kg H2O. Overall, osmolalities reach a cut-off at ∼200 mOsmoles/kg H2O, independently of increasing S:V ratio. The ability of species with small S:V ratios to maintain large osmotic gradients is mirrored in their putatively higher Na+/K+-AT Pase activities that drive ion uptake processes. Selection pressures on these morpho-physiological characteristics have led to differential osmoregulatory abilities, rendering possible the conquest of freshwater while retaining some tolerance of the ancestral medium.

Cells Electrical Characterization: Dielectric Properties, Mixture, and Modeling Theories - Nasir, Nida; Al Ahmad, Mahmoud (Journal of Engineering (United Kingdom), 2020)
Electrical detection of biotic materials and their properties is always crucial in Biomedical Engineering. It emphasizes elaborate analysis of a certain disease diagnosis using electrical means which includes the study of electrical properties followed by detection, identification, and quantification of biotic entities. Proper and early detection of cells, which can be normal or cancerous, holds never-ending demand. This review emphasizes the electrical characterization methods in modeling and classification of cell properties. Moreover, standard methods have been highlighted and discussed to yield performance analysis. This study suggests that techniques presented for single-cell analysis (SCA) are always precise and hold great scope compared to those for cell mixture. SCA plays a promising role in disease diagnosis and treatment planning, as it not only detects the cells but also helps in identification. Distinct electrical-based cell detection techniques are highlighted, along with the pros and cons of various SCA devices. The content, in terms of methodologies and available techniques, of this review paper is useful to attract researchers working in this area.

Review of non-invasive continuous glucose monitoring based on impedance spectroscopy - Huang, Jiamei; Zhang, Ying; Wu, Jayne (Sensors and Actuators, A: Physical, 2020)
The incidence of diabetes is increasing at an alarming rate worldwide, and glucose monitoring is critical to diabetes management. Non-invasive continuous blood glucose monitoring is highly sought after for diabetes management. While enzyme based approaches already have commercial products, they are invasive, inconvenient for patients to use, and cannot be continuous. Non-invasive glucose detection by spectroscopy methods have garnered much interest in recent years, however, still facing many challenges to be adopted for clinical applications. Among spectroscopy methods, electrical impedance methods have the advantages of being low cost and user-friendly. This review summarizes recent advances in non-invasive continuous glucose monitoring based on skin impedance measurement by electrical impedance spectroscopy (EIS), with emphasis on the devices that can potentially be integrated into wearable platforms. The discussion includes physical designs of bioimpedance sensors, signal measurement strategies, modeling and parameter estimation methods to extract blood glucose levels, and portable system designs. At the end, the challenges of EIS based glucose estimation devices and the trend of non-invasive glucose monitoring techniques are discussed.
Keywords: Bioimpedance; Electrical impedance spectroscopy; Glucose monitoring; Wearable biosensor

Bioelectrical understanding and engineering of cell biology - Schofield, Zoe; Meloni, Gabriel N.; Tran, Peter; Zerfass, Christian; Sena, Giovanni; Hayashi, Yoshikatsu; Grant, Murray; Contera, Sonia A.; Minteer, Shelley D.; Kim, Minsu; Prindle, Arthur; Rocha, Paulo; et al. (Journal of the Royal Society Interface, 2020)
The last five decades of molecular and systems biology research have provided unprecedented insights into the molecular and genetic basis of many cellular processes. Despite these insights, however, it is arguable that there is still only limited predictive understanding of cell behaviours. In particular, the basis of heterogeneity in single-cell behaviour and the initiation of many different metabolic, transcriptional or mechanical responses to environmental stimuli remain largely unexplained. To go beyond the status quo, the understanding of cell behaviours emerging from molecular genetics must be complemented with physical and physiological ones, focusing on the intracellular and extracellular conditions within and around cells. Here, we argue that such a combination of genetics, physics and physiology can be grounded on a bioelectrical conceptualization of cells. We motivate the reasoning behind such a proposal and describe examples where a bioelectrical view has been shown to, or can, provide predictive biological understanding. In addition, we discuss how this view opens up novel ways to control cell behaviours by electrical and electrochemical means, setting the stage for the emergence of bioelectrical engineering.
Keywords: Bioelectrical cell biology; Bioelectricity; Cell biophysics; Cell physiology; Electrochemistry

A review on electrical impedance tomography spectroscopy - Leitzke, Juliana Padilha; Zangl, Hubert (Sensors (Switzerland), 2020)
Electrical Impedance Tomography Spectroscopy (EITS) enables the reconstruction of material distributions inside an object based on the frequency-dependent characteristics of different substances. In this paper, we present a review of EITS focusing on physical principles of the technology, sensor geometries, existing measurement systems, reconstruction algorithms, and image representation methods. In addition, a novel imaging method is proposed which could fill some of the gaps found in the literature. As an example of an application, EITS of ice and water mixtures is used.
Keywords: Electrical impedance tomography spectroscopy; Image reconstruction; Multi-frequency electrical impedance tomography

Recent advances in monitoring cell behavior using cell-based impedance spectroscopy - Hassan, Qusai; Ahmadi, Soha; Kerman, Kagan (Micromachines, 2020)
Cell-based impedance spectroscopy (CBI) is a powerful tool that uses the principles of electrochemical impedance spectroscopy (EIS) by measuring changes in electrical impedance relative to a voltage applied to a cell layer. CBI provides a promising platform for the detection of several properties of cells including the adhesion, motility, proliferation, viability and metabolism of a cell culture. This review gives a brief overview of the theory, instrumentation, and detection principles of CBI. The recent applications of the technique are given in detail for research into cancer, neurodegenerative diseases, toxicology as well as its application to 2D and 3D in vitro cell cultures. CBI has been established as a biophysical marker to provide quantitative cellular information, which can readily be adapted for single-cell analysis to complement the existing biomarkers for clinical research on disease progression.
Keywords: Cell culture; Cell-based impedance; Electrochemical impedance spectroscopy; High-throughput screening

Electrical Impedance Tomography for Biomedical Applications: Circuits and Systems Review - Wu, Yu; Hanzaee, Farnaz Fahimi; Jiang, Dai; Bayford, Richard H.; Demosthenous, Andreas (IEEE Open Journal of Circuits and Systems, 2021)
There has been considerable interest in electrical impedance tomography (EIT) to provide low-cost, radiation-free, real-time and wearable means for physiological status monitoring. To be competitive with other well-established imaging modalities, it is important to understand the requirements of the specific application and determine a suitable system design. This paper presents an overview of EIT circuits and systems including architectures, current drivers, analog front-end and demodulation circuits, with emphasis on integrated circuit implementations. Commonly used circuit topologies are detailed, and tradeoffs are discussed to aid in choosing an appropriate design based on the application and system priorities. The paper also describes a number of integrated EIT systems for biomedical applications, as well as discussing current challenges and possible future directions.
Keywords: Analog front-end; bioimpedance; current driver; demodulation; electrical impedance tomography (EIT); integrated circuits; wearable technologies

Bioelectrical Impedance Spectroscopy for Monitoring Mammalian Cells and Tissues under Different Frequency Domains: A Review - Abasi, Sara; Aggas, John R.; Garayar-Leyva, Guillermo G.; Walther, Brandon K.; Guiseppi-Elie, Anthony (ACS Measurement Science Au, 2022)
Bioelectrical impedance analysis and bioelectrical impedance spectroscopy (BIA/BIS) of tissues reveal important information on molecular composition and physical structure that is useful in diagnostics and prognostics. The heterogeneity in structural elements of cells, tissues, organs, and the whole human body, the variability in molecular composition arising from the dynamics of biochemical reactions, and the contributions of inherently electroresponsive components, such as ions, proteins, and polarized membranes, have rendered bioimpedance challenging to interpret but also a powerful evaluation and monitoring technique in biomedicine. BIA/BIS has thus become the basis for a wide range of diagnostic and monitoring systems such as plethysmography and tomography. The use of BIA/BIS arises from (i) being a noninvasive and safe measurement modality, (ii) its ease of miniaturization, and (iii) multiple technological formats for its biomedical implementation. Considering the dependency of the absolute and relative values of impedance on frequency, and the uniqueness of the origins of the α-, β-, δ-, and γ-dispersions, this targeted review discusses biological events and underlying principles that are employed to analyze the impedance data based on the frequency range. The emergence of BIA/BIS in wearable devices and its relevance to the Internet of Medical Things (IoMT) are introduced and discussed.
Keywords: BIA/BIS wearables; Internet of Medical Things; bioelectrical impedance; bioelectrical impedance spectroscopy; bioimpedance instrumentation; clinical bioimpedance; equivalent circuit models; tissue response

Bioimpedance in Biomedical Applications and Research - Bertemes-Filho, Pedro; Simini, Franco (Bioimpedance in Biomedical Applications and Research, 2018)
This book is based on the best contributions to the advancement of bioimpedance knowledge and use from the Latin American Congress series, CLABIO. Basic bioimpedance facts as well as promising and original contributions to bioimpedance theory and applications are presented, giving the reader stimulating material for reflection, decision making, and further experiments. Contributions come from a diverse international pool of experts and address topics on electrode and skin impedance modelling, tomography, spectroscopy, instrumentation, and clinical applications.

Electrochemical impedimetric biosensors for food safety - Chai, Changhoon; Oh, Se Wook (Food Science and Biotechnology, 2020)
Electrochemical impedimetric biosensors (EIBs) have a simple structure and can be used to rapidly and sensitively detect and measure hazards in food. EIBs detect and measure target molecules by transducing biochemical reactions on their surface to electrical signal outputs responding to a sinusoidal electrical signal input. Due to their structural simplicity and analytical sensitivity, EIBs are regarded as the most potent method of food hazard monitoring that can be implemented in the food supply chain. This paper discusses the theoretical background, structure, and construction of EIB and its applications in food safety.
Keywords: Biosensor; Electrochemical impedance spectroscopy; Food safety; Mycotoxin; Pathogen

Review on the Study of Dielectric Properties of Food Materials - Bogale Teseme, Wondemu; Weldemichael Weldeselassie, Helen (American Journal of Engineering and Technology Management, 2020)
Dielectric properties of foods are used to explain interactions of foods with electric fields. It determines the interaction of electromagnetic waves with matter and defines the charge density under an electric field. For engineering point of view, dielectric properties are the foremost important physical properties related to radio frequency and microwave heating, it is critical to possess knowledge of the dielectric properties of materials in products and process development and, within the modern design of dielectric heating system for the need of desired process. Dielectric properties are often categorized into two: dielectric constant and dielectric loss factor. Dielectric constant is the ability of a material to store microwave energy and dielectric loss factor is the ability of a material to dissipate microwave energy into heat. Dielectric properties of food materials are required for various applications in food industry like microwave (at 915 or 2450 MHz), radio wave (at 13.56, 27.12 or 40.68 MHz) and magnetic field processing. In this review, the dielectric properties of various food groups were listed such as; Cereal grains and oilseeds, Bakery product, Dairy products, Poultry products, Fruits and vegetables. Dielectric properties are utilized in fruit drying processes, protect food materials from insects that already present in dried fruits, pasteurization, sterilization, tempering of concentration of liquid foods such as fruit juices, identification, processing, quality monitoring of fats and oils and improvement during oil processing and storage. The dielectric studies of food materials are an important tool to identify the quality of food materials and to improve dielectric heating uniformity. Frequency, moisture content, phase change, storage time and temperature are main factors that influence the dielectric properties of food material.

The impedance-based detection of total bacterial content in raw milk samples - Rajabzadeh, Elham; Sedighi, Mahsa; Jalili, Hasan; Nikfarjam, Alireza; Jarmoshti, Javad (Journal of Food Measurement and Characterization, 2024)
Monitoring the quality of food, particularly raw milk, is paramount for ensuring food safety and safeguarding human health. Therefore, the development of a rapid, sensitive, and cost-effective analytical system is imperative to prevent outbreaks of foodborne diseases. In this study, we assessed the total microbial content of raw milk using the impedance measurement and compared it to the standard plate count method. Furthermore, we investigated the impact of PEI-coated Fe3O4@SiO2 nanoparticles on capacitance changes through two electrode immobilization methods and direct addition to raw milk. Our findings revealed a strong correlation between impedance measurement at the optimal frequency of 10 kHz and the standard plate count method. Notably, capacitance changes occurred rapidly within the initial minutes of the experiment at a bacterial count of 1 × 104 CFU/ml, followed by a linear increase after 4 h. The detection times for bacterial counts of 102 CFU/ml and 104 CFU/ml were 5 h and 1 h, respectively. Utilizing PEI-coated Fe3O4@SiO2 NPs demonstrated enhanced signal response and sensitivity of the device when immobilizing the electrode and measuring capacitance after 5 min. These NPs facilitated the detection of a higher number of bacterial cells, indicating the potential of impedance analysis as a reliable method for determining the total bacterial concentration in raw milk. Consequently, the impedance-based system proposed in this study holds promise as an automated biosensor for detecting pathogenic bacteria in raw milk samples without the need for pretreatment.
Keywords: Capacitance; Impedance measurement; Magnetic nanoparticles; Polyethylene imine; Raw milk

A review on the use of impedimetric sensors for the inspection of food quality - He, Shan; Yuan, Yang; Nag, Anindya; Feng, Shilun; Afsarimanesh, Nasrin; Han, Tao; Mukhopadhyay, Subhas Chandra; Organ, Dominic Rowan (International Journal of Environmental Research and Public Health, 2020)
This paper exhibits a thorough review of the use of impedimetric sensors for the analysis of food quality. It helps to understand the contribution of some of the major types of impedimetric sensors that are used for this application. The deployment of impedimetric sensing prototypes has been advantageous due to their wide linear range of responses, detection of the target analyte at low concentrations, good stability, high accuracy and high reproducibility in the results. The choice of these sensors was classified on the basis of structure and the conductive material used to develop them. The first category included the use of nanomaterials such as graphene and metallic nanowires used to form the sensing devices. Different forms of graphene nanoparticles, such as nano-hybrids, nanosheets, and nano-powders, have been largely used to sense biomolecules in the micro-molar range. The use of conductive materials such as gold, copper, tungsten and tin to develop nanowire-based prototypes for the inspection of food quality has also been shown. The second category was based on conventional electromechanical circuits such as electronic noses and other smart systems. Within this sector, the standardized systems, such as electronic noses, and LC circuit-based systems have been explained. Finally, some of the challenges posed by the existing sensors have been listed out, along with an estimate of the increase in the number of sensors employed to assess food quality.
Keywords: Biomolecule; Food; Impedimetric; Quality; Sensors

Electrochemical impedance spectroscopy characterization of beverages - Soares, C.; Tenreiro Machado, J. A.; Lopes, António M.; Vieira, E.; Delerue-Matos, C. (Food Chemistry, 2020)
This paper compares the results of standard chemical analytical processes and electrochemical impedance spectroscopy (EIS) in the characterization of different beverages, namely ground coffee, soluble coffee, coffee substitutes, barley, cow milk, vegetable drinks, tea, plant infusions and plant mixtures. For the two approaches, the similarities between the experimental data are assessed by means of the Euclidean and Canberra distances. The resulting information is processed by means of the multidimensional scaling (MDS) clustering and visualization algorithm. The results of the chemical analytical processes and EIS reveal identical clusters for the two adopted distances. Furthermore, the robustness of the experimental and computational scheme are assessed by means of the Procrustes technique. The results confirm the effectiveness of combining the EIS and MDS.
Keywords: Clustering; Electrochemical impedance spectroscopy; Multidimensional scaling; Visualization

Application Status and Prospect of Impedance Spectroscopy in Agricultural Product Quality Detection - Cheng, Junhui; Yu, Pengpeng; Huang, Yourui; Zhang, Gang; Lu, Chengling; Jiang, Xueping (Agriculture (Switzerland), 2022)
The nondestructive testing of agricultural products has always been a key technology for the modernization of agriculture and food. By applying a sinusoidal voltage (current) excitation signal of variable frequency, the relationship between the amplitude, frequency and phase of the response signal is obtained, and the measured response function in a certain frequency range is obtained, constructing the correlation between impedance spectroscopy and matter properties. Electrical impedance spectroscopy (EIS) is a widely used method for the nondestructive characterization of agricultural products, and its applications in the agricultural field has attracted increasing attention. This paper summarizes the research of electrical impedance spectroscopy (EIS) in the detection of grain quality, fruit and vegetable quality, meat quality and food quality from 2005 to 2022. The potential and development direction of electrical impedance spectroscopy in the nondestructive testing of agricultural product quality are prospected, which provides a reference for scientific researchers who applied electrical impedance spectroscopy in agricultural product quality detection.
Keywords: agricultural products; detection; electrical impedance spectroscopy; quality

Utilization of electrical impedance spectroscopy and image classification for non-invasive early assessment of meat freshness - Huh, Sooin; Kim, Hye Jin; Lee, Seungah; Cho, Jinwoo; Jang, Aera; Bae, Joonsung (Sensors (Switzerland), 2021)
This study presents a system for assessing the freshness of meat with electrical impedance spectroscopy (EIS) in the frequency range of 125 Hz to 128 kHz combined with an image classifier for non-destructive and low-cost applications. The freshness standard is established by measuring the aerobic plate count (APC), 2-thiobarbituric acid reactive substances (TBARS), and composition analysis (crude fat, crude protein, and moisture) values of the microbiological detection to represent the correlation between EIS and meat freshness. The EIS and images of meat are combined to predict the freshness with the Adaboost classification and gradient boosting regression algorithms. As a result, when the elapsed time of beef storage for 48 h is classified into three classes, the time prediction accuracy is up to 85% compared to prediction accuracy of 56.7% when only images are used without EIS information. Significantly, the relative standard deviation (RSD) of APC and TBARS value predictions with EIS and images datum achieves 0.890 and 0.678, respectively.
Keywords: Electrical impedance spectroscopy (EIS); Freshness evaluation; Machine learning

Theoretical analysis of the electrochemical systems used for the application of direct current/voltage stimuli on cell cultures - Guette-Marquet, Simon; Roques, Christine; Bergel, Alain (2020)
Endogenous electric fields drive many essential functions relating to cell proliferation, motion, differentiation and tissue development. They are usually mimicked in vitro by using electrochemical systems to apply direct current or voltage stimuli to cell cultures. The many studies devoted to this topic have given rise to a wide variety of experimental systems, whose results are often difficult to compare. Here, these systems are analysed from an electrochemical standpoint to help harmonize protocols and facilitate optimal understanding of the data produced. The theoretical analysis of single-electrode systems shows the necessity of measuring the Nernst potential of the electrode and of discussing the results on this basis rather than using the value of the potential gradient. The paper then emphasizes the great complexity that can arise when high cell voltage is applied to a single electrode, because of the possible occurrence of anode and cathode sites. An analysis of two-electrode systems leads to the advice to change experimental practices by applying current instead of voltage. It also suggests that the values of electric fields reported so far may have been considerably overestimated in macro-sized devices. It would consequently be wise to revisit this area by testing considerably lower electric field values.
Keywords: Electric field; conductive polymer; electrotaxis; galvanotaxis; stem cell; tissue engineering

Ultrasensitive detection of nucleic acids using deformed graphene channel field effect biosensors - Hwang, Michael Taeyoung; Heiranian, Mohammad; Kim, Yerim; You, Seungyong; Leem, Juyoung; Taqieddin, Amir; Faramarzi, Vahid; Jing, Yuhang; Park, Insu; van der Zande, Arend M.; Nam, Sungwoo; Aluru, Narayana R.; et al. (Nature Communications, 2020)
Field-effect transistor (FET)-based biosensors allow label-free detection of biomolecules by measuring their intrinsic charges. The detection limit of these sensors is determined by the Debye screening of the charges from counter ions in solutions. Here, we use FETs with a deformed monolayer graphene channel for the detection of nucleic acids. These devices with even millimeter scale channels show an ultra-high sensitivity detection in buffer and human serum sample down to 600 zM and 20 aM, respectively, which are ∼18 and ∼600 nucleic acid molecules. Computational simulations reveal that the nanoscale deformations can form ‘electrical hot spots’ in the sensing channel which reduce the charge screening at the concave regions. Moreover, the deformed graphene could exhibit a band-gap, allowing an exponential change in the source-drain current from small numbers of charges. Collectively, these phenomena allow for ultrasensitive electronic biomolecular detection in millimeter scale structures.

Bioimpedance analysis of vascular tissue and fluid flow in human and plant body: A review - Prasad, Anamika; Roy, Mukesh (Biosystems Engineering, 2020)
Bioimpedance is a non-invasive technique that finds diverse applications in living systems for tissue characterisation and diagnosis of disease. Biological tissue exposed under alternating current exhibits complex impedance behaviour that requires effective underlying biophysical and electrical models for such applications. Whilst bioimpedance has been widely explored in clinical applications on human body, its impact on agriculture industry is currently limited. Hence the paper reviews bioimpedance method with a focus on evaluating underlying biophysical models and analysis techniques, and identifying differences and similarities between human and plant-based applications. The application emphasis for the human body includes tissue composition, nutritional assessment, and analysis of the cardiovascular system for blood flow, cardiac output, and vascular compliance. The emphasis for applications in plants includes nutritional assessment and vascular tissue and flow characteristics. Bioimpedance is shown to be an invaluable tool in tissue engineering for both the systems. However, many challenges remain for both, including insufficient accuracy of biophysical models leading to false-positive diagnosis, limitation of analysis techniques to specific population groups or tissue type, and need for devices and technological improvements to improve accessibility to new applications such as precision agriculture. This review thus identifies critical technological and application gaps in bioimpedance for future research.
Keywords: Bioimpedance; Body composition; Cardiovascular disease; Plant tissue; Tissue model; Vascular tissue

Comprehensive Overview of Meta-heuristic Algorithm Applications 1 on PV Cell Parameter Identification 2 3 - Yang, Bo; Wang, Jingbo; Zhang, Xiaoshun; Yu, Tao; Yao, Wei; Shu, Hongchun; Sun, Liming (2020)
14 15 Abstract: Accurate parameter identification is crucial for a precise PV cell modelling and 16 analysis of characteristics of PV systems, while high nonlinearity of output I-V curve makes 17 this problem extremely thorny. Hence, a large number of researches have aroused extensive 18 interests in the past few years. Due to the rapid advancement of computer technology and 19 swarm intelligence, various promising meta-heuristic algorithms have been proposed to further 20 accelerate this trend. This paper aims to undertake a comprehensive review on meta-heuristic 21 algorithms and related variants which have been applied on PV cell parameter identification. 22 Particularly, these algorithms are classified into four categories, e.g., biology-based algorithms, 23 physics-based algorithms, sociology-based algorithms and mathematics-based algorithms. 24 Meanwhile, the evaluation criteria and identification performance of each algorithm are 25 thoroughly addressed. Besides, in order to quantitatively evaluate and compare various 26 algorithms, the identified PV parameters including the specific error and the simulated output 27 I-V or P-V curves are provided at the end of each algorithm. Moreover, a comprehensive 28 summary is also introduced to more specifically guide the readers to grasp and utilize these 29 approaches. Lastly, based on the covered twenty-eight algorithms, conclusion presents some 30 perspectives and recommendations for future development. 31 32
Keywords: PV cell; meta-heuristic algorithms; optimization methods 33; parameter identification

Bioinspired bio-voltage memristors - Fu, Tianda; Liu, Xiaomeng; Gao, Hongyan; Ward, Joy E.; Liu, Xiaorong; Yin, Bing; Wang, Zhongrui; Zhuo, Ye; Walker, David J.F.; Joshua Yang, J.; Chen, Jianhan; Lovley, Derek R.; et al. (Nature Communications, 2020)
Memristive devices are promising candidates to emulate biological computing. However, the typical switching voltages (0.2-2 V) in previously described devices are much higher than the amplitude in biological counterparts. Here we demonstrate a type of diffusive memristor, fabricated from the protein nanowires harvested from the bacterium Geobacter sulfurreducens, that functions at the biological voltages of 40-100 mV. Memristive function at biological voltages is possible because the protein nanowires catalyze metallization. Artificial neurons built from these memristors not only function at biological action potentials (e.g., 100 mV, 1 ms) but also exhibit temporal integration close to that in biological neurons. The potential of using the memristor to directly process biosensing signals is also demonstrated.

A review of impact resistant biological and bioinspired materials and structures - Lazarus, Benjamin S.; Velasco-Hogan, Audrey; Gómez-del Río, Teresa; Meyers, Marc A.; Jasiuk, Iwona (Journal of Materials Research and Technology, 2020)
Biological systems must have the capability to withstand impacts generated during collisions due to combat and defense. Thus, evolution has created complex materials’ architectures at various length scales that are capable of withstanding repeated, low-to-medium-velocity impacts (up to 50 m/s). In this paper, we review impact resistant biological systems with a focus on their recurrent structural design elements, material properties, and energy absorbing mechanisms. We classify these impact resistant structures at the micro- and meso-scales into layered, gradient, tubular, sandwich, and sutured and show how they construct global hierarchical, composite, porous, and interfacial architectures. Additionally, we review how these individual structures and their design parameters can provide a tailored response. We conclude with a future outlook and discussion of their potential for impact resistant bioinspired designs.
Keywords: Bioinspiration; Biological materials; Hierarchical materials; Impact resistance; Natural composite materials; Structural design motifs

Associative mechanosensory conditioning of the proboscis extension reflex in honeybees - Giurfa, Martin; Malun, Dagmar (Learning and Memory, 2004)
The present work introduces a form of associative mechanosensory conditioning of the proboscis extension reflex (PER) in honeybees. In our paradigm, harnessed honeybees learn the elemental association between mechanosensory, antennal stimulation and a reward of sucrose solution delivered to the proboscis. Thereafter, bees extend their proboscis to the antennal mechanosensory stimulation alone. We show that bees can learn such an association in a side-specific manner, that is, they learn the association on the antennal side that was rewarded and not on the side that was @not rewarded. Responding produced by the paired training does likely contain a substantial Pavlovian component. Responding is only elicited by mechanosensory stimulation and not by spurious cues such as olfactory, visual, and contextual ones. The interstimulus interval (ISI) affects one-trial mechanosensory learning: a bell-shaped curve with a maximum of responding ∼4 sec ISI was obtained. Mechanosensory memory is still operative 24 h after conditioning. Apart from absolute conditioning in which mechanosensory stimulation of one antenna is paired with sucrose, differential, side-specific, mechanosensory conditioning using two mechanosensory stimulations, one rewarded and the other not, is also possible. This paradigm constitutes, therefore, a new standard procedure for further learning studies in honeybees.

Behavioural methods to assess the effects of pesticides on honey bees - Pham-Delègue, Minh Hà; Decourtye, Axel; Kaiser, Laure; Devillers, James (Apidologie, 2002)
We reported on the use of experimental procedures dealing with these behavioural skills in the assessment of pesticide effects. The relevance of the following methods are discussed: (1) use of automatic activity counters set at the hive entrance to establish the balance between outgoing and incoming worker bees; (2) observation of the homing flights of bees; (3) the analysis of the information encoded in the dances of returning foragers; and (4) recording of the conditioned proboscis extension response on restrained bees to evaluate individual learning performances involved in foraging behaviour. These behavioural assays could be developed for sublethal toxicity assessment. However, careful validation of the tests is needed before being used in a routine evaluation procedure. At a minimum, they are valuable tools to understand the mechanisms underlying insecticide toxicity.
Keywords: Apis mellifera; Behaviour; Ecotoxicology; Pesticide; Risk assessment

CLASSICAL CONDITIONED RESPONSE IN THE HONEY BEE* - Takeda, K (1960)
The classical olfactory conditioned response of the honey bee, involving the extension of the proboscis on tarsal contact with sucrose solution, has been investigated. The bee showed generalization between two similar aromas but distinguished the third. The bee clearly showed experimental extinction, differentiation, and conditioned inhibition, all of which were temporary and not retained until the following day. Thus, spontaneous recovery WE observed. The experiments also suggest the occurrence of a conditioned response of the second order.

Effect of genotype but not of age or caste on olfactory learning performance in the honey bee, Apis mellifera

IMPAIRMENT OF A CLASSICAL CONDITIONED RESPONSE OF THE HONEY BEE (APIS MELLIFERA L.) BY SUBLETHAL DOSES OF SYNTHETIC PYRETHROID INSECTICIDES - Taylor, Kevin S; Waller, Gordon D; Crowder, Larry A
A classical conditioning experiment was used to compare the odor-mediated learned responses of honey bees (Apis mellifera L.) previously exposed to one of 6 pyrethroid insecticides dissolved in acetone with the responses of bees exposed only to acetone. Untreated bees showed a relatively steep acquisition slope following training bouts 1-3, and then an asymptote in response of ca 90 % positive responses following training bouts 4-7. Pyrethroid-treated bees learned at a slower rate but continued to show an improvement in positive responses throughout the test. However, treated bees attained only ca 60 % positive responses after their seventh training bout. Odor training responses were least affected by fluvalinate and most seriously disrupted by flucythrinate and cyfluthrin ; permethrin, fenvalerate, and cypermethrin were intermediate in their effect on the conditioned response.

Olfactory perception in honeybees: Concatenated and mixed odorant stimuli, concentration, and exposure effects - Getz, Wayne M; Smith, Katherine B (J Comp Physiol A, 1991)
Here we present results obtained from 7 different series of experiments, all employing odor conditioning of proboscis extension in worker honeybees and each designed to address a particular question involving olfactory perception. The questions relate to: temporal complexity of odor cues; effects of concentration, suppression , and/or potentiation in mixture perception; acquisition and extinction rates, as well as levels of generalization associated with aliphatic compounds that have the same functional groups or same alkyl radical length; and the effects of continuous exposure to odorants in the first several days of adult life on various learning and discrimination tasks involving olfactory perception. From the data obtained in these experiments we were able to conclude the following: First, worker honeybees have a limited ability to perceive complex temporal odor-quality patterns in olfactory stimuli-they learn to associate the quality of only the last part of the stimulus with a sucrose reward. Second, we confirm that citral is qualitatively different in several perceptual contexts involving odor learning and conditioning and our results help elucidate the nature of these differences as they relate to learning, discrimination, mixture perception, and continuous exposure to particular odorants. Third, we appear to have uncovered some important perceptual differences between functional groups attached to the first as opposed to the second carbon atom of alkyl radicals. Finally, we failed to uncover any significant effects relating to continuous exposure to odorants during the first several days of a worker's adult life, despite evidence that considerable sensory development takes place during this period. Thus ontogenetic changes to the peripheral system due to environmental effects appear to leave basic perceptual systems unaltered.
Keywords: Differential conditioning; Learning; Proboscis exten-sion reflex

Acute ozone exposure impairs detection of floral odor, learning, and memory of honey bees, through olfactory generalization - Démares, Fabien; Gibert, Laëtitia; Creusot, Pierre; Lapeyre, Benoit; Proffit, Magali (Science of the Total Environment, 2022)
Air pollution stemming from human activities affects the environment in which plant and animal species live and interact. Similar to primary air pollutants which are emitted, secondary air pollutants, such as tropospheric ozone (O3) formed from nitrogen oxides, are also harmful to human health and plant physiology. Yet, few reports studied the effects of O3 on pollinators' physiology, despite that this pollutant, with its high oxidative potential, likely affects pollinators behaviors, especially the perception of signals they rely on to navigate their environment. Volatile Organic Compounds (VOCs) released by plants are used as signals by different animals. For pollination services, VOCs attract different insects to the flowers and strengthen these interactions. Here, we used the honey bee Apis mellifera as a model to characterize the effects of acute exposure to different realistic mixing ratios of O3 (80-, 120-, and 200-ppb) on two crucial aspects: first, how exposed honey bees detect VOCs; and second, how O3 affects these pollinators' learning and memory processes. With electroantennogram (EAG) recordings, we showed that increasing O3 mixing ratios had a biphasic effect: an initial 25% decrease of the antennal activity when bees were tested directly after exposure (O3 direct effect), followed by a 25% increase in activity and response when bees were allowed a two-hour rest after exposure (O3 delayed effect). In parallel, during olfactory conditioning, increasing O3 mixing ratios in both exposure protocols scarcely affected olfactory learning, followed by a decrease in recall of learned odors and an increase of response to new odors, leading to a higher generalization rate (i.e., discrimination impairment). These results suggest a link between O3-related oxidative stress and olfactory coding disturbance in the honey bee brain. If ozone affects the pollinators' olfaction, foraging behaviors may be modified, in addition with a possible long-term harmful effect on pollination services.
Keywords: Air pollution; Apis mellifera; Generalization; Olfaction; Plant-pollinator interactions; Volatile organic compounds

Chronic nicotine exposure influences learning and memory in the honey bee - Mustard, Julie A.; Dobb, Rachel; Wright, Geraldine A. (Journal of Insect Physiology, 2023)
In insects, nicotine activates nicotinic acetylcholine receptors, which are expressed throughout the central nervous system. However, little work has been done to investigate the effects of chronic nicotine treatment on learning or other behaviors in non-herbivorous insects. To examine the effects of long term nicotine consumption on learning and memory, honey bees were fed nicotine containing solutions over four days. Bees were able to detect nicotine at 0.1 mM in sucrose solutions, and in a no choice assay, bees reduced food intake when nicotine was 1 mM or higher. Treatment with a low dose of nicotine decreased the proportion of bees able to form an associative memory when bees were conditioned with either a massed or spaced appetitive olfactory training paradigm. On the other hand, higher doses of nicotine increased memory retention and the proportion of bees responding to the odor during 10 min and 24 h recall tests. The reduction in nicotine containing food consumed may also impact response levels during learning and recall tests. These data suggest that long term exposure to nicotine has complex effects on learning and memory.
Keywords: Acetylcholine receptor; Chronic nicotine; Honey bee; Learning; Memory; Satiation

Sublethal doses of glyphosate impair olfactory memory retention, but not learning in the honey bee (Apis mellifera scutellata) - Hernández, Juan; Riveros, Andre J.; Amaya-Márquez, Marisol (Journal of Insect Conservation, 2021)
Learning and memory are important biological processes that allow for optimized honey bee behavior. Factors negatively affecting bee cognition are important contributors to declines in pollination and food security. Agrochemical use, including herbicides, is one of the primary stressors linked to bee decline. Predicted agricultural expansion and associated increased use of glyphosate combined with scarcity of honey bees further highlights the need to understand the relationship between glyphosate and honey bee cognition and health. Here we investigated the effect of field-realistic doses of glyphosate on honey bee olfactory learning and memory. We used the conditioning of the Proboscis Extension Reflex (PER) to evaluate olfactory absolute conditioning. We found no differences in olfactory PER performance between glyphosate-exposed and control bees. We also did not find differences in olfactory memory retrieval at 15 min or 24 h after conditioning between exposed and non-exposed bees. However, we found that sublethal doses of glyphosate impaired memory retention; bees exposed to sublethal doses of glyphosate showed a decay trajectory of learned information, while in non-exposed bees the trajectory had a positive increment with time. This trend in memory retention was significantly different between bees exposed to 1500 ng and controls. Implications for insect conservation: Field-realistic doses of glyphosate had negative effect on memory dynamics in the honey bee. These results suggest glyphosate affects time-dependent neural mechanisms underlying information processing. This negative effect contributes to declines in pollination function and food security. We highlight the need to critically evaluate the cost-benefit analysis of indiscriminate glyphosate use.
Keywords: Bee health; Cognition; Food security; Pesticides; Pollinator-Conservation; Time-dependent effect

Fiji: An open-source platform for biological-image analysis - Schindelin, Johannes; Arganda-Carreras, Ignacio; Frise, Erwin; Kaynig, Verena; Longair, Mark; Pietzsch, Tobias; Preibisch, Stephan; Rueden, Curtis; Saalfeld, Stephan; Schmid, Benjamin; Tinevez, Jean Yves; White, Daniel James; et al. (Nature Methods, 2012)
Fiji is a distribution of the popular open-source software ImageJ focused on biological-image analysis. Fiji uses modern software engineering practices to combine powerful software libraries with a broad range of scripting languages to enable rapid prototyping of image-processing algorithms. Fiji facilitates the transformation of new algorithms into ImageJ plugins that can be shared with end users through an integrated update system. We propose Fiji as a platform for productive collaboration between computer science and biology research communities. © 2012 Nature America, Inc. All rights reserved.

The hemolymph microbiome of insects 1 2 - Blow, Frances; Douglas, Angela E (2019)
14

ON THE REGULATION OF INSECT DISCONTINUOUS GAS EXCHANGE CYCLES: THE ROLE OF HEMOLYMPH OXYGEN AND CARBON DIOXIDE ON VENTILATORY RHYTHMS IN MADAGASCAR HISSING COCKROACHES - Rowe, Tormod T C (2020)

The neonicotinoids thiacloprid, imidacloprid, and clothianidin affect the immunocompetence of honey bees (Apis mellifera L.) - Brandt, Annely; Gorenflo, Anna; Siede, Reinhold; Meixner, Marina; Büchler, Ralph (Journal of Insect Physiology, 2016)
A strong immune defense is vital for honey bee health and colony survival. This defense can be weakened by environmental factors that may render honey bees more vulnerable to parasites and pathogens. Honey bees are frequently exposed to neonicotinoid pesticides, which are being discussed as one of the stress factors that may lead to colony failure. We investigated the sublethal effects of the neonicotinoids thiacloprid, imidacloprid, and clothianidin on individual immunity, by studying three major aspects of immunocompetence in worker bees: total hemocyte number, encapsulation response, and antimicrobial activity of the hemolymph. In laboratory experiments, we found a strong impact of all three neonicotinoids. Thiacloprid (24 h oral exposure, 200 μg/l or 2000. μg/l) and imidacloprid (1 μg/l or 10 μg/l) reduced hemocyte density, encapsulation response, and antimicrobial activity even at field realistic concentrations. Clothianidin had an effect on these immune parameters only at higher than field realistic concentrations (50-200 μg/l). These results suggest that neonicotinoids affect the individual immunocompetence of honey bees, possibly leading to an impaired disease resistance capacity.
Keywords: Antimicrobial activity; Encapsulation; Hemocyte; Honey bee; Immune system; Neonicotinoid; Wound healing

Hemolectin expression reveals functional heterogeneity in honey bee (Apis mellifera) hemocytes - Gábor, Erika; Cinege, Gyöngyi; Csordás, Gábor; Török, Tibor; Folkl-Medzihradszky, Katalin; Darula, Zsuzsanna; Andó, István; Kurucz, Éva (Developmental and Comparative Immunology, 2017)
The identification of molecular markers considerably facilitated the classification and functional analysis of blood cell types. Apis mellifera hemocytes have been classified by morphological criteria and lectin binding properties; however, the use of molecular markers has been minimal. Here we describe a monoclonal antibody to a non-phagocytic subpopulation of A. mellifera hemocytes and to a constituent of the hemolymph clot. We demonstrate that the antibody identifies the A. mellifera hemolectin, a protein carrying human von Willebrand factor homology domains, characteristic of proteins involved in blood coagulation and platelet aggregation in mammals. Hemolectin expressing A. mellifera hemocytes contain the protein as cytoplasmic granules and contribute to the formation of a protein matrix, building up around foreign particles. Consequently, hemolectin as a marker molecule reveals a clear functional heterogeneity of hemocytes, allowing for the analytical separation of hemocyte classes, and could promote the molecular identification of hemocyte lineages in A. mellifera.
Keywords: Apis mellifera; Cellular immunity; Encapsulation; Hemocyte; Monoclonal antibody; Phagocytosis

Isolation and molecular characterization of a major hemolymph serpin from the triatomine, Panstrongylus megistus - Moreira, Carlos Jc; Waniek, Peter J; Valente, Richard H; Carvalho, Paulo C; Perales, Jonas; Feder, Denise; Geraldo, Reinaldo B; Castro, Helena C; Azambuja, Patricia; Ratcliffe, Norman A; Mello, Cícero B (2014)
Background: Chagas disease kills 2.5 thousand people per year of 15 million persons infected in Latin America. The disease is caused by the protozoan, Trypanosome cruzi, and vectored by triatomine insects, including Panstrongylus megistus, an important vector in Brazil. Medicines treating Chagas disease have unpleasant side effects and may be ineffective, therefore, alternative control techniques are required. Knowledge of the T. cruzi interactions with the triatomine host needs extending and new targets/strategies for control identified. Serine and cysteine peptidases play vital roles in protozoan life cycles including invasion and entry of T. cruzi into host cells. Peptidase inhibitors are, therefore, promising targets for disease control.

Haemolymph viscosity in hawkmoths and its implications for hovering flight - Brasovs, Artis; Palaoro, Alexandre V.; Aprelev, Pavel; Beard, Charles E.; Adler, Peter H.; Kornev, Konstantin G. (Proceedings of the Royal Society B: Biological Sciences, 2023)
Viscosity determines the resistance of haemolymph flow through the insect body. For flying insects, viscosity is a major physiological parameter limiting flight performance by controlling the flow rate of fuel to the flight muscles, circulating nutrients and rapidly removing metabolic waste products. The more viscous the haemolymph, the greater the metabolic energy needed to pump it through confined spaces. By employing magnetic rotational spectroscopy with nickel nanorods, we showed that viscosity of haemolymph in resting hawkmoths (Sphingidae) depends on wing size non-monotonically. Viscosity increases for small hawkmoths with high wingbeat frequencies, reaches a maximum for middle-sized hawkmoths with moderate wingbeat frequencies, and decreases in large hawkmoths with slower wingbeat frequencies but greater lift. Accordingly, hawkmoths with small and large wings have viscosities approaching that of water, whereas hawkmoths with mid-sized wings have more than twofold greater viscosity. The metabolic demands of flight correlate with significant changes in circulatory strategies via modulation of haemolymph viscosity. Thus, the evolution of hovering flight would require fine-tuned viscosity adjustments to balance the need for the haemolymph to carry more fuel to the flight muscles while decreasing the viscous dissipation associated with its circulation.
Keywords: Lepidoptera; Sphingidae; biomechanics; flight; haemolymph; metabolism

OPTIMIZED CENTRIFUGATION PREPARATION OF THE PLATELET RICH PLASMA : LITERATURE REVIEW - Croisé, Benjamin; Paré, Arnaud; Joly, Aline; Louisy, Agathe; Laure, Boris; Goga, Dominique; Croise, Benjamin (2019)
Nowadays, the Platelet Rich Plasma (PRP) is frequently used for its therapeutic effects on wound healing, and this due to secretion of many growth factors. However, no standardized procedure has been set up. The aim of this article is to check the various preparations (centrifugation time and speed). This review recorded all the international articles published between 2007 and 2018, for which the assessment criteria were the platelet concentration and /or the growth factor release rate. A multitude of protocols has been looked at with a simple or double centrifugation. All of them have shown an increase in the platelet concentration allowing a therapeutic effect. However, when the centrifugation force is extended, platelets can possibly be altered. The diversity of methods can be linked to the use of various centrifuges. A procedure with simple centrifugation would be a good compromise for the day-today use of the PRP in surgery.
Keywords: Platelet Rich Plasma; centrifugation; platelet concentration; preparation

Ferritin from the haemolymph of adult ants: an extraction method for characterization and a ferromagnetic study - Wajnberg, Eliane; Alves, Odivaldo C.; Perales, Jonas; da Rocha, Surza Lucia G.; Ferreira, André Teixeira; Cameron, Luiz Cláudio; Esquivel, Darci M.S.; de Lourdes Barriviera, Maria (European Biophysics Journal, 2018)
Ferritin has been studied in many animals, plants and bacteria. The main functions of ferritin in mammals are iron concentration and stabilization, protection against oxidants and iron storage for later developmental or iron-dependent activities. Although insect ferritin plays a key role in iron transport, only a few studies to date have examined its properties and function. Ferritin isolation from the haemolymph of adult Camponotus sericeiventris ants involved heating at 75 °C, followed by protein fractionation with 3.2 M KBr gradients and ferritin sedimentation with KBr. Protein identification was performed using high-resolution proteomics techniques. SDS-PAGE revealed three subunits with molecular weights (MW) of 26, 28 and 31 kDa. Native PAGE indicated a MW higher than 669 kDa. Proteomic analysis strongly suggested the 26 and 31 kDa bands as F2LCH and F1HCH subunits of ferritin, respectively. Ferromagnetic resonance (FMR) at 100 K showed, at low field, a characteristic broad component of the ferritin iron core, suggesting that its distribution was shifted to values greater than 3000, a higher content than in mammals. The protein yield and MW were comparable to those reported in other studies of insects. To the best of our knowledge, this is the first report on ferritin extracted from adult ants to date. These results are discussed on the basis of the protein structure–function relation of secreted insect and mammal ferritins. This purification method will allow the use of magnetic techniques, which are relevant for understanding the role of ferritin in the biomineralization of magnetic nanoparticles in insects.
Keywords: Ants; Eusocial insect; Ferritin; Ferromagnetic resonance (FMR); Iron transport

Method for collecting hemolymph of insects

Determining the hemolymoh volume of the cockroach. Pages 119-139, in Tested studies for laboratory teaching - Smith, J J B (ABLE, 1994)

What are the main proteins in the hemolymph of Haemaphysalis flava ticks? - Li, Dan; Liu, Lei; Liu, Zi Ling; Tian, Yuan; Gao, Xin; Cheng, Tian Yin (Frontiers in Veterinary Science, 2024)
Background: Haemaphysalis flava is a notorious parasite for humans and animals worldwide. The organs of H. flava are bathed in hemolymph, which is a freely circulating fluid. Nutrients, immune factors, and waste can be transported to any part of the body via hemolymph. The main soluble components in hemolymph are proteins. However, knowledge of the H. flava proteome is limited. Methods: The hemolymph was collected from fully engorged H. flava ticks by leg amputation. Hemolymph proteins were examined by both blue native polyacrylamide gel electrophoresis (BN-PAGE) and sodium dodecyl sulfate PAGE (SDS-PAGE). Proteins extracted from the gels were further identified by liquid chromatography–tandem mass spectrometry (LC–MS/MS). Results: Two bands (380 and 520 kDa) were separated from tick hemolymph by BN-PAGE and were further separated into four bands (105, 120, 130, and 360 kDa) by SDS-PAGE. LC–MS/MS revealed that seven tick proteins and 13 host proteins were present in the four bands. These tick proteins mainly belonged to the vitellogenin (Vg) family and the α-macroglobulin family members. In silico structural analysis showed that these Vg family members all had common conserved domains, including the N-terminus lipid binding domain (LPD-N), the C-terminus von Willebrand type D domain (vWD), and the domain of unknown function (DUF). Additionally, two of the Vg family proteins were determined to belong to the carrier protein (CP) by analyzing the unique N-terminal amino acid sequences and the cleaving sites. Conclusion: These findings suggest that the Vg family proteins and α-macroglobulin are the primary constituents of the hemolymph in the form of protein complexes. Our results provide a valuable resource for further functional investigations of H. flava hemolymph effectors and may be useful in tick management.
Keywords: Haemaphysalis flava; carrier protein; hemolymph; vitellogenin; α-macroglobulin

A newly optimized protocol to extract high-quality hemolymph from the cattle tick Rhipicephalus microplus: Improving the old conditions - Aguilar-Díaz, Hugo; Quiroz-Castañeda, Rosa Estela; Salazar-Morales, Karina; Miranda-Miranda, Estefan (Current Research in Parasitology and Vector-Borne Diseases, 2022)
Ticks are hematophagous ectoparasites with importance to animal and human health. In recent years, the study of ticks has had significant development, including immune response, vector-host interactions, physiological and multi-omics approaches. However, one of the main impediments is obtaining a significant amount of high-quality hemolymph. For this reason, we developed a protocol that allows obtaining up to 100 μl of hemolymph free of host blood per engorged tick. The technique consists of continuous hipocuticular punctures of the tick dorsum and an anticoagulant buffer that impedes hemolymph coagulation, allowing constant extravasation and ensuring high yields. Additionally, the hemocytes recovered with this protocol are intact and can be used for further analysis. The high-quality hemolymph obtained using this protocol and its applications will help to better understand the processes involving the hemolymph and its components. Although there are other hemolymph extraction protocols, the method developed here is very well suited for Rhipicephalus microplus, and in our experience, results in better yields and high-quality samples.
Keywords: Hemocytes; Hemolymph extraction; High-quality hemolymph; Ticks

A high quality method for hemolymph collection from honeybee larvae - Butolo, Nicole Pavan; Azevedo, Patricia; de Alencar, Luciano Delmondes; Domingues, Caio E.C.; Miotelo, Lucas; Malaspina, Osmar; Nocelli, Roberta Cornélio Ferreira (PLoS ONE, 2020)
The drastic decline of bees is associated with several factors, including the immune system suppression due to the increased exposure to pesticides. A widely used method to evaluate these effects on these insects' immune systems is the counting of circulating hemocytes in the hemolymph. However, the extraction of hemolymph from larvae is quite difficult, and the collected material is frequently contaminated with other tissues and gastrointestinal fluids, which complicates counting. Therefore, the present work established a high quality and easily reproducible method of extracting hemolymph from honeybee larvae (Apis mellifera), the extraction with ophthalmic scissors. Extraction methods with the following tools also were tested: 30G needle, fine-tipped forceps, hypodermic syringe, and capillaries tubes. The hemolymph was obtained via an incision on the larvae's right side for all methods, except for the extraction with ophthalmic scissors, in which the hemolymph was extracted from the head region. To assess the purity of the collected material, turbidity analyses of the samples using a turbidimeter were proposed, tested, and evaluated. The results showed that the use of ophthalmic scissors provided the clearest samples and was free from contamination. A reference range between 22,432.35 and 24,504.87 NTU (nephelometric turbidity units) was established, in which the collected samples may be considered of high quality and free from contamination.

Development of a new method for collecting hemolymph and measuring phenoloxidase activity in Tribolium castaneum - Tabunoki, Hiroko; Dittmer, Neal T.; Gorman, Maureen J.; Kanost, Michael R. (BMC Research Notes, 2019)
Objective: Hemolymph plays many important roles in the physiology of an insect throughout its lifetime; however, for small-bodied insects, studies are lacking because of the difficulties encountered while collecting hemolymph. The objective of our study was to develop a method to collect hemolymph plasma from various stages of Tribolium castaneum and to evaluate phenoloxidase activity in the plasma samples. We first designed a procedure for easily and quickly collecting clear hemolymph plasma from T. castaneum. Results: By using this method, we collected approximately 5 μl plasma from 30 individuals at the larval, pupal or adult stages. And then, we studied the expression of phenoloxidase by performing western blot analysis of the plasma samples and found that phenoloxidase is present in hemolymph in each developmental stage. We also measured phenoloxidase activity in control plasma and plasma treated with Gram-positive bacteria, Micrococcus luteus. Phenoloxidase activity was greater in some of the M. luteus-treated plasma samples compared with control samples. Thus, we developed a method to collect hemolymph plasma that is suitable for studies of phenoloxidase activity.
Keywords: Dopamine; Hemolymph; Innate immune response; Melanin; Melanization; Phenoloxidase; Small insects; Tribolium castaneum

Variation in hemolymph content and properties among three Mediterranean bee species - Elfar, Salma A.; Bahgat, Iman M.; Shebl, Mohamed A.; Lihoreau, Mathieu; Tawfik, Mohamed M. (2023)
Hemolymph, as mediator of immune responses and nutrient circulation, can be used as physiological marker of an insect’s health, environmental quality or ecological adaptations. Recent studies reported intraspecific variation in protein contents and biological activities of the hemolymph of honey bees related to their diet. Here we measured interspecific variation in three common bee species in the Mediterranean Basin with contrasting ecologies: Apis mellifera , Chalicodoma siculum, and Xylocopa pubescens . Despite all the bees were collected in the same area, we found important quantitative and qualitative variations of hemolymph extracts across species. Samples of A. mellifera and C. siculum had much higher protein concentration, anticancer, antimicrobial and antoxidant activities than samples of X. pubescens. This first descriptive study suggests life history traits of bee species have strong influences on their hemolymph properties and call for future large scale comparative analyses across more species and geographical areas.

Hemolymph proteome changes during worker brood development match the biological divergences between western honey bees (Apis mellifera) and eastern honey bees (Apis cerana) - Feng, Mao; Ramadan, Haitham; Han, Bin; Fang, Yu; Li, Jianke (BMC Genomics, 2014)
Background: Hemolymph plays key roles in honey bee molecule transport, immune defense, and in monitoring the physiological condition. There is a lack of knowledge regarding how the proteome achieves these biological missions for both the western and eastern honey bees (Apis mellifera and Apis cerana). A time-resolved proteome was compared using two-dimensional electrophoresis-based proteomics to reveal the mechanistic differences by analysis of hemolymph proteome changes between the worker bees of two bee species during the larval to pupal stages.Results: The brood body weight of Apis mellifera was significantly heavier than that of Apis cerana at each developmental stage. Significantly, different protein expression patterns and metabolic pathways were observed in 74 proteins (166 spots) that were differentially abundant between the two bee species. The function of hemolymph in energy storage, odor communication, and antioxidation is of equal importance for the western and eastern bees, indicated by the enhanced expression of different protein species. However, stronger expression of protein folding, cytoskeletal and developmental proteins, and more highly activated energy producing pathways in western bees suggests that the different bee species have developed unique strategies to match their specific physiology using hemolymph to deliver nutrients and in immune defense.Conclusions: Our disparate findings constitute a proof-of-concept of molecular details that the ecologically shaped different physiological conditions of different bee species match with the hemolymph proteome during the brood stage. This also provides a starting point for future research on the specific hemolymph proteins or pathways related to the differential phenotypes or physiology. © 2014 Feng et al.; licensee BioMed Central Ltd.
Keywords: Apis cerana cerana; Apis mellifera ligustica; Hemolymph; Larvae; Proteome; Pupae

Infrared (Ftir) spectral features of honey bee (apis mellifera L.) hemolymph - Horvatinec, Jelena; Svečnjak, Lidija (Journal of Central European Agriculture, 2020)
Hemolymph is a liquid of the open circulatory system of the honey bee (Apis mellifera L.) which represents a functional equivalent of vertebrate blood and lymph. The aim of this study was to determine the overall biochemical composition of honey bee hemolymph based on chemical characterization using Fourier transform infrared (FTIR) spectroscopy. Individual hemolymph samples of two age groups of workers (newly emerged bees-1 day old; foragers-42 days old) were collected by extraction from the thorax, and analysed by FTIR-ATR (Attentuated Total Reflectance) recording technique. The results have revealed a unique IR chemical fingerprint of honey bee hemolymph. Characteristic age-related spectral features indicating compositional variations between newly emerged bees and foragers were observed.
Keywords: Chemical characterization; FTIR-ATR spectroscopy; Hemolymph; Honey bee

Revisiting olfactory classical conditioning of the proboscis extension response in honey bees: A step toward standardized procedures - Matsumoto, Yukihisa; Menzel, Randolf; Sandoz, Jean Christophe; Giurfa, Martin (Journal of Neuroscience Methods, 2012)
The honey bee Apis mellifera has emerged as a robust and influential model for the study of classical conditioning thanks to the existence of a powerful Pavlovian conditioning protocol, the olfactory conditioning of the proboscis extension response (PER). In 2011, the olfactory PER conditioning protocol celebrated its 50. years since it was first introduced by Kimihisa Takeda in 1961. In this protocol, individually harnessed honey bees are trained to associate an odor with sucrose solution. The resulting olfactory learning is fast and induces robust olfactory memories that have been characterized at the behavioral, neuronal and molecular levels. Despite the success of this protocol for studying the bases of learning and memory at these different levels, innumerable procedural variants have arisen throughout the years, which render comparative analyses of behavioral performances difficult. Moreover, because even slight variations in conditioning procedures may introduce significant differences in acquisition and retention performances, we revisit olfactory PER conditioning and define here a standardized framework for experiments using this behavioral protocol. To this end, we present and discuss all the methodological steps and details necessary for successful implementation of olfactory PER conditioning. © 2012 Elsevier B.V.
Keywords: Honey bee; Insect; Invertebrate; Learning; Memory; Olfactory conditioning; Proboscis extension response (PER)

Invertebrate learning and memory: Fifty years of olfactory conditioning of the proboscis extension response in honeybees - Giurfa, Martin; Sandoz, Jean Christophe (Learning and Memory, 2012)
The honeybee Apis mellifera has emerged as a robust and influential model for the study of classical conditioning, thanks to the existence of a powerful Pavlovian conditioning protocol, the olfactory conditioning of the proboscis extension response (PER). In 2011, the olfactory PER conditioning protocol celebrates 50 years since it was first introduced by Kimihisa Takeda in 1961. Here, we review its origins, developments, and perspectives in order to define future research avenues and necessary methodological and conceptual evolutions. We show that olfactory PER conditioning has become a versatile tool for the study of questions in extremely diverse fields in addition to the study of learning and memory and that it has allowed behavioral characterizations, not only of honeybees, but also of other insect species, for which the protocol was adapted. We celebrate, therefore, Takeda's original work and prompt colleagues to conceive and establish further robust behavioral tools for an accurate characterization of insect learning and memory at multiple levels of analysis. © 2012 Cold Spring Harbor Laboratory Press.

Compound conditioning in honeybees: Blocking tests of the independence assumption - Funayama, E. S.; Couvillon, P. A.; Bitterman, M. E. (Animal Learning & Behavior, 1995)
Six experiments with color-odor compounds failed to produce convincing evidence of blocking in honeybees even when the possibility of masking by within-compound association could be discounted. The parsimonious assumption that the components of a compound stimulus gain and lose associative strength independently with reinforcement and nonreinforcement of the compounds (which the experiments were designed to challenge) remains tenable for color-odor compounds, although perhaps not for intramodal compounds. © 1995 Psychonomic Society, Inc.

Olfactory blocking and odorant similarity in the honeybee - Guerrieri, Fernando; Lachnit, Harald; Gerber, Bertram; Giurfa, Martin (Learning and Memory, 2005)
Blocking occurs when previous training with a stimulus A reduces (blocks) subsequent learning about a stimulus B, when A and B are trained in compound. The question of whether blocking exists in olfactory conditioning of proboscis extension reflex (PER) in honeybees is under debate. The last published accounts on blocking in honeybees state that blocking occurs when odors A and B are similar (the "similarity hypothesis"). We have tested this hypothesis using four odors (1-octanol, 1-nonanol, eugenol, and limonene) chosen on the basis of their chemical and physiological similarity (experiment 1). We established a generalization matrix that measured perceptual similarity. Bees in the "block group" were first trained with an odor A and, in the second phase, with the mixture AB. Bees in the "novel group" (control group) were first trained with an odor N and, in the second phase, with the mixture AB. After conditioning, bees in both groups were tested for their response to B. We assayed all 24 possible combinations for the four odors standing for A, B, and N. We found blocking in four cases, augmentation in two cases, and no difference in 18 cases; odor similarity could not account for these results. We also repeated the experiments with those six odor combinations that gave rise to the similarity hypothesis (experiment 2: 1-hexanol, 1-octanol, geraniol) and found augmentation in one and no effect in five cases. Thus, blocking is not a consistent phenomenon, nor does it depend on odor similarity. ©2005 by Cold Spring Harbor Laboratory Press.

Configural Olfactory Learning in Honeybees: Negative and Positive Patterning Discrimination - Deisig, Nina; Lachnit, Harald; Giurfa, Martin; Hellstern, Frank (2001)

Learning-related plasticity in PE1 and other mushroom body-extrinsic neurons in the honeybee brain - Okada, Ryuichi; Rybak, Jürgen; Manz, Gisela; Menzel, Randolf (Journal of Neuroscience, 2007)
Extracellular recording were performed from mushroom body-extrinsic neurons while the animal was exposed to differential conditioning to two odors, the forward-paired conditioned stimulus (CS+; the odor that will be or has been paired with sucrose reward) and the unpaired CS- (the odor that will be or has been specifically unpaired with sucrose reward). A single neuron, the pedunculus-extrinsic neuron number 1 (PE1), was identified on the basis of its firing pattern, and other neurons were grouped together as non-PE1 neurons. PE1 reduces its response to CS+ and does not change its response to CS- after learning. Most non-PE1 neurons do not change their responses during learning, butsomedecrease, and one neuron increases its response to CS+. PE1 receives inhibitory synaptic inputs, and neuroanatomical studies indicate closely attached GABA-immune reactive profiles originating at least partially from neurons of the protocerebral-calycal tract (PCT). Thus, either the associative reduction of odor responses originates within the PE1 via a long-term depression (LTD)-like mechanism, or PE1 receives stronger inhibition for the learned odor from the PCT neurons or from Kenyon cells. In any event, as the decreased firing of PE1 correlates with the increased probability of behavioral responses, our data suggest that the mushroom bodies exert general inhibition over sensory-motor connections, which relaxes selectively for learned stimuli. Copyright © 2007 Society for Neuroscience.
Keywords: Associative learning; Associative plasticity; Extracellular recording; Mushroom body; Olfactory learning; PE1 neuron

New vistas on honey bee vision - Avarguès-Weber, Aurore; Mota, Theo; Giurfa, Martin; Avarguès-weber, Aurore (Apidologie, 2012)
The honey bee is a traditional animal model for the study of visual perception, learning, and memory. Extensive behavioral studies have shown that honey bees perceive, learn, and memorize colors, shapes, and patterns when these visual cues are paired with sucrose reward. Bee color vision is trichromatic, based on three photoreceptor types (S, M, L), which peak in the UV, blue, and green region of the spectrum. Perceptual color spaces have been proposed to account for bee color vision, and the anatomy of the visual neuropils in the bee brain was described to a large extent. In the last decade, conceptual and technical advances improved significantly our comprehension of visual processing in bees. At the behavioral level, unexpected cognitive visual capacities were discovered such as categorical and conceptual categorization. At the neurobiological level, molecular analyses of the compound eye revealed an intricate heterogeneity in the distribution of photoreceptors in the retina. Spatial segregation and integration of visual information in the bee brain has been analyzed at functional levels so far unexploited. These recent discoveries associated with the perspective of accessing the bee brain of harnessed bees while they perceive and learn visual cues open new avenues toward a comprehension of the neural substrates of visual perception and learning in bees. Understanding how the miniature brain of bees achieves sophisticated visual performances is a fundamental goal for the comparative study of vision and cognition. vision / visual processing / visual cognition / honey bee / Apis mellifera / insect / invertebrate

Smell and Aftersmell: Fast Calcium Imaging Dynamics of Honey Bee Olfactory Coding - Paoli, Marco; Wystrach, Antoine; Ronsin, Brice; Giurfa, Martin (2023)
Odour processing exhibits multiple parallels between vertebrate and invertebrate olfactory systems. Insects, in particular, have emerged as relevant models for olfactory studies because of the tractability of their olfactory circuits. Here, we used fast calcium imaging to track the activity of projection neurons in the honey bee antennal lobe (AL) during olfactory stimulation at high temporal resolution. We observed a heterogeneity of response profiles and an abundance of inhibitory activities, resulting in various response latencies and stimulus- specific post-odour neural signatures. Recorded calcium signals were fed to a mushroom body (MB) model constructed implementing the fundamental features of connectivity between olfactory projection neurons, Kenyon cells (KC), and MB output neurons (MBON). The model accounts for the increase of odorant discrimination in the MB compared to the AL and reveals the recruitment of two distinct KC populations that represent odorants and their aftersmell as two separate but temporally coherent neural objects. Finally, we showed that the learning- induced modulation of KC-to-MBON synapses can explain both the variations in associative learning scores across different conditioning protocols used in bees and the bees’ response latency. Thus, it provides a simple explanation of how the time contingency between the stimulus and the reward can be encoded without the need for time tracking. This study broadens our understanding of olfactory coding and learning in honey bees. It demonstrates that a model based on simple MB connectivity rules and fed with real physiological data can explain fundamental aspects of odour processing and associative learning.

Assessment of gustatory responses to different sugars in harnessed and free-moving bumblebee workers (Bombus terrestris) - Mommaerts, Veerle; Wäckers, Felix; Smagghe, Guy (Chemical Senses, 2013)
For bumblebee colony survival, sugar responses are crucial as nectar is the main carbohydrate source and flower choice is likely determined by sugar composition. This study used a bioassay both with harnessed and with free-moving workers of the bumblebee Bombus terrestris to study the gustatory response to the 3 major plant sugars by both groups. In harnessed workers of B. terrestris, a concentration of 5.5% of fructose and glucose was required to induce the proboscis extension reflex in 50% of the workers, whereas for sucrose, a much higher concentration of 40% was needed. In contrast, free-moving workers given a choice between 30% glucose, 30% sucrose, 30% fructose, and water showed a strong preference for sucrose (66% of individuals) compared with 18% for glucose and 16% for fructose; water was never chosen. Familiarization with 30% fructose provoked a significant increase in preference toward fructose, indicating plasticity. In addition, by amputation of the tarsi, it was found that tarsi plays a role in the sugar response with especially the foreleg tarsi being involved in the response to fructose. Our results demonstrated that sugar response is different in free-moving versus harnessed bumblebee workers and that tarsi plays a role in sugar perception. © The Author 2013. Published by Oxford University Press. All rights reserved.
Keywords: Bombus terrestris; Harnessed bumblebees; Plant sugars; Sugar response; Tarsi; Taste

IMPAIRMENT OF A CLASSICAL CONDITIONED RESPONSE OF THE HONEY BEE (APIS MELLIFERA L.) BY SUBLETHAL DOSES OF SYNTHETIC PYRETHROID INSECTICIDES - Taylor, Kevin S; Waller, Gordon D; Crowder, Larry A
A classical conditioning experiment was used to compare the odor-mediated learned responses of honey bees (Apis mellifera L.) previously exposed to one of 6 pyrethroid insecticides dissolved in acetone with the responses of bees exposed only to acetone. Untreated bees showed a relatively steep acquisition slope following training bouts 1-3, and then an asymptote in response of ca 90 % positive responses following training bouts 4-7. Pyrethroid-treated bees learned at a slower rate but continued to show an improvement in positive responses throughout the test. However, treated bees attained only ca 60 % positive responses after their seventh training bout. Odor training responses were least affected by fluvalinate and most seriously disrupted by flucythrinate and cyfluthrin ; permethrin, fenvalerate, and cypermethrin were intermediate in their effect on the conditioned response.

Olfactory perception in honeybees: Concatenated and mixed odorant stimuli, concentration, and exposure effects - Getz, Wayne M; Smith, Katherine B (J Comp Physiol A, 1991)
Here we present results obtained from 7 different series of experiments, all employing odor conditioning of proboscis extension in worker honeybees and each designed to address a particular question involving olfactory perception. The questions relate to: temporal complexity of odor cues; effects of concentration, suppression , and/or potentiation in mixture perception; acquisition and extinction rates, as well as levels of generalization associated with aliphatic compounds that have the same functional groups or same alkyl radical length; and the effects of continuous exposure to odorants in the first several days of adult life on various learning and discrimination tasks involving olfactory perception. From the data obtained in these experiments we were able to conclude the following: First, worker honeybees have a limited ability to perceive complex temporal odor-quality patterns in olfactory stimuli-they learn to associate the quality of only the last part of the stimulus with a sucrose reward. Second, we confirm that citral is qualitatively different in several perceptual contexts involving odor learning and conditioning and our results help elucidate the nature of these differences as they relate to learning, discrimination, mixture perception, and continuous exposure to particular odorants. Third, we appear to have uncovered some important perceptual differences between functional groups attached to the first as opposed to the second carbon atom of alkyl radicals. Finally, we failed to uncover any significant effects relating to continuous exposure to odorants during the first several days of a worker's adult life, despite evidence that considerable sensory development takes place during this period. Thus ontogenetic changes to the peripheral system due to environmental effects appear to leave basic perceptual systems unaltered.
Keywords: Differential conditioning; Learning; Proboscis exten-sion reflex

Comparing first- and third-person perspectives in early elementary learning of honeybee systems - Peppler, Kylie; Thompson, Naomi; Danish, Joshua; Moczek, Armin; Corrigan, Seth (Instructional Science, 2020)
Prior literature has begun to demonstrate that even young children can learn about complex systems using participatory simulations. This study disentangles the impacts of third-person perspectives (offered by traditional simulations) and first-person perspectives (offered by participatory simulations) on children’s development of such systems thinking in the context of the emergent complexity of honeybee nectar foraging. Specifically, we worked with three first-grade classrooms assigned to one of three conditions—instruction through use of a first-person perspective only, third-person perspective only, and integrated instruction—to engage ideas of complex systems thinking. In each condition, systems concepts were targeted through instruction and assessment. The integrated and third-person classrooms demonstrated significant gains while the first-person classroom showed gains that were not statistically significant, suggesting that third-person perspectives play a critical role in how children learn systems thinking. This work also puts forth a novel assessment design for young children using multiple-choice questions.
Keywords: Early elementary; Role-play; Science learning; Systems thinking; Technology

Lower secondary school students’ knowledge and understandings of bees - Yang, Daihu (Journal of Biological Education, 2023)
Bees play a pivotal role in maintaining ecosystems and securing food for humankind. As such, it is crucial to shape a scientific understanding of bees for school students at a young age so as to value and protect the little creatures. This study is intended to identify teenage students’ knowledge and understandings of bees in relation to structures, behaviours, functions, threatening factors and loss of bees, via interviews and a drawing test which were administered to a total of 73 seventh-graders from two classes in a lower secondary school. The findings reveal that some drawn bees’ external structures are most often missing, misplaced and erroneously quantified, suggesting a lack of holistic knowledge of bees’ external structures. A majority of students tend to equate bees with social bees and some barely conceive the messages that certain behaviours of bees communicate. Anthropomorphism is commonly used in representing and formulating their understandings of bees. Students’ statements demonstrate that some unproved and insubstantial factors are deemed as a threat to bees and that their anticipations of the impacts of bee loss are characterised by immediacy and directness. Based on these findings, the sources of their misconceptions and misunderstandings as well as some implications are illuminated in relation to bee teaching in biological education.
Keywords: Secondary school; bee; functions; structure; understanding

Ecological Psychology Meets Ecology: Apis mellifera as a Model for Perception-Action, Social Dynamics, and Human Factors - Chiovaro, Megan; Paxton, Alexandra (Ecological Psychology, 2020)
Previous ecological research on social dynamics has largely been conducted on human dyads; however, to provide support for Hume's touchstone, ecological psychologists must also investigate the perception-action and collective action capabilities of non-humans. This approach allows us to circumvent possible cognitivist interpretations of complex social phenomena by exploring social dynamics across organisms with a range of abilities. Here, we outline how the integration of ecology and ecological psychology will benefit ecological theory (i.e., by informing large scale human collective coordination) and the way we engineer collaborative human groups. To demonstrate the benefits of this avenue of research, we detail the well-studied communication system of the western honey bee, Apis mellifera, and highlight the context-sensitivity and specificity of their communicative signals. We discuss two collective social phenomena in bees—swarming and task allocation—and how their study can inform human interpersonal dynamics. In order to use insects as a basis for improving human group coordination, we suggest that we must not only identify a suitable insect but also a particular phenomenon that shares the same values along critical dimensions of variability. We end by providing potential real-world implications of this disciplinary cross-pollination.

Honeybee cognition as a tool for scientific engagement - Denton, Jai A.; Koludarov, Ivan; Thompson, Michele; Bryk, Jarosław; Velasque, Mariana (Insects, 2021)
Apis mellifera (honeybees) are a well-established model for the study of learning and cognition. A robust conditioning protocol, the olfactory conditioning of the proboscis extension response (PER), provides a powerful but straightforward method to examine the impact of varying stimuli on learning performance. Herein, we provide a protocol that leverages PER for classroom-based community or student engagement. Specifically, we detail how a class of high school students, as part of the Ryukyu Girls Outreach Program, examined the effects of caffeine and dopamine on learning performance in honeybees. Using a modified version of the PER conditioning protocol, they demonstrated that caffeine, but not dopamine, significantly reduced the number of trials required for a successful conditioning response. In addition to providing an engaging and educational scientific activity, it could be employed, with careful oversight, to garner considerable reliable data examining the effects of varying stimuli on honeybee learning.
Keywords: Associative learning; Citizen science; Honeybee cognition; Honeybee learning; Memory; Proboscis extension response

Detection of coloured stimuli by honeybees: Minimum visual angles and receptor specific contrasts - Giurfa, M.; Vorobyev, M.; Kevan, P.; Menzel, R. (Journal of Comparative Physiology A: Sensory, Neural, and Behavioral Physiology, 1996)
Honeybees Apis mellifera were trained to distinguish between the presence and the absence of a rewarded coloured spot, presented on a vertical, achromatic plane in a Y-maze. They were subsequently tested with different subtended visual angles of that spot, generated by different disk diameters and different distances from the decision point in the device. Bees were trained easily to detect bee-chromatic colours, but not an achromatic one. Chromatic contrast was not the only parameter allowing learning and, therefore, detection: αmin, the subtended visual angle at which the bees detect a given stimulus with a probability P0 = 0.6, was 5° for stimuli presenting both chromatic contrast and contrast for the green photoreceptors [i.e. excitation difference in the green photoreceptors, between target and background (green contrast)], and 15° for stimuli presenting chromatic but no green contrast. Our results suggest that green contrast can be utilized for target detection if target recognition has been established by means of the colour vision system. The green-contrast signal would be used as a far-distance signal for flower detection. This signal would always be detected before chromatic contrast during an approach flight and would be learned in compound with chromatic contrast, in a facilitation-like process.
Keywords: Apis mellifera; Colour vision; Detection; Honeybees

Length of stimulus presentation and visual angle are critical for efficient visual PER conditioning in the restrained honey bee, Apis mellifera - Lichtenstein, Leonie; Lichtenstein, Matthias; Spaethe, Johannes (Journal of Experimental Biology, 2018)
Learning visual cues is an essential capability of bees for vital behaviors such as orientation in space and recognition of nest sites, food sources and mating partners. To study learning and memory in bees under controlled conditions, the proboscis extension response (PER) provides a well-established behavioral paradigm. While many studies have used the PER paradigm to test olfactory learning in bees because of its robustness and reproducibility, studies on PER conditioning of visual stimuli are rare. In this study, we designed a new setup to test the learning performance of restrained honey bees and the impact of several parameters: stimulus presentation length, stimulus size (i.e. visual angle) and ambient illumination. Intact honey bee workers could successfully discriminate between two monochromatic lights when the color stimulus was presented for 4, 7 and 10 s before a sugar reward was offered, reaching similar performance levels to those for olfactory conditioning. However, bees did not learn at shorter presentation durations. Similar to free-flying honey bees, harnessed bees were able to associate a visual stimulus with a reward at small visual angles (5 deg) but failed to utilize the chromatic information to discriminate the learned stimulus from a novel color. Finally, ambient light had no effect on acquisition performance. We discuss possible reasons for the distinct differences between olfactory and visual PER conditioning.
Keywords: Chromatic information; Color learning; Proboscis extension response; Vision; Visual cue

IMPAIRMENT OF A CLASSICAL CONDITIONED RESPONSE OF THE HONEY BEE (APIS MELLIFERA L.) BY SUBLETHAL DOSES OF SYNTHETIC PYRETHROID INSECTICIDES - Taylor, Kevin S; Waller, Gordon D; Crowder, Larry A (1987)
A classical conditioning experiment was used to compare the odor-mediated learned responses of honey bees (Apis mellifera L.) previously exposed to one of 6 pyrethroid insecticides dissolved in acetone with the responses of bees exposed only to acetone. Untreated bees showed a relatively steep acquisition slope following training bouts 1-3, and then an asymptote in response of ca 90 % positive responses following training bouts 4-7. Pyrethroid-treated bees learned at a slower rate but continued to show an improvement in positive responses throughout the test. However, treated bees attained only ca 60 % positive responses after their seventh training bout. Odor training responses were least affected by fluvalinate and most seriously disrupted by flucythrinate and cyfluthrin ; permethrin, fenvalerate, and cypermethrin were intermediate in their effect on the conditioned response.

Olfactory coding in honeybees - Paoli, Marco; Galizia, Giovanni C. (Cell and Tissue Research, 2021)
With less than a million neurons, the western honeybee Apis mellifera is capable of complex olfactory behaviors and provides an ideal model for investigating the neurophysiology of the olfactory circuit and the basis of olfactory perception and learning. Here, we review the most fundamental aspects of honeybee’s olfaction: first, we discuss which odorants dominate its environment, and how bees use them to communicate and regulate colony homeostasis; then, we describe the neuroanatomy and the neurophysiology of the olfactory circuit; finally, we explore the cellular and molecular mechanisms leading to olfactory memory formation. The vastity of histological, neurophysiological, and behavioral data collected during the last century, together with new technological advancements, including genetic tools, confirm the honeybee as an attractive research model for understanding olfactory coding and learning.
Keywords: Honeybee; Olfaction; Olfactory coding; Olfactory learning; Olfactory system

Olfactory perception in honeybees: Concatenated and mixed odorant stimuli, concentration, and exposure effects - Getz, Wayne M; Smith, Katherine B (J Comp Physiol A, 1991)
Here we present results obtained from 7 different series of experiments, all employing odor conditioning of proboscis extension in worker honeybees and each designed to address a particular question involving olfactory perception. The questions relate to: temporal complexity of odor cues; effects of concentration, suppression , and/or potentiation in mixture perception; acquisition and extinction rates, as well as levels of generalization associated with aliphatic compounds that have the same functional groups or same alkyl radical length; and the effects of continuous exposure to odorants in the first several days of adult life on various learning and discrimination tasks involving olfactory perception. From the data obtained in these experiments we were able to conclude the following: First, worker honeybees have a limited ability to perceive complex temporal odor-quality patterns in olfactory stimuli-they learn to associate the quality of only the last part of the stimulus with a sucrose reward. Second, we confirm that citral is qualitatively different in several perceptual contexts involving odor learning and conditioning and our results help elucidate the nature of these differences as they relate to learning, discrimination, mixture perception, and continuous exposure to particular odorants. Third, we appear to have uncovered some important perceptual differences between functional groups attached to the first as opposed to the second carbon atom of alkyl radicals. Finally, we failed to uncover any significant effects relating to continuous exposure to odorants during the first several days of a worker's adult life, despite evidence that considerable sensory development takes place during this period. Thus ontogenetic changes to the peripheral system due to environmental effects appear to leave basic perceptual systems unaltered.
Keywords: Differential conditioning; Learning; Proboscis exten-sion reflex

Effects of cold immobilization and recovery period on honeybee learning, memory, and responsiveness to sucrose - Frost, Elisabeth H.; Shutler, Dave; Hillier, Neil Kirk (Journal of Insect Physiology, 2011)
In addition to human error and variation in laboratory conditions, there are numerous factors that can complicate comparisons among studies. Furthermore, differences in how experimental methods are executed can make it difficult to distinguish between effects of focal versus extraneous variables. Insect neural function is commonly evaluated using Pavlovian conditioning techniques; learning and memory in many species can be assessed using the proboscis extension reflex (PER). However, there are significant inconsistencies in methods used to immobilize insects prior to PER tests. We compared responses of honeybees immobilized in a refrigerator, on ice, and in a freezer, and evaluated influence of recovery interval before testing. Ice-chilling weakly decreased learning (response to an originally neutral odor) more so than refrigeration or freezing, but not 24-h recall of odor. We found no significant differences in responsiveness to sucrose relative to cooling method, but responsiveness was significantly lower among honeybees left to recover for only 0.75. h versus 1.5 or 3. h. Finally, we observed increased responsiveness to sucrose and geraniol between June and August. Our results suggest that inconsistencies in cold immobilization methods could confound interpretation and comparison of results from a large body of work on honeybee learning and memory. © 2011 Elsevier Ltd.
Keywords: Cold immobilization; Honeybee; Proboscis conditioning; Recovery period; Sucrose response

Effects of different chilling procedures on honey bees (Apis mellifera) for anesthesia - Tutun, Hidayet; Sevin, Sedat; Çetintav, Bekir (Ankara Universitesi Veteriner Fakultesi Dergisi, 2020)
Immobilization is required for the examination and manipulation of honey bees (Apis mellifera), and many techniques have been developed to render honey bees immobile until this date. Among them, two methods, which are carbon dioxide (CO2) and low-temperature narcosis, have been commonly used to induce anesthesia on the bees. Although CO2-induced anesthesia changes the behavior and physiology of honey bees, the anesthesia induced by cold is considered commonly as non-damaging for the bees. There are a very limited number of studies on the effects of different chilling protocols in honey bees. Therefore, the purpose of this study was to investigate the effect of different chilling procedures on the survival rate and depth of anesthesia in honey bees. A total of 4 groups were formed, one of which was the control group. Three temperatures (+4°C,-20°C and-80°C) were applied to three different experimental groups. Furthermore, four different exposure times were implemented on each experimental group (n=20 worker bees in each trial). The depth of anesthesia was assessed and scored based on the movements and anesthesia recovery time in honeybees. There was a statistically significant relationship between duration and survival/death rate in the applications at +4°C,-20°C and-80°C (P<0.001). The method that was applied for 5 minutes at-20°C was the most ideal chilling method (P<0.03) and showed the lowest mortality in addition to the high depth of anesthesia. This study may assist in selecting the safest and deepest anesthesia method required in any study on honey bees.
Keywords: Anesthesia; Chilling; Honey bee

Effects of cold narcosis on memory acquisition, consolidation and retrieval in honeybees (Apis mellifera). - Chen, Yan Mei; Fu, Y.; He, Jing; Wang, Jian Hong (Dong wu xue yan jiu = Zoological research / "Dong wu xue yan jiu" bian ji wei yuan hui bian ji, 2014)
In learning and memory studies on honeybees (Apis mellifera), cold-induced narcosis has been widely used to temporarily immobilize honeybees. In this study, we investigated the effects of cold narcosis on the associative memories in honeybees by using the proboscis extension response (PER) paradigm. Severe impairments in memory acquisition was found when cold narcosis was performed 30 min, instead of 1 h before training. Locomotor activities were reduced when honeybees were tested 15 min, instead of 30 min after cold narcosis. These results indicate that cold narcosis impairs locomotor activities, as well as memory acquisition in a time-dependent manner, but by comparison no such effects on memory retrieval have yet been observed.[0].

Flight performance of actively foraging honey bees is reduced by a common pathogen - Wells, Trish; Wolf, Stephan; Nicholls, Elizabeth; Groll, Helga; Lim, Ka S.; Clark, Suzanne J.; Swain, Jennifer; Osborne, Juliet L.; Haughton, Alison J. (Environmental Microbiology Reports, 2016)
Sudden and severe declines in honey bee (Apis mellifera) colony health in the US and Europe have been attributed, in part, to emergent microbial pathogens, however, the mechanisms behind the impact are unclear. Using roundabout flight mills, we measured the flight distance and duration of actively foraging, healthy-looking honey bees sampled from standard colonies, before quantifying the level of infection by Nosema ceranae and Deformed Wing Virus complex (DWV) for each bee. Neither the presence nor the quantity of N. ceranae were at low, natural levels of infection had any effect on flight distance or duration, but presence of DWV reduced flight distance by two thirds and duration by one half. Quantity of DWV was shown to have a significant, but weakly positive relation with flight distance and duration, however, the low amount of variation that was accounted for suggests further investigation by dose-response assays is required. We conclude that widespread, naturally occurring levels of infection by DWV weaken the flight ability of honey bees and high levels of withincolony prevalence are likely to reduce efficiency and increase the cost of resource acquisition. Predictions of implications of pathogens on colony health and function should take account of sublethal effects on flight performance.

Learning and its neural correlates in a virtual environment for honeybees - Zwaka, Hanna; Bartels, Ruth; Lehfeldt, Sophie; Jusyte, Meida; Hantke, Sören; Menzel, Simon; Gora, Jacob; Alberdi, Rafael; Menzel, Randolf (Frontiers in Behavioral Neuroscience, 2019)
The search for neural correlates of operant and observational learning requires a combination of two (experimental) conditions that are very difficult to combine: stable recording from high order neurons and free movement of the animal in a rather natural environment. We developed a virtual environment (VE) that simulates a simplified 3D world for honey bees walking stationary on an air-supported spherical tread mill. We show that honeybees perceive the stimuli in the VE as meaningful by transferring learned information from free flight to the virtual world. In search for neural correlates of learning in the VE, mushroom body extrinsic neurons were recorded over days during learning. We found changes in the neural activity specific to the rewarded and unrewarded visual stimuli. Our results suggest an involvement of the mushroom body extrinsic neurons in operant learning in the honeybee (Apismellifera).
Keywords: Feedback neurons; GABA; Honey bee; Learning and memory; Mushroom body; Mushroom body extrinsic neurons; Operant learning; Virtual enviroment (VE)

Honeybees perform optimal scale-free searching flights when attempting to locate a food source - Reynolds, Andrew M.; Smith, Alan D.; Reynolds, Don R.; Carreck, Norman L.; Osborne, Juliet L. (Journal of Experimental Biology, 2007)
The foraging strategies used by animals are key to their success in spatially and temporally heterogeneous environments. We hypothesise that when a food source at a known location ceases to be available, flying insects will exhibit search patterns that optimise the rediscovery of such resources. In order to study these searching patterns, foraging honeybees were trained to an artificial feeder that was then removed, and the subsequent flight patterns of the bees were recorded using harmonic radar. We show that the flight patterns have a scale-free (Lévy-flight) characteristic that constitutes an optimal searching strategy for the location of the feeder. It is shown that this searching strategy would remain optimal even if the implementation of the Lévy-flights was imprecise due, for example, to errors in the bees' path integration system or difficulties in responding to variable wind conditions. The implications of these findings for animal foraging in general are discussed.
Keywords: Apis mellifera; Harmonic radar tracking; Honeybee; Imprecise Lévy-flight; Optimal search strategy

A lateralised design for the interaction of visual memories and heading representations in navigating ants - Wystrach, Antoine; Le Moël, Florent; Clement, Leo; Schwarz, Sebastian (2020)
The navigational skills of ants, bees and wasps represent one of the most baffling examples of the powers of minuscule brains. Insects store long-term memories of the visual scenes they experience 1 , and they use compass cues to build a robust representation of directions 2,3 . We know reasonably well how long-term memories are formed, in a brain area called the Mushroom Bodies (MB) 4–8 , as well as how heading representations are formed in another brain area called the Central Complex (CX) 9–12 . However, how such memories and heading representations interact to produce powerful navigational behaviours remains unclear 7,13,14 . Here we combine behavioural experiments with computational modelling that is strictly based on connectomic data to provide a new perspective on how navigation might be orchestrated in these insects. Our results reveal a lateralised design, where signals about whether to turn left or right are segregated in the left and right hemispheres, respectively. Furthermore, we show that guidance is a two-stage process: the recognition of visual memories – presumably in the MBs – does not directly drive the motor command, but instead updates a “desired heading” – presumably in the CX – which in turn is used to control guidance using celestial compass information. Overall, this circuit enables ants to recognise views independently of their body orientation, and combines terrestrial and celestial cues in a way that produces exceptionally robust navigation.

Artificial Life on a Dead Planet - Thorpe, Charles (Necroculture, 2016)

Classical olfactory conditioning in the oriental fruit fly, bactrocera dorsalise - Liu, Jia Li; Chen, Xiao Yan; Zeng, Xin Nian (PLoS ONE, 2015)
The oriental fruit fly, Bactrocera dorsalis, is a serious pest of fruits and vegetables. Methyl eugenol (ME), a male attractant, is used to against this fly by mass trapping. Control effect may be influenced by learning, which could modify the olfactory response of the fly to this attractant. To collect the behavioral evidence, studies on the capability of this fly for olfactory learning are necessary. We investigated olfactory learning in male flies with a classical olfactory conditioning procedure using restrained individuals under laboratory conditions. The acquisition of the proboscis extension reflex was used as the criterion for conditioning. A high conditioned response level was found in oriental fruit flies when an odor was presented in paired association with a sucrose reward but not when the odor and sucrose were presented unpaired. We also found that the conditioning performance was influenced by the odor concentration, intertrial interval, and starvation time. A slight sensitization elicited by imbibing sucrose was observed. These results indicate that oriental fruit flies have a high capacity to form an olfactory memory as a result of classical conditioning.

Bumblebee learning and memory is impaired by chronic exposure to a neonicotinoid pesticide - Stanley, Dara A.; Smith, Karen E.; Raine, Nigel E. (Scientific Reports, 2015)
Bumblebees are exposed to pesticides applied for crop protection while foraging on treated plants, with increasing evidence suggesting that this sublethal exposure has implications for pollinator declines. The challenges of navigating and learning to manipulate many different flowers underline the critical role learning plays for the foraging success and survival of bees. We assessed the impacts of both acute and chronic exposure to field-realistic levels of a widely applied neonicotinoid insecticide, thiamethoxam, on bumblebee odour learning and memory. Although bees exposed to acute doses showed conditioned responses less frequently than controls, we found no difference in the number of individuals able to learn at field-realistic exposure levels. However, following chronic pesticide exposure, bees exposed to field-realistic levels learnt more slowly and their short-term memory was significantly impaired following exposure to 2.4ppb pesticide. These results indicate that field-realistic pesticide exposure can have appreciable impacts on learning and memory, with potential implications for essential individual behaviour and colony fitness.

New method to Proboscis Extension Reflex to the assessment of gustatory responses for stingless bees - Nocelli, Roberta Cornélio Ferreira; Lourenço, Clara Tavares; Gheller, Sandra Eloisi Denardi-; Malaspina, Osmar; Pereira, Andrigo Monroe; Nominato, Fellipe Chaves (Revista Cincia, Tecnologia & Ambiente, 2018)
The proboscis extension reflex (PER) applied to restrained individuals is an important method to assess the sucrose responsiveness under laboratory conditions. Several authors have used the PER bioassay to assess behavioral effects of pesticides. A lot of them reported the difficult to use this method with non-Apis bees showing that this basic technique cannot be applied for all bees. The aim of this study was to evaluate the sucrose responsiveness of two brazilian stingless bees, Melipona scutellaris and Scaptotrigona postica using two different protocols: the traditional one and the new one where bees have free movements. In both cases, the bees were anesthetized (freezing) and inserted into plastic tubes with the tip cut out. After a starvation period were offered an increasing concentration of sucrose-water solution (w/v). Between the solutions, were offered water. With the traditional method, the sucrose responsiveness were observed only in M. scutellaris bees (12.5% of tested bees) in just one sucrose concentration (75%). Using the methodology with free movements, both species showed sucrose responsiveness in all concentrations (25%, 50% and 75%) tested. The number of M. scutellaris bees that had sucrose response ranged from 53.7% to 76.2% depending on the sucrose concentration. And the number of S. postica ranged from 54% to 79%. These results showed that using the methodology with free movements the sucrose responsiveness can be assessment non-Apis bees.

Olfactory learning in the stingless bee melipona eburnea friese (Apidae: Meliponini) - Amaya-Márquez, Marisol; Tusso, Sergio; Hernández, Juan; Jiménez, Juan Darío; Wells, Harrington; Abramson, Charles I. (Insects, 2019)
Olfactory learning and floral scents are co-adaptive traits in the plant–pollinator relationship. However, how scent relates to cognition and learning in the diverse group of Neotropical stingless bees is largely unknown. Here we evaluated the ability of Melipona eburnea to be conditioned to scent using the proboscis extension reflex (PER) protocol. Stingless bees did not show PER while harnessed but were able to be PER conditioned to scent when free-to-move in a mini-cage (fmPER). We evaluated the effect of: 1) unconditioned stimulus (US) reward, and 2) previous scent–reward associations on olfactory learning performance. When using unscented-US, PER-responses were low on day 1, but using scented-US reward the olfactory PER-response increased on day 1. On day 2 PER performance greatly increased in bees that previously had experienced the same odor and reward combination, while bees that experienced a different odor on day 2 showed poor olfactory learning. Bees showed higher olfactory PER conditioning to guava than to mango odor. The effect of the unconditioned stimulus reward was not a significant factor in the model on day 2. This indicates that olfactory learning performance can increase via either taste receptors or accumulated experience with the same odor. Our results have application in agriculture and pollination ecology.
Keywords: Cognitive ecology; Conditioning protocols; Free-moving-PER (fmPER); Learning; Olfactory conditioning; Pollinators; Scented-US; Stingless-bees

Sex and lifestyle dictate learning performance in a neotropical wasp - da Silva, Rafael Carvalho; Aguiar, João Marcelo Robazzi Bignelli Valente; Oi, Cintia Akemi; Batista, Jaqueline Eterna; Giurfa, Martin; do Nascimento, Fabio Santos (iScience, 2023)
In contrast to extensive investigations on bee cognition, the cognitive capacities of wasps remain largely unexplored despite their key role as pollinators and predators of insect pests. Here we studied learning and memory in the neotropical wasp Mischocyttarus cerberus using a Pavlovian conditioning in which harnessed wasps respond with conditioned movements of their mouthparts to a learned odorant. We focused on the different castes, sexes, and ages coexisting within a nest and found that adults of M. cerberus learned and memorized efficiently the odor-sugar associations. In contrast, newly emerged females, but not males, were unable to learn odorants. This difference concurs with their different lifestyle as young males perform regular excursions outside the nest while young females remain in it until older age. Our results thus highlight the importance of socio-ecological constraints on wasp cognition and set the basis for mechanistic studies on learning differences across ages and castes.
Keywords: Biological sciences; Ethology; Wildlife behavior

Issues in the study of proboscis conditioning - Abramson, Charles; Sokowski, Michel; Wells, Harrington (2011)

Assessment of the in vivo and in vitro release of chemical compounds from vespa velutina - Rodríguez-Flores, M. Shantal; Falcão, Soraia I.; Escuredo, Olga; Queijo, Luis; Seijo, M. Carmen; Vilas-Boas, Miguel (Molecules, 2021)
Vespa velutina has been rapidly expanding throughout Galicia since 2012. It is causing human health risks and well-known losses in the beekeeping sector. Control methods are scarce, unspecific, and ineffective. Semiochemicals are insect-derived chemicals that play a role in communication and they could be used an integrated pest management tool alternative to conventional pesticides. A previous determination of the organic chemical profile should be the first step in the study of these semiochemicals. HS-SPME in living individuals and the sting apparatus extraction followed by GC-MS spectrometry were combined to extract a possible profile of these compounds in 43 hornets from Galicia. The identified compounds were hydrocarbons, ketones, terpenes, and fatty acid, and fatty acid esters. Nonanal aldehyde appeared in important concentrations in living individuals. While pentadecane, 8-hexyl-and ethyl oleate were mainly extracted from the venom apparatus. Ketones 2-nonanone, 2-undecanone and 7-nonen-2-one, 4,8-dimethyl-were identified by both procedures, as was 1,7-Nonadiene, 4,8-dimethyl-. Some compounds were detected for the first time in V. velutina such as naphthalene, 1,6-dimethyl-4-(1-methylethyl). The chemical profile by caste was also characterized.
Keywords: HS-SPME/GC-MS; Nonanal; Pentadecane 8-hexyl-; Pest; Venom apparatus; Vespa velutina

COmparison of learning and memory of eastern (APIS Cerana Cerana) and western honey bees (APIS Mellifera L.) - Raza, M. F.; Li, Z.; Rizwan, M.; Aqai Kalan, H.; Su, S. (Applied Ecology and Environmental Research, 2019)
Honeybees are valuable pollinators strongly influencing ecosystem conservation, stability, genetic variation and ecological relationships in the floral diversity, plant community, evolution, and specialization. Honeybee is an excellent model organism for research on learning and memory among invertebrates. In their behavior, the subjective evaluation of a sucrose stimulus influences the behavioral performance. Here we report comparative behavioral data on the sensitization, habituation, short-term and long-term memory of Apis cerana and A. mellifera in China, using different sucrose concentrations. A. mellifera foragers have higher sucrose responsiveness than A. cerana foragers when tested using a proboscis extension response (PER) assay. Sensitization and habituation are well-known forms of non-associative learning. A. cerana took less number of habituation trials as compared to A. mellifera. Thus, these results significantly showed that A. cerana took less time to dishabituate. The sensitive stimuli of A. cerana against lemon extract were more than A. mellifera. In addition, although A. mellifera showed more sensitive stimuli against apple extract than A. cerana cerana, A. mellifera displayed significantly more learning and memory behavior than A. cerana after 2 and 24 hours.
Keywords: Honeybee; Odors; Olfactory learning; Proboscis extension response; Sensitization

CONFIDOR® SC350 | Proteccion de Cultivos | Agro Bayer Colombia - Bayer (2024)

Premier Pro - Adobe Inc (2024)

Rstudio - Posit Software, PBC (2024)

Correlation between concentration of hemolymph nutrients and amount of fat body consumed in lightly and heavily parasitized hosts (Pseudaletia separata) - Nakamatsu, Y.; Tanaka, T. (Journal of Insect Physiology, 2004)
Two states of parasitization in the Pseudaletia separata-Cotesia kariyai system were examined: one that was lightly parasitized and one that was heavily parasitized. We predicted that the consumption of fat body and hemolymph nutrients depends on the number of parasitoid larvae in the host. Lightly parasitized hosts (average clutch size±S.E.: 42.5±16.2, N=15) and heavily parasitized hosts (average clutch size±S.E.: 230.2±8.8, N=15) were prepared artificially. Eight days after parasitization, perivisceral fat body was depleted in the heavily parasitized host, although peripheral fat body was not yet consumed, but by day 10 most of the peripheral fat body was consumed. In lightly parasitized hosts, perivisceral fat body was not consumed by day 10. The parasitoid larvae deplete the perivisceral fat body first and then consume the peripheral fat body in the heavily parasitized host. The amount of trehalose, the major carbohydrate in the hemolymph, was related to the number of parasitoid larvae developing in the host. In a heavily parasitized host, trehalose concentrations remained low. However, in lightly parasitized hosts, the amount of trehalose increased 8 days after parasitization and then decreased by day 10. Protein and total lipid concentrations in the hemolymph of the heavily parasitized host were significantly lower than in lightly parasitized host on day 10, suggesting that the large number of parasitoid larvae depleted the fat body and hemolymph nutrients by day 10. High concentrations of total lipid on day 8 and 10 in lightly parasitized hosts and on day 8 in heavily parasitized host are likely to be attributed to the teratocytes. © 2003 Elsevier Ltd. All rights reserved.
Keywords: Fat body; Gregarious endoparasitoid; Koinobiont; Parasitoid clutch size; Teratocyte

The transition from diet to blood: Exploring homeostasis in the insect haemolymph nutrient pool - Holdbrook, Robert; Andongma, Awawing A.; Randall, Joanna L.; Reavey, Catherine E.; Tummala, Yamini; Wright, Geraldine A.; Simpson, Stephen J.; Smith, Judith A.; Wilson, Kenneth; Cotter, Sheena C. (Physiological Entomology, 2024)
Nutrition is vital to health, but while the link between diet and body nutritional composition is well explored in humans and other vertebrates, this information is not well understood in insects, despite the vital roles they play in ecosystems, and their increasing use as experimental models. Here we used Nutritional Geometry to explore the rapid physiological response to ingested nutrients in the haemolymph nutritional profile of Spodoptera littoralis caterpillars. We ask whether blood nutrients are maintained homeostatically in the face of variable nutritional intake, or if regulation is more flexible for some nutrients than others (allostasis), which allows animals to adapt to stress by responding in a way that prioritises efficiency of responses in the face of trade-offs. Caterpillars were placed on 1 of 20 diets, systematically varying in their nutrient ratios (protein: carbohydrate) and density (calorie content), and their consumption was measured. After 48 h, caterpillars were bled, and the macronutrient (protein, carbohydrates and lipids) and nutrient metabolite (amino acids and simple sugars) content of the haemolymph was measured. Proteins comprised 93% of the haemolymph macronutrient pool on average and their concentration increased with protein eaten. The amino acid (AA) pool was dominated by five AAs, and the total pool increased with total nutrient intake. However, the ratio of essential to non-essential AAs increased as the proportion of protein consumed increased. Carbohydrates were tightly controlled, increasing only on the most extreme carbohydrate intakes. Simple sugars were dominated by glucose and trehalose, and overall, the simple sugar pool showed high levels of homeostasis. Rather than strict homeostasis of blood nutritional properties, an allostatic model seemed to be a better fit for blood nutrient regulation in this generalist herbivore. This flexibility in response to the nutritional composition of the diet may, in part, explain how this species has evolved to extreme dietary generalism and may play a role in its worldwide pest status. Given the range of fitness-related processes affected by the haemolymph, future studies should examine the physiological impacts of blood nutrient variation on reproduction, growth and response to infection and the trade-offs between them.
Keywords: Spodoptera; allostasis; haemolymph nutrients; homeostasis; nutritional ecology; nutritional geometry

Changes in composition and levels of hemolymph proteins during metamorphosis of Manduca sexta - Cao, Xiaolong; Wang, Yang; Rogers, Janet; Hartson, Steve; Kanost, Michael R.; Jiang, Haobo (Insect Biochemistry and Molecular Biology, 2020)
The tobacco hornworm, Manduca sexta, is a lepidopteran model species widely used to study insect biochemical processes. Some of its larval hemolymph proteins are well studied, and a detailed proteomic analysis of larval plasma proteins became available in 2016, revealing features such as correlation with transcriptome data, formation of immune complexes, and constitution of an immune signaling system in hemolymph. It is unclear how the composition of these proteins may change in other developmental stages. In this paper, we report the proteomes of cell-free hemolymph from prepupae, pupae on day 4 and day 13, and young adults. Of the 1824 proteins identified, 907 have a signal peptide and 410 are related to immunity. Drastic changes in abundance of the storage proteins, lipophorins and vitellogenin, for instance, reflect physiological differences among prepupae, pupae, and adults. Considerably more proteins lacking signal peptide are present in the late pupae, suggesting that plasma contains relatively low concentrations of intracellular components released from remodeling tissues during metamorphosis. The defense proteins detected include 43 serine proteases and 11 serine protease homologs. Some of these proteins are members of the extracellular immune signaling network found in feeding larvae, and others may play additional roles and hence confer new features in the later life stages. In summary, the proteins and their levels revealed in this study, together with their transcriptome data, are expected to stimulate focused explorations of humoral immunity and other physiological systems in wandering larvae, pupae, and adults of M. sexta and shed light upon functional and comparative genomic research in other holometabolous insects.
Keywords: Hemolymph proteins; Insect immunity; LC-MS/MS; Protein processing

OPTIMIZED CENTRIFUGATION PREPARATION OF THE PLATELET RICH PLASMA : LITERATURE REVIEW - Croisé, Benjamin; Paré, Arnaud; Joly, Aline; Louisy, Agathe; Laure, Boris; Goga, Dominique; Croise, Benjamin (2019)
Nowadays, the Platelet Rich Plasma (PRP) is frequently used for its therapeutic effects on wound healing, and this due to secretion of many growth factors. However, no standardized procedure has been set up. The aim of this article is to check the various preparations (centrifugation time and speed). This review recorded all the international articles published between 2007 and 2018, for which the assessment criteria were the platelet concentration and /or the growth factor release rate. A multitude of protocols has been looked at with a simple or double centrifugation. All of them have shown an increase in the platelet concentration allowing a therapeutic effect. However, when the centrifugation force is extended, platelets can possibly be altered. The diversity of methods can be linked to the use of various centrifuges. A procedure with simple centrifugation would be a good compromise for the day-today use of the PRP in surgery.
Keywords: Platelet Rich Plasma; centrifugation; platelet concentration; preparation

A Modified Standardized Method to Extract and Store Insect Hemolymph with Use of a Glass Capillary - Migdał, Paweł; Murawska, Agnieszka; Roman, Adam (Journal of Apicultural Science, 2020)
Hemolymph is the "blood"circulating in the entire insect body. Analysis of this fluid gives information about the condition of the insect. The most precise analyses are conducted on insects' hemolymph suspended in 0.6% physiological saline (NaCl). Most current hemolymph extraction methods are either difficult or do not provide pure material, the contamination of collected insect "blood"can change results. This study aimed to develop a technique for extract hemolymph, both easy and without risk of contaminating derived material. The presented method is a modification of available ways to extract, store and transport hemolymph with the use of a glass capillary. For the development of this technique, adult worker honey bees (Apis mellifera L.) were used. The method required such basic equipment as a glass capillary, sterile tweezer, Eppendorf tube and physiological saline. The collected hemolymph were frozen and hence sent in a glass capillary to another laboratory for analysis.
Keywords: hemolymph; honey bee; insect; transporting hemolymph

The hemolymph proteome of the honeybee: Gel-based or gel-free? - Bogaerts, Annelies; Baggerman, Geert; Vierstraete, Evy; Schoofs, Liliane; Verleyen, Peter (Proteomics, 2009)
The honeybee has an invaluable economic impact and is a model for studying immunity, development and social behavior. The recent sequencing and annotation of the honeybee genome facilitates the study of its hemolymph, which reflects the physiological condition and mediates immune responses. We aimed at making a proteomic reference map of honeybee hemolymph and compared gel-free and gel-based techniques. One hundered and four 2-DE spots corresponding to 62 different proteins were identified. Eight identical 2-DLC experiments resulted in the identification of 32 unique proteins. One repeat was clearly not representative for the potential of the given 2-DLC setup. Only 27% of the identified hemolymph proteins were found by both techniques. In addition, we found proteins of three different viruses which creates possibilities for biomarker design. Future hemolymph studies will benefit from this work. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.
Keywords: 2-DE; 2-DLC; Hemolymph; Honeybee

Morphological and functional characterization of honey bee, Apis mellifera, hemocyte cell communities - Richardson, Rodney T.; Ballinger, Megan N.; Qian, Feng; Christman, John W.; Johnson, Reed M. (Apidologie, 2018)
Among invertebrates, cellular innate immunity is critical for wound healing and defense against parasites and pathogens. While the study of cellular immunity has received much attention in model insects, the study of hemocytes, including immune cells, in honey bees has received little attention. Much of our understanding of honey bee hemocytes is derived from a limited set of methodologies, predominately utilizing bright-field microscopy, which makes broad conclusions about honey bee cellular immunity difficult to infer. We build upon existing methodologies using differential cell staining, in vitro phagocytosis assays, and an analysis of respiratory burst activity as measured through reactive oxygen species (ROS) production. Further, we characterize the morphological diversity and functional capacity of honey bee hemocytes in both adult workers and young queen bees as well as the ontogeny of the hemocyte population across larval and adult stages of the worker caste. Our findings suggest that granulocytes are the major phagocytic cells in honey bees and that circulating larval granulocytes undergo mitotic cell division. Additionally, we demonstrate that ROS production in larval hemocytes can be stimulated with the protein kinase C activator, phorbol 12-myristate 13-acetate. This indicates the presence of a functional protein kinase C-dependent phagocyte oxidase system, though further experimentation is needed to confirm phagocyte oxidase as the source of ROS. Overall, this work expands our knowledge of honey bee hemocytes and provides additional methodological tools for studying immune mechanisms in insects.
Keywords: ROS production; cellular immunity; granulocytes; phagocytosis; plasmatocytes

Determining the hemolymoh volume of the cockroach. Pages 119-139, in Tested studies for laboratory teaching - Smith, J J B (ABLE, 1994)

Acute and oral exposure to imidacloprid does not affect the number of circulating hemocytes in the stingless bee Melipona quadrifasciata post immune challenge - Ravaiano, Samira Veiga; Barbosa, Wagner Faria; Tomé, Hudson Vaner Ventura; Campos, Lúcio Antônio de Oliveira; Martins, Gustavo Ferreira (Pesticide Biochemistry and Physiology, 2018)
In the present work, the effects of the neonicotinoid imidacloprid formulation on the total hemocyte counts (THC) and differential hemocyte counts (DHC) were investigated in foraging workers of the stingless bee Melipona quadrifasciata under (or not) the challenge with the bacteria Escherichia coli. The THC was not altered with the insecticide exposure and/or bacterial infection. However, the DHC of the bees changed with the imidacloprid exposure and/or bacterial infection. The number of prohemocytes (stem cells) increased in bees exposed to imidacloprid, but it did not change after the bacterial infection. The number of plasmatocytes (phagocytic cells) increased in imidacloprid-exposed and uninfected bees and decreased in infected bees regardless of the exposure to imidacloprid. On the other hand, there was a reduction of granulocytes, the most active immune cells, after imidacloprid exposure and an increase of granulocytes after the infection. Previous studies have shown that the neonicotinoids exposure can impair the immune system of bees. Our findings showed that the relative number of granulocytes declined with imidacloprid exposure, but the overall capacity of hemocyte responses in terms of total numbers after bacterial infection persisted even after the insecticide exposure.
Keywords: Cellular response; Insect immune system; Neonicotinoid; Wild bee

Method for collecting hemolymph of insects

Quantitative comparison of caste differences in honeybee hemolymph - Chan, Queenie W.T.; Howes, Charles G.; Foster, Leonard J. (Molecular and Cellular Proteomics, 2006)
The honeybee, Apis mellfera, is an invaluable partner in agriculture around the world both for its production of honey and, more importantly, for its role in pollination. Honeybees are largely unexplored at the molecular level despite a long and distinguished career as a model organism for understanding social behavior. Like other eusocial insects, honeybees can be divided into several castes: the queen (fertile female), Workers (sterile females), and drones (males). Each caste has different energetic and metabolic requirements, and each differs in its susceptibility to pathogens, many of which have evolved to take advantage of the close social network inside a colony. Hemolymph, arthropods' equivalent to blood, distributes nutrients throughout the bee, and the immune components contained within it form one of the primary lines of defense against invading microorganisms. In this study we have applied qualitative and quantitative proteomics to gain a better understanding of honeybee hemolymph and how it varies among the castes and during development. We found large differences in, hemplymph protein composition, especially between larval and adult stage bees and between male and female castes but even between adult workers and queens. We also provide experimental evidence for the expression of several unannotated honeybee genes and for the detection of biomarkers of a viral infection. Our data provide an initial molecular picture of honeybee hemolymph, to a greater depth than previous studies in other insects, and will pave the way for future biochemical studies of innate immunity in this animal. © 2006 by The American Society for Biochemistry and Molecular Biology, Inc.

Effect of the electric field at 50 Hz and variable intensities on biochemical markers in the honey bee’s hemolymph - Migdał, Paweł; Murawska, Agnieszka; Bieńkowski, Paweł; Strachecka, Aneta; Roman, Adam (PLoS ONE, 2021)
The amount of artificial electromagnetic fields of various parameters in the honey bee’s environment increases globally. So far, it had been proven that exposure to an E-field at 50 Hz can cause changes in bee’s behavior, alter the activity of proteases, and enzymatic antioxidants. Due to the potentially harmful effect of this factor on honey bees, we decided to investigate the activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP), and the concentration of albumin and creatinine in bee’s hemolymph after exposure to 50 Hz E-field. Honey bee workers were placed in wooden cages (200 × 150 × 70 mm) and exposed to the 50 Hz E-field with the intensity of <1, 5.0, 11.5, 23.0, or 34.5 kV/m for 1, 3, 6, or 12h. A homogeneous 50 Hz E-field was generated in the form of a plate capacitor. Hemolymph samples for analysis were taken immediately after the end of exposure to the E-field from 100 bees from each group. According to our study, the activity of AST, ALT, and ALP in honey bees’ hemolymph decreased after exposure to 50 Hz E-field with various intensities. The decrease in AST, ALT, and ALP activity intensified with prolonged exposure time. 50 Hz E-field may cause the impairment of crucial metabolic cycles in the honey bees’ organism (such as the citric acid cycle, ATP synthesis, oxidative phosphorylation, β-oxidation). Moreover, exposure to E-Field altered the concentration of creatinine and albumin, which are important non-enzymatic antioxidants. Such changes may indicate a disturbance in protein metabolism and increased muscle activity.

Imidacloprid markedly affects hemolymph proteolysis, biomarkers, DNA global methylation, and the cuticle proteolytic layer in western honeybees - Paleolog, Jerzy; Wilde, Jerzy; Siuda, Maciej; Bąk, Beata; Wójcik, Łukasz; Strachecka, Aneta (Apidologie, 2020)
Imidacloprid (IMD) may affect proteolysis, aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and global DNA methylation in honeybees. Queens, drones, and workers aged 1 or 20 days were exposed (free-flying colonies) to IMD (5 ppb and 200 ppb) in their diet. As a result, the colony depopulation did not occurred. IMD disturbed hemolymph/cuticle proteolysis; deactivated most of the cuticle protease inhibitors, activated hemolymph thiol and metal proteases and cuticle thiol proteases; downregulated ALP, ALT, AST; and increased DNA methylation in a caste- and age-dependent manner. The response in queens and workers differed, possibly due to eusocial evolution. Higher IMD dose had greater effects. The responses of ALP, ALT, AST, and DNA may reflect acceleration of biochemical senescence and epigenetic adaptation to IMD. All these biochemical side effects may lead to colony depopulation during future biotic/abiotic stress.
Keywords: DNA methylation; biomarker; honeybee; imidacloprid; proteolysis

Intraspecific Variability in Proteomic Profiles and Biological Activities of the Honey Bee Hemolymph - Elfar, Salma A.; Bahgat, Iman M.; Shebl, Mohamed A.; Lihoreau, Mathieu; Tawfik, Mohamed M. (Insects, 2023)
Pollinator declines have raised major concerns for the maintenance of biodiversity and food security, calling for a better understanding of environmental factors that affect their health. Here we used hemolymph analysis to monitor the health status of Western honey bees Apis mellifera. We evaluated the intraspecific proteomic variations and key biological activities of the hemolymph of bees collected from four Egyptian localities characterized by different food diversities and abundances. Overall, the lowest protein concentrations and the weakest biological activities (cytotoxicity, antimicrobial and antioxidant properties) were recorded in the hemolymph of bees artificially fed sucrose solution and no pollen. By contrast, the highest protein concentrations and biological activities were recorded in bees that had the opportunity to feed on various natural resources. While future studies should expand comparisons to honey bee populations exposed to more different diets and localities, our results suggest hemolymph samples can be used as reliable indicators of bee nutrition.
Keywords: anticancer; antimicrobial; antioxidant; honeybee; proteome

Hemolymph Metabolism Analysis of Honey Bee (Apis mellifera L.) Response to Different Bee Pollens - Chang, Hongcai; Ding, Guiling; Jia, Guangqun; Feng, Mao; Huang, Jiaxing (Insects, 2023)
Pollen is essential to the development of honey bees. The nutrients in bee pollen vary greatly among plant species. Here, we analyzed the differences in the amino acid compositions of pear (Pyrus bretschneideri), rape (Brassica napus), and apricot (Armeniaca sibirica) pollens and investigated the variation in hemolymph metabolites and metabolic pathways through untargeted metabolomics in caged adult bees at days 7 and 14. The results showed that the levels of five essential amino acids (isoleucine, phenylalanine, lysine, methionine, and histidine) were the highest in pear pollen, and the levels of four amino acids (isoleucine: 50.75 ± 1.93 mg/kg, phenylalanine: 87.25 ± 2.66 mg/kg, methionine: 16.00 ± 0.71 mg/kg and histidine: 647.50 ± 24.80 mg/kg) were significantly higher in pear pollen than in the other two kinds of bee pollen (p < 0.05). The number of metabolites in bee hemolymph on day 14 (615) was significantly lower than that on day 7 (1466). The key metabolic pathways of bees, namely, “sphingolipid metabolism (p = 0.0091)”, “tryptophan metabolism (p = 0.0245)”, and “cysteine and methionine metabolism (p = 0.0277)”, were significantly affected on day 7. There was no meaningful pathway enrichment on day 14. In conclusion, pear pollen had higher nutritional value among the three bee pollens in terms of amino acid level, followed by rape and apricot pollen, and the difference in amino acid composition among bee pollens was reflected in the lipid and amino acid metabolism pathways of early adult honey bee hemolymph. This study provides new insights into the physiological and metabolic functions of different bee pollens in bees.
Keywords: Apis melliferaL; amino acid; bee pollen; hemolymph; metabolomic

Chronic exposure to field-realistic doses of imidacloprid resulted in biphasic negative effects on honey bee physiology - Kim, Sanghyeon; Kim, Ju Hyeon; Cho, Susie; Lee, Do Eun; Clark, John Marshall; Lee, Si Hyeock (Insect Biochemistry and Molecular Biology, 2022)
There have been many investigations on the negative effects of imidacloprid (IMD) on honey bees. IMD is known to disrupt honey bee physiology and colony health at a relatively low concentration compared to other pesticides. In this study, honey bee colonies were chronically exposed to field-realistic concentrations (5, 20, and 100 ppb) of IMD, and the body weight, flight performance, carbohydrate reserve, and lipid contents of forager bees analyzed. Transcriptome analyses followed by quantitative PCR were also conducted for both nurse and forager bees to elucidate any changes in energy metabolism related to phenotypic disorders. The body weights of newly emerged and nurse bees showed decreasing tendencies as the IMD concentration increased. In forager bees, however, IMD induced a biphasic change in body weight: body weight was decreased at the lower concentrations (5 and 20 ppb) but increased at the higher concentration (100 ppb). Nevertheless, the flight capability of forager bees significantly decreased in a concentration-dependent manner. The effects of IMD on target gene transcription in forager bees showed biphasic patterns between low (5 and 20 ppb) and high (100 ppb) concentrations. Nurse bees showed typical features of premature transition to foragers in a concentration-dependent manner. When exposed to low concentrations, forager bees exhibited downregulation of genes involved in carbohydrate and lipid metabolism and in the insulin/insulin-like growth factor signaling pathway, upregulation of transporter activity, and a dose-dependent body weight reduction, which were similar to insulin resistance and diabetic symptoms. However, increased lipid metabolism and decreased energy metabolism with body weight gain were observed at high IMD concentration. Considered together, these results suggest that field-realistic doses of IMD alter honey bee energy metabolism in distinctly different ways at low and high concentrations, both of which negatively affect honey bee colony health.
Keywords: Biphasic effect; Carbohydrate metabolism; Chronic exposure; Diabetes; Honey bee; Imidacloprid

A high-throughput method of hemolymph extraction from adult Drosophila without anesthesia - MacMillan, Heath A.; Hughson, Bryon N. (Journal of Insect Physiology, 2014)
A rapid and cost-effective method of sampling hemolymph from the model insect Drosophila melanogaster is needed for studies in several fields, including ionoregulatory physiology, metabolism, immunology and toxicology. Here, we describe the construction and use of a device that uses airflow and pressure to manipulate adult flies and extract high-volume hemolymph samples. This method is rapid and inexpensive, and does not require cold or CO2 anesthesia at any point in the sampling process, thus avoiding the possible confounding effects of these treatments on the biochemical properties of the hemolymph sampled. To demonstrate one use for this method, we measure active concentrations of Na+ and K+ in isolated hemolymph droplets from individual adult D. melanogaster using an ion-selective microelectrode technique. © 2014 Elsevier Ltd.
Keywords: Circulation; Extracellular; Hemolymph; Ion balance; Metabolism

Hemolymph metabolism of black soldier fly (Diptera: Stratiomyidae), response to different supplemental fungi - Kannan, Mani; Vitenberg, Tzach; Schweitzer, Ron; Opatovsky, Itai (Journal of Insect Science, 2024)
The black soldier fly, Hermetia illucens L. (Diptera: Stratiomyidae), is commonly used for organic waste recycling and animal feed production. However, the often inadequate nutrients in organic waste necessitate nutritional enhancement of black soldier fly larvae, e.g., by fungal supplementation of its diet. We investigated the amino acid composition of two fungi, Candida tropicalis (Castell.) Berkhout (Saccharomycetales: Saccharomycetaceae) and Pichia kudriavzevii Boidin, Pignal & Besson (Saccharomycetales: Pichiaceae), from the black soldier fly gut, and commercial baker’s yeast, Saccharomyces cerevisiae Meyen ex E.C. Hansen (Saccharomycetales: Saccharomycetaceae), and their effects on larval growth and hemolymph metabolites in fifth-instar black soldier fly larvae. Liquid chromatography–mass spectrometry was used to study the effect of fungal metabolites on black soldier fly larval metabolism. Amino acid analysis revealed significant variation among the fungi. Fungal supplementation led to increased larval body mass and differential metabolite accumulation. The three fungal species caused distinct metabolic changes, with each over-accumulating and down-accumulating various metabolites. We identified significant alteration of histidine metabolism, aminoacyl-tRNA biosynthesis, and glycerophospholipid metabolism in BSF larvae treated with C. tropicalis. Treatment with P. kudriavzevii affected histidine metabolism and citrate cycle metabolites, while both P. kudriavzevii and S. cerevisiae treatments impacted tyrosine metabolism. Treatment with S. cerevisiae resulted in down-accumulation of metabolites related to glycine, serine, and threonine metabolism. This study suggests that adding fungi to the larval diet significantly affects black soldier fly larval metabolomics. Further research is needed to understand how individual amino acids and their metabolites contributed by fungi affect black soldier fly larval physiology, growth, and development, to elucidate the interaction between fungal nutrients and black soldier fly physiology.
Keywords: fungal supplementation; hemolymph metabolite; larval development; metabolomic analysis

A new method for quick and easy hemolymph collection from apidae adults - Borsuk, Grzegorz; Ptaszyńska, Aneta A.; Olszewski, Krzysztof; Domaciuk, Marcin; Krutmuang, Patcharin; Paleolog, Jerzy (PLoS ONE, 2017)
Bio-analysis of insects is increasingly dependent on highly sensitive methods that require high quality biological material, such as hemolymph. However, it is difficult to collect fresh and uncontaminated hemolymph from adult bees since they are very active and have the potential to sting, and because hemolymph is rapidly melanized. Here we aimed to develop and test a quick and easy method for sterile and contamination-free hemolymph sampling from adult Apidae. Our novel antennae method for hemolymph sampling (AMHS), entailed the detachment of an antenna, followed by application of delicate pressure to the bee's abdomen. This resulted in the appearance of a drop of hemolymph at the base of the detached antenna, which was then aspirated using an automatic pipetter. Larger insect size corresponded to easier and faster hemolymph sampling, and to a greater sample volume. We obtained 80-100 μL of sterile non-melanized hemolymph in 1 minute from one Bombus terrestris worker, in 6 minutes from 10 Apis mellifera workers, and in 15 minutes from 18 Apis cerana workers (+/-0.5 minutes). Compared to the most popular method of hemolymph collection, in which hemolymph is sampled by puncturing the dorsal sinus of the thorax with a capillary (TCHS), significantly fewer bees were required to collect 80-100 μL hemolymph using our novel AMHS method. Moreover, the time required for hemolymph collection was significantly shorter using the AMHS compared to the TCHS, which protects the acquired hemolymph against melanization, thus providing the highest quality material for biological analysis.

Refinement of a technique for collecting and evaluating the osmolality of haemolymph from Drosophila larvae - Kurio, Misato; Tsukasa, Yuma; Uemura, Tadashi; Usui, Tadao (2023)
ex vivo physiological experiments using small insect models such as Drosophila larvae have become increasingly useful to address fundamental biological questions. To perform such experiments, various artificial saline solutions have been developed, but their osmolality varies significantly from one to the next. Such a variation of osmolality stems, in part, from the difficulty of determining the true value of haemolymph osmolality in Drosophila larvae. Thus, there is a pressing need to refine protocols for collecting and measuring the osmolality of the larval haemolymph. Two major obstacles are thought to impede the accurate analysis of haemolymph collected from small insects: melanin formation and gut-derived contamination. Here, we greatly refined existing haemolymph collecting methods, evaluated the purity of the collected haemolymph under melanin-free conditions, and concluded that the true value of haemolymph osmolality is close to 306.0 mOsm kg −1 in Drosophila larvae.

Varroa destructor feeds primarily on honey bee fat body tissue and not hemolymph - Ramsey, Samuel D.; Ochoa, Ronald; Bauchan, Gary; Gulbronson, Connor; Mowery, Joseph D.; Cohen, Allen; Lim, David; Joklik, Judith; Cicero, Joseph M.; Ellis, James D.; Hawthorne, David; Van Engelsdorp, Dennis (Proceedings of the National Academy of Sciences of the United States of America, 2019)
The parasitic mite Varroa destructor is the greatest single driver of the global honey bee health decline. Better understanding of the association of this parasite and its host is critical to developing sustainable management practices. Our work shows that this parasite is not consuming hemolymph, as has been the accepted view, but damages host bees by consuming fat body, a tissue roughly analogous to the mammalian liver. Both hemolymph and fat body in honey bees were marked with fluorescent biostains. The fluorescence profile in the guts of mites allowed to feed on these bees was very different from that of the hemolymph of the host bee but consistently matched the fluorescence profile unique to the fat body. Via transmission electron microscopy, we observed externally digested fat body tissue in the wounds of parasitized bees. Mites in their reproductive phase were then fed a diet composed of one or both tissues. Mites fed hemolymph showed fitness metrics no different from the starved control. Mites fed fat body survived longer and produced more eggs than those fed hemolymph, suggesting that fat body is integral to their diet when feeding on brood as well. Collectively, these findings strongly suggest that Varroa are exploiting the fat body as their primary source of sustenance: a tissue integral to proper immune function, pesticide detoxification, overwinter survival, and several other essential processes in healthy bees. These findings underscore a need to revisit our understanding of this parasite and its impacts, both direct and indirect, on honey bee health.
Keywords: Apiculture; Fat body; Honey bee; Insect physiology; Varroa

A Simple Protocol for Isolating Hemolymph from Single Drosophila melanogaster Adult Flies - Jones, Kirah; Eleftherianos, Ioannis (Methods and Protocols, 2023)
Drosophila melanogaster is an excellent model for dissecting innate immune signaling and functions. Humoral and cellular immune mechanisms in the fly take place in the hemolymph, where host defense components are secreted and act in response to microbial invaders. Studying hemolymph factors is critical for understanding the regulation of the host’s antimicrobial immune system. Therefore, methods for extracting the fly hemolymph efficiently and in sufficient quantities are essential for isolating and characterizing immune proteins and peptides. Here, we describe a novel and simple hemolymph isolation protocol for single D. melanogaster male and female adults. This procedure substantially improves the already used technique and allows fly immunologists to explore innate immune hemolymph activity in D. melanogaster individuals.
Keywords: Drosophila; cellular response; hemolymph; humoral response; infection; innate immunity

An Efficient and Simple Method for Collecting Haemolymph of Cerambycidae (Insecta: Coleoptera) Adults - Niu, Yiming; Zhao, Yuxuan; Shi, Fengming; Li, Meng; Zhang, Sainan; Yang, Jinglin; Zong, Shixiang; Tao, Jing (Insects, 2023)
Cerambycid beetles (Cerambycidae) are major forest pests, posing a serious threat to the security of forest resources worldwide. Extensive research has focused on the control of cerambycid beetles from physiological and biochemical perspectives. Despite the important roles of insect haemolymph in physiological processes, efficient collection methods for Cerambycidae are lacking. For the efficient and easy collection of large amounts of pure haemolymph from adult cerambycid beetles, a new method, named net centrifugation, was developed. Three species of cerambycid beetles with large differences in size, Anoplophora chinensis, Monochamus saltuarius and Saperda populnea, were selected for the study. Haemolymph was collected by the newly developed net centrifugation method—in which an inner nylon net is used during centrifugation under optimised conditions, and a relatively small wound is generated on the insect—as well as the traditional tearing method and double centrifugation method. Among the three methods evaluated, the net centrifugation method caused the least damage to cerambycid beetles during the whole operation. This method resulted in the most haemolymph from a single beetle, with the lowest turbidity, mostly pure haemocytes in the precipitate, the clearest haemolymph smears by microscopy and the highest quality of RNA extracted from haemocytes. The net centrifugation method has a high collection efficiency, providing important technical support for haemolymph extraction and entomological research.
Keywords: Cerambycidae; centrifugation; cerambycid beetle; forestry pest; haemolymph

Isolation and molecular characterization of a major hemolymph serpin from the triatomine, Panstrongylus megistus - Moreira, Carlos Jc; Waniek, Peter J; Valente, Richard H; Carvalho, Paulo C; Perales, Jonas; Feder, Denise; Geraldo, Reinaldo B; Castro, Helena C; Azambuja, Patricia; Ratcliffe, Norman A; Mello, Cícero B (2014)
Background: Chagas disease kills 2.5 thousand people per year of 15 million persons infected in Latin America. The disease is caused by the protozoan, Trypanosome cruzi, and vectored by triatomine insects, including Panstrongylus megistus, an important vector in Brazil. Medicines treating Chagas disease have unpleasant side effects and may be ineffective, therefore, alternative control techniques are required. Knowledge of the T. cruzi interactions with the triatomine host needs extending and new targets/strategies for control identified. Serine and cysteine peptidases play vital roles in protozoan life cycles including invasion and entry of T. cruzi into host cells. Peptidase inhibitors are, therefore, promising targets for disease control.

Effects of stress on the hemolymph juvenile hormone binding protein titers of Manduca sexta - Tauchman, Seth J.; Lorch, Jeffrey M.; Orth, Anthony P.; Goodman, Walter G. (Insect Biochemistry and Molecular Biology, 2007)
External stressors disrupt physiological homeostasis; in insects, the response to stress may result in delayed development as the animal attempts to restore homeostasis before proceeding with its complex life cycle. Previous studies have demonstrated that exposure to stress leads to increased levels of the juvenile hormone (JH), a hormone responsible for maintaining the insect larval state. In Manduca sexta, JH is transported to target tissue by a high-affinity binding protein, hemolymph JH binding protein (hJHBP). Since JH titers are elevated in stressed Manduca, we examined levels of hJHBP to better understand (1) the role of JH in regulating hJHBP levels and (2) the hJHBP-regulated bioavailability of hormone at the target site. Fourth stadium Manduca (48 h post-ecdysis) were exposed for 24 h to various stressors including nutritional deprivation, microbial infection, cutaneous injury, episodic movement, and temperature elevation. Insects raised on diets lacking nutritional content exhibited mean hJHBP levels that were less than half (45%) those of control insects. Similarly, insects injected with Escherichia coli demonstrated a 47% reduction in hJHBP titers. Cutaneous injury, episodic movement, and temperature elevation lowered hJHBP levels by 47%, 43%, and 38%, respectively. Total hemolymph protein concentration was not affected. After a stress event (injury), a 50% reduction in abundance of fat body hJHBP mRNA was observed within 4 h; hJHBP levels did not drop until 24 h after injury. Stress in the fourth stadium was manifest in fifth instars, with 100% of the injured insects displaying an extended larval stadium or failing to pupate. Computational modeling of the JH-hJHBP interaction indicates that unbound JH doubles in stressed insects. These results indicate that in response to stress larval hJHBP titers are significantly reduced, increasing JH bioavailability at the target site and thereby impacting development and survival of the insect. Treatment of unstressed insects with physiological doses of JH I did not affect hJHBP levels, suggesting that elevated JH levels were not solely responsible for the observed down-regulation in stressed insects. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Carrier protein; Free hormone hypothesis; Hemolymph; Hormone transport; Larval development; Nutrition; Wound response

Protective effects of silkworm hemolymph extract and its fractions on UV-induced photoaging - Park, Ju Hyun; Lee, Ji Eun; Choi, Shin Sik; Park, Tai Hyun (Biotechnology and Bioprocess Engineering, 2017)
Ultraviolet (UV) irradiation induces skin photoaging by generating reactive oxygen species (ROS). ROS caused by UV-irradiation results in loss of skin cells and degradation of extracellular matrix. A number of antioxidants have been chemically synthesized or naturally extracted to prevent ROS-mediated skin photoaging. In our previous work, silkworm hemolymph extract (SHEX) was prepared, and its antioxidant activity was tested by free radical-scavenging assay. This study assessed the protective effects of SHEX on UV-induced photoaging of human immortalized keratinocytes (HaCaT). UVA (365 nm)-induced ROS generation was inhibited by supplementation of silkworm hemolymph (SH). Treatment with SHEX prepared by boiling SH inhibited death of HaCaT cells caused by UVB (315 nm) and UVA irradiation in a dose-dependent manner. Seven fractions were obtained by separating SHEX by gel permeation chromatography and the antioxidant activity of the fractions was examined. The fraction showing the highest protective efficacy on UV-induced cell damage corresponded to the lutein-containing fraction isolated in our previous study. Moreover, the SHEX fraction suppressed the expression of MMP-1 (matrix metalloproteinase-1), a matrix-degrading enzyme, suggesting that the active constituent of SHEX has the potential to inhibit skin photoaging. These results suggest that SHEX can be developed as a dietary and cosmetic supplement for prevention of skin photoaging.
Keywords: Silkworm hemolymph extract (SHEX); UV irradiation; antioxidant; reactive oxygen species (ROS); skin photoaging

Lipoprotein-induced phenoloxidase-activity in tarantula hemocyanin - Schenk, Sven; Schmidt, Juliane; Hoeger, Ulrich; Decker, Heinz (Biochimica et Biophysica Acta - Proteins and Proteomics, 2015)
Phenoloxidases play vital roles in invertebrate innate immune reactions, wound closure and sclerotization processes in arthropods. In chelicerates, where phenoloxidases are lacking, phenoloxidase-activity can be induced in the oxygen carrier hemocyanin in vitro by proteolytic cleavage, incubation with the artificial inducer SDS, or lipids. The role of protein-protein interaction has up to now received little attention. This is remarkable, as lipoproteins - complexes of proteins and lipids - are present at high concentrations in arthropod hemolymph. We characterized the three lipoproteins present in tarantula hemolymph, two high-density lipoproteins and one very high-density lipoprotein, and show that the two high-density lipoproteins have distinct structures: the more abundant high-density lipoprotein is an ellipsoid particle with axes of ~ 22.5 nm and ~ 16.8 nm, respectively. The second high-density lipoprotein, present only in trace amount, is a large discoidal lipoprotein with a diameter of ~ 38.4 nm and an on-edge thickness of ~ 7.1 nm. We further demonstrate that the interaction between lipoproteins and hemocyanin induces phenoloxidase activity in hemocyanin, and propose that this activation is due to protein-protein interaction rather than protein-lipid interaction, as neither lipid micelles nor lipid monomers were found to be activating. Activation was strongest in the presence of high-density lipoproteins; very high-density lipoproteins were found to be non-activating. This is the first time that the ability of lipoproteins to induce phenoloxidase activity of hemocyanin has been demonstrated, thus adding novel aspects to the function of lipoproteins apart from their known role in nutrient supply.
Keywords: Analytical ultracentrifugation; Dynamic light scattering; Fluorescence spectroscopy; Hemocyanin; Large discoidal lipoprotein; Phenoloxidase

Antioxidative properties of melanins and ommochromes from black soldier fly hermetia illucens - Ushakova, Nina; Dontsov, Alexander; Sakina, Natalia; Bastrakov, Alexander; Ostrovsky, Mikhail (Biomolecules, 2019)
A comparative study of melanin and ommochrome-containing samples, isolated from the black soldier fly (BSF) by enzymatic hydrolysis, alkaline and acid alcohol extraction or by acid hydrolysis, was carried out. Melanin was isolated both as a melanin-chitin complex and as a water-soluble melanin. Acid hydrolysis followed by delipidization yielded a more concentrated melanin sample, the electron spin resonance (ESR) signal of which was 2.6 × 1018 spin/g. The ommochromes were extracted from the BSF eyes with acid methanol. The antiradical activity of BSF melanins and ommochromes was determined by the method of quenching of luminol chemiluminescence. It has been shown that delipidization of water-soluble melanin increases its antioxidant properties. A comparison of the antioxidant activity of BSF melanins and ommochromes in relation to photoinduced lipid peroxidation was carried out. The ESR characteristics of native and oxidized melanins and ommochromes were studied. It is assumed that H. illucens adult flies can be a useful source of natural pigments with antioxidant properties.
Keywords: Antioxidant activity; Black soldier fly; ESR; Melanins; Ommochromes

Fluctuations of glucose levels in the haemolymph of fresh water Crab Barytelphusa cunicularis and its effect on Homeostasis - Jahan, Tasneem; Arbi, Suhani; Saad, Rehma; Zainab, Syeda; Fatima, Sundus
Crabs play an important roles in the food web of aquatic and terrestrial ecosystem. . The purpose of this study is to the investigate the mechanism of glucose regulation in crustacean crab Barytelphusa cunicularis. The present datasets were conducted to investigate glucose concentration in haemolymph, energy levels of the crabs when exposed to feeding environments, and stressed starvation during a 45-day culture period.

Microfluidic paper-based analytical device for determination of sucrose in sugarcane juice using Benedict’s reagent - Ratanawimarnwong, Nuanlaor; Suksomphot, Vanlada; Sornpipatpong, Khemika; Lengwan, Supamit; Donpudsa, Suchao; Choengchan, Nuthawut; Mantim, Thitirat (Analytical and Bioanalytical Chemistry, 2022)
This work presents a microfluidic paper-based analytical device (μPAD) for the determination of sucrose using the Benedict’s test. An asymmetric dumbbell-shaped hydrophobic barrier was produced by rubber stamping the barrier pattern onto a laboratory filter paper. Hydrochloric acid and solution containing sucrose were successively deposited onto the sample reservoir of the μPAD attached to a glass slide. The device was placed in a plastic bag and dipped into boiling water for accelerating the hydrolysis of sucrose into the reducing sugars. Then the Benedict’s reagent was added at the narrow straight channel connecting the two circular zones of the μPAD, which was replaced in the plastic bag and heated again for reduction of Cu(II) by the reducing sugars. Precipitate of brick-red copper(I) oxide was formed. The image of the μPAD was recorded by a smartphone. The ratio of the red to blue intensities gave linear correlation with the concentration of sucrose in the range of 0.5–10% w/v. The relative standard deviation of the measurement was less than 5% for 2 and 4% w/v sucrose (n = 10), with limit of determination, calculated using standard deviation of regression divided by slope of calibration, of 0.26% w/v sucrose. The method was successfully validated using the dinitrosalicylic acid method for sucrose measurement. Percent recoveries of sucrose were evaluated using ten sugarcane samples. The recoveries were in the range of 89 to 101%, demonstrating that there were no significant sample matrix effects on the quantification.
Keywords: Benedict’s reagent; Colorimetric detection; Microfluidic paper-based analytical device; Sucrose; Sugarcane juice

Spectral sensitivities of the orchid bee Euglossa dilemma - Figueiredo Dexheimer, Andreia; Outomuro, David; Dunlap, Aimee S; Morehouse, Nathan I (2022)
Manuscript_4ac0c673cfe9efa572571821b871fbc3 2 Diurnal pollinators often rely on color cues to make decisions when visiting flowers. Orchid bees are major tropical pollinators, with most studies of their pollination behavior to date focusing on scent collection and chemical ecology. The objective of this study was to measure their spectral sensitivities to preliminarily characterize color vision in the orchid bee Euglossa dilemma and compare it to the known spectral sensitivity of other closely related bees. We compared E. dilemma's spectral sensitivities and opsin protein sequences to four closely related corbiculate bees. E. dilemma appears to have trichromatic vision, with spectral sensitivity peaks in the ultraviolet, blue, and green wavelengths (347 ± 0.957 (SE) nm, 429 ± 6.570 nm, and 537 ± 1.183 nm, respectively), similar to other measured bees. We found no differences between male and female E. dilemma visual systems despite neuroanatomical and behavioral differences reported in the literature. The lambda maxes of the ultraviolet-sensitive photoreceptors appeared to be the most conserved among the bees we compared. Meanwhile, both the lambda maxes of the blue photoreceptors and the blue opsin proteins sequences were the least conserved. Our results open up new possibilities for the study of color vision and color-mediated pollination behaviors in orchid bees.
Keywords: corbiculate bees; opsin; pollination; sensory ecology; trichromacy; visual system

Why diversity matters for understanding the visual ecology and behaviour of bees - Somanathan, Hema (Current Opinion in Insect Science, 2024)
Two bee species, the European honeybee and the buff-tailed bumblebee, are well-developed models of visual behaviour and ecology. How representative of bees across phylogeny and geography are these two species? Bee sensory systems likely differ between temperate and tropical species due to differences in the intensity or the types of selection pressures. Differences in temperate and tropical floral diversity, abundance and seasonality can influence sensory adaptations and behaviours. Niche partitioning in the speciose tropics along the microhabitat and temporal axes is increasingly reported to involve special visual adaptations in bees. Inclusive approaches encompassing other bee species and building on lessons from the ‘model’ bees will inform how ecology shapes bee senses, and, in turn, the structure of plant–bee mutualisms.

Insect visual sensitivity to long wavelengths enhances colour contrast of insects against vegetation - Wang, Lu Yi; Stuart-Fox, Devi; Walker, Geoff; Roberts, Nicholas W.; Franklin, Amanda M. (Scientific Reports, 2022)
The sensitivity of animal photoreceptors to different wavelengths of light strongly influence the perceived visual contrast of objects in the environment. Outside of the human visual wavelength range, ultraviolet sensitivity in many species provides important and behaviourally relevant visual contrast between objects. However, at the opposite end of the spectrum, the potential advantage of red sensitivity remains unclear. We investigated the potential benefit of long wavelength sensitivity by modelling the visual contrast of a wide range of jewel beetle colours against flowers and leaves of their host plants to hypothetical insect visual systems. We find that the presence of a long wavelength sensitive photoreceptor increases estimated colour contrast, particularly of beetles against leaves. Moreover, under our model parameters, a trichromatic visual system with ultraviolet (λmax = 355 nm), short (λmax = 445 nm) and long (λmax = 600 nm) wavelength photoreceptors performed as well as a tetrachromatic visual system, which had an additional medium wavelength photoreceptor (λmax = 530 nm). When we varied λmax for the long wavelength sensitive receptor in a tetrachromatic system, contrast values between beetles, flowers and leaves were all enhanced with increasing λmax from 580 nm to at least 640 nm. These results suggest a potential advantage of red sensitivity in visual discrimination of insect colours against vegetation and highlight the potential adaptive value of long wavelength sensitivity in insects.

Methods of the Dehydration Process and Its Effect on the Physicochemical Properties of Stingless Bee Honey: A Review - Ikhsan, Liyana Nabihah; Chin, Kok Yong; Ahmad, Fairus (Molecules, 2022)
Stingless bee honey (SLBH) has a high moisture content, making it more prone to fermentation and leading to honey spoilage. Dehydration of SLBH after harvest is needed to reduce the moisture content. This review compiles the available data on the dehydration methods for SLBH and their effect on its physicochemical properties. This review discovered the dehydration process of vacuum drying at 60 °C and 5% moisture setting, freeze-drying at −54 °C and 5% moisture setting for 24 h, and using a food dehydrator at 55 °C for 18 h could extract >80% water content in SLBH. As a result, these methods could decrease moisture content to <17% and water activity to <0.6. These will prevent the fermentation process and microorganism growth. The hydroxymethylfurfural (HMF) contents remain within the permissible standard of <40 mg/kg. The total phenolic content increased after dehydration by these methods. Therefore, dehydration of SLBH is recommended to increase its benefits.
Keywords: chemical composition; dehydrated honey; dehydration method; stingless bee honey

Temperature Tolerance and Water Balance in Feral and Domestic Honey Bees, Apis mellifera L - Atmowidjojo, Anita H; Wheeler, Diana E; Erickson, Eric H; Cohen#, Allen C (Camp. Aiochem. Physiol, 1997)
Feral and domestic honey bees were compared to determine relative levels of adaptation to the Arizona desert. Feral honey bees were more tolerant to high temperatures than domestic honey bees. Monthly critical thermal maxima (CTMs) of feral bees were significantly different from rhose of domestic bees (P < 0.001). The highest mean CTM for feral bees was 50.7 ? l.O"C, and for domestic honey bees wab 42.8 t 2.8%; hoth were recorded in June 1991. Th ere was also a significant effect of sampling date on CTMs (P < 0.0001). Water loss increased with increasing temperature and with decreasing humidity for both feral and domestic honey bees. The rates of water loss for both types of bees were highest in dry air (0% relative humility) at 35"C, with the average value of 6.82-t 0.33 mg/g/h r or f d omestic bees. At 35"C, the rate of water loss of feral bees was more than twice that at 25°C (5.94 compared with 2.37 mg/g/hr). Water losses for feral and domesric honey bees were not significantly different; therefore, rates of water lilss do not explain the higher temperature tolerance of feral honey bees. COMP
Keywords: ADis mellifem; Honey bees; critical thermal maximum; domestic; feral; humidity; temperature; temperature tolerance; water balance

Honey bees save energy in honey processing by dehydrating nectar before returning to the nest - Nicolson, Susan W.; Human, Hannelie; Pirk, Christian W.W. (Scientific Reports, 2022)
Honey bees process nectar into honey by active evaporation on the tongue and passive evaporation involving nest ventilation and fanning behaviour, as well as enzymatic action. The elimination of excess water from nectar carries considerable energetic costs. The concentration of the nectar load is assumed to remain constant during transport. However, some of this water elimination may occur before foragers return to the nest and pass their nectar loads to receiver bees. In honey bees captured while foraging in Macadamia orchards, we show that the nectar in their crops has approximately twice the sugar concentration of the fresh nectar in flowers. This was true for four Macadamia cultivars, with up to 75% of the initial water content being removed. There is a further concentration increase in the crops of returning bees captured at the hive entrance. The only possible route of water elimination from the crop is via evaporation from the mouthparts. We calculate the savings in honey processing costs to be on average 35 times more than the reduction in flight costs due to reduced body mass. Pre-concentration of nectar in foraging honey bees may be widespread, and of crucial importance for honey storage.

A review on thermoregulation techniques in honey bees’ (Apis mellifera) beehive microclimate and its similarities to the heating and cooling management in buildings - Jarimi, Hasila; Tapia-Brito, Emmanuel; Riff, Saffa (Future Cities and Environment, 2020)
Apis mellifera – Apis, which is Latin for ‘bee’, and mellifera, which is Latin for ‘honey-bearing’ – refers to Western or European honey bees. Research shows that regardless of the ambient temperature, the in-hive microclimate of a beehive at the central brood area must be kept at the average optimum temperature of 35 °C for the colony to survive. Therefore, to survive both cold winters and hot summers, Apis mellifera will employ several heating and cooling strategies to thermoregulate their hives at the optimum tem-perature. Just like beehives, our buildings are designed with an envelope that is frequently viewed as the barrier that protects the internal occupied space from the impact of the external environment. We also employ similar methodologies to thermoregulate our buildings to reduce the heating and cooling load for less energy consumption while at the same time providing thermal comfort to the occupants. This paper presents the thermoregulation techniques employed by honey bees and the similarities to our buildings. Many similarities can be seen between the honey bees’ hive and our buildings’ thermal management sys-tem. However, we can still learn from the thermoregulation management demonstrated by the honey bees.
Keywords: Apis mellifera; Beehives; Human buildings; Thermoregulation techniques

Internal hive temperature as a means of monitoring honey bee colony health in a migratory beekeeping operation before and during winter - Meikle, William G.; Weiss, Milagra; Maes, Patrick W.; Fitz, William; Snyder, Lucy A.; Sheehan, Tim; Mott, Brendon M.; Anderson, Kirk E. (Apidologie, 2017)
Internal temperatures of honey bee hives kept at different sites in North Dakota were monitored before and during winter to evaluate the effects of treatment, in the form of exposure to commercial pollination, and location on colony health. In October, hives exposed to commercial pollination during the summer had fewer adult bees and less brood than hives kept near natural forage, as well as lower average temperatures throughout winter. Within-day temperature variability was higher among hives exposed to commercial agriculture than for those kept near natural forage, indicating reduced temperature control. Fungicides, insecticides, varroacides, and an herbicide were detected in bee bread and wax samples; no major differences were observed either in the diversity or in the concentrations of agrochemicals with the exception of chlorpyrifos at one site. Varroa and Nosema densities were low overall. Data from the same site used in successive years showed significantly more brood the first year, as well as lower temperature variability; high levels of chlorpyrifos were detected in bee bread of colonies in the second year. Colony average temperature and temperature variability were informative with respect to colony phenology and post-winter status.
Keywords: Hive temperature; Nosema; adult bee weight; bee colony phenology; brood production; pesticide residues; temperature amplitudes

Temperature Sensing and Honey Bee Colony Strength - Cook, Daniel; Tarlinton, Boyd; McGree, James M.; Blackler, Alethea; Hauxwell, Caroline (Journal of Economic Entomology, 2022)
Strength auditing of European honey bee (Apis mellifera Linnaeus, 1758 [Hymenoptera: Apidae]) colonies is critical for apiarists to manage colony health and meet pollination contracts conditions. Colony strength assessments used during pollination servicing in Australia typically use a frame-top cluster-count (Number of Frames) inspection. Sensing technology has potential to improve auditing processes, and commercial temperature sensors are widely available. We evaluate the use and placement of temperature sensing technology in colony strength assessment and identify key parameters linking temperature to colony strength. Custom-built temperature sensors measured hive temperature across the top of hive brood boxes. A linear mixed-effect model including harmonic sine and cosine curves representing diurnal temperature fluctuations in hives was used to compare Number of Frames with temperature sensor data. There was a significant effect of presence of bees on hive temperature and range: hives without bees recorded a 5.5°C lower mean temperature and greater temperature ranges than hives containing live bees. Hives without bees reach peak temperature earlier than hives with bees, regardless of colony strength. Sensor placement across the width of the hive was identified as an important factor when linking sensor data with colony strength. Data from sensors nearest to the hive geometric center were found to be more closely linked to colony strength. Furthermore, a one unit increase in Number of Frames was significantly associated with a mean temperature increase of 0.36°C. This demonstrates that statistical models that account for diurnal temperature patterns could be used to predict colony strength from temperature sensor data.
Keywords: Apis mellifera; honey bee; pollination; strength; temperature

The long summer: Pre-wintering temperatures affect metabolic expenditure and winter survival in a solitary bee - Sgolastra, Fabio; Kemp, William P.; Buckner, James S.; Pitts-Singer, Theresa L.; Maini, Stefano; Bosch, Jordi (Journal of Insect Physiology, 2011)
The impact of climate change on insect populations depends on specific life cycle traits and physiological adaptations. The solitary bee Osmia lignaria winters as a pre-emergent adult, and requires a period of cold temperature for winter diapause completion. It is a univoltine species, and diapause induction does not depend on photoperiod. To understand the potential effects of longer summers on O. lignaria populations, we exposed individuals to three treatments simulating early, mid and late winter arrivals, and measured respiration rates, metabolic expenditure, weight loss, fat body depletion, lipid levels and winter mortality. The early-winter treatment disrupted diapause development, but had no apparent negative effects on fitness. In contrast, late-winter bees had a greater energetic expenditure (1.5-fold), weight (1.4-fold) and lipid (2-fold) loss, greater fat body depletion, and a 19% increase in mortality compared to mid-winter bees. We also monitored adult eclosion and arrival of winter temperatures under natural conditions in four years. We found a positive correlation between mean degree-day accumulation during pre-wintering (a measure of asynchrony between adult eclosion and winter arrival) and yearly winter mortality. Individually, bees experiencing greater degree-day accumulations exhibited reduced post-winter longevity. Timing of adult eclosion in O. lignaria is dependent on the duration of the prepupal period, which occurs in mid-summer, is also diapause-mediated, and is longer in populations from southerly latitudes. In a global warming scenario, we expect long summer diapause phenotypes to replace short summer diapause phenotypes, effectively maintaining short pre-wintering periods in spite of delayed winter arrivals. © 2011 Elsevier Ltd.
Keywords: Adult diapause; Climate change; Energetic expenditure; Global warming; Megachilidae; Osmia lignaria

Metabolism and upper thermal limits of Apis mellifera carnica and A. m. ligustica - Kovac, Helmut; Käfer, Helmut; Stabentheiner, Anton; Costa, Cecilia (Apidologie, 2014)
The Western honeybees Apis mellifera carnica and A. m. ligustica are closely related subspecies living in neighbouring regions. Metabolism and the upper lethal thermal limits are crucial physiological traits, adapted in the evolutionary process to environment and climate conditions. We investigated whether samples from these two ecotypes differ in these traits. The standard metabolic rate was higher in the A. m. ligustica population only at a high temperature (Ta ~ 40 °C; dVCO2 = 12 nl s−1; P < 0.05), probably due to a higher body temperature (dTthorax = 1.5 °C; P < 0.01). The critical thermal maximum of activity and respiration was similar (difference activity CTmax = 0.8 °C, respiratory CTmax = 1.1 °C). The lethal temperature (LT50, 8h) revealed higher tolerance and survival rates of the Ligustica bees (Carnica 50.3 °C; Ligustica 51.7 °C; P < 0.02). Results reveal the adaptation of the two subspecies to their historic climate conditions, possibly favouring Ligustica in a warming environment.
Keywords: carnica; honeybee races; lethal temperature; ligustica; metabolic rate; respiration

Hypoxia-Controlled Winter Metabolism in Honeybees (Apis mellifera) - Nerum, Karel Van; Buelens, Herman (Biochem. Physiol, 1997)
Experiments during three winters have revealed a metabolism controlling function of bee-induced hypoxia in the winter cluster. Permanent low oxygen levels around 15% were found in its core. This hypoxia was actively controlled, probably via indirect mechanisms. Varying ambient oxygen levels demonstrated a causal relationship between lowered oxygen and reduced metabolic rate (MR). Under deeper ambient hypoxia the bees switched to ultra low MR (ULMR), optional-occasional at 15% oxygen, obligatory at 7.5% oxygen. This dormancy status resembled deep diapause in insects. It stayed reversible after at least several days, and was terminated under normal oxygen at 15°C. Reduced MR via core-hypoxia is essential in water conserving thermo-regulation of the wintering cluster. It allows bees to reconcile warm wintering in alert state-for defence of stores-with energy saving and longevity. Two further hypotheses discussed are that winter MR of bees might be related to insect diapause, and that in-body hypoxia might be functional in insect diapause. comp biochem physiol 117A;4:445-455, 1997.
Keywords: Apis mellifera; carbon dioxide; diapause; dormancy; hibernation; honey bee; hypoxia; metabolic rate; metabolism; oxygen; thermoregulation

Toxic temperatures: Bee behaviours exhibit divergent pesticide toxicity relationships with warming - Kenna, Daniel; Graystock, Peter; Gill, Richard J. (Global Change Biology, 2023)
Climate change and agricultural intensification are exposing insect pollinators to temperature extremes and increasing pesticide usage. Yet, we lack good quantification of how temperature modulates the sublethal effects of pesticides on behaviours vital for fitness and pollination performance. Consequently, we are uncertain if warming decreases or increases the severity of different pesticide impacts, and whether separate behaviours vary in the direction of response. Quantifying these interactive effects is vital in forecasting pesticide risk across climate regions and informing pesticide application strategies and pollinator conservation. This multi-stressor study investigated the responses of six functional behaviours of bumblebees when exposed to either a neonicotinoid (imidacloprid) or a sulfoximine (sulfoxaflor) across a standardised low, mid, and high temperature. We found the neonicotinoid had a significant effect on five of the six behaviours, with a greater effect at the lower temperature(s) when measuring responsiveness, the likelihood of movement, walking rate, and food consumption rate. In contrast, the neonicotinoid had a greater impact on flight distance at the higher temperature. Our findings show that different organismal functions can exhibit divergent thermal responses, with some pesticide-affected behaviours showing greater impact as temperatures dropped, and others as temperatures rose. We must therefore account for environmental context when determining pesticide risk. Moreover, we found evidence of synergistic effects, with just a 3°C increase causing a sudden drop in flight performance, despite seeing no effect of pesticide at the two lower temperatures. Our findings highlight the importance of multi-stressor studies to quantify threats to insects, which will help to improve dynamic evaluations of population tipping points and spatiotemporal risks to biodiversity across different climate regions.
Keywords: bumblebee; climate change; colony; flight; foraging; neonicotinoid; pollination; pollinator; responsiveness; sulfoximine; walking

Biophysical Ecology and Heat Exchange in Insects1 - Casey, Tlmothy M (Amer. Zool, 1992)
Synopsis. When used with observations of behavior and physiology of animals in known microclimates, a biophysical approach is a powerful tool for predicting body temperatures of insects. For ectothermic insects, solution ofthe energy budget equation and use of oper? ative temperature models have been used to determine the range of temperatures which an insect can exhibit in a given environment. Knowledge of body temperature has allowed predictions of when important behaviors are possible in the field, thereby directly relating biophysical models to fitness parameters of animals. A proper understanding of the phys? iological mechanism(s) controlling heat exchange is prerequisite to application and interpretation of information obtained using biophysical techniques. For endothermic insects, physiological regulation of heat exchange forces a more complicated analysis. Evaluation of thoracic heat exchange alone (aside from indicating whether insects are regulating Tth) is of little utility for either quantifying total heat exchange, or evaluating thermoregulatory mech? anisms without further information. Further studies of biophysics and physiology of endo? thermic insects during flight are needed to correct these deficiencies. Application of bio? physical techniques has allowed predictions of behavior of flying insects based on principles of heat exchange which cannot be examined directly. Analyses of endothermy of resting honeybee swarms and hives indicate that these "superorganisms" regulate temperature rather precisely over a remarkable range of environmental temperature using mechanisms equiv? alent to those used by resting endothermic vertebrates.

CONVECTIVE HEAT LOSS AND CHANGE IN BODY TEMPERATURE OF GRASSHOPPER AND LOCUST NYMPHS: RELATIVE IMPORTANCE OF WIND SPEED, INSECT SIZE AND INSECT ORIENTATION - Lactin, Derek J; Johnson, Dan L (J. therm. Eiol, 1998)
Ahstrati-I Grasshopper (Mefanoplus sanguinipes, M. bivittatus) and locust (Locusta migratoria migratorioides) (Orthoptera: Acrididae) nymphs were oriented at angles to the wind stream at four wind speeds. 2. Rates of temperature and energy change due to convection were measured after compensating for Stefan-Boltzmann radiative energy exchange. 3. The rate constant for Newton' s law of cooling, and the convective heat-transfer coefficient were both affected nonlinearly by insect size and wind speed, but were not significantly affected by insect orientation to the wind. 4. Comparison with published information suggests that the relationships observed apply widely within the animal kingdom. 0 1998 Department of Agriculture and Agri-Food. Published by Elsevier Science Ltd. All rights reserved a a0 A, b c CP c h h, LIST OF SYMBOLS Time constant Time constant where M = I g and U=O ms' Surface area of insect Exponent for effect of mass on a Exponent for effect of wind on a Specific heat capacity Rate of convective energy exchange Convective heat-transfer coefficient Convective heat-transfer coefficient where M = 1 g and U = 0 m .s-' Greybody heat exchange Exponent for effect of mass on h Exponent for effect of wind on h Absolute body temperature Absolute environmental temperature Insect mass Net rate of energy exchange External radiation, measured on a reference plane time Body temperature Air temperature Wind speed " c.s-' ." c-' " c.s-' ." C 1 m' J.g-'."C-' W.m-' w.m-' .OC-1 " c.s-l" .C-1 W.m-' K K g W.m-' W.m-* S "C "C m.s-'
Keywords: Acrididae; Key Word Index: Convection; Newton' s law of cooling; Orthoptera; biophysics; body temperature; convective heat-transfer coefficient; grasshopper; insect; locust

THERMOREGULATION AND HEAT EXCHANGE IN EUGLOSSINE BEES' - May, Michael L; Casey, Timothy M
The relations of the temperatures of the thorax (Tth), head (Th), and abdomen (Tab) to air temperature (T) are described for male euglossine bees attracted to baits. The large, pubescent bees in the genera Eulaema and Eufriesea regulated Tth fairly well, as indicated by the slope of T, on Ta; Th was distinctly elevated but probably not regulated; Tab was lowest and was most strongly elevated at high Ta, suggesting active heat transfer from the thorax. Euglossa spp., which are smaller and glabrous, regulated T, somewhat less effectively as a group; here, too, Th was elevated but not regulated; Tab was only slightly higher than Ta and gave no indication of active heat transfer. Measurements of heat-transfer coefficients as a function of size and wind velocity showed that pubescence is a moderately effective insulator of the thorax at wind speeds > 1.0 m s-'. Data on heat-transfer coefficients and body temperatures allowed rough estimation of total heat loss in the field. Heat loss values were consistent with independent measurements of oxygen consumption.

The plasticity of extracellular fluid homeostasis in insects - Beyenbach, Klaus W. (Journal of Experimental Biology, 2016)
In chemistry, the ratio of all dissolved solutes to the solution's volume yields the osmotic concentration. The present Review uses this chemical perspective to examine how insects deal with challenges to extracellular fluid (ECF) volume, solute content and osmotic concentration (pressure). Solute/volume plots of the ECF (hemolymph) reveal that insects tolerate large changes in all three of these ECF variables. Challenges beyond those tolerances may be 'corrected' or 'compensated'. While a correction simply reverses the challenge, compensation accommodates the challenge with changes in the other two variables. Most insects osmoregulate by keeping ECF volume and osmotic concentration within a wide range of tolerance. Other insects osmoconform, allowing the ECF osmotic concentration to match the ambient osmotic concentration. Aphids are unique in handling solute and volume loads largely outside the ECF, in the lumen of the gut. This strategy may be related to the apparent absence of Malpighian tubules in aphids. Other insects can suspend ECF homeostasis altogether in order to survive extreme temperatures. Thus, ECF homeostasis in insects is highly dynamic and plastic, which may partly explain why insects remain the most successful class of animals in terms of both species number and biomass.
Keywords: Anal papillae; Compensation; Correction; Environmental physiology; Gut; Hemolymph; Hyperosmotic challenge; Hypo-osmotic challenge; Intracellular fluid; Isosmotic; Malpighian tubules; Rectum; Solute/volume plots; Volume contraction; Volume expansion

Activities of Antioxidant and Proteolytic Systems and Biomarkers in the Fat Body and Hemolymph of Young Apis mellifera Females - Strachecka, Aneta; Kuszewska, Karolina; Olszewski, Krzysztof; Skowronek, Patrycja; Grzybek, Maciej; Grabowski, Marcin; Paleolog, Jerzy; Woyciechowski, Michał (Animals, 2022)
The proteolytic and antioxidant systems are important components of humoral immunity, and these biomarkers indicate the immune status. These compounds are synthesized in the bees' fat body and released into the hemolymph. Their functions maintain the organism's homeostasis and protect it against adverse environmental factors (including pathogens). We determined the activities of acidic, neutral, and alkaline proteases and their inhibitors, as well as superoxide dismutase (SOD), catalase (CAT), aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and the level of total antioxidant potential (TAC). These compounds were investigated in the fat body and hemolymph in the females with increased reproductive potential, i.e., queens and rebels, and in normal (non-reproductive sterile non-rebel) workers. The phenoloxidase (PO) activities were determined in the hemolymph. The normal workers had higher activities of proteases and their inhibitors, SOD and CAT, in the fat body and hemolymph, compared to the queens and rebels. The protease inhibitors were not usually active in the queens. As we predicted, the rebels revealed values between those of the queens and normal workers. The highest activities of proteases and antioxidants were identified in the fat body from the third tergite in comparison with the sternite and the fifth tergite. These results are important for oxidative stress ecology and give a better understanding of the functioning of the fat body and the division of labor in social insects. Simple Summary: The proteolytic system consists of compounds that, similar to “scissors”, cut proteins found in bee cells (e.g., to activate these proteins) or released by pathogens. During these reactions, reactive oxygen species are created and then removed by antioxidants. The actions of the proteolytic and antioxidant systems are enhanced by biomarkers. These compounds are produced mainly in the fat body and then released into the hemolymph. We determined the activities of these compounds in various localizations/segments of the fat body and in the hemolymph in females with increased reproductive potential, i.e., queens and rebels, and in normal (sterile non-rebel) workers. Rebels are workers who resemble the queen in terms of anatomical, behavioural, and physiological features. It was revealed that the activities of these compounds in the rebels were between those of queens and normal workers. Normal workers had higher activities of the proteolytic and antioxidant systems in the fat body and hemolymph than the other females. These results are important for understanding the functioning of the fat body, the stress ecology, and the formation of the different castes of Apis mellifera females.
Keywords: Antioxidant; Biomarkers; Fat body; Hemolymph; Honeybee; Inhibitor; Protease; Queen; Rebels; Workers

DISTRIBUTION OF HAEMOLYMPH IN THE HONEYBEE (APIS A~ELJ~IFICA) IN RELATION TO SEASON, AGE AND TEMPERATURE - Crailsheim, Karl (J. Insect Physiol, 1985)
[14C]Polyethylene glycol was proved to be a suitable marker for the determination of the extracellular space, which is identical with the volume of the haemolymph in insects. Bees kept at temperatures above 22°C show a fast circulation of haemolymph independent of the season. In winter at 5-25"C, immobilized isolated bees have a thoracic temperature which differs very little from that of the ambient. Under these conditions the time of mixing and the amount of haemolymph in head, thorax and abdomen depends on the temperature. At 5°C bees have much more haemolymph in their heads than at 25°C. At low temperatures the mixing time was increased and finally the mixing process was nearly stopped. Although bees are motionless at 5"C, limited activity of the circulatory system could be shown. The correlation between these distribution studies and the functional status of the bees within their colony is discussed.
Keywords: Key Word Index: Apis mellzjica; adaptation; haemolymph; polyethylene glycol; temperature; winter bees

Effective Permittivity of Biological Tissue: Comparison of Theoretical Model and Experiment - Gun, Li; Ning, Du; Liang, Zhang (Mathematical Problems in Engineering, 2017)
Permittivity of biological tissue is a critical issue for studying the biological effects of electromagnetic fields. Many theories and experiments were performed to measure or explain the permittivity characteristics in biological tissue. In this paper, we investigate the permittivity parameter in biological tissues via theoretical and experimental analysis. Firstly, we analyze the permittivity characteristic in tissue by using theories on composite material. Secondly, typical biological tissues, such as blood, fat, liver, and brain, are measured by HP4275A Multi-Frequency LCR Meter within 10 kHz to 10 MHz. Thirdly, experimental results are compared with the Bottcher-Bordewijk model, the Skipetrov equation, and the Maxwell-Gannett theory. From the theoretical perspective, blood and fat are regarded as the composition of liver and brain because of the high permittivity in blood and the opposite in fat. Volume fraction of blood in liver and brain is analyzed theoretically, and the applicability and the limitation of the models are also discussed. These results benefit further study on local biological effects of electromagnetic fields.

Body fluid volumes measurements by impedance: A review of bioimpedance spectroscopy (BIS) and bioimpedance analysis (BIA) methods - Jaffrin, Michel Y.; Morel, Hélène (Medical Engineering and Physics, 2008)
This paper reviews various bioimpedance methods permitting to measure non-invasively, extracellular, intracellular and total body water (TBW) and compares BIA methods based on empirical equations of the wrist-ankle resistance or impedance at 50 kHz, height and weight with BIS methods which rely on an electrical model of tissues and resistances measured at zero and infinite frequencies. In order to compare these methods, impedance measurements were made with a multifrequency Xitron 4200 impedancemeter on 57 healthy subjects which had undergone simultaneously a Dual X-ray absorptiometry examination (DXA), in order to estimate their TBW from their fat-free-mass. Extracellular (ECW) and TBW volumes were calculated for these subjects using the original BIS method and modifications of Matthie [Matthie JR. Second generation mixture theory equation for estimating intracellular water using bioimpedance spectroscopy. J Appl Physiol 2005;99:780-1], Jaffrin et al. [Jaffrin MY, Fenech M, Moreno MV, Kieffer R. Total body water measurement by a modification of the bioimpédance spectroscopy method. Med Bio Eng Comput 2006;44:873-82], Moissl et al. [Moissl UM, Wabel P, Chamney PW, Bosaeus I, Levin NW, et al. Body fluid volume determination via body composition spectroscopy in health and disease. Physiol Meas 2006;27:921-33] and their TBW resistivities were compared and discussed. ECW volumes were calculated by BIA methods of Sergi et al. [Sergi G, Bussolotto M, Perini P, Calliari I, et al. Accuracy of bioelectrical bioimpedance analysis for the assessment of extracellular space in healthy subjects and in fluid retention states. Ann Nutr Metab 1994;38(3):158-65] and Hannan et al. [Hannan WJ, Cowen SJ, Fearon KC, Plester CE, Falconer JS, Richardson RA. Evaluation of multi-frequency bio-impedance analysis for the assessment of extracellular and total body water in surgical patients. Clin Sci 1994;86:479-85] and TBW volumes by BIA methods of Kushner and Schoeller [Kushner RF, Schoeller DA. Estimation of total body water by bioelectrical impedance analysis. Am J Clin Nutr 1986;44(3):417-24], Lukaski et al. [Lukaski HC, Bolonchuk WW. Estimation of body fluid volumes using tetrapolar bioelectrical impedance measurements. Aviat Space Environ Med 1988;59:1163-9], Hannan et al. [Hannan WJ, Cowen SJ, Fearon KC, Plester CE, Falconer JS, Richardson RA. Evaluation of multi-frequency bio-impedance analysis for the assessment of extracellular and total body water in surgical patients. Clinical Science 1994;86:479-85], Deurenberg et al. [Deurenberg P, van der Koy K, Leenen R, Westrate JA, Seidell JC. Sex and age specific prediction formulas for estimating body composition from bioelectric impedance: a cross validation study. Int J Obesity 1991;15:17-25] These volumes were compared against those given by BIS method and, in the case of TBW, with those by DXA. For ECW, a good agreement was found between various BIS methods and that of Sergi while Hannan's values were higher. Both Matthie's and Moissl's methods gave mean TBW resistivities and volumes lower than those of Jaffrin's and DXA methods. Kushner et al. method gave values of TBW not significantly different from those of Jaffrin et al. and DXA, as Hannan's method in men, but Lukaski and Deurenberg methods led to an underestimation. © 2008 IPEM.
Keywords: Body fluid resistivity; Electrical modelling of tissues; Extracellular fluid; Total body water

Electrical conductivity of tissue at frequencies below 1 MHz - Gabriel, C.; Peyman, A.; Grant, E. H. (Physics in Medicine and Biology, 2009)
A two-pronged approach, review and measurement, has been adopted to characterize the conductivity of tissues at frequencies below 1 MHz. The review covers data published in the last decade and earlier data not included in recent reviews. The measurements were carried out on pig tissue, in vivo, and pig body fluids in vitro. Conductivity data have been obtained for skeletal and myocardial muscle, liver, skull, fat, lung and body fluids (blood, bile, CSF and urine). A critical analysis of the data highlights their usefulness and limitations and enables suggestions to be made for measuring the electrical properties of tissues. © 2009 Institute of Physics and Engineering in Medicine.

Impedance of Extracellular Fluid, Volume, and Local Tissue Water Can Be Reliably Measured in People With Lower Limb Lymphedema - Jönsson, Charlotta; Johansson, Karin; Bjurberg, Maria; Brogårdh, Christina (Physical Therapy, 2022)
Objective: Lower limb lymphedema (LLL) is a chronic condition. To be able to evaluate changes of LLL over time and effects of interventions, reliable measurement methods are important. Currently, there is limited knowledge of the reliability of commonly used measurement methods in LLL. The study objective was to evaluate the test-retest (intrarater) reliability of impedance of extracellular fluid, volume, and local tissue water measurements in people with unilateral or bilateral LLL and measurement errors both for a group of people and for a single individual. Methods: Forty-two people with mild to moderate unilateral or bilateral, primary or secondary LLL were measured twice, 2 weeks apart. Impedance of extracellular fluid was measured by bioimpedance spectroscopy and calculated as arm-to-leg ratio, volume with circumference measurements every 4 cm, and local tissue water with tissue dielectric constant at 14 points. Test-retest reliability was evaluated using the intraclass correlation coefficient [ICC(2,1)], changes in the mean, SE of measurement in relative terms (SEM%), and the smallest real difference in relative terms (SRD%). Results: For the impedance ratio, the reliability was high [ICC(2,1) = 0.79-0.90] and the measurement errors were acceptable (SEM% = 5.0%-5.2%; SRD% = 14.0%-14.4%). For volume, the reliability was high (ICC = 0.99) and the measurement errors were low (SEM% = 1.1%-1.7%; SRD% = 3.1%-4.6%). For the tissue dielectric constant, the reliability was fair to excellent [ICC(2,1) = 0.68-0.96] and the measurement errors were acceptable (SEM% = 4.2%-9.7%; SRD% = 11.7%-26.8%). Conclusions: Measurements of impedance of extracellular fluid, volume, and local tissue water are reliable in people with mild to moderate LLL. The measurement errors were acceptable in all 3 methods indicating that real, clinical changes in lymphedema can be measured both for a group of people and a single individual. Impact: The results from this test-retest reliability study can help clinicians and researchers to interpret if real clinical changes in lymphedema occur over time or after an intervention in people with mild to moderate LLL.
Keywords: Intrarater Reliability; Lower Limb; Lymphedema; Outcome Measures

Enhancing Tissue Impedance Measurements Through Modeling of Fluid Flow during Viscoelastic Relaxation - Veil, Carina; Muller, Daniel; Walz, Simon; Schule, Johannes; Somers, Peter; Tarin, Cristina; Stenzl, Arnulf; Sawodny, Oliver (IEEE Transactions on Biomedical Engineering, 2023)
Objective: Bladder cancer recurrence is an important issue after endoscopic urological surgeries. Additional sensor information such as electrical impedance measurements aim to support surgeons to ensure that the entirety of the tumor is removed. The foundation for differentiating lies in the altered sodium contents and cell structures within tumors that change their conductivity and permittivity. Mechanical deformations in the tissue expel fluid from the compressed area and pose a great difficulty, as they also lead to impedance changes. It is crucial to determine if this effect outweighs the alterations due to the tumorous tissue properties. Methods: Impedance measurements under ongoing viscoelastic relaxation are taken on healthy and tumorous tissue samples from human bladders and breasts. A fluid model to account for extra-and intracellular fluid flow under compression is derived. It is based on the fluid content within the individual tissue compartments and their outflow via diffusion. Results: After an initial deformation, the tissue relaxes and the impedance increases. The proposed model accurately represents these effects and validates the link between fluid flow under mechanical deformation and its impact on tissue impedance. A method to compensate for these undesired effects of fluid flow is proposed and the measurements are assessed in terms of differentiability between tumorous and healthy tissue samples. Conclusion: The electrical parameters are found to be promising for differentiation even under varying mechanical deformation, and the distinction is additionally improved by the proposed compensation approach. Significance: Electrical impedance measurements show great potential to support urologist during endoscopic surgeries.
Keywords: Electrical impedance spectroscopy; tissue differentiation; viscoelasticity

Extracellular and intracellular components of the impedance of neural tissue - Bedard, Claude; Piette, Charlotte; Venance, Laurent; Destexhe, Alain (Biophysical Journal, 2022)
Electric phenomena in brain tissue can be measured using extracellular potentials, such as the local field potential, or the electro-encephalogram. The interpretation of these signals depends on the electric structure and properties of extracellular media, but the measurements of these electric properties are still debated. Some measurements point to a model in which the extracellular medium is purely resistive, and thus parameters such as electric conductivity and permittivity should be independent of frequency. Other measurements point to a pronounced frequency dependence of these parameters, with scaling laws that are consistent with capacitive or diffusive effects. However, these experiments correspond to different preparations, and it is unclear how to correctly compare them. Here, we provide for the first time, impedance measurements (in the 1–10 kHz frequency range) using the same setup in various preparations, from primary cell cultures to acute brain slices, and a comparison with similar measurements performed in artificial cerebrospinal fluid with no biological material. The measurements show that when the current flows across a cell membrane, the frequency dependence of the macroscopic impedance between intracellular and extracellular electrodes is significant, and cannot be captured by a model with resistive media. Fitting a mean-field model to the data shows that this frequency dependence could be explained by the ionic diffusion mainly associated with Debye layers surrounding the membranes. We conclude that neuronal membranes and their ionic environment induce strong deviations to resistivity that should be taken into account to correctly interpret extracellular potentials generated by neurons.

Use of bioelectrical impedance spectroscopy to provide a measure of body composition in sows - Muller, T. L.; Ward, L. C.; Plush, K. J.; Pluske, J. R.; D'Souza, D. N.; Bryden, W. L.; van Barneveld, R. J. (Animal, 2021)
The ability to accurately estimate fat mass and fat-free mass (FFM) has the potential to improve the way in which sow body condition can be managed in a breeding herd. Bioelectrical impedance spectroscopy (BIS) has been evaluated as a practical technique for assessment of body composition in several livestock species, but similar work is lacking in sows. Bioelectrical impedance uses population-specific algorithms that require values for the apparent resistivities of body fluids and body proportion factors. This study comprised three major aims: (i) to derive apparent resistivity coefficients for extracellular water (ECW) and intracellular water (ICW) required for validation of BIS predictions of total body water (TBW) in live sows against standard reference tracer dilution methods; (ii) to develop predictions of TBW to body composition prediction algorithms, namely FFM, by developing a body geometry correction factor (Kb) and (iii) to compare the BIS predictions of FFM against existing impedance predictors and published prediction equations for use in sows, based on physical measurements of back-fat depth and BW (P2-based predictors). Whole body impedance measurements and the determination of TBW by deuterium dilution and ECW by bromide dilution were performed on 40 Large White x Landrace sows. Mean apparent resistivity coefficients of body fluids were 431.1 Ω.cm for ECW and 1827.8 Ω.cm for ICW. Using these coefficients, TBW and ECW were over-estimated by 6.5 and 3.3%, respectively, compared to measured reference values, although these differences were not statistically different (P > 0.05). Mean Kb was 1.09 ± 0.14. Fat-free mass predictions were 194.9 kg, which equates to 60.9% of total sow weight, and 183.0 kg for BIS and the deuterium dilution method, respectively. Mean differences between the predicted and measured FFM values ranged from − 8.2 to 32.7%, but were not statistically different (P > 0.05). Method validation (leave-one-out procedure) revealed that mean differences between predicted and measured values were not statistically significant (P > 0.05). Of the impedance-based predictors, equivalence testing revealed that BIS displayed the lowest test bias of 11.9 kg (8.2%), although the P2-based prediction equations exhibited the lowest bias and percentage equivalence, with narrow limits of agreement. Results indicate although differences between mean predicted and measured values were not significantly different, relatively wide limits of agreement suggest BIS as an impractical option for assessing body composition in individual sows compared to the use of existing prediction equations based on BW and back fat.
Keywords: Fat; Fat-free mass; Pig; Total body water; Tracer dilution

Thoracic electrical impedance tomography identifies heterogeneity in lungs associated with respiratory disease in cattle. A pilot study - Brabant, Olivia; Karpievitch, Yuliya V.; Gwatimba, Alphons; Ditcham, William; Ho, Ho Yin; Raisis, Anthea; Mosing, Martina (Frontiers in Veterinary Science, 2023)
Respiratory disease in cattle is a significant global concern, yet current diagnostic methods are limited, and there is a lack of crush-side tests for detecting active disease. To address this gap, we propose utilizing electrical impedance tomography (EIT), a non-invasive imaging technique that provides real-time visualization of lung ventilation dynamics. The study included adult cattle from farms in Western Australia. The cattle were restrained in a crush. A standardized respiratory scoring system, which combined visual, auscultation, and clinical scores, was conducted by two non-conferring clinicians for each animal. The scores were blinded and averaged. During assessment, an EIT electrode belt was placed around the thorax. EIT recordings of ten suitable breaths were taken for analysis before the cattle were released back to the herd. Based on the combined examination scoring, the cattle were categorized as having healthy or diseased lungs. To allow visual interpretation of each breath and enable the creation of the quartile ventilation ratio (VQR), Flow/Tidal Impedance Variation curves (F/TIV) were generated for each breath. The analysis focused on two EIT variables: The novel VQR over time during inhalation and exhalation and global expiratory impedance (TIVEXP) adjusted by breath length. A mixed effects model was used to compare these variables between healthy and diseased cattle. Ten adult cattle of mixed ages were used in the current analysis. Five cattle were scored as healthy and five as diseased. There was a significant difference in the examination scores between the healthy and diseased group (P = 0.03). A significant difference in VQR during inhalation (P = 0.03) was observed between the healthy and diseased groups. No difference was seen in VQR over time during exhalation (P = 0.3). The TIVEXP was not different between groups (P = 0.36). In this study, EIT was able to detect differences in inhalation mechanics when comparing healthy and diseased cattle as defined via clinical examination, highlighting the clinical utility of EIT.
Keywords: cattle; electrical impedance tomography; imaging; respiratory disease; thorax

Thoracic Electrical Impedance Tomography—The 2022 Veterinary Consensus Statement - Brabant, Olivia A.; Byrne, David P.; Sacks, Muriel; Moreno Martinez, Fernando; Raisis, Anthea L.; Araos, Joaquin B.; Waldmann, Andreas D.; Schramel, Johannes P.; Ambrosio, Aline; Hosgood, Giselle; Braun, Christina; Auer, Ulrike; et al. (Frontiers in Veterinary Science, 2022)
Electrical impedance tomography (EIT) is a non-invasive real-time non-ionising imaging modality that has many applications. Since the first recorded use in 1978, the technology has become more widely used especially in human adult and neonatal critical care monitoring. Recently, there has been an increase in research on thoracic EIT in veterinary medicine. Real-time imaging of the thorax allows evaluation of ventilation distribution in anesthetised and conscious animals. As the technology becomes recognised in the veterinary community there is a need to standardize approaches to data collection, analysis, interpretation and nomenclature, ensuring comparison and repeatability between researchers and studies. A group of nineteen veterinarians and two biomedical engineers experienced in veterinary EIT were consulted and contributed to the preparation of this statement. The aim of this consensus is to provide an introduction to this imaging modality, to highlight clinical relevance and to include recommendations on how to effectively use thoracic EIT in veterinary species. Based on this, the consensus statement aims to address the need for a streamlined approach to veterinary thoracic EIT and includes: an introduction to the use of EIT in veterinary species, the technical background to creation of the functional images, a consensus from all contributing authors on the practical application and use of the technology, descriptions and interpretation of current available variables including appropriate statistical analysis, nomenclature recommended for consistency and future developments in thoracic EIT. The information provided in this consensus statement may benefit researchers and clinicians working within the field of veterinary thoracic EIT. We endeavor to inform future users of the benefits of this imaging modality and provide opportunities to further explore applications of this technology with regards to perfusion imaging and pathology diagnosis.
Keywords: animals; chest; consensus; electrical impedance tomography; imaging

Electrical impedance myography detects age-related skeletal muscle atrophy in adult zebrafish - Rutkove, Seward B.; Callegari, Santiago; Concepcion, Holly; Mourey, Tyler; Widrick, Jeffrey; Nagy, Janice A.; Nath, Anjali K. (Scientific Reports, 2023)
Age-related deficits in skeletal muscle function, termed sarcopenia, are due to loss of muscle mass and changes in the intrinsic mechanisms underlying contraction. Sarcopenia is associated with falls, functional decline, and mortality. Electrical impedance myography (EIM)—a minimally invasive, rapid electrophysiological tool—can be applied to animals and humans to monitor muscle health, thereby serving as a biomarker in both preclinical and clinical studies. EIM has been successfully employed in several species; however, the application of EIM to the assessment of zebrafish—a model organism amenable to high-throughput experimentation—has not been reported. Here, we demonstrated differences in EIM measures between the skeletal muscles of young (6 months of age) and aged (33 months of age) zebrafish. For example, EIM phase angle and reactance at 2 kHz showed significantly decreased phase angle (5.3 ± 2.1 versus 10.7 ± 1.5°; p = 0.001) and reactance (89.0 ± 3.9 versus 172.2 ± 54.8 ohms; p = 0.007) in aged versus young animals. Total muscle area, in addition to other morphometric features, was also strongly correlated to EIM 2 kHz phase angle across both groups (r = 0.7133, p = 0.01). Moreover, there was a strong correlation between 2 kHz phase angle and established metrics of zebrafish swimming performance, including turn angle, angular velocity, and lateral motion (r = 0.7253, r = 0.7308, r = 0.7857, respectively, p < 0.01 for all). In addition, the technique was shown to have high reproducibility between repeated measurements with a mean percentage difference of 5.34 ± 1.17% for phase angle. These relationships were also confirmed in a separate replication cohort. Together, these findings establish EIM as a fast, sensitive method for quantifying zebrafish muscle function and quality. Moreover, identifying the abnormalities in the bioelectrical properties of sarcopenic zebrafish provides new opportunities to evaluate potential therapeutics for age-related neuromuscular disorders and to interrogate the disease mechanisms of muscle degeneration.

Electrical Impedance tomography – Recent applications and developments - Mansouri, Sofiene; Alharbi, Yousef; Haddad, Fatma; Chabcoub, Souhir; Alshrouf, Anwar; Abd-Elghany, Amr A. (Journal of Electrical Bioimpedance, 2021)
Electrical impedance tomography (EIT) is a low-cost noninvasive imaging method. The main purpose of this paper is to highlight the main aspects of the EIT method and to review the recent advances and developments. The advances in instrumentation and in the different image reconstruction methods and systems are demonstrated in this review. The main applications of the EIT are presented and a special attention made to the papers published during the last years (from 2015 until 2020). The advantages and limitations of EIT are also presented. In conclusion, EIT is a promising imaging approach with a strong potential that has a large margin of progression before reaching the maturity phase.
Keywords: Electrical impedance tomography; Image reconstruction; Imaging technique; Instrumentation; Medical applications

Transendothelial electrical resistance measurement across the blood–brain barrier: A critical review of methods - Vigh, Judit P.; Kincses, András; Ozgür, Burak; Walter, Fruzsina R.; Santa-Maria, Ana Raquel; Valkai, Sándor; Vastag, Mónika; Neuhaus, Winfried; Brodin, Birger; Dér, András; Deli, Mária A. (Micromachines, 2021)
The blood–brain barrier (BBB) represents the tightest endothelial barrier within the cardio-vascular system characterized by very low ionic permeability. Our aim was to describe the setups, electrodes, and instruments to measure electrical resistance across brain microvessels and culture models of the BBB, as well as critically assess the influence of often neglected physical and technical parameters such as temperature, viscosity, current density generated by different electrode types, surface size, circumference, and porosity of the culture insert membrane. We demonstrate that these physical and technical parameters greatly influence the measurement of transendothelial electrical resistance/resistivity (TEER) across BBB culture models resulting in severalfold differences in TEER values of the same biological model, especially in the low-TEER range. We show that elevated culture medium viscosity significantly increases, while higher membrane porosity decreases TEER values. TEER data measured by chopstick electrodes can be threefold higher than values measured by chamber electrodes due to different electrode size and geometry, resulting in current distribution inhomogeneity. An additional shunt resistance at the circumference of culture inserts results in lower TEER values. A detailed description of setups and technical parameters is crucial for the correct interpretation and comparison of TEER values of BBB models.
Keywords: Blood–brain barrier; Cell culture insert; Electrodes; Endothelial cell; Epithelial cell; Impedance; Lab-on-a-chip; Transendothelial electrical resistance; Viscosity

Advances in electrical impedance tomography-based brain imaging - Ke, Xi Yang; Hou, Wei; Huang, Qi; Hou, Xue; Bao, Xue Ying; Kong, Wei Xuan; Li, Cheng Xiang; Qiu, Yu Qi; Hu, Si Yi; Dong, Li Hua (Military Medical Research, 2022)
Novel advances in the field of brain imaging have enabled the unprecedented clinical application of various imaging modalities to facilitate disease diagnosis and treatment. Electrical impedance tomography (EIT) is a functional imaging technique that measures the transfer impedances between electrodes on the body surface to estimate the spatial distribution of electrical properties of tissues. EIT offers many advantages over other neuroimaging technologies, which has led to its potential clinical use. This qualitative review provides an overview of the basic principles, algorithms, and system composition of EIT. Recent advances in the field of EIT are discussed in the context of epilepsy, stroke, brain injuries and edema, and other brain diseases. Further, we summarize factors limiting the development of brain EIT and highlight prospects for the field. In epilepsy imaging, there have been advances in EIT imaging depth, from cortical to subcortical regions. In stroke research, a bedside EIT stroke monitoring system has been developed for clinical practice, and data support the role of EIT in multi-modal imaging for diagnosing stroke. Additionally, EIT has been applied to monitor the changes in brain water content associated with cerebral edema, enabling the early identification of brain edema and the evaluation of mannitol dehydration. However, anatomically realistic geometry, inhomogeneity, cranium completeness, anisotropy and skull type, etc., must be considered to improve the accuracy of EIT modeling. Thus, the further establishment of EIT as a mature and routine diagnostic technique will necessitate the accumulation of more supporting evidence.
Keywords: Brain diseases; Electrical impedance tomography (EIT); Microelectrode array; Tissue impedance

Recent advances in electrical impedance sensing technology for single-cell analysis - Zhang, Zhao; Huang, Xiaowen; Liu, Ke; Lan, Tiancong; Wang, Zixin; Zhu, Zhen (Biosensors, 2021)
Cellular heterogeneity is of significance in cell-based assays for life science, biomedicine and clinical diagnostics. Electrical impedance sensing technology has become a powerful tool, allowing for rapid, non-invasive, and label-free acquisition of electrical parameters of single cells. These electrical parameters, i.e., equivalent cell resistance, membrane capacitance and cytoplasm conductivity, are closely related to cellular biophysical properties and dynamic activities, such as size, morphology, membrane intactness, growth state, and proliferation. This review summarizes basic principles, analytical models and design concepts of single-cell impedance sensing devices, including impedance flow cytometry (IFC) to detect flow-through single cells and electrical impedance spectroscopy (EIS) to monitor immobilized single cells. Then, recent advances of both electrical impedance sensing systems applied in cell recognition, cell counting, viability detection, phenotypic assay, cell screening, and other cell detection are presented. Finally, prospects of impedance sensing technology in single-cell analysis are discussed.
Keywords: Electrical impedance spectroscopy; Impedance flow cytometry; Microfluidics; Single cell analysis

Smart Bio-Impedance-Based Sensor for Guiding Standard Needle Insertion - Kudashov, Ivan; Shchukin, Sergey; Al-Harosh, Mugeb; Shcherbachev, Andrew (Sensors, 2022)
A venipuncture is the most common non-invasive medical procedure, and is frequently used with patients; however, a high probability of post-injection complications accompanies intravenous injection. The most common complication is a hematoma, which is associated with puncture of the uppermost and lowermost walls. To simplify and reduce complications of the venipuncture procedure, and as well as automation of this process, a device that can provide information of the needle tip position into patient’s tissues needs to be developed. This paper presents a peripheral vascular puncture control system based on electrical impedance measurements. A special electrode system was designed to achieve the maximum sensitivity for puncture identification using a tradi-tional needle, which is usually used in clinical practice. An experimental study on subjects showed that the electrical impedance signal changed significantly once the standard needle entered the blood vessel. On basis of theoretical and experimental studies, a decision rule of puncture identification based on the analysis of amplitude-time parameters of experimental signals was proposed. The proposed method was tested on 15 test and 9 control samples, with the results showing that 97% accuracy was obtained.
Keywords: Electrical impedance; Electrode system; Puncture identification

Electric impedance spectroscopy feature extraction for tissue classification with electrode embedded surgical needles through a modified forward stepwise method - Kent, B.; Rossa, C. (Computers in Biology and Medicine, 2021)
There has been a growing interest in developing electric impedance sensing surgical tools for tissue identification during surgery. A key facet of this development is identifying distinct features that can be used to identify tissues from one another. This paper explores several feature extraction techniques and classification methods applied to electric impedance data. Furthermore, a modified forward stepwise method is proposed. The method introduces a scoring metric to help select features to add to the model, that is based off of the coefficient of variation and overlapping index from the feature's probability density functions for each of the classes. The proposed and existing methods were applied to spectral data measured at 23 frequencies, from 132 samples across 6 different tissues including ex-vivo bovine kidney, liver and muscle, poultry liver, as well as freshly excised canine testicle and ovary samples. These methods were able to successfully find impedance spectra features for the investigated biological tissues. The best predictive accuracy was with Boruta feature extraction and a Random Forest classifier but without significantly reducing the number of features in the classifier model. The proposed method was able to reduce the number of features in the model to an average of 5.8 features for all tested classifiers. These methods may have use in finding features to discriminate other tissue types, possibly to aid in targeting lesions in minimally invasive cancer treatment surgeries.
Keywords: Electric impedance spectroscopy; Feature extraction; Tissue classification

Biopsy Needle System with a Steerable Concentric Tube and Online Monitoring of Electrical Resistivity and Insertion Forces - Su, Baiquan; Yu, Shi; Yan, Hao; Hu, Yida David; Buzurovic, Ivan; Liu, Dongyun; Liu, Liaoliao; Teng, Yunlai; Tang, Jie; Wang, Junchen; Liu, Wenyong (IEEE Transactions on Biomedical Engineering, 2021)
Objective: Biopsies are the gold standard for clinical diagnosis. However, a discrepancy between the biopsy sample and target tissue because of misplacement of the biopsy spoon can lead to errors in the diagnosis and subsequent treatment. Thus, correctly determining whether the needle tip is in the tumor is crucial for accurate biopsy results. Methods: A biopsy needle system was designed with a steerable, flexible, and superelastic concentric tube; electrodes to monitor the electrical resistivity; and load cells to monitor the insertion force. The degrees of freedom were analyzed for two working modes: straight-line and deflection. Results: Experimental results showed that the system could perceive the tissue type in online based on the electrical resistivity. In addition, changes in the insertion force indicated transitions between the interfaces of adjacent tissue layers. Conclusion: The two monitoring methods guarantee that the biopsy spoon is at the desired position inside the tumor during an operation. Significance: The proposed biopsy needle system can be integrated into an autonomous robotic biopsy system.
Keywords: Force measurement; medical robotic system; resistivity measurement; steerable needle; tissue biopsy

Neural tissue-microelectrode interaction: Brain micromotion, electrical impedance, and flexible microelectrode insertion - Sharafkhani, Naser; Kouzani, Abbas Z.; Adams, Scott D.; Long, John M.; Lissorgues, Gaëlle; Rousseau, Lionel; Orwa, Julius O. (Journal of Neuroscience Methods, 2022)
Insertion of a microelectrode into the brain to record/stimulate neurons damages neural tissue and blood vessels and initiates the brain's wound healing response. Due to the large difference between the stiffness of neural tissue and microelectrode, brain micromotion also leads to neural tissue damage and associated local immune response. Over time, following implantation, the brain's response to the tissue damage can result in microelectrode failure. Reducing the microelectrode's cross-sectional dimensions to single-digit microns or using soft materials with elastic modulus close to that of the neural tissue are effective methods to alleviate the neural tissue damage and enhance microelectrode longevity. However, the increase in electrical impedance of the microelectrode caused by reducing the microelectrode contact site's dimensions can decrease the signal-to-noise ratio. Most importantly, the reduced dimensions also lead to a reduction in the critical buckling force, which increases the microelectrode's propensity to buckling during insertion. After discussing brain micromotion, the main source of neural tissue damage, surface modification of the microelectrode contact site is reviewed as a key method for addressing the increase in electrical impedance issue. The review then focuses on recent approaches to aiding insertion of flexible microelectrodes into the brain, including bending stiffness modification, effective length reduction, and application of a magnetic field to pull the electrode. An understanding of the advantages and drawbacks of the developed strategies offers a guide for dealing with the buckling phenomenon during implantation.
Keywords: Brain micromotion; Electrical impedance; Flexible microelectrode; Insertion approach; Neural tissue; Surface modification

Ion channels: Molecular targets of neuroactive insecticides - Raymond-Delpech, Valérie; Matsuda, Kazuhiko; Sattelle, Benedict M.; Rauh, James J.; Sattelle, David B. (Invertebrate Neuroscience, 2005)
Many of the insecticides in current use act on molecular targets in the insect nervous system. Recently, our understanding of these targets has improved as a result of the complete sequencing of an insect genome, i.e., Drosophila melanogaster. Here we examine the recent work, drawing on genetics, genomics and physiology, which has provided evidence that specific receptors and ion channels are targeted by distinct chemical classes of insect control agents. The examples discussed include, sodium channels (pyrethroids, p,p′- dichlorodiphenyl-trichloroethane (DDT), dihydropyrazoles and oxadiazines); nicotinic acetylcholine receptors (cartap, spinosad, imidacloprid and related nitromethylenes/nitroguanidines); γ-aminobutyric acid (GABA) receptors (cyclodienes, γ-BHC and fipronil) and L-glutamate receptors (avermectins). Finally, we have examined the molecular basis of resistance to these molecules, which in some cases involves mutations in the molecular target, and we also consider the future impact of molecular genetic technologies in our understanding of the actions of neuroactive insecticides. © Springer-Verlag 2005.
Keywords: Ionotropic receptors; Molecular targets of insecticides; Resistance genes; Sodium channels

A nicotinic acetylcholine receptor mutation (Y151S) causes reduced agonist potency to a range of neonicotinoid insecticides - Liu, Zewen; Williamson, Martin S.; Lansdell, Stuart J.; Han, Zhaojun; Denholm, Ian; Millar, Neil S. (Journal of Neurochemistry, 2006)
Neonicotinoid insecticides are potent selective agonists of insect nicotinic acetylcholine receptors (nAChRs). Since their introduction in 1991, resistance to neonicotinoids has been slow to develop, but it is now established in some insect field populations such as the planthopper, Nilaparvata lugens, a major rice pest in many parts of Asia. We have reported recently the identification of a target-site mutation (Y151S) within two nAChR subunits (Nlα1 and Nlα3) from a laboratory-selected field population of N. lugens. In the present study, we have examined the influence of this mutation upon the functional properties of recombinant nAChRs expressed in Xenopus oocytes (as hybrid nAChRs, co-expressed with a rat β2 subunit). The agonist potency of several nicotinic agonists has been examined, including all of the neonicotinoid insecticides that are currently licensed for either crop protection or animal health applications (acetamiprid, clothianidin, dinotefuran, imidacloprid, nitenpyram, thiacloprid and thiamethoxam). The Y151S mutation was found to have no significant effect on the maximal current (I max) observed with the endogenous agonist, acetylcholine. In contrast, a significant reduction in Imax was observed for all neonicotinoids (the Imax for mutant nAChRs ranged from 13 to 81% of that observed on wild-type receptors). In addition, nAChRs containing the Y151S mutation caused a significant rightward shift in agonist dose-response curves for all neonicotinoids, but of varying magnitude (shifts in EC50 values ranged from 1.3 to 3.6-fold). The relationship between neonicotinoid structure and their potency on nAChRs containing the Y151S target-site mutation is discussed. © 2006 The Authors.
Keywords: Insecticide resistance; Neonicotinoid; Nicotinic acetylcholine receptor

Imidacloprid activates ROS and causes mortality in honey bees (Apis mellifera) by inducing iron overload - He, Biao; Liu, Zhihao; Wang, Yuedi; Cheng, Lanchun; Qing, Qiqian; Duan, Jiaxin; Xu, Jinshan; Dang, Xiaoqun; Zhou, Zeyang; Li, Zhi (Ecotoxicology and Environmental Safety, 2021)
Imidacloprid, a neonicotinoid pesticide widely used for insect pest control, has become a potential pollutant to pollinators. Previous reports have demonstrated the toxicity of this drug in activating oxidative stress resulting in high mortality in the honey bee Apis mellifera. However, the mechanisms underlying the toxicity of imidacloprid have not been fully elucidated. In this study, sublethal (36 ng/bee) and median lethal (132 ng/bee) doses of imidacloprid were administered to bees. The results showed dose-dependent increases in reactive oxygen species (ROS), Fe2+, and mortality in bees. Notably, imidacloprid also induced upregulation of the gene encoding ferritin (AmFth), which plays a pivotal role in reducing Fe2+ overload. Upregulation of AmFth has been suggested to be closely related to ROS accumulation and high mortality in bees. To confirm the role played by AmFth in imidacloprid-activated ROS, dsAmFth double-strand was orally administered to bees after exposure to imidacloprid. The results revealed aggravated Fe2+ overload, higher ROS activation, and elevated mortality in the bees, indicating that imidacloprid activated ROS and caused mortality in the bees, probably by inducing iron overload. This study helps to elucidate the molecular mechanisms underlying the toxicity of imidacloprid from the perspective of iron metabolism.
Keywords: Apis mellifera; Imidacloprid; Iron metabolism; Oxidative stress

Imidacloprid Disturbs the Nitrogen Metabolism and Triggers an Overall Stress Response in Maize Seedlings - Zhang, Xingxing; Fu, Hongkai; Wu, Qihua; Chen, Lijuan; Lu, Yinglin; Gao, Shuai (Agronomy, 2022)
Imidacloprid (IMI) protects crops from pests; however, its potential toxicity to plants and underlying mechanisms are still poorly understood. We investigated the effects of IMI on maize seedlings under different nitrogen sufficiency conditions. Our measurement of the maize seedlings’ growth traits and physiological indicators found that a 5 ppm IMI treatment stunted the maize’s growth and enhanced membrane lipid peroxidation under a nitrogen-supplied condition, but that it promoted an increase in biomass and alleviated chlorosis in maize shoots under nitrogen deficiency. These results suggest that IMI causes serious toxicity in maize seedlings under nitrogen-sufficient conditions. The content of IMI indicated that the leaf was the main site of IMI accumulation in maize, and that NO3− was beneficial for the transportation of IMI from the roots to the leaves. The three groups of seedlings, which received 0 (−N), 4 (N) or 10 mmol L−1 NO3− (NN), were either treated or not treated with 5 ppm IMI. The six sets of transcriptome profiles from the shoots and roots were compared using Illumina sequencing. Transcriptome analysis revealed that IMI treatment led to changes in the expression of the genes involved in multiple biological processes, including nitrate transporter, nitrogen assimilation, nitrogen-regulatory factors, detoxification-related genes and several antioxidant-related genes in maize roots. The above results and the data for the nitrate content, glutamine synthetase activities and nitrate reductase activities showed that IMI disturbed nitrogen absorption and metabolism in maize seedlings. Glutathione S-transferase genes, C-type ATP-binding cassette (ABC) transporter 4, anthocyanins and lignin may play an important role in the detoxification of IMI in maize. These findings have helped us to elaborate the underlying detoxification mechanisms of IMI in plants, which is highly important in the cultivation of anti-pesticide crop varieties.
Keywords: detoxification; imidacloprid; maize; nitrogen; transcriptome analysis

Neonicotinoids: mechanisms of systemic toxicity based on oxidative stress-mitochondrial damage - Xu, Xiaoqing; Wang, Xiaohui; Yang, Yaqin; Ares, Irma; Martínez, Marta; Lopez-Torres, Bernardo; Martínez-Larrañaga, María Rosa; Wang, Xu; Anadón, Arturo; Martinez, María Aránzazu (Archives of Toxicology, 2022)
Neonicotinoids are the most widely used pesticides in the world. However, research studies have shown that it can affect the cognitive abilities and health of non-target bees and other wild pollinators by inducing DNA damage, apoptosis and mitochondrial damage, injure to its central nervous system, and it is even developmentally neurotoxic to mammals and humans, with mitochondria being an important target of neonicotinoids. Therefore, this article reviews the role of mitochondrial morphology, calcium ions (Ca2+) homeostasis, respiratory function, apoptosis, and DNA damage in neonicotinoids-induced systemic toxicity. Additionally, it evaluates the protective effects of various active substances including vitamin C, N-acetylcysteine (NAC), curcumin (CUR), glutathione reduced (GSH), caffeic acid phenethyl ester (CAPE), resveratrol, and thymoquinone (TQ) on neonicotinoids-induced toxicity. This review manuscript found that mitochondria are important targets to neonicotinoids. Neonicotinoids can cause DNA damage, apoptosis, protein oxidation, and lipid peroxidation in non-target organisms by altering mitochondrial Ca2+ homeostasis, inhibiting mitochondrial respiration, and inducing reactive oxygen species (ROS) production. Several active substances (vitamin C, NAC, CUR, GSH, resveratrol, CAPE, and TQ) play a protective role against neonicotinoid-induced systemic toxicity by inhibiting ROS signaling pathways, apoptosis, and lipid peroxidation. This review manuscript emphasizes the importance and urgency of the development of neonicotinoid antidotes, emphasizes the prospect of the application of targeted mitochondrial antidotes, and prospects the development of neonicotinoid antidotes in order to provide some strategies for the prevention of neonicotinoid toxicity.
Keywords: Antioxidants; Mitochondria; Neonicotinoids; Oxidative stress; Reactive oxygen species

Towards eco-friendly crop protection: natural deep eutectic solvents and defensive secondary metabolites - Mouden, Sanae; Klinkhamer, Peter G.L.; Choi, Young Hae; Leiss, Kirsten A. (Phytochemistry Reviews, 2017)
With mounting concerns over health and environmental effects of pesticides, the search for environmentally acceptable substitutes has amplified. Plant secondary metabolites appear in the horizon as an attractive solution for green crop protection. This paper reviews the need for changes in the techniques and compounds that, until recently, have been the mainstay for dealing with pest insects. Here we describe and discuss main strategies for selecting plant-derived metabolites as candidates for sustainable agriculture. The second part surveys ten important insecticidal compounds, with special emphasis on those involved in human health. Many of these insecticidal metabolites, however, are crystalline solids with limited solubility which might potentially hamper commercial formulation. As such, we introduce the concept of natural deep eutectic solvents for enhancing solubility and stability of such compounds. The concept, principles and examples of green pest control discussed here offer a new suite of environmental-friendly tools designed to promote and adopt sustainable agriculture.
Keywords: Insecticidal; Metabolomics; NADES; Plant protection compounds; Solubility

Plant Secondary Metabolites: The Weapons for Biotic Stress Management - Al-Khayri, Jameel M.; Rashmi, Ramakrishnan; Toppo, Varsha; Chole, Pranjali Bajrang; Banadka, Akshatha; Sudheer, Wudali Narasimha; Nagella, Praveen; Shehata, Wael Fathi; Al-Mssallem, Muneera Qassim; Alessa, Fatima Mohammed; Almaghasla, Mustafa Ibrahim; Rezk, Adel Abdel Sabour (Metabolites, 2023)
The rise in global temperature also favors the multiplication of pests and pathogens, which calls into question global food security. Plants have developed special coping mechanisms since they are sessile and lack an immune system. These mechanisms use a variety of secondary metabolites as weapons to avoid obstacles, adapt to their changing environment, and survive in less-than-ideal circumstances. Plant secondary metabolites include phenolic compounds, alkaloids, glycosides, and terpenoids, which are stored in specialized structures such as latex, trichomes, resin ducts, etc. Secondary metabolites help the plants to be safe from biotic stressors, either by repelling them or attracting their enemies, or exerting toxic effects on them. Modern omics technologies enable the elucidation of the structural and functional properties of these metabolites along with their biosynthesis. A better understanding of the enzymatic regulations and molecular mechanisms aids in the exploitation of secondary metabolites in modern pest management approaches such as biopesticides and integrated pest management. The current review provides an overview of the major plant secondary metabolites that play significant roles in enhancing biotic stress tolerance. It examines their involvement in both indirect and direct defense mechanisms, as well as their storage within plant tissues. Additionally, this review explores the importance of metabolomics approaches in elucidating the significance of secondary metabolites in biotic stress tolerance. The application of metabolic engineering in breeding for biotic stress resistance is discussed, along with the exploitation of secondary metabolites for sustainable pest management.
Keywords: aposematic signals; biopesticides; biotic stress; companion farming; feeding deterrents; metabolomics engineering; plant secondary metabolites

Evaluating the Effects of Flavonoids on Insects: Implications for Managing Pests Without Harming Beneficials - Riddick, Eric Wellington (Insects, 2024)
Flavonoids have multiple functions, including host-plant defense against attacks from herbivorous insects. This manuscript reviewed and analyzed the scientific literature to test the hypothesis that flavonoids can be utilized to manage pests without causing significant harm to beneficials. The methodology involved using recognized literature databases, e.g., Web of Science, Scopus, and CAB Abstracts, via the USDA-ARS, National Agricultural Library, DigiTop literature retrieval system. Data were compiled in tables and subjected to statistical analysis, when appropriate. Flavonoids were generally harmful to true bugs and true flies but harmless to honey bees. Flavonoid glycosides showed a tendency to harm true bugs (Heteroptera) and true flies (Diptera). Flavonoid glycosides were harmless to sawflies. Flavonoids and flavonoid glycosides produced a mixture of harmful and harmless outcomes to herbivorous beetles, depending on the species. Flavonoid glycosides were harmless to butterflies. In conclusion, specific flavonoids could function as feeding stimulants or deterrents, oviposition stimulants or deterrents, chemical protectants from pesticides, mating attractants, less-toxic insecticides, and other functions. Flavonoids could manage some insect pests without causing significant harm to beneficials (e.g., honey bees). Flavonoid-based insecticides could serve as environmentally benign alternatives to broad-spectrum insecticides against some pests, but field testing is necessary.
Keywords: chemical ecology; flavonoid-insect interactions; herbivores; insect health; integrated pest management; pollinators

Combined Neurotoxic Effects of Commercial Formulations of Pyrethroid (Deltamethrin) and Neonicotinoid (Imidacloprid) Pesticides on Adult Zebrafish (Danio rerio): Behavioral, Molecular, and Histopathological Analysis - Petrovici, Adriana; Savuța, Gheorghe; Lucini, Carla; Robea, Madalina-Andreea; Solcan, Carmen (Life, 2025)
The use of different commercial products that involve one or multiple active substances with specific targeted-pests control has become a widespread practice. Because of this, a severe range of significant consequences has been often reported. Among the most used pesticides worldwide are deltamethrin (DM) and imidacloprid (IMI). With a significative effect on the insect’s nervous system, DM acts on the voltage-gated sodium channels in nerve cell membranes, while IMI mimics the acetylcholine neurotransmitter by binding irreversibly to the nicotinic acetylcholine receptors. This study investigates the neurotoxic effects of sub-chronic exposure to commercial formulations of deltamethrin (DM) and imidacloprid (IMI) in adult zebrafish, both individually and in combination. The formulations used in this study contain additional ingredients commonly found in commercial pesticide products, which may contribute to overall toxicity. Fish were exposed to environmentally relevant concentrations of these pesticides for 21 days, individually or in combination. Behavioral, molecular, and histopathological analyses were conducted to assess the impact of these pesticides. Zebrafish exhibited dose-dependent behavioral alterations, particularly in the combined exposure groups, including increased erratic swimming and anxiety-like behavior. Gene expression analysis revealed significant changes in neurotrophic factors (BDNF, NGF, ntf-3, ntf-4/5, ntf-6/7) and their receptors (ntrk1, ntrk2a, ntrk2b, ntrk3a, ntrk3b, ngfra, ngfrb), indicating potential neurotoxic effects. Histopathological examination confirmed neuronal degeneration, gliosis, and vacuolization, with more severe impairments observed in pesticide mixture treatments. These findings highlight the neurotoxic potential of pesticide formulations in aquatic environments and emphasize the need for stricter regulations on pesticide mixtures and further research on pesticide interactions. Our findings emphasize that the combination of pesticides could trigger a synergistic effect by maximizing the toxicity of each compound. Thus, it is a well-known practice for pyrethroids and neonicotinoids to be used together in agriculture. Even so, its prevalence in agriculture and the need to investigate its actual impact on human health, biodiversity, and ecosystem mitigates the development of new strategies for assessing the risk and, at the same time, enhancing the effectiveness.

Monitoring of imidacloprid residues in fresh fruits and vegetables from the central parts of Jordan - Al-Hawadi, Jehad S.; Al-Sayaydeh, Rabea S.; Al-Rawashdeh, Ziad B.; Ayad, Jamal Y. (Heliyon, 2023)
Imidacloprid pesticide is widely utilized in agriculture due to its effectiveness in controlling a broad spectrum of insect pests. However, its usage has raised concerns about potential environmental impacts, and requires careful monitoring and responsible application to ensure sustainable agricultural practices. Thus, Gas chromatography-mass spectrometry (GC-MS) was utilized to analyze imidacloprid in 300 vegetable and fruit samples obtained from 15 major wholesalers in four regions of Amman, Jordan's capital city. Among the examined samples, 39.7 % were found to be contaminated with imidacloprid residues. Imidacloprid levels in different edible fruits and vegetables ranged from less than the Limit of Quantification (LOQ) to 0.40 mg kg−1. Significantly, eggplant and apples exhibited the highest average values (0.40 and 0.25 mg kg−1, respectively). Lower levels were detected in bananas (0.04 mg kg−1), potatoes (0.05 mg kg−1), grapes (0.07 mg kg−1), and cabbage (0.07 mg kg−1). Imidacloprid was below the method detection limit (BD) in samples of okra, peaches, apricots, and carrots. Overall, 25 samples (8.3 %) exceeded the Codex maximum residue limit (MRL) for imidacloprid. Moreover, 8 out of the 300 samples (2.7 %) exceeded the MRL established by the Pest Management Regulatory Agency (PMRA). Notably, the fruits of eggplant and apple contained the highest residual levels (1.30 and 0.83 mg kg−1, respectively), markedly exceeding the CODEX and PMRA MRLs. Additionally, the maximum detected imidacloprid residue concentration in bananas (0.25 mg kg−1) was 500 % higher than the CODEX MRLs. The estimated average daily intake (EDI) of the Amman population varied from 0.00 to 0.144 μg kg−1 body weight day−1 across various products. The hazard index (HI) for imidacloprid ranged from 0.00 to 0.24, all of which were below unity in all samples (<1). In conclusion, this investigation reveals low HI levels of imidacloprid residues in commonly consumed fruits and vegetables. However, the significant presence of imidacloprid residues in some samples highlights the urgent need for comprehensive measures to limit potential health hazards to consumers.
Keywords: Estimated daily intakes; GC-MS; Hazard index; Imidacloprid; Insecticides residues; Maximum residue limit

Relationship between imidacloprid residues and control effect on cotton aphids in arid region - Jie, Menglei; Gao, Youhua; Kuang, Daihong; Shi, Yingshuang; Wang, Huanhuan; Jing, Weiwen (Environmental Geochemistry and Health, 2021)
In this case, the dissipation and residues of imidacloprid as well as its control efficacy against aphids (Aphis gossypii Glover) in cotton cropping system were reported. After the final spray at the rates of 10.5–42.5 g a.i. ha−1, the initial deposits were 0.59–2.25 mg kg−1 with half-lives of 2.12–2.84 days on leaves and 0.06–0.21 mg kg−1 with half-lives of 1.51–4.20 days in soil, respectively. The initial residues were significantly higher with longer persistence in the upper position of the leaf than in middle and lower positions. The different application dosages could induce a significant difference in the initial deposits, but not show consistent correlation with the dissipation rate. The repeated applications of imidacloprid could alter its residue levels and dissipation rates. The long-term residue concentrations of imidacloprid (60 days after the final application) reached to the nondetectable level in soil. Combined with the control efficacy results, it was considered that the recommended dose of imidacloprid on cotton could be used effectively and safe in this arid area from the view of crop protection and environmental contamination.
Keywords: Control effect; Cotton; Imidacloprid dissipation

Defensive Behavior and Morphometric Variation in Apis mellifera Colonies From Two Different Agro-Ecological Zones of North-Western Argentina - Bianchi, Eliana; Agra, Marcelo Nicolás; García, Cristina; Gennari, Gerardo; Maldonado, Luis; Rodríguez, Graciela Adriana; Palacio, María Alejandra; Scannapieco, Alejandra Carla; Lanzavecchia, Silvia Beatriz (Frontiers in Ecology and Evolution, 2021)
European lineages of Apis mellifera were first introduced into America for beekeeping purposes. A subsequent introduction and accidental release of A. m. scutellata resulted in hybridization events that gave rise to Africanized populations that rapidly spread throughout the continent. In Argentina, Africanized honey bees (AHBs) have been mostly detected in northern regions of the territory, and represent a valuable genetic resource for the selection of stocks with advantageous characteristics for beekeeping. The objective of the present study was to profile honey bee colonies of wild origin with potential beneficial traits for apiculture using morphological, molecular and behavioral traits. Honey bee colonies chosen for evaluation were located in two different agro-ecological regions in north-western Argentina (Tucumán province): The Chaco Depressed Plain (Leales apiary) and the Piedmont (Famaillá apiary). Each apiary was surveyed three times during the 2017–2018 season (mid-season, wintertime, and early spring) for: brood population, phoretic Varroa level and defensive behavior (run, fly, sting, and hang). At the midpoint of the beekeeping season colonies were also characterized by morphometry (45 variables) and mitochondrial haplotypes (COI–COII intergenic region). Apiaries studied showed similar patterns throughout the beekeeping season, for most of the characteristics monitored. However, significant variation in defensive behavior parameters was found between apiaries at the different times of evaluation. Twelve of 45 morphometric variables also showed significant differences between apiaries. The mitochondrial haplotype analysis revealed a high representation of African A4 and A1 haplotypes (91%) in both apiaries. Haplotype variation was associated with morphometric and behavioral traits. Multivariate analyses [principal component analysis (PCA) and principal coordinate analysis (PCoA)] including morphometric and behavior variables explained 65.3% (PCA) and 48.1% (PCoA) of the variability observed between colonies in the first two components. Several morphometric parameters and “fly” behavior were mainly associated with the separation of the colonies. The results from this study point to a possible association between morphometric and behavioral variation and the adaptation of honey bee colonies to differential agro-ecological conditions. We discuss how the detected variation between apiaries can be used for the selection and preservation of honey bee ecotypes in regional breeding programs.
Keywords: defensiveness; environment; honey bees; mitochondrial haplotype; morphometry

Hornets and honey bees: A coevolutionary arms race between ancient adaptations and new invasive threats - Cappa, Federico; Cini, Alessandro; Bortolotti, Laura; Poidatz, Juliette; Cervo, Rita (Insects, 2021)
Hornets and honey bees have a long history of coevolution resulting in a plethora of capti-vating adaptations and counteradaptations between predator and prey. From simple physiological mechanisms to complex behavioral strategies, some Vespa hornets have specialized in hunting honey bees, while the latter have put in place effective defenses to counteract their attack. Both hornets and honey bees have evolved the ability to detect the odors and the pheromones emitted by the other to locate the prey or to spot foraging predators. Hornets often rely on their bigger size, heavily armored body and destructive attacks, while honey bees differentiated collective defense responses finely coordinated to deter or kill the hornet menace. However, when new species of hornets and honey bees come into contact, the absence of coevolution can have a heavy impact on the defenseless bees. The evolutionary arms race between hornets and honey bees provides not only compelling examples of adaptations and counteradaptations between predator and prey, but could also represent a starting point for the development of effective and sustainable strategies to protect honey bees and beekeeping activities and to control invasive alien species of hornets.
Keywords: Alien invasive species; Apis; Asian hornets; Coevolution; Vespa

Honey Bee Colonies (Apis mellifera L.) Perform Orientation Defensiveness That Varies among Bred Lines - Akongte, Peter Njukang; Park, Bo Sun; Kim, Dong Won; Choi, Yong Soo (Insects, 2023)
Honey bees (Apis mellifera L.) express complex behavioral patterns (aggressiveness) in defensive mechanisms for their survival. Their phenotypic expression of defensive behavior is influenced by internal and external stimuli. Knowledge of this behavior has recently become increasingly important, though beekeepers are still faced with the challenges of selecting defensive and less-defensive bred lines. Field evaluation of defensive behavior among bred lines of honey bees is required to overcome the challenges. Chemical cues (alarm pheromone and isopentyl acetate mixed with paraffin oil) and physical and visual stimuli (dark leather suede, colony marbling, and suede jiggling) were used to evaluate defensiveness and orientation among five bred lines of honeybee colonies. Our results showed that both chemical assays recruited bees, but the time of recruitment was significantly faster for alarm pheromone. Honeybees’ response to both assays culminated in stings that differed among bred lines for alarm pheromone and paraffin when colonies were marbled. Honeybee orientation defensiveness varied among bred lines and was higher in more defensive bred lines compared to less-defensive bred lines. Our findings suggest that it is crucial to repeatedly evaluate orientation defensiveness at the colony level and among bred lines when selecting breeding colonies.
Keywords: Apis melliferaL; chemical pheromone; controlled breeding; defensive behavior; honey bee bred lines

SUBCHRONIC EXPOSURE OF HONEYBEES TO SUBLETHAL DOSES OF PESTICIDES: EFFECTS ON BEHAVIOR - Aliouane, Yassine; El Hassani, Adessalam K; Gary, Vincent; Armengaud, Catherine; Lambin, Michel; Gauthier, Monique (Environmental Toxicology and Chemistry, 2009)
Laboratory bioassays were conducted to evaluate the effects on honeybee behavior of sublethal doses of insecticides chronically administered orally or by contact. Emergent honeybees received a daily dose of insecticide ranging from one-fifth to one-five-hundredth of the median lethal dose (LD50) during 11 d. After exposure to fipronil (0.1 and 0.01 ng/bee), acetamiprid (1 and 0.1 g/bee), or thiamethoxam (1 and 0.1 ng/bee), behavioral functions of honeybees were tested on day 12. Fipronil, used at the dose of 0.1 ng/bee, induced mortality of all honeybees after one week of treatment. As a result of contact treatment at 0.01 ng/bee, honeybees spent significantly more time immobile in an open-field apparatus and ingested significantly more water. In the olfactory conditioning paradigm, fipronil-treated honeybees failed to discriminate between a known and an unknown odorant. Thiamethoxam by contact induced either a significant decrease of olfactory memory 24 h after learning at 0.1 ng/bee or a significant impairment of learning performance with no effect on memory at 1 ng/bee. Responsiveness to antennal sucrose stimulation was significantly decreased for high sucrose concentrations in honeybees treated orally with thiamethoxam (1 ng/bee). The only significant effect of acetamiprid (administered orally, 0.1 g/bee) was an increase in responsiveness to water. The neonicotinoids acetamiprid and thiamethoxam tested at the highest dose (one-tenth and one-fifth of their oral LD50, respectively) and fipronil at one-five-hundredth of LD50 have limited effects on the motor, sensory, and cognitive functions of the honeybee. Our data on the intrinsic toxicity of the compounds after chronic exposure have to be taken into account for evaluation of risk to honeybees in field conditions.

Evidence of forage distance limitations for small bees (Hymenoptera: Apidae) - Wright, Ivan R.; Roberts, Stuart P.M.; Collins, Bonnie E. (European Journal of Entomology, 2015)
The distribution of ground-nesting bees was investigated using transects of water traps in a mosaic of nesting and forage habitats at Shotover Hill in Oxfordshire, UK. The site includes a large area of ground-nesting bee activity and is adjoined on three sides by floristic hay meadows. This study showed that the females of small bee species (< 1.5 mm intertegular span) that were foraging in the hay meadows demonstrated a functional limitation to their homing range. The abundance of small bees declined rapidly with increasing distance from areas of high density nesting; declining more rapidly than might be expected from uniform dispersal into the surrounding landscape. By modelling the occurrence of bees along each transect it was found that the probability of observing a small bee in the hay meadows was reduced to 10% at a distance of 250-370 m from the nesting habitat. The result emphasises the scale on which habitat fragmentation will begin to impact upon bee diversity, and the relative contribution of managed "pollen and nectar" strips to areas of nesting habitat.
Keywords: Apidae; Flight distance; Forage; Ground-nesting bees; Habitat fragmentation; Hymenoptera; Partial habitats

RFID tracking of sublethal effects of two neonicotinoid insecticides on the foraging behavior of Apis mellifera - Schneider, Christof W.; Tautz, Jürgen; Grünewald, Bernd; Fuchs, Stefan (PLoS ONE, 2012)
The development of insecticides requires valid risk assessment procedures to avoid causing harm to beneficial insects and especially to pollinators such as the honeybee Apis mellifera. In addition to testing according to current guidelines designed to detect bee mortality, tests are needed to determine possible sublethal effects interfering with the animal's vitality and behavioral performance. Several methods have been used to detect sublethal effects of different insecticides under laboratory conditions using olfactory conditioning. Furthermore, studies have been conducted on the influence insecticides have on foraging activity and homing ability which require time-consuming visual observation. We tested an experimental design using the radiofrequency identification (RFID) method to monitor the influence of sublethal doses of insecticides on individual honeybee foragers on an automated basis. With electronic readers positioned at the hive entrance and at an artificial food source, we obtained quantifiable data on honeybee foraging behavior. This enabled us to efficiently retrieve detailed information on flight parameters. We compared several groups of bees, fed simultaneously with different dosages of a tested substance. With this experimental approach we monitored the acute effects of sublethal doses of the neonicotinoids imidacloprid (0.15-6 ng/bee) and clothianidin (0.05-2 ng/bee) under field-like circumstances. At field-relevant doses for nectar and pollen no adverse effects were observed for either substance. Both substances led to a significant reduction of foraging activity and to longer foraging flights at doses of ≥0.5 ng/bee (clothianidin) and ≥1.5 ng/bee (imidacloprid) during the first three hours after treatment. This study demonstrates that the RFID-method is an effective way to record short-term alterations in foraging activity after insecticides have been administered once, orally, to individual bees. We contribute further information on the understanding of how honeybees are affected by sublethal doses of insecticides. © 2012 Schneider et al.

A QUANTITATIVE ANALYSIS OF THE OSMOLYTES IN THE HEMOLYMPH OF THE LARVAL GYPSY MOTH, LYMANTRIA DISPAR - Pannafsecker, T L; Andrews, F; Beyenbach, K W (J. Insect Physiol, 1992)
In spite of the growing number of in vitro studies conducted with the gypsy moth there are no reports which describe its hemolymph composition. For this reason we have conducted a quantitative analysis of the osmolytes in the hemolymph of the fifth-instar gypsy moth larva reared on a wheat-germ diet. The osmotic pressure of hemolymph is 313 mOsm/kg water and the hemolymph pH is 6.6. The dominant inorganic cations are potassium (29.1 mM), magnesium (25.9 mM), calcium (6.8 mM) and sodium (5.0 mM). The dominant inorganic anions are chloride (14.9 mM), sulfate (12.3 mM), and phosphate (5.7 mM). The electrical conductivity of the hemolymph (4.52 ms/cm) is equivalent to the conductivity of a 98.8 mOsm/kg water NaCl solution. Since the sum of the measured hemolymph cations and anions approaches this osmolality, more than 200 mOsm/kg water of hemolymph solutes are non-electrolytes. Among these non-electrolytes we have identified 18 amino acids (112.0 mM), trehalose (21.1 mM), glucose (2.4 mM) and urea (4.8 mM). Organic solutes such as arginine (0.9 mM), histidine (3.9 mM), lysine (13.9 mM), tyrosine (2.5 mM), aspartic acid (0.3 mM), glutamic acid (1.6 mM), organic phosphates (29.6 mM) and uric acid (0.2 mM) are expected to exist in ionized forms at the hemolymph pH. Together the identified electrolytes and non-electrolytes account for nearly 85% of the measured hemolymph osmolality.
Keywords: Key Word Index: Gypsy moth; amino acids; carbohydrates; electrolytes; hemolymph; phosphates

The dielectric properties of biological tissues: III. Parametric models for the dielectric spectrum of tissues - Gabriel, S; Lau, R W; Gabriel, C (Phys. Med. Biol, 1996)
A parametric model was developed to describe the variation of dielectric properties of tissues as a function of frequency. The experimental spectrum from 10 Hz to 100 GHz was modelled with four dispersion regions. The development of the model was based on recently acquired data, complemented by data surveyed from the literature. The purpose is to enable the prediction of dielectric data that are in line with those contained in the vast body of literature on the subject. The analysis was carried out on a Microsoft Excel spreadsheet. Parameters are given for 17 tissue types.

Dielectric spectroscopy as a viable biosensing tool for cell and tissue characterization and analysis - Heileman, Khalil; Daoud, Jamal; Tabrizian, Maryam (Biosensors and Bioelectronics, 2013)
The use of dielectric spectroscopy to carry out real time observations of cells and to extract a wealth of information about their physiological properties has expanded in recent years. This popularity is due to the simple, easy to use, non-invasive and real time nature of dielectric spectroscopy. The ease of integrating dielectric spectroscopy with microfluidic devices has allowed the technology to further expand into biomedical research. Dielectric spectra are obtained by applying an electrical signal to cells, which is swept over a frequency range. This review covers the different methods of interpreting dielectric spectra and progress made in applications of impedance spectroscopy for cell observations. First, methods of obtaining specific electrical properties of cells (cell membrane capacitance and cytoplasm conductivity) are discussed. These electrical properties are obtained by fitting the dielectric spectra to different models and equations. Integrating models to reduce the effects of the electrical double layer are subsequently covered. Impedance platforms are then discussed including electrical cell substrate impedance sensing (ECIS). Categories of ECIS systems are divided into microelectrode arrays, interdigitated electrodes and those that allow differential ECIS measurements. Platforms that allow single cell and sub-single cell measurements are then discussed. Finally, applications of impedance spectroscopy in a range of cell observations are elaborated. These applications include observing cell differentiation, mitosis and the cell cycle and cytotoxicity/cell death. Future applications such as drug screening and in point of care applications are then covered. © 2013.
Keywords: Dielectric biosensors; Dielectric cell models; Dielectric spectroscopy; Impedance monitoring; Microelectrodes; Microfluidic impedance

THE HEMOLYMPH OF CATERPILLARS SPODOPTERA LIT-TORALI9. PHYSICO-CHEMICAL PROPERTIES AND IONIC COMPOSITION COMPARED TO CULTURE MEDIA - Smagghe, G; Van Leeuwen, T (Comm. Appl. Biol. Sci, 2004)
In this paper, we determined some physico-chemical properties like osmotic pressure, pH and electrical conductivity of the hemolymph ffom caterpillars of Spodoptera lit-toralis (Lepidoptera: Noctuidae) during the last larval instar. It was of interest that we observed an increase in osmotic pressure with the increase in age in the last instar that may concur with the start of histolysis at metamorphosis. These physico-chemical properties were then compared to those of Grace's and modified Grace's tissue culture medium. In addition, concentrations of the cations Na, K. Ca and Mg, and the anions Cl, NO3, PO4 and SO4 were determined in the insect hemolymph of S. littoralis. The cations K and Mg reached high values with a percent of about 52% of the total amount of cations. The concentration of sodium was low. The total sum of the anions consisted about 56 meq/1, and this allows to neutralise about 45 % of the total cations.

Global pollinator declines: Trends, impacts and drivers - Potts, Simon G.; Biesmeijer, Jacobus C.; Kremen, Claire; Neumann, Peter; Schweiger, Oliver; Kunin, William E. (Trends in Ecology and Evolution, 2010)
Pollinators are a key component of global biodiversity, providing vital ecosystem services to crops and wild plants. There is clear evidence of recent declines in both wild and domesticated pollinators, and parallel declines in the plants that rely upon them. Here we describe the nature and extent of reported declines, and review the potential drivers of pollinator loss, including habitat loss and fragmentation, agrochemicals, pathogens, alien species, climate change and the interactions between them. Pollinator declines can result in loss of pollination services which have important negative ecological and economic impacts that could significantly affect the maintenance of wild plant diversity, wider ecosystem stability, crop production, food security and human welfare. © 2010 Elsevier Ltd.

Neonicotinoid insecticide toxicology: Mechanisms of selective action - Tomizawa, Motohiro; Casida, John E. (Annual Review of Pharmacology and Toxicology, 2005)
The neonicotinoids, the newest major class of insecticides, have outstanding potency and systemic action for crop protection against piercing-sucking pests, and they are highly effective for flea control on cats and dogs. Their common names are acetamiprid, clothianidin, dinotefuran, imidacloprid, nitenpyram, thiacloprid, and thiamethoxam. They generally have low toxicity to mammals (acute and chronic), birds, and fish. Biotransformations involve some activation reactions but largely detoxification mechanisms. In contrast to nicotine, epibatidine, and other ammonium or iminium nicotinoids, which are mostly protonated at physiological pH, the neonicotinoids are not protonated and have an electronegative nitro or cyano pharmacophore. Agonist recognition by the nicotinic receptor involves cation-π interaction for nicotinoids in mammals and possibly a cationic subsite for interaction with the nitro or cyano substituent of neonicotinoids in insects. The low affinity of neonicotinoids for vertebrate relative to insect nicotinic receptors is a major factor in their favorable toxicological profile.
Keywords: Binding site specificity; Biotransformation; Imidacloprid; Nicotinic receptor; Selective toxicity

The action of the insecticide imidacloprid on the respiratory rhythm of an insect: The beetle Tenebrio molitor - Zafeiridou, Georgia; Theophilidis, George (Neuroscience Letters, 2004)
Imidacloprid is an insecticide which has the nicotinic acetylcholine receptors (nAChRs) as its primary site of action; acetylcholine is the major excitatory neurotransmitter in the insect central nervous system (CNS). In this study, the action of imidacloprid was tested using the synapses of the respiratory central pattern generator of the beetle Tenebrio molitor. The no observed effect concentration (NOEC) for imidacloprid was estimated to be between 0.001 and 0.010 μM. A concentration of 0.10 μM caused hyperexcitation in firing of the respiratory motoneurons, while the concentration of 1.00 μM caused an abrupt increase in their frequency and then a complete inhibition of the activity of the respiratory motoneurons. The possible implication of the action of such low concentrations of imidacloprid in the contraction of the respiratory muscles is also demonstrated and discussed. © 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: Beetle; Imidacloprid; In vitro; Insect; Motoneurons; Nerve cord; Respiration

WATER CONTENT AND WATER ACTIVITY IN THE CUTICLE OF TERRESTRIAL ISOPODS - Lindqvist, Ossi V; Salminen, Inga; Winston, Paul W (J. Exp. Biol, 1972)

A perspective on insect water balance - O’Donnell, Michael J. (Journal of Experimental Biology, 2022)
Insects have a large ratio of surface area to volume because of their small size; thus, they face the potential for desiccation in the terrestrial environment. Nonetheless, they constitute over half of identified species and their success on land can be attributed, in part, to adaptations that limit water loss and allow for effective gains of water from food, fluids or atmospheric water vapour. Reduction of water loss from the gut involves sophisticated mechanisms of ion recycling and water recovery by epithelia of the Malpighian tubules and hindgut. Water loss across the body surface is greatly reduced by the evolution of very thin but highly impermeable lipid-rich layers in the epicuticle. Respiratory water loss can be reduced through effective spiracular control mechanisms and by mechanisms for convective rather than diffusive gas exchange. In addition to extracting water from food sources, some insects are capable of absorption of atmospheric water vapour through processes that have evolved independently in multiple groups.
Keywords: Cuticle; Hindgut; Malpighian tubule; Respiration; Water vapour absorption

Osmotic concentration in three races of honey bee, Apis mellifera L. under environmental conditions of arid zone - Ali, Hussain; Alqarni, Abdulaziz S.; Owayss, Ayman A.; Hassan, Awad M.; Smith, Brian H. (Saudi Journal of Biological Sciences, 2017)
Hemolymph osmolarity has great effect on honey bee health, especially in arid and semi-arid zones. It regulates water and nutrients in stressed tissues. Osmotic concentration in three races (Apis mellifera ligustica, A. m. carnica and A. m. jemenitica) of Apis mellifera was tested in central Saudi Arabia during spring and summer seasons in 2015. Newly emerged bee workers were first marked and later their hemolymph was extracted after intervals of 1, 5, 10, 15, 20 and 25 days. A significant positive correlation between age and osmolarity was found in all three races during spring and summer seasons. The lowest combined osmotic concentration for all three races was found after 1 day interval, while the highest osmotic concentration was recorded after 25 days. Among all races, A. m. ligustica showed significantly high osmotic concentration after 25 days in spring and summer seasons as compared to the other two races. Only A. m. jemenitica showed similar osmotic concentration after 10 and 15 days in both spring and summer seasons compared to other two races. Mean osmotic concentration of all three races was significantly different after 20 and 25 days in spring and summer seasons. Overall mean recorded during summer was significantly higher than the mean of spring season. Combined osmotic concentration in young drones of all races was significantly lower than that of old drones during spring and summer seasons.
Keywords: Apis mellifera races; Arid zone; Environmental stresses; Hemolymph; Osmolarity

Implications of animal water balance for terrestrial food webs - McCluney, Kevin E. (Current Opinion in Insect Science, 2017)
Recent research has documented shifts in per capita trophic interactions and food webs in response to changes in environmental moisture, from the top-down (consumers to plants), rather than solely bottom-up (plants to consumers). These responses may be predictable from effects of physiological, behavioral, and ecological traits on animal water balance, although predictions could be modified by energy or nutrient requirements, the risk of predation, population-level responses, and bottom-up effects. Relatively little work has explicitly explored food web effects of changes in animal water balance, despite the likelihood of widespread relevance, including during periodic droughts in mesic locations, where taxa may lack adaptations for water conservation. More research is needed, particularly in light of climate change and hydrological alteration.

Water loss in insects: An environmental change perspective - Chown, Steven L.; Sørensen, Jesper G.; Terblanche, John S. (Journal of Insect Physiology, 2011)
In the context of global environmental change much of the focus has been on changing temperatures. However, patterns of rainfall and water availability have also been changing and are expected to continue doing so. In consequence, understanding the responses of insects to water availability is important, especially because it has a pronounced influence on insect activity, distribution patterns, and species richness. Here we therefore provide a critical review of key questions that either are being or need to be addressed in this field. First, an overview of insect behavioural responses to changing humidity conditions and the mechanisms underlying sensing of humidity variation is provided. The primary sensors in insects belong to the temperature receptor protein superfamily of cation channels. Temperature-activated transient receptor potential ion channels, or thermoTRPs, respond to a diverse range of stimuli and may be a primary integrator of sensory information, such as environmental temperature and moisture. Next we touch briefly on the components of water loss, drawing attention to a new, universal model of the water costs of gas exchange and its implications for responses to a warming, and in places drying, world. We also provide an overview of new understanding of the role of the sub-elytral chamber for water conservation, and developments in understanding of the role of cuticular hydrocarbons in preventing water loss. Because of an increasing focus on the molecular basis of responses to dehydration stress we touch briefly on this area, drawing attention to the role of sugars, heat shock proteins, aquaporins, and LEA proteins. Next we consider phenotypic plasticity or acclimation responses in insect water balance after initial exposures to altered humidity, temperature or nutrition. Although beneficial acclimation has been demonstrated in several instances, this is not always the case. Laboratory studies show that responses to selection for enhanced ability to survive water stress do evolve and that genetic variation for traits underlying such responses does exist in many species. However, in others, especially tropical, typically narrowly distributed species, this appears not to be the case. Using the above information we then demonstrate that habitat alteration, climate change, biological invasions, pollution and overexploitation are likely to be having considerable effects on insect populations mediated through physiological responses (or the lack thereof) to water stress, and that these effects may often be non-intuitive. © 2011 Elsevier Ltd.
Keywords: Aquaporins; Desiccation resistance; Global environmental change; Humidity preference; Sensing; Subelytral chamber; ThermoTRPs; Water loss

Surface area–volume ratios in insects - Kühsel, Sara; Brückner, Adrian; Schmelzle, Sebastian; Heethoff, Michael; Blüthgen, Nico (Insect Science, 2017)
Body mass, volume and surface area are important for many aspects of the physiology and performance of species. Whereas body mass scaling received a lot of attention in the literature, surface areas of animals have not been measured explicitly in this context. We quantified surface area–volume (SA/V) ratios for the first time using 3D surface models based on a structured light scanning method for 126 species of pollinating insects from 4 orders (Diptera, Hymenoptera, Lepidoptera, and Coleoptera). Water loss of 67 species was measured gravimetrically at very dry conditions for 2 h at 15 and 30 °C to demonstrate the applicability of the new 3D surface measurements and relevance for predicting the performance of insects. Quantified SA/V ratios significantly explained the variation in water loss across species, both directly or after accounting for isometric scaling (residuals of the SA/V ∼ mass2/3 relationship). Small insects with a proportionally larger surface area had the highest water loss rates. Surface scans of insects to quantify allometric SA/V ratios thus provide a promising method to predict physiological responses, improving the potential of body mass isometry alone that assume geometric similarity.
Keywords: 3D surface imaging; body shape; body size; sphericity; structured light; water loss

Changes in hemolymph total CO2 content during the water-to-air respiratory transition of amphibiotic dragonflies - Lee, Daniel J.; Gutbrod, Martin; Ferreras, Fernando M.; Matthews, Philip G.D. (Journal of Experimental Biology, 2018)
Dragonflies (Odonata, Anisoptera) are amphibiotic; the nymph is aquatic and breathes water using a rectal gill before metamorphosing into the winged adult, which breathes air through spiracles. While the evolutionary and developmental transition from water breathing to air breathing is known to be associated with a dramatic rise in internal CO2 levels, the changes in blood-gas composition experienced by amphibiotic insects, which represent an ancestral air-to-water transition, are unknown. This study measured total CO2 (TCO2) in hemolymph collected from aquatic nymphs and air-breathing adults of Anax junius, Aeshna multicolor (Aeshnidae), Libellula quadrimaculata and Libellula forensis (Libellulidae). Hemolymph PCO2 was also measured in vivo in both aeshnid nymphs and marbled crayfish (Procambarus fallax. F. Virginalis) using a novel fiber-optic CO2 sensor. The hemolymph TCO2 of the pre-and early-final instar nymphs was found to be significantly lower than that of the air-breathing adults. However, the TCO2 of the late-final instar aeshnid nymphs was not significantly different from that of the air-breathing adults, despite the late-final nymphs still breathing water. TCO2 and PCO2 were also significantly higher in the hemolymph of early-final aeshnid nymphs compared with values for the water-breathing crayfish. Thus, while dragonfly nymphs show an increase in internal CO2 as they transition from water to air, from an evolutionary standpoint, the nymph's ability to breathe water is associated with a comparatively minor decrease in hemolymph TCO2 relative to that of the air-breathing adult.
Keywords: Aquatic; Blood-gas composition; Insect; PCO2; TCO2; Tracheal gill

Adult Paederus fuscipes (Coleoptera: Staphylinidae) Beetles Overcome Water Loss with Increased Total Body Water Content, Energy Metabolite Storage, and Reduced Cuticular Permeability: Age, Sex-Specific, and Mating Status Effects on Desiccation - Wang, Chia Yu; Bong, Lee Jin; Neoh, Kok Boon (Environmental Entomology, 2019)
The ability of Paederus beetles to resist desiccation stress is vital to their adaptability in various ecological niches. How water relations and their response to desiccation vary among adult beetles of different age, sex, and mating status is unclear. We examined the water relations of adult Paederus fuscipes Curtis and the mechanisms used to reduce desiccation stress. One-day-old beetles had an exceptionally high percent total body water (%TBW) content and tolerated a high level of %TBW loss. Newly emerged beetles contained a high level of trehalose and 40 to 60% lipid content of their total dry mass, which allowed them to endure desiccation. Beetles that were 10 wk old and older exhibited reduced cuticular permeability. Glucose, glycogen, and lipid contents were crucial throughout most of the adult life span, as they helped compensate for water loss via increased water vapor absorption and metabolic water. In particular, the accumulation of lipid after mating was significant and may further confer tolerance to water loss. The effect of melanization on the desiccation tolerance of beetles was not significant. Females had better tolerance in response to desiccation stress compared with males. We suggest that the observed differences between sexes likely were a function of water relations and an effect of energy metabolite reserves. However, the mortality of females at 24-h postdesiccating stage was marginally significant compared with males. These results demonstrate that P. fuscipes adults prevent dehydration using multiple mechanisms that collectively reduce desiccation stress and increase dehydration tolerance.
Keywords: body lipid content; desiccation tolerance; energy metabolite reserves; rove beetle

Differential sensitivity of bees to urbanization-driven changes in body temperature and water content - Burdine, Justin D.; McCluney, Kevin E. (Scientific Reports, 2019)
Predicting how species will respond to climate change and land use modification is essential for conserving organisms and maintaining ecosystem services. Thermal tolerances have been shown to have strong predictive power, but the potential importance of desiccation tolerances have been less explored in some species. Here, we report measurements of thermal and desiccation tolerances and safety margins across a gradient of urbanization, for three bee species: silky striped sweat bees (Agapostemon sericeus), western honeybees (Apis mellifera), and common eastern bumblebees (Bombus impatiens). We found significant differences in thermal tolerances, measured as critical thermal maximum (CT max ), amongst species. Bumblebees were the least sensitive to warming, with a higher CT max (53.1 °C) than sweat bees (50.3 °C) and honeybees (49.1 °C). We also found significant differences in desiccation tolerances, measured as critical water content (CWC), between all species. Sweat bees were the least sensitive to desiccation, with the lowest CWC (51.7%), followed by bumblebees (63.7%) and honeybees (74.2%). Moreover, bumblebees and sweat bees were closer to their CT max in more urbanized locations, while honeybees were closer to their CWC. These results suggest that bees have differential sensitivities to environmental change and managing for diverse bee communities in the face of global change may require mitigating both changes in temperature and water.

Nanostructured alumina: biocidal properties and mechanism of action of a novel insecticide powder - Stadler, Teodoro; López García, Guillermo P; Gitto, Javier G; Buteler, Micaela (Bulletin of Insectology, 2016)
Pest control using synthetic chemical pesticides is facing economic and environmental challenges worldwide. In this context, nanomaterials, emerge as potential tools that need to be investigated. The aim of this study was to examine the insecticidal effect and mode of action of nanostructured alumina (NSA) on Sitophilus oryzae (L.) (Coleoptera Dryophthoridae), an insect pest of stored products. Results demonstrated that the mechanism of insecticide action of NSA is based on physical phenomena rather than on biochemical mechanisms. Charged NSA particles attach to the insects cuticle due to triboelectric forces, sorbing its wax layer by surface area phenomena, resulting in insect dehydration. Moreover, intake of NSA particles was observed to be an additional mortality factor in exposed insects. Results show that NSA could provide an alternative to conventional synthetic organic insecticides and warrant further research on the development of enhanced NSA derived products.
Keywords: Sitophilus oryzae; biological efficacy; mode of action; nanoinsecticide

Body stores of emergent aquatic insects are associated with body size, sex, swarming behaviour and dispersal strategies - Gerber, Rémi; Cabon, Lilian; Piscart, Christophe; Roussel, Jean Marc; Bergerot, Benjamin (Freshwater Biology, 2022)
Dispersal is a determining step in the life cycle of insects and a key factor of their energy budget. If the body stores of terrestrial insects are relatively well-documented, those of merolimnic insects (i.e., with aquatic larvae and terrestrial winged adults) remain poorly investigated. We assayed the body stores (protein, carbohydrate and lipid contents) of 18 families of merolimnic insects, encompassing a wide diversity of biological and ecological traits. We highlighted allometry between body stores and mass. The proportion of triglyceride and free carbohydrate relatively decreases with an increase in absolute insect mass, whereas protein and glycogen contents are proportional. We found a significant effect of insect order, Diptera having relatively more proteins than Trichoptera. For swarming taxa, males have relatively more triglycerides than their conspecific female. Passive dispersers are characterised by higher protein and glycogen contents Each body store was associated with specific life-history traits, emphasising the importance of considering each body store independently to better understand the associated functions. Dispersal strategies seem to be the main structuring factor underlying body store patterns of merolimnic insects, being significantly associated with the variation in adjusted triglycerides (30%), proteins (21%), glycogen (29%) and free carbohydrates (17%). However, our study estimated the role of flight only indirectly through the biological traits of insects. Future works should focus on identifying which substrates are used for flight, by comparing the proportion of body stores before and after flight, as well as protein identification to distinguish proteins associated with flight or reproduction. These further studies will help researchers in understanding the link between body stores of emerging merolimnic insects and the various facets of their ecology.
Keywords: allometry; aquatic insects; carbohydrates; lipids; proteins

Water Balance in Land Arthropods - Edney, Eric B. (Water Balance in Land Arthropods, 1977)
no abstract available

Annual Review of Entomology Dehydration Dynamics in Terrestrial Arthropods: From Water Sensing to Trophic Interactions - Benoit, Joshua B; Mccluney, Kevin E; Degennaro, Matthew J; Dow, Julian A T (Annu. Rev. Entomol. 2023, 2022)
Since the transition from water to land, maintaining water balance has been a key challenge for terrestrial arthropods. We explore factors that allow terrestrial arthropods to survive within a variably dry world and how they shape ecological interactions. Detection of water and hydration is critical for maintaining water content. Efficient regulation of internal water content is accomplished by excretory and osmoregulatory systems that balance water intake and loss. Biochemical and physiological responses are necessary as water content declines to prevent and repair the damage that occurs during dehydration. Desiccation avoidance can occur seasonally or daily via a move to more favorable areas. Dehydration and its avoidance have ecological impacts that extend beyond a single species to alter trophic interactions. As climate changes, evolutionary and ecological processes will be critical to species survival during drought.
Keywords: climate change; dehydration; drought; humidity sensing; water balance

Comparative efficacy of Neem derivatives and imidacloprid against some cotton pests - Asif, Muhammad Usman; Muhammad, Raza; Sohail, Mubasshir (2018)

An overview on the fate and behavior of imidacloprid in agricultural environments - Fouad, Mohamed R.; Abdel-Raheem, Shaban A.A. (Environmental Science and Pollution Research, 2024)
This review provides an overview on the fate and behavior of imidacloprid, a neonicotinoid insecticide, in agricultural environments. The study focuses on four key aspects: adsorption and leaching of imidacloprid in soil, degradation and hydrolysis of imidacloprid in soil and water, uptake and persistence of imidacloprid in plants, and volatilization of imidacloprid to the atmosphere. The review presents the latest findings from research on each of these topics. While imidacloprid is highly effective at controlling pests, it is also known to persist in the environment, posing risks to non-target organisms such as bees, birds, and aquatic life. Moreover, there is increasing concern about its potential to accumulate in the soil and water systems, which may have long-term effects on the ecosystem. The review suggests that better understanding of the behavior and fate of imidacloprid in agricultural environments is essential for developing effective strategies to minimize its environmental impact. Graphical abstract: (Figure presented.).
Keywords: Degradation; Environment; Hydrolysis; Imidacloprid; Neonicotinoid insecticides; Toxicity

Neonicotinoids: Systemic Insecticides and Systematic Failure - Kurwadkar, Sudarshan; Evans, Amanda (Bulletin of Environmental Contamination and Toxicology, 2016)

Neonics vs bees - CRESSEY, DANIEL (Nature, 2017)

Worldwide pesticide usage and its impacts on ecosystem - Sharma, Anket; Kumar, Vinod; Shahzad, Babar; Tanveer, Mohsin; Sidhu, Gagan Preet Singh; Handa, Neha; Kohli, Sukhmeen Kaur; Yadav, Poonam; Bali, Aditi Shreeya; Parihar, Ripu Daman; Dar, Owias Iqbal; Singh, Kirpal; et al. (SN Applied Sciences, 2019)
Pesticides are extensively used in modern agriculture and are an effective and economical way to enhance the yield quality and quantity, thus ensuring food security for the ever-growing population around the globe. Approximately, 2 million tonnes of pesticides are utilized annually worldwide, where China is the major contributing country, followed by the USA and Argentina, which is increasing rapidly. However, by the year 2020, the global pesticide usage has been estimated to increase up to 3.5 million tonnes. Although pesticides are beneficial for crop production point of view, extensive use of pesticides can possess serious consequences because of their bio-magnification and persistent nature. Diverse pesticides directly or indirectly polluted air, water, soil and overall ecosystem which cause serious health hazard for living being. In the present manuscript, an attempt has been made to critically review the global usage of different pesticides and their major adverse impacts on ecosystem, which will provide guidance for a wide range of researchers in this area.
Keywords: Global pesticide usage; Pesticide application; Pesticide bio-magnification; Pesticide ecotoxicology

A beekeeper's perspective on the neonicotinoid ban - Carreck, Norman L. (Pest Management Science, 2017)
Bees and agrochemicals have a long history. For example, the first volume of IBRA's journal Bee World in 1919 contains mention of poisoning of bees by spraying an orchard with lead arsenate. Bees being insects, it is self-evident that the use of insecticides to control crop pests poses a risk to them. Bee poisoning incidents became a very serious problem in the 1960s and 1970s with spraying of, in particular, oilseed rape with organophosphorus compounds. The introduction of carbamates and then especially synthetic pyrethroids reduced these problems. Data from the Wildlife Incident Investigation Scheme show that in recent years there have been very few poisoning incidents in the United Kingdom that can be attributed to agricultural insecticides. The introduction of neonicotinoid insecticides has, however, been very controversial. Almost as soon as they were introduced in the 1990s, French beekeepers blamed colony losses on imidacloprid used on sunflowers and maize, but restrictions on its use did not lead to a reduction in losses or to a reduction in beekeepers' concerns. Acute pesticide poisoning incidents by neonicotinoids in Germany and Italy in 2008 further sealed their reputation. Despite laboratory evidence showing their harm, field experience remains equivocal, and many commercial beekeepers continue to move their colonies to oilseed rape crops for honey production. The neonicotinoid moratorium has undoubtedly led to the increased use of older insecticides, and the effect of this on bee populations is unknown and unquantified. Many beekeepers are currently confused by the conflicting evidence. © 2016 Society of Chemical Industry.
Keywords: beekeepers; bees; moratorium; neonicotinoids

Regulatory Evolution of Neonicotinoid Insecticides as Plant Protection Active Substances in Europe - Marchand, Patrice A. (Agrochemicals, 2023)
Neonicotinoid (NN) insecticides derived from natural insecticide nicotine are EU chemical crop protection systemic active substances that are controversial regarding their toxicity and ecotoxicity, especially versus pollinators and birds. Clearly, the last European evaluation by the European Food Safety Authority exhibited a danger to wild and managed bees. Concomitantly, the decline in birds was partially attributed to this class of substances, which constitutes a family in itself, both in Europe and the USA. At the regulatory level, following the initial approval waves in 2011 and 2019, and mainly taking into account these ecotoxicological considerations, the commission banned the use of three NN insecticides in 2013 (imidacloprid, clothianidin, and thiamethoxam), and later, only one NN (acetamiprid) was renewed. Four NN approvals were removed by the end of approval or non-renewal in 2019 and 2020, and two are currently concerns for renewals in 2025, even if extensions of the approval durations of these NNs are to be expected due to the current slowness of the renewal procedure. Therefore, from the total number (17) of NN insecticide molecules known all over the world, up to seven NN were approved by the EU plant protection Regulation EC 1107/2009 between 2011 and now. All of these active substances are listed in Parts A and B of Regulation EU 540/2011 managing active substances. The regulatory evolution of these agrochemicals is analysed in this work, from the corresponding global modifications in terms of the number of active substances, employment, functions, uses covered, protected crops, and maximum residue limits. We also analysed their ability to persist as an agrochemical family and the potential of the inclusion of new NN members together with their current restrictions during their active substance life in Europe.

Neonicotinoids: Still present in farmland birds despite their ban - Fuentes, Elva; Gaffard, Agathe; Rodrigues, Anaïs; Millet, Maurice; Bretagnolle, Vincent; Moreau, Jérôme; Monceau, Karine (2023)

Neonicotinoid insecticides in global agricultural surface waters – Exposure, risks and regulatory challenges - Stehle, Sebastian; Ovcharova, Viktoriia; Wolfram, Jakob; Bub, Sascha; Herrmann, Larissa Zoë; Petschick, Lara Luisa; Schulz, Ralf (Science of the Total Environment, 2023)
Neonicotinoids are the most widely used insecticides worldwide. However, the widespread usage of neonicotinoids has sparked concerns over their effects on non-target ecosystems including surface waters. We present here a comprehensive meta-analysis of 173 peer-reviewed studies (1998–2022) reporting measured insecticide concentrations (MICs; n = 3983) for neonicotinoids in global surface waters resulting from agricultural nonpoint source pollution. We used compound-specific regulatory threshold levels for water (RTLSW) and sediment (RTLSED) defined for pesticide authorization in Canada, the EU and the US, and multispecies endpoints (MSESW) to assess acute and chronic risks of global neonicotinoid water-phase (MICSW; n = 3790) and sediment (MICSED; n = 193) concentrations. Results show a complete lack of exposure information for surface waters in >90 % of agricultural areas globally. However, available data indicates for MICSW overall acute risks to be low (6.7 % RTLSW_acute exceedances), but chronic risks to be of concern (20.7 % RTLSW_chronic exceedances); exceedance frequencies were particularly high for chronic MSESW (63.3 %). We found RTLSW exceedances to be highest for imidacloprid and in less regulated countries. Linear model analysis revealed risks for global agricultural surface waters to decrease significantly over time, potentially biased by the lack of sensitive analytical methods in early years of neonicotinoid monitoring. The Canadian, EU and US RTLSW differ considerably (up to factors of 223 for RTLSW_acute and 13,889 for RTLSW_chronic) for individual neonicotinoids, indicating large uncertainties and regulatory challenges in defining robust and protective RTLs. We conclude that protective threshold levels, in concert with increasing monitoring efforts targeting agricultural surface waters worldwide, are essential to further assess the ecological consequences from anticipated increases of agricultural neonicotinoid uses.
Keywords: Agricultural surface waters; Meta-analysis; Monitoring; Pesticides; Regulatory risk assessment

Sub-lethal Effects of Imidacloprid on Nile Tilapia (Oreochromis niloticus) - Günal, Aysel Çağlan; Erkmen, Belda; Paçal, Elif; Arslan, Pınar; Yildirim, Zuhal; Erkoç, Figen (Water, Air, and Soil Pollution, 2020)
Imidacloprid (1-(6-chloro-3-pyridylmethyl)-N-nitroimidazolidin-2-ylideneamine (CAS No: 138261–41-3), neonicotinoid insecticide, and agricultural plant protectants were applied as seed and soil treatments. The aim of the present study is to determine the effects of sub-lethal imidacloprid concentrations on the histopathology and oxidative stress parameters with lipid peroxidation (LPO) to standard non-target test organism, tilapia (Oreochromis niloticus). 50 and 100 mgL−1 imidacloprid concentrations were chosen for experimental groups with control group. Fish were stocked in 60 L glass aquaria, maintained in aerated and dechlorinated tap water. The mean weight and length of tilapia were 37.78 ± 2.19 g and 12.98 ± 0.22 cm, respectively. After 24 and 96 h exposure to sub-lethal imidacloprid concentrations, the fish were sacrificed; tissue samples of gill and liver were snap frozen in liquid nitrogen for oxidative stress parameters and LPO assays, fixed (buffered 10% formalin) for histopathology. After exposure to sub-lethal imidacloprid, LPO was induced in both tissues. MDA levels were increased in both tissues, while GSH levels were reduced at the high concentration of imidacloprid in the gill tissues after 96 h and both concentrations in the liver tissues (P < 0.05). There were no significant differences for antioxidant enzymes CAT, SOD and GPx between exposed and control groups (P > 0.05). Gill tissues revealed hyperaemia, epithelial lifting, fusion of secondary lamellae and telangiectasia, whereas hyperaemia, mononuclear cell infiltration vacuolization of hepatocytes and hydropic degeneration were observed in liver tissues. Imidacloprid is very toxic to the non-target species in the aquatic ecosystem even at sub-lethal concentrations.
Keywords: Antioxidant system biomarkers; Histopathology; Lipid peroxidation; Oxidative stress biomarkers

Occurrence and Distribution of Neonicotinoid Pesticides in Chinese Waterways: A Review - Zhang, Shaoqing; Jiang, Jia Qian (Environments - MDPI, 2023)
Neonicotinoid pesticides (NEOs) were initially considered viable alternatives to conventional organo-pesticides extensively used in agriculture, horticulture, and households. However, the increased frequency and concentration of NEOs in waterways have drawn significant attention and concern due to the resulting threats to ecosystems and public health worldwide. The demand for monitoring NEOs in water has led to numerous efforts in many countries and regions. Given occurrence and distribution of these pesticides/insecticides. This study reviews NEOs monitoring in China from 2019 to 2022, aiming to gather and analyse information on China’s efforts in NEOs monitoring to provide reference for future research. The study primarily focuses on the southern and southeastern regions of China, specifically on lakes and tributaries of rivers, including Taihu Lake, Pearl River, Yangtze River, Songhua River, and Liao River. This focus can be attributed to the prioritisation and environmental demands related to the local economic status and major developmental tasks. The evaluation of the corresponding ecological risks of human exposure to NEOs ranged from low to medium-high levels. However, despite these findings, contamination from NEOs is still considered to lack sufficient attention and concern. Additionally, the presence of NEOs in other environmental media, such as indoor dust, wheat grains, vegetables, and teas, requires close attention in the future.
Keywords: ecological risk; neonicotinoid pesticides (NEOs) occurrence; public health; water contaminant monitoring

Pollution characteristics, environmental issues, and green development of neonicotinoid insecticides in China: Insights from Imidacloprid - Wang, Jin Ze; Hou, Jie; Wang, Li Xi; Zhu, Zi Yang; Han, Bing Jun; Chen, Li Yuan; Liu, Wen Xin (Environmental Pollution, 2025)
Imidacloprid (IMI), a leading neonicotinoid insecticide, is widely used in China. Nevertheless, owing to its high toxicity to pollinators, regulatory scrutiny of its usage has increased in recent years. Despite this, no relevant issues have been announced in China, and its usage continues to rise. In this study, we systematically reviewed the development history, pollution characteristics, and environmental problems associated with IMI in China, which is imperative to promote its green development. The results show that most IMI products (97.1%) in China are registered for agricultural use. Owing to its extensive use and strong migration ability in different environmental matrices, IMI has been broadly detected in multiple environmental media. The average detection rate (DR) of IMI in soils, ambient water, and sediments were 90.7%, 81.3% and 84.5%, respectively, and the corresponding concentrations were 54.6 ± 83.8 ng/g dry weight (dw), 32.8 ± 103 ng/L, and 1.7 ± 2.9 ng/g dw, respectively, indicating high IMI abundance in multiple environmental media in China. The spatiotemporal distribution of IMI was generally determined by its application modes, transport, and degradation rates. IMI is commonly overused in China, leading to the development of high IMI resistance in many pests, and a high DR of IMI in food, drinking water, and human bodies. To alleviate IMI pollution in China, the joint efforts of the government, farmers, and scientists are necessary, including but not limited to formulating laws and regulations, strengthening governmental supervision, improving farmers’ knowledge of IMI use, and promoting technological innovation in IMI and application methods.
Keywords: China; Environmental pollution; Green development; Imidacloprid; Interventions

Environmental impacts of an imidaclopridcontaining formulation: from soils to waters - Bori, Jaume; Ribalta, Carla; Xavier, Domene; Riva, Maria; Ribó, Juan (2015)

INFLUENCE OF SYLGARD 309 ADJUVANT ON IMIDACLOPRID USED IN CONTROLLING TOMATO LEAF MINOR, Tuta absoluta INFESTING TOMATO GROWN IN OPEN FIELD - Ismail, Hassan S; Omar, A E; El-Sobki, A E; Hendawi, M Y (Zagazig J. Agric. Res)
Tomato is the most widely grown vegetables in the world and also the most important item of the vegetables processing sector. Tomato is important vegetable plant in our agriculture map which used as food in many countries of the world and especially Egypt. It infested with many pests, among of the most serious pest, tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae). This study was aimed to investigate efficiency of Imidacloprid applied alone and in a binary mixture with Sylgard 309 adjuvant against this pest under field conditions, effect of Imidacloprid on tomato yield and determination of Imidacloprid residues in tomato fruits and soil. Results illustrated that adding Sylgard 309 adjuvant to Imidacloprid caused increasing mean reduction percentage to 98.02%, recording the first superior treatment. In case of tomato yield during two summer successive seasons 2014 and 2015, results reported that tomato yield increased by adding Sylgard 309 adjuvant to Imidacloprid and recorded superior yield of 600.75 and 613.15 Kg with increasing value of 41.27% and 35.44%, respectively during seasons 2014 and 2015 compared with control. Unfortunately, adding Sylgard 309 adjuvant to Imidacloprid was causation in increasing the half-life (T ½) values and the quantities of residues in tomato fruits and soil, that were less than the maximum residue level (0.5 mg/kg).
Keywords: Tomato; Tuta absoluta; imidacloprid; residues; soil; sylgard 309; yield

Effect of formulations and adjuvants on the properties of acetamiprid solution and droplet deposition characteristics sprayed by UAV - Zeeshan, Muhammad; Li, Haoran; Yousaf, Gulfam; Ren, Hao; Liu, Yapeng; Arshad, Muhammad; Dou, Zechen; Han, Xiaoqiang (Frontiers in Plant Science, 2024)
While the pesticide formulations are widely used for pest control, the combined effects of these formulations with adjuvants on droplet behavior, spraying characteristics, and pest control still need to be studied. To clarify their impact on droplet behavior, spraying characteristics, and control efficacy, six formulations of acetamiprid and six adjuvants were examined. A series of laboratory and field experiments were conducted to analyze the physicochemical properties, toxicity against cotton aphids, droplet deposition characteristics, and droplet drift. The results indicated that 5% acetamiprid micro-emulsion (ME) enhanced the physicochemical features and effectiveness in pest control compared to other formulations. The nongjianfei considerably enhanced the efficiency of all acetamiprid formulations when added. The addition of selected adjuvants to pesticide formulations improved the performance of certain physicochemical properties such as viscosity and surface tension and led to higher aphid mortality rates, demonstrating enhanced pest control effectiveness during the present study. In the field experiments, the combination effect of acetamiprid formulations and adjuvants exhibited a higher droplet size, coverage, and density within the cotton canopy. However, 5% acetamiprid ME was found to be most effective followed by nongjianfei. Furthermore, 5% acetamiprid ME with adjuvant reduced the droplet drift and provided better deposition when compared with other formulations. Overall, the combination of specific formulations and adjuvants led to improved physicochemical properties, enhanced droplet deposition characteristics, reduced spray drift, and increased pesticide deposition. These findings highlighted the significance of selecting appropriate pesticide formulations and adjuvants and provided a solid foundation for efficient pesticide spraying through UAVs.
Keywords: adjuvants; droplet deposition; formulations; physicochemical properties; unmanned aerial vehicles

Photocatalytic degradation of imidacloprid in soil: Application of response surface methodology for the optimization of parameters - Sharma, Teena; Toor, Amrit Pal; Rajor, Anita (RSC Advances, 2015)
The photocatalytic mineralization of imidacloprid (IMI) in soil to inorganic ions and the formation of various intermediates using TiO2 as the photocatalyst have been investigated under UV light. Various parameters, viz., catalyst concentration, soil depth and pH, intensity of light and initial concentration of IMI were optimized theoretically by using a central composite design based on a response surface methodology and were correlated with experimental results. The statistical analysis from the modelling results indicates that the degradation efficiency of IMI is affected by the depth of soil and the intensity of light, but the effects of the pH and the initial concentration of imidacloprid are more dominant. The optimum conditions obtained for the maximum degradation of imidacloprid were at pH = 3, intensity of UV light = 30 W m-2, soil depth = 0.2 cm and initial concentration of imidacloprid = 10 mg kg-1 of soil. Under these optimum conditions, the highest degradation efficiency of 83% was achieved after 18 h of UV light irradiation. The identification of various photoproduced intermediates of IMI by LC-MS analysis revealed its degradation, whereas the increase in the formation of inorganic ions with time of UV light irradiation confirms its mineralization. This journal is

Modeling photodegradation kinetics of three systemic neonicotinoids—dinotefuran, imidacloprid, and thiamethoxam—in aqueous and soil environment - Kurwadkar, Sudarshan; Evans, Amanda; DeWinne, Dustan; White, Peter; Mitchell, Forrest (Environmental Toxicology and Chemistry, 2016)
Environmental presence and retention of commonly used neonicotinoid insecticides such as dinotefuran (DNT), imidacloprid (IMD), and thiamethoxam (THM) are a cause for concern and prevention because of their potential toxicity to nontarget species. In the present study the kinetics of the photodegradation of these insecticides were investigated in water and soil compartments under natural light conditions. The results suggest that these insecticides are fairly unstable in both aqueous and soil environments when exposed to natural sunlight. All 3 insecticides exhibit strong first-order degradation rate kinetics in the aqueous phase, with rate constants kDNT, kIMD, and kTHM of 0.20 h−1, 0.30 h−1, and 0.18 h−1, respectively. However, in the soil phase, the modeled photodegradation kinetics appear to be biphasic, with optimal rate constants k1DNT and k2DNT of 0.0198 h−1 and 0.0022 h−1 and k1THM and k2THM of 0.0053 h−1 and 0.0014 h−1, respectively. Differentially, in the soil phase, imidacloprid appears to follow the first-order rate kinetics with a kIMD of 0.0013 h−1. These results indicate that all 3 neonicotinoids are photodegradable, with higher degradation rates in aqueous environments relative to soil environments. In addition, soil-encapsulated imidacloprid appears to degrade slowly compared with dinotefuran and thiamethoxam and does not emulate the faster degradation rates observed in the aqueous phase. Environ Toxicol Chem 2016;35:1718–1726. © 2015 SETAC.
Keywords: Agriculture; Environmental fate; Environmental impact; Insecticide; Neonicotinoids

Effect of Abiotic Factors on Degradation of Imidacloprid - Mahapatra, Bibhab; Adak, Totan; Patil, Naveen K.B.; Pandi, G. Guru P.; Gowda, G. Basana; Yadav, Manoj Kumar; Mohapatra, S. D.; Rath, P. C.; Munda, Sushmita; Jena, Mayabini (Bulletin of Environmental Contamination and Toxicology, 2017)
The role of soil moisture, light and pH on imidacloprid dissipation was investigated. A high performance liquid chromatography (HPLC) based method was developed to quantify imidacloprid present in soil with a recovery of more than 82%. Rate of dissipation of imidacloprid from soil was faster in submerged condition compared to field capacity and air dried condition. Imidacloprid dissipated non-significantly between sterile and non-sterile soils, but at field capacity, the dissipation was faster in non-sterile soil compared to sterile soil after 60 days of incubation. Similarly, under submergence, the dissipation of imidacloprid was 66.2% and 79.8% of the initial in sterile and non-sterile soils, respectively. Imidacloprid was rather stable in acidic and neutral water but was prone to photo-degradation. Therefore, imidacloprid degradation will be faster under direct sunlight and at higher soil moisture.
Keywords: Dissipation; Field capacity; Half life; Sunlight; pH

Efficient degradation of imidacloprid in soil by thermally activated persulfate process: Performance, kinetics, and mechanisms - Zou, Ziyu; Huang, Xin; Guo, Xingle; Jia, Chunhong; Li, Baotong; Zhao, Ercheng; Wu, Junxue (Ecotoxicology and Environmental Safety, 2022)
Imidacloprid (IMI) as a first-generation commercial neonicotinoid has been frequently detected in the environment in recent years. In this study, the efficient degradation of IMI in soil by a thermally activated persulfate (PS) process was investigated. The degradation efficiencies of IMI were in the range of 82–97% with the PS dosage of 10 mM, when the initial concentrations of IMI were 5–50 mg/kg in the soil. Degradation of the IMI was fitted with a pseudo-first-order kinetic model under different reaction temperatures. Inhibition effects of the common inorganic anions on the IMI degradation in the system followed the order Cl- > HCO3- > H2PO4- > NO3-. Soil pH and soil organic matter were also main factors affecting the degradation of IMI. The degradation efficiencies (64–97%) of three other typical neonicotinoids (acetamiprid, clothianidin, and dinotefuran) indicated that the thermally activated persulfate process could be used for remediation of neonicotinoid-contaminated soil. Quenching experiments indicated that the major reactive species in IMI degradation were SO4•-, O2•-, and •OH. Six degradation intermediates of IMI were inferred in the soil, and degradation pathways of IMI included hydroxylation, denitrification, C-N bond break and further oxidation.
Keywords: Degradation mechanisms; Imidacloprid; Persulfate; Soil

Removal of imidacloprid from polluted water using adsorption and membrane separation technologies - Qurie, Mohannad; Alkhatib, Mahmoud; Bufo, Sabino Aurelio; Scrano, Laura; Khamis, Mustafa; Ayyad, Ibrahim; Karaman, Rafik (Desalination and Water Treatment, 2021)
In this work, the stability of imidacloprid in fresh water and sludge was studied. The results revealed that the pesticide is unstable in both media. In fresh water, it underwent hydrolysis whereas a degradation to several metabolites has been observed in sludge. The rate constants for the hydrolysis and degradation at 25°C were 0.0.0067 and 0.0.0099 d–1, respectively. Monitoring the degradation of imidacloprid in sludge by high-pressure liquid chromatography-mass spec trometry (HPLC-MS) revealed that five metabolites have emerged during the study. These metab-olites include imidacloprid urea, imidacloprid-guanidine, 6-hydroxynicotinic acid, an olefin, and 5-hydroxy, 1-(6-chloro-3-pyridylmethyl)-2-(nitroimino)-imidazolidin-5-ol. The efficiency of Al-Quds University Wastewater Treatment Plant towards the removal of imidacloprid indicates that the ultrafiltration-hollow fiber unit was insufficient, whereas the ultrafiltration-spiral wound, activated carbon, and reverse osmosis units were efficient for complete removal of the pesticide. Adsorption experiments of imidacloprid using either activated charcoal or micelle-clay complex were found to fit Langmuir isotherms better than Freundlich isotherm. The data demonstrate a higher Langmuir Qmax value for the activated charcoal (126.6 mg g–1) when compared to the micelle-clay complex (11.76 mg g–1). Filtration column experiments conducted with mixed micelle-clay complex and sand (using a ratio of 1/50 by mass) at a flow rate of 2 mL min–1 and influent concentration of 50 mg L–1 revealed that a sufficient removal of imidacloprid was achieved in the first fraction of 100 Ml elution. These findings indicate that the adsorption technology using the micelle-clay comple provides efficient removal of imidacloprid in continuous flow mode.
Keywords: Charcoal; Freundlich isotherm; Imidacloprid; Langmuir isotherm; Micelle-clay complex; Pesticides

Effects of imidacloprid on the ecology of sub-tropical freshwater microcosms - Sumon, Kizar Ahmed; Ritika, Afifat Khanam; Peeters, Edwin T.H.M.; Rashid, Harunur; Bosma, Roel H.; Rahman, Md Shahidur; Fatema, Mst Kaniz; Van den Brink, Paul J. (Environmental Pollution, 2018)
The neonicotinoid insecticide imidacloprid is used in Bangladesh for a variety of crop protection purposes. Imidacloprid may contaminate aquatic ecosystems via spray drift, surface runoff and ground water leaching. The present study aimed at assessing the fate and effects of imidacloprid on structural (phytoplankton, zooplankton, macroinvertebrates and periphyton) and functional (organic matter decomposition) endpoints of freshwater, sub-tropical ecosystems in Bangladesh. Imidacloprid was applied weekly to 16 freshwater microcosms (PVC tanks containing 400 L de-chlorinated tap water) at nominal concentrations of 0, 30, 300, 3000 ng/L over a period of 4 weeks. Results indicated that imidacloprid concentrations from the microcosm water column declined rapidly. Univariate and multivariate analysis showed significant effects of imidacloprid on the zooplankton and macroinvertebrate community, some individual phytoplankton taxa, and water quality variables (i.e. DO, alkalinity, ammonia and nitrate), with Cloeon sp., Diaptomus sp. and Keratella sp. being the most affected species, i.e. showing lower abundance values in all treatments compared to the control. The observed high sensitivity of Cloeon sp. and Diaptomus sp. was confirmed by the results of single species tests. No significant effects were observed on the species composition of the phytoplankton, periphyton biomass and organic matter decomposition for any of the sampling days. Our study indicates that (sub-)tropical aquatic ecosystems can be much more sensitive to imidacloprid compared to temperate ones.
Keywords: Bangladesh; Freshwater ecosystem; Insecticide; Neonicotinoid

Microporous carbon for fast and simple electrochemical detection of imidacloprid insecticide in fruit and water samples - Kaewket, Keerakit; Ngamchuea, Kamonwad (RSC Advances, 2023)
Herein, a fast and sensitive electrochemical sensor was developed for imidacloprid detection using low-cost disposable microporous carbon screen-printed electrodes. The electrochemical behaviour of imidacloprid at the microporous material was investigated in detail. The developed sensor allowed imidacloprid detection in the linear range of 0.00-1.00 mM with a sensitivity of 14.43 ± 0.42 μA mM−1 and a detection limit of 2.54 μM (3sB/m). The sensor showed excellent selectivity and high tolerance to possible interference from other tested insecticides and ions. Excellent repeatability (3.42%, n = 3) and reproducibility (2.23%, n = 3) were demonstrated. Application of the sensor in various fruit and water samples without any treatment showed 96.2-103.0% recoveries. The developed sensor further revealed that the most effective method for removing imidacloprid residue from fruit samples was via washing with a mixture of 5% w/v NaCl and 5% w/v bicarbonate at 40 °C.

Degradation of the neonicotinoid pesticide imidacloprid by electrocoagulation and ultrasound - Halkijevic, Ivan; Licht, Katarina; Kosar, Vanja; Bogdan, Lucija (Scientific Reports, 2024)
Imidacloprid is still a widely used neonicotinoid insecticide that is banned in many countries because of the associated environmental risks. Due to the inefficiency of conventional wastewater treatments for pesticide removal, new treatment methods are being investigated. Electrochemical methods, including electrocoagulation (EC), seem to be promising alternatives considering their effectiveness in removing various pollutants from wastewater. The aim of this study was to investigate the effects of electrode material, current density, ultrasound, and operation time on the efficiency of imidacloprid removal from a model solution by EC. The combination of aluminum electrodes and 20 A of applied current for 20 min resulted in total imidacloprid degradation. A simplified energy balance was introduced as a form of process evaluation. Combining ultrasound with EC resulted in 7% to 12% greater efficacy than using only EC.

Hydrophilic magnetic COFs: The Answer to photocatalytic degradation and removal of imidacloprid insecticide - AlNeyadi, Shaikha S.; Alhassani, Mohammed T.; Mukhtar, Muneb R.; Alblooshi, Hamad K.; Jama, Sultan A.; Al Mujaini, Ibrahim; Aleissaee, Ali S. (Heliyon, 2024)
The widespread use of imidacloprid (IMI) in pest control presents significant environmental challenges due to its persistence and low removal efficiency. This study introduces magnetic Covalent Organic Frameworks (COFs) functionalized with Fe₃O₄ nanoparticles (Fe₃O₄@HMN-COF, Fe₃O₄@MAN-COF, and Fe₃O₄@SIN-COF) as efficient adsorbents for IMI removal from water. These COFs, engineered with nitrogen-rich structures and extensive π-electron systems, achieve superior adsorption through π-π interactions, hydrophobic interactions, and hydrogen bonding. Characterization via FT-IR, XRD, and nitrogen sorption isotherms confirmed their high hydrophilicity, stability, and large surface areas. The magnetic properties of the COFs facilitated easy separation from water, enhancing practicality. Kinetic studies for all COFs indicated a pseudo-second-order model, suggesting chemisorption, with adsorption capacities of 600 mg/g for Fe₃O₄@HMN-COF, 480 mg/g for Fe₃O₄@MAN-COF, and 375 mg/g for Fe₃O₄@SIN-COF. Thermodynamic analyses revealed spontaneous and endothermic adsorption processes. Reusability tests showed minimal capacity loss over multiple cycles, underscoring their practical applicability. Practical tests in honey and fruit samples confirmed high efficacy, demonstrating the COFs' versatility. The study also optimized the photocatalytic degradation of imidacloprid using these COFs, with Fe₃O₄@HMN-COF achieving 98.5 % efficiency under optimal conditions (10 mg L−1 IMI, 0.01 g catalyst dose, pH 11, 30 °C, UV light). These findings highlight the potential of magnetic COFs for sustainable environmental remediation of pesticide-contaminated water.
Keywords: Adsorption capacity; Imidacloprid; Magnetic COF; Photocatalytic degradation

Delayed and time-cumulative toxicity of imidacloprid in bees, ants and termites - Rondeau, Gary; Sánchez-Bayo, Francisco; Tennekes, Henk A.; Decourtye, Axel; Ramírez-Romero, Ricardo; Desneux, Nicolas (Scientific Reports, 2014)
Imidacloprid, one of the most commonly used insecticides, is highly toxic to bees and other beneficial insects. The regulatory challenge to determine safe levels of residual pesticides can benefit from information about the time-dependent toxicity of this chemical. Using published toxicity data for imidacloprid for several insect species, we construct time-to-lethal-effect toxicity plots and fit temporal power-law scaling curves to the data. The level of toxic exposure that results in 50% mortality after time t is found to scale as t 1.7 for ants, from t 1.6 to t 5 for honeybees, and from t 1.46 to t 2.9 for termites. We present a simple toxicological model that can explain t 2 scaling. Extrapolating the toxicity scaling for honeybees to the lifespan of winter bees suggests that imidacloprid in honey at 0.25 μ ... 1/4g/kg would be lethal to a large proportion of bees nearing the end of their life.

UNITED STATES ENVIRONMENTAL PROTECTION AGENCY WASHINGTON, DC 20460 OFFICE OF CHEMICAL SAFETY AND POLLUTION PREVENTION (2019)

Temporal and spatial trends of imidacloprid-related hazards in France - Perrot, Thomas; Bonmatin, Jean Marc; Jactel, Hervé; Leboulanger, Christophe; Goffaux, Robin; Gaba, Sabrina (Science of the Total Environment, 2024)
Neonicotinoids are the top-selling insecticides worldwide. Because of their method of use, mainly to coat seeds, neonicotinoids have been found to widely contaminate the environment. Their high toxicity has been shown to be a major concern in terms of impact on biodiversity, and the use of these insecticides has been associated with population declines of species in different countries. Despite the widespread recognition of the risk of neonicotinoids to biodiversity, their temporal and spatial use remains poorly known in many countries. Yet this information is essential to address the potential impacts of these pesticides on biodiversity and to inform measures to establish protected areas or biodiversity restoration. The present study relied a large publicly available dataset to characterise the temporal and spatial use in France of imidacloprid, the most widely used neonicotinoid worldwide, as well as analysed water contamination surveys between 2005 and 2022 to assess the contamination of the environment. The results show that imidacloprid was the main neonicotinoid used in France over the study period. This use was spatially structured, with higher use in northern and western France, particularly related to cereal and beet crops area. The water contamination survey indicated that imidacloprid has widely contaminated the environment and consequently increased the risk to biodiversity, especially in counties crossed by the Loire, Seine and Vilaine rivers. This risk increased between 2005 and 2018 due to the higher use of imidacloprid and decreased sharply after 2018 due to its ban, although it was reauthorized by derogation for sugar beet in 2021. This study is the first assessment of imidacloprid pressure on biodiversity in France and shows the spatial and temporal correlation between agricultural practices and the freshwater contamination level. These results will help to identify priority areas for mitigation and restoration measures.
Keywords: Agriculture; Biodiversity decline; Pesticide pollution; Pesticide risks; Surface water monitoring

What is the shelf life of Prime Source Imidacloprid 2F Select T/I?

Imidacloprid 5%EC, 25%WP, 30%FS, 70%WP Insecticide - POMAIS Agriculture

Imidacloprid CAS:138261-41-3

Is This Pesticide On My Shelf Still Good?

Using old pesticides may be perilous to your plants - MSU Extension - Getter, Kristin (2015)

Temporal variation of imidacloprid concentration and risk in waterways discharging to the Great Barrier Reef and potential causes - Warne, Michael St J.; Turner, Ryan D.R.; Davis, Aaron M.; Smith, Rachael; Huang, A. (Science of the Total Environment, 2022)
The widely used neonicotinoid insecticide imidacloprid has emerged as a significant risk to surface waters and the diverse aquatic and terrestrial fauna these ecosystems support. While herbicides have been the focus of research on pesticides in Australia's Great Barrier Reef catchment area, imidacloprid has been monitored in catchments across the region since 2009. This study assessed the spatial and temporal dynamics of imidacloprid in 14 waterways in Queensland, Australia over seven years in relation to land use and concentration trends. Imidacloprid could be quantified (i.e., concentrations were greater than the limit of reporting) in approximately 54% of all samples, but within individual waterways imidacloprid was quantified in 0 to 99.7% of samples. The percent of each catchment used to grow bananas, sugar cane and urban explained approximately 45% of the variation in imidacloprid concentrations and waterway discharge accounted for another 18%. In six waterways there were significant increases in imidacloprid concentrations and the frequency and magnitude of exceedances of aquatic ecosystem protection guidelines over time. Overall, the risk posed by imidacloprid was low with 74% of samples protecting at least 99% of species but it was estimated that upto 42% of aquatic species would experience harmful chronic effects. Potential explanations of the changes in imidacloprid were examined. Not surprisingly, the only plausible explanation of the increases was increased use of imidacloprid. While field-based measurement of the effects of imidacloprid are limited in the Great Barrier Reef Catchment Area (GBRCA) the risk assessment indicates that biological harm to aquatic organisms is highly likely. Action to reduce imidacloprid concentrations in the GBRCA waterways is urgently required to reverse the current trends and mitigate environmental impacts.
Keywords: Agrochemicals; Insecticides; Neonicotinoid; Risk assessment; Run-off; Water quality

Adsorption behavior of imidacloprid pesticide on polar microplastics under environmental conditions: critical role of photo-aging - Liu, Weiyi; Pan, Ting; Liu, Hang; Jiang, Mengyun; Zhang, Tingting (Frontiers of Environmental Science and Engineering, 2023)
The photo-aging behavior of microplastics (MPs) in natural environment has become a global concern. The ultraviolet radiation has enough energy to change the polymer structure and physical-chemical properties of MPs. Less attention has focused on the interactions of the photo-aged polar and biodegradable MPs with organic pollutants. This work investigated the structural properties of aged polar polyamide (PA) MPs and biodegradable polylactic acid (PLA) MPs exposed to ultraviolet irradiation and their adsorption behavior and mechanism for neonicotinoid insecticide imidacloprid (IMI). The results showed that the MPs had extensive changes in surface morphology and chemical properties after photo-aging. The C−N bond of PA MPs was disrupted to form more carbonyl groups. The oxygen-containing functional groups on the surface of aged PLA MPs were broken and generated relatively smaller molecules. The adsorption capacity of IMI on PA MPs decreased by 19.2 %, while the adsorption capacity of IMI on PLA MPs increased by 41.2 % after photo-aging. This depended on the natural structure of the MPs and their ability to absorb ultraviolet light. The electrostatic interactions, hydrogen bonds, van der Waals interactions, and polar-polar interactions were the main adsorption mechanisms of IMI on MPs. High initial solution pH and low ionic strength favored the adsorption of IMI by altering charge distribution on the MPs surface. The formation of the humic acid-IMI complexes decreased the concentration of IMI in the water phase and further decreased the adsorption on MPs. These results are enlightening for a scientific comprehension of the environmental behavior of the polar MPs. [Figure not available: see fulltext.].
Keywords: Environmental conditions; Microplastics; Neonicotinoid insecticide; Photo-aging; adsorption

Soil erosion and transport of Imidacloprid and Clothianidin in the upland field under simulated rainfall condition - Yadav, Ishwar Chandra; Watanabe, Hirozumi (Science of the Total Environment, 2018)
Surface runoff has been recognized as an important medium of pesticides transport to surface water and groundwater causing critical risk to the aquatic ecosystem. Although total pesticide transport in surface runoff in most cases reported being below 1% of applied mass, much larger losses may occur in extreme cases. In this study, surface runoff potential of Imidacloprid and Clothianidin was investigated in an upland field with 5% slope under two simulated rainfall experiments of 70 mm/h intensity. Additionally, the downward movement of the pesticides was determined in soil (n = 87) taken at several depths on different time scales. The result showed that the second rainfall experiment caused more surface runoff than first rainfall experiment, and accounted 30.0 mm and 21.2 mm of applied rainfall, respectively. The cumulative surface runoff developed during first and second rainfall experiments was equal to 30% and 44% of the applied rainfall, respectively. The sediment transport in runoff was relatively higher in second rainfall than first rainfall, and was mostly stable after 30 min of rainfall. The chemical masses of Imidacloprid and Clothianidin were primarily transported in runoff sediments than runoff water and accounted for 10.8% and 7.93% of the applied mass, respectively. The transport of Imidacloprid both in runoff water and sediment was 1–2 times greater than that of Clothianidin. The concentrations of both pesticides were measured highest in the second fraction of runoff (10 min) collected during the first experiment. In soil, the transport of both pesticides prior to rainfall experiment was 1–2 times greater than post-rainfall experiments. The concentration of these pesticides decreased continuously with the time in the upper layer of soil; while a gradual increase of the pesticides mass was observed in the second soil layer. The cumulative mass transport of both pesticides was directly proportional to the cumulative runoff depth.
Keywords: Clothianidin; Imidacloprid; Pesticide fate; Sediment transport; Soil erosion; Surface runoff

Wash off of imidacloprid and fipronil from turf and concrete surfaces using simulated rainfall - Thuyet, Dang Quoc; Jorgenson, Brant C.; Wissel-Tyson, Christopher; Watanabe, Hirozumi; Young, Thomas M. (Science of the Total Environment, 2012)
The surface runoff of imidacloprid granular product (GR) from turf surfaces, and imidacloprid emulsifiable concentrate (EC), fipronil suspension concentrate (SC) products and fipronil byproducts from concrete surfaces was investigated during 1. h rainfall simulations at 50. mm/h or 25. mm/h with product incubation times of 1.5. h, 1. d, 7. d, and 14. d. About 57.3% of the applied mass of imidacloprid, corresponding to an event mean concentration of 392.0μg/L, was washed off from the concrete surfaces after 1.5. h of incubation. After 1. d, 7. d, and 14. d of incubation on either turf or concrete surfaces, up to 5.9% of the applied mass of pesticide was removed in each of the run-off events. The maximum concentrations of pesticides were observed in the initial fraction of the runoff collected in the first rainfall event. They were 157.8, 3267.8 and 143.3μg/L for imidacloprid GR, imidacloprid EC and fipronil SC, respectively. Imidacloprid was not persistent on concrete surfaces, with run-off concentrations below detection limits in 7. d incubation experiments. The cumulative mass losses of imidacloprid from turf and fipronil from concrete had a linear relation with cumulative surface run-off depth, while cumulative mass losses of imidacloprid from concrete surfaces were better fit by a power function of the cumulative surface run-off depth. The concentrations of fipronil in the runoff from the third rainfall event at 14. d incubation time were still relatively high and ranged from 12.0 to 31.0μg/L. A toxicity unit approach was also employed to evaluate the potential acute toxicity of fipronil and its byproducts to aquatic organisms. © 2011 Elsevier B.V.
Keywords: Byproduct; First flush; Formulation; Insecticide; Runoff; Urban

Pesticides in water sources used for human consumption in the semiarid region of Argentina - Mas, Laura I.; Aparicio, Virginia C.; De Gerónimo, Eduardo; Costa, José L. (SN Applied Sciences, 2020)
Presence of pesticides in drinking water is an issue of great concern in agricultural areas. In Argentina’s semiarid regions, where surface water sources are scarce and groundwater may be of poor quality, rainwater becomes important for safe water supply. The expansion of agriculture in these regions due to no till management has led to a high use of pesticides which jeopardize the safety of all water sources used for human consumption. The objective was to monitor the presence of pesticides in different water sources from two agricultural areas of Santiago del Estero. Samples belonged to cisterns in which rainwater is collected, wells and dams. The most contaminated sources were dams, followed by cisterns and wells. Applied doses and frequency of use played an important role in the presence of pesticides. Thus, the most frequent molecules were mainly herbicides; atrazine and metolachlor were the most abundant. Glyphosate and aminomethylphosphonic acid presented the highest concentrations. Almost all measured values were below the US Environmental Protection Agency limits, but 73% of the samples exceeded the limit of 0.5 μg L−1 established by the European Union for the sum of molecules although only 7.4% of individual molecules exceeded the limit of 0.1 μg L−1. However, risk assessment showed that pesticides from all sources presented a low potential risk to human health through drinking water exposure route.
Keywords: Groundwater; Herbicides; Pesticides; Rainwater; Surface water

Soil water status shapes nutrient cycling in agroecosystems from micrometer to landscape scales - Bauke, Sara L.; Amelung, Wulf; Bol, Roland; Brandt, Luise; Brüggemann, Nicolas; Kandeler, Ellen; Meyer, Nele; Or, Dani; Schnepf, Andrea; Schloter, Michael; Schulz, Stefanie; Siebers, Nina; et al. (Journal of Plant Nutrition and Soil Science, 2022)
Soil water status, which refers to the wetness or dryness of soils, is crucial for the productivity of agroecosystems, as it determines nutrient cycling and uptake physically via transport, biologically via the moisture-dependent activity of soil flora, fauna, and plants, and chemically via specific hydrolyses and redox reactions. Here, we focus on the dynamics of nitrogen (N), phosphorus (P), and sulfur (S) and review how soil water is coupled to the cycling of these elements and related stoichiometric controls across different scales within agroecosystems. These scales span processes at the molecular level, where nutrients and water are consumed, to processes in the soil pore system, within a soil profile and across the landscape. We highlight that with increasing mobility of the nutrients in water, water-based nutrient flux may alleviate or even exacerbate imbalances in nutrient supply within soils, for example, by transport of mobile nutrients towards previously depleted microsites (alleviating imbalances), or by selective loss of mobile nutrients from microsites (increasing imbalances). These imbalances can be modulated by biological activity, especially by fungal hyphae and roots, which contribute to nutrient redistribution within soils, and which are themselves dependent on specific, optimal water availability. At larger scales, such small-scale effects converge with nutrient inputs from atmospheric (wet deposition) or nonlocal sources and with nutrient losses from the soil system towards aquifers. Hence, water acts as a major control in nutrient cycling across scales in agroecosystems and may either exacerbate or remove spatial disparities in the availability of the individual nutrients (N, P, S) required for biological activity.
Keywords: catchments; microbiology; molecular chemistry; nitrogen; phosphorus; plants; sulfur

Modeling soil water content and reference evapotranspiration from climate data using deep learning method - Alibabaei, Khadijeh; Gaspar, Pedro D.; Lima, Tânia M. (Applied Sciences (Switzerland), 2021)
In recent years, deep learning algorithms have been successfully applied in the development of decision support systems in various aspects of agriculture, such as yield estimation, crop diseases, weed detection, etc. Agriculture is the largest consumer of freshwater. Due to challenges such as lack of natural resources and climate change, an efficient decision support system for irrigation is crucial. Evapotranspiration and soil water content are the most critical factors in irrigation scheduling. In this paper, the ability of Long Short-Term Memory (LSTM) and Bidirectional LSTM (BLSTM) to model daily reference evapotranspiration and soil water content is investigated. The application of these techniques to predict these parameters was tested for three sites in Portugal. A single-layer BLSTM with 512 nodes was selected. Bayesian optimization was used to determine the hyperparameters, such as learning rate, decay, batch size, and dropout size.The model achieved the values of mean square error values within the range of 0.014 to 0.056 and R2 ranging from 0.96 to 0.98. A Convolutional Neural Network (CNN) model was added to the LSTM to investigate potential performance improvement. Performance dropped in all datasets due to the complexity of the model. The performance of the models was also compared with CNN, traditional machine learning algorithms Support Vector Regression, and Random Forest. LSTM achieved the best performance. Finally, the impact of the loss function on the performance of the proposed models was investigated. The model with the mean square error as loss function performed better than the model with other loss functions.
Keywords: Agriculture; Deep learning; Irrigation management; LSTM; Support decision-making algorithms

Soil water content estimation using high-frequency ground penetrating radar - Zhou, Ligang; Yu, Dongsheng; Wang, Zhaoyan; Wang, Xiangdong (Water (Switzerland), 2019)
The rapid high-precision and nondestructive determination of shallow soil water content (SWC) is of vital importance to precision agriculture and water resource management. However, the low-frequency ground penetrating radar (GPR) technology currently in use is insufficient for precisely determining the shallow SWC. Therefore, it is essential to develop and use a high-precision detection technology to determine SWC. In this paper, a laboratory study was conducted to evaluate the use of a high-frequency GPR antenna to determine the SWC of loamy sand, clay, and silty loam. We collected soil samples (0-20 cm) of six soil types of loamy sand, clay, and silty loam and used a high-frequency (2-GHz) GPR antenna to determine the SWC. In addition, we obtained GPR data and images as well as characteristic parameters of the electromagnetic spectrum and analyzed the quantitative relationship with SWC. The GPR reflection two-way travel times and the known depths of reflectors were used to calculate the average soil dielectric permittivities above the reflectors and establish a spatial relationship between the soil dielectric permittivity (ε) and SWC (θ), which was used to estimate the depth-averaged SWC. The results show that the SWC, which affects the attenuation of wave energy and the wave velocity of the GPR signal, is a dominant factor affecting the soil dielectric permittivity. In addition, the conductivity, magnetic soil, soil texture, soil organic matter, and soil temperature have substantial effects on the soil dielectric permittivity, which consequentially affects the prediction of SWC. The correlation coefficients R2 of the "θ ~ ε" cubic curve models, which were used to fit the relationships between the soil dielectric permittivity (ε) and SWC (θ), were greater than 0.89, and the root-mean-square errors were less than 2.9%, which demonstrate that high-frequency GPR technology can be applied to determine shallow SWC under variable hydrological conditions.
Keywords: GPR; Soil dielectric permittivity; Soil type; Soil water content; Velocity of electromagnetic wave

Nanopesticides: State of knowledge, environmental fate, and exposure modeling - Kah, M.; Beulke, S.; Tiede, K.; Hofmann, T. (Critical Reviews in Environmental Science and Technology, 2013)
Published literature has been reviewed in order to (a) explore the (potential) applications of nanotechnology in pesticide formulation, (b) identify possible impacts on environmental fate, and (c) analyze the suitability of current exposure assessment procedures to account for the novel properties of nanopesticides within the EU regulatory context. The term nanopesticide covers a wide variety of products and cannot be considered to represent a single category. Many nanoformulations combine several surfactants, polymers, and metal nanoparticles in the nanometer size range. The aims of nanoformulations are generally common to other pesticide formulations, these being to increase the apparent solubility of poorly soluble active ingredients, to release the active ingredient in a slow/targeted manner and/or to protect against premature degradation. Nanoformulations are thus expected to (a) have significant impacts on the fate of active ingredients and/or (b) introduce new ingredients for which the environmental fate is still poorly understood (e.g., nanosilver). Therefore, it seems that adaptations of current exposure assessment approaches will be necessary, at least for some nanopesticides. The present analysis provides a useful framework to identify priorities for future research in order to achieve more robust risk assessments of nanopesticides. © 2013 Taylor and Francis Group, LLC.
Keywords: agriculture; formulation; microemulsion; nanoparticle; nanotechnology; pesticide; plant protection product; regulation; silver

Manual on the development and use of FAO and WHO specifications for chemical pesticides - Food and Agriculture Organization of the United Nations (Manual on the development and use of FAO and WHO specifications for chemical pesticides, 2022)
In 2001, the Food and Agriculture Organization of the United Nations (FAO) and the World Health Organization (WHO) agreed to develop specifications for pesticides jointly, thus providing unique, robust and universally applicable standards for pesticide quality. This joint programme is based on a Memorandum of Understanding between the two Organizations. This 2021 second edition of the Manual on development and use of FAO and WHO specifications for pesticides, which is only available online, supersedes the March 2020 third revision of the first edition and previous manuals and guidance documents published by either FAO or WHO on this subject. This Manual provides the standard process, unified requirements and procedures, harmonized definitions and nomenclature, technical guidelines and standards applicable to pesticides for use in agriculture and public health. FAO and WHO specifications for pesticides based on this manual are developed through the FAO/ WHO Joint Meeting on Pesticide Specifications (JMPS) and published on the web sites of the two Organizations. FAO/WHO specifications apply only to the products of manufacturers whose technical materials have been evaluated. The specifications may be used to provide an international point of reference against which the quality of products can be judged, either for regulatory purposes or in commercial dealings, thereby helping to prevent the trade, sale and use of inferior quality pesticide products. Thus, the specifications will enhance confidence in the purchase and use of pesticides, and at the same time contribute towards better pest control, sound agricultural production, effective vector control measures and improved user, public and environmental safety throughout the world, especially in developing countries. www.fao.org/pest-and-pesticide-management/guidelines-standards/faowho-joint-meeting-on-pesticide-management-jmpm/en and https://extranet.who.

Recent developments of safer formulations of agrochemicals - Knowles, Alan (Environmentalist, 2008)
The primary objectives of formulation technology are to optimise the biological activity of the pesticide, and to give a product which is safe and convenient for use. However, because of the wide variety of pesticide active ingredients which are available, many different types of formulations have been developed depending mainly on the physico-chemical properties of the active ingredients. In the past most formulations were based on simple solutions in water (SL), emulsifiable concentrates in a petroleum-based solvent (EC), or dusts (DP) and wettable powders (WP). The presence of petroleum-based solvents in EC formulations and dusty powders in DP and WP formulations can lead to safety hazards in use and a negative impact on the envirnoment generally. Most government and regulatory authorities are now demanding formulations which are cleaner and safer for the user, have minimal impact on the environment, and can be applied at the lowest dose rate. Developments in formulation technology and novel formulation types, sometimes in special packaging such as water-soluble packs, can also give products a competitive advantage, add value or extend the lif-cycle of active ingredients. There is also a demand from government authorities and consumer groups to use safer formulation additives and adjuvants, and to minimise the residues of pesticides on food crops after spraying. All of these aspects are putting increasing pressure on the development of improved formulation and adjuvant technologies. Pesticide formulations for spray application and for seed treatment are discussed, along with developments in bioenchancement. © 2007 Springer Science+Business Media, LLC.
Keywords: Adjuvants; Bioenhancement; Conventional formulations; Formulation trends; Pesticide formulations; Safer formulations; Seed treatment formulations; Surfactants

Adsorption-desorption, persistence, and leaching behavior of dithiopyr in an alluvial soil of India - Gupta, Suman; Gajbhiye, V. T. (Journal of Environmental Science and Health - Part B Pesticides, Food Contaminants, and Agricultural Wastes, 2002)
Investigations were undertaken to determine the adsorption-desorption, persistence and leaching of dithiopyr (S, S′-dimethyl 2-difluoromethyl-4-isobutyl-6-trifluoromethyl pyridine-3,5-dicarbothioate) in an alluvial soil under laboratory condition. The adsorption-desorption studies were carried out using batch equilibration technique. The mass balance studies showed that 83-97% of the pesticide was recovered during adsorption-desorption studies. The results revealed strong adsorption of dithiopyr in alluvial soil with Kd values ranging from 3.97-5.78 and Freundlich capacity factor (KF) value of 2.41. The strong adsorption was evident from the hysteresis effect observed during desorption. The hysteresis coefficients ranged from 0.17-0.40. The persistence studies were carried out at two concentrations (1.0 and 10.0 μg g-1 level) under field capacity moisture and submerged condition by incubating the treated soil at 25±1°C. In general, dithiopyr persisted beyond 90 days with half-life varying from 11.5-12.9 days under different conditions. The rate of application and moisture regimes had no overall effect on the persistence. The leaching studies carried out in packed column under saturated flow condition revealed that dithiopyr was highly immobile in alluvial soil. Only small amounts (0.02-0.04%) were recovered from leachate whereas major portion (99.9%) remained in top layer of the soil column. The data suggest that strong adsorption of dithiopyr will cause a greater persistence problem in the soil. However, the chances of its movement to ground water will be negligible due to its immobility.
Keywords: Dissipation; Dithiopyr; Herbicide; Leaching; Soil; Sorption

Hazard identification of imidacloprid to aquatic environment - Tišler, Tatjana; Jemec, Anita; Mozetič, Branka; Trebše, Polonca (Chemosphere, 2009)
The use of a very effective insecticide against sucking pests, neonicotinoid imidacloprid, has been increasing extensively. For this reason elevated concentrations are expected in aquatic environment. Despite this fact, there is still a lack of data available on its possible risk for the environment. In this study, the potential hazards of imidacloprid and its commercial product Confidor SL 200 to aquatic environment were identified by the acute and chronic toxicity assessment using bacteria Vibrio fischeri, algae Desmodesmus subspicatus, crustacean Daphnia magna, fish Danio rerio and the ready biodegradability determination. We found out, that imidacloprid was not highly toxic to tested organisms in comparison to some other environmental pollutants tested in the same experimental set-up. Among the organisms tested, water flea D. magna proved to be the most sensitive species after a short-term (48 h EC50 = 56.6 mg L-1) and long-term exposure (21 d NOEC = 1.25 mg L-1). On the contrary, the intensified toxicity of Confidor SL 200 in comparison to analytical grade imidacloprid was observed in the case of algae and slight increase of its toxicity was detected testing daphnids and fish. The activities of cholinesterase, catalase and glutathione S-transferase of daphnids were not early biomarkers of exposure to imidacloprid and its commercial product. Imidacloprid was found persistent in water samples and not readily biodegradable in aquatic environment. Due to increased future predicted use of commercial products containing imidacloprid and the findings of this work, we recommend additional toxicity and biodegradability studies of other commercial products with imidacloprid as an active constituent. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Aquatic organisms; Biodegradation; Confidor SL 200; Imidacloprid; Toxicity

Persistence, sorption, and forced degradation of imidacloprid in environmental matrix - Kumar, Jitesh; Kaur, Paramjeet; Sud, Dhiraj; Saini, Anju; Bansal, Priti (Materials Today: Proceedings, 2023)
The enhanced utilization of insecticides over various crops has led the toxicity in the environmental matrix. In this study, the behavior of Imidacloprid is observed in soil and water. The adsorption–desorption characteristics of Imidacloprid are observed on three different soils (Bathinda, Moga, and Sangrur) of the Malwa Region. The soil of Bathinda has shown maximum adsorption followed by Sangrur and then by Moga soil. The reverse order is observed in the desorption process under optimum conditions of pH 6 and temperature 33 °C. The adsorption behavior is observed to be related to the mineral content of the soils. The various adsorption and kinetic models reveal the suitability of chemical adsorption. The persistence study indicates the presence of insecticide in water for more than 100 days. In the forced degradation studies, ZnO photocatalyst has shown higher degradation of Imidacloprid nearly 91 % after 5 h under UV light, whereas with TiO2, degradation has reached up to 85 % during the same period.
Keywords: Adsorption; Degradation; Desorption; Insecticide; Persistence

Insights into the Toxicity and Degradation Mechanisms of Imidacloprid Via Physicochemical and Microbial Approaches - Pang, Shimei; Lin, Ziqiu; Zhang, Yuming; Zhang, Wenping; Alansary, Nasser; Mishra, Sandhya; Bhatt, Pankaj; Chen, Shaohua (Toxics, 2020)
Imidacloprid is a neonicotinoid insecticide that has been widely used to control insect pests in agricultural fields for decades. It shows insecticidal activity mainly by blocking the normal conduction of the central nervous system in insects. However, in recent years, imidacloprid has been reported to be an emerging contaminant in all parts of the world, and has different toxic effects on a variety of non-target organisms, including human beings, due to its large-scale use. Hence, the removal of imidacloprid from the ecosystem has received widespread attention. Different remediation approaches have been studied to eliminate imidacloprid residues from the environment, such as oxidation, hydrolysis, adsorption, ultrasound, illumination, and biodegradation. In nature, microbial degradation is one of the most important processes controlling the fate of and transformation from imidacloprid use, and from an environmental point of view, it is the most promising means, as it is the most effective, least hazardous, and most environmentally friendly. To date, several imidacloprid-degrading microbes, including Bacillus, Pseudoxanthomonas, Mycobacterium, Rhizobium, Rhodococcus, and Stenotrophomonas, have been characterized for biodegradation. In addition, previous studies have found that many insects and microorganisms have developed resistance genes to and degradation enzymes of imidacloprid. Furthermore, the metabolites and degradation pathways of imidacloprid have been reported. However, reviews of the toxicity and degradation mechanisms of imidacloprid are rare. In this review, the toxicity and degradation mechanisms of imidacloprid are summarized in order to provide a theoretical and practical basis for the remediation of imidacloprid-contaminated environments.
Keywords: degradationmechanisms; imidacloprid; microbialdegradation; physicochemicaldegradation; toxicity

The Degradation Process of Typical Neonicotinoid Insecticides in Tidal Streams in Subtropical Cities: A Case Study of the Wuchong Stream, South China - Jia, Qunpo; Cai, Yanpeng; Yuan, Xiao; Li, Bowen; Li, Bo (Toxics, 2023)
Neonicotinoid insecticides (NEOs) are commonly used to prevent unwanted insects in urban fields. Degradation processes have been one of the important environmental behaviors of NEOs in an aquatic environment. In this research, hydrolysis, biodegradation, and photolysis processes of four typical NEOs (i.e., thiacloprid (THA), clothianidin (CLO), acetamiprid (ACE), and imidacloprid (IMI)) were examined through the adoption of response surface methodology–central composite design (RSM-CCD) for an urban tidal stream in South China. The influences of multiple environmental parameters and concentration levels on the three degradation processes of these NEOs were then evaluated. The results indicated that the three degradation processes of the typical NEOs followed a pseudo-first-order reaction kinetics model. The primary degradation process of the NEOs were hydrolysis and photolysis processes in the urban stream. The hydrolysis degradation rate of THA was the highest (1.97 × 10−5 s−1), and that of CLO was the lowest (1.28 × 10−5 s−1). The temperature of water samples was the main environmental factor influencing the degradation processes of these NEOs in the urban tidal stream. Salinity and humic acids could inhibit the degradation processes of the NEOs. Under the influence of extreme climate events, the biodegradation processes of these typical NEOs could be suppressed, and other degradation processes could be further accelerated. In addition, extreme climate events could pose severe challenges to the migration and degradation process simulation of NEOs.
Keywords: central composite design (CCD); degradation kinetics; mathematical modeling; neonicotinoid insecticides (NEOs); urban tidal stream

Dynamic study of [Emim]Ac ionic liquid droplet impact on mildly heated solid surfaces - Zhang, Fangfang; Li, Xiangyu; Li, Huajie; Tang, Jingdan; Chen, Gang; Zhang, Leigang; Li, Guopei (International Communications in Heat and Mass Transfer, 2022)
The impingement dynamics of the 1-ethyl-3-methylimidazolium acetate ([Emim]Ac) ionic liquid (IL) droplets on mildly heated solid wall were investigated. Comparison of the impingement dynamics of water, 60 wt% IL aqueous solution, and pure IL droplets were made, and the spreading characteristics of the 60 wt% IL aqueous solution droplets under different impact velocities and surface temperatures were discussed. A constant contact radius with a sharp decrease subsequently and a linearly decreasing residual volume were observed for water droplet. By contrast, a gradually increased spreading factor was observed for the pure IL and 60 wt% IL aqueous solution droplets, and the residual volume stays the same and goes through a polynomially decreasing for the pure IL and 60 wt% IL aqueous solution droplets, respectively.
Keywords: Droplet; Heated surfaces; Impingement dynamics; Ionic liquid

Parameters affecting the photodegradation rate of imidacloprid catalyzed by ZnO nanoparticles - Atwan, Asmaa A; Elmehasseb, Ibrahim M; Talha, N I; El-Kemary, Maged (J. Mater. Environ. Sci, 2019)

Exploring the role of biopolymers and surfactants on the electrical conductivity of water-based CuO, Fe3O4, and hybrid nanofluids - Mane, Nikhil S.; Hemadri, Vadiraj; Tripathi, Siddhartha (Journal of Dispersion Science and Technology, 2024)
The research on the application of nanofluids in the thermal management of electric components is gaining widespread attention. In this context, and as past studies on nanofluids mainly focus on thermal properties, the investigation of the electrical properties of nanofluids has become important. The role of dispersants on the electrical conductivity of nanofluids stabilized using two biopolymer dispersants, chitosan, and gum arabica (GA), and a synthetic dispersant Sodium Dodecyl Benzoic Sulfate (SDBS) is investigated in this work. The nanofluids are prepared with water, nanoparticles (0.1 wt%), and dispersants (0.05 and 0.5 wt%), and the electrical conductivity is measured to examine the role of nanoparticle materials (CuO, Fe3O4, and CuO + Fe3O4), dispersants, and temperatures (25–40 °C). According to observations, the dispersants significantly affect the electrical conductivity, while nanoparticle material has a minimal impact. At 0.5 wt% concentration, SDBS stabilized nanofluids have electrical conductivity 708.7 times higher than water, whereas, with chitosan and GA, it is 144.2 and 12.8 times higher than water, respectively. CuO-water nanofluids show relatively higher electrical conductivity than Fe3O4 and hybrid CuO + Fe3O4 water nanofluids. Measured electrical conductivity is used for regression analysis using response surface methodology (RSM). Three quadratic nonlinear polynomial equations are developed to predict the electrical conductivity based on the input parameters (dispersant concentration and temperature). The predicted and measured values were in excellent agreement with each other. The current study offers a novel perspective on the electrical behavior of nanofluids with biopolymer dispersants and provides a prediction model for nanofluid electrical conductivity.
Keywords: Nanofluids; RSM; biopolymers; electrical conductivity; regression

IMPACTS OF CO-FORMULANTS ON PESTICIDE SORPTION AND LEACHING THROUGH SOIL - Ali Khan, Majid (2016)
2 ABSTRACT A large variety of co-formulants are added to commercial pesticide formulations to enhance

Pesticide and Adjuvant Mixture Impacts on the Physical–Chemical Properties, Droplet Spectrum, and Absorption of Spray Applied in Soybean Crop - Tavares, Rafael Marcão; Cunha, João Paulo Arantes Rodrigues da (AgriEngineering, 2023)
Tank mixing of pesticides, a common practice in many countries, when performed incorrectly, can negatively impact the effectiveness of the pesticides. This study aimed to investigate the physical–chemical properties, droplet spectrum, and absorption by soybean plants of mixtures of the azoxystrobin fungicide with glyphosate herbicide and different adjuvants (mineral oil, propionic acid, and orange oil). The study design was completely randomized, with five treatments (T): T1, only fungicide; T2, fungicide + glyphosate; T3, fungicide + mineral oil; T4, fungicide + propionic acid; and T5, fungicide + orange oil. The spray concentrations simulated an application rate of 160 L ha−1 using the TT110015 nozzle. The physical stability, hydrogen ion potential, electrical conductivity, surface tension, droplet spectrum, and azoxystrobin absorption in soybean plants were evaluated. To measure absorption, soybean plants were sprayed at the reproductive growth stage, and leaf samples were collected after 0, 2, and 48 h. The amount of azoxystrobin absorbed was determined using gas chromatography. The results indicated that the spray mixtures were physically compatible. All mixtures produced a medium droplet spectrum. T2 had the lowest absorption percentages, suggesting that these pesticides should not be mixed. Adjuvants increased the amount of azoxystrobin absorbed by the plants, and it took 2 h on average for the soybean leaves to absorb 72.58% of the applied spray.
Keywords: Glycine max; pesticide application technology; plant absorption; tank mixture

Influence of Thermal Aging on Dielectric Properties of High Voltage Cable Insulation Layer - Liang, Boyuan; Lan, Rui; Zang, Qian; Liu, Zhen; Tian, Lin; Wang, Zhaochen; Li, Guochang (Coatings, 2023)
Thermal aging is one of the main reasons for the degradation of insulation properties of high voltage cable. Dielectric properties and breakdown strength are important parameters to reflect the insulation performance of the cable insulation materials. In the work, the influence of thermal aging on dielectric and breakdown performance of the cable insulation layer was studied. Firstly, XLPE cable insulation samples were prepared and the thermal aging treatment was carried out. Secondly, the microstructure and molecular structure of XLPE samples under different thermal aging time were analyzed. The dielectric properties and breakdown characteristics of XLPE samples under different thermal aging times were characterized in macro aspect. Finally, the effects of different temperatures on the molecular microstructure of XLPE were studied. The results show that with the extension of thermal aging time, the microstructure of XLPE molecule is destroyed, the macromolecular chain is gradually cleaved, and the carbonyl absorption intensity increases. At power frequency, the breakdown strength decreases from 75.37 kV/mm to 62.18 kV/mm, the relative permittivity increases from 2.44 to 2.51, and the dielectric loss increases from 1.47 × 10−4 to 3.10 × 10−3. The free volume rate of XLPE molecules increases with the increasing temperature, and the mean square displacement gradually increases. The work has good guiding significance for the safe operation and condition assessment of high-voltage cables.
Keywords: electrical properties; high voltage cable; insulating layer; molecular motion; thermal aging

Dielectric Properties of Aqueous Electrolyte Solutions Confined in Silica Nanopore: Molecular Simulation vs. Continuum‐Based Models - Zhu, Haochen; Hu, Bo (Membranes, 2022)
Dielectric behavior of electrolyte aqueous solutions with various concentrations in a cylindrical nanopore of MCM 41 silica has been investigated. The effect of confinement is investigated by using isothermal‐isosurface‐isobaric statistical ensemble, which has proved to be an effective alternative to the Grand Canonical Monte Carlo (GCMC) simulation method. Several single‐salt solutions have been considered (e.g., NaCl, NaI, BaCl2, MgCl2) in order to investigate the effect of ion polarizability, ion size, and ion charge. The effect of salt concentration has also been addressed by considering NaCl solutions at different concentrations (i.e., 0.1 mol/L, 0.5 mol/L, and 1 mol/L). The motivation in performing this integrated set of simulations is to provide deep insight into the dielectric exclusion in NF theory that plays a significant role in separation processes. It was shown that the dielectric constant increased when ions were added to water inside the nanopore (with respect to the dielectric constant of confined pure water) unlike what was obtained in the bulk phase and this phenomenon was even more pronounced for electrolytes with divalent ions (MgCl2 and BaCl2). Therefore, our simulations indicate opposite effects of ions on the dielectric constant of free (bulk) and nanoconfined aqueous solutions.
Keywords: Dielectric constant; Electrolyte aqueous solutions; Molecular dynamics simulation; Nanofiltration theory; Silica nanopore

Frequency-dependent dielectric spectroscopic analysis on phytochemical and antioxidant activities in Radix Glycyrrhizae extract - Hong Liang, Ong; Ee Meng, Cheng; Mohamad, Che Wan Sharifah Robiah; Mohd Nasir, Nashrul Fazli; Xiao Jian, Tan; Chong You, Beh; Ziezie Mohd Tarmizi, Emma; Kim Yee, Lee; Kok Yeow, You; Shing Fhan, Khor; Kim Fey, Leu; Kian Keong, Te; et al. (Heliyon, 2024)
Radix Glycyrrhizae, the dried roots of the Glycyrrhiza glabra plant, is a popular Chinese herbal medicine known for its various health benefits. It is particularly effective in relieving respiratory problems like coughs, sore throats, bronchitis, and asthma. However, there is limited research on the electrical properties of Radix Glycyrrhizae, likely due to its complex composition of phytochemical and antioxidant activities. This research aims to investigate the potential of these active biological compounds and understand their electrochemical properties. In this study, High-Performance Liquid Chromatography (HPLC) analysis revealed that Radix Glycyrrhizae decoction contains significant amounts of flavonoids and saponins, compounds known for their health benefits and therapeutic effects. Further analysis using Fourier Transform Infrared Spectroscopy (FTIR) identified several functional groups, including phenols, alcohols, alkynes, alkenes, ethers, and glycosides, which contribute to the plant's medicinal potential and affect the impedance and dielectric properties of the extract. The antioxidant activity of Radix Glycyrrhizae decoction was also evaluated using DPPH assays, showing similar radical scavenging activity to gallic acid. Dielectric and impedance measurement of Radix Glycyrrhizae extract were performed using an Agilent vector network analyzer and a Hioki impedance analyzer. The dielectric constant measured was consistent across both analyzers. However, the loss factor showed different trends: the vector network analyzer indicated a decrease in the loss factor with increasing frequency in the range of 5 MHz–20 GHz, while the impedance analyzer showed the opposite trend in the frequency range of 4 Hz–5 MHz.
Keywords: Antioxidant; Dielectric; Phytochemical; Radix Glycyrrhizae

Environmental fate and exposure; neonicotinoids and fipronil - Bonmatin, J. M.; Giorio, C.; Girolami, V.; Goulson, D.; Kreutzweiser, D. P.; Krupke, C.; Liess, M.; Long, E.; Marzaro, M.; Mitchell, E. A.; Noome, D. A.; Simon-Delso, N.; et al. (Environmental Science and Pollution Research, 2015)
Systemic insecticides are applied to plants using a wide variety of methods, ranging from foliar sprays to seed treatments and soil drenches. Neonicotinoids and fipronil are among the most widely used pesticides in the world. Their popularity is largely due to their high toxicity to invertebrates, the ease and flexibility with which they can be applied, their long persistence, and their systemic nature, which ensures that they spread to all parts of the target crop. However, these properties also increase the probability of environmental contamination and exposure of nontarget organisms. Environmental contamination occurs via a number of routes including dust generated during drilling of dressed seeds, contamination and accumulation in arable soils and soil water, runoff into waterways, and uptake of pesticides by nontarget plants via their roots or dust deposition on leaves. Persistence in soils, waterways, and nontarget plants is variable but can be prolonged; for example, the half-lives of neonicotinoids in soils can exceed 1,000 days, so they can accumulate when used repeatedly. Similarly, they can persist in woody plants for periods exceeding 1 year. Breakdown results in toxic metabolites, though concentrations of these in the environment are rarely measured. Overall, there is strong evidence that soils, waterways, and plants in agricultural environments and neighboring areas are contaminated with variable levels of neonicotinoids or fipronil mixtures and their metabolites (soil, parts per billion (ppb)-parts per million (ppm) range; water, parts per trillion (ppt)-ppb range; and plants, ppb-ppm range). This provides multiple routes for chronic (and acute in some cases) exposure of nontarget animals. For example, pollinators are exposed through direct contact with dust during drilling; consumption of pollen, nectar, or guttation drops from seed-treated crops, water, and consumption of contaminated pollen and nectar from wild flowers and trees growing near-treated crops. Studies of food stores in honeybee colonies from across the globe demonstrate that colonies are routinely and chronically exposed to neonicotinoids, fipronil, and their metabolites (generally in the 1–100 ppb range), mixed with other pesticides some of which are known to act synergistically with neonicotinoids. Other nontarget organisms, particularly those inhabiting soils, aquatic habitats, or herbivorous insects feeding on noncrop plants in farmland, will also inevitably receive exposure, although data are generally lacking for these groups. We summarize the current state of knowledge regarding the environmental fate of these compounds by outlining what is known about the chemical properties of these compounds, and placing these properties in the context of modern agricultural practices.
Keywords: Bee; Dust; Fipronil; Guttation; Invertebrates; Neonicotinoid; Nontarget; Plant; Pollen; Soil; Vertebrates; Water

Interactions of dissolved organic matter with natural and engineered inorganic colloids: A review - Philippe, Allan; Schaumann, Gabriele E. (Environmental Science and Technology, 2014)
This contribution critically reviews the state of knowledge on interactions of natural colloids and engineered nanoparticles with natural dissolved organic materials (DOM). These interactions determine the behavior and impact of colloids in natural system. Humic substances, polysaccharides, and proteins present in natural waters adsorb onto the surface of most colloids. We outline major adsorption mechanisms and structures of adsorption layers reported in the literature and discuss their generality on the basis of particle type, DOM type, and media composition. Advanced characterization methods of both DOM and colloids are needed to address insufficiently understood aspects as DOM fractionation upon adsorption, adsorption reversibility, and effect of capping agent. Precise knowledge on adsorption layer helps in predicting the colloidal stability of the sorbent. While humic substances tend to decrease aggregation and deposition through electrostatic and steric effects, bridging-flocculation can occur in the presence of multivalent cations. In the presence of DOM, aggregation may become reversible and aggregate structure dynamic. Nonetheless, the role of shear forces is still poorly understood. If traditional approaches based on the DLVO-theory can be useful in specific cases, quantitative aggregation models taking into account DOM dynamics, bridging, and disaggregation are needed for a comprehensive modeling of colloids stability in natural media. © 2014 American Chemical Society.

Imidacloprid and Groundwater Imidacloprid - Minnesota Department of Health (2020)

IMIDACLOPRID FOR SALMONIDS ENVIRONMENTAL ASSESSMENT IN SUPPORT OF AN IMPORT TOLERANCE REQUEST Final: Original signed and on file - Mchenery Bsc, John G
Keywords: Environmental Assessment; Imidacloprid; Salmonids

Recent Advances in Photocatalytic Degradation of Imidacloprid in Aqueous Solutions Using Solid Catalysts - Gao, Song; Li, Shanshan; Sun, Shaofan; Chen, Maolong (Catalysts, 2024)
Imidacloprid (IMI), a widely used neonicotinoid pesticide, has led to significant water contamination due to excessive use. As a result, there is an urgent need for effective and straightforward methods to remove IMI residues from water. Photocatalytic technology, an integral part of advanced oxidation processes, is particularly promising due to its renewability, high catalytic efficiency, fast degradation ratio, and cost-effectiveness. This review systematically examines recent progress in the photocatalytic degradation of imidacloprid in aqueous solutions using various solid catalysts. It provides a comparative analysis of key factors affecting catalytic performance, such as catalyst synthesis methods, reaction times, catalyst loading, and IMI concentrations. Among the solid catalysts studied, nano-ZnO achieved a higher degradation rate of IMI in a shorter period and with a reduced catalyst dosage, reaching approximately 95% degradation efficiency within one hour. Additionally, this review explores the types of heterojunctions formed by the catalysts and elucidates the mechanisms involved in the photocatalytic degradation of IMI. In conclusion, this review offers a comprehensive evaluation of solid catalysts for the photocatalytic removal of IMI from water, serving as an important reference for developing innovative catalysts aimed at eliminating organic pollutants from aquatic environments.
Keywords: imidacloprid; mechanism; photocatalytic degradation; solid catalysts

Photocatalytic degradation of imidacloprid using Ag2O/CuO composites - Tariq, Saadia Rashid; Niaz, Zunaira; Chotana, Ghayoor Abbass; Ahmad, Dildar; Rafique, Nazia (RSC Advances, 2023)
Imidacloprid is one of the most commonly used neonicotinoid pesticides that has been identified as a neurotoxin for various non-target organisms. It binds to the central nervous system of organisms, causing paralysis and eventually death. Thus, it is imperative to treat waterwaters contaminated with imidacloprid using an efficient and cost effective method. The present study presents Ag2O/CuO composites as excellent catalysts for the photocatalytic degradation of imidacloprid. The Ag2O/CuO composites were prepared in different compositions by adopting the co-precipitation method and used as a catalyst for the degradation of imidacloprid. The degradation process was monitored using UV-vis spectroscopy. The composition, structure, and morphologies of the composites were determined by FT-IR, XRD, TGA, and SEM analyses. The effect of different parameters i.e time, concentration of pesticide, concentration of catalyst, pH, and temperature on the degradation was studied under UV irradiation and dark conditions. The results of the study evidenced the 92.3% degradation of imidacloprid in only 180 minutes, which was 19.25 hours under natural conditions. The degradation followed first-order kinetics, with the half life of the pesticide being 3.7 hours. Thus, the Ag2O/CuO composite was an excellent cost-effective catalyst. The non-toxic nature of the material adds further benefits to its use. The stability of the catalyst and its reusability for consecutive cycles make it more cost effective. The use of this material may help to ensure an immidacloprid free environment with minimal use of resources. Moreover, the potential of this material to degrade other environmental pollutants may also be explored.

Understanding the Dielectric Properties of Water - Elton, Daniel C (2016)
The user has requested enhancement of the downloaded file.

Photocatalytic degradation of imidacloprid pesticide in aqueous solution by TiO2 nanoparticles immobilized on the glass plate - Akbari Shorgoli, Amir; Shokri, Mohammad (Chemical Engineering Communications, 2017)
The purpose of this study is to appraise the photocatalytic degradation of imidacloprid pesticide in an aqueous solution. To this end, imidacloprid was degraded using TiO2 nanoparticles immobilized on a glass plate under UV light illumination. The effects of operational parameters (initial concentration of imidacloprid, pH, and light intensity) on the activity of TiO2 nanophotocatalyst and the kinetics of the reaction were investigated. The results indicated that TiO2 had impressive photocatalytic proficiency in the presence of UV-C light irradiation for the removal of imidacloprid from the aqueous solution. The highest efficiency for the removal of imidacloprid (R% = 90.24) was obtained in the initial concentration of 20 mg L−1 imidacloprid, pH = 5, and light intensity of 17 W m−2 after 180 min. The results of the mineralization studies represented a subtractive trend of total organic carbon (TOC) and an increase in the mineralization products during the reaction time.
Keywords: Advanced oxidation processes; TiO2 nanoparticles; imidacloprid; photocatalytic degradation

Dielectric Constant of Water from 0 0 to 100 0 C - Malmberg, C G; Maryott, A A (Journal of Research of the National Bureau of Standards, 1956)
An equal ratio arm, capacitance-conductance bridge, operated at frequencies below 100 kilocycles per second, was med to measure the dielectric constant of water with an accuracy of better than 0.1 percent at 5-degree intervals over the range .0° to 100° C. At 25° C the dielectric constant was found to have the value 78.30, which is about 0.3 percent lower than t hat usually accepted. The data fit the equation E= 87. 740-0.400081+ 9.398(10-4) tL 1.410 (10-6)13, with a maximum deviation of 0.01 unit in dielectric constant. The experimental method and sources of error are considered in some detail.

Insect locomotion: Flies show you how to stay on course - Zimmer, Manuel (Current Biology, 2021)
Walking animals are faced with making a trade-off between maintaining a stable posture and gait and pursuing other goals such as keeping a straight path. A new study on exploratory walking in flies provides a sophisticated quantitative account of this behavioural problem, with some intriguing discoveries.

Sensorimotor delays constrain robust locomotion in a 3D kinematic model of fly walking - Karashchuk, Lili; Li, Jing Shuang; Chou, Grant M; Walling-Bell, Sarah; Brunton, Steven L; Tuthill, John C; Brunton, Bingni W (eLife, 2025)
Walking animals must maintain stability in the presence of external perturbations, despite significant temporal delays in neural signaling and muscle actuation. Here, we develop a 3D kinematic model with a layered control architecture to investigate how sensorimotor delays constrain the robustness of walking behavior in the fruit fly, Drosophila . Motivated by the anatomical architecture of insect locomotor control circuits, our model consists of three component layers: a neural network that generates realistic 3D joint kinematics for each leg, an optimal controller that executes the joint kinematics while accounting for delays, and an inter-leg coordinator. The model generates realistic simulated walking that resembles real fly walking kinematics and sustains walking even when subjected to unexpected perturbations, generalizing beyond its training data. However, we found that the model’s robustness to perturbations deteriorates when sensorimotor delay parameters exceed the physiological range. These results suggest that fly sensorimotor control circuits operate close to the temporal limit at which they can detect and respond to external perturbations. More broadly, we show how a modular, layered model architecture can be used to investigate physiological constraints on animal behavior.

Insect Cell-Based Models: Cell Line Establishment and Application in Insecticide Screening and Toxicology Research - He, Xuan; Lu, Lidan; Huang, Ping; Yu, Bo; Peng, Lianxin; Zou, Liang; Ren, Yuanhang (Insects, 2023)
During the past decades, research on insect cell culture has grown tremendously. Thousands of lines have been established from different species of insect orders, originating from several tissue sources. These cell lines have often been employed in insect science research. In particular, they have played important roles in pest management, where they have been used as tools to evaluate the activity and explore the toxic mechanisms of insecticide candidate compounds. This review intends to first briefly summarize the progression of insect cell line establishment. Then, several recent studies based on insect cell lines coupled with advanced technologies are introduced. These investigations revealed that insect cell lines can be exploited as novel models with unique advantages such as increased efficiency and reduced cost compared with traditional insecticide research. Most notably, the insect cell line-based models provide a global and in-depth perspective to study the toxicology mechanisms of insecticides. However, challenges and limitations still exist, especially in the connection between in vitro activity and in vivo effectiveness. Despite all this, recent advances have suggested that insect cell line-based models promote the progress and sensible application of insecticides, which benefits pest management.
Keywords: cell lines; high-throughput screening; insect; insecticide; mode of action

Characterization in Potent Modulation on Voltage-Gated Na+ Current Exerted by Deltamethrin, a Pyrethroid Insecticide - Lin, Mao Hsun; Lin, Jen Feng; Yu, Meng Cheng; Wu, Sheng Nan; Wu, Chao Liang; Cho, Hsin Yen (International Journal of Molecular Sciences, 2022)
Deltamethrin (DLT) is a type-II pyrethroid ester insecticide used in agricultural and domestic applications as well as in public health. However, transmembrane ionic channels perturbed by this compound remain largely unclear, although the agent is thought to alter the gating characteristics of voltage-gated Na+ (NaV) channel current. In this study, we reappraised whether and how it and other related compounds can make any further modifications on voltage-gated Na+ current (INa) in pituitary tumor (GH3) cells. Cell exposure to DLT produced a differential and dose-dependent stimulation of peak (transient, INa(T)) or sustained (late, INa(L)) INa; consequently, the EC50 value required for DLT-stimulated INa(T) or INa(L) was determined to be 11.2 or 2.5 μM, respectively. However, neither the fast nor slow component in the inactivation time constant of INa(T) activated by short depolarizing pulse was changed with the DLT presence; conversely, tefluthrin (Tef), a type-I pyrethroid insecticide, can accentuate INa with a slowing in inactivation time course of the current. The INa(L) augmented by DLT was attenuated by further application of either dapagliflozin (Dapa) or amiloride, but not by chlorotoxin. During pulse train (PT) stimulation, with the Tef or DLT presence, the cumulative inhibition of INa(T) became slowed; moreover, following PT stimuli, a large tail current with a slowly recovering process was observed. Alternatively, during rapid depolarizing pulse, the amplitude of INa(L) and tail INa (INa(Tail)) for each depolarizing pulse became progressively increased by adding DLT, not by Tef. The recovery time constant following PT stimulation with continued presence of Tef or DLT was shortened by further addition of Dapa. The voltage-dependent hysteresis (Hys(V)) of persistent INa was differentially augmented by Tef or DLT. Taken together, the magnitude, gating, frequency dependence, as well as Hys(V) behavior of INa exerted by the presence of DLT or Tef might exert a synergistic impact on varying functional activities of excitable cells in culture or in vivo.
Keywords: late Na+ current; persistent Na+ current; pyrethroids; transient Na+ current; voltage-gated Na+ current

The Diversity Decline in Wild and Managed Honey Bee Populations Urges for an Integrated Conservation Approach - Panziera, Delphine; Requier, Fabrice; Chantawannakul, Panuwan; Pirk, Christian W.W.; Blacquière, Tjeerd (Frontiers in Ecology and Evolution, 2022)
Many parts of the globe experience severe losses and fragmentation of habitats, affecting the self-sustainability of pollinator populations. A number of bee species coexist as wild and managed populations. Using honey bees as an example, we argue that several management practices in beekeeping threaten genetic diversity in both wild and managed populations, and drive population decline. Large-scale movement of hive stocks, introductions into new areas, breeding programs and trading of queens contribute to reducing genetic diversity, as recent research demonstrated for wild and managed honey bees within a few decades. Examples of the effects of domestication in other organisms show losses of both genetic diversity and fitness functions. Cases of natural selection and feralization resulted in maintenance of a higher genetic diversity, including in a Varroa destructor surviving population of honey bees. To protect the genetic diversity of honey bee populations, exchange between regions should be avoided. The proposed solution to selectively breed all local subspecies for a use in beekeeping would reduce the genetic diversity of each, and not address the value of the genetic diversity present in hybridized populations. The protection of Apis mellifera’s, Apis cerana’s and Apis koschevnikovi’s genetic diversities could be based on natural selection. In beekeeping, it implies to not selectively breed but to leave the choice of the next generation of queens to the colonies, as in nature. Wild populations surrounded by beekeeping activity could be preserved by allowing Darwinian beekeeping in a buffer zone between the wild and regular beekeeping area.
Keywords: biodiversity; genetic variation; honey bees; natural selection; selective breeding

Predictive systems models can help elucidate bee declines driven by multiple combined stressors - Henry, Mickaël; Becher, Matthias A.; Osborne, Juliet L.; Kennedy, Peter J.; Aupinel, Pierrick; Bretagnolle, Vincent; Brun, François; Grimm, Volker; Horn, Juliane; Requier, Fabrice (Apidologie, 2017)
Bee declines are driven by multiple combined stresses, making it exceedingly difficult to identify experimentally the most critical threats to bees and their pollination services. We highlight here the too often ignored potential of mechanistic models in identifying critical stress combinations. Advanced bee models are now available as open access tools and offer an unprecedented opportunity for bee biologists to explore bee resilience tipping points in a variety of environmental contexts. We provide general guidelines on how to run bee models to help detect a priori critical stress combinations to be targeted in the field. This so-called funnel analysis should be performed in tight conjunction with the recent development of large-scale field monitoring programs for bee health surveillance.
Keywords: Apis mellifera; agent-based models; field monitoring program; honeybees; mechanistic modeling

Decline in Honeybees and Its Consequences for Beekeepers and Crop Pollination in Western Nepal - Kortsch, Susanne; Timberlake, Thomas P.; Cirtwill, Alyssa R.; Sapkota, Sujan; Rokoya, Manish; Devkota, Kedar; Roslin, Tomas; Memmott, Jane; Saville, Naomi (Insects, 2024)
In understudied regions of the world, beekeeper records can provide valuable insights into changes in pollinator population trends. We conducted a questionnaire survey of 116 beekeepers in a mountainous area of Western Nepal, where the native honeybee Apis cerana cerana is kept as a managed bee. We complemented the survey with field data on insect–crop visitation, a household income survey, and an interview with a local lead beekeeper. In total, 76% of beekeepers reported declines in honeybees, while 86% and 78% reported declines in honey yield and number of beehives, respectively. Honey yield per hive fell by 50% between 2012 and 2022, whilst the number of occupied hives decreased by 44%. Beekeepers ranked climate change and declining flower abundance as the most important drivers of the decline. This raises concern for the future food and economic security of this region, where honey sales contribute to 16% of total household income, and where Apis cerana cerana plays a major role in crop pollination, contributing more than 50% of all flower visits to apple, cucumber, and pumpkin. To mitigate further declines, we promote native habitat and wildflower preservation, and using well-insulated log hives to buffer bees against the increasingly extreme temperature fluctuations.
Keywords: Apis cerana cerana; beekeeping; climate change; crop production; insect decline; insect pollination; pollinator decline; smallholder farming

Imidacloprid alters foraging and decreases bee avoidance of predators - Tan, Ken; Chen, Weiwen; Dong, Shihao; Liu, Xiwen; Wang, Yuchong; Nieh, James C. (PLoS ONE, 2014)
Concern is growing over the effects of neonicotinoid pesticides, which can impair honey bee cognition. We provide the first demonstration that sublethal concentrations of imidacloprid can harm honey bee decision-making about danger by significantly increasing the probability of a bee visiting a dangerous food source. Apis cerana is a native bee that is an important pollinator of agricultural crops and native plants in Asia. When foraging on nectar containing 40 μg/L (34 ppb) imidacloprid, honey bees (Apis cerana) showed no aversion to a feeder with a hornet predator, and 1.8 fold more bees chose the dangerous feeder as compared to control bees. Control bees exhibited significant predator avoidance. We also give the first evidence that foraging by A. cerana workers can be inhibited by sublethal concentrations of the pesticide, imidacloprid, which is widely used in Asia. Compared to bees collecting uncontaminated nectar, 23% fewer foragers returned to collect the nectar with 40 μg/L imidacloprid. Bees that did return respectively collected 46% and 63% less nectar containing 20 μg/L and 40 μg/L imidacloprid. These results suggest that the effects of neonicotinoids on honey bee decision-making and other advanced cognitive functions should be explored. Moreover, research should extend beyond the classic model, the European honey bee (A. mellifera ), to other important bee species. © 2014 Tan et al.

Neonicotinoids interfere with specific components of navigation in honeybees - Fischer, Johannes; Müller, Teresa; Spatz, Anne Kathrin; Greggers, Uwe; Grünewald, Bernd; Menzel, Randolf (PLoS ONE, 2014)
Three neonicotinoids, imidacloprid, clothianidin and thiacloprid, agonists of the nicotinic acetylcholine receptor in the central brain of insects, were applied at non-lethal doses in order to test their effects on honeybee navigation. A catch-and-release experimental design was applied in which feeder trained bees were caught when arriving at the feeder, treated with one of the neonicotinoids, and released 1.5 hours later at a remote site. The flight paths of individual bees were tracked with harmonic radar. The initial flight phase controlled by the recently acquired navigation memory (vector memory) was less compromised than the second phase that leads the animal back to the hive (homing flight). The rate of successful return was significantly lower in treated bees, the probability of a correct turn at a salient landscape structure was reduced, and less directed flights during homing flights were performed. Since the homing phase in catch-and-release experiments documents the ability of a foraging honeybee to activate a remote memory acquired during its exploratory orientation flights, we conclude that non-lethal doses of the three neonicotinoids tested either block the retrieval of exploratory navigation memory or alter this form of navigation memory. These findings are discussed in the context of the application of neonicotinoids in plant protection. © 2014 Fischer et al.

Proboscis behavioral response of four honey bee Apis species towards different concentrations of sucrose, glucose, and fructose - Ali, Hussain; Iqbal, Javaid; Raweh, Hael S.; Alqarni, Abdulaziz S. (Saudi Journal of Biological Sciences, 2021)
Honey bees forage for pollen and nectar. Sugar is an important stimulus for foraging and a major source of energy for honey bees. Any differential response of bees to different concentrations of sugary nectar can affect their foraging. The sugar responsiveness of Apis species (Apis dorsata, Apis florea, and Apis cerana) was determined in comparison to that of Apis mellifera by evaluating the proboscis extension response (PER) with eight serial concentrations (0.00001, 0.0001, 0.001, 0.01, 0.1, 0.5, 1.0, and 1.5 M) of sucrose, glucose and fructose. Nectar foragers of bee species (A. dorsata, A. florea, A. cerana, and A. mellifera) exhibited an equal response for sucrose, glucose, and fructose, with no significant differences in their PER at all tested concentrations of these sugars within the same species. The inter-species comparison between Apis species revealed the differential responsiveness to the different concentrations of sugars, and the lowest concentration at which a response occurs was considered as the response threshold of these bee species for sugar solutions. A. mellifera presented significantly higher responsiveness than A. dorsata to low concentrations (0.00001, 0.0001, 0.001, 0.01, and 0.1 M) of sucrose, glucose and fructose. A. mellifera displayed a significantly higher response to water than A. dorsata. A. florea and A. mellifera presented no significant difference in their responsiveness to sucrose, glucose, and fructose at all tested concentrations, and their water responsiveness was also significantly at par but relatively higher in A. mellifera than in A. florea. Likewise, the responsiveness of A. cerana and A. mellifera to different concentrations of sucrose, glucose and fructose was significantly at par with no difference in their water responsiveness. This study represents preliminary research comparing the response of different honey bee species to three sugar types at different concentrations. The results imply that the native species are all better adapted than A. mellifera under local climate conditions.
Keywords: Antennal response; Apis cerana; Apis dorsata; Apis florea, Apis mellifera; Nectar sugars; Proboscis extension response

Sucrose sensitivity of honey bees is differently affected by dietary protein and a neonicotinoid pesticide - Démares, Fabien J.; Crous, Kendall L.; Pirk, Christian W.W.; Nicolson, Susan W.; Human, Hannelie (PLoS ONE, 2016)
Over a decade, declines in honey bee colonies have raised worldwide concerns. Several potentially contributing factors have been investigated, e.g. parasites, diseases, and pesticides. Neonicotinoid pesticides have received much attention due to their intensive use in crop protection, and their adverse effects on many levels of honey bee physiology led the European Union to ban these compounds. Due to their neuronal target, a receptor expressed throughout the insect nervous system, studies have focused mainly on neuroscience and behaviour. Through the Geometric Framework of nutrition, we investigated effects of the neonicotinoid thiamethoxam on survival, food consumption and sucrose sensitivity of honey bees (Apis mellifera). Thiamethoxam did not affect protein and carbohydrate intake, but decreased responses to high concentrations of sucrose. Interestingly, when bees ate fixed unbalanced diets, dietary protein facilitated better sucrose detection. Both thiamethoxam and dietary protein influenced survival. These findings suggest that, in the presence of a pesticide and unbalanced food, honey bee health may be severely challenged. Consequences for foraging efficiency and colony activity, cornerstones of honey bee health, are also discussed.

Aversive learning in honeybees revealed by the olfactory conditioning of the sting extension reflex - Vergoz, Vanina; Roussel, Edith; Sandoz, Jean Christophe; Giurfa, Martin (PLoS ONE, 2007)
Invertebrates have contributed greatly to our understanding of associative learning because they allow learning protocols to be combined with experimental access to the nervous system. The honeybee Apis mellifera constitutes a standard model for the study of appetitive learning and memory since it was shown, almost a century ago, that bees learn to associate different sensory cues with a reward of sugar solution. However, up to now, no study has explored aversive learning in bees in such a way that simultaneous access to its neural bases is granted. Using odorants paired with electric shocks, we conditioned the sting extension reflex, which is exhibited by harnessed bees when subjected to a noxious stimulation. We show that this response can be conditioned so that bees learn to extend their sting in response to the odorant previously punished. Bees also learn to extend the proboscis to one odorant paired with sugar solution and the sting to a different odorant paired with electric shock, thus showing that they can master both appetitive and aversive associations simultaneously. Responding to the appropriate odorant with the appropriate response is possible because two different biogenic amines, octopamine and dopamine subserve appetitive and aversive reinforcement, respectively. While octopamine has been previously shown to substitute for appetitive reinforcement, we demonstrate that blocking of dopaminergic, but not octopaminergic, receptors suppresses aversive learning. Therefore, aversive learning in honeybees can now be accessed both at the behavioral and neural levels, thus opening new research avenues for understanding basic mechanisms of learning and memory. © 2007 Vergos et al.

Rules and mechanisms of punishment learning in honey bees: The aversive conditioning of the sting extension response - Tedjakumala, Stevanus Rio; Giurfa, Martin (Journal of Experimental Biology, 2013)
Honeybees constitute established model organisms for the study of appetitive learning and memory. In recent years, the establishment of the technique of olfactory conditioning of the sting extension response (SER) has yielded new insights into the rules and mechanisms of aversive learning in insects. In olfactory SER conditioning, a harnessed bee learns to associate an olfactory stimulus as the conditioned stimulus with the noxious stimulation of an electric shock as the unconditioned stimulus. Here, we review the multiple aspects of honeybee aversive learning that have been uncovered using Pavlovian conditioning of the SER. From its behavioral principles and sensory variants to its cellular bases and implications for understanding social organization, we present the latest advancements in the study of punishment learning in bees and discuss its perspectives in order to define future research avenues and necessary improvements. The studies presented here underline the importance of studying honeybee learning not only from an appetitive but also from an aversive perspective, in order to uncover behavioral and cellular mechanisms of individual and social plasticity. © 2013. Published by The Company of Biologists Ltd.
Keywords: Aversive conditioning; Conditioning; Division of labor; Honeybee; Insect; Learning; Memory; SER; Stimulus responsiveness; Stimulus sensitivity; Sting extension response

Acetylcholine, GABA and glutamate induce ionic currents in cultured antennal lobe neurons of the honeybee, Apis mellifera. - Barbara, Guillaume Stephane; Zube, Christina; Rybak, Jürgen; Gauthier, Monique; Grünewald, Bernd (Journal of comparative physiology. A, Neuroethology, sensory, neural, and behavioral physiology, 2005)
The honeybee, Apis mellifera, is a valuable model system for the study of olfactory coding and its learning and memory capabilities. In order to understand the synaptic organisation of olfactory information processing, the transmitter receptors of the antennal lobe need to be characterized. Using whole-cell patch-clamp recordings, we analysed the ligand-gated ionic currents of antennal lobe neurons in primary cell culture. Pressure applications of acetylcholine (ACh), gamma-amino butyric acid (GABA) or glutamate induced rapidly activating ionic currents. The ACh-induced current flows through a cation-selective ionotropic receptor with a nicotinic profile. The ACh-induced current is partially blocked by alpha-bungarotoxin. Epibatidine and imidacloprid are partial agonists. Our data indicate the existence of an ionotropic GABA receptor which is permeable to chloride ions and sensitive to picrotoxin (PTX) and the insecticide fipronil. We also identified the existence of a chloride current activated by pressure applications of glutamate. The glutamate-induced current is sensitive to PTX. Thus, within the honeybee antennal lobe, an excitatory cholinergic transmitter system and two inhibitory networks that use GABA or glutamate as their neurotransmitter were identified.

The neonicotinoid imidacloprid, and the pyrethroid deltamethrin, are antagonists of the insect Rdl GABA receptor - Taylor-Wells, Jennina; Brooke, Basil D.; Bermudez, Isabel; Jones, Andrew K. (Journal of Neurochemistry, 2015)
A mutation in the second transmembrane domain of the GABA receptor subunit, Rdl, is associated with resistance to insecticides such as dieldrin and fipronil. Molecular cloning of Rdl cDNA from a strain of the malaria mosquito, Anopheles gambiae, which is highly resistant to dieldrin revealed this mutation (A296G) as well as another mutation in the third transmembrane domain (T345M). Wild-type, A296G, T345M and A296G + T345M homomultimeric Rdl were expressed in Xenopus laevis oocytes and their sensitivities to fipronil, deltamethrin, 1,1,1-trichloro-2,2-bis(p-chlorophenyl) ethane (DDT), imidacloprid and spinosad were measured using two-electrode voltage-clamp electrophysiology. Spinosad and DDT had no agonist or antagonist actions on Rdl. However, fipronil, deltamethrin and imidacloprid decreased GABA-evoked currents. These antagonistic actions were either reduced or abolished with the A296G and the A296G + T345M mutations while T345M alone appeared to have no significant effect. In conclusion, this study identifies another mutation in the mosquito Rdl that is associated with insecticide resistance. While T345M itself does not affect insecticide sensitivity, it may serve to offset the structural impact of A296G. The present study also highlights Rdl as a potential secondary target for neonicotinoids and pyrethroids.
Keywords: Anopheles gambiae; GABA receptor; deltamethrin; fipronil; imidacloprid; insecticide resistance

Understanding the Impact of Heat Stress on Honeybee Populations: Insights into Thermoregulation, Colony Dynamics, and Environmental Interactions - Kamboj, Parul; Kaur, Guramrit; Gupta, Garima (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Nowadays, heat stress is emerging as a significant issue for honeybees in apiculture due to its potential to negatively impact the honey bees' health, the bee colony, and the economic stability. This review aims to thoroughly analyze the impact of heat stress on honeybee populations by consolidating existing research to provide accurate information. The thermoregulation process in honeybees and associated behavioral and molecular adaptations in worker bees, specific to Apis mellifera. Additionally covers the various ways that individual bees respond to heat stress, including changes in their metabolic rate and feeding habits. Furthermore, the paper provides a comprehensive analysis of how heat stress affects the entire bee colony, including detrimental effects on brood development, decreased productivity, and heightened susceptibility to illnesses and parasites. Also, it investigates the correlation between heat stress and other stressors, such as pesticide exposure, nutritional stress, biotic pressures, habitat loss, and the combined effects on bee health. To safeguard these important pollinators from the negative effects of climate change, this review stresses the need of interdisciplinary research and the need of identifying health stress as a major component influencing honeybee populations.

Non-optimal ambient temperatures aggravate insecticide toxicity and affect honey bees Apis mellifera L. gene regulation - Alburaki, Mohamed; Madella, Shayne; Cook, Steven C. (Scientific Reports, 2023)
In this study, we conducted a transcriptional analysis of five honey bee genes to examine their functional involvement vis-à-vis ambient temperatures and exposure to imidacloprid. In a 15-day cage experiment, three cohorts of one-day-old sister bees emerged in incubators, were distributed into cages, and maintained at three different temperatures (26 °C, 32 °C, 38 °C). Each cohort was fed a protein patty and three concentrations of imidacloprid-tainted sugar (0 ppb, 5 ppb and 20 ppb) ad libitum. Honey bee mortality, syrup and patty consumption were monitored daily over 15 days. Bees were sampled every three days for a total of five time points. RT-qPCR was used to longitudinally assess gene regulation of Vg, mrjp1, Rsod, AChE-2 and Trx-1 using RNA extracted from whole bee bodies. Kaplan–Meier models show that bees kept at both non-optimal temperatures (26 °C and 38 °C) were more susceptible to imidacloprid, with significantly higher mortality (P < 0.001 and P < 0.01, respectively) compared to the control. At 32 °C, no differences in mortality (P = 0.3) were recorded among treatments. In both imidacloprid treatment groups and the control, the expression of Vg and mrjp1 was significantly downregulated at 26 °C and 38 °C compared to the optimal temperature of 32 °C, indicating major influence of ambient temperature on the regulation of these genes. Within the ambient temperature groups, both imidacloprid treatments exclusively downregulated Vg and mrjp1 at 26 °C. AChE-2 and the poorly characterized Rsod gene were both consistently upregulated at the highest temperature (38 °C) compared to the ideal temperature (32 °C) in all treatment groups. Trx-1 showed no effect to both temperature and imidacloprid treatments and was regulated in an age-related manner. Overall, our results indicate that ambient temperatures amplify imidacloprid toxicity and affect honey bee gene regulation.

Imidacloprid decreases energy production in the hemolymph and fat body of western honeybees even though, in sublethal doses, it increased the values of six of the nine compounds in the respiratory and citric cycle - Paleolog, Jerzy; Wilde, Jerzy; Gancarz, Marek; Strachecka, Aneta (PLOS ONE, 2025)
Background Neonicotinoids, including imidacloprid (IM), cause harm to Apis mellifera in a number of ways, among others by impairing body maintenance, resistance and immunity. Energy resources are important to preventing this, as we hypothesized, not only in the hemolymph but particularly in the fat body, the insufficiently investigated, as yet, equivalent of the mammalian liver and pancreas. Both suppression and hormesis (diaphasic stressor response) of energy supply was reported in the energy-dependent traits of bees exposed to sublethal doses of imidacloprid. Therefore, our goal was to answer which of these two phenomena occurs in the hemolymph/fat body and at what doses of imidacloprid. Methods Concentrations/activities of respiratory/citric cycle compounds (acetyl-CoA, IDH-2, AKG, succinate, fumarate, NADH2, COX, UQRC, and ATP) were compared in the hemolymph and fat bodies of nurse workerbees sampled from honeybee colonies fed with diets containing 200 ppb (IM-200), 5 ppb (IM-5; sublethal), and 0 ppb of IM in a field experiment. Results The assayed compounds had higher values in the fat body than in the hemolymph, whereas their variability was higher in the hemolymph. The pattern of response to IM was the same in both tissues, but markedly differed between IM-200 and IM-5. The concentrations of the strongly correlated NADH2, ATP and acetyl-CoA decreased both in IM-200 and IM-5, whereas the levels of the other compounds decreased in IM-200 but increased in IM-5. Conclusions and significance Decreased ATP and acetyl-CoA levels both in IM-5 and IM-200 show that the pesticide impairs the hemolymph and fat-body energy metabolism in spite of hormesis in six of the nine respiratory and citric cycle compounds even in low, residual doses. This finding better explains how residual doses of neonicotinoids may disturb the fat body functions, and therefore suppress the apian resistance, which expands our knowledge about honeybee colony losses.

Modeling pesticide residues in nectar and pollen in support of pesticide exposure assessment for honeybees: A generic modeling approach - Li, Zijian (Ecotoxicology and Environmental Safety, 2022)
Pesticide residues in nectar and pollen of plants can damage honeybees; however, few modeling approaches have simulated residue levels in nectar and pollen in support of exposure assessment for honeybees. This study introduced a generic modeling approach based on plant uptake models and simple partitioning rules that specifies soil incorporation and foliar spray application scenarios of pesticides and is flexible for conducting variability analysis for various environmental conditions, pesticide application patterns, chemical individuals, and plant varieties. The results indicated that, in general, systemic or moderate lipophilicity (log KOW of ~2.5) pesticides have relatively high simulated residue levels in nectar and pollen because of the enhanced residue uptake process from soil. For non-systemic or highly lipophilic pesticides, the residue uptake via leaf surface deposition pathway can be enhanced, and more residues will be bioaccumulated in pollen than nectar due to a relatively high lipid content of pollen (as compared to nectar), but the overall residue levels in nectar and pollen are lower than systemic or moderately lipophilic pesticides. The variability analysis showed that environmental conditions, pesticide application patterns, chemical properties, and plant varieties cause considerable variations in simulated residue levels in nectar and pollen, indicating that spatiotemporal, chemical, and plant-related factors must be considered in pesticide exposure assessment for honeybees. Moreover, the comparison between the simulated and measured data showed a high degree of consistency, indicating that the proposed model could be used to conduct a screening-level pesticide exposure assessment for honeybees.
Keywords: Bioaccumulation; Bioconcentration; Environmental fate model; Pesticide residues; Residue uptake model

Lethal, sublethal, and combined effects of pesticides on bees: A meta-analysis and new risk assessment tools - Tosi, Simone; Sfeir, Cynthia; Carnesecchi, Edoardo; vanEngelsdorp, Dennis; Chauzat, Marie Pierre (Science of the Total Environment, 2022)
Multiple stressors, threaten bee health, a major one being pesticides. Bees are simultaneously exposed to multiple pesticides that can cause both lethal and sublethal effects. Risk assessment and most research on bee health, however, focus on lethal individual effects. Here, we performed a systematic literature review and meta-analysis that summarizes and re-interprets the available qualitative and quantitative information on lethal, sublethal, and combined toxicity of a comprehensive range of pesticides on bees. We provide results (1970–2019) for multiple bee species (Bombus, Osmia, Megachile, Melipona, Partamona, Scaptotrigona), although most works focused on Apis mellifera L. (78 %). We provided harmonised results on the lethal toxicity of pesticides in bees (n = 377 pesticides) and documented the types of sublethal testing methods and related effects that cause a sublethal effect (n = 375 sublethal experiments). We identified the most common combinations of pesticides and mode of actions tested, and summarize the experimental methods, magnitude of the interactions, and robustness of available data (n = 361 experiments). We provide open access searchable, comprehensive, and integrated list of pesticides and their levels causing lethal, sublethal, and combined effects. We report major data gaps related to pesticide's sublethal (71 %) and combined (e.g., ~99 %) toxicity. We identified pesticides and mode of actions of greatest concern in terms of sublethal (chlorothalonil, pymetrozine, glyphosate; neonicotinoids) and combined (tau-fluvalinate combinations; acetylcholinesterase inhibitors and neonicotinoids) effects. Although certain pesticides have faced regulatory restrictions in specific countries (chlorothalonil, pymetrozine, neonicotinoids), most are still widely used worldwide (e.g., glyphosate). This work aims at facilitating the implementation of more comprehensive and harmonised research and risk assessments, considering sublethal and combined effects. To ensure safeguarding pollinators and the environment, we advocate for a more refined and holistic assessment that do not only focus on lethality but uses harmonised methods to test sublethal and relevant combinations.
Keywords: Apis; Behaviour; Insecticide; Interaction; Synergistic; Toxicity

Honeybee colony thermoregulation - Regulatory mechanisms and contribution of individuals in dependence on age, location and thermal stress - Stabentheiner, Anton; Kovac, Helmut; Brodschneider, Robert (PLoS ONE, 2010)
Honeybee larvae and pupae are extremely stenothermic, i.e. they strongly depend on accurate regulation of brood nest temperature for proper development (33-36uC). Here we study the mechanisms of social thermoregulation of honeybee colonies under changing environmental temperatures concerning the contribution of individuals to colony temperature homeostasis. Beside migration activity within the nest, the main active process is ''endothermy on demand'' of adults. An increase of cold stress (cooling of the colony) increases the intensity of heat production with thoracic flight muscles and the number of endothermic individuals, especially in the brood nest. As endothermy means hard work for bees, this eases much burden of nestmates which can stay ectothermic. Concerning the active reaction to cold stress by endothermy, age polyethism is reduced to only two physiologically predetermined task divisions, 0 to ,2 days and older. Endothermic heat production is the job of bees older than about two days. They are all similarly engaged in active heat production both in intensity and frequency. Their active heat production has an important reinforcement effect on passive heat production of the many ectothermic bees and of the brood. Ectothermy is most frequent in young bees (,,2 days) both outside and inside of brood nest cells. We suggest young bees visit warm brood nest cells not only to clean them but also to speed up flight muscle development for proper endothermy and foraging later in their life. Young bees inside brood nest cells mostly receive heat from the surrounding cell wall during cold stress, whereas older bees predominantly transfer heat from the thorax to the cell wall. Endothermic bees regulate brood comb temperature more accurately than local air temperature. They apply the heat as close to the brood as possible: workers heating cells from within have a higher probability of endothermy than those on the comb surface. The findings show that thermal homeostasis of honeybee colonies is achieved by a combination of active and passive processes. The differential individual endothermic and behavioral reactions sum up to an integrated action of the honeybee colony as a superorganism. © 2010 Stabentheiner et al.

Coping with the cold and fighting the heat: thermal homeostasis of a superorganism, the honeybee colony - Stabentheiner, Anton; Kovac, Helmut; Mandl, Monika; Käfer, Helmut (Journal of Comparative Physiology A: Neuroethology, Sensory, Neural, and Behavioral Physiology, 2021)
The worldwide distribution of honeybees and their fast propagation to new areas rests on their ability to keep up optimal ‘tropical conditions’ in their brood nest both in the cold and in the heat. Honeybee colonies behave like ‘superorganisms’ where individuals work together to promote reproduction of the colony. Social cooperation has developed strongly in thermal homeostasis, which guarantees a fast and constant development of the brood. We here report on the cooperation of individuals in reaction to environmental variation to achieve thermal constancy of 34–36 °C. The measurement of body temperature together with bee density and in-hive microclimate showed that behaviours for hive heating or cooling are strongly interlaced and differ in their start values. When environmental temperature changes, heat production is adjusted both by regulation of bee density due to migration activity and by the degree of endothermy. Overheating of the brood is prevented by cooling with water droplets and increased fanning, which start already at moderate temperatures where heat production and bee density are still at an increased level. This interlaced change and onset of different thermoregulatory behaviours guarantees a graded adaptation of individual behaviour to stabilise the temperature of the brood.
Keywords: Behaviour; Honeybee colony; Temperature; Thermography; Thermoregulation

DISCREPANCY BETWEEN ACUTE AND CHRONIC TOXICITY INDUCED BY IMIDACLOPRID AND ITS METABOLITES IN APIS MELLIFERA - Verine Suchail, Sé; Guez, David; Belzunces, Luc P (Environmental Toxicology and Chemistry, 2001)
Imidacloprid is a systemic nitroguanidine insecticide that belongs to the neonicotinoid family. As an agonist of the acetylcholine receptor, it attacks the insect nervous system and is extremely effective against various sucking and mining pests. Oral acute and chronic toxicity of imidacloprid and its main metabolites (5-hydroxyimidacloprid, 4,5-dihydroxyimidacloprid, desnitroimidacloprid, 6-chloronicotinic acid, olefin, and urea derivative) were investigated in Apis mellifera. Acute intoxication by imidacloprid or its metabolites resulted in the rapid appearance of neurotoxicity symptoms, such as hyperresponsiveness, hyper-activity, and trembling and led to hyporesponsiveness and hypoactivity. For acute toxicity tests, bees were treated with doses of toxic compounds ranging from 1 to 1,000 ng/bee (10-10,000 g/kg). Acute toxicity (LD50) values of imidacloprid were about 60 ng/bee (600 g/kg) at 48 h and about 40 ng/bee (400 g/kg) at 72 and 96 h. Out of the six imidacloprid metabolites tested, only two (5-hydroxyimidacloprid and olefin) exhibited a toxicity close to that of imidacloprid. Olefin LD50 values were lower than those of imidacloprid. The 5-hydroxyimidacloprid showed a lower toxicity than imidacloprid with a LD50 four to six times higher than that of imidacloprid. Urea also appeared as a compound of nonnegligible toxicity by eliciting close to 40% mortality at 1,000 ng/bee (10,000 g/kg). However, no significant toxicity was observed with 4,5-dihydroxyimidacloprid, 6-chloronicotinic acid, and desnitroimidacloprid in the range of doses tested. To test chronic toxicity, worker bees were fed sucrose solutions containing 0.1, 1, and 10 g/L of imidacloprid and its metabolites for 10 d. Fifty percent mortality was reached at approximately 8 d. Hence, considering that sucrose syrup was consumed at the mean rate of 12 l/d and per bee, after an 8-d period the cumulated doses were approximately 0.01, 0.

Neonicotinoid pesticides and nutritional stress synergistically reduce survival in honey bees - Tosi, Simone; Nieh, James C.; Sgolastra, Fabio; Cabbri, Riccardo; Medrzycki, Piotr (Proceedings of the Royal Society B: Biological Sciences, 2017)
The honey bee is a major pollinator whose health is of global concern. Declines in bee health are related to multiple factors, including resource quality and pesticide contamination. Intensive agricultural areas with crop monocultures potentially reduce the quality and quantity of available nutrients and expose bee foragers to pesticides. However, there is, to date, no evidence for synergistic effects between pesticides and nutritional stress in animals. The neonicotinoids clothianidin (CLO) and thiamethoxam (TMX) are common systemic pesticides that are used worldwide and found in nectar and pollen. We therefore tested if nutritional stress (limited access to nectar and access to nectar with low-sugar concentrations) and sublethal, field-realistic acute exposures to two neonicotinoids (CLO and TMX at 1/5 and 1/25 of LD50) could alter bee survival, food consumption and haemolymph sugar levels. Bee survival was synergistically reduced by the combination of poor nutrition and pesticide exposure (-50%). Nutritional and pesticide stressors reduced also food consumption (-48%) and haemolymph levels of glucose (-60%) and trehalose (-27%). Our results provide the first demonstration that field-realistic nutritional stress and pesticide exposure can synergistically interact and cause significant harm to animal survival. These findings have implications for current pesticide risk assessment and pollinator protection.
Keywords: Bee health; Carbohydrates; Clothianidin; Food consumption; Haemolymph; Thiamethoxam

In vivo distribution and metabolisation of 14C-imidacloprid in different compartments of Apis mellifera L - Suchail, Séverine; De Sousa, Georges; Rahmani, Roger; Belzunces, Luc P. (Pest Management Science, 2004)
In vivo distribution of the neonicotinoid insecticide, imidacloprid, was followed during 72 h in six biological compartments of Apis mellifera L: head, thorax, abdomen, haemolymph, midgut and rectum. Honeybees were treated orally with 100 μg of 14C-imidacloprid per kg of bee, a dose close to the median lethal dose. Elimination half-life of total radioactivity in honeybee was 25 h. Haemolymph was the compartment with the lowest and rectum that with the highest level of total radioactivity during the whole study, with a maximum 24 h after treatment. Elimination half-life of imidacloprid in whole honeybee was 5 h. Imidacloprid was readily distributed and metabolised only by Phase I enzymes into five metabolites: 4/5-hydroxy-imidacloprid, 4,5-dihydroxy- imidacloprid, 6-chloronicotinic acid, and olefin and urea derivatives. The guanidine derivative was not detected. The urea derivative and 6-chloronicotinic acid were the main metabolites and appeared particularly in midgut and rectum. The olefin derivative and 4/5-hydroxy-imidacloprid preferentially occurred in head, thorax and abdomen, which are nicotinic acetylcholine receptor-rich tissues. Moreover, they presented a peak value around 4 h after imidacloprid ingestion. These results explain the prolongation of imidacloprid action in bees, and particularly the differences between rapid intoxication symptoms and late mortality. © 2004 Society of Chemical Industry.
Keywords: Apis mellifera; Compartment; Honeybee; Imidacloprid; Metabolisation; Metabolite

Acute exposure to a sublethal dose of imidacloprid and coumaphos enhances olfactory learning and memory in the honeybee Apis mellifera - Williamson, Sally M.; Baker, Daniel D.; Wright, Geraldine A. (Invertebrate Neuroscience, 2013)
The decline of honeybees and other pollinating insects is a current cause for concern. A major factor implicated in their decline is exposure to agricultural chemicals, in particular the neonicotinoid insecticides such as imidacloprid. Honeybees are also subjected to additional chemical exposure when beekeepers treat hives with acaricides to combat the mite Varroa destructor. Here, we assess the effects of acute sublethal doses of the neonicotinoid imidacloprid, and the organophosphate acaricide coumaphos, on honey bee learning and memory. Imidacloprid had little effect on performance in a six-trial olfactory conditioning assay, while coumaphos caused a modest impairment. We report a surprising lack of additive adverse effects when both compounds were administered simultaneously, which instead produced a modest improvement in learning and memory. © 2012 The Author(s).
Keywords: Apis mellifera; Coumaphos; Imidacloprid; Olfactory learning; Pesticide

Imidacloprid impairs memory and brain metabolism in the honeybee (Apis mellifera L.) - Decourtye, Axel; Armengaud, Catherine; Renou, Michel; Devillers, James; Cluzeau, Sophie; Gauthier, Monique; Pham-Delègue, Minh Hà (Pesticide Biochemistry and Physiology, 2004)
Imidacloprid is a chloronicotinyl insecticide which interacts with insect nicotinic acetylcholine receptors. Thirty minutes after oral treatment of honeybees with imidacloprid, the olfactory learning performances in a proboscis extension reflex (PER) procedure were impaired. In parallel, an increase of the cytochrome oxidase labelling was found into the calyces of the mushroom bodies. Imidacloprid administered 15min or 1h after a one-trial conditioning of PER impaired the medium-term olfactory memory. By contrast, the short-term (30s or 3min conditioning-treatment time interval) and long-term (24h conditioning-treatment time interval) memories were unaffected. The impairment of medium-term olfactory memory by imidacloprid is discussed in the context of neural circuits suspected to mediate memory formation in the honeybee brain. © 2003 Elsevier Inc. All rights reserved.
Keywords: Cytochrome oxidase; Honeybee; Imidacloprid; Memory phases; Olfactory learning; Proboscis extension reflex

Effects of sublethal doses of imidacloprid on young adult honeybee behaviour - Goñalons, Carolina Mengoni; Farina, Walter Marcelo (PLoS ONE, 2015)
Imidacloprid (IMI), a neonicotinoid used for its high selective toxicity to insects, is one of the most commonly used pesticides. However, its effect on beneficial insects such as the honeybee Apis mellifera L is still controversial. As young adult workers perform in-hive duties that are crucial for colony maintenance and survival, we aimed to assess the effect of sublethal IMI doses on honeybee behaviour during this period. Also, because this insecticide acts as a cholinergic-nicotinic agonist and these pathways take part in insect learning and memory processes; we used IMI to assess their role and the changes they suffer along early adulthood.We focused on appetitive behaviours based on the proboscis extension response. Laboratory reared adults of 2 to 10 days of age were exposed to sublethal IMI doses (0.25 or 0.50ng) administered orally or topically prior to behavioural assessment. Modification of gustatory responsiveness and impairment of learning and memory were found as a result of IMI exposure. These outcomes differed depending on age of evaluation, type of exposure and IMI dose, being the youngest bees more sensitive and the highest oral dose more toxic. Altogether, these results imply that IMI administered at levels found in agroecosystems can reduce sensitivity to reward and impair associative learning in young honeybees. Therefore, once a nectar inflow with IMI traces is distributed within the hive, it could impair in-door duties with negative consequences on colony performance.

A common neonicotinoid pesticide, thiamethoxam, alters honey bee activity, motor functions, and movement to light - Tosi, S.; Nieh, J. C. (Scientific Reports, 2017)
Honey bees provide key ecosystem services. To pollinate and to sustain the colony, workers must walk, climb, and use phototaxis as they move inside and outside the nest. Phototaxis, orientation to light, is linked to sucrose responsiveness and the transition of work from inside to outside the nest, and is also a key component of division of labour. However, the sublethal effects of pesticides on locomotion and movement to light are relatively poorly understood. Thiamethoxam (TMX) is a common neonicotinoid pesticide that bees can consume in nectar and pollen. We used a vertical arena illuminated from the top to test the effects of acute and chronic sublethal exposures to TMX. Acute consumption (1.34 ng/bee) impaired locomotion, caused hyperactivity (velocity: +109%; time moving: +44%) shortly after exposure (30 min), and impaired motor functions (falls: +83%; time top: -43%; time bottom: +93%; abnormal behaviours: +138%; inability to ascend: +280%) over a longer period (60 min). A 2-day chronic exposure (field-relevant daily intakes of 1.42-3.48 ng/bee/day) impaired bee ability to ascend. TMX increased movement to light after acute and chronic exposure. Thus, TMX could reduce colony health by harming worker locomotion and, potentially, alter division of labour if bees move outside or remain outdoors.

Nicotinic acetylcholine receptor modulator insecticides act on diverse receptor subtypes with distinct subunit compositions - Lu, Wanjun; Liu, Zhihan; Fan, Xinyu; Zhang, Xinzhong; Qiao, Xiaomu; Huang, Jia (PLoS Genetics, 2022)
Insect nicotinic acetylcholine receptors (nAChRs) are pentameric ligand-gated ion channels mainly expressed in the central nervous system of insects. They are the directed targets of many insecticides, including neonicotinoids, which are the most widely used insecticides in the world. However, the development of resistance in pests and the negative impacts on bee pollinators affect the application of insecticides and have created a demand for alternatives. Thus, it is very important to understand the mode of action of these insecticides, which is not fully understood at the molecular level. In this study, we systematically examined the susceptibility of ten Drosophila melanogaster nAChR subunit mutants to eleven insecticides acting on nAChRs. Our results showed that there are several subtypes of nAChRs with distinct subunit compositions that are responsible for the toxicity of different insecticides. At least three of them are the major molecular targets of seven structurally similar neonicotinoids in vivo. Moreover, spinosyns may act exclusively on the α6 homomeric pentamers but not any other nAChRs. Behavioral assays using thermogenetic tools further confirmed the bioassay results and supported the idea that receptor activation rather than inhibition leads to the insecticidal effects of neonicotinoids. The present findings reveal native nAChR subunit interactions with various insecticides and have important implications for the management of resistance and the development of novel insecticides targeting these important ion channels.

The condition of the bee colony (Apis mellifera) after exposure to pesticide and their mixtures - Murawska, Agnieszka; Migdał, Paweł; Latarowski, Krzysztof; Berbeć, Ewelina; Zarębski, Karol (Apidologie, 2025)
In the natural environment, bees are often exposed to low concentrations of pesticide mixtures while foraging. These substances can be carried back to the hive, threatening the health and life of the entire colony. For seven consecutive days, honey bee workers were fed daily with 0.5 L of sugar syrup containing a commercial formulation of acetamiprid, glyphosate, and tebuconazole, administered either individually or in two- or three-component mixtures The feed was both actively consumed by the bee colonies and stored in the combs. As a result, their exposure to the pesticides was chronic and lasted until the stored feed was fully consumed before the onset of winter. Pesticide concentrations in the syrup reflected environmental residue levels: 250 ppb for acetamiprid, 7200 ppb for glyphosate, and 147 ppb for tebuconazole. The study aims to assess the impact of these pesticides on colony health, focusing on colony size, brood, and food reserves. No statistically significant differences were found between the groups. Despite the results showing no negative effects of acetamiprid, glyphosate, and tebuconazole on the parameters studied, pesticides still pose a major risk to bees, which may contribute to a decline in their population and consequently in environmental biodiversity. Future research should focus on using acetamiprid, glyphosate, and tebuconazole, but in combination with other commonly used pesticides. The potential risks of unresearched mixtures should be investigated.
Keywords: Bee colony; Exposure; Honey bee; Pesticide mixture; Plant protection products

Behavioral responses of honey bees (Apis mellifera) to natural and synthetic xenobiotics in food - Liao, Ling Hsiu; Wu, Wen Yen; Berenbaum, May R. (Scientific Reports, 2017)
While the natural foods of the western honey bee (Apis mellifera) contain diverse phytochemicals, in contemporary agroecosystems honey bees also encounter pesticides as floral tissue contaminants. Whereas some ubiquitous phytochemicals in bee foods up-regulate detoxification and immunity genes, thereby benefiting nestmates, many agrochemical pesticides adversely affect bee health even at sublethal levels. How honey bees assess xenobiotic risk to nestmates as they forage is poorly understood. Accordingly, we tested nine phytochemicals ubiquitous in nectar, pollen, or propolis, as well as five synthetic xenobiotics that frequently contaminate hives-two herbicides (atrazine and glyphosate) and three fungicides (boscalid, chlorothalonil, and prochloraz). In semi-field free-flight experiments, bees were offered a choice between paired sugar water feeders amended with either a xenobiotic or solvent only (control). Among the phytochemicals, foragers consistently preferred quercetin at all five concentrations tested, as evidenced by both visitation frequency and consumption rates. This preference may reflect the long evolutionary association between honey bees and floral tissues. Of pesticides eliciting a response, bees displayed a preference at specific concentrations for glyphosate and chlorothalonil. This paradoxical preference may account for the frequency with which these pesticides occur as hive contaminants and suggests that they present a greater risk factor for honey bee health than previously suspected.

Pesticides and pollinator brain: How do neonicotinoids affect the central nervous system of bees? - Paoli, Marco; Giurfa, Martin (European Journal of Neuroscience, 2024)
Neonicotinoids represent over a quarter of the global pesticide market. Research on their environmental impact has revealed their adverse effect on the cognitive functions of pollinators, in particular of bees. Cognitive impairments, mostly revealed by behavioural studies, are the phenotypic expression of an alteration in the underlying neural circuits, a matter deserving greater attention. Here, we reviewed studies on the impact of field-relevant doses of neonicotinoids on the neurophysiology and neurodevelopment of bees. In particular, we focus on their olfactory system as much knowledge has been gained on the different brain areas that participate in odour processing. Recent studies have revealed the detrimental effects of neonicotinoids at multiple levels of the olfactory system, including modulation of odorant-induced activity in olfactory sensory neurons, diminished neural responses in the antennal lobe (the first olfactory processing centre) and abnormal development of the neural connectivity within the mushroom bodies (central neuropils involved in multisensory integration, learning and memory storage, among others). Given the importance of olfactory perception for multiple aspects of bee biology, the reported disruption of the olfactory circuit, which can occur even upon exposure to sublethal doses of neonicotinoids, has severe consequences at both individual and colony levels. Moreover, the effects reported for a multimodal structure such as the mushroom bodies indicate that neonicotinoids' impact translates to other sensory domains. Assessing the impact of field-relevant doses of pesticides on bee neurophysiology is crucial for understanding how neonicotinoids influence their behaviour in ecological contexts and for defining effective and sustainable agricultural practices.
Keywords: brain; central nervous system; honey bees; neonicotinoids; pesticides; pollinators

Chronic exposure to insecticides impairs honeybee optomotor behaviour - Parkinson, Rachel H.; Fecher, Caroline; Gray, John R. (Frontiers in Insect Science, 2022)
Honeybees use wide-field visual motion information to calculate the distance they have flown from the hive, and this information is communicated to conspecifics during the waggle dance. Seed treatment insecticides, including neonicotinoids and novel insecticides like sulfoxaflor, display detrimental effects on wild and managed bees, even when present at sublethal quantities. These effects include deficits in flight navigation and homing ability, and decreased survival of exposed worker bees. Neonicotinoid insecticides disrupt visual motion detection in the locust, resulting in impaired escape behaviors, but it had not previously been shown whether seed treatment insecticides disrupt wide-field motion detection in the honeybee. Here, we show that sublethal exposure to two commonly used insecticides, imidacloprid (a neonicotinoid) and sulfoxaflor, results in impaired optomotor behavior in the honeybee. This behavioral effect correlates with altered stress and detoxification gene expression in the brain. Exposure to sulfoxaflor led to sparse increases in neuronal apoptosis, localized primarily in the optic lobes, however there was no effect of imidacloprid. We propose that exposure to cholinergic insecticides disrupts the honeybee’s ability to accurately encode wide-field visual motion, resulting in impaired optomotor behaviors. These findings provide a novel explanation for previously described effects of neonicotinoid insecticides on navigation and link these effects to sulfoxaflor for which there is a gap in scientific knowledge.
Keywords: honeybee; imidacloprid; optomotor behavior; sulfoxaflor; visually guided behavior

Lethal and sublethal effects of thiamethoxam, a neonicotinoid molecule, on colony performance of A. mellifera - Negi, Budhi Ram; Harish, &; Sharma, Kumar; Thakur, Meena; Prashad, Hema
Among insect pollinators, honey bees, Apis mellifera (Hymenoptera: Apidae), are universally acknowledged, most important managed pollinators that also provide honey production. In recent years, neonicotinoids are widely used against a broad spectrum sucking pests. However, they also pose a major threat to the beekeeping industry. The present study aimed to quantify the impact of thiamethoxam, a second-generation, broad-spectrum neonicotinoid on foraging behavior, colony performance, and survival of Apis mellifera L. in mustard crop under semi-field (cage) and field conditions. Under semi-field conditions, the foraging activity of A. mellifera on mustard bloom reduced significantly on the 2nd day after spray of thiamethoxam as compared to pre-count and control. Significant decrease in brood area (7th to 21st day), nectar stores (7th to 28th day), and pollen stores (7th to 21st day) were also recorded after the spray. The bee mortality under semi-field conditions was significantly higher on the 1st and 2nd day after spray in comparison to control. Under field conditions, average bee activity remained statistically low up to the 12th day after spray on mustard bloom in comparison to pre-count and control. The effect of thiamethoxam under field conditions was less pronounced for bee mortality and colony parameters. Based on LD 50 , thiamethoxam was proved toxic to adults and larvae of A. mellifera.
Keywords: Apis mellifera; Bee activity; Mortality; Neonicotinoids; Pesticide toxicity; Pollinators

Sublethal effects of imidacloprid-contaminated honey stores on colony performance, queens, and worker activities in fall and early winter colonies - Carroll, Mark J.; Brown, Nicholas J.; Reitz, Dylan (PLoS ONE, 2024)
Neonicotinoid-contaminated sugar stores can have both near term and long term effects on honey bees due to their persistence in honey stores. Effects of imidacloprid food stores contaminants were examined in subtropical colonies that experience reduced brood rearing and foraging during overwintering. Colonies were given treatment sugar syrup containing 0 ppb (control), 20 ppb (field relevant), or 100 ppb (above field relevant) imidacloprid over six weeks to simulate contaminated fall nectar. Colonies were evaluated immediately (post-treatment) and 10 weeks (mid-winter) after treatment to compare proximal and latent effects. Post-treatment 0 ppb and 20 ppb colonies had more workers than 100 ppb colonies while 0 ppb colonies more brood than 20 ppb or 100 ppb colonies. Mid-winter 0 ppb and 20 ppb colonies had more workers than 100 ppb colonies and 0 ppb colonies more brood than 100 ppb colonies. Colonies experienced seasonal declines in stored pollen but no treatment effects. Lower 100 ppb colony performance was associated with reduced effort rather than lifespan. RFID (Radio Frequency Identification) tracking revealed that workers had similar adult lifespans across treatments; however, 100 ppb workers engaged in activities outside the colony for less time than 0 ppb workers. Imidacloprid exposure affected queen but not worker nutritional physiology. Nurses retained well-developed hypopharyngeal glands (as indicated by head protein) across treatments. Mid-winter queens from 0 ppb colonies had marginally higher ovary protein than queens from 100 ppb colonies and more ovary lipids than queens from 20 ppb colonies. However, queen nutrient stores in non-reproductive tissues (fat bodies) did not differ across treatments. Queens from different treatments were attended by comparable numbers of retinue workers and had similar gland contents of four QMP (Queen Mandibular Pheromone) components essential to queen care. High levels of imidacloprid in sugar stores can negatively affect colony performance months after initial storage.

Effect of repeated intakes of a neonicotinoid insecticide on the foraging behaviours of Apis mellifera in field trials - Girolami, Vincenzo; Toffolo, Edoardo Petrucco; Mazzon, Luca; Zampieri, Francesca; Lentola, Andrea; Giorio, Chiara; Tapparo, Andrea (Environmental Science and Pollution Research, 2023)
Evaluating the effects of neonicotinoids on forager bees in conditions as near as possible to those in nature presents a considerable challenge. Tackling this challenge is, however, necessary to establish their negative side effects on these pollinators. For instance, it is still under debate the mechanism by which bees seem to recognize low-level contaminations of neonicotinoid insecticides in nectar and pollen of the flowers they visit and limit collection to protect themselves and their hive from a possible intoxication. In this study, we propose an experimental system that involves the use of foragers in free flight foraging repeatedly on artificial feeders containing a sucrose solution contaminated with clothianidin, as well as foragers feeding at adjacent control feeders, allowing us to observe changes in their foraging activity. The progressive disappearance of foragers from the contaminated feeders became increasingly clear and rapid with the increase in clothianidin concentration. The lowest concentration at which we observed an effect was around 10 µg/L, which corresponds to the maximum residual concentration (10 ng/g) observed in pollen and nectar of flowers close to open fields sown with seeds coated with insecticides. At the highest concentrations tested (80 µg/L), there was an almost total abandonment of the feeders. The estimated quantity of contaminated sucrose solution collected by foragers showed an almost linear relationship inversely proportional to clothianidin concentration, whilst the estimated quantity of insecticide collected by a forager increased and then stabilised at the highest concentrations tested of 40 and 80 µg/L. Irregular mortality was not observed in front of the hives, furthermore, foragers did not show evident memory of the position of the treated units in the trials on the 2 consecutive days. The decrease in foraging activity in the presence of a few µg/L of insecticide in the sucrose solution appears to limit the introduction of elevated amounts of toxic substances into the hives, which would have serious consequences for the young bees and the brood. At the same time, in the absence of an alternative energy source, even reduced feeding of the hive can compromise colony health.
Keywords: Clothianidin toxicity; Foraging activity; Honeybee behaviour; Sub-lethal doses

Current Insights into Sublethal Effects of Pesticides on Insects - Bartling, Merle Theresa; Brandt, Annely; Hollert, Henner; Vilcinskas, Andreas (International Journal of Molecular Sciences, 2024)
The effect of pesticides on insects is often discussed in terms of acute and chronic toxicity, but an important and often overlooked aspect is the impact of sublethal doses on insect physiology and behavior. Pesticides can influence various physiological parameters of insects, including the innate immune system, development, and reproduction, through a combination of direct effects on specific exposed tissues and the modification of behaviors that contribute to health and reproductive success. Such behaviors include mobility, feeding, oviposition, navigation, and the ability to detect pheromones. Pesticides also have a profound effect on insect learning and memory. The precise effects depend on many different factors, including the insect species, age, sex, caste, physiological condition, as well as the type and concentration of the active ingredients and the exposure route. More studies are needed to assess the effects of different active ingredients (and combinations thereof) on a wider range of species to understand how sublethal doses of pesticides can contribute to insect decline. This review reflects our current knowledge about sublethal effects of pesticides on insects and advancements in the development of innovative methods to detect them.
Keywords: beneficial arthropods; insecticides; pest insects; pesticides; sublethal doses; toxicology

Memory formation following appetitive conditioning is variably dependent on retinoid signaling - Wong, Raymond K.; Spencer, Gaynor E. (Neurobiology of Learning and Memory, 2025)
Retinoic acid (RA), the metabolite of Vitamin A, plays an important role in central nervous system development and regeneration, as well as learning and memory in vertebrates. We have previously shown that RA signaling is also important for consolidation of long-term memory (LTM) in the invertebrate mollusc, Lymnaea stagnalis, following operant conditioning of the aerial respiratory behaviour. Here, we examine whether retinoids also play a role in classical reward conditioning in this mollusc. A single-trial appetitive conditioning paradigm was used, with amyl acetate as the conditioned stimulus (CS) and sucrose as the unconditioned stimulus (US). This produced an acquired conditioned response whereby the animal exhibited a feeding response to amyl acetate. A single-pairing of CS with US produced long-term memory at both 1d and 6d after training. Pharmacological treatments that disrupt RA signaling did not block the formation of long term memory when a 6-day food deprivation period was implemented before training. However, two different paradigms induced susceptibility of the conditioned response (memory) to retinoid signaling inhibitors. The first paradigm change involved using a shorter, 3-day food deprivation period in order to reduce motivational drive to feed, whereas the second paradigm manipulation reduced the strength of the unconditioned stimulus (sucrose). These findings suggest different susceptibility of memories to retinoid inhibition, depending on shifts in both external parameters of the experiment, as well as internal motivational states of the animal.
Keywords: Classical conditioning; Feeding behavior; Lymnaea stagnalis; Mollusc; Motivational state; Retinoic acid

Antennal movements can be used as behavioral readout of odor valence in honey bees - Gascue, Federico; Marachlian, Emiliano; Azcueta, Milagros; Locatelli, Fernando F.; Klappenbach, Martín (IBRO Neuroscience Reports, 2022)
The fact that honey bees have a relatively simple nervous system that allows complex behaviors has made them an outstanding model for studying neurobiological processes. Studies on learning and memory routinely use appetitive and aversive learning paradigms that involve recording of the proboscis or the sting extension. However, these protocols are based on all-or-none responses, which has the disadvantage of occluding intermediate and more elaborated behaviors. Nowadays, the great advances in tracking software and data analysis, combined with affordable video recording systems, have made it possible to extract very detailed information about animal behavior. Here we describe antennal movements that are elicited by odor that have no, positive or negative valence. We show that animals orient their antennae towards the source of the odor when it is positive, and orient them in the opposite direction when the odor is negative. Moreover, we found that this behavior was modified between animals that had been trained based on protocols of different strength. Since this procedure allows a more accurate description of the behavioral outcome using a relatively small number of animals, it represents a great tool for studying different cognitive processes and olfactory perception.

No evidence for neonicotinoid preferences in the bumblebee Bombus impatiens - Muth, Felicity; Gaxiola, Rebekah L.; Leonard, Anne S. (Royal Society Open Science, 2020)
Neonicotinoid pesticides can have a multitude of negative sublethal effects on bees. Understanding their impact on wild populations requires accurately estimating the dosages bees encounter under natural conditions. This is complicated by the possibility that bees might influence their own exposure: two recent studies found that bumblebees (Bombus terrestris) preferentially consumed neonicotinoid-contaminated nectar, even though these chemicals are thought to be tasteless and odourless. Here, we used Bombus impatiens to explore two elements of these reported preferences, with the aim of understanding their ecological implication and underlying mechanism. First, we asked whether preferences persisted across a range of realistic nectar sugar concentrations, when measured at a series of time points up until 24 h. Second, we tested whether bees’ neonicotinoid preferences were driven by an ability to associate their post-ingestive consequences with floral stimuli such as colour, location or scent. We found no evidence that foragers preferred to consume neonicotinoid-containing solutions, despite finding effects on feeding motivation and locomotor activity in line with previous work. Bees also did not preferentially visit floral stimuli previously paired with a neonicotinoid-containing solution. These results highlight the need for further research into the mechanisms underlying bees’ responses to these pesticides, critical for determining how neonicotinoid-driven foraging preferences might operate in the real world for different bee species.
Keywords: Activity; Bee; Behaviour; Imidacloprid; Learning; Locomotor

A phototaxis assay to measure sublethal effects of pesticides on bees - Sancho, Gonzalo; Albacete, Sergio; Azpiazu, Celeste; Sgolastra, Fabio; Rodrigo, Anselm; Bosch, Jordi (Scientific Reports, 2025)
In agricultural areas, bees are pervasively exposed to pesticides at sublethal concentrations. Methods to establish whether these concentrations may cause negative effects are needed to assess the potential hazards of field-realistic levels of exposure. Bee risk assessment relies on a single species, the highly social Apis mellifera and, due to fundamental life history differences, available sublethal tests cannot be applied to solitary bees. We provide a simple phototaxis assay to detect sublethal pesticide effects on bees. The assay is highly effective (86–97% response) and provides an unambiguous binary outcome (bees either walk straight to the light source or walk erratically across the arena). We validate the assay by conducting two experiments. First, we build dose–response curves and estimate ED50 and BMD values of an insecticide (acetamiprid) on Osmia bicornis and Osmia tricornis. Second, we assess the effects of sublethal insecticide-fungicide mixtures (acetamiprid-tebuconazole) on Osmia cornuta and A. mellifera. These experiments show that our assay can detect effects of field-realistic levels of acetamiprid exposure as low as 1–30 ng/bee. The phototaxis assay can be used to obtain relevant ecotoxicological endpoints at low sublethal concentrations in both solitary and honey bees, thus contributing to fill an important gap in bee risk assessment.
Keywords: Bee ecotoxicology; Benchmark dose (BMD); Median effective dose (ED50); Phototactic response; Sublethal exposure; Sublethal toxicity ratio

Exposure to Magnetic Fields Changes the Behavioral Pattern in Honeybees (Apis mellifera L.) under Laboratory Conditions - Migdał, Paweł; Berbeć, Ewelina; Bieńkowski, Paweł; Plotnik, Mateusz; Murawska, Agnieszka; Latarowski, Krzysztof (Animals, 2022)
Earth’s magnetic field (MF) plays an important role for many species, including the honeybee, in navigation. Nowadays, much larger alternating fields are emitted by miscellaneous electric infrastructure components, such as transformers and power lines, and the environment is therefore polluted by an anthropogenic electromagnetic field, though little is known regarding its impact on living organisms. The behavior of animals is the first and easiest way to establish the impact of stress. It shows if the animal can detect the exposure and react to it. To investigate this, one-day-old bees were exposed to a 50 Hz magnetic field of induction at 1 mT and 1.7 mT for 10 min, 1 h, and 3 h under laboratory conditions. All groups exposed to the magnetic field showed differences in behavioral patterns. What is more, they presented a behavior absent in the control: loss of balance. There were differences, both in the ratio of behaviors and in the number of bouts—exposed bees more often changed behavior. Occurrence of differences is an indication of the reaction of the honeybee organism to the magnetic field. Loss of balance is a disturbing symptom, and behavior changes indicate a disturbance of the honeybee by the electromagnetic field.
Keywords: behavior; electromagnetic field; honeybee; insect; invertebrates; magnetic field; social insects

Antenna movements as a function of odorants’ biological value in honeybees (Apis mellifera L.) - Cholé, Hanna; Merlin, Alice; Henderson, Nicholas; Paupy, Estelle; Mahé, Prisca; Arnold, Gérard; Sandoz, Jean Christophe (Scientific Reports, 2022)
In honeybees, the antennae are highly mobile sensory organs that express scanning movements in various behavioral contexts and toward many stimuli, especially odorants. The rules underlying these movements are still unclear. Using a motion-capture system, we analyzed bees’ antennal responses to a panel of pheromonal and other biologically relevant odorants. We observed clear differences in bees’ antennal responses, with opposite movements to stimuli related to opposite contexts: slow backward movements were expressed in response to alarm pheromones, while fast forward movements were elicited by food related cues as well as brood and queen related pheromones. These responses are reproducible, as a similar pattern of odor-specific responses was observed in bees from different colonies, on different years. We then tested whether odorants’ attractiveness for bees, measured using an original olfactory orientation setup, may predict antenna movements. This simple measure of odorants’ valence did however not correlate with either antennal position or velocity measures, showing that more complex rules than simple hedonics underlie bees’ antennal responses to odorants. Lastly, we show that newly-emerged bees express only limited antennal responses compared to older bees, suggesting that a significant part of the observed responses are acquired during bees’ behavioral development.

Behavioral impairments in Africanized Apis mellifera exposed to lethal and sublethal doses of acetamiprid, fipronil, and thiamethoxam - Barroso, Geovanny; Pereira, A. M.; Bueno, Odair Correa; Nocelli, Roberta Cornélio Ferreira; Malaspina, Osmar (Ecotoxicology, 2025)
The honeybee (Apis mellifera Linnaeus (Hymenoptera: Apidae)) is a crucial contributor to the maintenance of biodiversity, ecosystem function, and food security. The widespread use of pesticides, particularly neurotoxic insecticides such as acetamiprid, fipronil, and thiamethoxam, is potentially harmful to honey bees. In this study, we aimed to determine the mean lethal dose (LD50) and time-to-effect of the lethal dose of these three insecticides to assess their acute toxicity to honey bees. Furthermore, we assessed the effects of lethal and sublethal doses on two key behavioral parameters: proboscis extension reflex (PER) and locomotor activity. Briefly, bees were exposed to lethal and different sublethal doses of insecticides and their responses were evaluated at various time intervals. Acetamiprid temporarily affected honeybee foraging capacity and mobility, with signs of recovery observed after 24 h. Fipronil exhibited delayed toxicity, whereas thiamethoxam immediately affected the PER response. Overall, our study suggested acetamiprid as the safest option among the tested insecticides, considering its acute topical toxicity. Future studies should investigate the potential long-term effects of other factors on honeybee behavior.
Keywords: Honeybee; Locomotor activity; Neonicotinoids; Neurotoxicity; Phenylpyrazole; Risk assessment

Effects of coumaphos on locomotor activities of different honeybee (Apis mellifera L.) subspecies and ecotypes - Arslan, Okan Can; Erdem, Babür; Somel, Mehmet; Giray, Tugrul; Kence, Meral (Apidologie, 2023)
The effects of acute sublethal doses of coumaphos, an acaricide used against Varroa destructor infestation in beekeeping, on the locomotor activities of four native honeybee subspecies of Türkiye including two ecotypes (Carniolan honeybee -A. m. carnica, Syrian honeybee -A. m. syriaca, Caucasian honeybee- A. m. caucasica, and Muğla and Yığılca ecotypes of Anatolian honeybee A. m. anatoliaca) were investigated using an individual locomotor activity monitoring system. Analysis of locomotor activity data in the first 12-h, last 12-h, and 24-h time periods showed that bees from caucasica and carnica subspecies were not affected by coumaphos at all three acute doses (1, 2, and 5 μg coumaphos in 10 μl sucrose syrup for each bee). In contrast, bees from A. m. syriaca subspecies showed significantly elevated locomotor activity levels at 2 and 5 μg coumaphos doses within the first 12 h. Bees from both Muğla and Yığılca ecotypes of anatoliaca subspecies also showed elevated locomotor activity levels at 5 μg coumaphos dose but the magnitude of increase was lower in these ecotypes compared to that seen in syriaca subspecies in the first 12-h period. In general, increasing doses of coumaphos resulted in increased locomotor activity (locomotor activity), with differences in sensitivity across honeybee populations. Possible mechanisms underlying this variance and suggestions for further studies are discussed.
Keywords: Acaricides; Acetylcholinesterase (AChE); Coumaphos; Honey bee (Apis mellifera); Learning; Varroa destructor

Exposure of the stingless bee Melipona scutellaris to imidacloprid, pyraclostrobin, and glyphosate, alone and in combination, impair its walking activity and fat body morphology and physiology - Farder-Gomes, Cliver Fernandes; de Oliveira, Marco Antônio; Malaspina, Osmar; Nocelli, Roberta Ferreira Cornélio (Environmental Pollution, 2024)
The stingless bee Melipona scutellaris performs buzz pollination, effectively pollinating several wild plants and crops with economic relevance. However, most research has focused on honeybees, leaving a significant gap in studies concerning native species, particularly regarding the impacts of pesticide combinations on these pollinators. Thus, this study aimed to evaluate the sublethal effects of imidacloprid (IMD), pyraclostrobin (PYR), and glyphosate (GLY) on the behavior and fat body cell morphology and physiology of M. scutellaris. Foragers were orally exposed to the different pesticides alone and in combination for 48 h. Bees fed with contaminated solution walked less, moved slower, presented morphological changes in the fat body, including vacuolization, altered cell shape and nuclei morphology, and exhibited a higher count of altered oenocytes and trophocytes. In all exposed groups, alone and in combination, the number of cells expressing caspase-3 increased, but the TLR4 number of cells expressing decreased compared to the control groups. The intensity of HSP70 immunolabeling increased compared to the control groups. However, the intensity of the immunolabeling of HSP90 decreased in the IMD, GLY, and I + G (IMD + GLY) groups but increased in I + P-exposed bees (IMD + PYR). Alternatively, exposure to PYR and P + G (PYR + GLY) did not affect the immunolabeling intensity. Our findings demonstrate the hazardous effects and environmental consequences of isolated and combined pesticides on a vital neotropical pollinator. Understanding how pesticides impact the fat body can provide crucial insights into the overall health and survival of native bee populations, which can help develop more environmentally friendly approaches to agricultural practices.
Keywords: Cell death; Immune defense; Pollination; Sublethal effects; Toxicology

Neural effects of insecticides in the honey bee - Belzunces, Luc P.; Tchamitchian, Sylvie; Brunet, Jean Luc (Apidologie, 2012)
During their foraging activity, honey bees are often exposed to direct and residual contacts with pesticides, especially insecticides, all substances specifically designed to kill, repel, attract or perturb the vital functions of insects. Insecticides may elicit lethal and sublethal effects of different natures that may affect various biological systems of the honey bee. The first step in the induction of toxicity by a chemical is the interaction between the toxic compound and its molecular target. The action on the molecular target can lead to the induction of observable or non-visible effects. The toxic substance may impair important processes involved in cognitive functions, behaviour or integrity of physiological functions. This review is focused on the neural effects of insecticides that have repercussions on (a) cognitive functions, including learning and memory, habituation, olfaction and gustation, navigation and orientation; (b) behaviour, including foraging and (c) physiological functions, including thermoregulation and muscle activity. © INRA, DIB and Springer-Verlag, France, 2012.
Keywords: Behavior; Insecticides; Mode of action; Molecular targets; Neural effects

Exposure to neonicotinoids influences the motor function of adult worker honeybees - Williamson, Sally M.; Willis, Sarah J.; Wright, Geraldine A. (Ecotoxicology, 2014)
Systemic pesticides such as neonicotinoids are commonly used on flowering crops visited by pollinators, and their use has been implicated in the decline of insect pollinator populations in Europe and North America. Several studies show that neonicotinoids affect navigation and learning in bees but few studies have examined whether these substances influence their basic motor function. Here, we investigated how prolonged exposure to sublethal doses of four neonicotinoid pesticides (imidacloprid, thiamethoxam, clothianidin, dinotefuran) and the plant toxin, nicotine, affect basic motor function and postural control in foraging-age worker honeybees. We used doses of 10 nM for each neonicotinoid: field-relevant doses that we determined to be sublethal and willingly consumed by bees. The neonicotinoids were placed in food solutions given to bees for 24 h. After the exposure period, bees were more likely to lose postural control during the motor function assay and fail to right themselves if exposed to imidacloprid, thiamethoxam, clothianidin. Bees exposed to thiamethoxam and nicotine also spent more time grooming. Other behaviours (walking, sitting and flying) were not significantly affected. Expression of changes in motor function after exposure to imidacloprid was dose-dependent and affected all measured behaviours. Our data illustrate that 24 h exposure to sublethal doses of neonicotinoid pesticides has a subtle influence on bee behaviour that is likely to affect normal function in a field setting.
Keywords: Apis mellifera; Honeybee; Imidacloprid; Neonicotinoid; Pesticide; Pollinator

Acute Application of Imidacloprid Alters the Sensitivity of Direction Selective Motion Detecting Neurons in an Insect Pollinator - Rigosi, Elisa; O’Carroll, David C. (Frontiers in Physiology, 2021)
Cholinergic pesticides, such as the neonicotinoid imidacloprid, are the most important insecticides used for plant protection worldwide. In recent decades, concerns have been raised about side effects on non-target insect species, including altered foraging behavior and navigation. Although pollinators rely on visual cues to forage and navigate their environment, the effects of neonicotinoids on visual processing have been largely overlooked. To test the effect of acute treatment with imidacloprid at known concentrations in the brain, we developed a modified electrophysiological setup that allows recordings of visually evoked responses while perfusing the brain in vivo. We obtained long-lasting recordings from direction selective wide-field, motion sensitive neurons of the hoverfly pollinator, Eristalis tenax. Neurons were treated with imidacloprid (3.9 μM, 0.39 μM or a sham control treatment using the solvent (dimethylsulfoxide) only. Exposure to a high, yet sub-lethal concentration of imidacloprid significantly alters their physiological response to motion stimuli. We observed a general effect of imidacloprid (3.9 μM) increasing spontaneous activity, reducing contrast sensitivity and giving weaker directional tuning to wide-field moving stimuli, with likely implications for errors in flight control, hovering and routing. Our electrophysiological approach reveals the robustness of the fly visual pathway against cholinergic perturbance (i.e., at 0.39 μM) but also potential threatening effects of cholinergic pesticides (i.e., evident at 3.9 μM) for the visual motion detecting system of an important pollinator.
Keywords: contrast sensitivity; insect vision; lobula plate tangential cells; motion detection; neonicotinoid; nicotinic acetylcholine receptors; pesticides

Is Apis mellifera more sensitive to insecticides than other insects? - Hardstone, Melissa C.; Scott, Jeffrey G. (Pest Management Science, 2010)
BACKGROUND: Honey bees (Apis mellifera L.) are among the most important pollinators in natural and agricultural settings. They commonly encounter insecticides, and the effects of insecticides on honey bees have been frequently noted. It has been suggested that honey bees may be (as a species) uniquely sensitive to insecticides, although no comparative toxicology study has been undertaken to examine this claim. An extensive literature review was conducted, using data in which adult insects were topically treated with insecticides. The goal of this review was to summarize insecticide toxicity data between A. mellifera and other insects to determine the relative sensitivity of honey bees to insecticides. RESULTS: It was found that, in general, honey bees were no more sensitive than other insect species across the 62 insecticides examined. In addition, honey bees were not more sensitive to any of the six classes of insecticides (carbamates, nicotinoids, organochlorines, organophosphates, pyrethroids and miscellaneous) examined. CONCLUSIONS: While honey bees can be sensitive to individual insecticides, they are not a highly sensitive species to insecticides overall, or even to specific classes of insecticides. However, all pesticides should be used in a way that minimizes honey bee exposure, so as to minimize possible declines in the number of bees and/or honey contamination. © 2010 Society of Chemical Industry.
Keywords: Carbamate; Comparative toxicology; Neonicotinoid; Organophosphate; Pyrethroid

Imidacloprid: Impact on Africanized Apis mellifera L. (Hymenoptera: Apidae) workers and honey contamination - Paloschi, Cristiane Lurdes; Tavares, Maria Hermínia Ferreira; Berte, Elizabeth Artus; Model, Kathleen; Rosa, Karine Medina; Conceição, Fagner Goes da; Domanski, Fernanda Raulino; de Souza Vismara, Edgar; Montanher, Paula Fernandes; Maciel, Rodrigo Mendes Antunes; Ribeiro, Leticia da Silva; Ramos Mertz, Natalia; et al. (Chemosphere, 2023)
Apis mellifera L. (Hymenoptera: Apidae) is fundamental in the production chain, ensuring food diversity through the ecosystem service of pollination. The aim of this work was to evaluate the impact of imidacloprid, orally, topically, and by contact, on A. mellifera workers and to verify the presence of this active ingredient in honey. Toxicity levels were verified by bioassays. In bioassay 1, the levels correspond to the percentages of 100, 10, 1, 0.1, and 0.01% of the recommended concentration for field application of the commercial product Nortox® (active ingredient imidacloprid), with which we obtained the mean lethal concentration (LC50) in 48 h for A. mellifera, determining the concentration ranges to be used in the subsequent bioassays. Bioassays 2 and 3 followed the guidelines of the Organization for Economic Cooperation and Development, which specify the LC50 (48 h). In bioassay 4, the LC50 (48 h) and the survival rate of bees for a period of 120 h were determined by contact with a surface contaminated with imidacloprid, and in bioassay 5, the interference of the insecticide with the flight behavior of bees was evaluated. Honey samples were collected in agroecological and conventional georeferenced apiaries and traces of the imidacloprid were detected by means of high-performance liquid chromatography (HPLC-UV) with extraction by SPE C18. Bee survival was directly affected by the concentration and exposure time, as well behavioral performance, demonstrating the residual effect of imidacloprid on A. mellifera workers. Honey samples from a conventional apiary showed detection above the maximum residue limits (MRL) allowed by the European Union (0.05 μg mL−1), but samples from other apiaries showed no traces of this insecticide. Imidacloprid affects the survival rate and behavior of Africanized A. mellifera and honey quality.
Keywords: Bee; Neonicotinoids; Selectivity; Toxicity